Age-Related RPE changes in Wildtype C57BL/6J Mice between 2 and 32 Months. - Shelton, Debresha A; Gefke, Isabelle; Summers, Vivian; Kim, Yong-Kyu; Yu, Hanyi; Getz, Yana; Ferdous, Salma; Donaldson, Kevin; Liao, Kristie; Papania, Jack T; Chrenek, Micah A; Boatright, Jeffrey H; et al. (bioRxiv, 2024)
PURPOSE: This study provides a systematic evaluation of age-related changes in RPE cell structure and function using a morphometric approach. We aim to better capture nuanced predictive changes in cell heterogeneity that reflect loss of RPE integrity during normal aging. Using C57BL6/J mice ranging from P60-P730, we sought to evaluate how regional changes in RPE shape reflect incremental losses in RPE cell function with advancing age. We hypothesize that tracking global morphological changes in RPE is predictive of functional defects over time. METHODS: We tested three groups of C57BL/6J mice (young: P60-180; Middle-aged: P365-729; aged: 730+) for function and structural defects using electroretinograms, immunofluorescence, and phagocytosis assays. RESULTS: The largest changes in RPE morphology were evident between the young and aged groups, while the middle-aged group exhibited smaller but notable region-specific differences. We observed a 1.9-fold increase in cytoplasmic alpha-catenin expression specifically in the central-medial region of the eye between the young and aged group. There was an 8-fold increase in subretinal, IBA-1-positive immune cell recruitment and a significant decrease in visual function in aged mice compared to young mice. Functional defects in the RPE corroborated by changes in RPE phagocytotic capacity. CONCLUSIONS: The marked increase of cytoplasmic alpha-catenin expression and subretinal immune cell deposition, and decreased visual output coincide with regional changes in RPE cell morphometrics when stratified by age. These cumulative changes in the RPE morphology showed predictive regional patterns of stress associated with loss of RPE integrity.

Bi-allelic variants in CELSR3 are implicated in central nervous system and urinary tract anomalies. - Stegmann, Jil D; Kalanithy, Jeshurun C; Dworschak, Gabriel C; Ishorst, Nina; Mingardo, Enrico; Lopes, Filipa M; Ho, Yee Mang; Grote, Phillip; Lindenberg, Tobias T; Yilmaz, Öznur; Channab, Khadija; Seltzsam, Steve; et al. (NPJ Genom Med, 2024)
CELSR3 codes for a planar cell polarity protein. We describe twelve affected individuals from eleven independent families with bi-allelic variants in CELSR3. Affected individuals presented with an overlapping phenotypic spectrum comprising central nervous system (CNS) anomalies (7/12), combined CNS anomalies and congenital anomalies of the kidneys and urinary tract (CAKUT) (3/12) and CAKUT only (2/12). Computational simulation of the 3D protein structure suggests the position of the identified variants to be implicated in penetrance and phenotype expression. CELSR3 immunolocalization in human embryonic urinary tract and transient suppression and rescue experiments of Celsr3 in fluorescent zebrafish reporter lines further support an embryonic role of CELSR3 in CNS and urinary tract formation.

Biallelic variation in the choline and ethanolamine transporter FLVCR1 underlies a pleiotropic disease spectrum from adult neurodegeneration to severe developmental disorders - Calame, Daniel G; Wong, Jovi Huixin; Panda, Puravi; Nguyen, Dat Tuan; Leong, Nancy C P; Sangermano, Riccardo; Patankar, Sohil G; Abdel-Hamid, Mohamed; Alabdi, Lama; Safwat, Sylvia; Flannery, Kyle P; Dardas, Zain; et al. (medRxiv, 2024)
FLVCR1 encodes Feline leukemia virus subgroup C receptor 1 (FLVCR1), a solute carrier (SLC) transporter within the Major Facilitator Superfamily. FLVCR1 is a widely expressed transmembrane protein with plasma membrane and mitochondrial isoforms implicated in heme, choline, and ethanolamine transport. While Flvcr1 knockout mice die in utero with skeletal malformations and defective erythropoiesis reminiscent of Diamond-Blackfan anemia, rare biallelic pathogenic FLVCR1 variants are linked to childhood or adult-onset neurodegeneration of the retina, spinal cord, and peripheral nervous system. We ascertained from research and clinical exome sequencing 27 individuals from 20 unrelated families with biallelic ultra-rare missense and predicted loss-of-function (pLoF) FLVCR1 variant alleles. We characterize an expansive FLVCR1 phenotypic spectrum ranging from adult-onset retinitis pigmentosa to severe developmental disorders with microcephaly, reduced brain volume, epilepsy, spasticity, and premature death. The most severely affected individuals, including three individuals with homozygous pLoF variants, share traits with Flvcr1 knockout mice and Diamond-Blackfan anemia including macrocytic anemia and congenital skeletal malformations. Pathogenic FLVCR1 missense variants primarily lie within transmembrane domains and reduce choline and ethanolamine transport activity compared with wild-type FLVCR1 with minimal impact on FLVCR1 stability or subcellular localization. Several variants disrupt splicing in a mini-gene assay which may contribute to genotype-phenotype correlations. Taken together, these data support an allele-specific gene dosage model in which phenotypic severity reflects residual FLVCR1 activity. This study expands our understanding of Mendelian disorders of choline and ethanolamine transport and demonstrates the importance of choline and ethanolamine in neurodevelopment and neuronal homeostasis.

Characterization and visualization of tandem repeats at genome scale. - Dolzhenko, Egor; English, Adam; Dashnow, Harriet; De Sena Brandine, Guilherme; Mokveld, Tom; Rowell, William J; Karniski, Caitlin; Kronenberg, Zev; Danzi, Matt C; Cheung, Warren A; Bi, Chengpeng; Farrow, Emily; et al. (Nat Biotechnol, 2024)
Tandem repeat (TR) variation is associated with gene expression changes and numerous rare monogenic diseases. Although long-read sequencing provides accurate full-length sequences and methylation of TRs, there is still a need for computational methods to profile TRs across the genome. Here we introduce the Tandem Repeat Genotyping Tool (TRGT) and an accompanying TR database. TRGT determines the consensus sequences and methylation levels of specified TRs from PacBio HiFi sequencing data. It also reports reads that support each repeat allele. These reads can be subsequently visualized with a companion TR visualization tool. Assessing 937,122 TRs, TRGT showed a Mendelian concordance of 98.38%, allowing a single repeat unit difference. In six samples with known repeat expansions, TRGT detected all expansions while also identifying methylation signals and mosaicism and providing finer repeat length resolution than existing methods. Additionally, we released a database with allele sequences and methylation levels for 937,122 TRs across 100 genomes.

Expanding the phenotype of PPP1R21-related neurodevelopmental disorder. - Almannai, Mohammed; Marafi, Dana; Zaki, Maha S; Maroofian, Reza; Efthymiou, Stephanie; Saadi, Nebal Waill; Filimban, Bilal; Dafsari, Hormos Salimi; Rahman, Fatima; Maqbool, Shazia; Faqeih, Eissa; Al Mutairi, Fuad; et al. (Clin Genet, 2024)
PPP1R21 encodes for a conserved protein that is involved in endosomal maturation. Biallelic pathogenic variants in PPP1R21 have been associated with a syndromic neurodevelopmental disorder from studying 13 affected individuals. In this report, we present 11 additional individuals from nine unrelated families and their clinical, radiological, and molecular findings. We identified eight different variants in PPP1R21, of which six were novel variants. Global developmental delay and hypotonia are neurological features that were observed in all individuals. There is also a similar pattern of dysmorphic features with coarse faces as a gestalt observed in several individuals. Common findings in 75% of individuals with available brain imaging include delays in myelination, wavy outline of the bodies of the lateral ventricles, and slight prominence of the bodies of the lateral ventricles. PPP1R21-related neurodevelopmental disorder is associated with a consistent phenotype and should be considered in highly consanguineous individuals presenting with developmental delay/intellectual disability along with coarse facial features.

Identification of constrained sequence elements across 239 primate genomes. - Kuderna, Lukas F K; Ulirsch, Jacob C; Rashid, Sabrina; Ameen, Mohamed; Sundaram, Laksshman; Hickey, Glenn; Cox, Anthony J; Gao, Hong; Kumar, Arvind; Aguet, Francois; Christmas, Matthew J; Clawson, Hiram; et al. (Nature, 2024)
Noncoding DNA is central to our understanding of human gene regulation and complex diseases, and measuring the evolutionary sequence constraint can establish the functional relevance of putative regulatory elements in the human genome. Identifying the genomic elements that have become constrained specifically in primates has been hampered by the faster evolution of noncoding DNA compared to protein-coding DNA, the relatively short timescales separating primate species, and the previously limited availability of whole-genome sequences. Here we construct a whole-genome alignment of 239 species, representing nearly half of all extant species in the primate order. Using this resource, we identified human regulatory elements that are under selective constraint across primates and other mammals at a 5% false discovery rate. We detected 111,318 DNase I hypersensitivity sites and 267,410 transcription factor binding sites that are constrained specifically in primates but not across other placental mammals and validate their cis-regulatory effects on gene expression. These regulatory elements are enriched for human genetic variants that affect gene expression and complex traits and diseases. Our results highlight the important role of recent evolution in regulatory sequence elements differentiating primates, including humans, from other placental mammals.
Keywords: Animals; Conserved Sequence; Deoxyribonuclease I; DNA; Evolution, Molecular; Female; Gene Expression Regulation; Genome; Humans; Mammals; Placenta; Pregnancy; Primates; Proteins; Regulatory Sequences, Nucleic Acid; Reproducibility of Results; Transcription Factors

Loss-of-function variants in UBAP1L cause autosomal recessive retinal degeneration. - Han, Ji Hoon; Rodenburg, Kim; Hayman, Tamar; Calzetti, Giacomo; Kaminska, Karolina; Quinodoz, Mathieu; Marra, Molly; Wallerich, Sandrine; Allon, Gilad; Nagy, Zoltán Z; Knézy, Krisztina; Yumei Li; et al. (Genet Med, 2024)
PURPOSE: Inherited retinal diseases (IRDs) are a group of monogenic conditions that can lead to progressive blindness. Their missing heritability is still considerable, due in part to the presence of disease genes that await molecular identification. The purpose of this work was to identify novel genetic associations with IRDs. METHODS: Patients underwent a comprehensive ophthalmological evaluation using standard-of-care tests, such as detailed retinal imaging (macular OCT, short-wavelength fundus autofluorescence) and electrophysiological testing. Exome and genome sequencing, as well as computer-assisted data analysis were used for genotyping and detection of DNA variants. A minigene-driven splicing assay was performed to validate the deleterious effects of one of such variants. RESULTS: We identified 8 unrelated families from Hungary, the United States, Israel, and the Netherlands with members presenting with a form of autosomal recessive and nonsyndromic retinal degeneration, predominantly described as rod-cone dystrophy but also including cases of cone / cone-rod dystrophy. Age of disease onset was very variable, with some patients experiencing first symptoms during their fourth decade of life or later. Myopia greater than 5 diopters was present in 5 of 7 cases with available refractive data, and retinal detachment was reported in 2 cases. All ascertained patients carried biallelic loss-of-function variants in UBAP1L (HGNC: 40028), a gene with unknown function and with homologies to UBAP1, encoding a protein involved in ubiquitin metabolism. One of these pathogenic variants, the intronic NM_001163692.2:c.910-7G>A substitution, was identified in five unrelated families. Minigene-driven splicing assays in HEK293T cells confirmed that this DNA change is responsible for the creation of a new acceptor splice site, resulting in aberrant splicing. CONCLUSION: We identified UBAP1L as a novel IRD gene. Although its function is currently unknown, UBAP1L is almost exclusively expressed in photoreceptors and the retinal pigment epithelium, hence possibly explaining the link between pathogenic variants in this gene and an ocular phenotype.

A polygenic risk score of atrial fibrillation improves prediction of lifetime risk for heart failure. - Alkis, Taryn; Luo, Xi; Wall, Katherine; Brody, Jennifer; Bartz, Traci; Chang, Patricia P; Norby, Faye L; Hoogeveen, Ron C; Morrison, Alanna C; Ballantyne, Christie M; Coresh, Josef; Eric Boerwinkle; et al. (ESC Heart Fail, 2024)
AIMS: Heart failure (HF) has shared genetic architecture with its risk factors: atrial fibrillation (AF), body mass index (BMI), coronary heart disease (CHD), systolic blood pressure (SBP), and type 2 diabetes (T2D). We aim to assess the association and risk prediction performance of risk-factor polygenic risk scores (PRSs) for incident HF and its subtypes in bi-racial populations. METHODS AND RESULTS: Five PRSs were constructed for AF, BMI, CHD, SBP, and T2D in White participants of the Atherosclerosis Risk in Communities (ARIC) study. The associations between PRSs and incident HF and its subtypes were assessed using Cox models, and the risk prediction performance of PRSs was assessed using C statistics. Replication was performed in the ARIC study Black and Cardiovascular Health Study (CHS) White participants. In 8624 ARIC study Whites, 1922 (31% cumulative incidence) HF cases developed over 30 years of follow-up. PRSs of AF, BMI, and CHD were associated with incident HF (P < 0.001), where PRS showed the strongest association [hazard ratio (HR): 1.47, 95% confidence interval (CI): 1.41-1.53]. Only the addition of PRS to the ARIC study HF risk equation improved C statistics for 10 year risk prediction from 0.812 to 0.829 (∆C: 0.017, 95% CI: 0.009-0.026). The PRS was associated with both incident HF with reduced ejection fraction (HR: 1.43, 95% CI: 1.27-1.60) and incident HF with preserved ejection fraction (HR: 1.46, 95% CI: 1.33-1.62). The associations between PRS and incident HF and its subtypes, as well as the improved risk prediction, were replicated in the ARIC study Blacks and the CHS Whites (P < 0.050). Protein analyses revealed that N-terminal pro-brain natriuretic peptide and other 98 proteins were associated with PRS . CONCLUSIONS: The PRS was associated with incident HF and its subtypes and had significant incremental value over an established HF risk prediction equation.

Variants in ZFX are associated with an X-linked neurodevelopmental disorder with recurrent facial gestalt. - Shepherdson, James L; Hutchison, Katie; Don, Dilan Wellalage; McGillivray, George; Choi, Tae-Ik; Allan, Carolyn A; Amor, David J; Banka, Siddharth; Basel, Donald G; Buch, Laura D; Carere, Deanna Alexis; Carroll, Renée; et al. (Am J Hum Genet, 2024)
Pathogenic variants in multiple genes on the X chromosome have been implicated in syndromic and non-syndromic intellectual disability disorders. ZFX on Xp22.11 encodes a transcription factor that has been linked to diverse processes including oncogenesis and development, but germline variants have not been characterized in association with disease. Here, we present clinical and molecular characterization of 18 individuals with germline ZFX variants. Exome or genome sequencing revealed 11 variants in 18 subjects (14 males and 4 females) from 16 unrelated families. Four missense variants were identified in 11 subjects, with seven truncation variants in the remaining individuals. Clinical findings included developmental delay/intellectual disability, behavioral abnormalities, hypotonia, and congenital anomalies. Overlapping and recurrent facial features were identified in all subjects, including thickening and medial broadening of eyebrows, variations in the shape of the face, external eye abnormalities, smooth and/or long philtrum, and ear abnormalities. Hyperparathyroidism was found in four families with missense variants, and enrichment of different tumor types was observed. In molecular studies, DNA-binding domain variants elicited differential expression of a small set of target genes relative to wild-type ZFX in cultured cells, suggesting a gain or loss of transcriptional activity. Additionally, a zebrafish model of ZFX loss displayed an altered behavioral phenotype, providing additional evidence for the functional significance of ZFX. Our clinical and experimental data support that variants in ZFX are associated with an X-linked intellectual disability syndrome characterized by a recurrent facial gestalt, neurocognitive and behavioral abnormalities, and an increased risk for congenital anomalies and hyperparathyroidism.
Keywords: Animals; Female; Humans; Hyperparathyroidism; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype; Transcription Factors; Zebrafish

Variant-specific pathophysiological mechanisms of AFF3 differently influence transcriptome profiles. - Bassani, Sissy; Chrast, Jacqueline; Ambrosini, Giovanna; Voisin, Norine; Schütz, Frédéric; Brusco, Alfredo; Sirchia, Fabio; Turban, Lydia; Schubert, Susanna; Jamra, Rami Abou; Schlump, Jan-Ulrich; DeMille, Desiree; et al. (medRxiv, 2024)
BACKGROUND: We previously described the KINSSHIP syndrome, an autosomal dominant disorder associated with intellectual disability (ID), mesomelic dysplasia and horseshoe kidney,caused by variants in the degron of AFF3. Mouse knock-ins and overexpression in zebrafish provided evidence for a dominant-negative (DN) mode-of-action, wherein an increased level of AFF3 resulted in pathological effects. METHODS: Evolutionary constraints suggest that other mode-of-inheritance could be at play. We challenged this hypothesis by screening ID cohorts for individuals with predicted-to-be deleterious variants in . We used both animal and cellular models to assess the deleteriousness of the identified variants. RESULTS: We identified an individual with a KINSSHIP-like phenotype carrying a partial duplication of further strengthening the hypothesis that an increased level of AFF3 is pathological. We also detected seventeen individuals displaying a milder syndrome with either heterozygous LoF or biallelic missense variants in . Consistent with semi-dominance, we discovered three patients with homozygous LoF and one compound heterozygote for a LoF and a missense variant, who presented more severe phenotypes than their heterozygous parents. Matching zebrafish knockdowns exhibit neurological defects that could be rescued by expressing human mRNA, confirming their association with the ablation of . Conversely, some of the human mRNAs carrying missense variants identified in affected individuals did not complement. Overexpression of mutated mRNAs in zebrafish embryos produced a significant increase of abnormal larvae compared to wild-type overexpression further demonstrating deleteriousness. To further assess the effect of variation, we profiled the transcriptome of fibroblasts from affected individuals and engineered isogenic cells harboring +/+, DN/DN, LoF/+, LoF/LoF or DN/LoF genotypes. The expression of more than a third of the AFF3 bound loci is modified in either the DN/DN or the LoF/LoF lines. While the same pathways are affected, only about one-third of the differentially expressed genes are common to these homozygote datasets, indicating that LoF and DN variants largely modulate transcriptomes differently, e.g. the DNA repair pathway displayed opposite modulation. CONCLUSIONS: Our results and the high pleiotropy shown by variation at this locus suggest that minute changes in function are deleterious.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association of Common and Rare Variants with Alzheimer's Disease in over 13,000 Diverse Individuals with Whole-Genome Sequencing from the Alzheimer's Disease Sequencing Project. - Lee, Wan-Ping; Choi, Seung Hoan; Shea, Margaret G; Cheng, Po-Liang; Dombroski, Beth A; Pitsillides, Achilleas N; Heard-Costa, Nancy L; Wang, Hui; Bulekova, Katia; Kuzma, Amanda B; Leung, Yuk Yee; Farrell, John J; et al. (medRxiv, 2023)
Alzheimer's Disease (AD) is a common disorder of the elderly that is both highly heritable and genetically heterogeneous. Here, we investigated the association between AD and both common variants and aggregates of rare coding and noncoding variants in 13,371 individuals of diverse ancestry with whole genome sequence (WGS) data. Pooled-population analyses identified genetic variants in or near , , and significantly associated with AD (p < 5×10). Population-specific analyses identified a haplotype on chromosome 14 including associated with AD in Hispanics, further supported by aggregate testing of rare coding and noncoding variants in this region. Finally, we observed suggestive associations (p < 5×10) of aggregates of rare coding rare variants in ABCA7 among non-Hispanic Whites (p=5.4×10), and rare noncoding variants in the promoter of distinct of in pooled-population analyses (p=7.2×10). Complementary pooled-population and population-specific analyses offered unique insights into the genetic architecture of AD.

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest that lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer disease (AD) and AD-related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from 9 diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5-20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (β = 0.04; 95% CI 0.02-0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the United States. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.
Keywords: Aged; Alzheimer Disease; Brain; Cognition; Cross-Sectional Studies; DNA Copy Number Variations; DNA, Mitochondrial; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Eric Boerwinkle; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.
Keywords: Adult; Aged; Apolipoproteins B; Cholesterol, LDL; Coronary Disease; DNA; Female; Humans; Male; Middle Aged; Proprotein Convertase 9; Prospective Studies

Author Correction: Analyses of non-coding somatic drivers in 2,658 cancer whole genomes. - Rheinbay, Esther; Nielsen, Morten Muhlig; Abascal, Federico; Wala, Jeremiah A; Shapira, Ofer; Tiao, Grace; Hornshøj, Henrik; Hess, Julian M; Juul, Randi Istrup; Lin, Ziao; Feuerbach, Lars; Sabarinathan, Radhakrishnan; et al. (Nature, 2023)

Author Correction: Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)

Author Correction: Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2023)

Author Correction: The repertoire of mutational signatures in human cancer. - Alexandrov, Ludmil B; Kim, Jaegil; Haradhvala, Nicholas J; Huang, Mi Ni; Tian Ng, Alvin Wei; Wu, Yang; Boot, Arnoud; Covington, Kyle R; Gordenin, Dmitry A; Bergstrom, Erik N; Islam, S M Ashiqul; Lopez-Bigas, Nuria; et al. (Nature, 2023)

Bi-allelic ACBD6 variants lead to a neurodevelopmental syndrome with progressive and complex movement disorders. - Kaiyrzhanov, Rauan; Rad, Aboulfazl; Lin, Sheng-Jia; Bertoli-Avella, Aida; Kallemeijn, Wouter W; Godwin, Annie; Zaki, Maha S; Huang, Kevin; Lau, Tracy; Petree, Cassidy; Efthymiou, Stephanie; Ghayoor Karimiani, Ehsan; et al. (Brain, 2023)
The acyl-CoA-binding domain-containing protein 6 (ACBD6) is ubiquitously expressed, plays a role in the acylation of lipids and proteins, and regulates the N-myristoylation of proteins via N-myristoyltransferase enzymes (NMTs). However, its precise function in cells is still unclear, as is the consequence of ACBD6 defects on human pathophysiology. Utilizing exome sequencing and extensive international data sharing efforts, we identified 45 affected individuals from 28 unrelated families (consanguinity 93%) with bi-allelic pathogenic, predominantly loss-of-function (18/20) variants in ACBD6. We generated zebrafish and Xenopus tropicalis acbd6 knockouts by CRISPR/Cas9 and characterized the role of ACBD6 on protein N-myristoylation with YnMyr chemical proteomics in the model organisms and human cells, with the latter also being subjected further to ACBD6 peroxisomal localization studies. The affected individuals (23 males and 22 females), with ages ranging from 1 to 50 years old, typically present with a complex and progressive disease involving moderate-to-severe global developmental delay/intellectual disability (100%) with significant expressive language impairment (98%), movement disorders (97%), facial dysmorphism (95%), and mild cerebellar ataxia (85%) associated with gait impairment (94%), limb spasticity/hypertonia (76%), oculomotor (71%) and behavioural abnormalities (65%), overweight (59%), microcephaly (39%) and epilepsy (33%). The most conspicuous and common movement disorder was dystonia (94%), frequently leading to early-onset progressive postural deformities (97%), limb dystonia (55%), and cervical dystonia (31%). A jerky tremor in the upper limbs (63%), a mild head tremor (59%), parkinsonism/hypokinesia developing with advancing age (32%), and simple motor and vocal tics were among other frequent movement disorders. Midline brain malformations including corpus callosum abnormalities (70%), hypoplasia/agenesis of the anterior commissure (66%), short midbrain and small inferior cerebellar vermis (38% each), as well as hypertrophy of the clava (24%) were common neuroimaging findings. acbd6-deficient zebrafish and Xenopus models effectively recapitulated many clinical phenotypes reported in patients including movement disorders, progressive neuromotor impairment, seizures, microcephaly, craniofacial dysmorphism, and midbrain defects accompanied by developmental delay with increased mortality over time. Unlike ACBD5, ACBD6 did not show a peroxisomal localisation and ACBD6-deficiency was not associated with altered peroxisomal parameters in patient fibroblasts. Significant differences in YnMyr-labelling were observed for 68 co- and 18 post-translationally N-myristoylated proteins in patient-derived fibroblasts. N-Myristoylation was similarly affected in acbd6-deficient zebrafish and Xenopus tropicalis models, including Fus, Marcks, and Chchd-related proteins implicated in neurological diseases. The present study provides evidence that bi-allelic pathogenic variants in ACBD6 lead to a distinct neurodevelopmental syndrome accompanied by complex and progressive cognitive and movement disorders.

A biallelic frameshift indel in PPP1R35 as a cause of primary microcephaly. - Dawood, Moez; Akay, Gulsen; Mitani, Tadahiro; Marafi, Dana; Fatih, Jawid M; Gezdirici, Alper; Najmabadi, Hossein; Kahrizi, Kimia; Punetha, Jaya; Grochowski, Christopher M; Du, Haowei; Jolly, Angad; et al. (Am J Med Genet A, 2023)
Protein phosphatase 1 regulatory subunit 35 (PPP1R35) encodes a centrosomal protein required for recruiting microtubule-binding elongation machinery. Several proteins in this centriole biogenesis pathway correspond to established primary microcephaly (MCPH) genes, and multiple model organism studies hypothesize PPP1R35 as a candidate MCPH gene. Here, using exome sequencing (ES) and family-based rare variant analyses, we report a homozygous, frameshifting indel deleting the canonical stop codon in the last exon of PPP1R35 [Chr7: c.753_*3delGGAAGCGTAGACCinsCG (p.Trp251Cysfs*22)]; the variant allele maps in a 3.7 Mb block of absence of heterozygosity (AOH) in a proband with severe MCPH (-4.3 SD at birth, -6.1 SD by 42 months), pachygyria, and global developmental delay from a consanguineous Turkish kindred. Droplet digital PCR (ddPCR) confirmed mutant mRNA expression in fibroblasts. In silico prediction of the translation of mutant PPP1R35 is expected to be elongated by 18 amino acids before encountering a downstream stop codon. This complex indel allele is absent in public databases (ClinVar, gnomAD, ARIC, 1000 genomes) and our in-house database of 14,000+ exomes including 1800+ Turkish exomes supporting predicted pathogenicity. Comprehensive literature searches for PPP1R35 variants yielded two probands affected with severe microcephaly (-15 SD and -12 SD) with the same homozygous indel from a single, consanguineous, Iranian family from a cohort of 404 predominantly Iranian families. The lack of heterozygous cases in two large cohorts representative of the genetic background of these two families decreased our suspicion of a founder allele and supports the contention of a recurrent mutation. We propose two potential secondary structure mutagenesis models for the origin of this variant allele mediated by hairpin formation between complementary GC rich segments flanking the stop codon via secondary structure mutagenesis.
Keywords: Codon, Terminator; Frameshift Mutation; Humans; Infant, Newborn; Iran; Microcephaly; Microtubule-Associated Proteins; Pedigree

Biallelic missense variants in COG3 cause a congenital disorder of glycosylation with impairment of retrograde vesicular trafficking. - Duan, Ruizhi; Marafi, Dana; Xia, Zhi-Jie; Ng, Bobby G; Maroofian, Reza; Sumya, Farhana Taher; Saad, Ahmed K; Du, Haowei; Fatih, Jawid M; Hunter, Jill V; Elbendary, Hasnaa M; Baig, Shahid M; et al. (J Inherit Metab Dis, 2023)
Biallelic variants in genes for seven out of eight subunits of the conserved oligomeric Golgi complex (COG) are known to cause recessive congenital disorders of glycosylation (CDG) with variable clinical manifestations. COG3 encodes a constituent subunit of the COG complex that has not been associated with disease traits in humans. Herein, we report two COG3 homozygous missense variants in four individuals from two unrelated consanguineous families that co-segregated with COG3-CDG presentations. Clinical phenotypes of affected individuals include global developmental delay, severe intellectual disability, microcephaly, epilepsy, facial dysmorphism, and variable neurological findings. Biochemical analysis of serum transferrin from one family showed the loss of a single sialic acid. Western blotting on patient-derived fibroblasts revealed reduced COG3 and COG4. Further experiments showed delayed retrograde vesicular recycling in patient cells. This report adds to the knowledge of the COG-CDG network by providing collective evidence for a COG3-CDG rare disease trait and implicating a likely pathology of the disorder as the perturbation of Golgi trafficking.
Keywords: Adaptor Proteins, Vesicular Transport; Congenital Disorders of Glycosylation; Fibroblasts; Glycosylation; Humans; Phenotype

Bi-allelic SNAPC4 variants dysregulate global alternative splicing and lead to neuroregression and progressive spastic paraparesis. - Frost, F Graeme; Morimoto, Marie; Sharma, Prashant; Ruaud, Lyse; Belnap, Newell; Calame, Daniel G; Uchiyama, Yuri; Matsumoto, Naomichi; Oud, Machteld M; Ferreira, Elise A; Narayanan, Vinodh; Rangasamy, Sampath; et al. (Am J Hum Genet, 2023)
The vast majority of human genes encode multiple isoforms through alternative splicing, and the temporal and spatial regulation of those isoforms is critical for organismal development and function. The spliceosome, which regulates and executes splicing reactions, is primarily composed of small nuclear ribonucleoproteins (snRNPs) that consist of small nuclear RNAs (snRNAs) and protein subunits. snRNA gene transcription is initiated by the snRNA-activating protein complex (SNAPc). Here, we report ten individuals, from eight families, with bi-allelic, deleterious SNAPC4 variants. SNAPC4 encoded one of the five SNAPc subunits that is critical for DNA binding. Most affected individuals presented with delayed motor development and developmental regression after the first year of life, followed by progressive spasticity that led to gait alterations, paraparesis, and oromotor dysfunction. Most individuals had cerebral, cerebellar, or basal ganglia volume loss by brain MRI. In the available cells from affected individuals, SNAPC4 abundance was decreased compared to unaffected controls, suggesting that the bi-allelic variants affect SNAPC4 accumulation. The depletion of SNAPC4 levels in HeLa cell lines via genomic editing led to decreased snRNA expression and global dysregulation of alternative splicing. Analysis of available fibroblasts from affected individuals showed decreased snRNA expression and global dysregulation of alternative splicing compared to unaffected cells. Altogether, these data suggest that these bi-allelic SNAPC4 variants result in loss of function and underlie the neuroregression and progressive spasticity in these affected individuals.
Keywords: Adolescent; Alleles; Alternative Splicing; Child; Child, Preschool; DNA-Binding Proteins; Female; HeLa Cells; Humans; Infant; Male; Paraparesis, Spastic; Pedigree; Protein Isoforms; Protein Structure, Secondary; RNA, Small Nuclear; RNA-Seq; Transcription Factors

Bi-allelic TTI1 variants cause an autosomal-recessive neurodevelopmental disorder with microcephaly. - Serey-Gaut, Margaux; Cortes, Marisol; Makrythanasis, Periklis; Suri, Mohnish; Taylor, Alexander M R; Sullivan, Jennifer A; Asleh, Ayat N; Mitra, Jaba; Dar, Mohamad A; McNamara, Amy; Shashi, Vandana; Dugan, Sarah; et al. (Am J Hum Genet, 2023)
Telomere maintenance 2 (TELO2), Tel2 interacting protein 2 (TTI2), and Tel2 interacting protein 1 (TTI1) are the three components of the conserved Triple T (TTT) complex that modulates activity of phosphatidylinositol 3-kinase-related protein kinases (PIKKs), including mTOR, ATM, and ATR, by regulating the assembly of mTOR complex 1 (mTORC1). The TTT complex is essential for the expression, maturation, and stability of ATM and ATR in response to DNA damage. TELO2- and TTI2-related bi-allelic autosomal-recessive (AR) encephalopathies have been described in individuals with moderate to severe intellectual disability (ID), short stature, postnatal microcephaly, and a movement disorder (in the case of variants within TELO2). We present clinical, genomic, and functional data from 11 individuals in 9 unrelated families with bi-allelic variants in TTI1. All present with ID, and most with microcephaly, short stature, and a movement disorder. Functional studies performed in HEK293T cell lines and fibroblasts and lymphoblastoid cells derived from 4 unrelated individuals showed impairment of the TTT complex and of mTOR pathway activity which is improved by treatment with Rapamycin. Our data delineate a TTI1-related neurodevelopmental disorder and expand the group of disorders related to the TTT complex.
Keywords: HEK293 Cells; Humans; Intracellular Signaling Peptides and Proteins; Microcephaly; Movement Disorders; Neurodevelopmental Disorders; TOR Serine-Threonine Kinases

Biallelic variants in HECT E3 paralogs, HECTD4 and UBE3C, encoding ubiquitin ligases cause neurodevelopmental disorders that overlap with Angelman syndrome. - Faqeih, Eissa A; Alghamdi, Malak Ali; Almahroos, Marwa A; Alharby, Essa; Almuntashri, Makki; Alshangiti, Amnah M; Clément, Prouteau; Calame, Daniel G; Qebibo, Leila; Burglen, Lydie; Doco-Fenzy, Martine; Mastrangelo, Mario; et al. (Genet Med, 2023)
PURPOSE: Pathogenic variants in genes encoding ubiquitin E3 ligases are known to cause neurodevelopmental syndromes. Additional neurodevelopmental disorders associated with the other genes encoding E3 ligases are yet to be identified. METHODS: Chromosomal analysis and exome sequencing were used to identify the genetic causes in 10 patients from 7 unrelated families with syndromic neurodevelopmental, seizure, and movement disorders and neurobehavioral phenotypes. RESULTS: In total, 4 patients were found to have 3 different homozygous loss-of-function (LoF) variants, and 3 patients had 4 compound heterozygous missense variants in the candidate E3 ligase gene, HECTD4, that were rare, absent from controls as homozygous, and predicted to be deleterious in silico. In 3 patients from 2 families with Angelman-like syndrome, paralog-directed candidate gene approach detected 2 LoF variants in the other candidate E3 ligase gene, UBE3C, a paralog of the Angelman syndrome E3 ligase gene, UBE3A. The RNA studies in 4 patients with LoF variants in HECTD4 and UBE3C provided evidence for the LoF effect. CONCLUSION: HECTD4 and UBE3C are novel biallelic rare disease genes, expand the association of the other HECT E3 ligase group with neurodevelopmental syndromes, and could explain some of the missing heritability in patients with a suggestive clinical diagnosis of Angelman syndrome.
Keywords: Angelman Syndrome; Humans; Neurodevelopmental Disorders; Phenotype; Ubiquitin; Ubiquitin-Protein Ligases

Bi-allelic variants in the ESAM tight-junction gene cause a neurodevelopmental disorder associated with fetal intracranial hemorrhage. - Lecca, Mauro; Pehlivan, Davut; Suñer, Damià Heine; Weiss, Karin; Coste, Thibault; Zweier, Markus; Oktay, Yavuz; Danial-Farran, Nada; Rosti, Vittorio; Bonasoni, Maria Paola; Malara, Alessandro; Contrò, Gianluca; et al. (Am J Hum Genet, 2023)
The blood-brain barrier (BBB) is an essential gatekeeper for the central nervous system and incidence of neurodevelopmental disorders (NDDs) is higher in infants with a history of intracerebral hemorrhage (ICH). We discovered a rare disease trait in thirteen individuals, including four fetuses, from eight unrelated families associated with homozygous loss-of-function variant alleles of ESAM which encodes an endothelial cell adhesion molecule. The c.115del (p.Arg39Glyfs33) variant, identified in six individuals from four independent families of Southeastern Anatolia, severely impaired the in vitro tubulogenic process of endothelial colony-forming cells, recapitulating previous evidence in null mice, and caused lack of ESAM expression in the capillary endothelial cells of damaged brain. Affected individuals with bi-allelic ESAM variants showed profound global developmental delay/unspecified intellectual disability, epilepsy, absent or severely delayed speech, varying degrees of spasticity, ventriculomegaly, and ICH/cerebral calcifications, the latter being also observed in the fetuses. Phenotypic traits observed in individuals with bi-allelic ESAM variants overlap very closely with other known conditions characterized by endothelial dysfunction due to mutation of genes encoding tight junction molecules. Our findings emphasize the role of brain endothelial dysfunction in NDDs and contribute to the expansion of an emerging group of diseases that we propose to rename as "tightjunctionopathies."
Keywords: Alleles; Animals; Brain Diseases; Cell Adhesion Molecules; Endothelial Cells; Humans; Intracranial Hemorrhages; Mice; Nervous System Malformations; Neurodevelopmental Disorders; Tight Junctions

Breast Cancer Detection with an Ensemble of Deep Learning Networks Using a Consensus-Adaptive Weighting Method. - Dehghan Rouzi, Mohammad; Moshiri, Behzad; Khoshnevisan, Mohammad; Akhaee, Mohammad Ali; Jaryani, Farhang; Salehi Nasab, Samaneh; Lee, Myeounggon (J Imaging, 2023)
Breast cancer's high mortality rate is often linked to late diagnosis, with mammograms as key but sometimes limited tools in early detection. To enhance diagnostic accuracy and speed, this study introduces a novel computer-aided detection (CAD) ensemble system. This system incorporates advanced deep learning networks-EfficientNet, Xception, MobileNetV2, InceptionV3, and Resnet50-integrated via our innovative consensus-adaptive weighting (CAW) method. This method permits the dynamic adjustment of multiple deep networks, bolstering the system's detection capabilities. Our approach also addresses a major challenge in pixel-level data annotation of faster R-CNNs, highlighted in a prominent previous study. Evaluations on various datasets, including the cropped DDSM (Digital Database for Screening Mammography), DDSM, and INbreast, demonstrated the system's superior performance. In particular, our CAD system showed marked improvement on the cropped DDSM dataset, enhancing detection rates by approximately 1.59% and achieving an accuracy of 95.48%. This innovative system represents a significant advancement in early breast cancer detection, offering the potential for more precise and timely diagnosis, ultimately fostering improved patient outcomes.

Chimeric RNAs reveal putative neoantigen peptides for developing tumor vaccines for breast cancer. - Mistretta, Brandon; Rankothgedera, Sakuni; Castillo, Micah; Rao, Mitchell; Holloway, Kimberly; Bhardwaj, Anjana; El Noafal, Maha; Albarracin, Constance; El-Zein, Randa; Rezaei, Hengameh; Su, Xiaoping; Akbani, Rehan; et al. (Front Immunol, 2023)
INTRODUCTION: We present here a strategy to identify immunogenic neoantigen candidates from unique amino acid sequences at the junctions of fusion proteins which can serve as targets in the development of tumor vaccines for the treatment of breastcancer. METHOD: We mined the sequence reads of breast tumor tissue that are usually discarded as discordant paired-end reads and discovered cancer specific fusion transcripts using tissue from cancer free controls as reference. Binding affinity predictions of novel peptide sequences crossing the fusion junction were analyzed by the MHC Class I binding predictor, MHCnuggets. CD8+ T cell responses against the 15 peptides were assessed through in vitro Enzyme Linked Immunospot (ELISpot). RESULTS: We uncovered 20 novel fusion transcripts from 75 breast tumors of 3 subtypes: TNBC, HER2+, and HR+. Of these, the NSFP1-LRRC37A2 fusion transcript was selected for further study. The 3833 bp chimeric RNA predicted by the consensus fusion junction sequence is consistent with a read-through transcription of the 5'-gene NSFP1-Pseudo gene NSFP1 (NSFtruncation at exon 12/13) followed by trans-splicing to connect withLRRC37A2 located immediately 3' through exon 1/2. A total of 15 different 8-mer neoantigen peptides discovered from the NSFP1 and LRRC37A2 truncations were predicted to bind to a total of 35 unique MHC class I alleles with a binding affinity of IC50<500nM.); 1 of which elicited a robust immune response. CONCLUSION: Our data provides a framework to identify immunogenic neoantigen candidates from fusion transcripts and suggests a potential vaccine strategy to target the immunogenic neopeptides in patients with tumors carrying the NSFP1-LRRC37A2 fusion.
Keywords: Animals; Breast; Breast Neoplasms; Cancer Vaccines; Female; Genes, MHC Class I; Humans; Mammary Neoplasms, Animal

Clinical and functional heterogeneity associated with the disruption of retinoic acid receptor beta. - Caron, Véronique; Chassaing, Nicolas; Ragge, Nicola; Boschann, Felix; Ngu, Angelina My-Hoa; Meloche, Elisabeth; Chorfi, Sarah; Lakhani, Saquib A; Ji, Weizhen; Steiner, Laurie; Marcadier, Julien; Jansen, Philip R; et al. (Genet Med, 2023)
PURPOSE: Dominant variants in the retinoic acid receptor beta (RARB) gene underlie a syndromic form of microphthalmia, known as MCOPS12, which is associated with other birth anomalies and global developmental delay with spasticity and/or dystonia. Here, we report 25 affected individuals with 17 novel pathogenic or likely pathogenic variants in RARB. This study aims to characterize the functional impact of these variants and describe the clinical spectrum of MCOPS12. METHODS: We used in vitro transcriptional assays and in silico structural analysis to assess the functional relevance of RARB variants in affecting the normal response to retinoids. RESULTS: We found that all RARB variants tested in our assays exhibited either a gain-of-function or a loss-of-function activity. Loss-of-function variants disrupted RARB function through a dominant-negative effect, possibly by disrupting ligand binding and/or coactivators' recruitment. By reviewing clinical data from 52 affected individuals, we found that disruption of RARB is associated with a more variable phenotype than initially suspected, with the absence in some individuals of cardinal features of MCOPS12, such as developmental eye anomaly or motor impairment. CONCLUSION: Our study indicates that pathogenic variants in RARB are functionally heterogeneous and associated with extensive clinical heterogeneity.
Keywords: Humans; Microphthalmos; Receptors, Retinoic Acid; Retinoids

Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)
Chronic liver disease is a major public health burden worldwide. Although different aetiologies and mechanisms of liver injury exist, progression of chronic liver disease follows a common pathway of liver inflammation, injury and fibrosis. Here we examined the association between clonal haematopoiesis of indeterminate potential (CHIP) and chronic liver disease in 214,563 individuals from 4 independent cohorts with whole-exome sequencing data (Framingham Heart Study, Atherosclerosis Risk in Communities Study, UK Biobank and Mass General Brigham Biobank). CHIP was associated with an increased risk of prevalent and incident chronic liver disease (odds ratio = 2.01, 95% confidence interval (95% CI) [1.46, 2.79]; P < 0.001). Individuals with CHIP were more likely to demonstrate liver inflammation and fibrosis detectable by magnetic resonance imaging compared to those without CHIP (odds ratio = 1.74, 95% CI [1.16, 2.60]; P = 0.007). To assess potential causality, Mendelian randomization analyses showed that genetic predisposition to CHIP was associated with a greater risk of chronic liver disease (odds ratio = 2.37, 95% CI [1.57, 3.6]; P < 0.001). In a dietary model of non-alcoholic steatohepatitis, mice transplanted with Tet2-deficient haematopoietic cells demonstrated more severe liver inflammation and fibrosis. These effects were mediated by the NLRP3 inflammasome and increased levels of expression of downstream inflammatory cytokines in Tet2-deficient macrophages. In summary, clonal haematopoiesis is associated with an elevated risk of liver inflammation and chronic liver disease progression through an aberrant inflammatory response.
Keywords: Animals; Clonal Hematopoiesis; Disease Progression; Disease Susceptibility; Hepatitis; Inflammation; Liver Cirrhosis; Mice; Non-alcoholic Fatty Liver Disease; Odds Ratio

The complete sequence of a human Y chromosome. - Rhie, Arang; Nurk, Sergey; Cechova, Monika; Hoyt, Savannah J; Taylor, Dylan J; Altemose, Nicolas; Hook, Paul W; Koren, Sergey; Rautiainen, Mikko; Alexandrov, Ivan A; Allen, Jamie; Asri, Mobin; et al. (Nature, 2023)
The human Y chromosome has been notoriously difficult to sequence and assemble because of its complex repeat structure that includes long palindromes, tandem repeats and segmental duplications. As a result, more than half of the Y chromosome is missing from the GRCh38 reference sequence and it remains the last human chromosome to be finished. Here, the Telomere-to-Telomere (T2T) consortium presents the complete 62,460,029-base-pair sequence of a human Y chromosome from the HG002 genome (T2T-Y) that corrects multiple errors in GRCh38-Y and adds over 30 million base pairs of sequence to the reference, showing the complete ampliconic structures of gene families TSPY, DAZ and RBMY; 41 additional protein-coding genes, mostly from the TSPY family; and an alternating pattern of human satellite 1 and 3 blocks in the heterochromatic Yq12 region. We have combined T2T-Y with a previous assembly of the CHM13 genome and mapped available population variation, clinical variants and functional genomics data to produce a complete and comprehensive reference sequence for all 24 human chromosomes.
Keywords: Base Sequence; Chromosomes, Human, Y; DNA, Satellite; Genetic Variation; Genetics, Population; Genomics; Heterochromatin; Humans; Multigene Family; Reference Standards; Segmental Duplications, Genomic; Sequence Analysis, DNA; Tandem Repeat Sequences; Telomere

An efficient genotyper and star-allele caller for pharmacogenomics. - Hari, Ananth; Zhou, Qinghui; Gonzaludo, Nina; Harting, John; Scott, Stuart A; Xiang Qin; Steven E Scherer; Sahinalp, S Cenk; Numanagić, Ibrahim (Genome Res, 2023)
High-throughput sequencing provides sufficient means for determining genotypes of clinically important pharmacogenes that can be used to tailor medical decisions to individual patients. However, pharmacogene genotyping, also known as star-allele calling, is a challenging problem that requires accurate copy number calling, structural variation identification, variant calling, and phasing within each pharmacogene copy present in the sample. Here we introduce Aldy 4, a fast and efficient tool for genotyping pharmacogenes that uses combinatorial optimization for accurate star-allele calling across different sequencing technologies. Aldy 4 adds support for long reads and uses a novel phasing model and improved copy number and variant calling models. We compare Aldy 4 against the current state-of-the-art star-allele callers on a large and diverse set of samples and genes sequenced by various sequencing technologies, such as whole-genome and targeted Illumina sequencing, barcoded 10x Genomics, and Pacific Biosciences (PacBio) HiFi. We show that Aldy 4 is the most accurate star-allele caller with near-perfect accuracy in all evaluated contexts, and hope that Aldy remains an invaluable tool in the clinical toolbox even with the advent of long-read sequencing technologies.
Keywords: Alleles; Genomics; Genotype; High-Throughput Nucleotide Sequencing; Humans; Pharmacogenetics; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

The EN-TEx resource of multi-tissue personal epigenomes & variant-impact models. - Rozowsky, Joel; Gao, Jiahao; Borsari, Beatrice; Yang, Yucheng T; Galeev, Timur; Gürsoy, Gamze; Epstein, Charles B; Xiong, Kun; Xu, Jinrui; Li, Tianxiao; Liu, Jason; Yu, Keyang; et al. (Cell, 2023)
Understanding how genetic variants impact molecular phenotypes is a key goal of functional genomics, currently hindered by reliance on a single haploid reference genome. Here, we present the EN-TEx resource of 1,635 open-access datasets from four donors (∼30 tissues × ∼15 assays). The datasets are mapped to matched, diploid genomes with long-read phasing and structural variants, instantiating a catalog of >1 million allele-specific loci. These loci exhibit coordinated activity along haplotypes and are less conserved than corresponding, non-allele-specific ones. Surprisingly, a deep-learning transformer model can predict the allele-specific activity based only on local nucleotide-sequence context, highlighting the importance of transcription-factor-binding motifs particularly sensitive to variants. Furthermore, combining EN-TEx with existing genome annotations reveals strong associations between allele-specific and GWAS loci. It also enables models for transferring known eQTLs to difficult-to-profile tissues (e.g., from skin to heart). Overall, EN-TEx provides rich data and generalizable models for more accurate personal functional genomics.
Keywords: Epigenome; Genome-Wide Association Study; Genomics; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Exome Sequencing Implicates DGKZ , ESRRA , and GXYLT1 for Modulating Granuloma Formation in Crohn Disease. - R. Alan Harris; Bush, Allyson H; Eagar, Todd N; Qian, Justin; Greenwood, Michael P; Opekun, Antone R; Baldassano, Robert; Guthery, Stephen L; Noe, Joshua D; Otley, Anthony; Rosh, Joel R; Kugathasan, Subra; et al. (J Pediatr Gastroenterol Nutr, 2023)
Non-caseating granulomas may indicate a more aggressive phenotype of Crohn disease (CD). Genetic associations of granulomatous CD (GCD) may help elucidate disease pathogenesis. Whole-exome sequencing was performed on peripheral blood-derived DNA from 17 pediatric patients with GCD and 19 with non-GCD (NGCD), and from an independent validation cohort of 44 GCD and 19 NGCD cases. PLINK (a tool set for whole-genome association and population-based linkage analyses) analysis was used to identify single nucleotide polymorphisms (SNPs) differentiating between groups, and subgroup allele frequencies were also compared to a public genomic database (gnomAD). The Combined Annotation Dependent Depletion scoring tool was used to predict deleteriousness of SNPs. Human leukocyte antigen (HLA) haplotype findings were compared to a control group (n = 8496). PLINK-based analysis between GCD and NGCD groups did not find consistently significant hits. gnomAD control comparisons, however, showed consistent subgroup associations with DGKZ , ESRRA , and GXYLT1 , genes that have been implicated in mammalian granulomatous inflammation. Our findings may guide future research and precision medicine.
Keywords: Child; Crohn Disease; ERRalpha Estrogen-Related Receptor; Exome Sequencing; Genetic Predisposition to Disease; Granuloma; Humans; Phenotype

Exome-wide assessment of isolated biliary atresia: A report from the National Birth Defects Prevention Study using child-parent trios and a case-control design to identify novel rare variants. - Sok, Pagna; Aniko Sabo; Almli, Lynn M; Jenkins, Mary M; Nembhard, Wendy N; Agopian, A J; Bamshad, Michael J; Blue, Elizabeth E; Brody, Lawrence C; Brown, Austin L; Browne, Marilyn L; Canfield, Mark A; et al. (Am J Med Genet A, 2023)
The etiology of biliary atresia (BA) is unknown, but recent studies suggest a role for rare protein-altering variants (PAVs). Exome sequencing data from the National Birth Defects Prevention Study on 54 child-parent trios, one child-mother duo, and 1513 parents of children with other birth defects were analyzed. Most (91%) cases were isolated BA. We performed (1) a trio-based analysis to identify rare de novo, homozygous, and compound heterozygous PAVs and (2) a case-control analysis using a sequence kernel-based association test to identify genes enriched with rare PAVs. While we replicated previous findings on PKD1L1, our results do not suggest that recurrent de novo PAVs play important roles in BA susceptibility. In fact, our finding in NOTCH2, a disease gene associated with Alagille syndrome, highlights the difficulty in BA diagnosis. Notably, IFRD2 has been implicated in other gastrointestinal conditions and warrants additional study. Overall, our findings strengthen the hypothesis that the etiology of BA is complex.
Keywords: Biliary Atresia; Case-Control Studies; Exome; Homozygote; Humans; Membrane Proteins; Parents

FOXI3 pathogenic variants cause one form of craniofacial microsomia. - Mao, Ke; Borel, Christelle; Ansar, Muhammad; Jolly, Angad; Makrythanasis, Periklis; Froehlich, Christine; Iwaszkiewicz, Justyna; Wang, Bingqing; Xu, Xiaopeng; Li, Qiang; Blanc, Xavier; Zhu, Hao; et al. (Nat Commun, 2023)
Craniofacial microsomia (CFM; also known as Goldenhar syndrome), is a craniofacial developmental disorder of variable expressivity and severity with a recognizable set of abnormalities. These birth defects are associated with structures derived from the first and second pharyngeal arches, can occur unilaterally and include ear dysplasia, microtia, preauricular tags and pits, facial asymmetry and other malformations. The inheritance pattern is controversial, and the molecular etiology of this syndrome is largely unknown. A total of 670 patients belonging to unrelated pedigrees with European and Chinese ancestry with CFM, are investigated. We identify 18 likely pathogenic variants in 21 probands (3.1%) in FOXI3. Biochemical experiments on transcriptional activity and subcellular localization of the likely pathogenic FOXI3 variants, and knock-in mouse studies strongly support the involvement of FOXI3 in CFM. Our findings indicate autosomal dominant inheritance with reduced penetrance, and/or autosomal recessive inheritance. The phenotypic expression of the FOXI3 variants is variable. The penetrance of the likely pathogenic variants in the seemingly dominant form is reduced, since a considerable number of such variants in affected individuals were inherited from non-affected parents. Here we provide suggestive evidence that common variation in the FOXI3 allele in trans with the pathogenic variant could modify the phenotypic severity and accounts for the incomplete penetrance.
Keywords: Animals; Facial Asymmetry; Forkhead Transcription Factors; Goldenhar Syndrome; Mice; Pedigree

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (Genetics, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-sequencing data in GTEx V8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased whole genome sequencing data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.
Keywords: Alternative Splicing; Exons; Genotype; Penetrance; RNA Splice Sites; RNA Splicing; RNA, Messenger

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Eric Boerwinkle; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Genome-Wide Analysis of Structural Variants in Parkinson Disease. - Billingsley, Kimberley J; Ding, Jinhui; Jerez, Pilar Alvarez; Illarionova, Anastasia; Levine, Kristin; Grenn, Francis P; Makarious, Mary B; Moore, Anni; Vitale, Daniel; Reed, Xylena; Hernandez, Dena; Torkamani, Ali; et al. (Ann Neurol, 2023)
OBJECTIVE: Identification of genetic risk factors for Parkinson disease (PD) has to date been primarily limited to the study of single nucleotide variants, which only represent a small fraction of the genetic variation in the human genome. Consequently, causal variants for most PD risk are not known. Here we focused on structural variants (SVs), which represent a major source of genetic variation in the human genome. We aimed to discover SVs associated with PD risk by performing the first large-scale characterization of SVs in PD. METHODS: We leveraged a recently developed computational pipeline to detect and genotype SVs from 7,772 Illumina short-read whole genome sequencing samples. Using this set of SV variants, we performed a genome-wide association study using 2,585 cases and 2,779 controls and identified SVs associated with PD risk. Furthermore, to validate the presence of these variants, we generated a subset of matched whole-genome long-read sequencing data. RESULTS: We genotyped and tested 3,154 common SVs, representing over 412 million nucleotides of previously uncatalogued genetic variation. Using long-read sequencing data, we validated the presence of three novel deletion SVs that are associated with risk of PD from our initial association analysis, including a 2 kb intronic deletion within the gene LRRN4. INTERPRETATION: We identified three SVs associated with genetic risk of PD. This study represents the most comprehensive assessment of the contribution of SVs to the genetic risk of PD to date. ANN NEUROL 2023;93:1012-1022.
Keywords: Genome, Human; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Whole Genome Sequencing

Genomic analysis of two phlebotomine sand fly vectors of Leishmania from the New and Old World. - Labbé, Frédéric; Abdeladhim, Maha; Abrudan, Jenica; Araki, Alejandra Saori; Araujo, Ricardo N; Arensburger, Peter; Benoit, Joshua B; Brazil, Reginaldo Pecanha; Bruno, Rafaela V; Bueno da Silva Rivas, Gustavo; Carvalho de Abreu, Vinicius; Charamis, Jason; et al. (PLoS Negl Trop Dis, 2023)
Phlebotomine sand flies are of global significance as important vectors of human disease, transmitting bacterial, viral, and protozoan pathogens, including the kinetoplastid parasites of the genus Leishmania, the causative agents of devastating diseases collectively termed leishmaniasis. More than 40 pathogenic Leishmania species are transmitted to humans by approximately 35 sand fly species in 98 countries with hundreds of millions of people at risk around the world. No approved efficacious vaccine exists for leishmaniasis and available therapeutic drugs are either toxic and/or expensive, or the parasites are becoming resistant to the more recently developed drugs. Therefore, sand fly and/or reservoir control are currently the most effective strategies to break transmission. To better understand the biology of sand flies, including the mechanisms involved in their vectorial capacity, insecticide resistance, and population structures we sequenced the genomes of two geographically widespread and important sand fly vector species: Phlebotomus papatasi, a vector of Leishmania parasites that cause cutaneous leishmaniasis, (distributed in Europe, the Middle East and North Africa) and Lutzomyia longipalpis, a vector of Leishmania parasites that cause visceral leishmaniasis (distributed across Central and South America). We categorized and curated genes involved in processes important to their roles as disease vectors, including chemosensation, blood feeding, circadian rhythm, immunity, and detoxification, as well as mobile genetic elements. We also defined gene orthology and observed micro-synteny among the genomes. Finally, we present the genetic diversity and population structure of these species in their respective geographical areas. These genomes will be a foundation on which to base future efforts to prevent vector-borne transmission of Leishmania parasites.
Keywords: Animals; Genomics; Humans; Leishmania; Leishmaniasis, Cutaneous; Phlebotomus; Psychodidae

The genomic landscape of familial glioma. - Choi, Dong-Joo; Armstrong, Georgina; Lozzi, Brittney; Vijayaraghavan, Prashanth; Plon, Sharon E; Wong, Terence C; Eric Boerwinkle; Donna M Muzny; Chen, Hsiao-Chi; Richard A Gibbs; Ostrom, Quinn T; Melin, Beatrice; et al. (Sci Adv, 2023)
Glioma is a rare brain tumor with a poor prognosis. Familial glioma is a subset of glioma with a strong genetic predisposition that accounts for approximately 5% of glioma cases. We performed whole-genome sequencing on an exploratory cohort of 203 individuals from 189 families with a history of familial glioma and an additional validation cohort of 122 individuals from 115 families. We found significant enrichment of rare deleterious variants of seven genes in both cohorts, and the most significantly enriched gene was ( = 0.0006). Furthermore, we identified rare noncoding variants in both cohorts that were predicted to affect transcription factor binding sites or cause cryptic splicing. Last, we selected a subset of discovered genes for validation by CRISPR knockdown screening and found that , have profound impacts on proliferation. This study performs comprehensive surveillance of the genomic landscape of familial glioma.
Keywords: Brain Neoplasms; Calcium-Binding Proteins; DNA-Binding Proteins; Genetic Predisposition to Disease; Genomics; Glioma; Humans; Tumor Suppressor Proteins; Whole Genome Sequencing

A global catalog of whole-genome diversity from 233 primate species. - Kuderna, Lukas F K; Gao, Hong; Janiak, Mareike C; Kuhlwilm, Martin; Orkin, Joseph D; Bataillon, Thomas; Manu, Shivakumara; Valenzuela, Alejandro; Bergman, Juraj; Rousselle, Marjolaine; Silva, Felipe Ennes; Agueda, Lidia; et al. (Science, 2023)
The rich diversity of morphology and behavior displayed across primate species provides an informative context in which to study the impact of genomic diversity on fundamental biological processes. Analysis of that diversity provides insight into long-standing questions in evolutionary and conservation biology and is urgent given severe threats these species are facing. Here, we present high-coverage whole-genome data from 233 primate species representing 86% of genera and all 16 families. This dataset was used, together with fossil calibration, to create a nuclear DNA phylogeny and to reassess evolutionary divergence times among primate clades. We found within-species genetic diversity across families and geographic regions to be associated with climate and sociality, but not with extinction risk. Furthermore, mutation rates differ across species, potentially influenced by effective population sizes. Lastly, we identified extensive recurrence of missense mutations previously thought to be human specific. This study will open a wide range of research avenues for future primate genomic research.
Keywords: Animals; Biological Evolution; Genetic Variation; Genome; Humans; Mutation Rate; Phylogeny; Population Density; Primates

Identification of allele-specific KIV-2 repeats and impact on Lp(a) measurements for cardiovascular disease risk. - Behera, S; Belyeu, J R; Chen, X; Paulin, L F; Nguyen, N Q H; Newman, E; Mahmoud, M; Menon, V K; Qi, Q; Joshi, P; Marcovina, S; Rossi, M; et al. (bioRxiv, 2023)
The abundance of Lp(a) protein holds significant implications for the risk of cardiovascular disease (CVD), which is directly impacted by the copy number (CN) of KIV-2, a 5.5 kbp sub-region. KIV-2 is highly polymorphic in the population and accurate analysis is challenging. In this study, we present the DRAGEN KIV-2 CN caller, which utilizes short reads. Data across 166 WGS show that the caller has high accuracy, compared to optical mapping and can further phase ~50% of the samples. We compared KIV-2 CN numbers to 24 previously postulated KIV-2 relevant SNVs, revealing that many are ineffective predictors of KIV-2 copy number. Population studies, including USA-based cohorts, showed distinct KIV-2 CN, distributions for European-, African-, and Hispanic-American populations and further underscored the limitations of SNV predictors. We demonstrate that the CN estimates correlate significantly with the available Lp(a) protein levels and that phasing is highly important.

Investigating Gene-Diet Interactions Impacting the Association Between Macronutrient Intake and Glycemic Traits. - Westerman, Kenneth E; Walker, Maura E; Gaynor, Sheila M; Wessel, Jennifer; DiCorpo, Daniel; Ma, Jiantao; Alonso, Alvaro; Aslibekyan, Stella; Baldridge, Abigail S; Bertoni, Alain G; Biggs, Mary L; Brody, Jennifer A; et al. (Diabetes, 2023)
UNLABELLED: Few studies have demonstrated reproducible gene-diet interactions (GDIs) impacting metabolic disease risk factors, likely due in part to measurement error in dietary intake estimation and insufficient capture of rare genetic variation. We aimed to identify GDIs across the genetic frequency spectrum impacting the macronutrient-glycemia relationship in genetically and culturally diverse cohorts. We analyzed 33,187 participants free of diabetes from 10 National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program cohorts with whole-genome sequencing, self-reported diet, and glycemic trait data. We fit cohort-specific, multivariable-adjusted linear mixed models for the effect of diet, modeled as an isocaloric substitution of carbohydrate for fat, and its interactions with common and rare variants genome-wide. In main effect meta-analyses, participants consuming more carbohydrate had modestly lower glycemic trait values (e.g., for glycated hemoglobin [HbA1c], -0.013% HbA1c/250 kcal substitution). In GDI meta-analyses, a common African ancestry-enriched variant (rs79762542) reached study-wide significance and replicated in the UK Biobank cohort, indicating a negative carbohydrate-HbA1c association among major allele homozygotes only. Simulations revealed that >150,000 samples may be necessary to identify similar macronutrient GDIs under realistic assumptions about effect size and measurement error. These results generate hypotheses for further exploration of modifiable metabolic disease risk in additional cohorts with African ancestry. ARTICLE HIGHLIGHTS: We aimed to identify genetic modifiers of the dietary macronutrient-glycemia relationship using whole-genome sequence data from 10 Trans-Omics for Precision Medicine program cohorts. Substitution models indicated a modest reduction in glycemia associated with an increase in dietary carbohydrate at the expense of fat. Genome-wide interaction analysis identified one African ancestry-enriched variant near the FRAS1 gene that may interact with macronutrient intake to influence hemoglobin A1c. Simulation-based power calculations accounting for measurement error suggested that substantially larger sample sizes may be necessary to discover further gene-macronutrient interactions.
Keywords: Diabetes Mellitus; Diet; Eating; Genome-Wide Association Study; Glycated Hemoglobin; Guanine Nucleotide Dissociation Inhibitors; Humans

The landscape of tolerated genetic variation in humans and primates. - Gao, Hong; Hamp, Tobias; Ede, Jeffrey; Schraiber, Joshua G; McRae, Jeremy; Singer-Berk, Moriel; Yang, Yanshen; Dietrich, Anastasia S D; Fiziev, Petko P; Kuderna, Lukas F K; Sundaram, Laksshman; Wu, Yibing; et al. (Science, 2023)
Personalized genome sequencing has revealed millions of genetic differences between individuals, but our understanding of their clinical relevance remains largely incomplete. To systematically decipher the effects of human genetic variants, we obtained whole-genome sequencing data for 809 individuals from 233 primate species and identified 4.3 million common protein-altering variants with orthologs in humans. We show that these variants can be inferred to have nondeleterious effects in humans based on their presence at high allele frequencies in other primate populations. We use this resource to classify 6% of all possible human protein-altering variants as likely benign and impute the pathogenicity of the remaining 94% of variants with deep learning, achieving state-of-the-art accuracy for diagnosing pathogenic variants in patients with genetic diseases.
Keywords: Animals; Base Sequence; Gene Frequency; Genetic Variation; Humans; Primates; Whole Genome Sequencing

The landscape of tolerated genetic variation in humans and primates. - Gao, Hong; Hamp, Tobias; Ede, Jeffrey; Schraiber, Joshua G; McRae, Jeremy; Singer-Berk, Moriel; Yang, Yanshen; Dietrich, Anastasia; Fiziev, Petko; Kuderna, Lukas; Sundaram, Laksshman; Wu, Yibing; et al. (bioRxiv, 2023)
UNLABELLED: Personalized genome sequencing has revealed millions of genetic differences between individuals, but our understanding of their clinical relevance remains largely incomplete. To systematically decipher the effects of human genetic variants, we obtained whole genome sequencing data for 809 individuals from 233 primate species, and identified 4.3 million common protein-altering variants with orthologs in human. We show that these variants can be inferred to have non-deleterious effects in human based on their presence at high allele frequencies in other primate populations. We use this resource to classify 6% of all possible human protein-altering variants as likely benign and impute the pathogenicity of the remaining 94% of variants with deep learning, achieving state-of-the-art accuracy for diagnosing pathogenic variants in patients with genetic diseases. ONE SENTENCE SUMMARY: Deep learning classifier trained on 4.3 million common primate missense variants predicts variant pathogenicity in humans.

Longitudinal host transcriptional responses to SARS-CoV-2 infection in adults with extremely high viral load. - Avadhanula, Vasanthi; Creighton, Chad J; Ferlic-Stark, Laura; Sucgang, Richard; Zhang, Yiqun; Nagaraj, Divya; Nicholson, Erin G; Rajan, Anubama; Menon, Vipin Kumar; Harshavardhan Doddapaneni; Donna M Muzny; Ginger A Metcalf; et al. (bioRxiv, 2023)
Current understanding of viral dynamics of SARS-CoV-2 and host responses driving the pathogenic mechanisms in COVID-19 is rapidly evolving. Here, we conducted a longitudinal study to investigate gene expression patterns during acute SARS-CoV-2 illness. Cases included SARS-CoV-2 infected individuals with extremely high viral loads early in their illness, individuals having low SARS-CoV-2 viral loads early in their infection, and individuals testing negative for SARS-CoV-2. We could identify widespread transcriptional host responses to SARS-CoV-2 infection that were initially most strongly manifested in patients with extremely high initial viral loads, then attenuating within the patient over time as viral loads decreased. Genes correlated with SARS-CoV-2 viral load over time were similarly differentially expressed across independent datasets of SARS-CoV-2 infected lung and upper airway cells, from both in vitro systems and patient samples. We also generated expression data on the human nose organoid model during SARS-CoV-2 infection. The human nose organoid-generated host transcriptional response captured many aspects of responses observed in the above patient samples, while suggesting the existence of distinct host responses to SARS-CoV-2 depending on the cellular context, involving both epithelial and cellular immune responses. Our findings provide a catalog of SARS-CoV-2 host response genes changing over time.

Mental health trends among medical students. - Nair, Muktha; Moss, Nathaniel; Bashir, Amna; Garate, David; Thomas, Devon; Fu, Shangyi; Phu, Daniel; Pham, Christine (Proc (Bayl Univ Med Cent), 2023)
Student mental health concerns can manifest in several forms. Medical students juggling a multitude of trials (i.e., intense academic rigor, financial debt, sleep deprivation, lack of control, continual exposure to sickness and death, and training mistreatment) can help explain the higher prevalence of psychological disorders within this population. Furthermore, these mental health difficulties are not static; certain challenges move into the forefront as students face key transition points in schooling. Primary examples include the entry year of medical school, the shift from preclinical curriculum to clinical training, and the final moments prior to beginning residency. Given the existing mental health trends among medical students at baseline, it can be concluded that the COVID-19 pandemic has exacerbated the stress, anxiety, and depression associated with medical education. Solutions do indeed exist to address the moral injury medical students face, from expanded crisis management training and implementation of peer support networks to destigmatization of and improved access to professional mental health resources. It is up to the curators of the medical education system to make these solutions the new status quo.

Monoallelic variation in DHX9, the gene encoding the DExH-box helicase DHX9, underlies neurodevelopment disorders and Charcot-Marie-Tooth disease. - Calame, Daniel G; Guo, Tianyu; Wang, Chen; Garrett, Lillian; Jolly, Angad; Dawood, Moez; Kurolap, Alina; Henig, Noa Zunz; Fatih, Jawid M; Herman, Isabella; Du, Haowei; Mitani, Tadahiro; et al. (Am J Hum Genet, 2023)
DExD/H-box RNA helicases (DDX/DHX) are encoded by a large paralogous gene family; in a subset of these human helicase genes, pathogenic variation causes neurodevelopmental disorder (NDD) traits and cancer. DHX9 encodes a BRCA1-interacting nuclear helicase regulating transcription, R-loops, and homologous recombination and exhibits the highest mutational constraint of all DDX/DHX paralogs but remains unassociated with disease traits in OMIM. Using exome sequencing and family-based rare-variant analyses, we identified 20 individuals with de novo, ultra-rare, heterozygous missense or loss-of-function (LoF) DHX9 variant alleles. Phenotypes ranged from NDDs to the distal symmetric polyneuropathy axonal Charcot-Marie-Tooth disease (CMT2). Quantitative Human Phenotype Ontology (HPO) analysis demonstrated genotype-phenotype correlations with LoF variants causing mild NDD phenotypes and nuclear localization signal (NLS) missense variants causing severe NDD. We investigated DHX9 variant-associated cellular phenotypes in human cell lines. Whereas wild-type DHX9 was restricted to the nucleus, NLS missense variants abnormally accumulated in the cytoplasm. Fibroblasts from an individual with an NLS variant also showed abnormal cytoplasmic DHX9 accumulation. CMT2-associated missense variants caused aberrant nucleolar DHX9 accumulation, a phenomenon previously associated with cellular stress. Two NDD-associated variants, p.Gly411Glu and p.Arg761Gln, altered DHX9 ATPase activity. The severe NDD-associated variant p.Arg141Gln did not affect DHX9 localization but instead increased R-loop levels and double-stranded DNA breaks. Dhx9 mice exhibited hypoactivity in novel environments, tremor, and sensorineural hearing loss. All together, these results establish DHX9 as a critical regulator of mammalian neurodevelopment and neuronal homeostasis.
Keywords: Animals; Cell Line; Charcot-Marie-Tooth Disease; DEAD-box RNA Helicases; Dichlorodiphenyl Dichloroethylene; DNA Helicases; Humans; Mammals; Mice; Neoplasm Proteins; Neurodevelopmental Disorders

Powerful, scalable and resource-efficient meta-analysis of rare variant associations in large whole genome sequencing studies. - Li, Xihao; Quick, Corbin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Selvaraj, Margaret Sunitha; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Bielak, Lawrence F; Bis, Joshua C; et al. (Nat Genet, 2023)
Meta-analysis of whole genome sequencing/whole exome sequencing (WGS/WES) studies provides an attractive solution to the problem of collecting large sample sizes for discovering rare variants associated with complex phenotypes. Existing rare variant meta-analysis approaches are not scalable to biobank-scale WGS data. Here we present MetaSTAAR, a powerful and resource-efficient rare variant meta-analysis framework for large-scale WGS/WES studies. MetaSTAAR accounts for relatedness and population structure, can analyze both quantitative and dichotomous traits and boosts the power of rare variant tests by incorporating multiple variant functional annotations. Through meta-analysis of four lipid traits in 30,138 ancestrally diverse samples from 14 studies of the Trans Omics for Precision Medicine (TOPMed) Program, we show that MetaSTAAR performs rare variant meta-analysis at scale and produces results comparable to using pooled data. Additionally, we identified several conditionally significant rare variant associations with lipid traits. We further demonstrate that MetaSTAAR is scalable to biobank-scale cohorts through meta-analysis of TOPMed WGS data and UK Biobank WES data of ~200,000 samples.
Keywords: Exome Sequencing; Genome-Wide Association Study; Lipids; Phenotype; Whole Genome Sequencing

Proteomics analysis of plasma from middle-aged adults identifies protein markers of dementia risk in later life. - Walker, Keenan A; Chen, Jingsha; Shi, Liu; Yang, Yunju; Fornage, Myriam; Zhou, Linda; Schlosser, Pascal; Surapaneni, Aditya; Grams, Morgan E; Duggan, Michael R; Peng, Zhongsheng; Gomez, Gabriela T; et al. (Sci Transl Med, 2023)
A diverse set of biological processes have been implicated in the pathophysiology of Alzheimer's disease (AD) and related dementias. However, there is limited understanding of the peripheral biological mechanisms relevant in the earliest phases of the disease. Here, we used a large-scale proteomics platform to examine the association of 4877 plasma proteins with 25-year dementia risk in 10,981 middle-aged adults. We found 32 dementia-associated plasma proteins that were involved in proteostasis, immunity, synaptic function, and extracellular matrix organization. We then replicated the association between 15 of these proteins and clinically relevant neurocognitive outcomes in two independent cohorts. We demonstrated that 12 of these 32 dementia-associated proteins were associated with cerebrospinal fluid (CSF) biomarkers of AD, neurodegeneration, or neuroinflammation. We found that eight of these candidate protein markers were abnormally expressed in human postmortem brain tissue from patients with AD, although some of the proteins that were most strongly associated with dementia risk, such as GDF15, were not detected in these brain tissue samples. Using network analyses, we found a protein signature for dementia risk that was characterized by dysregulation of specific immune and proteostasis/autophagy pathways in adults in midlife ~20 years before dementia onset, as well as abnormal coagulation and complement signaling ~10 years before dementia onset. Bidirectional two-sample Mendelian randomization genetically validated nine of our candidate proteins as markers of AD in midlife and inferred causality of SERPINA3 in AD pathogenesis. Last, we prioritized a set of candidate markers for AD and dementia risk prediction in midlife.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Humans; Middle Aged; Proteomics; tau Proteins

Rare Genetic Variants Associated With Sudden Cardiac Arrest in the Young: A Prospective, Population-Based Study. - Holmstrom, Lauri; Chaudhary, Ninad S; Nakamura, Kotoka; Chugh, Harpriya; Uy-Evanado, Audrey; Norby, Faye; Ginger A Metcalf; Menon, Vipin K; Yu, Bing; Eric Boerwinkle; Chugh, Sumeet S; Akdemir, Zeynep; et al. (Circ Genom Precis Med, 2023)
Keywords: Death, Sudden, Cardiac; Heart Arrest; Humans; Prospective Studies

Rare penetrant mutations confer severe risk of common diseases. - Fiziev, Petko P; McRae, Jeremy; Ulirsch, Jacob C; Dron, Jacqueline S; Hamp, Tobias; Yang, Yanshen; Wainschtein, Pierrick; Ni, Zijian; Schraiber, Joshua G; Gao, Hong; Cable, Dylan; Field, Yair; et al. (Science, 2023)
We examined 454,712 exomes for genes associated with a wide spectrum of complex traits and common diseases and observed that rare, penetrant mutations in genes implicated by genome-wide association studies confer ~10-fold larger effects than common variants in the same genes. Consequently, an individual at the phenotypic extreme and at the greatest risk for severe, early-onset disease is better identified by a few rare penetrant variants than by the collective action of many common variants with weak effects. By combining rare variants across phenotype-associated genes into a unified genetic risk model, we demonstrate superior portability across diverse global populations compared with common-variant polygenic risk scores, greatly improving the clinical utility of genetic-based risk prediction.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Multifactorial Inheritance; Mutation; Penetrance; Phenotype; Risk Factors

Rare penetrant mutations confer severe risk of common diseases. - Fiziev, Petko; McRae, Jeremy; Ulirsch, Jacob C; Dron, Jacqueline S; Hamp, Tobias; Yang, Yanshen; Wainschtein, Pierrick; Ni, Zijian; Schraiber, Joshua G; Gao, Hong; Cable, Dylan; Field, Yair; et al. (medRxiv, 2023)
UNLABELLED: We examined 454,712 exomes for genes associated with a wide spectrum of complex traits and common diseases and observed that rare, penetrant mutations in genes implicated by genome-wide association studies confer ∼10-fold larger effects than common variants in the same genes. Consequently, an individual at the phenotypic extreme and at the greatest risk for severe, early-onset disease is better identified by a few rare penetrant variants than by the collective action of many common variants with weak effects. By combining rare variants across phenotype-associated genes into a unified genetic risk model, we demonstrate superior portability across diverse global populations compared to common variant polygenic risk scores, greatly improving the clinical utility of genetic-based risk prediction. ONE SENTENCE SUMMARY: Rare variant polygenic risk scores identify individuals with outlier phenotypes in common human diseases and complex traits.

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed whole-genome sequencing study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (Am J Hum Genet, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions in lipid metabolism. Large-scale whole-genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess more associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with measurement of blood lipids and lipoproteins (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare-variant aggregate association tests using the STAAR (variant-set test for association using annotation information) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare-coding variants in nearby protein-coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500-kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variation and rare protein-coding variation at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNAs.
Keywords: Genome-Wide Association Study; Humans; Lipids; Polymorphism, Single Nucleotide; Precision Medicine; RNA, Long Noncoding; Whole Genome Sequencing

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

Scalable Nanopore sequencing of human genomes provides a comprehensive view of haplotype-resolved variation and methylation. - Kolmogorov, Mikhail; Billingsley, Kimberley J; Mastoras, Mira; Meredith, Melissa; Monlong, Jean; Lorig-Roach, Ryan; Asri, Mobin; Jerez, Pilar Alvarez; Malik, Laksh; Dewan, Ramita; Reed, Xylena; Genner, Rylee M; et al. (bioRxiv, 2023)
Long-read sequencing technologies substantially overcome the limitations of short-reads but to date have not been considered as feasible replacement at scale due to a combination of being too expensive, not scalable enough, or too error-prone. Here, we develop an efficient and scalable wet lab and computational protocol for Oxford Nanopore Technologies (ONT) long-read sequencing that seeks to provide a genuine alternative to short-reads for large-scale genomics projects. We applied our protocol to cell lines and brain tissue samples as part of a pilot project for the NIH Center for Alzheimer's and Related Dementias (CARD). Using a single PromethION flow cell, we can detect SNPs with F1-score better than Illumina short-read sequencing. Small indel calling remains to be difficult inside homopolymers and tandem repeats, but is comparable to Illumina calls elsewhere. Further, we can discover structural variants with F1-score comparable to state-of the-art methods involving Pacific Biosciences HiFi sequencing and trio information (but at a lower cost and greater throughput). Using ONT based phasing, we can then combine and phase small and structural variants at megabase scales. Our protocol also produces highly accurate, haplotype-specific methylation calls. Overall, this makes large-scale long-read sequencing projects feasible; the protocol is currently being used to sequence thousands of brain-based genomes as a part of the NIH CARD initiative. We provide the protocol and software as open-source integrated pipelines for generating phased variant calls and assemblies.

Single-nucleotide variant calling in single-cell sequencing data with Monopogen. - Dou, Jinzhuang; Tan, Yukun; Kock, Kian Hong; Wang, Jun; Cheng, Xuesen; Tan, Le Min; Han, Kyung Yeon; Hon, Chung-Chau; Park, Woong-Yang; Shin, Jay W; Jin, Haijing; Wang, Yujia; et al. (Nat Biotechnol, 2023)
Single-cell omics technologies enable molecular characterization of diverse cell types and states, but how the resulting transcriptional and epigenetic profiles depend on the cell's genetic background remains understudied. We describe Monopogen, a computational tool to detect single-nucleotide variants (SNVs) from single-cell sequencing data. Monopogen leverages linkage disequilibrium from external reference panels to identify germline SNVs and detects putative somatic SNVs using allele cosegregating patterns at the cell population level. It can identify 100 K to 3 M germline SNVs achieving a genotyping accuracy of 95%, together with hundreds of putative somatic SNVs. Monopogen-derived genotypes enable global and local ancestry inference and identification of admixed samples. It identifies variants associated with cardiomyocyte metabolic levels and epigenomic programs. It also improves putative somatic SNV detection that enables clonal lineage tracing in primary human clonal hematopoiesis. Monopogen brings together population genetics, cell lineage tracing and single-cell omics to uncover genetic determinants of cellular processes.

SRSF1 haploinsufficiency is responsible for a syndromic developmental disorder associated with intellectual disability. - Bogaert, Elke; Garde, Aurore; Gautier, Thierry; Rooney, Kathleen; Duffourd, Yannis; LeBlanc, Pontus; van Reempts, Emma; Tran Mau-Them, Frederic; Wentzensen, Ingrid M; Au, Kit Sing; Richardson, Kate; Northrup, Hope; et al. (Am J Hum Genet, 2023)
SRSF1 (also known as ASF/SF2) is a non-small nuclear ribonucleoprotein (non-snRNP) that belongs to the arginine/serine (R/S) domain family. It recognizes and binds to mRNA, regulating both constitutive and alternative splicing. The complete loss of this proto-oncogene in mice is embryonically lethal. Through international data sharing, we identified 17 individuals (10 females and 7 males) with a neurodevelopmental disorder (NDD) with heterozygous germline SRSF1 variants, mostly de novo, including three frameshift variants, three nonsense variants, seven missense variants, and two microdeletions within region 17q22 encompassing SRSF1. Only in one family, the de novo origin could not be established. All individuals featured a recurrent phenotype including developmental delay and intellectual disability (DD/ID), hypotonia, neurobehavioral problems, with variable skeletal (66.7%) and cardiac (46%) anomalies. To investigate the functional consequences of SRSF1 variants, we performed in silico structural modeling, developed an in vivo splicing assay in Drosophila, and carried out episignature analysis in blood-derived DNA from affected individuals. We found that all loss-of-function and 5 out of 7 missense variants were pathogenic, leading to a loss of SRSF1 splicing activity in Drosophila, correlating with a detectable and specific DNA methylation episignature. In addition, our orthogonal in silico, in vivo, and epigenetics analyses enabled the separation of clearly pathogenic missense variants from those with uncertain significance. Overall, these results indicated that haploinsufficiency of SRSF1 is responsible for a syndromic NDD with ID due to a partial loss of SRSF1-mediated splicing activity.
Keywords: Child; Developmental Disabilities; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Mutation, Missense; Neurodevelopmental Disorders; Phenotype

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Arnett, Donna K; Bis, Joshua C; Blangero, John; et al. (bioRxiv, 2023)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally-scalable analytical pipeline for functionally-informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides) in 61,861 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered new associations with lipid traits missed by single-trait analysis, including rare variants within an enhancer of and an intergenic region on chromosome 1.

Telehealth reform post-public health emergency: crucial next steps. - Thomas, Devon; Garate, David; Fu, Shangyi; Bashir, Amna; Moss, Nathaniel; Nair, Muktha (Proc (Bayl Univ Med Cent), 2023)
As the pandemic made it unsafe for providers and patients to meet in person, the US government implemented key temporary telehealth waivers in March 2020 that expanded Medicare telehealth coverage dramatically. Some of the most significant changes included the removal of location restrictions so that patients and providers could engage in telehealth from their homes, full provider reimbursement for telehealth visits, coverage for more medical specialties and types of practitioners such as occupational and physical therapists, and the allowance of telehealth prescription of controlled substances. The waivers will end when the government removes the federal status of a public health emergency, which is expected to occur in 2023. Nearly 64 million Medicare patients are at risk of losing most modalities of telehealth access. We present current legislation that could combat this "telehealth cliff" and defend the position that Medicare telehealth access should remain permanently expanded.

Type 2 Diabetes Modifies the Association of CAD Genomic Risk Variants With Subclinical Atherosclerosis. - Hasbani, Natalie R; Westerman, Kenneth E; Kwak, Soo Heon; Chen, Han; Li, Xihao; Di Corpo, Daniel; Wessel, Jennifer; Bis, Joshua C; Sarnowski, Chloe; Wu, Peitao; Bielak, Lawrence F; Guo, Xiuqing; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of coronary artery disease (CAD), but questions remain about the underlying pathology. Identifying which CAD loci are modified by T2D in the development of subclinical atherosclerosis (coronary artery calcification [CAC], carotid intima-media thickness, or carotid plaque) may improve our understanding of the mechanisms leading to the increased CAD in T2D. METHODS: We compared the common and rare variant associations of known CAD loci from the literature on CAC, carotid intima-media thickness, and carotid plaque in up to 29 670 participants, including up to 24 157 normoglycemic controls and 5513 T2D cases leveraging whole-genome sequencing data from the Trans-Omics for Precision Medicine program. We included first-order T2D interaction terms in each model to determine whether CAD loci were modified by T2D. The genetic main and interaction effects were assessed using a joint test to determine whether a CAD variant, or gene-based rare variant set, was associated with the respective subclinical atherosclerosis measures and then further determined whether these loci had a significant interaction test. RESULTS: Using a Bonferroni-corrected significance threshold of <1.6×10, we identified 3 genes (, , and ) associated with CAC and 2 genes ( and ) associated with carotid intima-media thickness and carotid plaque, respectively, through gene-based rare variant set analysis. Both and also had significantly different associations for CAC in T2D cases versus controls. No significant interaction tests were identified through the candidate single-variant analysis. CONCLUSIONS: These results highlight T2D as an important modifier of rare variant associations in CAD loci with CAC.
Keywords: Atherosclerosis; Carotid Intima-Media Thickness; Coronary Artery Disease; Diabetes Mellitus, Type 2; Genomics; Humans; Plaque, Atherosclerotic; Risk Factors

Whole Genome Sequencing Based Analysis of Inflammation Biomarkers in the Trans-Omics for Precision Medicine (TOPMed) Consortium. - Jiang, Min-Zhi; Gaynor, Sheila M; Li, Xihao; Van Buren, Eric; Stilp, Adrienne; Buth, Erin; Wang, Fei Fei; Manansala, Regina; Gogarten, Stephanie M; Li, Zilin; Polfus, Linda M; Salimi, Shabnam; et al. (bioRxiv, 2023)
Inflammation biomarkers can provide valuable insight into the role of inflammatory processes in many diseases and conditions. Sequencing based analyses of such biomarkers can also serve as an exemplar of the genetic architecture of quantitative traits. To evaluate the biological insight, which can be provided by a multi-ancestry, whole-genome based association study, we performed a comprehensive analysis of 21 inflammation biomarkers from up to 38,465 individuals with whole-genome sequencing from the Trans-Omics for Precision Medicine (TOPMed) program. We identified 22 distinct single-variant associations across 6 traits - E-selectin, intercellular adhesion molecule 1, interleukin-6, lipoprotein-associated phospholipase A2 activity and mass, and P-selectin - that remained significant after conditioning on previously identified associations for these inflammatory biomarkers. We further expanded upon known biomarker associations by pairing the single-variant analysis with a rare variant set-based analysis that further identified 19 significant rare variant set-based associations with 5 traits. These signals were distinct from both significant single variant association signals within TOPMed and genetic signals observed in prior studies, demonstrating the complementary value of performing both single and rare variant analyses when analyzing quantitative traits. We also confirm several previously reported signals from semi-quantitative proteomics platforms. Many of these signals demonstrate the extensive allelic heterogeneity and ancestry-differentiated variant-trait associations common for inflammation biomarkers, a characteristic we hypothesize will be increasingly observed with well-powered, large-scale analyses of complex traits.

Whole-exome sequencing study identifies four novel gene loci associated with diabetic kidney disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Ginger A Metcalf; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2023)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease and diabetes. Our two-stage WES study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort and Atherosclerosis Risk in Communities studies (stage 1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine participants (stage 2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single-variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds [95% confidence interval (CI): 33.6, 1105] of DKD compared with noncarriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% CI: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.
Keywords: Aminopeptidases; Diabetes Mellitus; Diabetic Nephropathies; Exome Sequencing; Humans; Kidney; Renal Insufficiency, Chronic

Accounting for population structure in genetic studies of cystic fibrosis. - Kingston, Hanley; Stilp, Adrienne M; Gordon, William; Broome, Jai; Gogarten, Stephanie M; Ling, Hua; Barnard, John; Dugan-Perez, Shannon; Ellinor, Patrick T; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; et al. (HGG Adv, 2022)
F508del (c.1521_1523delCTT, p.Phe508delPhe) is the most common pathogenic allele underlying cystic fibrosis (CF), and its frequency varies in a geographic cline across Europe. We hypothesized that genetic variation associated with this cline is overrepresented in a large cohort (N > 5,000) of persons with CF who underwent whole-genome sequencing and that this pattern could result in spurious associations between variants correlated with both the F508del genotype and CF-related outcomes. Using principal-component (PC) analyses, we showed that variation in the region disproportionately contributes to a PC explaining a relatively high proportion of genetic variance. Variation near was correlated with population structure among persons with CF, and this correlation was driven by a subset of the sample inferred to have European ancestry. We performed genome-wide association studies comparing persons with CF with one versus two copies of the F508del allele; this allowed us to identify genetic variation associated with the F508del allele and to determine that standard PC-adjustment strategies eliminated the significant association signals. Our results suggest that PC adjustment can adequately prevent spurious associations between genetic variants and CF-related traits and are therefore effective tools to control for population structure even when population structure is confounded with disease severity and a common pathogenic variant.

Assessing reproducibility of inherited variants detected with short-read whole genome sequencing. - Pan, Bohu; Ren, Luyao; Onuchic, Vitor; Guan, Meijian; Kusko, Rebecca; Bruinsma, Steve; Trigg, Len; Scherer, Andreas; Ning, Baitang; Zhang, Chaoyang; Glidewell-Kenney, Christine; Xiao, Chunlin; et al. (Genome Biol, 2022)
BACKGROUND: Reproducible detection of inherited variants with whole genome sequencing (WGS) is vital for the implementation of precision medicine and is a complicated process in which each step affects variant call quality. Systematically assessing reproducibility of inherited variants with WGS and impact of each step in the process is needed for understanding and improving quality of inherited variants from WGS. RESULTS: To dissect the impact of factors involved in detection of inherited variants with WGS, we sequence triplicates of eight DNA samples representing two populations on three short-read sequencing platforms using three library kits in six labs and call variants with 56 combinations of aligners and callers. We find that bioinformatics pipelines (callers and aligners) have a larger impact on variant reproducibility than WGS platform or library preparation. Single-nucleotide variants (SNVs), particularly outside difficult-to-map regions, are more reproducible than small insertions and deletions (indels), which are least reproducible when > 5 bp. Increasing sequencing coverage improves indel reproducibility but has limited impact on SNVs above 30×. CONCLUSIONS: Our findings highlight sources of variability in variant detection and the need for improvement of bioinformatics pipelines in the era of precision medicine with WGS.
Keywords: Genome, Human; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Polymorphism, Single Nucleotide; Reproducibility of Results; Whole Genome Sequencing

Assessing the contribution of rare genetic variants to phenotypes of chronic obstructive pulmonary disease using whole-genome sequence data. - Kim, Wonji; Hecker, Julian; Barr, R Graham; Eric Boerwinkle; Cade, Brian; Correa, Adolfo; Dupuis, Josée; Gharib, Sina A; Lange, Leslie; London, Stephanie J; Morrison, Alanna C; O'Connor, George T; et al. (Hum Mol Genet, 2022)
RATIONALE: Genetic variation has a substantial contribution to chronic obstructive pulmonary disease (COPD) and lung function measurements. Heritability estimates using genome-wide genotyping data can be biased if analyses do not appropriately account for the nonuniform distribution of genetic effects across the allele frequency and linkage disequilibrium (LD) spectrum. In addition, the contribution of rare variants has been unclear. OBJECTIVES: We sought to assess the heritability of COPD and lung function using whole-genome sequence data from the Trans-Omics for Precision Medicine program. METHODS: Using the genome-based restricted maximum likelihood method, we partitioned the genome into bins based on minor allele frequency and LD scores and estimated heritability of COPD, FEV1% predicted and FEV1/FVC ratio in 11 051 European ancestry and 5853 African-American participants. MEASUREMENTS AND MAIN RESULTS: In European ancestry participants, the estimated heritability of COPD, FEV1% predicted and FEV1/FVC ratio were 35.5%, 55.6% and 32.5%, of which 18.8%, 19.7%, 17.8% were from common variants, and 16.6%, 35.8%, and 14.6% were from rare variants. These estimates had wide confidence intervals, with common variants and some sets of rare variants showing a statistically significant contribution (P-value < 0.05). In African-Americans, common variant heritability was similar to European ancestry participants, but lower sample size precluded calculation of rare variant heritability. CONCLUSIONS: Our study provides updated and unbiased estimates of heritability for COPD and lung function, and suggests an important contribution of rare variants. Larger studies of more diverse ancestry will improve accuracy of these estimates.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Author Correction: Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Kim C Worley; Nazareth, Lynne V; Donna M Muzny; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2022)

Author Correction: High-coverage whole-genome analysis of 1220 cancers reveals hundreds of genes deregulated by rearrangement-mediated cis-regulatory alterations. - Zhang, Yiqun; Chen, Fengju; Fonseca, Nuno A; He, Yao; Fujita, Masashi; Nakagawa, Hidewaki; Zhang, Zemin; Brazma, Alvis; Creighton, Chad J (Nat Commun, 2022)

Benchmarking challenging small variants with linked and long reads. - Wagner, Justin; Olson, Nathan D; Harris, Lindsay; Ziad Khan; Farek, Jesse; Mahmoud, Medhat; Stankovic, Ana; Kovacevic, Vladimir; Yoo, Byunggil; Miller, Neil; Rosenfeld, Jeffrey A; Ni, Bohan; et al. (Cell Genom, 2022)
Genome in a Bottle benchmarks are widely used to help validate clinical sequencing pipelines and develop variant calling and sequencing methods. Here we use accurate linked and long reads to expand benchmarks in 7 samples to include difficult-to-map regions and segmental duplications that are challenging for short reads. These benchmarks add more than 300,000 SNVs and 50,000 insertions or deletions (indels) and include 16% more exonic variants, many in challenging, clinically relevant genes not covered previously, such as . For HG002, we include 92% of the autosomal GRCh38 assembly while excluding regions problematic for benchmarking small variants, such as copy number variants, that should not have been in the previous version, which included 85% of GRCh38. It identifies eight times more false negatives in a short read variant call set relative to our previous benchmark. We demonstrate that this benchmark reliably identifies false positives and false negatives across technologies, enabling ongoing methods development.

Bi-allelic CAMSAP1 variants cause a clinically recognizable neuronal migration disorder. - Khalaf-Nazzal, Reham; Fasham, James; Inskeep, Katherine A; Blizzard, Lauren E; Leslie, Joseph S; Wakeling, Matthew N; Ubeyratna, Nishanka; Mitani, Tadahiro; Griffith, Jennifer L; Baker, Wisam; Al-Hijawi, Fida'; Keough, Karen C; et al. (Am J Hum Genet, 2022)
Non-centrosomal microtubules are essential cytoskeletal filaments that are important for neurite formation, axonal transport, and neuronal migration. They require stabilization by microtubule minus-end-targeting proteins including the CAMSAP family of molecules. Using exome sequencing on samples from five unrelated families, we show that bi-allelic CAMSAP1 loss-of-function variants cause a clinically recognizable, syndromic neuronal migration disorder. The cardinal clinical features of the syndrome include a characteristic craniofacial appearance, primary microcephaly, severe neurodevelopmental delay, cortical visual impairment, and seizures. The neuroradiological phenotype comprises a highly recognizable combination of classic lissencephaly with a posterior more severe than anterior gradient similar to PAFAH1B1(LIS1)-related lissencephaly and severe hypoplasia or absence of the corpus callosum; dysplasia of the basal ganglia, hippocampus, and midbrain; and cerebellar hypodysplasia, similar to the tubulinopathies, a group of monogenic tubulin-associated disorders of cortical dysgenesis. Neural cell rosette lineages derived from affected individuals displayed findings consistent with these phenotypes, including abnormal morphology, decreased cell proliferation, and neuronal differentiation. Camsap1-null mice displayed increased perinatal mortality, and RNAScope studies identified high expression levels in the brain throughout neurogenesis and in facial structures, consistent with the mouse and human neurodevelopmental and craniofacial phenotypes. Together our findings confirm a fundamental role of CAMSAP1 in neuronal migration and brain development and define bi-allelic variants as a cause of a clinically distinct neurodevelopmental disorder in humans and mice.
Keywords: Alleles; Animals; Classical Lissencephalies and Subcortical Band Heterotopias; Humans; Lissencephaly; Mice; Mice, Knockout; Microtubule-Associated Proteins; Nervous System Malformations; Phenotype; Tubulin

Biallelic Variants in the Ectonucleotidase ENTPD1 Cause a Complex Neurodevelopmental Disorder with Intellectual Disability, Distinct White Matter Abnormalities, and Spastic Paraplegia. - Calame, Daniel G; Herman, Isabella; Maroofian, Reza; Marshall, Aren E; Donis, Karina Carvalho; Fatih, Jawid M; Mitani, Tadahiro; Du, Haowei; Grochowski, Christopher M; Sousa, Sergio B; Gijavanekar, Charul; Bakhtiari, Somayeh; et al. (Ann Neurol, 2022)
OBJECTIVE: Human genomics established that pathogenic variation in diverse genes can underlie a single disorder. For example, hereditary spastic paraplegia is associated with >80 genes, with frequently only few affected individuals described for each gene. Herein, we characterize a large cohort of individuals with biallelic variation in ENTPD1, a gene previously linked to spastic paraplegia 64 (Mendelian Inheritance in Man # 615683). METHODS: Individuals with biallelic ENTPD1 variants were recruited worldwide. Deep phenotyping and molecular characterization were performed. RESULTS: A total of 27 individuals from 17 unrelated families were studied; additional phenotypic information was collected from published cases. Twelve novel pathogenic ENTPD1 variants are described (NM 001776.6): c.398_399delinsAA; p.(Gly133Glu), c.540del; p.(Thr181Leufs*18), c.640del; p.(Gly216Glufs*75), c.185 T > G; p.(Leu62*), c.1531 T > C; p.(*511Glnext*100), c.967C > T; p.(Gln323*), c.414-2_414-1del, and c.146 A > G; p.(Tyr49Cys) including 4 recurrent variants c.1109 T > A; p.(Leu370*), c.574-6_574-3del, c.770_771del; p.(Gly257Glufs*18), and c.1041del; p.(Ile348Phefs*19). Shared disease traits include childhood onset, progressive spastic paraplegia, intellectual disability (ID), dysarthria, and white matter abnormalities. In vitro assays demonstrate that ENTPD1 expression and function are impaired and that c.574-6_574-3del causes exon skipping. Global metabolomics demonstrate ENTPD1 deficiency leads to impaired nucleotide, lipid, and energy metabolism. INTERPRETATION: The ENTPD1 locus trait consists of childhood disease onset, ID, progressive spastic paraparesis, dysarthria, dysmorphisms, and white matter abnormalities, with some individuals showing neurocognitive regression. Investigation of an allelic series of ENTPD1 (1) expands previously described features of ENTPD1-related neurological disease, (2) highlights the importance of genotype-driven deep phenotyping, (3) documents the need for global collaborative efforts to characterize rare autosomal recessive disease traits, and (4) provides insights into disease trait neurobiology. ANN NEUROL 2022;92:304-321.
Keywords: Apyrase; Dysarthria; Humans; Intellectual Disability; Mutation; Paraplegia; Pedigree; Phenotype; Spastic Paraplegia, Hereditary; White Matter

Centers for Mendelian Genomics: A decade of facilitating gene discovery. - Baxter, Samantha M; Posey, Jennifer E; Lake, Nicole J; Sobreira, Nara; Chong, Jessica X; Buyske, Steven; Blue, Elizabeth E; Chadwick, Lisa H; Coban-Akdemir, Zeynep H; Doheny, Kimberly F; Davis, Colleen P; Lek, Monkol; et al. (Genet Med, 2022)
PURPOSE: Mendelian disease genomic research has undergone a massive transformation over the past decade. With increasing availability of exome and genome sequencing, the role of Mendelian research has expanded beyond data collection, sequencing, and analysis to worldwide data sharing and collaboration. METHODS: Over the past 10 years, the National Institutes of Health-supported Centers for Mendelian Genomics (CMGs) have played a major role in this research and clinical evolution. RESULTS: We highlight the cumulative gene discoveries facilitated by the program, biomedical research leveraged by the approach, and the larger impact on the research community. Beyond generating a list of gene-phenotype relationships and participating in widespread data sharing, the CMGs have created resources, tools, and training for the larger community to foster understanding of genes and genome variation. The CMGs have participated in a wide range of data sharing activities, including deposition of all eligible CMG data into the Analysis, Visualization, and Informatics Lab-space (AnVIL), sharing candidate genes through the Matchmaker Exchange and the CMG website, and sharing variants in Genotypes to Mendelian Phenotypes (Geno2MP) and VariantMatcher. CONCLUSION: The work is far from complete; strengthening communication between research and clinical realms, continued development and sharing of knowledge and tools, and improving access to richly characterized data sets are all required to diagnose the remaining molecularly undiagnosed patients.
Keywords: Exome; Exome Sequencing; Genetic Association Studies; Genomics; Humans; Phenotype

Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease. - Uddin, M D Mesbah; Nguyen, Ngoc Quynh H; Yu, Bing; Brody, Jennifer A; Pampana, Akhil; Nakao, Tetsushi; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; Weinstock, Joshua S; Honigberg, Michael C; Nachun, Daniel; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.
Keywords: Clonal Hematopoiesis; Coronary Artery Disease; DNA Methylation; Hematopoiesis; Hematopoietic Stem Cells; Humans

The complete sequence of a human genome. - Nurk, Sergey; Koren, Sergey; Rhie, Arang; Rautiainen, Mikko; Bzikadze, Andrey V; Mikheenko, Alla; Vollger, Mitchell R; Altemose, Nicolas; Uralsky, Lev; Gershman, Ariel; Aganezov, Sergey; Hoyt, Savannah J; et al. (Science, 2022)
Since its initial release in 2000, the human reference genome has covered only the euchromatic fraction of the genome, leaving important heterochromatic regions unfinished. Addressing the remaining 8% of the genome, the Telomere-to-Telomere (T2T) Consortium presents a complete 3.055 billion-base pair sequence of a human genome, T2T-CHM13, that includes gapless assemblies for all chromosomes except Y, corrects errors in the prior references, and introduces nearly 200 million base pairs of sequence containing 1956 gene predictions, 99 of which are predicted to be protein coding. The completed regions include all centromeric satellite arrays, recent segmental duplications, and the short arms of all five acrocentric chromosomes, unlocking these complex regions of the genome to variational and functional studies.
Keywords: Cell Line; Chromosomes, Artificial, Bacterial; Chromosomes, Human; Genome, Human; Human Genome Project; Humans; Reference Values; Sequence Analysis, DNA

Correction: Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2022)

Curated variation benchmarks for challenging medically relevant autosomal genes. - Wagner, Justin; Olson, Nathan D; Harris, Lindsay; McDaniel, Jennifer; Cheng, Haoyu; Fungtammasan, Arkarachai; Hwang, Yih-Chii; Gupta, Richa; Wenger, Aaron M; Rowell, William J; Khan, Ziad M; Farek, Jesse; et al. (Nat Biotechnol, 2022)
The repetitive nature and complexity of some medically relevant genes poses a challenge for their accurate analysis in a clinical setting. The Genome in a Bottle Consortium has provided variant benchmark sets, but these exclude nearly 400 medically relevant genes due to their repetitiveness or polymorphic complexity. Here, we characterize 273 of these 395 challenging autosomal genes using a haplotype-resolved whole-genome assembly. This curated benchmark reports over 17,000 single-nucleotide variations, 3,600 insertions and deletions and 200 structural variations each for human genome reference GRCh37 and GRCh38 across HG002. We show that false duplications in either GRCh37 or GRCh38 result in reference-specific, missed variants for short- and long-read technologies in medically relevant genes, including CBS, CRYAA and KCNE1. When masking these false duplications, variant recall can improve from 8% to 100%. Forming benchmarks from a haplotype-resolved whole-genome assembly may become a prototype for future benchmarks covering the whole genome.
Keywords: Genome, Human; Haplotypes; Humans; Sequence Analysis, DNA

CYP2C8, CYP2C9, and CYP2C19 Characterization Using Next-Generation Sequencing and Haplotype Analysis: A GeT-RM Collaborative Project. - Gaedigk, Andrea; Boone, Erin C; Steven E Scherer; Lee, Seung-Been; Numanagić, Ibrahim; Sahinalp, Cenk; Smith, Joshua D; McGee, Sean; Radhakrishnan, Aparna; Xiang Qin; Wang, Wendy Y; Farrow, Emily G; et al. (J Mol Diagn, 2022)
Pharmacogenetic tests typically target selected sequence variants to identify haplotypes that are often defined by star (∗) allele nomenclature. Due to their design, these targeted genotyping assays are unable to detect novel variants that may change the function of the gene product and thereby affect phenotype prediction and patient care. In the current study, 137 DNA samples that were previously characterized by the Genetic Testing Reference Material (GeT-RM) program using a variety of targeted genotyping methods were recharacterized using targeted and whole genome sequencing analysis. Sequence data were analyzed using three genotype calling tools to identify star allele diplotypes for CYP2C8, CYP2C9, and CYP2C19. The genotype calls from next-generation sequencing (NGS) correlated well to those previously reported, except when novel alleles were present in a sample. Six novel alleles and 38 novel suballeles were identified in the three genes due to identification of variants not covered by targeted genotyping assays. In addition, several ambiguous genotype calls from a previous study were resolved using the NGS and/or long-read NGS data. Diplotype calls were mostly consistent between the calling algorithms, although several discrepancies were noted. This study highlights the utility of NGS for pharmacogenetic testing and demonstrates that there are many novel alleles that are yet to be discovered, even in highly characterized genes such as CYP2C9 and CYP2C19.
Keywords: Alleles; Cytochrome P-450 CYP2C19; Cytochrome P-450 CYP2C8; Cytochrome P-450 CYP2C9; Genetic Testing; Genotype; Haplotypes; High-Throughput Nucleotide Sequencing; Humans

Discovery and systematic characterization of risk variants and genes for coronary artery disease in over a million participants. - Aragam, Krishna G; Jiang, Tao; Goel, Anuj; Kanoni, Stavroula; Wolford, Brooke N; Atri, Deepak S; Weeks, Elle M; Wang, Minxian; Hindy, George; Zhou, Wei; Grace, Christopher; Roselli, Carolina; et al. (Nat Genet, 2022)
The discovery of genetic loci associated with complex diseases has outpaced the elucidation of mechanisms of disease pathogenesis. Here we conducted a genome-wide association study (GWAS) for coronary artery disease (CAD) comprising 181,522 cases among 1,165,690 participants of predominantly European ancestry. We detected 241 associations, including 30 new loci. Cross-ancestry meta-analysis with a Japanese GWAS yielded 38 additional new loci. We prioritized likely causal variants using functionally informed fine-mapping, yielding 42 associations with less than five variants in the 95% credible set. Similarity-based clustering suggested roles for early developmental processes, cell cycle signaling and vascular cell migration and proliferation in the pathogenesis of CAD. We prioritized 220 candidate causal genes, combining eight complementary approaches, including 123 supported by three or more approaches. Using CRISPR-Cas9, we experimentally validated the effect of an enhancer in MYO9B, which appears to mediate CAD risk by regulating vascular cell motility. Our analysis identifies and systematically characterizes >250 risk loci for CAD to inform experimental interrogation of putative causal mechanisms for CAD.
Keywords: Coronary Artery Disease; Genome-Wide Association Study; Humans

DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases. - Wielscher, Matthias; Mandaviya, Pooja R; Kuehnel, Brigitte; Joehanes, Roby; Mustafa, Rima; Robinson, Oliver; Zhang, Yan; Bodinier, Barbara; Walton, Esther; Mishra, Pashupati P; Schlosser, Pascal; Wilson, Rory; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.
Keywords: C-Reactive Protein; CpG Islands; DNA Methylation; Humans; Inflammation; Nucleotide Motifs

Elucidating the clinical spectrum and molecular basis of HYAL2 deficiency. - Fasham, James; Lin, Siying; Ghosh, Promita; Radio, Francesca Clementina; Farrow, Emily G; Thiffault, Isabelle; Kussman, Jennifer; Zhou, Dihong; Hemming, Rick; Zahka, Kenneth; Chioza, Barry A; Rawlins, Lettie E; et al. (Genet Med, 2022)
PURPOSE: We previously defined biallelic HYAL2 variants causing a novel disorder in 2 families, involving orofacial clefting, facial dysmorphism, congenital heart disease, and ocular abnormalities, with Hyal2 knockout mice displaying similar phenotypes. In this study, we better define the phenotype and pathologic disease mechanism. METHODS: Clinical and genomic investigations were undertaken alongside molecular studies, including immunoblotting and immunofluorescence analyses of variant/wild-type human HYAL2 expressed in mouse fibroblasts, and in silico modeling of putative pathogenic variants. RESULTS: Ten newly identified individuals with this condition were investigated, and they were associated with 9 novel pathogenic variants. Clinical studies defined genotype-phenotype correlations and confirmed a recognizable craniofacial phenotype in addition to myopia, cleft lip/palate, and congenital cardiac anomalies as the most consistent manifestations of the condition. In silico modeling of missense variants identified likely deleterious effects on protein folding. Consistent with this, functional studies indicated that these variants cause protein instability and a concomitant cell surface absence of HYAL2 protein. CONCLUSION: These studies confirm an association between HYAL2 alterations and syndromic cleft lip/palate, provide experimental evidence for the pathogenicity of missense alleles, enable further insights into the pathomolecular basis of the disease, and delineate the core and variable clinical outcomes of the condition.
Keywords: Alleles; Animals; Cell Adhesion Molecules; Cleft Lip; Cleft Palate; Genetic Association Studies; GPI-Linked Proteins; Humans; Hyaluronoglucosaminidase; Mice; Phenotype

Expanding the mutation and phenotype spectrum of MYH3-associated skeletal disorders. - Zhao, Sen; Zhang, Yuanqiang; Hallgrimsdottir, Sigrun; Zuo, Yuzhi; Li, Xiaoxin; Batkovskyte, Dominyka; Liu, Sen; Lindelöf, Hillevi; Wang, Shengru; Hammarsjö, Anna; Yang, Yang; Ye, Yongyu; et al. (NPJ Genom Med, 2022)
Pathogenic variants in MYH3 cause distal arthrogryposis type 2A and type 2B3 as well as contractures, pterygia and spondylocarpotarsal fusion syndromes types 1A and 1B. These disorders are ultra-rare and their natural course and phenotypic variability are not well described. In this study, we summarize the clinical features and genetic findings of 17 patients from 10 unrelated families with vertebral malformations caused by dominant or recessive pathogenic variants in MYH3. Twelve novel pathogenic variants in MYH3 (NM_002470.4) were identified: three of them were de novo or inherited in autosomal dominant way and nine were inherited in autosomal recessive way. The patients had vertebral segmentation anomalies accompanied with variable joint contractures, short stature and dysmorphic facial features. There was a significant phenotypic overlap between dominant and recessive MYH3-associated conditions regarding the degree of short stature as well as the number of vertebral fusions. All monoallelic variants caused significantly decreased SMAD3 phosphorylation, which is consistent with the previously proposed pathogenic mechanism of impaired canonical TGF-β signaling. Most of the biallelic variants were predicted to be protein-truncating, while one missense variant c.4244T>G,p.(Leu1415Arg), which was inherited in an autosomal recessive way, was found to alter the phosphorylation level of p38, suggesting an inhibition of the non-canonical pathway of TGF-β signaling. In conclusion, the identification of 12 novel pathogenic variants and overlapping phenotypes in 17 affected individuals from 10 unrelated families expands the mutation and phenotype spectrum of MYH3-associated skeletal disorders. We show that disturbances of canonical or non-canonical TGF-β signaling pathways are involved in pathogenesis of MYH3-associated skeletal fusion (MASF) syndrome.

EYS-Associated Sector Retinitis Pigmentosa. - Marques, João Pedro; Porto, Fernanda Belga Ottoni; Carvalho, Ana Luísa; Neves, Emmanuel; Rui Chen; Sampaio, Shirley Aparecida Madureira; Murta, Joaquim; Saraiva, Jorge; Silva, Rufino (Graefes Arch Clin Exp Ophthalmol, 2022)
PURPOSE: Sector retinitis pigmentosa (RP) is a rare form of rod-cone degeneration typically associated with mutations in the RHO gene. We describe six unrelated patients presenting with this atypical phenotype in association with biallelic mutations in EYS gene. METHODS: Multinational, multicentre cross-sectional case series. Patients with biallelic disease-causing variants in EYS and a clinical diagnosis of sector RP were recruited from specialized centres in Portugal and Brazil. All patients underwent a comprehensive ophthalmologic examination complemented by deep phenotyping. Peripheral blood samples were collected from all probands and available relatives for genetic analysis. Genetic counselling was provided to all subjects. RESULTS: Seven disease-causing variants (4 pathogenic; 3 likely pathogenic) were identified in 6 unrelated female patients. Best-corrected visual acuity ranged from 75 to 85 ETDRS letters. All eyes showed bilateral and symmetrical areas of outer retinal atrophy distributed along the inferior vascular arcades and extending temporally and/or nasally in a crescent-shaped pattern. On fundus autofluorescence (AF), a foveal-sparing curvilinear band of hyperAF encroaching the optic nerve head and extending temporally was seen in 4 patients. The remaining 2 presented bilateral and symmetrical patches of hypoAF inside crescent-shaped areas of hyperAF along the inferior temporal vascular arcade. Visual field testing revealed superior visual field defects of varying extents, always in close association with the fundus AF findings. CONCLUSIONS: Even though EYS has only recently been listed as a cause of the sector RP phenotype, we believe that this presentation is not infrequent and should be considered an important differential for sector RP.
Keywords: Cone-Rod Dystrophies; Cross-Sectional Studies; DNA Mutational Analysis; Eye Proteins; Female; Humans; Mutation; Retinitis Pigmentosa

A framework for detecting noncoding rare-variant associations of large-scale whole-genome sequencing studies. - Li, Zilin; Li, Xihao; Zhou, Hufeng; Gaynor, Sheila M; Selvaraj, Margaret Sunitha; Arapoglou, Theodore; Quick, Corbin; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; et al. (Nat Methods, 2022)
Large-scale whole-genome sequencing studies have enabled analysis of noncoding rare-variant (RV) associations with complex human diseases and traits. Variant-set analysis is a powerful approach to study RV association. However, existing methods have limited ability in analyzing the noncoding genome. We propose a computationally efficient and robust noncoding RV association detection framework, STAARpipeline, to automatically annotate a whole-genome sequencing study and perform flexible noncoding RV association analysis, including gene-centric analysis and fixed window-based and dynamic window-based non-gene-centric analysis by incorporating variant functional annotations. In gene-centric analysis, STAARpipeline uses STAAR to group noncoding variants based on functional categories of genes and incorporate multiple functional annotations. In non-gene-centric analysis, STAARpipeline uses SCANG-STAAR to incorporate dynamic window sizes and multiple functional annotations. We apply STAARpipeline to identify noncoding RV sets associated with four lipid traits in 21,015 discovery samples from the Trans-Omics for Precision Medicine (TOPMed) program and replicate several of them in an additional 9,123 TOPMed samples. We also analyze five non-lipid TOPMed traits.
Keywords: Genetic Variation; Genome; Genome-Wide Association Study; Humans; Phenotype; Whole Genome Sequencing

Functional characteristics of a broad spectrum of TBX6 variants in Mayer-Rokitansky-Küster-Hauser syndrome. - Ma, Congcong; Chen, Na; Jolly, Angad; Zhao, Sen; Coban-Akdemir, Zeynep; Tian, Weijie; Kang, Jia; Ye, Yang; Wang, Yuan; Koch, André; Zhang, Yuanqiang; Qin, Chenglu; et al. (Genet Med, 2022)
PURPOSE: Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) is characterized by congenital absence of the uterus, cervix, and the upper part of the vagina in females. Whole-gene deletion and loss-of-function variants in TBX6 have been identified in association with MRKHS. We aimed to expand the spectrum of TBX6 variants in MRKHS and explore the biological effect of the variant alleles. METHODS: Rare variants in TBX6 were called from a combined multiethnic cohort of 622 probands with MRKHS who underwent exome sequencing or genome sequencing. Multiple in vitro functional experiments were performed, including messenger RNA analysis, western blotting, transcriptional activity assay, and immunofluorescence staining. RESULTS: We identified 16 rare variants in TBX6 from the combined cohort, including 1 protein-truncating variant reported in our previous study and 15 variants with unknown effects. By comparing the prevalence of TBX6 variants in the Chinese MRKHS cohort vs 1038 female controls, we observed a significant mutational burden of TBX6 in affected individuals (P = .0004, odds ratio = 5.25), suggesting a causal role of TBX6 variants in MRKHS. Of the 15 variants with uncertain effects, 7 were shown to induce a loss-of-function effect through various mechanisms. The c.423G>A (p.Leu141=) and c.839+5G>A variants impaired the normal splicing of TBX6 messenger RNA, c.422T>C (p.Leu141Pro) and c.745G>A (p.Val249Met) led to decreased protein expression, c.10C>T (p.Pro4Ser) and c.400G>A (p.Glu134Lys) resulted in perturbed transcriptional activity, and c.356G>A (p.Arg119His) caused protein mislocalization. We observed incomplete penetrance and variable expressivity in families carrying deleterious variants, which indicates a more complex genetic mechanism than classical Mendelian inheritance. CONCLUSION: Our study expands the mutational spectrum of TBX6 in MRKHS and delineates the molecular pathogenesis of TBX6 variants, supporting the association between deleterious variants in TBX6 and MRKHS.
Keywords: 46, XX Disorders of Sex Development; Congenital Abnormalities; Female; Humans; Mullerian Ducts; RNA, Messenger; T-Box Domain Proteins; Vagina

Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways. - Young, William J; Lahrouchi, Najim; Isaacs, Aaron; Duong, ThuyVy; Foco, Luisa; Ahmed, Farah; Brody, Jennifer A; Salman, Reem; Noordam, Raymond; Benjamins, Jan-Walter; Haessler, Jeffrey; Lyytikäinen, Leo-Pekka; et al. (Nat Commun, 2022)
The QT interval is an electrocardiographic measure representing the sum of ventricular depolarization and repolarization, estimated by QRS duration and JT interval, respectively. QT interval abnormalities are associated with potentially fatal ventricular arrhythmia. Using genome-wide multi-ancestry analyses (>250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.
Keywords: Arrhythmias, Cardiac; Death, Sudden, Cardiac; Electrocardiography; Genetic Testing; Humans; Male

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Eric Boerwinkle; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.
Keywords: Brain; Learning; Memory, Short-Term; Multifactorial Inheritance; Verbal Learning

Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases. - Li, Yong; Cheng, Yurong; Consolato, Francesco; Schiano, Guglielmo; Chong, Michael R; Pietzner, Maik; Nguyen, Ngoc Quynh H; Scherer, Nora; Biggs, Mary L; Kleber, Marcus E; Haug, Stefan; Göçmen, Burulça; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Hypertension; Renal Insufficiency, Chronic; Uromodulin

Genomic signatures of high-altitude adaptation and chromosomal polymorphism in geladas. - Chiou, Kenneth L; Janiak, Mareike C; Schneider-Crease, India A; Sen, Sharmi; Ayele, Ferehiwot; Chuma, Idrissa S; Knauf, Sascha; Lemma, Alemayehu; Signore, Anthony V; D'Ippolito, Anthony M; Abebe, Belayneh; Haile, Abebaw Azanaw; et al. (Nat Ecol Evol, 2022)
Primates have adapted to numerous environments and lifestyles but very few species are native to high elevations. Here we investigated high-altitude adaptations in the gelada (Theropithecus gelada), a monkey endemic to the Ethiopian Plateau. We examined genome-wide variation in conjunction with measurements of haematological and morphological traits. Our new gelada reference genome is highly intact and assembled at chromosome-length levels. Unexpectedly, we identified a chromosomal polymorphism in geladas that could potentially contribute to reproductive barriers between populations. Compared with baboons at low altitude, we found that high-altitude geladas exhibit significantly expanded chest circumferences, potentially allowing for greater lung surface area for increased oxygen diffusion. We identified gelada-specific amino acid substitutions in the alpha-chain subunit of adult haemoglobin but found that gelada haemoglobin does not exhibit markedly altered oxygenation properties compared with lowland primates. We also found that geladas at high altitude do not exhibit elevated blood haemoglobin concentrations, in contrast to the normal acclimatization response to hypoxia in lowland primates. The absence of altitude-related polycythaemia suggests that geladas are able to sustain adequate tissue-oxygen delivery despite environmental hypoxia. Finally, we identified numerous genes and genomic regions exhibiting accelerated rates of evolution, as well as gene families exhibiting expansions in the gelada lineage, potentially reflecting altitude-related selection. Our findings lend insight into putative mechanisms of high-altitude adaptation while suggesting promising avenues for functional hypoxia research.
Keywords: Altitude; Animals; Chromosomes; Genomics; Hypoxia; Oxygen; Theropithecus

Implementation of preemptive DNA sequence-based pharmacogenomics testing across a large academic medical center: The Mayo-Baylor RIGHT 10K Study. - Wang, Liewei; Steven E Scherer; Bielinski, Suzette J; Donna M Muzny; Jones, Leila A; Black, John Logan; Moyer, Ann M; Giri, Jyothsna; Sharp, Richard R; Matey, Eric T; Wright, Jessica A; Oyen, Lance J; et al. (Genet Med, 2022)
PURPOSE: The Mayo-Baylor RIGHT 10K Study enabled preemptive, sequence-based pharmacogenomics (PGx)-driven drug prescribing practices in routine clinical care within a large cohort. We also generated the tools and resources necessary for clinical PGx implementation and identified challenges that need to be overcome. Furthermore, we measured the frequency of both common genetic variation for which clinical guidelines already exist and rare variation that could be detected by DNA sequencing, rather than genotyping. METHODS: Targeted oligonucleotide-capture sequencing of 77 pharmacogenes was performed using DNA from 10,077 consented Mayo Clinic Biobank volunteers. The resulting predicted drug response-related phenotypes for 13 genes, including CYP2D6 and HLA, affecting 21 drug-gene pairs, were deposited preemptively in the Mayo electronic health record. RESULTS: For the 13 pharmacogenes of interest, the genomes of 79% of participants carried clinically actionable variants in 3 or more genes, and DNA sequencing identified an average of 3.3 additional conservatively predicted deleterious variants that would not have been evident using genotyping. CONCLUSION: Implementation of preemptive rather than reactive and sequence-based rather than genotype-based PGx prescribing revealed nearly universal patient applicability and required integrated institution-wide resources to fully realize individualized drug therapy and to show more efficient use of health care resources.
Keywords: Academic Medical Centers; Base Sequence; Cytochrome P-450 CYP2D6; Genotype; Humans; Pharmacogenetics

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.
Keywords: Blood Pressure; Genome-Wide Association Study; Genomics; Humans; Hypertension; Polymorphism, Single Nucleotide; Precision Medicine

Isolation and Barcoding of Trace Pollen-free DNA for Authentication of Honey. - Chavan, Dimple; Adolacion, Jay R T; Crum, Mary; Nandy, Suman; Lee, Kyung Hyun; Vu, Binh; Kourentzi, Katerina; Aniko Sabo; Willson, Richard C (J Agric Food Chem, 2022)
Adulteration and mislabeling of honey to mask its true origin have become a global concern. Pollen microscopy, the current gold standard for identifying honey's geographical and plant origins, is laborious, requires extensive training, and fails to identify filtered honey and honey spiked with pollen from a more favorable plant to disguise its origins. We successfully isolated pollen-free DNA from filtered honey using three types of adsorbents: (i) anti-dsDNA antibodies coupled to magnetic microspheres; (ii) anion-exchange adsorbent; and (iii) ceramic hydroxyapatite. The internal transcribed spacer 2 region of the captured pollen-free DNA was polymerase chain reaction-amplified and subjected to next-generation sequencing. Using an in-house bioinformatics pipeline, initial experiments showed that anion exchange had the greatest capacity to capture trace pollen-free DNA, and it was successfully applied to isolate DNA from five honey samples. Enrichment of trace pollen-free DNA from filtered honey samples opens a new approach for identifying the true origins of honey.
Keywords: DNA; DNA Barcoding, Taxonomic; Honey; Pollen

Multiple genome alignment in the telomere-to-telomere assembly era. - Kille, Bryce; Balaji, Advait; Fritz J Sedlazeck; Nute, Michael; Treangen, Todd J (Genome Biol, 2022)
With the arrival of telomere-to-telomere (T2T) assemblies of the human genome comes the computational challenge of efficiently and accurately constructing multiple genome alignments at an unprecedented scale. By identifying nucleotides across genomes which share a common ancestor, multiple genome alignments commonly serve as the bedrock for comparative genomics studies. In this review, we provide an overview of the algorithmic template that most multiple genome alignment methods follow. We also discuss prospective areas of improvement of multiple genome alignment for keeping up with continuously arriving high-quality T2T assembled genomes and for unlocking clinically-relevant insights.
Keywords: Genome, Human; Genomics; Humans; Nucleotides; Telomere

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

Novel pathogenic variants and quantitative phenotypic analyses of Robinow syndrome: WNT signaling perturbation and phenotypic variability. - Zhang, Chaofan; Jolly, Angad; Shayota, Brian J; Mazzeu, Juliana F; Du, Haowei; Dawood, Moez; Soper, Patricia Celestino; Ramalho de Lima, Ariadne; Ferreira, Barbara Merfort; Coban-Akdemir, Zeynep; White, Janson; Shears, Deborah; et al. (HGG Adv, 2022)
Robinow syndrome (RS) is a genetically heterogeneous disorder with six genes that converge on the WNT/planar cell polarity (PCP) signaling pathway implicated (, , , , , and ). RS is characterized by skeletal dysplasia and distinctive facial and physical characteristics. To further explore the genetic heterogeneity, paralog contribution, and phenotypic variability of RS, we investigated a cohort of 22 individuals clinically diagnosed with RS from 18 unrelated families. Pathogenic or likely pathogenic variants in genes associated with RS or RS phenocopies were identified in all 22 individuals, including the first variant to be reported in . We retrospectively collected medical records of 16 individuals from this cohort and extracted clinical descriptions from 52 previously published cases. We performed Human Phenotype Ontology (HPO) based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. Individuals with variants clustered into two groups with demonstrable phenotypic differences between those with missense and truncating alleles. Probands with biallelic variants clustered together with the majority of probands carrying , , and variants, demonstrating no phenotypic distinction between the -autosomal recessive and dominant forms of RS. While phenotypically similar diseases on the RS differential matched through HPO analysis, clustering using phenotype similarity score placed RS-associated phenotypes in a unique cluster containing , , and apart from non-RS-associated paralogs. Through human phenotype analyses of this RS cohort and OMIM clinical synopses of Mendelian disease, this study begins to tease apart specific biologic roles for non-canonical WNT-pathway proteins.

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.
Keywords: Humans; Lung; National Heart, Lung, and Blood Institute (U.S.); Pulmonary Disease, Chronic Obstructive; Risk Factors; Transcriptome; United States

PrecisionFDA Truth Challenge V2: Calling variants from short and long reads in difficult-to-map regions. - Olson, Nathan D; Wagner, Justin; McDaniel, Jennifer; Stephens, Sarah H; Westreich, Samuel T; Prasanna, Anish G; Johanson, Elaine; Boja, Emily; Maier, Ezekiel J; Serang, Omar; Jáspez, David; Lorenzo-Salazar, José M; et al. (Cell Genom, 2022)
The precisionFDA Truth Challenge V2 aimed to assess the state of the art of variant calling in challenging genomic regions. Starting with FASTQs, 20 challenge participants applied their variant-calling pipelines and submitted 64 variant call sets for one or more sequencing technologies (Illumina, PacBio HiFi, and Oxford Nanopore Technologies). Submissions were evaluated following best practices for benchmarking small variants with updated Genome in a Bottle benchmark sets and genome stratifications. Challenge submissions included numerous innovative methods, with graph-based and machine learning methods scoring best for short-read and long-read datasets, respectively. With machine learning approaches, combining multiple sequencing technologies performed particularly well. Recent developments in sequencing and variant calling have enabled benchmarking variants in challenging genomic regions, paving the way for the identification of previously unknown clinically relevant variants.

Proteogenomic Markers of Chemotherapy Resistance and Response in Triple-Negative Breast Cancer. - Anurag, Meenakshi; Jaehnig, Eric J; Krug, Karsten; Lei, Jonathan T; Bergstrom, Erik J; Kim, Beom-Jun; Vashist, Tanmayi D; Huynh, Anh Minh Tran; Dou, Yongchao; Gou, Xuxu; Huang, Chen; Shi, Zhiao; et al. (Cancer Discov, 2022)
UNLABELLED: Microscaled proteogenomics was deployed to probe the molecular basis for differential response to neoadjuvant carboplatin and docetaxel combination chemotherapy for triple-negative breast cancer (TNBC). Proteomic analyses of pretreatment patient biopsies uniquely revealed metabolic pathways, including oxidative phosphorylation, adipogenesis, and fatty acid metabolism, that were associated with resistance. Both proteomics and transcriptomics revealed that sensitivity was marked by elevation of DNA repair, E2F targets, G2-M checkpoint, interferon-gamma signaling, and immune-checkpoint components. Proteogenomic analyses of somatic copy-number aberrations identified a resistance-associated 19q13.31-33 deletion where LIG1, POLD1, and XRCC1 are located. In orthogonal datasets, LIG1 (DNA ligase I) gene deletion and/or low mRNA expression levels were associated with lack of pathologic complete response, higher chromosomal instability index (CIN), and poor prognosis in TNBC, as well as carboplatin-selective resistance in TNBC preclinical models. Hemizygous loss of LIG1 was also associated with higher CIN and poor prognosis in other cancer types, demonstrating broader clinical implications. SIGNIFICANCE: Proteogenomic analysis of triple-negative breast tumors revealed a complex landscape of chemotherapy response associations, including a 19q13.31-33 somatic deletion encoding genes serving lagging-strand DNA synthesis (LIG1, POLD1, and XRCC1), that correlate with lack of pathologic response, carboplatin-selective resistance, and, in pan-cancer studies, poor prognosis and CIN. This article is highlighted in the In This Issue feature, p. 2483.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Carboplatin; Humans; Neoadjuvant Therapy; Proteogenomics; Proteomics; Triple Negative Breast Neoplasms; X-ray Repair Cross Complementing Protein 1

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare coding variants in RCN3 are associated with blood pressure. - He, Karen Y; Kelly, Tanika N; Wang, Heming; Liang, Jingjing; Zhu, Luke; Cade, Brian E; Assimes, Themistocles L; Becker, Lewis C; Beitelshees, Amber L; Bielak, Lawrence F; Bress, Adam P; Brody, Jennifer A; et al. (BMC Genomics, 2022)
BACKGROUND: While large genome-wide association studies have identified nearly one thousand loci associated with variation in blood pressure, rare variant identification is still a challenge. In family-based cohorts, genome-wide linkage scans have been successful in identifying rare genetic variants for blood pressure. This study aims to identify low frequency and rare genetic variants within previously reported linkage regions on chromosomes 1 and 19 in African American families from the Trans-Omics for Precision Medicine (TOPMed) program. Genetic association analyses weighted by linkage evidence were completed with whole genome sequencing data within and across TOPMed ancestral groups consisting of 60,388 individuals of European, African, East Asian, Hispanic, and Samoan ancestries. RESULTS: Associations of low frequency and rare variants in RCN3 and multiple other genes were observed for blood pressure traits in TOPMed samples. The association of low frequency and rare coding variants in RCN3 was further replicated in UK Biobank samples (N = 403,522), and reached genome-wide significance for diastolic blood pressure (p = 2.01 × 10). CONCLUSIONS: Low frequency and rare variants in RCN3 contributes blood pressure variation. This study demonstrates that focusing association analyses in linkage regions greatly reduces multiple-testing burden and improves power to identify novel rare variants associated with blood pressure traits.
Keywords: Blood Pressure; Genetic Linkage; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Precision Medicine; Whole Genome Sequencing

Rare Variants in Genes Encoding Subunits of the Epithelial Na Channel Are Associated With Blood Pressure and Kidney Function. - Blobner, Brandon M; Kirabo, Annet; Kashlan, Ossama B; Sheng, Shaohu; Arnett, Donna K; Becker, Lewis C; Eric Boerwinkle; Carlson, Jenna C; Gao, Yan; Richard A Gibbs; He, Jiang; Irvin, Marguerite R; et al. (Hypertension, 2022)
BACKGROUND: The epithelial Na channel (ENaC) is intrinsically linked to fluid volume homeostasis and blood pressure. Specific rare mutations in , , and , genes encoding the α, β, and γ subunits of ENaC, respectively, are associated with extreme blood pressure phenotypes. No associations between blood pressure and , which encodes the δ subunit of ENaC, have been reported. A small number of sequence variants in ENaC subunits have been reported to affect functional transport in vitro or blood pressure. The effects of the vast majority of rare and low-frequency ENaC variants on blood pressure are not known. METHODS: We explored the association of low frequency and rare variants in the genes encoding ENaC subunits, with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure. Using whole-genome sequencing data from 14 studies participating in the Trans-Omics in Precision Medicine Whole-Genome Sequencing Program, and sequence kernel association tests. RESULTS: We found that variants in and were associated with diastolic blood pressure and mean arterial pressure (<0.00625). Although is poorly expressed in human kidney tissue, variants were associated with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure (<0.00625). ENaC variants in 2 of the 4 subunits ( and ) were also associated with estimated glomerular filtration rate (<0.00625), but not with stroke. CONCLUSIONS: Our results suggest that variants in extrarenal ENaCs, in addition to ENaCs expressed in kidneys, influence blood pressure and kidney function.
Keywords: Blood Pressure; Epithelial Sodium Channels; Humans; Kidney; Phenotype; Sodium

A reverse genetics and genomics approach to gene paralog function and disease: Myokymia and the juxtaparanode. - Marafi, Dana; Kozar, Nina; Duan, Ruizhi; Bradley, Stephen; Yokochi, Kenji; Al Mutairi, Fuad; Saadi, Nebal Waill; Whalen, Sandra; Brunet, Theresa; Kotzaeridou, Urania; Choukair, Daniela; Keren, Boris; et al. (Am J Hum Genet, 2022)
The leucine-rich glioma-inactivated (LGI) family consists of four highly conserved paralogous genes, LGI1-4, that are highly expressed in mammalian central and/or peripheral nervous systems. LGI1 antibodies are detected in subjects with autoimmune limbic encephalitis and peripheral nerve hyperexcitability syndromes (PNHSs) such as Isaacs and Morvan syndromes. Pathogenic variations of LGI1 and LGI4 are associated with neurological disorders as disease traits including familial temporal lobe epilepsy and neurogenic arthrogryposis multiplex congenita 1 with myelin defects, respectively. No human disease has been reported associated with either LGI2 or LGI3. We implemented exome sequencing and family-based genomics to identify individuals with deleterious variants in LGI3 and utilized GeneMatcher to connect practitioners and researchers worldwide to investigate the clinical and electrophysiological phenotype in affected subjects. We also generated Lgi3-null mice and performed peripheral nerve dissection and immunohistochemistry to examine the juxtaparanode LGI3 microarchitecture. As a result, we identified 16 individuals from eight unrelated families with loss-of-function (LoF) bi-allelic variants in LGI3. Deep phenotypic characterization showed LGI3 LoF causes a potentially clinically recognizable PNHS trait characterized by global developmental delay, intellectual disability, distal deformities with diminished reflexes, visible facial myokymia, and distinctive electromyographic features suggestive of motor nerve instability. Lgi3-null mice showed reduced and mis-localized Kv1 channel complexes in myelinated peripheral axons. Our data demonstrate bi-allelic LoF variants in LGI3 cause a clinically distinguishable disease trait of PNHS, most likely caused by disturbed Kv1 channel distribution in the absence of LGI3.
Keywords: Animals; Autoantibodies; Axons; Genomics; Humans; Intracellular Signaling Peptides and Proteins; Mammals; Mice; Myokymia; Nerve Tissue Proteins; Phenotype; Reverse Genetics

Sequencing individual genomes with recurrent genomic disorder deletions: an approach to characterize genes for autosomal recessive rare disease traits. - Bo Yuan; Schulze, Katharina V; Assia Batzir, Nurit; Sinson, Jefferson; Dai, Hongzheng; Zhu, Wenmiao; Bocanegra, Francia; Fong, Chin-To; Holder, Jimmy; Nguyen, Joanne; Schaaf, Christian P; Yang, Yaping; et al. (Genome Med, 2022)
BACKGROUND: In medical genetics, discovery and characterization of disease trait contributory genes and alleles depends on genetic reasoning, study design, and patient ascertainment; we suggest a segmental haploid genetics approach to enhance gene discovery and molecular diagnostics. METHODS: We constructed a genome-wide map for nonallelic homologous recombination (NAHR)-mediated recurrent genomic deletions and used this map to estimate population frequencies of NAHR deletions based on large-scale population cohorts and region-specific studies. We calculated recessive disease carrier burden using high-quality pathogenic or likely pathogenic variants from ClinVar and gnomAD. We developed a NIRD (NAHR deletion Impact to Recessive Disease) score for recessive disorders by quantifying the contribution of NAHR deletion to the overall allele load that enumerated all pairwise combinations of disease-causing alleles; we used a Punnett square approach based on an assumption of random mating. Literature mining was conducted to identify all reported patients with defects in a gene with a high NIRD score; meta-analysis was performed on these patients to estimate the representation of NAHR deletions in recessive traits from contemporary human genomics studies. Retrospective analyses of extant clinical exome sequencing (cES) were performed for novel rare recessive disease trait gene and allele discovery from individuals with NAHR deletions. RESULTS: We present novel genomic insights regarding the genome-wide impact of NAHR recurrent segmental variants on recessive disease burden; we demonstrate the utility of NAHR recurrent deletions to enhance discovery in the challenging context of autosomal recessive (AR) traits and biallelic variation. Computational results demonstrate new mutations mediated by NAHR, involving recurrent deletions at 30 genomic regions, likely drive recessive disease burden for over 74% of loci within these segmental deletions or at least 2% of loci genome-wide. Meta-analyses on 170 literature-reported patients implicate that NAHR deletions are depleted from the ascertained pool of AR trait alleles. Exome reanalysis of personal genomes from subjects harboring recurrent deletions uncovered new disease-contributing variants in genes including COX10, ERCC6, PRRT2, and OTUD7A. CONCLUSIONS: Our results demonstrate that genomic sequencing of personal genomes with NAHR deletions could dramatically improve allele and gene discovery and enhance clinical molecular diagnosis. Moreover, results suggest NAHR events could potentially enable human haploid genetic screens as an approach to experimental inquiry into disease biology.
Keywords: Base Sequence; Genomics; Homologous Recombination; Humans; Rare Diseases; Retrospective Studies

TOP-LD: A tool to explore linkage disequilibrium with TOPMed whole-genome sequence data. - Huang, Le; Rosen, Jonathan D; Sun, Quan; Chen, Jiawen; Wheeler, Marsha M; Zhou, Ying; Min, Yuan-I; Kooperberg, Charles; Conomos, Matthew P; Stilp, Adrienne M; Rich, Stephen S; Rotter, Jerome I; et al. (Am J Hum Genet, 2022)
Current publicly available tools that allow rapid exploration of linkage disequilibrium (LD) between markers (e.g., HaploReg and LDlink) are based on whole-genome sequence (WGS) data from 2,504 individuals in the 1000 Genomes Project. Here, we present TOP-LD, an online tool to explore LD inferred with high-coverage (∼30×) WGS data from 15,578 individuals in the NHLBI Trans-Omics for Precision Medicine (TOPMed) program. TOP-LD provides a significant upgrade compared to current LD tools, as the TOPMed WGS data provide a more comprehensive representation of genetic variation than the 1000 Genomes data, particularly for rare variants and in the specific populations that we analyzed. For example, TOP-LD encompasses LD information for 150.3, 62.2, and 36.7 million variants for European, African, and East Asian ancestral samples, respectively, offering 2.6- to 9.1-fold increase in variant coverage compared to HaploReg 4.0 or LDlink. In addition, TOP-LD includes tens of thousands of structural variants (SVs). We demonstrate the value of TOP-LD in fine-mapping at the GGT1 locus associated with gamma glutamyltransferase in the African ancestry participants in UK Biobank. Beyond fine-mapping, TOP-LD can facilitate a wide range of applications that are based on summary statistics and estimates of LD. TOP-LD is freely available online.
Keywords: Asian People; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Precision Medicine; Whole Genome Sequencing

Type 2 Diabetes Partitioned Polygenic Scores Associate With Disease Outcomes in 454,193 Individuals Across 13 Cohorts. - DiCorpo, Daniel; LeClair, Jessica; Cole, Joanne B; Sarnowski, Chloe; Ahmadizar, Fariba; Bielak, Lawrence F; Blokstra, Anneke; Bottinger, Erwin P; Chaker, Layal; Chen, Yii-Der I; Chen, Ye; de Vries, Paul S; et al. (Diabetes Care, 2022)
OBJECTIVE: Type 2 diabetes (T2D) has heterogeneous patient clinical characteristics and outcomes. In previous work, we investigated the genetic basis of this heterogeneity by clustering 94 T2D genetic loci using their associations with 47 diabetes-related traits and identified five clusters, termed β-cell, proinsulin, obesity, lipodystrophy, and liver/lipid. The relationship between these clusters and individual-level metabolic disease outcomes has not been assessed. RESEARCH DESIGN AND METHODS: Here we constructed individual-level partitioned polygenic scores (pPS) for these five clusters in 12 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (n = 454,193) and tested for cross-sectional association with T2D-related outcomes, including blood pressure, renal function, insulin use, age at T2D diagnosis, and coronary artery disease (CAD). RESULTS: Despite all clusters containing T2D risk-increasing alleles, they had differential associations with metabolic outcomes. Increased obesity and lipodystrophy cluster pPS, which had opposite directions of association with measures of adiposity, were both significantly associated with increased blood pressure and hypertension. The lipodystrophy and liver/lipid cluster pPS were each associated with CAD, with increasing and decreasing effects, respectively. An increased liver/lipid cluster pPS was also significantly associated with reduced renal function. The liver/lipid cluster includes known loci linked to liver lipid metabolism (e.g., GCKR, PNPLA3, and TM6SF2), and these findings suggest that cardiovascular disease risk and renal function may be impacted by these loci through their shared disease pathway. CONCLUSIONS: Our findings support that genetically driven pathways leading to T2D also predispose differentially to clinical outcomes.
Keywords: Alleles; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Genetic Loci; Humans; Obesity; Pharmaceutical Preparations

Use of medical exome sequencing for identification of underlying genetic defects in NICU: Experience in a cohort of 2303 neonates in China. - Yang, Lin; Wei, Zejun; Chen, Xiang; Hu, Liyuan; Peng, Xiaomin; Wang, Jin; Lu, Chunmei; Kong, Yanting; Dong, Xinran; Ni, Qi; Lu, Yulan; Wu, Bingbing; et al. (Clin Genet, 2022)
Emerging evidence demonstrates the clinical utility of genomic applications in newborn intensive care unit (NICU) patients with strong indications of Mendelian etiology. However, such applications' diagnostic yield and utility remain unclear for NICU cohorts with minimal phenotype selection. In this study, focused medical exome sequencing was used as a first-tier, singleton-focused diagnostic tool for 2303 unrelated sick neonates. Integrated analysis of single nucleotide variants (SNVs), small insertions and deletions (Indels), and large copy number variants (CNVs) was performed. The diagnostic rate in this NICU cohort is 12.3% (284/2303), with 190 probands with molecular diagnoses made from SNV/Indel analyses (66.9%), 93 patients with diagnostic aneuploidy/CNVs findings (32.8%), and 1 patient with both SNV and CNV (0.4%). In addition, 54 (2.3%) of patients had a reportable incidental finding. Multiple organ involvements, craniofacial abnormalities, and dermatologic abnormalities were the strongest positive predictors for a molecular diagnosis. Among the 190 cases with SNV/Indel defects, direct impacts on medical management were observed in 46.8% of patients after the results were reported. In this study, we demonstrate that focused medical exome sequencing is a powerful first-line diagnostic tool for NICU patients. Significant number of diagnosed NICU patients can benefit from more focused medical management and long-term care.
Keywords: Alleles; China; Chromosome Mapping; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Humans; INDEL Mutation; Intensive Care Units, Neonatal; Male; Polymorphism, Single Nucleotide; Whole Genome Sequencing

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Eric Boerwinkle; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Whole genome sequence analysis of blood lipid levels in >66,000 individuals. - Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Pampana, Akhil; Zhang, David Y; Park, Joseph; Aslibekyan, Stella; Bis, Joshua C; Brody, Jennifer A; Cade, Brian E; Chuang, Lee-Ming; Chung, Ren-Hua; et al. (Nat Commun, 2022)
Blood lipids are heritable modifiable causal factors for coronary artery disease. Despite well-described monogenic and polygenic bases of dyslipidemia, limitations remain in discovery of lipid-associated alleles using whole genome sequencing (WGS), partly due to limited sample sizes, ancestral diversity, and interpretation of clinical significance. Among 66,329 ancestrally diverse (56% non-European) participants, we associate 428M variants from deep-coverage WGS with lipid levels; ~400M variants were not assessed in prior lipids genetic analyses. We find multiple lipid-related genes strongly associated with blood lipids through analysis of common and rare coding variants. We discover several associated rare non-coding variants, largely at Mendelian lipid genes. Notably, we observe rare LDLR intronic variants associated with markedly increased LDL-C, similar to rare LDLR exonic variants. In conclusion, we conducted a systematic whole genome scan for blood lipids expanding the alleles linked to lipids for multiple ancestries and characterize a clinically-relevant rare non-coding variant model for lipids.
Keywords: Alleles; Cholesterol, LDL; Genome-Wide Association Study; Humans; Lipids; Whole Genome Sequencing

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldórsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

Whole-genome sequencing as an investigational device for return of hereditary disease risk and pharmacogenomic results as part of the All of Us Research Program. - Eric Venner; Donna M Muzny; Smith, Joshua D; Kimberly Walker; Neben, Cynthia L; Lockwood, Christina M; Empey, Phillip E; Ginger A Metcalf; Kachulis, Chris; Mian, Sana; Musick, Anjene; Rehm, Heidi L; et al. (Genome Med, 2022)
BACKGROUND: The All of Us Research Program (AoURP, "the program") is an initiative, sponsored by the National Institutes of Health (NIH), that aims to enroll one million people (or more) across the USA. Through repeated engagement of participants, a research resource is being created to enable a variety of future observational and interventional studies. The program has also committed to genomic data generation and returning important health-related information to participants. METHODS: Whole-genome sequencing (WGS), variant calling processes, data interpretation, and return-of-results procedures had to be created and receive an Investigational Device Exemption (IDE) from the United States Food and Drug Administration (FDA). The performance of the entire workflow was assessed through the largest known cross-center, WGS-based, validation activity that was refined iteratively through interactions with the FDA over many months. RESULTS: The accuracy and precision of the WGS process as a device for the return of certain health-related genomic results was determined to be sufficient, and an IDE was granted. CONCLUSIONS: We present here both the process of navigating the IDE application process with the FDA and the results of the validation study as a guide to future projects which may need to follow a similar path. Changes to the program in the future will be covered in supplementary submissions to the IDE and will support additional variant classes, sample types, and any expansion to the reportable regions.
Keywords: Genomics; Humans; Pharmacogenetics; Population Health; United States; Whole Genome Sequencing

Absent B cells, agammaglobulinemia, and hypertrophic cardiomyopathy in folliculin-interacting protein 1 deficiency. - Saettini, Francesco; Poli, Cecilia; Vengoechea, Jaime; Bonanomi, Sonia; Orellana, Julio C; Fazio, Grazia; Rodriguez, Fred H; Noguera, Loreani P; Booth, Claire; Jarur-Chamy, Valentina; Shams, Marissa; Iascone, Maria; et al. (Blood, 2021)
Agammaglobulinemia is the most profound primary antibody deficiency that can occur due to an early termination of B-cell development. We here investigated 3 novel patients, including the first known adult, from unrelated families with agammaglobulinemia, recurrent infections, and hypertrophic cardiomyopathy (HCM). Two of them also presented with intermittent or severe chronic neutropenia. We identified homozygous or compound-heterozygous variants in the gene for folliculin interacting protein 1 (FNIP1), leading to loss of the FNIP1 protein. B-cell metabolism, including mitochondrial numbers and activity and phosphatidylinositol 3-kinase/AKT pathway, was impaired. These defects recapitulated the Fnip1-/- animal model. Moreover, we identified either uniparental disomy or copy-number variants (CNVs) in 2 patients, expanding the variant spectrum of this novel inborn error of immunity. The results indicate that FNIP1 deficiency can be caused by complex genetic mechanisms and support the clinical utility of exome sequencing and CNV analysis in patients with broad phenotypes, including agammaglobulinemia and HCM. FNIP1 deficiency is a novel inborn error of immunity characterized by early and severe B-cell development defect, agammaglobulinemia, variable neutropenia, and HCM. Our findings elucidate a functional and relevant role of FNIP1 in B-cell development and metabolism and potentially neutrophil activity.
Keywords: Adult; Agammaglobulinemia; Animals; B-Lymphocytes; Cardiomyopathy, Hypertrophic; Carrier Proteins; Child; Child, Preschool; Chromosomes, Human, Pair 5; Codon, Nonsense; Consanguinity; Crohn Disease; Developmental Disabilities; Disease Models, Animal; Disease Susceptibility; DNA Copy Number Variations; Female; Heart Defects, Congenital; Humans; Immunologic Deficiency Syndromes; Infections; Loss of Function Mutation; Lymphopenia; Male; Mice; Neutropenia; Pedigree; Uniparental Disomy; Whole Exome Sequencing

Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Eric Boerwinkle; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Eczema; Exome; Exome Sequencing; Facies; Female; Genetic Predisposition to Disease; Genome, Human; Genomics; Growth Disorders; Histone Deacetylases; Humans; Infant; Intellectual Disability; Male; Microcephaly; Phenotype; Repressor Proteins

Association Between Midlife Obesity and Kidney Function Trajectories: The Atherosclerosis Risk in Communities (ARIC) Study. - Yu, Zhi; Grams, Morgan E; Ndumele, Chiadi E; Wagenknecht, Lynne; Eric Boerwinkle; North, Kari E; Rebholz, Casey M; Giovannucci, Edward L; Coresh, Josef (Am J Kidney Dis, 2021)
RATIONALE & OBJECTIVE: Obesity has been related to risk for chronic kidney disease. However, the associations of different measures of midlife obesity with long-term kidney function trajectories and whether they differ by sex and race are unknown. STUDY DESIGN: Observational study. SETTING & PARTICIPANTS: 13,496 participants from the Atherosclerosis Risk in Communities (ARIC) Study. PREDICTORS: Midlife obesity status as measured by body mass index (BMI), waist-to-hip ratio, and predicted percent fat at baseline. OUTCOMES: Estimated glomerular filtration rate (eGFR) calculated using serum creatinine level measured at 5 study visits, and incident kidney failure with replacement therapy (KFRT). ANALYTICAL APPROACH: Mixed models with random intercepts and random slopes for eGFR. Cox proportional hazards models for KFRT. RESULTS: Baseline mean age was 54 years, median eGFR was 103mL/min/1.73m, and median BMI was 27kg/m. Over 30 years of follow-up, midlife obesity measures were associated with eGFR decline in White and Black women but not consistently in men. Adjusted for age, center, smoking, and coronary heart disease, the differences in eGFR slope per 1-SD higher BMI, waist-to-hip ratio, and predicted percent fat were 0.09 (95% CI, -0.18 to 0.36), -0.25 (95% CI, -0.50 to 0.01), and-0.14 (95% CI, -0.41 to 0.13) mL/min/1.73m per decade for White men; -0.91 (95% CI, -1.15 to-0.67), -0.82 (95% CI, -1.06 to-0.58), and-1.02 (95% CI, -1.26 to-0.78) mL/min/1.73m per decade for White women; -0.70 (95% CI, -1.54 to 0.14), -1.60 (95% CI, -2.42 to-0.78), and-1.24 (95% CI, -2.08 to-0.40) mL/min/1.73m per decade for Black men; and-1.24 (95% CI, -2.08 to-0.40), -1.50 (95% CI, -2.05 to-0.95), and-1.43 (95% CI, -2.00 to-0.86) mL/min/1.73m per decade for Black women. Obesity indicators were independently associated with risk for KFRT for all sex-race groups except White men. LIMITATIONS: Loss to follow-up during 3 decades of follow-up with 5 eGFR assessments. CONCLUSIONS: Obesity status is a risk factor for future decline in kidney function and development of KFRT in Black and White women, with less consistent associations among men.
Keywords: Black or African American; Body Mass Index; Creatinine; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Longitudinal Studies; Male; Middle Aged; Obesity; Proportional Hazards Models; Renal Replacement Therapy; Sex Factors; Waist-Hip Ratio; White People

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Author Correction: High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2021)

Author Correction: Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2021)

Author Correction: Performance assessment of DNA sequencing platforms in the ABRF Next-Generation Sequencing Study. - Foox, Jonathan; Tighe, Scott W; Nicolet, Charles M; Zook, Justin M; Byrska-Bishop, Marta; Clarke, Wayne E; Khayat, Michael M; Mahmoud, Medhat; Laaguiby, Phoebe K; Herbert, Zachary T; Warner, Derek; Grills, George S; et al. (Nat Biotechnol, 2021)

Biallelic and monoallelic variants in PLXNA1 are implicated in a novel neurodevelopmental disorder with variable cerebral and eye anomalies. - Dworschak, Gabriel C; Punetha, Jaya; Kalanithy, Jeshurun C; Mingardo, Enrico; Erdem, Haktan B; Akdemir, Zeynep C; Karaca, Ender; Mitani, Tadahiro; Marafi, Dana; Fatih, Jawid M; Jhangiani, Shalini N; Hunter, Jill V; et al. (Genet Med, 2021)
PURPOSE: To investigate the effect of PLXNA1 variants on the phenotype of patients with autosomal dominant and recessive inheritance patterns and to functionally characterize the zebrafish homologs plxna1a and plxna1b during development. METHODS: We assembled ten patients from seven families with biallelic or de novo PLXNA1 variants. We describe genotype-phenotype correlations, investigated the variants by structural modeling, and used Morpholino knockdown experiments in zebrafish to characterize the embryonic role of plxna1a and plxna1b. RESULTS: Shared phenotypic features among patients include global developmental delay (9/10), brain anomalies (6/10), and eye anomalies (7/10). Notably, seizures were predominantly reported in patients with monoallelic variants. Structural modeling of missense variants in PLXNA1 suggests distortion in the native protein. Our zebrafish studies enforce an embryonic role of plxna1a and plxna1b in the development of the central nervous system and the eye. CONCLUSION: We propose that different biallelic and monoallelic variants in PLXNA1 result in a novel neurodevelopmental syndrome mainly comprising developmental delay, brain, and eye anomalies. We hypothesize that biallelic variants in the extracellular Plexin-A1 domains lead to impaired dimerization or lack of receptor molecules, whereas monoallelic variants in the intracellular Plexin-A1 domains might impair downstream signaling through a dominant-negative effect.
Keywords: Animals; Eye Abnormalities; Genetic Association Studies; Humans; Nerve Tissue Proteins; Neurodevelopmental Disorders; Phenotype; Receptors, Cell Surface; Zebrafish

Biallelic loss-of-function variants in the splicing regulator NSRP1 cause a severe neurodevelopmental disorder with spastic cerebral palsy and epilepsy. - Calame, Daniel G; Bakhtiari, Somayeh; Logan, Rachel; Coban-Akdemir, Zeynep; Du, Haowei; Mitani, Tadahiro; Fatih, Jawid M; Hunter, Jill V; Herman, Isabella; Pehlivan, Davut; Jhangiani, Shalini N; Person, Richard; et al. (Genet Med, 2021)
PURPOSE: Alternative splicing plays a critical role in mouse neurodevelopment, regulating neurogenesis, cortical lamination, and synaptogenesis, yet few human neurodevelopmental disorders are known to result from pathogenic variation in splicing regulator genes. Nuclear Speckle Splicing Regulator Protein 1 (NSRP1) is a ubiquitously expressed splicing regulator not known to underlie a Mendelian disorder. METHODS: Exome sequencing and rare variant family-based genomics was performed as a part of the Baylor-Hopkins Center for Mendelian Genomics Initiative. Additional families were identified via GeneMatcher. RESULTS: We identified six patients from three unrelated families with homozygous loss-of-function variants in NSRP1. Clinical features include developmental delay, epilepsy, variable microcephaly (Z-scores -0.95 to -5.60), hypotonia, and spastic cerebral palsy. Brain abnormalities included simplified gyral pattern, underopercularization, and/or vermian hypoplasia. Molecular analysis identified three pathogenic NSRP1 predicted loss-of-function variant alleles: c.1359_1362delAAAG (p.Glu455AlafsTer20), c.1272dupG (p.Lys425GlufsTer5), and c.52C>T (p.Gln18Ter). The two frameshift variants result in a premature termination codon in the last exon, and the mutant transcripts are predicted to escape nonsense mediated decay and cause loss of a C-terminal nuclear localization signal required for NSRP1 function. CONCLUSION: We establish NSRP1 as a gene for a severe autosomal recessive neurodevelopmental disease trait characterized by developmental delay, epilepsy, microcephaly, and spastic cerebral palsy.
Keywords: Cerebral Palsy; Epilepsy; Humans; Microcephaly; Neurodevelopmental Disorders; Nuclear Proteins; Pedigree; RNA Splicing

BinomiRare: A robust test for association of a rare genetic variant with a binary outcome for mixed models and any case-control proportion. - Sofer, Tamar; Lee, Jiwon; Kurniansyah, Nuzulul; Jain, Deepti; Laurie, Cecelia A; Gogarten, Stephanie M; Conomos, Matthew P; Heavner, Ben; Hu, Yao; Kooperberg, Charles; Haessler, Jeffrey; Vasan, Ramachandran S; et al. (HGG Adv, 2021)
Whole-genome sequencing (WGS) and whole-exome sequencing studies have become increasingly available and are being used to identify rare genetic variants associated with health and disease outcomes. Investigators routinely use mixed models to account for genetic relatedness or other clustering variables (e.g., family or household) when testing genetic associations. However, no existing tests of the association of a rare variant with a binary outcome in the presence of correlated data control the type 1 error where there are (1) few individuals harboring the rare allele, (2) a small proportion of cases relative to controls, and (3) covariates to adjust for. Here, we address all three issues in developing a framework for testing rare variant association with a binary trait in individuals harboring at least one risk allele. In this framework, we estimate outcome probabilities under the null hypothesis and then use them, within the individuals with at least one risk allele, to test variant associations. We extend the BinomiRare test, which was previously proposed for independent observations, and develop the Conway-Maxwell-Poisson (CMP) test and study their properties in simulations. We show that the BinomiRare test always controls the type 1 error, while the CMP test sometimes does not. We then use the BinomiRare test to test the association of rare genetic variants in target genes with small-vessel disease (SVD) stroke, short sleep, and venous thromboembolism (VTE), in whole-genome sequence data from the Trans-Omics for Precision Medicine (TOPMed) program.

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.
Keywords: Cardiometabolic Risk Factors; Chromosomes, Human, X; Eye Proteins; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Lipids; Male; Middle Aged; Nerve Tissue Proteins; Phenomics; Polymorphism, Single Nucleotide; Subcutaneous Tissue; Whole Genome Sequencing

Clinical, neuroimaging, and molecular spectrum of TECPR2-associated hereditary sensory and autonomic neuropathy with intellectual disability. - Neuser, Sonja; Brechmann, Barbara; Heimer, Gali; Brösse, Ines; Schubert, Susanna; O'Grady, Lauren; Zech, Michael; Srivastava, Siddharth; Sweetser, David A; Dincer, Yasemin; Mall, Volker; Winkelmann, Juliane; et al. (Hum Mutat, 2021)
Bi-allelic TECPR2 variants have been associated with a complex syndrome with features of both a neurodevelopmental and neurodegenerative disorder. Here, we provide a comprehensive clinical description and variant interpretation framework for this genetic locus. Through international collaboration, we identified 17 individuals from 15 families with bi-allelic TECPR2-variants. We systemically reviewed clinical and molecular data from this cohort and 11 cases previously reported. Phenotypes were standardized using Human Phenotype Ontology terms. A cross-sectional analysis revealed global developmental delay/intellectual disability, muscular hypotonia, ataxia, hyporeflexia, respiratory infections, and central/nocturnal hypopnea as core manifestations. A review of brain magnetic resonance imaging scans demonstrated a thin corpus callosum in 52%. We evaluated 17 distinct variants. Missense variants in TECPR2 are predominantly located in the N- and C-terminal regions containing β-propeller repeats. Despite constituting nearly half of disease-associated TECPR2 variants, classifying missense variants as (likely) pathogenic according to ACMG criteria remains challenging. We estimate a pathogenic variant carrier frequency of 1/1221 in the general and 1/155 in the Jewish Ashkenazi populations. Based on clinical, neuroimaging, and genetic data, we provide recommendations for variant reporting, clinical assessment, and surveillance/treatment of individuals with TECPR2-associated disorder. This sets the stage for future prospective natural history studies.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Cohort Studies; Cross-Sectional Studies; Family; Female; Hereditary Sensory and Autonomic Neuropathies; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Models, Molecular; Mutation, Missense; Nerve Tissue Proteins; Neuroimaging; Pedigree; Phenotype; Protein Conformation

Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2021)
Genetic discoveries of Alzheimer's disease are the drivers of our understanding, and together with polygenetic risk stratification can contribute towards planning of feasible and efficient preventive and curative clinical trials. We first perform a large genetic association study by merging all available case-control datasets and by-proxy study results (discovery n = 409,435 and validation size n = 58,190). Here, we add six variants associated with Alzheimer's disease risk (near APP, CHRNE, PRKD3/NDUFAF7, PLCG2 and two exonic variants in the SHARPIN gene). Assessment of the polygenic risk score and stratifying by APOE reveal a 4 to 5.5 years difference in median age at onset of Alzheimer's disease patients in APOE ɛ4 carriers. Because of this study, the underlying mechanisms of APP can be studied to refine the amyloid cascade and the polygenic risk score provides a tool to select individuals at high risk of Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Protein Precursor; Apolipoproteins E; Case-Control Studies; Cohort Studies; Datasets as Topic; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Male; Middle Aged; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors

Complicated Diagnosis and Treatment of HA20 due to Contiguous Gene Deletions involving 6q23.3. - Wu, Chung Wah; Sasa, Ghadir; Salih, Amanda; Nicholas, Sarah; Vogel, Tiphanie P; Cahill, Gina; Kuehn, Hye Sun; Rosenzweig, Sergio D; Zhou, Qing; Chinn, Ivan K; Bo Yuan (J Clin Immunol, 2021)
Keywords: Adolescent; Antibodies, Monoclonal, Humanized; Chromosomes, Human, Pair 6; Female; Gene Deletion; Haploinsufficiency; Hereditary Autoinflammatory Diseases; Humans; Tumor Necrosis Factor alpha-Induced Protein 3

Correction to: Diversity and evolution of the transposable element repertoire in arthropods with particular reference to insects. - Petersen, Malte; Armisén, David; Richard A Gibbs; Hering, Lars; Khila, Abderrahman; Mayer, Georg; Stephen Richards; Niehuis, Oliver; Misof, Bernhard (BMC Ecol Evol, 2021)

Cross-oncopanel study reveals high sensitivity and accuracy with overall analytical performance depending on genomic regions. - Gong, Binsheng; Li, Dan; Kusko, Rebecca; Novoradovskaya, Natalia; Zhang, Yifan; Wang, Shangzi; Pabón-Peña, Carlos; Zhang, Zhihong; Lai, Kevin; Cai, Wanshi; LoCoco, Jennifer S; Lader, Eric; et al. (Genome Biol, 2021)
BACKGROUND: Targeted sequencing using oncopanels requires comprehensive assessments of accuracy and detection sensitivity to ensure analytical validity. By employing reference materials characterized by the U.S. Food and Drug Administration-led SEquence Quality Control project phase2 (SEQC2) effort, we perform a cross-platform multi-lab evaluation of eight Pan-Cancer panels to assess best practices for oncopanel sequencing. RESULTS: All panels demonstrate high sensitivity across targeted high-confidence coding regions and variant types for the variants previously verified to have variant allele frequency (VAF) in the 5-20% range. Sensitivity is reduced by utilizing VAF thresholds due to inherent variability in VAF measurements. Enforcing a VAF threshold for reporting has a positive impact on reducing false positive calls. Importantly, the false positive rate is found to be significantly higher outside the high-confidence coding regions, resulting in lower reproducibility. Thus, region restriction and VAF thresholds lead to low relative technical variability in estimating promising biomarkers and tumor mutational burden. CONCLUSION: This comprehensive study provides actionable guidelines for oncopanel sequencing and clear evidence that supports a simplified approach to assess the analytical performance of oncopanels. It will facilitate the rapid implementation, validation, and quality control of oncopanels in clinical use.
Keywords: Biomarkers, Tumor; DNA Copy Number Variations; Genetic Testing; Genomics; Humans; Molecular Diagnostic Techniques; Mutation; Neoplasms; Oncogenes; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.
Keywords: Adolescent; Adult; Age of Onset; Child, Preschool; China; Cohort Studies; Exome; Exome Sequencing; Female; Genetic Predisposition to Disease; Humans; Male; Retrospective Studies; Scoliosis

DNA methylation patterns identify subgroups of pancreatic neuroendocrine tumors with clinical association. - Lakis, Vanessa; Lawlor, Rita T; Newell, Felicity; Patch, Ann-Marie; Mafficini, Andrea; Sadanandam, Anguraj; Koufariotis, Lambros T; Johnston, Rebecca L; Leonard, Conrad; Wood, Scott; Rusev, Borislav; Corbo, Vincenzo; et al. (Commun Biol, 2021)
Here we report the DNA methylation profile of 84 sporadic pancreatic neuroendocrine tumors (PanNETs) with associated clinical and genomic information. We identified three subgroups of PanNETs, termed T1, T2 and T3, with distinct patterns of methylation. The T1 subgroup was enriched for functional tumors and ATRX, DAXX and MEN1 wild-type genotypes. The T2 subgroup contained tumors with mutations in ATRX, DAXX and MEN1 and recurrent patterns of chromosomal losses in half of the genome with no association between regions with recurrent loss and methylation levels. T2 tumors were larger and had lower methylation in the MGMT gene body, which showed positive correlation with gene expression. The T3 subgroup harboured mutations in MEN1 with recurrent loss of chromosome 11, was enriched for grade G1 tumors and showed histological parameters associated with better prognosis. Our results suggest a role for methylation in both driving tumorigenesis and potentially stratifying prognosis in PanNETs.
Keywords: Biomarkers, Tumor; Carcinoma, Neuroendocrine; DNA Methylation; Epigenesis, Genetic; Epigenome; Epigenomics; Genetic Predisposition to Disease; Humans; Neoplasm Grading; Pancreatic Neoplasms; Phenotype; Tumor Burden

Epigenome-wide association study of mitochondrial genome copy number. - Wang, Penglong; Castellani, Christina A; Yao, Jie; Huan, Tianxiao; Bielak, Lawrence F; Zhao, Wei; Haessler, Jeffrey; Joehanes, Roby; Sun, Xianbang; Guo, Xiuqing; Longchamps, Ryan J; Manson, JoAnn E; et al. (Hum Mol Genet, 2021)
We conducted cohort- and race-specific epigenome-wide association analyses of mitochondrial deoxyribonucleic acid (mtDNA) copy number (mtDNA CN) measured in whole blood from participants of African and European origins in five cohorts (n = 6182, mean age = 57-67 years, 65% women). In the meta-analysis of all the participants, we discovered 21 mtDNA CN-associated DNA methylation sites (CpG) (P < 1 × 10-7), with a 0.7-3.0 standard deviation increase (3 CpGs) or decrease (18 CpGs) in mtDNA CN corresponding to a 1% increase in DNA methylation. Several significant CpGs have been reported to be associated with at least two risk factors (e.g. chronological age or smoking) for cardiovascular disease (CVD). Five genes [PR/SET domain 16, nuclear receptor subfamily 1 group H member 3 (NR1H3), DNA repair protein, DNA polymerase kappa and decaprenyl-diphosphate synthase subunit 2], which harbor nine significant CpGs, are known to be involved in mitochondrial biosynthesis and functions. For example, NR1H3 encodes a transcription factor that is differentially expressed during an adipose tissue transition. The methylation level of cg09548275 in NR1H3 was negatively associated with mtDNA CN (effect size = -1.71, P = 4 × 10-8) and was positively associated with the NR1H3 expression level (effect size = 0.43, P = 0.0003), which indicates that the methylation level in NR1H3 may underlie the relationship between mtDNA CN, the NR1H3 transcription factor and energy expenditure. In summary, the study results suggest that mtDNA CN variation in whole blood is associated with DNA methylation levels in genes that are involved in a wide range of mitochondrial activities. These findings will help reveal molecular mechanisms between mtDNA CN and CVD.
Keywords: Aged; DNA Copy Number Variations; DNA Methylation; DNA, Mitochondrial; Epigenome; Female; Genome, Mitochondrial; Humans; Male; Middle Aged

The Exceptional Responders Initiative: Feasibility of a National Cancer Institute Pilot Study. - Conley, Barbara A; Staudt, Lou; Takebe, Naoko; David A Wheeler; Wang, Linghua; Cardenas, Maria F; Korchina, Viktoriya; Zenklusen, Jean Claude; McShane, Lisa M; Tricoli, James V; Williams, Paul M; Lubensky, Irina; et al. (J Natl Cancer Inst, 2021)
BACKGROUND: Tumor molecular profiling from patients experiencing exceptional responses to systemic therapy may provide insights into cancer biology and improve treatment tailoring. This pilot study evaluates the feasibility of identifying exceptional responders retrospectively, obtaining pre-exceptional response treatment tumor tissues, and analyzing them with state-of-the-art molecular analysis tools to identify potential molecular explanations for responses. METHODS: Exceptional response was defined as partial (PR) or complete (CR) response to a systemic treatment with population PR or CR rate less than 10% or an unusually long response (eg, duration >3 times published median). Cases proposed by patients' clinicians were reviewed by clinical and translational experts. Tumor and normal tissue (if possible) were profiled with whole exome sequencing and, if possible, targeted deep sequencing, RNA sequencing, methylation arrays, and immunohistochemistry. Potential germline mutations were tracked for relevance to disease. RESULTS: Cases reflected a variety of tumors and standard and investigational treatments. Of 520 cases, 476 (91.5%) were accepted for further review, and 222 of 476 (46.6%) proposed cases met requirements as exceptional responders. Clinical data were obtained from 168 of 222 cases (75.7%). Tumor was provided from 130 of 168 cases (77.4%). Of 117 of the 130 (90.0%) cases with sufficient nucleic acids, 109 (93.2%) were successfully analyzed; 6 patients had potentially actionable germline mutations. CONCLUSION: Exceptional responses occur with standard and investigational treatment. Retrospective identification of exceptional responders, accessioning, and sequencing of pretreatment archived tissue is feasible. Data from molecular analyses of tumors, particularly when combining results from patients who received similar treatments, may elucidate molecular bases for exceptional responses.
Keywords: Adult; Aged; Aged, 80 and over; Exome Sequencing; Feasibility Studies; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; National Cancer Institute (U.S.); Neoplasms; Pilot Projects; Precision Medicine; Retrospective Studies; Sequence Analysis, RNA; Transcriptome; United States

Exome sequencing reveals genetic architecture in patients with isolated or syndromic short stature. - Fan, Xin; Zhao, Sen; Yu, Chenxi; Wu, Di; Yan, Zihui; Fan, Lijun; Song, Yanning; Wang, Yi; Li, Chuan; Ming, Yue; Gui, Baoheng; Niu, Yuchen; et al. (J Genet Genomics, 2021)
Short stature is among the most common endocrinological disease phenotypes of childhood and may occur as an isolated finding or in conjunction with other clinical manifestations. Although the diagnostic utility of clinical genetic testing in short stature has been implicated, the genetic architecture and the utility of genomic studies such as exome sequencing (ES) in a sizable cohort of patients with short stature have not been investigated systematically. In this study, we recruited 561 individuals with short stature from two centers in China during a 4-year period. We performed ES for all patients and available parents. All patients were retrospectively divided into two groups: an isolated short stature group (group I, n = 257) and an apparently syndromic short stature group (group II, n = 304). Causal variants were identified in 135 of 561 (24.1%) patients. In group I, 29 of 257 (11.3%) of the patients were solved by variants in 24 genes. In group II, 106 of 304 (34.9%) patients were solved by variants in 57 genes. Genes involved in fundamental cellular process played an important role in the genetic architecture of syndromic short stature. Distinct genetic architectures and pathophysiological processes underlie isolated and syndromic short stature.
Keywords: Adolescent; Alleles; Child; Child, Preschool; China; Disease Management; DNA Copy Number Variations; Dwarfism; Exome; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Genotype; Humans; Male; Mutation; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Syndrome

Exome sequencing reveals predominantly de novo variants in disorders with intellectual disability (ID) in the founder population of Finland. - Järvelä, Irma; Määttä, Tuomo; Acharya, Anushree; Leppälä, Juha; Jhangiani, Shalini N; Arvio, Maria; Siren, Auli; Kankuri-Tammilehto, Minna; Kokkonen, Hannaleena; Palomäki, Maarit; Varilo, Teppo; Fang, Mary; et al. (Hum Genet, 2021)
The genetics of autosomal recessive intellectual disability (ARID) has mainly been studied in consanguineous families, however, founder populations may also be of interest to study intellectual disability (ID) and the contribution of ARID. Here, we used a genotype-driven approach to study the genetic landscape of ID in the founder population of Finland. A total of 39 families with syndromic and non-syndromic ID were analyzed using exome sequencing, which revealed a variant in a known ID gene in 27 families. Notably, 75% of these variants in known ID genes were de novo or suspected de novo (64% autosomal dominant; 11% X-linked) and 25% were inherited (14% autosomal recessive; 7% X-linked; and 4% autosomal dominant). A dual molecular diagnosis was suggested in two families (5%). Via additional analysis and molecular testing, we identified three cases with an abnormal molecular karyotype, including chr21q22.12q22.2 uniparental disomy with a mosaic interstitial 2.7 Mb deletion covering DYRK1A and KCNJ6. Overall, a pathogenic or likely pathogenic variant was identified in 64% (25/39) of the families. Last, we report an alternate inheritance model for 3 known ID genes (UBA7, DDX47, DHX58) and discuss potential candidate genes for ID, including SYPL1 and ERGIC3 with homozygous founder variants and de novo variants in POLR2F and DNAH3. In summary, similar to other European populations, de novo variants were the most common variants underlying ID in the studied Finnish population, with limited contribution of ARID to ID etiology, though mainly driven by founder and potential founder variation in the latter case.
Keywords: Exome; Exome Sequencing; Family; Female; Finland; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Homozygote; Humans; Intellectual Disability; Male; Pedigree

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2021)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.
Keywords: Blood Pressure; Epistasis, Genetic; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Polymorphism, Single Nucleotide

Genetically determined NLRP3 inflammasome activation associates with systemic inflammation and cardiovascular mortality. - Schunk, Stefan J; Kleber, Marcus E; Marz, Winfried; Pang, Shichao; Zewinger, Stephen; Triem, Sarah; Ege, Philipp; Reichert, Matthias C; Krawczyk, Marcin; Weber, Susanne N; Jaumann, Isabella; Schmit, David; et al. (Eur Heart J, 2021)
AIMS: Inflammation plays an important role in cardiovascular disease (CVD) development. The NOD-like receptor protein-3 (NLRP3) inflammasome contributes to the development of atherosclerosis in animal models. Components of the NLRP3 inflammasome pathway such as interleukin-1β can therapeutically be targeted. Associations of genetically determined inflammasome-mediated systemic inflammation with CVD and mortality in humans are unknown. METHODS AND RESULTS: We explored the association of genetic NLRP3 variants with prevalent CVD and cardiovascular mortality in 538 167 subjects on the individual participant level in an explorative gene-centric approach without performing multiple testing. Functional relevance of single-nucleotide polymorphisms on NLRP3 inflammasome activation has been evaluated in monocyte-enriched peripheral blood mononuclear cells (PBMCs). Genetic analyses identified the highly prevalent (minor allele frequency 39.9%) intronic NLRP3 variant rs10754555 to affect NLRP3 gene expression. rs10754555 carriers showed significantly higher C-reactive protein and serum amyloid A plasma levels. Carriers of the G allele showed higher NLRP3 inflammasome activation in isolated human PBMCs. In carriers of the rs10754555 variant, the prevalence of coronary artery disease was significantly higher as compared to non-carriers with a significant interaction between rs10754555 and age. Importantly, rs10754555 carriers had significantly higher risk for cardiovascular mortality during follow-up. Inflammasome inducers (e.g. urate, triglycerides, apolipoprotein C3) modulated the association between rs10754555 and mortality. CONCLUSION: The NLRP3 intronic variant rs10754555 is associated with increased systemic inflammation, inflammasome activation, prevalent coronary artery disease, and mortality. This study provides evidence for a substantial role of genetically driven systemic inflammation in CVD and highlights the NLRP3 inflammasome as a therapeutic target.
Keywords: Cardiovascular Diseases; Humans; Inflammasomes; Inflammation; Leukocytes, Mononuclear; NLR Family, Pyrin Domain-Containing 3 Protein

Genome-wide association study of circulating interleukin 6 levels identifies novel loci. - Ahluwalia, Tarunveer S; Prins, Bram P; Abdollahi, Mohammadreza; Armstrong, Nicola J; Aslibekyan, Stella; Bain, Lisa; Jefferis, Barbara; Baumert, Jens; Beekman, Marian; Ben-Shlomo, Yoav; Bis, Joshua C; Mitchell, Braxton D; et al. (Hum Mol Genet, 2021)
Interleukin 6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on chromosome (Chr) 2q14, (Pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (Pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (Pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.
Keywords: Cohort Studies; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; HLA-DRB1 Chains; Humans; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Interleukin-6; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; White People

Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women. - Jones, Garan; Trajanoska, Katerina; Santanasto, Adam J; Stringa, Najada; Kuo, Chia-Ling; Atkins, Janice L; Lewis, Joshua R; Duong, ThuyVy; Hong, Shengjun; Biggs, Mary L; Luan, Jian'an; Sarnowski, Chloe; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10), arthritis (GDF5 p = 4 × 10), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 5; HLA-DQ alpha-Chains; Humans; Male; Middle Aged; Muscle Strength; Muscle Weakness; Polymorphism, Single Nucleotide; Sarcopenia

Genomic analysis and preclinical xenograft model development identify potential therapeutic targets for MYOD1-mutant soft-tissue sarcoma of childhood. - Ting, Michelle A; Reuther, Jacquelyn; Chandramohan, Raghu; Voicu, Horatiu; Gandhi, Ilavarasi; Liu, Meng; Cortes-Santiago, Nahir; Foster, Jennifer H; Hicks, John; Nuchtern, Jed; Scollon, Sarah; Plon, Sharon E; et al. (J Pathol, 2021)
The myogenic differentiation 1 gene (MYOD1) p.L122R somatic mutation was first discovered in a subset of clinically aggressive embryonal rhabdomyosarcomas and has since been described in both pediatric and adult spindle cell/sclerosing rhabdomyosarcomas. Relatively little is known about the clinical, molecular, and histopathological features of these tumors in children. In order to further characterize the genomic and clinical features of pediatric MYOD1-mutant sarcomas, we evaluated a cohort of soft-tissue sarcoma patients treated at Texas Children's Hospital. Tumor DNA was subjected to next-generation panel sequencing and/or Sanger sequencing of the MYOD1 hotspot mutation. The MYOD1 p.L122R mutation was identified in six tumors, with a variant allele fraction greater than 0.8 in three cases, suggestive of loss of heterozygosity. One sclerosing rhabdomyosarcoma lacking the MYOD1 hotspot mutation was observed to have a MYOD1 copy number gain, also with evidence of loss of heterozygosity. Cancer gene panel sequencing revealed potentially targetable alterations in six of seven (86%) patients with MYOD1 alterations, including four patients with an alteration in the PI3K-AKT pathway: two hotspot PIK3CA mutations and deletions in PTEN and TSC2. On histopathologic review, MYOD1-altered tumors exhibited spindle and/or round cells and varying degrees of hyaline sclerosis. At last follow-up, six patients had died of disease and the seventh progressed early and was subsequently lost to follow-up. Both pre- and post-therapy patient-derived xenograft models were generated from one patient's tumor. These models were confirmed to harbor the MYOD1 and PIK3CA mutations seen in the primary tumor and were shown to be sensitive to PI3K/mTOR inhibition in vitro and in vivo. In conclusion, this study adds to recent reports describing the clinicopathologic and genomic features of MYOD1-altered soft-tissue sarcomas in children, including dismal prognosis and potential molecular targets for therapy. The novel preclinical models developed will facilitate further biological and preclinical study of this rare and aggressive tumor. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Keywords: Adolescent; Animals; Antineoplastic Agents; Child; Female; Genomics; Humans; Imidazoles; Male; Mice; Mutation; MyoD Protein; Quinolines; Rhabdomyosarcoma; Soft Tissue Neoplasms; Xenograft Model Antitumor Assays; Young Adult

The genomic basis of evolutionary differentiation among honey bees. - Fouks, Bertrand; Brand, Philipp; Nguyen, Hung N; Herman, Jacob; Camara, Francisco; Ence, Daniel; Hagen, Darren E; Hoff, Katharina J; Nachweide, Stefanie; Romoth, Lars; Walden, Kimberly K O; Guigó, Roderic; et al. (Genome Res, 2021)
In contrast to the western honey bee, , other honey bee species have been largely neglected despite their importance and diversity. The genetic basis of the evolutionary diversification of honey bees remains largely unknown. Here, we provide a genome-wide comparison of three honey bee species, each representing one of the three subgenera of honey bees, namely the dwarf (), giant (), and cavity-nesting () honey bees with bumblebees as an outgroup. Our analyses resolve the phylogeny of honey bees with the dwarf honey bees diverging first. We find that evolution of increased eusocial complexity in proceeds via increases in the complexity of gene regulation, which is in agreement with previous studies. However, this process seems to be related to pathways other than transcriptional control. Positive selection patterns across reveal a trade-off between maintaining genome stability and generating genetic diversity, with a rapidly evolving piRNA pathway leading to genomes depleted of transposable elements, and a rapidly evolving DNA repair pathway associated with high recombination rates in all species. Diversification within is accompanied by positive selection in several genes whose putative functions present candidate mechanisms for lineage-specific adaptations, such as migration, immunity, and nesting behavior.

Genomic considerations for FHIR®; eMERGE implementation lessons. - Mullai Murugan; Babb, Lawrence J; Overby Taylor, Casey; Rasmussen, Luke V; Freimuth, Robert R; Eric Venner; Yan, Fei; Yi, Victoria; Granite, Stephen J; Zouk, Hana; Aronson, Samuel J; Power, Kevin; et al. (J Biomed Inform, 2021)
Structured representation of clinical genetic results is necessary for advancing precision medicine. The Electronic Medical Records and Genomics (eMERGE) Network's Phase III program initially used a commercially developed XML message format for standardized and structured representation of genetic results for electronic health record (EHR) integration. In a desire to move towards a standard representation, the network created a new standardized format based upon Health Level Seven Fast Healthcare Interoperability Resources (HL7® FHIR®), to represent clinical genomics results. These new standards improve the utility of HL7® FHIR® as an international healthcare interoperability standard for management of genetic data from patients. This work advances the establishment of standards that are being designed for broad adoption in the current health information technology landscape.
Keywords: Electronic Health Records; Genomics; Health Level Seven; Humans; Medical Informatics; Precision Medicine

Haploinsufficiency of ARFGEF1 is associated with developmental delay, intellectual disability, and epilepsy with variable expressivity. - Thomas, Quentin; Gautier, Thierry; Marafi, Dana; Besnard, Thomas; Willems, Marjolaine; Moutton, Sebastien; Isidor, Bertand; Cogné, Benjamin; Conrad, Solène; Tenconi, Romano; Iascone, Maria; Sorlin, Arthur; et al. (Genet Med, 2021)
PURPOSE: ADP ribosylation factor guanine nucleotide exchange factors (ARFGEFs) are a family of proteins implicated in cellular trafficking between the Golgi apparatus and the plasma membrane through vesicle formation. Among them is ARFGEF1/BIG1, a protein involved in axon elongation, neurite development, and polarization processes. ARFGEF1 has been previously suggested as a candidate gene for different types of epilepsies, although its implication in human disease has not been well characterized. METHODS: International data sharing, in silico predictions, and in vitro assays with minigene study, western blot analyses, and RNA sequencing. RESULTS: We identified 13 individuals with heterozygous likely pathogenic variants in ARFGEF1. These individuals displayed congruent clinical features of developmental delay, behavioral problems, abnormal findings on brain magnetic resonance image (MRI), and epilepsy for almost half of them. While nearly half of the cohort carried de novo variants, at least 40% of variants were inherited from mildly affected parents who were clinically re-evaluated by reverse phenotyping. Our in silico predictions and in vitro assays support the contention that ARFGEF1-related conditions are caused by haploinsufficiency, and are transmitted in an autosomal dominant fashion with variable expressivity. CONCLUSION: We provide evidence that loss-of-function variants in ARFGEF1 are implicated in sporadic and familial cases of developmental delay with or without epilepsy.
Keywords: Epilepsy; Guanine Nucleotide Exchange Factors; Haploinsufficiency; Heterozygote; Humans; Intellectual Disability

Lifestyle Risk Score: handling missingness of individual lifestyle components in meta-analysis of gene-by-lifestyle interactions. - Xu, Hanfei; Schwander, Karen; Brown, Michael R; Wang, Wenyi; Waken, R J; Eric Boerwinkle; Cupples, L Adrienne; de Las Fuentes, Lisa; van Heemst, Diana; Osazuwa-Peters, Oyomoare; de Vries, Paul S; van Dijk, Ko Willems; et al. (Eur J Hum Genet, 2021)
Recent studies consider lifestyle risk score (LRS), an aggregation of multiple lifestyle exposures, in identifying association of gene-lifestyle interaction with disease traits. However, not all cohorts have data on all lifestyle factors, leading to increased heterogeneity in the environmental exposure in collaborative meta-analyses. We compared and evaluated four approaches (Naïve, Safe, Complete and Moderator Approaches) to handle the missingness in LRS-stratified meta-analyses under various scenarios. Compared to "benchmark" results with all lifestyle factors available for all cohorts, the Complete Approach, which included only cohorts with all lifestyle components, was underpowered due to lower sample size, and the Naïve Approach, which utilized all available data and ignored the missingness, was slightly inflated. The Safe Approach, which used all data in LRS-exposed group and only included cohorts with all lifestyle factors available in the LRS-unexposed group, and the Moderator Approach, which handled missingness via moderator meta-regression, were both slightly conservative and yielded almost identical p values. We also evaluated the performance of the Safe Approach under different scenarios. We observed that the larger the proportion of cohorts without missingness included, the more accurate the results compared to "benchmark" results. In conclusion, we generally recommend the Safe Approach, a straightforward and non-inflated approach, to handle heterogeneity among cohorts in the LRS based genome-wide interaction meta-analyses.
Keywords: Cardiometabolic Risk Factors; Gene-Environment Interaction; Genome-Wide Association Study; Healthy Lifestyle; Humans; Hypertension; Obesity

Loss of C2orf69 defines a fatal autoinflammatory syndrome in humans and zebrafish that evokes a glycogen-storage-associated mitochondriopathy. - Wong, Hui Hui; Seet, Sze Hwee; Maier, Michael; Gurel, Ayse; Traspas, Ricardo Moreno; Lee, Cheryl; Zhang, Shan; Talim, Beril; Loh, Abigail Y T; Chia, Crystal Y; Teoh, Tze Shin; Sng, Danielle; et al. (Am J Hum Genet, 2021)
Human C2orf69 is an evolutionarily conserved gene whose function is unknown. Here, we report eight unrelated families from which 20 children presented with a fatal syndrome consisting of severe autoinflammation and progredient leukoencephalopathy with recurrent seizures; 12 of these subjects, whose DNA was available, segregated homozygous loss-of-function C2orf69 variants. C2ORF69 bears homology to esterase enzymes, and orthologs can be found in most eukaryotic genomes, including that of unicellular phytoplankton. We found that endogenous C2ORF69 (1) is loosely bound to mitochondria, (2) affects mitochondrial membrane potential and oxidative respiration in cultured neurons, and (3) controls the levels of the glycogen branching enzyme 1 (GBE1) consistent with a glycogen-storage-associated mitochondriopathy. We show that CRISPR-Cas9-mediated inactivation of zebrafish C2orf69 results in lethality by 8 months of age due to spontaneous epileptic seizures, which is preceded by persistent brain inflammation. Collectively, our results delineate an autoinflammatory Mendelian disorder of C2orf69 deficiency that disrupts the development/homeostasis of the immune and central nervous systems.
Keywords: Animals; Biological Evolution; Cell Line; CRISPR-Cas Systems; Encephalitis; Female; Genes, Recessive; Glycogen; Humans; Inflammation; Male; Membrane Proteins; Mitochondrial Diseases; Pedigree; Seizures; Zebrafish

Molecular Features of Cancers Exhibiting Exceptional Responses to Treatment. - David A Wheeler; Takebe, Naoko; Hinoue, Toshinori; Hoadley, Katherine A; Cardenas, Maria F; Hamilton, Alina M; Laird, Peter W; Wang, Linghua; Johnson, Adrienne; Dewal, Ninad; Miller, Vincent; Piñeyro, David; et al. (Cancer Cell, 2021)
A small fraction of cancer patients with advanced disease survive significantly longer than patients with clinically comparable tumors. Molecular mechanisms for exceptional responses to therapy have been identified by genomic analysis of tumor biopsies from individual patients. Here, we analyzed tumor biopsies from an unbiased cohort of 111 exceptional responder patients using multiple platforms to profile genetic and epigenetic aberrations as well as the tumor microenvironment. Integrative analysis uncovered plausible mechanisms for the therapeutic response in nearly a quarter of the patients. The mechanisms were assigned to four broad categories-DNA damage response, intracellular signaling, immune engagement, and genetic alterations characteristic of favorable prognosis-with many tumors falling into multiple categories. These analyses revealed synthetic lethal relationships that may be exploited therapeutically and rare genetic lesions that favor therapeutic success, while also providing a wealth of testable hypotheses regarding oncogenic mechanisms that may influence the response to cancer therapy.
Keywords: Antineoplastic Agents; Biopsy; Epigenesis, Genetic; Female; Gene Regulatory Networks; Genetic Variation; Genomics; Humans; Male; Neoplasms; Prognosis; Survival Analysis; Treatment Outcome; Tumor Microenvironment

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.
Keywords: Blood Pressure; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Polymorphism, Single Nucleotide; Sleep

Neuropeptide S receptor 1 is a nonhormonal treatment target in endometriosis. - Tapmeier, Thomas T; Rahmioglu, Nilufer; Lin, Jianghai; De Leo, Bianca; Obendorf, Maik; Raveendran, Muthuswamy; Fischer, Oliver M; Bafligil, Cemsel; Guo, Manman; R. Alan Harris; Hess-Stumpp, Holger; Laux-Biehlmann, Alexis; et al. (Sci Transl Med, 2021)
Endometriosis is a common chronic inflammatory condition causing pelvic pain and infertility in women, with limited treatment options and 50% heritability. We leveraged genetic analyses in two species with spontaneous endometriosis, humans and the rhesus macaque, to uncover treatment targets. We sequenced DNA from 32 human families contributing to a genetic linkage signal on chromosome 7p13-15 and observed significant overrepresentation of predicted deleterious low-frequency coding variants in , the gene encoding neuropeptide S receptor 1, in cases (predominantly stage III/IV) versus controls ( = 7.8 × 10). Significant linkage to the region orthologous to human 7p13-15 was replicated in a pedigree of 849 rhesus macaques ( = 0.0095). Targeted association analyses in 3194 surgically confirmed, unrelated cases and 7060 controls revealed that a common insertion/deletion variant, rs142885915, was significantly associated with stage III/IV endometriosis ( = 5.2 × 10; odds ratio, 1.23; 95% CI, 1.09 to 1.39). Immunohistochemistry, qRT-PCR, and flow cytometry experiments demonstrated that NPSR1 was expressed in glandular epithelium from eutopic and ectopic endometrium, and on monocytes in peritoneal fluid. The NPSR1 inhibitor SHA 68R blocked NPSR1-mediated signaling, proinflammatory TNF-α release, and monocyte chemotaxis in vitro ( < 0.01), and led to a significant reduction of inflammatory cell infiltrate and abdominal pain ( < 0.05) in a mouse model of peritoneal inflammation as well as in a mouse model of endometriosis. We conclude that the NPSR1/NPS system is a genetically validated, nonhormonal target for the treatment of endometriosis with likely increased relevance to stage III/IV disease.
Keywords: Animals; Endometriosis; Endometrium; Female; Humans; Macaca mulatta; Mice; Receptors, G-Protein-Coupled; Tumor Necrosis Factor-alpha

NMIHBA results from hypomorphic PRUNE1 variants that lack short-chain exopolyphosphatase activity. - Nistala, Harikiran; Dronzek, John; Gonzaga-Jauregui, Claudia; Chim, Shek Man; Rajamani, Saathyaki; Nuwayhid, Samer; Delgado, Dennis; Burke, Elizabeth; Karaca, Ender; Franklin, Matthew C; Sarangapani, Prasad; Podgorski, Michael; et al. (Hum Mol Genet, 2021)
Neurodevelopmental disorder with microcephaly, hypotonia and variable brain anomalies (NMIHBA) is an autosomal recessive neurodevelopmental and neurodegenerative disorder characterized by global developmental delay and severe intellectual disability. Microcephaly, progressive cortical atrophy, cerebellar hypoplasia and delayed myelination are neurological hallmarks in affected individuals. NMIHBA is caused by biallelic variants in PRUNE1 encoding prune exopolyphosphatase 1. We provide in-depth clinical description of two affected siblings harboring compound heterozygous variant alleles, c.383G > A (p.Arg128Gln), c.520G > T (p.Gly174*) in PRUNE1. To gain insights into disease biology, we biochemically characterized missense variants within the conserved N-terminal aspartic acid-histidine-histidine (DHH) motif and provide evidence that they result in the destabilization of protein structure and/or loss of exopolyphosphatase activity. Genetic ablation of Prune1 results in midgestational lethality in mice, associated with perturbations to embryonic growth and vascular development. Our findings suggest that NMIHBA results from hypomorphic variant alleles in humans and underscore the potential key role of PRUNE1 exopolyphoshatase activity in neurodevelopment.
Keywords: Acid Anhydride Hydrolases; Alleles; Animals; Child, Preschool; Female; Humans; Infant; Intellectual Disability; Male; Mice; Microcephaly; Muscle Hypotonia; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Phosphoric Monoester Hydrolases

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (PLoS One, 2021)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity among samples. Mixed allelic frequencies along the 20kb ORF1ab gene in one sample, suggested the presence of a defective viral RNA species subpopulation maintained in mixture with functional RNA in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.
Keywords: COVID-19; DNA, Complementary; Gene Frequency; Genetic Variation; Genome, Viral; Humans; Open Reading Frames; Real-Time Polymerase Chain Reaction; RNA, Viral; SARS-CoV-2; Sequence Analysis, DNA; Viral Load

Origins and Long-Term Patterns of Copy-Number Variation in Rhesus Macaques. - Thomas, Gregg W C; Wang, Richard J; Nguyen, Jelena; R. Alan Harris; Raveendran, Muthuswamy; Jeffrey Rogers; Hahn, Matthew W (Mol Biol Evol, 2021)
Mutations play a key role in the development of disease in an individual and the evolution of traits within species. Recent work in humans and other primates has clarified the origins and patterns of single-nucleotide variants, showing that most arise in the father's germline during spermatogenesis. It remains unknown whether larger mutations, such as deletions and duplications of hundreds or thousands of nucleotides, follow similar patterns. Such mutations lead to copy-number variation (CNV) within and between species, and can have profound effects by deleting or duplicating genes. Here, we analyze patterns of CNV mutations in 32 rhesus macaque individuals from 14 parent-offspring trios. We find the rate of CNV mutations per generation is low (less than one per genome) and we observe no correlation between parental age and the number of CNVs that are passed on to offspring. We also examine segregating CNVs within the rhesus macaque sample and compare them to a similar data set from humans, finding that both species have far more segregating deletions than duplications. We contrast this with long-term patterns of gene copy-number evolution between 17 mammals, where the proportion of deletions that become fixed along the macaque lineage is much smaller than the proportion of segregating deletions. These results suggest purifying selection acting on deletions, such that the majority of them are removed from the population over time. Rhesus macaques are an important biomedical model organism, so these results will aid in our understanding of this species and the disease models it supports.
Keywords: Animals; DNA Copy Number Variations; Female; Gene Duplication; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Mutation; Selection, Genetic; Sequence Deletion; Whole Genome Sequencing

Performance assessment of DNA sequencing platforms in the ABRF Next-Generation Sequencing Study. - Foox, Jonathan; Tighe, Scott W; Nicolet, Charles M; Zook, Justin M; Byrska-Bishop, Marta; Clarke, Wayne E; Khayat, Michael M; Mahmoud, Medhat; Laaguiby, Phoebe K; Herbert, Zachary T; Warner, Derek; Grills, George S; et al. (Nat Biotechnol, 2021)
Assessing the reproducibility, accuracy and utility of massively parallel DNA sequencing platforms remains an ongoing challenge. Here the Association of Biomolecular Resource Facilities (ABRF) Next-Generation Sequencing Study benchmarks the performance of a set of sequencing instruments (HiSeq/NovaSeq/paired-end 2 × 250-bp chemistry, Ion S5/Proton, PacBio circular consensus sequencing (CCS), Oxford Nanopore Technologies PromethION/MinION, BGISEQ-500/MGISEQ-2000 and GS111) on human and bacterial reference DNA samples. Among short-read instruments, HiSeq 4000 and X10 provided the most consistent, highest genome coverage, while BGI/MGISEQ provided the lowest sequencing error rates. The long-read instrument PacBio CCS had the highest reference-based mapping rate and lowest non-mapping rate. The two long-read platforms PacBio CCS and PromethION/MinION showed the best sequence mapping in repeat-rich areas and across homopolymers. NovaSeq 6000 using 2 × 250-bp read chemistry was the most robust instrument for capturing known insertion/deletion events. This study serves as a benchmark for current genomics technologies, as well as a resource to inform experimental design and next-generation sequencing variant calling.
Keywords: Base Pair Mismatch; Benchmarking; DNA; DNA, Bacterial; Genome, Bacterial; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

Population sequencing data reveal a compendium of mutational processes in the human germ line. - Seplyarskiy, Vladimir B; Soldatov, Ruslan A; Koch, Evan; McGinty, Ryan J; Goldmann, Jakob M; Hernandez, Ryan D; Barnes, Kathleen; Correa, Adolfo; Burchard, Esteban G; Ellinor, Patrick T; McGarvey, Stephen T; Mitchell, Braxton D; et al. (Science, 2021)
Biological mechanisms underlying human germline mutations remain largely unknown. We statistically decompose variation in the rate and spectra of mutations along the genome using volume-regularized nonnegative matrix factorization. The analysis of a sequencing dataset (TOPMed) reveals nine processes that explain the variation in mutation properties between loci. We provide a biological interpretation for seven of these processes. We associate one process with bulky DNA lesions that are resolved asymmetrically with respect to transcription and replication. Two processes track direction of replication fork and replication timing, respectively. We identify a mutagenic effect of active demethylation primarily acting in regulatory regions and a mutagenic effect of long interspersed nuclear elements. We localize a mutagenic process specific to oocytes from population sequencing data. This process appears transcriptionally asymmetric.
Keywords: Algorithms; CpG Islands; DNA Damage; DNA Demethylation; DNA Mutational Analysis; DNA Replication; Genetic Variation; Genome, Human; Germ Cells; Germ-Line Mutation; Humans; Long Interspersed Nucleotide Elements; Mutagenesis; Oocytes; Transcription, Genetic

Publisher Correction: Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals. - Surendran, Praveen; Feofanova, Elena V; Lahrouchi, Najim; Ntalla, Ioanna; Karthikeyan, Savita; Cook, James; Chen, Lingyan; Mifsud, Borbala; Yao, Chen; Kraja, Aldi T; Cartwright, James H; Hellwege, Jacklyn N; et al. (Nat Genet, 2021)

Robust, flexible, and scalable tests for Hardy-Weinberg equilibrium across diverse ancestries. - Kwong, Alan M; Blackwell, Thomas W; LeFaive, Jonathon; de Andrade, Mariza; Barnard, John; Barnes, Kathleen C; Blangero, John; Eric Boerwinkle; Burchard, Esteban G; Cade, Brian E; Chasman, Daniel I; Chen, Han; et al. (Genetics, 2021)
Traditional Hardy-Weinberg equilibrium (HWE) tests (the χ2 test and the exact test) have long been used as a metric for evaluating genotype quality, as technical artifacts leading to incorrect genotype calls often can be identified as deviations from HWE. However, in data sets composed of individuals from diverse ancestries, HWE can be violated even without genotyping error, complicating the use of HWE testing to assess genotype data quality. In this manuscript, we present the Robust Unified Test for HWE (RUTH) to test for HWE while accounting for population structure and genotype uncertainty, and to evaluate the impact of population heterogeneity and genotype uncertainty on the standard HWE tests and alternative methods using simulated and real sequence data sets. Our results demonstrate that ignoring population structure or genotype uncertainty in HWE tests can inflate false-positive rates by many orders of magnitude. Our evaluations demonstrate different tradeoffs between false positives and statistical power across the methods, with RUTH consistently among the best across all evaluations. RUTH is implemented as a practical and scalable software tool to rapidly perform HWE tests across millions of markers and hundreds of thousands of individuals while supporting standard VCF/BCF formats. RUTH is publicly available at https://www.github.com/statgen/ruth.
Keywords: Alleles; Gene Frequency; Genetics, Population; Genotype; Humans; Linkage Disequilibrium; Models, Genetic; Models, Statistical; Phenotype; Software

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.
Keywords: Cytochrome P-450 CYP2D6; Genetic Variation; Genome, Human; Genomics; Haplotypes; Heterozygote; Humans; INDEL Mutation; Loss of Function Mutation; Mutagenesis; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Population Density; Precision Medicine; Quality Control; Sample Size; United States; Whole Genome Sequencing

Sequencing of a central nervous system tumor demonstrates cancer transmission in an organ transplant. - Marie-Claude Gingras; Aniko Sabo; Cardenas, Maria; Rana, Abbas; Dhingra, Sadhna; Meng, Qingchang; Jianhong Hu; Donna M Muzny; Harshavardhan Doddapaneni; Perez, Lesette; Korchina, Viktoriya; Nessner, Caitlin; et al. (Life Sci Alliance, 2021)
Four organ transplant recipients from an organ donor diagnosed with anaplastic pleomorphic xanthoastrocytoma developed fatal malignancies for which the origin could not be confirmed by standard methods. We identified the somatic mutational profiles of the neoplasms using next-generation sequencing technologies and tracked the relationship between the different samples. The data were consistent with the presence of an aggressive clonal entity in the donor and the subsequent proliferation of descendent tumors in each recipient. Deleterious mutations in , , , , and , and a chromosomal deletion spanning the genes, were shared between the recipients' lesions. In addition to demonstrating that DNA sequencing tracked a donor/recipient cancer transmission, this study established that the genetic profile of a donor tumor and its potential aggressive phenotype could have been determined before transplantation was considered. As the genetic correlates of tumor invasion and metastases become better known, adding genetic profiling by DNA sequencing to the data considered for transplant safety should be considered.
Keywords: Adolescent; Adult; Biomarkers, Tumor; Biopsy; Central Nervous System Neoplasms; DNA Mutational Analysis; Exome Sequencing; Female; Humans; INDEL Mutation; Male; Middle Aged; Mutation; Organ Transplantation; Prognosis; Sequence Analysis, DNA; Tissue Donors; Transplant Recipients; Transplants; Young Adult

Shotgun transcriptome, spatial omics, and isothermal profiling of SARS-CoV-2 infection reveals unique host responses, viral diversification, and drug interactions. - Butler, Daniel; Mozsary, Christopher; Meydan, Cem; Foox, Jonathan; Rosiene, Joel; Shaiber, Alon; Danko, David; Afshinnekoo, Ebrahim; MacKay, Matthew; Fritz J Sedlazeck; Ivanov, Nikolay A; Sierra, Maria; et al. (Nat Commun, 2021)
In less than nine months, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) killed over a million people, including >25,000 in New York City (NYC) alone. The COVID-19 pandemic caused by SARS-CoV-2 highlights clinical needs to detect infection, track strain evolution, and identify biomarkers of disease course. To address these challenges, we designed a fast (30-minute) colorimetric test (LAMP) for SARS-CoV-2 infection from naso/oropharyngeal swabs and a large-scale shotgun metatranscriptomics platform (total-RNA-seq) for host, viral, and microbial profiling. We applied these methods to clinical specimens gathered from 669 patients in New York City during the first two months of the outbreak, yielding a broad molecular portrait of the emerging COVID-19 disease. We find significant enrichment of a NYC-distinctive clade of the virus (20C), as well as host responses in interferon, ACE, hematological, and olfaction pathways. In addition, we use 50,821 patient records to find that renin-angiotensin-aldosterone system inhibitors have a protective effect for severe COVID-19 outcomes, unlike similar drugs. Finally, spatial transcriptomic data from COVID-19 patient autopsy tissues reveal distinct ACE2 expression loci, with macrophage and neutrophil infiltration in the lungs. These findings can inform public health and may help develop and drive SARS-CoV-2 diagnostic, prevention, and treatment strategies.
Keywords: Adult; Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antiviral Agents; COVID-19; COVID-19 Drug Treatment; COVID-19 Nucleic Acid Testing; Drug Interactions; Female; Gene Expression Profiling; Genome, Viral; HLA Antigens; Host Microbial Interactions; Humans; Male; Middle Aged; Molecular Diagnostic Techniques; New York City; Nucleic Acid Amplification Techniques; Pandemics; RNA-Seq; SARS-CoV-2

Stephen T. Warren: Human geneticist who advanced understanding of mutational mechanisms and developmental disorders. - Nelson, David L; Caskey, C Thomas (Proc Natl Acad Sci U S A, 2021)
Keywords: Developmental Disabilities; Genetic Diseases, Inborn; Genetics, Medical; History, 20th Century; History, 21st Century; Humans; Mutation; Physician's Role

The trans-ancestral genomic architecture of glycemic traits. - Chen, Ji; Spracklen, Cassandra N; Marenne, Gaëlle; Varshney, Arushi; Corbin, Laura J; Luan, Jian'an; Willems, Sara M; Wu, Ying; Zhang, Xiaoshuai; Horikoshi, Momoko; Boutin, Thibaud S; Mägi, Reedik; et al. (Nat Genet, 2021)
Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.
Keywords: Alleles; Blood Glucose; Epigenesis, Genetic; Gene Expression Profiling; Genome, Human; Genome-Wide Association Study; Glycated Hemoglobin; Humans; Multifactorial Inheritance; Physical Chromosome Mapping; Quantitative Trait Loci; Quantitative Trait, Heritable; White People

Variation in predicted COVID-19 risk among lemurs and lorises. - Melin, Amanda D; Orkin, Joseph D; Janiak, Mareike C; Valenzuela, Alejandro; Kuderna, Lukas; Marrone, Frank; Ramangason, Hasinala; Horvath, Julie E; Roos, Christian; Kitchener, Andrew C; Khor, Chiea Chuen; Lim, Weng Khong; et al. (Am J Primatol, 2021)
The novel coronavirus SARS-CoV-2, which in humans leads to the disease COVID-19, has caused global disruption and more than 2 million fatalities since it first emerged in late 2019. As we write, infection rates are at their highest point globally and are rising extremely rapidly in some areas due to more infectious variants. The primary target of SARS-CoV-2 is the cellular receptor angiotensin-converting enzyme-2 (ACE2). Recent sequence analyses of the ACE2 gene predict that many nonhuman primates are also likely to be highly susceptible to infection. However, the anticipated risk is not equal across the Order. Furthermore, some taxonomic groups show high ACE2 amino acid conservation, while others exhibit high variability at this locus. As an example of the latter, analyses of strepsirrhine primate ACE2 sequences to date indicate large variation among lemurs and lorises compared to other primate clades despite low sampling effort. Here, we report ACE2 gene and protein sequences for 71 individual strepsirrhines, spanning 51 species and 19 genera. Our study reinforces previous results while finding additional variability in other strepsirrhine species, and suggests several clades of lemurs have high potential susceptibility to SARS-CoV-2 infection. Troublingly, some species, including the rare and endangered aye-aye (Daubentonia madagascariensis), as well as those in the genera Avahi and Propithecus, may be at high risk. Given that lemurs are endemic to Madagascar and among the primates at highest risk of extinction globally, further understanding of the potential threat of COVID-19 to their health should be a conservation priority. All feasible actions should be taken to limit their exposure to SARS-CoV-2.
Keywords: Angiotensin-Converting Enzyme 2; Animals; COVID-19; Lemur; Lorisidae; Primate Diseases; Risk Factors

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.
Keywords: Alleles; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Glomerular Filtration Rate; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Precision Medicine; Public Health Surveillance; Quantitative Trait, Heritable; United States; Whole Genome Sequencing

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.
Keywords: Alleles; Chromatin Immunoprecipitation Sequencing; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Research; Signal Transduction; Sleep Apnea Syndromes; United States; Whole Genome Sequencing

Accumulation of Molecular Aberrations Distinctive to Hepatocellular Carcinoma Progression. - Midorikawa, Yutaka; Yamamoto, Shogo; Tatsuno, Kenji; Renard-Guillet, Claire; Tsuji, Shingo; Hayashi, Akimasa; Ueda, Hiroki; Fukuda, Shiro; Fujita, Takanori; Katoh, Hiroto; Ishikawa, Shumpei; Covington, Kyle R; et al. (Cancer Res, 2020)
Cancer develops through the accumulation of genetic and epigenetic aberrations. To identify sequential molecular alterations that occur during the development of hepatocellular carcinoma (HCC), we compared 52 early and 108 overt HCC samples by genome sequencing. Gene mutations in the p53/RB1 pathway, WNT pathway, MLL protein family, SWI/SNF complexes, and AKT/PI3K pathway were common in HCC. In the early phase of all entities, was the most frequently upregulated gene owing to diverse mechanisms. Despite frequent somatic mutations in driver genes, including and , early HCC was a separate molecular entity from overt HCC, as each had a distinct expression profile. Notably, WNT target genes were not activated in early HCC regardless of mutation status because β-catenin did not translocate into the nucleus due to the E-cadherin/β-catenin complex at the membrane. Conversely, WNT targets were definitively upregulated in overt HCC, with mutation associated with downregulation of and hypomethylation of CpG islands in target genes. Similarly, cell-cycle genes downstream of the p53/RB pathway were upregulated only in overt HCC, with or gene mutations associated with chromosomal deletion of 4q or 16q. HCC was epigenetically distinguished into four subclasses: normal-like methylation, global-hypomethylation (favorable prognosis), stem-like methylation (poor prognosis), and CpG island methylation. These methylation statuses were globally maintained through HCC progression. Collectively, these data show that as HCC progresses, additional molecular events exclusive of driver gene mutations cooperatively contribute to transcriptional activation of downstream targets according to methylation status. SIGNIFICANCE: In addition to driver gene mutations in the WNT and p53 pathways, further molecular events are required for aberrant transcriptional activation of these pathways as HCC progresses.
Keywords: beta Catenin; Carcinoma, Hepatocellular; Disease Progression; DNA Methylation; DNA, Neoplasm; Epigenesis, Genetic; Gene Dosage; Gene Drive Technology; Gene Expression; Genes, cdc; Genes, p53; Histone-Lysine N-Methyltransferase; Humans; Liver Neoplasms; Mutation; Myeloid-Lymphoid Leukemia Protein; Oncogene Protein v-akt; Phosphatidylinositol 3-Kinases; Probability; Reverse Transcriptase Polymerase Chain Reaction; RNA, Neoplasm; Sequence Analysis, DNA; Telomerase; Transcriptional Activation; Up-Regulation; Wnt Proteins

Allelic Heterogeneity at the CRP Locus Identified by Whole-Genome Sequencing in Multi-ancestry Cohorts. - Raffield, Laura M; Iyengar, Apoorva K; Wang, Biqi; Gaynor, Sheila M; Spracklen, Cassandra N; Zhong, Xue; Kowalski, Madeline H; Salimi, Shabnam; Polfus, Linda M; Benjamin, Emelia J; Bis, Joshua C; Bowler, Russell; et al. (Am J Hum Genet, 2020)
Whole-genome sequencing (WGS) can improve assessment of low-frequency and rare variants, particularly in non-European populations that have been underrepresented in existing genomic studies. The genetic determinants of C-reactive protein (CRP), a biomarker of chronic inflammation, have been extensively studied, with existing genome-wide association studies (GWASs) conducted in >200,000 individuals of European ancestry. In order to discover novel loci associated with CRP levels, we examined a multi-ancestry population (n = 23,279) with WGS (∼38× coverage) from the Trans-Omics for Precision Medicine (TOPMed) program. We found evidence for eight distinct associations at the CRP locus, including two variants that have not been identified previously (rs11265259 and rs181704186), both of which are non-coding and more common in individuals of African ancestry (∼10% and ∼1% minor allele frequency, respectively, and rare or monomorphic in 1000 Genomes populations of East Asian, South Asian, and European ancestry). We show that the minor (G) allele of rs181704186 is associated with lower CRP levels and decreased transcriptional activity and protein binding in vitro, providing a plausible molecular mechanism for this African ancestry-specific signal. The individuals homozygous for rs181704186-G have a mean CRP level of 0.23 mg/L, in contrast to individuals heterozygous for rs181704186 with mean CRP of 2.97 mg/L and major allele homozygotes with mean CRP of 4.11 mg/L. This study demonstrates the utility of WGS in multi-ethnic populations to drive discovery of complex trait associations of large effect and to identify functional alleles in noncoding regulatory regions.
Keywords: Asian People; Black People; C-Reactive Protein; Cohort Studies; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; White People; Whole Genome Sequencing

Analyses of non-coding somatic drivers in 2,658 cancer whole genomes. - Rheinbay, Esther; Nielsen, Morten Muhlig; Abascal, Federico; Wala, Jeremiah A; Shapira, Ofer; Tiao, Grace; Hornshøj, Henrik; Hess, Julian M; Juul, Randi Istrup; Lin, Ziao; Feuerbach, Lars; Sabarinathan, Radhakrishnan; et al. (Nature, 2020)
The discovery of drivers of cancer has traditionally focused on protein-coding genes. Here we present analyses of driver point mutations and structural variants in non-coding regions across 2,658 genomes from the Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium of the International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA). For point mutations, we developed a statistically rigorous strategy for combining significance levels from multiple methods of driver discovery that overcomes the limitations of individual methods. For structural variants, we present two methods of driver discovery, and identify regions that are significantly affected by recurrent breakpoints and recurrent somatic juxtapositions. Our analyses confirm previously reported drivers, raise doubts about others and identify novel candidates, including point mutations in the 5' region of TP53, in the 3' untranslated regions of NFKBIZ and TOB1, focal deletions in BRD4 and rearrangements in the loci of AKR1C genes. We show that although point mutations and structural variants that drive cancer are less frequent in non-coding genes and regulatory sequences than in protein-coding genes, additional examples of these drivers will be found as more cancer genomes become available.
Keywords: Databases, Genetic; DNA Breaks; Gene Expression Regulation, Neoplastic; Genome, Human; Genome-Wide Association Study; Humans; INDEL Mutation; Mutation; Neoplasms

BICRA, a SWI/SNF Complex Member, Is Associated with BAF-Disorder Related Phenotypes in Humans and Model Organisms. - Barish, Scott; Barakat, Tahsin Stefan; Michel, Brittany C; Mashtalir, Nazar; Phillips, Jennifer B; Valencia, Alfredo M; Ugur, Berrak; Wegner, Jeremy; Scott, Tiana M; Bostwick, Brett; David R Murdock; Dai, Hongzheng; et al. (Am J Hum Genet, 2020)
SWI/SNF-related intellectual disability disorders (SSRIDDs) are rare neurodevelopmental disorders characterized by developmental disability, coarse facial features, and fifth digit/nail hypoplasia that are caused by pathogenic variants in genes that encode for members of the SWI/SNF (or BAF) family of chromatin remodeling complexes. We have identified 12 individuals with rare variants (10 loss-of-function, 2 missense) in the BICRA (BRD4 interacting chromatin remodeling complex-associated protein) gene, also known as GLTSCR1, which encodes a subunit of the non-canonical BAF (ncBAF) complex. These individuals exhibited neurodevelopmental phenotypes that include developmental delay, intellectual disability, autism spectrum disorder, and behavioral abnormalities as well as dysmorphic features. Notably, the majority of individuals lack the fifth digit/nail hypoplasia phenotype, a hallmark of most SSRIDDs. To confirm the role of BICRA in the development of these phenotypes, we performed functional characterization of the zebrafish and Drosophila orthologs of BICRA. In zebrafish, a mutation of bicra that mimics one of the loss-of-function variants leads to craniofacial defects possibly akin to the dysmorphic facial features seen in individuals harboring putatively pathogenic BICRA variants. We further show that Bicra physically binds to other non-canonical ncBAF complex members, including the BRD9/7 ortholog, CG7154, and is the defining member of the ncBAF complex in flies. Like other SWI/SNF complex members, loss of Bicra function in flies acts as a dominant enhancer of position effect variegation but in a more context-specific manner. We conclude that haploinsufficiency of BICRA leads to a unique SSRIDD in humans whose phenotypes overlap with those previously reported.
Keywords: Adolescent; Animals; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Developmental Disabilities; Drosophila melanogaster; Drosophila Proteins; Female; Genes, Dominant; Genetic Variation; Haploinsufficiency; Humans; Infant; Male; Microscopy, Confocal; Mutation, Missense; Neuroglia; Neurons; Phenotype; Protein Binding; Tumor Suppressor Proteins; Zebrafish; Zebrafish Proteins

Brown marmorated stink bug, Halyomorpha halys (Stål), genome: putative underpinnings of polyphagy, insecticide resistance potential and biology of a top worldwide pest. - Sparks, Michael E; Bansal, Raman; Benoit, Joshua B; Blackburn, Michael B; Chao, Hsu; Chen, Mengyao; Cheng, Sammy; Childers, Christopher; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Elpidina, Elena N; et al. (BMC Genomics, 2020)
BACKGROUND: Halyomorpha halys (Stål), the brown marmorated stink bug, is a highly invasive insect species due in part to its exceptionally high levels of polyphagy. This species is also a nuisance due to overwintering in human-made structures. It has caused significant agricultural losses in recent years along the Atlantic seaboard of North America and in continental Europe. Genomic resources will assist with determining the molecular basis for this species' feeding and habitat traits, defining potential targets for pest management strategies. RESULTS: Analysis of the 1.15-Gb draft genome assembly has identified a wide variety of genetic elements underpinning the biological characteristics of this formidable pest species, encompassing the roles of sensory functions, digestion, immunity, detoxification and development, all of which likely support H. halys' capacity for invasiveness. Many of the genes identified herein have potential for biomolecular pesticide applications. CONCLUSIONS: Availability of the H. halys genome sequence will be useful for the development of environmentally friendly biomolecular pesticides to be applied in concert with more traditional, synthetic chemical-based controls.
Keywords: Animals; Ecosystem; Gene Transfer, Horizontal; Genome Size; Heteroptera; Insect Proteins; Insecticide Resistance; Introduced Species; Phylogeny; Whole Genome Sequencing

Cohort Profile: The Right Drug, Right Dose, Right Time: Using Genomic Data to Individualize Treatment Protocol (RIGHT Protocol). - Bielinski, Suzette J; St Sauver, Jennifer L; Olson, Janet E; Larson, Nicholas B; Black, John L; Steven E Scherer; Bernard, Matthew E; Eric Boerwinkle; Borah, Bijan J; Caraballo, Pedro J; Curry, Timothy B; Harshavardhan Doddapaneni; et al. (Int J Epidemiol, 2020)
Keywords: Clinical Protocols; Cohort Studies; Female; Genomics; Humans; Male; Pharmacogenetics; Precision Medicine

Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; R. Alan Harris; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Jeffrey Rogers; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Correction: Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
A correction to this paper has been published and can be accessed via a link at the top of the paper.

Cytogenetically visible inversions are formed by multiple molecular mechanisms. - Pettersson, Maria; Grochowski, Christopher M; Wincent, Josephine; Eisfeldt, Jesper; Breman, Amy M; Cheung, Sau W; Krepischi, Ana C V; Rosenberg, Carla; James R Lupski; Ottosson, Jesper; Lovmar, Lovisa; Gacic, Jelena; et al. (Hum Mutat, 2020)
Cytogenetically detected inversions are generally assumed to be copy number and phenotypically neutral events. While nonallelic homologous recombination is thought to play a major role, recent data suggest the involvement of other molecular mechanisms in inversion formation. Using a combination of short-read whole-genome sequencing (WGS), 10X Genomics Chromium WGS, droplet digital polymerase chain reaction and array comparative genomic hybridization we investigated the genomic structure of 18 large unique cytogenetically detected chromosomal inversions and achieved nucleotide resolution of at least one chromosomal inversion junction for 13/18 (72%). Surprisingly, we observed that seemingly copy number neutral inversions can be accompanied by a copy-number gain of up to 350 kb and local genomic complexities (3/18, 17%). In the resolved inversions, the mutational signatures are consistent with nonhomologous end-joining (8/13, 62%) or microhomology-mediated break-induced replication (5/13, 38%). Our study indicates that short-read 30x coverage WGS can detect a substantial fraction of chromosomal inversions. Moreover, replication-based mechanisms are responsible for approximately 38% of those events leading to a significant proportion of inversions that are actually accompanied by additional copy-number variation potentially contributing to the overall phenotypic presentation of those patients.
Keywords: Chromosome Inversion; Comparative Genomic Hybridization; DNA End-Joining Repair; DNA Repair; Female; Gene Frequency; Haplotypes; Heterozygote; Homologous Recombination; Humans; Karyotyping; Male; Pedigree; Whole Genome Sequencing

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.
Keywords: Cerebellar Ataxia; DNA Copy Number Variations; Exome; Exome Sequencing; Genetic Association Studies; Genetic Linkage; Genetic Predisposition to Disease; Humans; Microsatellite Repeats; Nervous System Diseases

Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals. - Surendran, Praveen; Feofanova, Elena V; Lahrouchi, Najim; Ntalla, Ioanna; Karthikeyan, Savita; Cook, James; Chen, Lingyan; Mifsud, Borbala; Yao, Chen; Kraja, Aldi T; Cartwright, James H; Hellwege, Jacklyn N; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to ~1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency ≤ 0.01) variant BP associations (P < 5 × 10), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were ~8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.
Keywords: Blood Pressure; GATA5 Transcription Factor; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Hypertension; Mutation; Phospholipase C beta; Polymorphism, Single Nucleotide

Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale. - Li, Xihao; Li, Zilin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Aslibekyan, Stella; Ballantyne, Christie M; Bielak, Lawrence F; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.
Keywords: Cholesterol, LDL; Computer Simulation; Genetic Predisposition to Disease; Genetic Variation; Genome; Genome-Wide Association Study; Humans; Models, Genetic; Molecular Sequence Annotation; Phenotype; Whole Genome Sequencing

Evaluation of mitochondrial DNA copy number estimation techniques. - Longchamps, Ryan J; Castellani, Christina A; Yang, Stephanie Y; Newcomb, Charles E; Sumpter, Jason A; Lane, John; Grove, Megan L; Guallar, Eliseo; Pankratz, Nathan; Taylor, Kent D; Rotter, Jerome I; Eric Boerwinkle; et al. (PLoS One, 2020)
Mitochondrial DNA copy number (mtDNA-CN), a measure of the number of mitochondrial genomes per cell, is a minimally invasive proxy measure for mitochondrial function and has been associated with several aging-related diseases. Although quantitative real-time PCR (qPCR) is the current gold standard method for measuring mtDNA-CN, mtDNA-CN can also be measured from genotyping microarray probe intensities and DNA sequencing read counts. To conduct a comprehensive examination on the performance of these methods, we use known mtDNA-CN correlates (age, sex, white blood cell count, Duffy locus genotype, incident cardiovascular disease) to evaluate mtDNA-CN calculated from qPCR, two microarray platforms, as well as whole genome (WGS) and whole exome sequence (WES) data across 1,085 participants from the Atherosclerosis Risk in Communities (ARIC) study and 3,489 participants from the Multi-Ethnic Study of Atherosclerosis (MESA). We observe mtDNA-CN derived from WGS data is significantly more associated with known correlates compared to all other methods (p < 0.001). Additionally, mtDNA-CN measured from WGS is on average more significantly associated with traits by 5.6 orders of magnitude and has effect size estimates 5.8 times more extreme than the current gold standard of qPCR. We further investigated the role of DNA extraction method on mtDNA-CN estimate reproducibility and found mtDNA-CN estimated from cell lysate is significantly less variable than traditional phenol-chloroform-isoamyl alcohol (p = 5.44x10-4) and silica-based column selection (p = 2.82x10-7). In conclusion, we recommend the field moves towards more accurate methods for mtDNA-CN, as well as re-analyze trait associations as more WGS data becomes available from larger initiatives such as TOPMed.
Keywords: Aged; DNA, Mitochondrial; Female; Gene Dosage; Genomics; Humans; Male; Middle Aged

Exome sequencing reveals a novel variant in causing intracranial aneurysm in a Chinese family. - Ding, Xinghuan; Zhao, Sen; Zhang, Qianqian; Yan, Zihui; Wang, Yang; Wu, Yong; Li, Xiaoxin; Liu, Jian; Niu, Yuchen; Zhang, Yisen; Zhang, Mingqi; Wang, Huizi; et al. (J Neurointerv Surg, 2020)
BACKGROUND: Genetic risk factors play an important role in the pathogenesis of familial intracranial aneurysms (FIAs); however, the molecular mechanisms remain largely unknown. OBJECTIVE: To investigate potential FIA-causing genetic variants by rare variant interrogation and a family-based genomics approach in a large family with an extensive multigenerational pedigree with FIAs. METHOD: Exome sequencing (ES) was performed in a dominant likely family with intracranial aneurysms (IAs). Variants were analyzed by an in-house developed pipeline and prioritized using various filtering strategies, including population frequency, variant type, and predicted variant pathogenicity. Sanger sequencing was also performed to evaluate the segregation of the variants with the phenotype. RESULTS: Based on the ES data obtained from five individuals from a family with 7/21 living members affected with IAs, a total of 14 variants were prioritized as candidate variants. Familial segregation analysis revealed that c.2519T>C (p.Leu840Pro) segregated in accordance with Mendelian expectations with the phenotype within the family-that is, present in all IA-affected cases and absent from all unaffected members of the second generation. This missense variant is absent from public databases (1000genome, ExAC, gnomAD, ESP5400), and has damaging predictions by bioinformatics tools (Gerp ++ score = 5.88, CADD score = 16.43, MutationTaster score = 1, LRT score = 0). In addition, 840Leu in NFX1 is robustly conserved in mammals and maps in a region before the RING-type zinc finger domain. CONCLUSION: c.2519T>C (p.Leu840Pro) may contribute to the pathogenetics of a subset of FIAs.
Keywords: Adult; Asian People; Computational Biology; Exome; Female; Genetic Variation; Humans; Intracranial Aneurysm; Male; Middle Aged; Pedigree; Phenotype; Repressor Proteins

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gozde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Bo Yuan; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Gene content evolution in the arthropods. - Thomas, Gregg W C; Dohmen, Elias; Hughes, Daniel S T; Murali, Shwetha C; Poelchau, Monica; Glastad, Karl; Anstead, Clare A; Ayoub, Nadia A; Batterham, Phillip; Bellair, Michelle; Binford, Greta J; Chao, Hsu; et al. (Genome Biol, 2020)
BACKGROUND: Arthropods comprise the largest and most diverse phylum on Earth and play vital roles in nearly every ecosystem. Their diversity stems in part from variations on a conserved body plan, resulting from and recorded in adaptive changes in the genome. Dissection of the genomic record of sequence change enables broad questions regarding genome evolution to be addressed, even across hyper-diverse taxa within arthropods. RESULTS: Using 76 whole genome sequences representing 21 orders spanning more than 500 million years of arthropod evolution, we document changes in gene and protein domain content and provide temporal and phylogenetic context for interpreting these innovations. We identify many novel gene families that arose early in the evolution of arthropods and during the diversification of insects into modern orders. We reveal unexpected variation in patterns of DNA methylation across arthropods and examples of gene family and protein domain evolution coincident with the appearance of notable phenotypic and physiological adaptations such as flight, metamorphosis, sociality, and chemoperception. CONCLUSIONS: These analyses demonstrate how large-scale comparative genomics can provide broad new insights into the genotype to phenotype map and generate testable hypotheses about the evolution of animal diversity.
Keywords: Animals; Arthropods; DNA Methylation; Evolution, Molecular; Genetic Speciation; Genetic Variation; Phylogeny

Genetic and molecular mechanism for distinct clinical phenotypes conveyed by allelic truncating mutations implicated in FBN1. - Lin, Mao; Liu, Zhenlei; Liu, Gang; Zhao, Sen; Li, Chao; Chen, Weisheng; Coban Akdemir, Zeynep; Lin, Jiachen; Song, Xiaofei; Wang, Shengru; Xu, Qiming; Zhao, Yanxue; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: The molecular and genetic mechanisms by which different single nucleotide variant alleles in specific genes, or at the same genetic locus, cause distinct disease phenotypes often remain unclear. Allelic truncating mutations of FBN1 could cause either classical Marfan syndrome (MFS) or a more complicated phenotype associated with Marfanoid-progeroid-lipodystrophy syndrome (MPLS). METHODS: We investigated a small cohort, encompassing two classical MFS and one MPLS subjects from China, whose clinical presentation included scoliosis potentially requiring surgical intervention. Targeted next generation sequencing was performed on all the participants. We analyzed the molecular diagnosis, clinical features, and the potential molecular mechanism involved in the MPLS subject in our cohort. RESULTS: We report a novel de novo FBN1 mutation for the first Chinese subject with MPLS, a more complicated fibrillinopathy, and two subjects with more classical MFS. We further predict that the MPLS truncating mutation, and others previously reported, is prone to escape the nonsense-mediated decay (NMD), while MFS mutations are predicted to be subjected to NMD. Also, the MPLS mutation occurs within the glucogenic hormone asprosin domain of FBN1. In vitro experiments showed that the single MPLS mutation p.Glu2759Cysfs*9 appears to perturb proper FBN1 protein aggregation as compared with the classical MFS mutation p.Tyr2596Thrfs*86. Both mutations appear to upregulate SMAD2 phosphorylation in vitro. CONCLUSION: We provide direct evidence that a dominant-negative interaction of FBN1 potentially explains the complex MPLS phenotypes through genetic and functional analysis. Our study expands the mutation spectrum of FBN1 and highlights the potential molecular mechanism for MPLS.
Keywords: Adolescent; Adult; Child; Female; Fibrillin-1; HEK293 Cells; Humans; Lipodystrophy; Marfan Syndrome; Mutation; Phenotype; Progeria; Protein Domains; Smad2 Protein

Genetic Burden Contributing to Extremely Low or High Bone Mineral Density in a Senior Male Population From the Osteoporotic Fractures in Men Study (MrOS). - Chen, Shan; Jain, Mahim; Jhangiani, Shalini; Akdemir, Zeynep C; Campeau, Philippe M; Klein, Robert F; Nielson, Carrie; Dai, Hongzheng; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Orwoll, Eric S; et al. (JBMR Plus, 2020)
Worldwide, one in five men aged over 50 years will experience osteoporosis or a clinical bone fracture, with a greater fracture-related mortality rate than women. However, the genetic etiology of osteoporosis in men is still poorly understood. We aimed to identify the genetic variants and candidate genes associated with extremely low or high BMD for a better understanding of the biology underlying low bone density that may point to potential therapeutic targets for increasing bone mass. Subjects from the Osteoporotic Fractures in Men Study (MrOS) cohort were evaluated by age and BMI-adjusted total hip BMD. Those with BMD values 3 SDs away from the mean were selected and the remaining individuals whose adjusted BMD ranked at the highest or lowest 100 were included. Men with the lowest adjusted BMD ( = 98) and highest adjusted BMD ( = 110) were chosen for exome sequencing. Controls ( = 82) were men of Northern and Western European descent from the US Utah population of the 1000 Genomes Project. Fisher's exact test was performed to compare low- or high-BMD subjects with controls for single-gene associations. Additionally, sets of candidate genes causative of heritable disorders of connective tissue, including osteogenesis imperfecta (OI) and Ehlers-Danlos syndrome (EDS), were grouped for multigene and mutation burden analyses. No single-gene associations with rare variants were found for either the low BMD group (33 genes) or high BMD group (18 genes). In the group of OI genes, we detected a significant threefold increased accumulation of rare variants in low-BMD subjects compared with controls ( = 0.009). Additionally, genes associated with EDS had a twofold increased frequency in low-BMD subjects compared with controls ( = 0.03). These findings reveal a rare variant burden in OI and EDS disease genes at low BMD, which suggests a potential gene-panel approach to screen for multivariant associations in larger cohorts. © 2019 The Authors. published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

High-coverage whole-genome analysis of 1220 cancers reveals hundreds of genes deregulated by rearrangement-mediated cis-regulatory alterations. - Zhang, Yiqun; Chen, Fengju; Fonseca, Nuno A; He, Yao; Fujita, Masashi; Nakagawa, Hidewaki; Zhang, Zemin; Brazma, Alvis; Creighton, Chad J (Nat Commun, 2020)
The impact of somatic structural variants (SVs) on gene expression in cancer is largely unknown. Here, as part of the ICGC/TCGA Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium, which aggregated whole-genome sequencing data and RNA sequencing from a common set of 1220 cancer cases, we report hundreds of genes for which the presence within 100 kb of an SV breakpoint associates with altered expression. For the majority of these genes, expression increases rather than decreases with corresponding breakpoint events. Up-regulated cancer-associated genes impacted by this phenomenon include TERT, MDM2, CDK4, ERBB2, CD274, PDCD1LG2, and IGF2. TERT-associated breakpoints involve ~3% of cases, most frequently in liver biliary, melanoma, sarcoma, stomach, and kidney cancers. SVs associated with up-regulation of PD1 and PDL1 genes involve ~1% of non-amplified cases. For many genes, SVs are significantly associated with increased numbers or greater proximity of enhancer regulatory elements near the gene. DNA methylation near the promoter is often increased with nearby SV breakpoint, which may involve inactivation of repressor elements.
Keywords: Databases, Genetic; DNA Methylation; Enhancer Elements, Genetic; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Genomic Structural Variation; Humans; Neoplasms; Oncogenes; Regulatory Sequences, Nucleic Acid; Whole Genome Sequencing

High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2020)
The African continent is regarded as the cradle of modern humans and African genomes contain more genetic variation than those from any other continent, yet only a fraction of the genetic diversity among African individuals has been surveyed. Here we performed whole-genome sequencing analyses of 426 individuals-comprising 50 ethnolinguistic groups, including previously unsampled populations-to explore the breadth of genomic diversity across Africa. We uncovered more than 3 million previously undescribed variants, most of which were found among individuals from newly sampled ethnolinguistic groups, as well as 62 previously unreported loci that are under strong selection, which were predominantly found in genes that are involved in viral immunity, DNA repair and metabolism. We observed complex patterns of ancestral admixture and putative-damaging and novel variation, both within and between populations, alongside evidence that Zambia was a likely intermediate site along the routes of expansion of Bantu-speaking populations. Pathogenic variants in genes that are currently characterized as medically relevant were uncommon-but in other genes, variants denoted as 'likely pathogenic' in the ClinVar database were commonly observed. Collectively, these findings refine our current understanding of continental migration, identify gene flow and the response to human disease as strong drivers of genome-level population variation, and underscore the scientific imperative for a broader characterization of the genomic diversity of African individuals to understand human ancestry and improve health.
Keywords: Africa; Datasets as Topic; DNA Repair; Female; Gene Flow; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genomics; Health; History, Ancient; Human Migration; Humans; Immunity; Language; Male; Metabolism; Selection, Genetic; Whole Genome Sequencing

In vivo modeling of metastatic human high-grade serous ovarian cancer in mice. - Kim, Olga; Park, Eun Young; Klinkebiel, David L; Pack, Svetlana D; Shin, Yong-Hyun; Abdullaev, Zied; Emerson, Robert E; Coffey, Donna M; Kwon, Sun Young; Creighton, Chad J; Kwon, Sanghoon; Chang, Edmund C; et al. (PLoS Genet, 2020)
Metastasis is responsible for 90% of human cancer mortality, yet it remains a challenge to model human cancer metastasis in vivo. Here we describe mouse models of high-grade serous ovarian cancer, also known as high-grade serous carcinoma (HGSC), the most common and deadliest human ovarian cancer type. Mice genetically engineered to harbor Dicer1 and Pten inactivation and mutant p53 robustly replicate the peritoneal metastases of human HGSC with complete penetrance. Arising from the fallopian tube, tumors spread to the ovary and metastasize throughout the pelvic and peritoneal cavities, invariably inducing hemorrhagic ascites. Widespread and abundant peritoneal metastases ultimately cause mouse deaths (100%). Besides the phenotypic and histopathological similarities, mouse HGSCs also display marked chromosomal instability, impaired DNA repair, and chemosensitivity. Faithfully recapitulating the clinical metastases as well as molecular and genomic features of human HGSC, this murine model will be valuable for elucidating the mechanisms underlying the development and progression of metastatic ovarian cancer and also for evaluating potential therapies.
Keywords: Animals; Antineoplastic Agents; Cell Line, Tumor; Chromosomal Instability; Cystadenocarcinoma, Serous; DEAD-box RNA Helicases; Disease Models, Animal; DNA Repair; Drug Resistance, Neoplasm; Drug Screening Assays, Antitumor; Feasibility Studies; Female; Humans; Mice; Mice, Knockout; Mutation; Neoplasm Grading; Neoplasm Metastasis; Ovarian Neoplasms; Peritoneal Neoplasms; Primary Cell Culture; PTEN Phosphohydrolase; Ribonuclease III; Tumor Suppressor Protein p53

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; Aged; Aged, 80 and over; alpha Karyopherins; Black People; Cell Self Renewal; Clonal Hematopoiesis; Dioxygenases; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

Knockout of mouse receptor accessory protein 6 leads to sperm function and morphology defects†. - Devlin, Darius J; Agrawal Zaneveld, Smriti; Nozawa, Kaori; Han, Xiao; Moye, Abigail R; Liang, Qingnan; Harnish, Jacob Michael; Matzuk, Martin M; Rui Chen (Biol Reprod, 2020)
Receptor accessory protein 6 (REEP6) is a member of the REEP/Ypt-interacting protein family that we recently identified as essential for normal endoplasmic reticulum homeostasis and protein trafficking in the retina of mice and humans. Interestingly, in addition to the loss of REEP6 in our knockout (KO) mouse model recapitulating the retinal degeneration of humans with REEP6 mutations causing retinitis pigmentosa (RP), we also found that male mice are sterile. Herein, we characterize the infertility caused by loss of Reep6. Expression of both Reep6 mRNA transcripts is present in the testis; however, isoform 1 becomes overexpressed during spermiogenesis. In vitro fertilization assays reveal that Reep6 KO spermatozoa are able to bind the zona pellucida but are only able to fertilize oocytes lacking the zona pellucida. Although spermatogenesis appears normal in KO mice, cauda epididymal spermatozoa have severe motility defects and variable morphological abnormalities, including bent or absent tails. Immunofluorescent staining reveals that REEP6 expression first appears in stage IV tubules within step 15 spermatids, and REEP6 localizes to the connecting piece, midpiece, and annulus of mature spermatozoa. These data reveal an important role for REEP6 in sperm motility and morphology and is the first reported function for a REEP protein in reproductive processes. Additionally, this work identifies a new gene potentially responsible for human infertility and has implications for patients with RP harboring mutations in REEP6.
Keywords: Animals; Eye Proteins; Gene Expression Regulation; Infertility, Male; Male; Membrane Proteins; Mice; Mice, Knockout; Mutation; RNA, Messenger; Spermatozoa

Mapping and characterization of structural variation in 17,795 human genomes. - Abel, Haley J; Larson, David E; Regier, Allison A; Chiang, Colby; Das, Indraniel; Kanchi, Krishna L; Layer, Ryan M; Neale, Benjamin M; Salerno, William J; Reeves, Catherine; Buyske, Steven; Matise, Tara C; et al. (Nature, 2020)
A key goal of whole-genome sequencing for studies of human genetics is to interrogate all forms of variation, including single-nucleotide variants, small insertion or deletion (indel) variants and structural variants. However, tools and resources for the study of structural variants have lagged behind those for smaller variants. Here we used a scalable pipeline to map and characterize structural variants in 17,795 deeply sequenced human genomes. We publicly release site-frequency data to create the largest, to our knowledge, whole-genome-sequencing-based structural variant resource so far. On average, individuals carry 2.9 rare structural variants that alter coding regions; these variants affect the dosage or structure of 4.2 genes and account for 4.0-11.2% of rare high-impact coding alleles. Using a computational model, we estimate that structural variants account for 17.2% of rare alleles genome-wide, with predicted deleterious effects that are equivalent to loss-of-function coding alleles; approximately 90% of such structural variants are noncoding deletions (mean 19.1 per genome). We report 158,991 ultra-rare structural variants and show that 2% of individuals carry ultra-rare megabase-scale structural variants, nearly half of which are balanced or complex rearrangements. Finally, we infer the dosage sensitivity of genes and noncoding elements, and reveal trends that relate to element class and conservation. This work will help to guide the analysis and interpretation of structural variants in the era of whole-genome sequencing.
Keywords: Alleles; Case-Control Studies; Epigenesis, Genetic; Female; Gene Dosage; Genetic Variation; Genetics, Population; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Sequence Annotation; Quantitative Trait Loci; Racial Groups; Software; Whole Genome Sequencing

Methylome-wide association study of central adiposity implicates genes involved in immune and endocrine systems. - Justice, Anne E; Chittoor, Geetha; Gondalia, Rahul; Melton, Phillip E; Lim, Elise; Grove, Megan L; Whitsel, Eric A; Liu, Ching-Ti; Cupples, L Adrienne; Fernandez-Rhodes, Lindsay; Guan, Weihua; Bressler, Jan; et al. (Epigenomics, 2020)
We conducted a methylome-wide association study to examine associations between DNA methylation in whole blood and central adiposity and body fat distribution, measured as waist circumference, waist-to-hip ratio and waist-to-height ratio adjusted for body mass index, in 2684 African-American adults in the Atherosclerosis Risk in Communities study. We validated significantly associated cytosine-phosphate-guanine methylation sites (CpGs) among adults using the Women's Health Initiative and Framingham Heart Study participants (combined n = 5743) and generalized associations in adolescents from The Raine Study (n = 820). We identified 11 CpGs that were robustly associated with one or more central adiposity trait in adults and two in adolescents, including CpG site associations near , ,  and that had not previously been associated with obesity-related traits.
Keywords: Adiposity; Cohort Studies; CpG Islands; Disease Susceptibility; DNA Methylation; Endocrine System; Epigenesis, Genetic; Epigenomics; Genome-Wide Association Study; Humans; Immune System; Obesity

Next Generation Sequencing of 134 Children with Autism Spectrum Disorder and Regression. - Yin, Jiani; Chun, Chun-An; Zavadenko, Nikolay N; Pechatnikova, Natalia L; Naumova, Oxana Yu; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Schaaf, Christian P; Grigorenko, Elena L (Genes (Basel), 2020)
Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACMG standards and guidelines. Among these were recurring variants in and , variants in genes that were linked to syndromic forms of ASD (, , , , , and ), and variants in the form of oligogenic heterozygosity (, , and ).
Keywords: Autism Spectrum Disorder; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Gene Expression Regulation; Genetic Markers; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Mutation

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (bioRxiv, 2020)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity and provided evidence of expression of ORF10. Heterogeneous allelic frequencies along the 20kb ORF1ab gene suggested the presence of a defective interfering viral RNA species subpopulation in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.

Oligonucleotide Capture Sequencing of the SARS-CoV-2 Genome and Subgenomic Fragments from COVID-19 Individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (bioRxiv, 2020)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity and provided evidence of expression of ORF10. Heterogeneous allelic frequencies along the 20kb ORF1ab gene suggested the presence of a defective interfering viral RNA species subpopulation in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.

Pharmacogenomics of Nicotine Metabolism: Novel CYP2A6 and CYP2B6 Genetic Variation Patterns in Alaska Native and American Indian Populations. - Claw, Katrina G; Beans, Julie A; Lee, Seung-Been; Avey, Jaedon P; Stapleton, Patricia A; Steven E Scherer; El-Boraie, Ahmed; Tyndale, Rachel F; Nickerson, Deborah A; Dillard, Denise A; Thummel, Kenneth E; Robinson, Renee F (Nicotine Tob Res, 2020)
INTRODUCTION: Alaska Native and American Indian (AN/AI) populations have higher tobacco use prevalence than other ethnic/racial groups. Pharmacogenetic testing to tailor tobacco cessation treatment may improve cessation rates. This study characterized polymorphic variations among AN/AI people in genes associated with metabolism of nicotine and drugs used for tobacco cessation. METHODS: Recruitment of AN/AI individuals represented six subgroups, five geographic subgroups throughout Alaska and a subgroup comprised of AIs from the lower 48 states living in Alaska. We sequenced the CYP2A6 and CYP2B6 genes to identify known and novel gain, reduced, and loss-of-function alleles, including structural variation (eg, gene deletions, duplications, and hybridizations). RESULTS: Variant allele frequencies differed substantially between AN/AI subgroups. The gene deletion CYP2A6*4 and reduced function CYP2A6*9 alleles were found at high frequency in Northern/Western subgroups and in Lower 48/Interior subgroups, respectively. The reduced function CYP2B6*6 allele was observed in all subgroups and a novel, predicted reduced function CYP2B6 variant was found at relatively high frequency in the Southeastern subgroup. CONCLUSIONS: Diverse CYP2A6 and CYP2B6 variation among the subgroups highlight the need for comprehensive pharmacogenetic testing to guide tobacco cessation therapy for AN/AI populations. IMPLICATIONS: Nicotine metabolism is largely determined by CYP2A6 genotype, and variation in CYP2A6 activity has altered the treatment success in other populations. These findings suggest pharmacogenetic-guided smoking cessation drug treatment could provide benefit to this unique population seeking tobacco cessation therapy.
Keywords: Adolescent; Adult; Aged; Alaska; Alaskan Natives; Cytochrome P-450 CYP2A6; Cytochrome P-450 CYP2B6; Genetic Variation; Genotype; Humans; Indians, North American; Middle Aged; Nicotine; Pharmacogenetics; Smoking; Smoking Cessation; Smoking Cessation Agents; Young Adult

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.
Keywords: Abnormalities, Multiple; Actins; Adult; Amino Acid Substitution; Arginine; Colon; DNA Mutational Analysis; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Intestinal Pseudo-Obstruction; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Urinary Bladder; Young Adult

The repertoire of mutational signatures in human cancer. - Alexandrov, Ludmil B; Kim, Jaegil; Haradhvala, Nicholas J; Huang, Mi Ni; Tian Ng, Alvin Wei; Wu, Yang; Boot, Arnoud; Covington, Kyle R; Gordenin, Dmitry A; Bergstrom, Erik N; Islam, S M Ashiqul; Lopez-Bigas, Nuria; et al. (Nature, 2020)
Somatic mutations in cancer genomes are caused by multiple mutational processes, each of which generates a characteristic mutational signature. Here, as part of the Pan-Cancer Analysis of Whole Genomes (PCAWG) Consortium of the International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA), we characterized mutational signatures using 84,729,690 somatic mutations from 4,645 whole-genome and 19,184 exome sequences that encompass most types of cancer. We identified 49 single-base-substitution, 11 doublet-base-substitution, 4 clustered-base-substitution and 17 small insertion-and-deletion signatures. The substantial size of our dataset, compared with previous analyses, enabled the discovery of new signatures, the separation of overlapping signatures and the decomposition of signatures into components that may represent associated-but distinct-DNA damage, repair and/or replication mechanisms. By estimating the contribution of each signature to the mutational catalogues of individual cancer genomes, we revealed associations of signatures to exogenous or endogenous exposures, as well as to defective DNA-maintenance processes. However, many signatures are of unknown cause. This analysis provides a systematic perspective on the repertoire of mutational processes that contribute to the development of human cancer.
Keywords: Age Factors; Base Sequence; Exome; Genome, Human; Humans; Mutation; Neoplasms; Sequence Analysis, DNA

Role of Rare and Low-Frequency Variants in Gene-Alcohol Interactions on Plasma Lipid Levels. - Wang, Zhe; Chen, Han; Bartz, Traci M; Bielak, Lawrence F; Chasman, Daniel I; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Lim, Elise; Noordam, Raymond; Richard, Melissa A; Wang, Heming; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Alcohol intake influences plasma lipid levels, and such effects may be moderated by genetic variants. We aimed to characterize the role of aggregated rare and low-frequency protein-coding variants in gene by alcohol consumption interactions associated with fasting plasma lipid levels. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, fasting plasma triglycerides and high- and low-density lipoprotein cholesterol were measured in 34 153 individuals with European ancestry from 5 discovery studies and 32 277 individuals from 6 replication studies. Rare and low-frequency functional protein-coding variants (minor allele frequency, ≤5%) measured by an exome array were aggregated by genes and evaluated by a gene-environment interaction test and a joint test of genetic main and gene-environment interaction effects. Two dichotomous self-reported alcohol consumption variables, current drinker, defined as any recurrent drinking behavior, and regular drinker, defined as the subset of current drinkers who consume at least 2 drinks per week, were considered. RESULTS: We discovered and replicated 21 gene-lipid associations at 13 known lipid loci through the joint test. Eight loci (, , , , , , , and ) remained significant after conditioning on the common index single-nucleotide polymorphism identified by previous genome-wide association studies, suggesting an independent role for rare and low-frequency variants at these loci. One significant gene-alcohol interaction on triglycerides in a novel locus was significantly discovered (=6.65×10 for the interaction test) and replicated at nominal significance level (=0.013) in . CONCLUSIONS: In conclusion, this study applied new gene-based statistical approaches and suggested that rare and low-frequency genetic variants interacted with alcohol consumption on lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Apolipoproteins E; Cholesterol, HDL; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Triglycerides; White People; Young Adult

Sawfly Genomes Reveal Evolutionary Acquisitions That Fostered the Mega-Radiation of Parasitoid and Eusocial Hymenoptera. - Oeyen, Jan Philip; Baa-Puyoulet, Patrice; Benoit, Joshua B; Beukeboom, Leo W; Bornberg-Bauer, Erich; Buttstedt, Anja; Calevro, Federica; Cash, Elizabeth I; Chao, Hsu; Charles, Hubert; Chen, Mei-Ju May; Childers, Christopher; et al. (Genome Biol Evol, 2020)
The tremendous diversity of Hymenoptera is commonly attributed to the evolution of parasitoidism in the last common ancestor of parasitoid sawflies (Orussidae) and wasp-waisted Hymenoptera (Apocrita). However, Apocrita and Orussidae differ dramatically in their species richness, indicating that the diversification of Apocrita was promoted by additional traits. These traits have remained elusive due to a paucity of sawfly genome sequences, in particular those of parasitoid sawflies. Here, we present comparative analyses of draft genomes of the primarily phytophagous sawfly Athalia rosae and the parasitoid sawfly Orussus abietinus. Our analyses revealed that the ancestral hymenopteran genome exhibited traits that were previously considered unique to eusocial Apocrita (e.g., low transposable element content and activity) and a wider gene repertoire than previously thought (e.g., genes for CO2 detection). Moreover, we discovered that Apocrita evolved a significantly larger array of odorant receptors than sawflies, which could be relevant to the remarkable diversification of Apocrita by enabling efficient detection and reliable identification of hosts.
Keywords: Amino Acid Sequence; Animals; Conserved Sequence; DNA Transposable Elements; Female; Gene Dosage; Genetic Speciation; Genome, Insect; Glycoproteins; Herbivory; Host-Parasite Interactions; Hymenoptera; Immunity; Insect Proteins; Male; Multigene Family; Receptors, Odorant; Social Behavior; Vision, Ocular

Telomere Maintenance Mechanisms Define Clinical Outcome in High-Risk Neuroblastoma. - Koneru, Balakrishna; Lopez, Gonzalo; Farooqi, Ahsan; Conkrite, Karina L; Nguyen, Thinh H; Macha, Shawn J; Modi, Apexa; Rokita, Jo Lynne; Urias, Eduardo; Hindle, Ashly; Davidson, Heather; McCoy, Kristyn; et al. (Cancer Res, 2020)
Neuroblastoma is a childhood cancer with heterogeneous clinical outcomes. To comprehensively assess the impact of telomere maintenance mechanism (TMM) on clinical outcomes in high-risk neuroblastoma, we integrated the C-circle assay [a marker for alternative lengthening of telomeres (ALT)], TERT mRNA expression by RNA-sequencing, whole-genome/exome sequencing, and clinical covariates in 134 neuroblastoma patient samples at diagnosis. In addition, we assessed TMM in neuroblastoma cell lines ( = 104) and patient-derived xenografts ( = 28). ALT was identified in 23.4% of high-risk neuroblastoma tumors and genomic alterations in were detected in 60% of ALT tumors; 40% of ALT tumors lacked genomic alterations in known ALT-associated genes. Patients with high-risk neuroblastoma were classified into three subgroups (TERT-high, ALT, and TERT-low/non-ALT) based on presence of C-circles and TERT mRNA expression (above or below median TERT expression). Event-free survival was similar among TERT-high, ALT, or TERT-low/non-ALT patients. However, overall survival (OS) for TERT-low/non-ALT patients was significantly higher relative to TERT-high or ALT patients (log-rank test; < 0.01) independent of current clinical and molecular prognostic markers. Consistent with the observed higher OS in patients with TERT-low/non-ALT tumors, continuous shortening of telomeres and decreasing viability occurred in low TERT-expressing, non-ALT patient-derived high-risk neuroblastoma cell lines. These findings demonstrate that assaying TMM with TERT mRNA expression and C-circles provides precise stratification of high-risk neuroblastoma into three subgroups with substantially different OS: a previously undescribed TERT-low/non-ALT cohort with superior OS (even after relapse) and two cohorts of patients with poor survival that have distinct molecular therapeutic targets. SIGNIFICANCE: These findings assess telomere maintenance mechanisms with TERT mRNA and the ALT DNA biomarker C-circles to stratify neuroblastoma into three groups, with distinct overall survival independent of currently used clinical risk classifiers.
Keywords: Cell Line, Tumor; Child; Child, Preschool; Disease-Free Survival; Female; Follow-Up Studies; Gene Expression Regulation, Neoplastic; Humans; Infant; Male; Neoplasm Recurrence, Local; Neuroblastoma; RNA, Messenger; RNA-Seq; Telomerase; Telomere; Telomere Homeostasis; Whole Genome Sequencing; X-linked Nuclear Protein; Xenograft Model Antitumor Assays

Variants, N-Acetylated Amino Acids, and Progression of CKD. - Luo, Shengyuan; Surapaneni, Aditya; Zheng, Zihe; Rhee, Eugene P; Coresh, Josef; Hung, Adriana M; Nadkarni, Girish N; Yu, Bing; Eric Boerwinkle; Tin, Adrienne; Arking, Dan E; Steinbrenner, Inga; et al. (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: Genetic variants in , a liver- and kidney-specific acetyltransferase encoding gene, have been associated with eGFR and CKD in European populations. Higher circulating levels of two -associated metabolites, N--acetylornithine and N-acetyl-1-methylhistidine, have been linked to lower eGFR and higher risk of incident CKD in the Black population. We aimed to expand upon prior studies to investigate associations between rs13538, a missense variant in , N-acetylated amino acids, and kidney failure in multiple, well-characterized cohorts. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We conducted analyses among participants with genetic and/or serum metabolomic data in the African American Study of Kidney Disease and Hypertension (AASK; =962), the Atherosclerosis Risk in Communities (ARIC) study (=1050), and Bio, an electronic health record-linked biorepository (=680). Separately, we evaluated associations between rs13538, urinary N-acetylated amino acids, and kidney failure in participants in the German CKD (GCKD) study (=1624). RESULTS: Of 31 N-acetylated amino acids evaluated, the circulating and urinary levels of 14 were associated with rs13538 (<0.05/31). Higher circulating levels of five of these N-acetylated amino acids, namely, N--acetylornithine, N-acetyl-1-methylhistidine, N-acetyl-3-methylhistidine, N-acetylhistidine, and N2,N5-diacetylornithine, were associated with kidney failure, after adjustment for confounders and combining results in meta-analysis (combined hazard ratios per two-fold higher amino acid levels: 1.48, 1.44, 1.21, 1.65, and 1.41, respectively; 95% confidence intervals: 1.21 to 1.81, 1.22 to 1.70, 1.08 to 1.37, 1.29 to 2.10, and 1.17 to 1.71, respectively; all values <0.05/14). None of the urinary levels of these N-acetylated amino acids were associated with kidney failure in the GCKD study. CONCLUSIONS: We demonstrate significant associations between an gene variant and 14 N-acetylated amino acids, five of which had circulation levels that were associated with kidney failure.
Keywords: Acetylation; Acetyltransferases; Adult; Aged; Aged, 80 and over; Amino Acids; Black People; Disease Progression; Female; Follow-Up Studies; Glomerular Filtration Rate; Histidine; Humans; Kidney Failure, Chronic; Male; Metabolomics; Methylhistidines; Middle Aged; Ornithine; Polymorphism, Single Nucleotide; Prospective Studies; Randomized Controlled Trials as Topic; White People

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Exome Sequencing; Female; Gene Expression Regulation; Haplotypes; Humans; Immunity; Immunoglobulin G; Kruppel-Like Transcription Factors; Male; Polymorphism, Genetic; RNA, Long Noncoding; Transcription, Genetic

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Black or African American; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

Ancestral Admixture Is the Main Determinant of Global Biodiversity in Fission Yeast. - Tusso, Sergio; Nieuwenhuis, Bart P S; Fritz J Sedlazeck; Davey, John W; Jeffares, Daniel C; Wolf, Jochen B W (Mol Biol Evol, 2019)
Mutation and recombination are key evolutionary processes governing phenotypic variation and reproductive isolation. We here demonstrate that biodiversity within all globally known strains of Schizosaccharomyces pombe arose through admixture between two divergent ancestral lineages. Initial hybridization was inferred to have occurred ∼20-60 sexual outcrossing generations ago consistent with recent, human-induced migration at the onset of intensified transcontinental trade. Species-wide heritable phenotypic variation was explained near-exclusively by strain-specific arrangements of alternating ancestry components with evidence for transgressive segregation. Reproductive compatibility between strains was likewise predicted by the degree of shared ancestry. To assess the genetic determinants of ancestry block distribution across the genome, we characterized the type, frequency, and position of structural genomic variation using nanopore and single-molecule real-time sequencing. Despite being associated with double-strand break initiation points, over 800 segregating structural variants exerted overall little influence on the introgression landscape or on reproductive compatibility between strains. In contrast, we found strong ancestry disequilibrium consistent with negative epistatic selection shaping genomic ancestry combinations during the course of hybridization. This study provides a detailed, experimentally tractable example that genomes of natural populations are mosaics reflecting different evolutionary histories. Exploiting genome-wide heterogeneity in the history of ancestral recombination and lineage-specific mutations sheds new light on the population history of S. pombe and highlights the importance of hybridization as a creative force in generating biodiversity.
Keywords: Epistasis, Genetic; Genetic Variation; Genomic Structural Variation; Hybridization, Genetic; Reproductive Isolation; Schizosaccharomyces; Whole Genome Sequencing

Author Correction: Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Author Correction: Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2019)
Christina M. Lill, who contributed to analysis of data, was inadvertently omitted from the author list in the originally published version of this article. This has now been corrected in both the PDF and HTML versions of the article.

Bi-allelic Pathogenic Variants in TUBGCP2 Cause Microcephaly and Lissencephaly Spectrum Disorders. - Mitani, Tadahiro; Punetha, Jaya; Akalin, Ibrahim; Pehlivan, Davut; Dawidziuk, Mateusz; Coban Akdemir, Zeynep; Yilmaz, Sarenur; Aslan, Ezgi; Hunter, Jill V; Hijazi, Hadia; Grochowski, Christopher M; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2019)
Lissencephaly comprises a spectrum of malformations of cortical development. This spectrum includes agyria, pachygyria, and subcortical band heterotopia; each represents anatomical malformations of brain cortical development caused by neuronal migration defects. The molecular etiologies of neuronal migration anomalies are highly enriched for genes encoding microtubules and microtubule-associated proteins, and this enrichment highlights the critical role for these genes in cortical growth and gyrification. Using exome sequencing and family based rare variant analyses, we identified a homozygous variant (c.997C>T [p.Arg333Cys]) in TUBGCP2, encoding gamma-tubulin complex protein 2 (GCP2), in two individuals from a consanguineous family; both individuals presented with microcephaly and developmental delay. GCP2 forms the multiprotein γ-tubulin ring complex (γ-TuRC) together with γ-tubulin and other GCPs to regulate the assembly of microtubules. By querying clinical exome sequencing cases and through GeneMatcher-facilitated collaborations, we found three additional families with bi-allelic variation and similarly affected phenotypes including a homozygous variant (c.1843G>C [p.Ala615Pro]) in two families and compound heterozygous variants consisting of one missense variant (c.889C>T [p.Arg297Cys]) and one splice variant (c.2025-2A>G) in another family. Brain imaging from all five affected individuals revealed varying degrees of cortical malformations including pachygyria and subcortical band heterotopia, presumably caused by disruption of neuronal migration. Our data demonstrate that pathogenic variants in TUBGCP2 cause an autosomal recessive neurodevelopmental trait consisting of a neuronal migration disorder, and our data implicate GCP2 as a core component of γ-TuRC in neuronal migrating cells.
Keywords: Alleles; Brain; Cell Movement; Child; Exome; Female; Genetic Variation; Homozygote; Humans; Lissencephaly; Male; Microcephaly; Microtubule-Associated Proteins; Microtubules; Nervous System Malformations; Neurons; Phenotype; Tubulin

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Bo Yuan; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

The comparative genomics and complex population history of baboons. - Jeffrey Rogers; Raveendran, Muthuswamy; R. Alan Harris; Mailund, Thomas; Leppälä, Kalle; Athanasiadis, Georgios; Schierup, Mikkel Heide; Cheng, Jade; Munch, Kasper; Walker, Jerilyn A; Konkel, Miriam K; Jordan, Vallmer; et al. (Sci Adv, 2019)
Recent studies suggest that closely related species can accumulate substantial genetic and phenotypic differences despite ongoing gene flow, thus challenging traditional ideas regarding the genetics of speciation. Baboons (genus ) are Old World monkeys consisting of six readily distinguishable species. Baboon species hybridize in the wild, and prior data imply a complex history of differentiation and introgression. We produced a reference genome assembly for the olive baboon () and whole-genome sequence data for all six extant species. We document multiple episodes of admixture and introgression during the radiation of baboons, thus demonstrating their value as a model of complex evolutionary divergence, hybridization, and reticulation. These results help inform our understanding of similar cases, including modern humans, Neanderthals, Denisovans, and other ancient hominins.
Keywords: Animals; Base Sequence; Biological Evolution; Female; Gene Flow; Genomics; Haplotypes; Humans; Hybridization, Genetic; Male; Papio; Phylogeny; Polymorphism, Genetic; Whole Genome Sequencing

Correction to: De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
It was highlighted that the original article [1] contained a typographical error in the Results section. Subject 17 was incorrectly cited as Subject 1. This Correction article shows the revised statement. The original article has been updated.

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Delineating the expanding phenotype associated with SCAPER gene mutation. - Fasham, James; Arno, Gavin; Lin, Siying; Xu, Mingchu; Carss, Keren J; Hull, Sarah; Lane, Amelia; Robson, Anthony G; Wenger, Olivia; Self, Jay E; Harlalka, Gaurav V; Salter, Claire G; et al. (Am J Med Genet A, 2019)
Keywords: Adolescent; Adult; Carrier Proteins; Child; Consanguinity; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Phenotype; Young Adult

Diversity and evolution of the transposable element repertoire in arthropods with particular reference to insects. - Petersen, Malte; Armisén, David; Richard A Gibbs; Hering, Lars; Khila, Abderrahman; Mayer, Georg; Richards, Stephen; Niehuis, Oliver; Misof, Bernhard (BMC Evol Biol, 2019)
BACKGROUND: Transposable elements (TEs) are a major component of metazoan genomes and are associated with a variety of mechanisms that shape genome architecture and evolution. Despite the ever-growing number of insect genomes sequenced to date, our understanding of the diversity and evolution of insect TEs remains poor. RESULTS: Here, we present a standardized characterization and an order-level comparison of arthropod TE repertoires, encompassing 62 insect and 11 outgroup species. The insect TE repertoire contains TEs of almost every class previously described, and in some cases even TEs previously reported only from vertebrates and plants. Additionally, we identified a large fraction of unclassifiable TEs. We found high variation in TE content, ranging from less than 6% in the antarctic midge (Diptera), the honey bee and the turnip sawfly (Hymenoptera) to more than 58% in the malaria mosquito (Diptera) and the migratory locust (Orthoptera), and a possible relationship between the content and diversity of TEs and the genome size. CONCLUSION: While most insect orders exhibit a characteristic TE composition, we also observed intraordinal differences, e.g., in Diptera, Hymenoptera, and Hemiptera. Our findings shed light on common patterns and reveal lineage-specific differences in content and evolution of TEs in insects. We anticipate our study to provide the basis for future comparative research on the insect TE repertoire.
Keywords: Animals; Antarctic Regions; Base Sequence; DNA Transposable Elements; Evolution, Molecular; Genetic Variation; Genome Size; Genome, Insect; Insecta; Phylogeny

Efficient Variant Set Mixed Model Association Tests for Continuous and Binary Traits in Large-Scale Whole-Genome Sequencing Studies. - Chen, Han; Huffman, Jennifer E; Brody, Jennifer A; Wang, Chaolong; Lee, Seunggeun; Li, Zilin; Gogarten, Stephanie M; Sofer, Tamar; Bielak, Lawrence F; Bis, Joshua C; Blangero, John; Bowler, Russell P; et al. (Am J Hum Genet, 2019)
With advances in whole-genome sequencing (WGS) technology, more advanced statistical methods for testing genetic association with rare variants are being developed. Methods in which variants are grouped for analysis are also known as variant-set, gene-based, and aggregate unit tests. The burden test and sequence kernel association test (SKAT) are two widely used variant-set tests, which were originally developed for samples of unrelated individuals and later have been extended to family data with known pedigree structures. However, computationally efficient and powerful variant-set tests are needed to make analyses tractable in large-scale WGS studies with complex study samples. In this paper, we propose the variant-set mixed model association tests (SMMAT) for continuous and binary traits using the generalized linear mixed model framework. These tests can be applied to large-scale WGS studies involving samples with population structure and relatedness, such as in the National Heart, Lung, and Blood Institute's Trans-Omics for Precision Medicine (TOPMed) program. SMMATs share the same null model for different variant sets, and a virtue of this null model, which includes covariates only, is that it needs to be fit only once for all tests in each genome-wide analysis. Simulation studies show that all the proposed SMMATs correctly control type I error rates for both continuous and binary traits in the presence of population structure and relatedness. We also illustrate our tests in a real data example of analysis of plasma fibrinogen levels in the TOPMed program (n = 23,763), using the Analysis Commons, a cloud-based computing platform.
Keywords: Chromosomes, Human, Pair 4; Cloud Computing; Female; Fibrinogen; Genetic Association Studies; Genetics, Population; Humans; Male; Models, Genetic; National Heart, Lung, and Blood Institute (U.S.); Precision Medicine; Research Design; Time Factors; United States; Whole Genome Sequencing

Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls. - Flannick, Jason; Mercader, Josep M; Fuchsberger, Christian; Udler, Miriam S; Mahajan, Anubha; Wessel, Jennifer; Teslovich, Tanya M; Caulkins, Lizz; Koesterer, Ryan; Barajas-Olmos, Francisco; Blackwell, Thomas W; Eric Boerwinkle; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 × 10) and candidate genes from knockout mice (P = 5.2 × 10). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.
Keywords: Animals; Case-Control Studies; Decision Support Techniques; Diabetes Mellitus, Type 2; Exome; Exome Sequencing; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Mice; Mice, Knockout

Gene Therapy Rescues Retinal Degeneration in Receptor Expression-Enhancing Protein 6 Mutant Mice. - Zaneveld, Smriti Agrawal; Eblimit, Aiden; Liang, Qingnan; Bertrand, Renae; Wu, Nathaniel; Liu, Hehe; Nguyen, Quynh; Zaneveld, Jacques; Wang, Keqing; Yumei Li; Rui Chen (Hum Gene Ther, 2019)
Hereditary retinal dystrophy is clinically defined as a broad group of chronic and progressive disorders that affect visual function by causing photoreceptor degeneration. Previously, we identified mutations in the gene encoding receptor expression-enhancing protein 6 (REEP6), in individuals with autosomal recessive retinitis pigmentosa (RP), the most common form of inherited retinal dystrophy. One individual was molecularly diagnosed with biallelic REEP6 mutations, a missense mutation over a frameshift mutation. In this study, we generated Reep6 compound heterozygous mice, Reep6, which mimic the patient genotype and recapitulate the early-onset retinal degeneration phenotypes observed in the individual with RP. To determine the feasibility of rescuing the Reep6 mutant phenotype via gene replacement therapy, we delivered Reep6.1, the mouse retina-specific isoform of REEP6, to photoreceptors of Reep6 mutant mice on postnatal day 20. Evaluation of the therapeutic effects 2 months posttreatment showed improvements in the photoresponse as well as preservation of photoreceptor cells. Importantly, guanylyl cyclase 1 (GC1) expression was also restored to the outer segment after treatment. Furthermore, rAAV8-Reep6.1 single treatment in Reep6 mutant mice 1 year postinjection showed significant improvements in retinal function and morphology, suggesting that the treatment is effective even after a prolonged period. Findings from this study show that gene replacement therapy in the retina with rAAV overexpressing Reep6 is effective, preserving photoreceptor function in Reep6 mutant mice. These findings provide evidence that rAAV8-based gene therapy can prolong survival of photoreceptors in vivo and can be potentially used as a therapeutic modality for treatment of patients with RP.
Keywords: Animals; Dependovirus; Disease Models, Animal; Electrophysiological Phenomena; Electroretinography; Endoplasmic Reticulum Stress; Eye Proteins; Gene Expression; Genetic Therapy; Genetic Vectors; Genotype; Guanylate Cyclase; Immunohistochemistry; Light; Membrane Proteins; Mice; Mice, Knockout; Mutation; Photoreceptor Cells; Protein Transport; Receptors, Cell Surface; Retinal Degeneration; Transduction, Genetic; Transgenes

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.
Keywords: Animals; Body Patterning; Embryonic Development; Exome Sequencing; Female; Genetic Association Studies; Genome, Human; Genomics; GTP Phosphohydrolases; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Male; Peroxidases; Zebrafish; Zebrafish Proteins

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Case-Control Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Haplotypes; Humans; Immunity; Lipid Metabolism; Lipids; Male; tau Proteins

Genome-wide patterns of transposon proliferation in an evolutionary young hybrid fish. - Dennenmoser, Stefan; Fritz J Sedlazeck; Schatz, Michael C; Altmüller, Janine; Zytnicki, Matthias; Nolte, Arne W (Mol Ecol, 2019)
Hybridization can induce transposons to jump into new genomic positions, which may result in their accumulation across the genome. Alternatively, transposon copy numbers may increase through nonallelic (ectopic) homologous recombination in highly repetitive regions of the genome. The relative contribution of transposition bursts versus recombination-based mechanisms to evolutionary processes remains unclear because studies on transposon dynamics in natural systems are rare. We assessed the genomewide distribution of transposon insertions in a young hybrid lineage ("invasive Cottus", n = 11) and its parental species Cottus rhenanus (n = 17) and Cottus perifretum(n = 9) using a reference genome assembled from long single molecule pacbio reads. An inventory of transposable elements was reconstructed from the same data and annotated. Transposon copy numbers in the hybrid lineage increased in 120 (15.9%) out of 757 transposons studied here. The copy number increased on average by 69% (range: 10%-197%). Given the age of the hybrid lineage, this suggests that they have proliferated within a few hundred generations since admixture began. However, frequency spectra of transposon insertions revealed no increase in novel and rare insertions across assembled parts of the genome. This implies that transposons were added to repetitive regions of the genome that remain difficult to assemble. Future studies will need to evaluate whether recombination-based mechanisms rather than genomewide transposition may explain the majority of the recent transposon proliferation in the hybrid lineage. Irrespectively of the underlying mechanism, the observed overabundance in repetitive parts of the genome suggests that gene-rich regions are unlikely to be directly affected.
Keywords: Animals; DNA Copy Number Variations; DNA Transposable Elements; Evolution, Molecular; Fishes; Genome; Hybridization, Genetic

Genomic Profiling of Childhood Tumor Patient-Derived Xenograft Models to Enable Rational Clinical Trial Design. - Rokita, Jo Lynne; Rathi, Komal S; Cardenas, Maria F; Upton, Kristen A; Jayaseelan, Joy; Cross, Katherine L; Pfeil, Jacob; Egolf, Laura E; Way, Gregory P; Farrel, Alvin; Kendsersky, Nathan M; Patel, Khushbu; et al. (Cell Rep, 2019)
Accelerating cures for children with cancer remains an immediate challenge as a result of extensive oncogenic heterogeneity between and within histologies, distinct molecular mechanisms evolving between diagnosis and relapsed disease, and limited therapeutic options. To systematically prioritize and rationally test novel agents in preclinical murine models, researchers within the Pediatric Preclinical Testing Consortium are continuously developing patient-derived xenografts (PDXs)-many of which are refractory to current standard-of-care treatments-from high-risk childhood cancers. Here, we genomically characterize 261 PDX models from 37 unique pediatric cancers; demonstrate faithful recapitulation of histologies and subtypes; and refine our understanding of relapsed disease. In addition, we use expression signatures to classify tumors for TP53 and NF1 pathway inactivation. We anticipate that these data will serve as a resource for pediatric oncology drug development and will guide rational clinical trial design for children with cancer.
Keywords: Animals; Cell Line, Tumor; Central Nervous System Neoplasms; Child; Clinical Trials as Topic; Disease Models, Animal; Exome Sequencing; Genomics; Humans; Mice; Mutation; Neuroblastoma; Neurofibromin 1; Osteosarcoma; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Rhabdomyosarcoma; Sarcoma, Ewing; Tumor Suppressor Protein p53; Wilms Tumor; Xenograft Model Antitumor Assays

HFE H63D Polymorphism and the Risk for Systemic Hypertension, Myocardial Remodeling, and Adverse Cardiovascular Events in the ARIC Study. - Selvaraj, Senthil; Seidelmann, Sara; Silvestre, Odilson M; Claggett, Brian; Ndumele, Chiadi E; Cheng, Susan; Yu, Bing; Fernandes-Silva, Miguel M; Grove, Megan L; Eric Boerwinkle; Shah, Amil M; Solomon, Scott D (Hypertension, 2019)
H63D has been identified as a novel locus associated with the development of hypertension. The quantitative risks for hypertension, cardiac remodeling, and adverse events are not well studied. We analyzed white participants from the ARIC study (Atherosclerosis Risk in Communities) with H63D genotyping (N=10 902). We related genotype status to prevalence of hypertension at each of 5 study visits and risk for adverse cardiovascular events. Among visit 5 participants (N=4507), we related genotype status to echocardiographic features. Frequencies of wild type (WT)/WT, H63D/WT, and H63D/H63D were 73%, 24.6%, and 2.4%. The average age at baseline was 54.9±5.7 years and 47% were men. Participants carrying the H63D variant had higher systolic blood pressure ( P=0.004), diastolic blood pressure (0.012), and more frequently had hypertension ( P<0.001). Compared with WT/WT, H63D/WT and H63D/H63D participants had a 2% to 4% and 4% to 7% absolute increase in hypertension risk at each visit, respectively. The population attributable risk of H63D for hypertension among individuals aged 45 to 64 was 3.2% (95% CI, 1.3-5.1%) and 1.3% (95% CI, 0.0-2.4%) among individuals >65 years. After 25 years of follow-up, there was no relationship between genotype status and any outcome ( P>0.05). H63D/WT and H63D/H63D genotypes were associated with small differences in cardiac remodeling. In conclusion, the HFE H63D variant confers an increased risk for hypertension per allele and, given its frequency, accounts for a significant number of cases of hypertension. However, there was no increased risk for adverse cardiovascular events or substantial left ventricular remodeling.
Keywords: Cardiovascular Diseases; Echocardiography; Female; Genetic Predisposition to Disease; Hemochromatosis Protein; Humans; Hypertension; Male; Middle Aged; Mutation; Polymorphism, Genetic; Risk Assessment; United States; Ventricular Remodeling

Homozygous Missense Variants in NTNG2, Encoding a Presynaptic Netrin-G2 Adhesion Protein, Lead to a Distinct Neurodevelopmental Disorder. - Dias, Caroline M; Punetha, Jaya; Zheng, Céline; Mazaheri, Neda; Rad, Abolfazl; Efthymiou, Stephanie; Petersen, Andrea; Dehghani, Mohammadreza; Pehlivan, Davut; Partlow, Jennifer N; Posey, Jennifer E; Salpietro, Vincenzo; et al. (Am J Hum Genet, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Exome Sequencing; Female; GPI-Linked Proteins; Homozygote; Humans; Intellectual Disability; Male; Mutation, Missense; Netrins; Neurodevelopmental Disorders; Pedigree; Young Adult

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.
Keywords: Cohort Studies; Diabetes Mellitus; Female; Genetic Variation; Glycated Hemoglobin; Humans; Male; Polymorphism, Single Nucleotide; Population Groups; Precision Medicine

Improved annotation of the insect vector of citrus greening disease: biocuration by a diverse genomics community. - Saha, Surya; Hosmani, Prashant S; Villalobos-Ayala, Krystal; Miller, Sherry; Shippy, Teresa; Flores, Mirella; Rosendale, Andrew; Cordola, Chris; Bell, Tracey; Mann, Hannah; DeAvila, Gabe; DeAvila, Daniel; et al. (Database (Oxford), 2019)

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Exome Sequencing; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data. - He, Karen Y; Li, Xiaoyin; Kelly, Tanika N; Liang, Jingjing; Cade, Brian E; Assimes, Themistocles L; Becker, Lewis C; Beitelshees, Amber L; Bress, Adam P; Chang, Yen-Pei Christy; Chen, Yii-Der Ida; de Vries, Paul S; et al. (Hum Genet, 2019)
In this study, we investigated low-frequency and rare variants associated with blood pressure (BP) by focusing on a linkage region on chromosome 16p13. We used whole genome sequencing (WGS) data obtained through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program on 395 Cleveland Family Study (CFS) European Americans (CFS-EA). By analyzing functional coding variants and non-coding rare variants with CADD score > 10 residing within the chromosomal region in families with linkage evidence, we observed 25 genes with nominal statistical evidence (burden or SKAT p < 0.05). One of the genes is RBFOX1, an evolutionarily conserved RNA-binding protein that regulates tissue-specific alternative splicing that we previously reported to be associated with BP using exome array data in CFS. After follow-up analysis of the 25 genes in ten independent TOPMed studies with individuals of European, African, and East Asian ancestry, and Hispanics (N = 29,988), we identified variants in SLX4 (p = 2.19 × 10) to be significantly associated with BP traits when accounting for multiple testing. We also replicated the associations previously reported for RBFOX1 (p = 0.007). Follow-up analysis with GTEx eQTL data shows SLX4 variants are associated with gene expression in coronary artery, multiple brain tissues, and right atrial appendage of the heart. Our study demonstrates that linkage analysis of family data can provide an efficient approach for detecting rare variants associated with complex traits in WGS data.
Keywords: Alternative Splicing; Blood Pressure; Chromosomes, Human, Pair 16; Exome; Female; Follow-Up Studies; Genetic Linkage; Genetic Variation; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Male; Recombinases; RNA Splicing Factors

Metabolomic Pattern Predicts Incident Coronary Heart Disease. - Wang, Zhe; Zhu, Cong; Nambi, Vijay; Morrison, Alanna C; Folsom, Aaron R; Ballantyne, Christie M; Eric Boerwinkle; Yu, Bing (Arterioscler Thromb Vasc Biol, 2019)
Objective- Alterations in the serum metabolome may be detectable in at-risk individuals before the onset of coronary heart disease (CHD). Identifying metabolomic signatures associated with CHD may provide insight into disease pathophysiology and prevention. Approach and Results- Metabolomic profiling (chromatography-mass spectrometry) was performed in 2232 African Americans and 1366 European Americans from the ARIC study (Atherosclerosis Risk in Communities). We applied Cox regression with least absolute shrinkage and selection operator to select metabolites associated with incident CHD. A metabolite risk score was constructed to evaluate whether the metabolite risk score predicted CHD risk beyond traditional risk factors. After 30 years of follow-up, we observed 633 incident CHD cases. Thirty-two metabolites were selected by least absolute shrinkage and selection operator to be associated with CHD, and 19 of the 32 showed significant individual associations with CHD, including a sugar substitute, erythritol. Theophylline (hazard ratio [95% CI] =1.16 [1.09-1.25]) and gamma-linolenic acid (hazard ratio [95% CI] =0.89 [0.81-0.97]) showed the greatest positive and negative associations with CHD, respectively. A 1 SD greater standardized metabolite risk score was associated with a 1.37-fold higher risk of CHD (hazard ratio [95% CI] =1.37 [1.27-1.47]). Adding the metabolite risk score to the traditional risk factors significantly improved model predictive performance (30-year risk prediction: Δ C statistics [95% CI] =0.016 [0.008-0.024], continuous net reclassification index [95% CI] =0.522 [0.480-0.556], integrated discrimination index [95% CI] =0.038 [0.019-0.065]). Conclusions- We identified 19 metabolites from known and novel metabolic pathways that collectively improved CHD risk prediction. Visual Overview- An online visual overview is available for this article.
Keywords: Atherosclerosis; Coronary Disease; Female; Humans; Male; Metabolomics; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Factors

Metabolomics Identifies Novel Blood Biomarkers of Pulmonary Function and COPD in the General Population. - Yu, Bing; Flexeder, Claudia; McGarrah, Robert W; Wyss, Annah; Morrison, Alanna C; North, Kari E; Eric Boerwinkle; Kastenmüller, Gabi; Gieger, Christian; Suhre, Karsten; Karrasch, Stefan; Peters, Annette; et al. (Metabolites, 2019)
Determination of metabolomic signatures of pulmonary function and chronic obstructive pulmonary disease (COPD) in the general population could aid in identification and understanding of early disease processes. Metabolome measurements were performed on serum from 4742 individuals (2354 African-Americans and 1529 European-Americans from the Atherosclerosis Risk in Communities study and 859 Europeans from the Cooperative Health Research in the Region of Augsburg study). We examined 368 metabolites in relation to cross-sectional measures of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), their ratio (FEV1/FVC) and COPD using multivariable regression followed by meta-analysis. At a false discovery rate of 0.05, 95 metabolites were associated with FEV1 and 100 with FVC (73 overlapping), including inverse associations with branched-chain amino acids and positive associations with glutamine. Ten metabolites were associated with FEV1/FVC and seventeen with COPD (393 cases). Enriched pathways of amino acid metabolism were identified. Associations with FEV1 and FVC were not driven by individuals with COPD. We identified novel metabolic signatures of pulmonary function and COPD in African and European ancestry populations. These may allow development of biomarkers in the general population of early disease pathogenesis, before pulmonary function has decreased to levels diagnostic for COPD.

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Amino Acid Sequence; Autistic Disorder; Child; Child, Preschool; Female; Genetic Association Studies; Humans; Infant; Intellectual Disability; Male; Mutation, Missense; Nuclear Proteins; Prognosis; Sequence Homology; Syndrome; Young Adult

Multiancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
A person's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multiancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in stage 1 (genome-wide discovery) and 66 studies in stage 2 (focused follow-up), for a total of 394,584 individuals from 5 ancestry groups. Analyses covered the period July 2014-November 2017. Genetic main effects and interaction effects were jointly assessed by means of a 2-degrees-of-freedom (df) test, and a 1-df test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in stage 1 and were evaluated in stage 2, followed by combined analyses of stage 1 and stage 2. In the combined analysis of stages 1 and 2, a total of 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2-df tests, of which 18 were novel. No genome-wide-significant associations were found testing the interaction effect alone. The novel loci included several genes (proprotein convertase subtilisin/kexin type 5 (PCSK5), vascular endothelial growth factor B (VEGFB), and apolipoprotein B mRNA editing enzyme, catalytic polypeptide 1 (APOBEC1) complementation factor (A1CF)) that have a putative role in lipid metabolism on the basis of existing evidence from cellular and experimental models.
Keywords: Adolescent; Adult; Aged; Alcohol Drinking; Cholesterol, HDL; Cholesterol, LDL; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Lipids; Male; Middle Aged; Phenotype; Racial Groups; Triglycerides; Vascular Endothelial Growth Factor B; Young Adult

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Linkage Disequilibrium; Lipids; Male; Middle Aged; Smoking; Young Adult

A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure. - Sung, Yun Ju; de Las Fuentes, Lisa; Winkler, Thomas W; Chasman, Daniel I; Bentley, Amy R; Kraja, Aldi T; Ntalla, Ioanna; Warren, Helen R; Guo, Xiuqing; Schwander, Karen; Manning, Alisa K; Brown, Michael R; et al. (Hum Mol Genet, 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 × 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Antiporters; Arterial Pressure; Blood Pressure; Caspase 9; Ethnicity; Female; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Middle Aged; Polymorphism, Genetic; Racial Groups; Receptors, Vasopressin; Smoking; Sulfate Transporters; Tumor Suppressor Proteins; Young Adult

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Chromosome Mapping; Female; Genetic Loci; Humans; Lipids; Male; Middle Aged; Phylogeny; Polymorphism, Single Nucleotide; Sleep; Young Adult

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian People; Black People; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic or Latino; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; White People; Young Adult

A novel disorder involving dyshematopoiesis, inflammation, and HLH due to aberrant CDC42 function. - Lam, Michael T; Coppola, Simona; Krumbach, Oliver H F; Prencipe, Giusi; Insalaco, Antonella; Cifaldi, Cristina; Brigida, Immacolata; Zara, Erika; Scala, Serena; Di Cesare, Silvia; Martinelli, Simone; Di Rocco, Martina; et al. (J Exp Med, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by immune dysregulation due to inadequate restraint of overactivated immune cells and is associated with a variable clinical spectrum having overlap with more common pathophysiologies. HLH is difficult to diagnose and can be part of inflammatory syndromes. Here, we identify a novel hematological/autoinflammatory condition (NOCARH syndrome) in four unrelated patients with superimposable features, including neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and HLH. Patients shared the same de novo mutation (Chr1:22417990C>T, p.R186C) and altered hematopoietic compartment, immune dysregulation, and inflammation. mutations had been associated with syndromic neurodevelopmental disorders. In vitro and in vivo assays documented unique effects of p.R186C on CDC42 localization and function, correlating with the distinctiveness of the trait. Emapalumab was critical to the survival of one patient, who underwent successful bone marrow transplantation. Early recognition of the disorder and establishment of treatment followed by bone marrow transplant are important to survival.
Keywords: Alleles; Amino Acid Substitution; Animals; Binding Sites; cdc42 GTP-Binding Protein; Cell Line, Tumor; Child; Disease Susceptibility; Female; Genetic Association Studies; Genotype; Humans; Infant; Lymphohistiocytosis, Hemophagocytic; Male; Mice; Models, Molecular; Molecular Conformation; Mutation; Phenotype; Protein Binding

Pharmacogenomic Next-Generation DNA Sequencing: Lessons from the Identification and Functional Characterization of Variants of Unknown Significance in and . - Devarajan, Sandhya; Moon, Irene; Ho, Ming-Fen; Larson, Nicholas B; Neavin, Drew R; Moyer, Ann M; Black, John L; Bielinski, Suzette J; Steven E Scherer; Wang, Liewei; Weinshilboum, Richard M; Reid, Joel M (Drug Metab Dispos, 2019)
and are highly polymorphic pharmacogenes; however, clinically actionable genetic variability in drug metabolism due to these genes has been limited to a few common alleles. The identification and functional characterization of less-common open reading frame sequence variation might help to individualize therapy with drugs that are substrates for the enzymes encoded by these genes. The present study identified seven uncharacterized variants each in and using next-generation sequence data for 1013 subjects, and functionally characterized the encoded proteins. Constructs were created and transiently expressed in COS-1 cells for the assay of protein concentration and enzyme activities using fluorometric substrates and liquid chromatography- tandem mass spectrometry with tolbutamide () and (S)-mephenytoin () as prototypic substrates. The results were compared with the SIFT, Polyphen, and Provean functional prediction software programs. Cytochrome P450 oxidoreductase (CPR) activities were also determined. Positive correlations were observed between protein content and fluorometric enzyme activity for variants of ( < 0.05) and ( < 0.0005). However, 709G>C and 65A>G activities were much lower than predicted based on protein content. Substrate intrinsic clearance values for 218C>T, 343A>C, and 337G>A, 518C>T, 556C>T, and 557G>A were less than 25% of wild-type allozymes. CPR activity levels were similar for all variants. In summary, sequencing of and in 1013 subjects identified low-frequency variants that had not previously been functionally characterized. In silico predictions were not always consistent with functional assay results. These observations emphasize the need for high-throughput methods for pharmacogene variant mutagenesis and functional characterization.

Protein-coding variants implicate novel genes related to lipid homeostasis contributing to body-fat distribution. - Justice, Anne E; Karaderi, Tugce; Highland, Heather M; Young, Kristin L; Graff, Mariaelisa; Lu, Yingchang; Turcot, Valérie; Auer, Paul L; Fine, Rebecca S; Guo, Xiuqing; Schurmann, Claudia; Lempradl, Adelheid; et al. (Nat Genet, 2019)
Body-fat distribution is a risk factor for adverse cardiovascular health consequences. We analyzed the association of body-fat distribution, assessed by waist-to-hip ratio adjusted for body mass index, with 228,985 predicted coding and splice site variants available on exome arrays in up to 344,369 individuals from five major ancestries (discovery) and 132,177 European-ancestry individuals (validation). We identified 15 common (minor allele frequency, MAF ≥5%) and nine low-frequency or rare (MAF <5%) coding novel variants. Pathway/gene set enrichment analyses identified lipid particle, adiponectin, abnormal white adipose tissue physiology and bone development and morphology as important contributors to fat distribution, while cross-trait associations highlight cardiometabolic traits. In functional follow-up analyses, specifically in Drosophila RNAi-knockdowns, we observed a significant increase in the total body triglyceride levels for two genes (DNAH10 and PLXND1). We implicate novel genes in fat distribution, stressing the importance of interrogating low-frequency and protein-coding variants.
Keywords: Animals; Body Fat Distribution; Body Mass Index; Case-Control Studies; Drosophila; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeostasis; Humans; Lipids; Male; Proteins; Risk Factors; Waist-Hip Ratio

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Quality control and integration of genotypes from two calling pipelines for whole genome sequence data in the Alzheimer's disease sequencing project. - Naj, Adam C; Lin, Honghuang; Vardarajan, Badri N; White, Simon; Lancour, Daniel; Ma, Yiyi; Schmidt, Michael; Sun, Fangui; Butkiewicz, Mariusz; Bush, William S; Kunkle, Brian W; Malamon, John; et al. (Genomics, 2019)
The Alzheimer's Disease Sequencing Project (ADSP) performed whole genome sequencing (WGS) of 584 subjects from 111 multiplex families at three sequencing centers. Genotype calling of single nucleotide variants (SNVs) and insertion-deletion variants (indels) was performed centrally using GATK-HaplotypeCaller and Atlas V2. The ADSP Quality Control (QC) Working Group applied QC protocols to project-level variant call format files (VCFs) from each pipeline, and developed and implemented a novel protocol, termed "consensus calling," to combine genotype calls from both pipelines into a single high-quality set. QC was applied to autosomal bi-allelic SNVs and indels, and included pipeline-recommended QC filters, variant-level QC, and sample-level QC. Low-quality variants or genotypes were excluded, and sample outliers were noted. Quality was assessed by examining Mendelian inconsistencies (MIs) among 67 parent-offspring pairs, and MIs were used to establish additional genotype-specific filters for GATK calls. After QC, 578 subjects remained. Pipeline-specific QC excluded ~12.0% of GATK and 14.5% of Atlas SNVs. Between pipelines, ~91% of SNV genotypes across all QCed variants were concordant; 4.23% and 4.56% of genotypes were exclusive to Atlas or GATK, respectively; the remaining ~0.01% of discordant genotypes were excluded. For indels, variant-level QC excluded ~36.8% of GATK and 35.3% of Atlas indels. Between pipelines, ~55.6% of indel genotypes were concordant; while 10.3% and 28.3% were exclusive to Atlas or GATK, respectively; and ~0.29% of discordant genotypes were. The final WGS consensus dataset contains 27,896,774 SNVs and 3,133,926 indels and is publicly available.
Keywords: Algorithms; Alzheimer Disease; Female; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Male; Polymorphism, Genetic; Quality Control; Whole Genome Sequencing

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Bo Yuan; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.
Keywords: Chromosomes, Human, Pair 8; Genetic Linkage; Genome-Wide Association Study; GTPase-Activating Proteins; Humans; Oxyhemoglobins; Sleep; Tumor Suppressor Proteins; Whole Genome Sequencing

A strategy for building and using a human reference pangenome. - Llamas, Bastien; Narzisi, Giuseppe; Schneider, Valerie; Audano, Peter A; Biederstedt, Evan; Blauvelt, Lon; Bradbury, Peter; Chang, Xian; Chin, Chen-Shan; Fungtammasan, Arkarachai; Clarke, Wayne E; Cleary, Alan; et al. (F1000Res, 2019)
In March 2019, 45 scientists and software engineers from around the world converged at the University of California, Santa Cruz for the first pangenomics codeathon. The purpose of the meeting was to propose technical specifications and standards for a usable human pangenome as well as to build relevant tools for genome graph infrastructures. During the meeting, the group held several intense and productive discussions covering a diverse set of topics, including advantages of graph genomes over a linear reference representation, design of new methods that can leverage graph-based data structures, and novel visualization and annotation approaches for pangenomes. Additionally, the participants self-organized themselves into teams that worked intensely over a three-day period to build a set of pipelines and tools for specific pangenomic applications. A summary of the questions raised and the tools developed are reported in this manuscript.

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.
Keywords: Animals; Cohort Studies; Disease Models, Animal; Gene Dosage; Humans; Inheritance Patterns; Mice; Models, Genetic; Scoliosis; Spine; T-Box Domain Proteins

Use of >100,000 NHLBI Trans-Omics for Precision Medicine (TOPMed) Consortium whole genome sequences improves imputation quality and detection of rare variant associations in admixed African and Hispanic/Latino populations. - Kowalski, Madeline H; Qian, Huijun; Hou, Ziyi; Rosen, Jonathan D; Tapia, Amanda L; Shan, Yue; Jain, Deepti; Argos, Maria; Arnett, Donna K; Avery, Christy; Barnes, Kathleen C; Becker, Lewis C; et al. (PLoS Genet, 2019)
Most genome-wide association and fine-mapping studies to date have been conducted in individuals of European descent, and genetic studies of populations of Hispanic/Latino and African ancestry are limited. In addition, these populations have more complex linkage disequilibrium structure. In order to better define the genetic architecture of these understudied populations, we leveraged >100,000 phased sequences available from deep-coverage whole genome sequencing through the multi-ethnic NHLBI Trans-Omics for Precision Medicine (TOPMed) program to impute genotypes into admixed African and Hispanic/Latino samples with genome-wide genotyping array data. We demonstrated that using TOPMed sequencing data as the imputation reference panel improves genotype imputation quality in these populations, which subsequently enhanced gene-mapping power for complex traits. For rare variants with minor allele frequency (MAF) < 0.5%, we observed a 2.3- to 6.1-fold increase in the number of well-imputed variants, with 11-34% improvement in average imputation quality, compared to the state-of-the-art 1000 Genomes Project Phase 3 and Haplotype Reference Consortium reference panels. Impressively, even for extremely rare variants with minor allele count <10 (including singletons) in the imputation target samples, average information content rescued was >86%. Subsequent association analyses of TOPMed reference panel-imputed genotype data with hematological traits (hemoglobin (HGB), hematocrit (HCT), and white blood cell count (WBC)) in ~21,600 African-ancestry and ~21,700 Hispanic/Latino individuals identified associations with two rare variants in the HBB gene (rs33930165 with higher WBC [p = 8.8x10-15] in African populations, rs11549407 with lower HGB [p = 1.5x10-12] and HCT [p = 8.8x10-10] in Hispanics/Latinos). By comparison, neither variant would have been genome-wide significant if either 1000 Genomes Project Phase 3 or Haplotype Reference Consortium reference panels had been used for imputation. Our findings highlight the utility of the TOPMed imputation reference panel for identification of novel rare variant associations not previously detected in similarly sized genome-wide studies of under-represented African and Hispanic/Latino populations.
Keywords: Adult; Aged; Aged, 80 and over; beta-Globins; Black or African American; Computational Biology; Databases, Genetic; Female; Gene Frequency; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Genotyping Techniques; Hispanic or Latino; Humans; Linkage Disequilibrium; Male; Middle Aged; Precision Medicine; United States; Whole Genome Sequencing

Accurate detection of complex structural variations using single-molecule sequencing. - Sedlazeck, Fritz J; Rescheneder, Philipp; Smolka, Moritz; Fang, Han; Nattestad, Maria; von Haeseler, Arndt; Schatz, Michael C (Nat Methods, 2018)
Structural variations are the greatest source of genetic variation, but they remain poorly understood because of technological limitations. Single-molecule long-read sequencing has the potential to dramatically advance the field, although high error rates are a challenge with existing methods. Addressing this need, we introduce open-source methods for long-read alignment (NGMLR; https://github.com/philres/ngmlr ) and structural variant identification (Sniffles; https://github.com/fritzsedlazeck/Sniffles ) that provide unprecedented sensitivity and precision for variant detection, even in repeat-rich regions and for complex nested events that can have substantial effects on human health. In several long-read datasets, including healthy and cancerous human genomes, we discovered thousands of novel variants and categorized systematic errors in short-read approaches. NGMLR and Sniffles can automatically filter false events and operate on low-coverage data, thereby reducing the high costs that have hindered the application of long reads in clinical and research settings.
Keywords: DNA Mutational Analysis; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA

Allelic decomposition and exact genotyping of highly polymorphic and structurally variant genes. - Numanagić, Ibrahim; Malikić, Salem; Ford, Michael; Qin, Xiang; Toji, Lorraine; Radovich, Milan; Skaar, Todd C; Pratt, Victoria M; Berger, Bonnie; Scherer, Steve; Sahinalp, S Cenk (Nat Commun, 2018)
High-throughput sequencing provides the means to determine the allelic decomposition for any gene of interest-the number of copies and the exact sequence content of each copy of a gene. Although many clinically and functionally important genes are highly polymorphic and have undergone structural alterations, no high-throughput sequencing data analysis tool has yet been designed to effectively solve the full allelic decomposition problem. Here we introduce a combinatorial optimization framework that successfully resolves this challenging problem, including for genes with structural alterations. We provide an associated computational tool Aldy that performs allelic decomposition of highly polymorphic, multi-copy genes through using whole or targeted genome sequencing data. For a large diverse sequencing data set, Aldy identifies multiple rare and novel alleles for several important pharmacogenes, significantly improving upon the accuracy and utility of current genotyping assays. As more data sets become available, we expect Aldy to become an essential component of genotyping toolkits.
Keywords: Alleles; Chromosome Mapping; Cytochrome P-450 CYP2D6; DNA Copy Number Variations; Genome, Human; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Isoenzymes; Phenotype; Polymorphism, Genetic; Sequence Analysis, DNA; Software

Bi-allelic CCDC47 Variants Cause a Disorder Characterized by Woolly Hair, Liver Dysfunction, Dysmorphic Features, and Global Developmental Delay. - Morimoto, Marie; Waller-Evans, Helen; Ammous, Zineb; Song, Xiaofei; Strauss, Kevin A; Pehlivan, Davut; Gonzaga-Jauregui, Claudia; Puffenberger, Erik G; Holst, Charles R; Karaca, Ender; Brigatti, Karlla W; Maguire, Emily; et al. (Am J Hum Genet, 2018)
Ca signaling is vital for various cellular processes including synaptic vesicle exocytosis, muscle contraction, regulation of secretion, gene transcription, and cellular proliferation. The endoplasmic reticulum (ER) is the largest intracellular Ca store, and dysregulation of ER Ca signaling and homeostasis contributes to the pathogenesis of various complex disorders and Mendelian disease traits. We describe four unrelated individuals with a complex multisystem disorder characterized by woolly hair, liver dysfunction, pruritus, dysmorphic features, hypotonia, and global developmental delay. Through whole-exome sequencing and family-based genomics, we identified bi-allelic variants in CCDC47 that encodes the Ca-binding ER transmembrane protein CCDC47. CCDC47, also known as calumin, has been shown to bind Ca with low affinity and high capacity. In mice, loss of Ccdc47 leads to embryonic lethality, suggesting that Ccdc47 is essential for early development. Characterization of cells from individuals with predicted likely damaging alleles showed decreased CCDC47 mRNA expression and protein levels. In vitro cellular experiments showed decreased total ER Ca storage, impaired Ca signaling mediated by the IPR Ca release channel, and reduced ER Ca refilling via store-operated Ca entry. These results, together with the previously described role of CCDC47 in Ca signaling and development, suggest that bi-allelic loss-of-function variants in CCDC47 underlie the pathogenesis of this multisystem disorder.

Change in Neutrophil-to-lymphocyte ratio (NLR) in response to immune checkpoint blockade for metastatic renal cell carcinoma. - Lalani, Aly-Khan A; Xie, Wanling; Martini, Dylan J; Steinharter, John A; Norton, Craig K; Krajewski, Katherine M; Duquette, Audrey; Bossé, Dominick; Bellmunt, Joaquim; Van Allen, Eliezer M; McGregor, Bradley A; Creighton, Chad J; et al. (J Immunother Cancer, 2018)
BACKGROUND: An elevated Neutrophil-to-lymphocyte ratio (NLR) is associated with worse outcomes in several malignancies. However, its role with contemporary immune checkpoint blockade (ICB) is unknown. We investigated the utility of NLR in metastatic renal cell carcinoma (mRCC) patients treated with PD-1/PD-L1 ICB. METHODS: We examined NLR at baseline and 6 (±2) weeks later in 142 patients treated between 2009 and 2017 at Dana-Farber Cancer Institute (Boston, USA). Landmark analysis at 6 weeks was conducted to explore the prognostic value of relative NLR change on overall survival (OS), progression-free survival (PFS), and objective response rate (ORR). Cox and logistic regression models allowed for adjustment of line of therapy, number of IMDC risk factors, histology and baseline NLR. RESULTS: Median follow up was 16.6 months (range: 0.7-67.8). Median duration on therapy was 5.1 months (<1-61.4). IMDC risk groups were: 18% favorable, 60% intermediate, 23% poor-risk. Forty-four percent were on first-line ICB and 56% on 2nd line or more. Median NLR was 3.9 (1.3-42.4) at baseline and 4.1 (1.1-96.4) at week 6. Patients with a higher baseline NLR showed a trend toward lower ORR, shorter PFS, and shorter OS. Higher NLR at 6 weeks was a significantly stronger predictor of all three outcomes than baseline NLR. Relative NLR change by ≥25% from baseline to 6 weeks after ICB therapy was associated with reduced ORR and an independent prognostic factor for PFS (p < 0.001) and OS (p = 0.004), whereas a decrease in NLR by ≥25% was associated with improved outcomes. CONCLUSIONS: Early decline and NLR at 6 weeks are associated with significantly improved outcomes in mRCC patients treated with ICB. The prognostic value of the readily-available NLR warrants larger, prospective validation.
Keywords: Adult; Aged; Aged, 80 and over; Antineoplastic Agents, Immunological; B7-H1 Antigen; Carcinoma, Renal Cell; Female; Humans; Kidney Neoplasms; Lymphocytes; Male; Middle Aged; Neutrophils; Programmed Cell Death 1 Receptor; Survival Analysis; Treatment Outcome; Young Adult

Characterizing reduced coverage regions through comparison of exome and genome sequencing data across 10 centers. - Sanghvi, Rashesh V; Buhay, Christian J; Powell, Bradford C; Tsai, Ellen A; Dorschner, Michael O; Hong, Celine S; Lebo, Matthew S; Sasson, Ariella; Hanna, David S; McGee, Sean; Bowling, Kevin M; Cooper, Gregory M; et al. (Genet Med, 2018)
PURPOSE: As massively parallel sequencing is increasingly being used for clinical decision making, it has become critical to understand parameters that affect sequencing quality and to establish methods for measuring and reporting clinical sequencing standards. In this report, we propose a definition for reduced coverage regions and describe a set of standards for variant calling in clinical sequencing applications. METHODS: To enable sequencing centers to assess the regions of poor sequencing quality in their own data, we optimized and used a tool (ExCID) to identify reduced coverage loci within genes or regions of particular interest. We used this framework to examine sequencing data from 500 patients generated in 10 projects at sequencing centers in the National Human Genome Research Institute/National Cancer Institute Clinical Sequencing Exploratory Research Consortium. RESULTS: This approach identified reduced coverage regions in clinically relevant genes, including known clinically relevant loci that were uniquely missed at individual centers, in multiple centers, and in all centers. CONCLUSION: This report provides a process road map for clinical sequencing centers looking to perform similar analyses on their data.
Keywords: Base Sequence; Chromosome Mapping; Exome; Exome Sequencing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software; Whole Genome Sequencing

Clinical exome sequencing for fetuses with ultrasound abnormalities and a suspected Mendelian disorder. - Normand, Elizabeth A; Braxton, Alicia; Nassef, Salma; Ward, Patricia A; Vetrini, Francesco; He, Weimin; Patel, Vipulkumar; Qu, Chunjing; Westerfield, Lauren E; Stover, Samantha; Dharmadhikari, Avinash V; Donna M Muzny; et al. (Genome Med, 2018)
BACKGROUND: Exome sequencing is now being incorporated into clinical care for pediatric and adult populations, but its integration into prenatal diagnosis has been more limited. One reason for this is the paucity of information about the clinical utility of exome sequencing in the prenatal setting. METHODS: We retrospectively reviewed indications, results, time to results (turnaround time, TAT), and impact of exome results for 146 consecutive "fetal exomes" performed in a clinical diagnostic laboratory between March 2012 and November 2017. We define a fetal exome as one performed on a sample obtained from a fetus or a product of conception with at least one structural anomaly detected by prenatal imaging or autopsy. Statistical comparisons were performed using Fisher's exact test. RESULTS: Prenatal exome yielded an overall molecular diagnostic rate of 32% (n = 46/146). Of the 46 molecular diagnoses, 50% were autosomal dominant disorders (n = 23/46), 41% were autosomal recessive disorders (n = 19/46), and 9% were X-linked disorders (n = 4/46). The molecular diagnostic rate was highest for fetuses with anomalies affecting multiple organ systems and for fetuses with craniofacial anomalies. Out of 146 cases, a prenatal trio exome option designed for ongoing pregnancies was performed on 62 fetal specimens, resulting in a diagnostic yield of 35% with an average TAT of 14 days for initial reporting (excluding tissue culture time). The molecular diagnoses led to refined recurrence risk estimates, altered medical management, and informed reproductive planning for families. CONCLUSION: Exome sequencing is a useful diagnostic tool when fetal structural anomalies suggest a genetic etiology, but other standard prenatal genetic tests did not provide a diagnosis.
Keywords: Exome Sequencing; Family; Fetus; Genetic Diseases, Inborn; Humans; Inheritance Patterns; Phenotype; Ultrasonography, Prenatal

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease. - Liu, Jiaqi; Zhou, Yangzhong; Liu, Sen; Song, Xiaofei; Yang, Xin-Zhuang; Fan, Yanhui; Chen, Weisheng; Akdemir, Zeynep Coban; Yan, Zihui; Zuo, Yuzhi; Du, Renqian; Liu, Zhenlei; et al. (Hum Genet, 2018)
With the recent advance in genome-wide association studies (GWAS), disease-associated single nucleotide polymorphisms (SNPs) and copy number variants (CNVs) have been extensively reported. Accordingly, the issue of incorrect identification of recombination events that can induce the distortion of multi-allelic or hemizygous variants has received more attention. However, the potential distorted calculation bias or significance of a detected association in a GWAS due to the coexistence of CNVs and SNPs in the same genomic region may remain under-recognized. Here we performed the association study within a congenital scoliosis (CS) cohort whose genetic etiology was recently elucidated as a compound inheritance model, including mostly one rare variant deletion CNV null allele and one common variant non-coding hypomorphic haplotype of the TBX6 gene. We demonstrated that the existence of a deletion in TBX6 led to an overestimation of the contribution of the SNPs on the hypomorphic allele. Furthermore, we generalized a model to explain the calculation bias, or distorted significance calculation for an association study, that can be 'induced' by CNVs at a locus. Meanwhile, overlapping between the disease-associated SNPs from published GWAS and common CNVs (overlap 10%) and pathogenic/likely pathogenic CNVs (overlap 99.69%) was significantly higher than the random distribution (p < 1 × 10 and p = 0.034, respectively), indicating that such co-existence of CNV and SNV alleles might generally influence data interpretation and potential outcomes of a GWAS. We also verified and assessed the influence of colocalizing CNVs to the detection sensitivity of disease-associated SNP variant alleles in another adolescent idiopathic scoliosis (AIS) genome-wide association study. We proposed that detecting co-existent CNVs when evaluating the association signals between SNPs and disease traits could improve genetic model analyses and better integrate GWAS with robust Mendelian principles.
Keywords: Adolescent; Congenital Abnormalities; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Phenotype; Polymorphism, Single Nucleotide; Scoliosis

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.
Keywords: Biophysical Phenomena; Electrocardiography; Genetic Association Studies; Haplotypes; Heart Conduction System; Humans; Ion Channel Gating; Mutation, Missense; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Complex rearrangements and oncogene amplifications revealed by long-read DNA and RNA sequencing of a breast cancer cell line. - Nattestad, Maria; Goodwin, Sara; Ng, Karen; Baslan, Timour; Fritz J Sedlazeck; Rescheneder, Philipp; Garvin, Tyler; Fang, Han; Gurtowski, James; Hutton, Elizabeth; Tseng, Elizabeth; Chin, Chen-Shan; et al. (Genome Res, 2018)
The SK-BR-3 cell line is one of the most important models for HER2+ breast cancers, which affect one in five breast cancer patients. SK-BR-3 is known to be highly rearranged, although much of the variation is in complex and repetitive regions that may be underreported. Addressing this, we sequenced SK-BR-3 using long-read single molecule sequencing from Pacific Biosciences and develop one of the most detailed maps of structural variations (SVs) in a cancer genome available, with nearly 20,000 variants present, most of which were missed by short-read sequencing. Surrounding the important oncogene (also known as ), we discover a complex sequence of nested duplications and translocations, suggesting a punctuated progression. Full-length transcriptome sequencing further revealed several novel gene fusions within the nested genomic variants. Combining long-read genome and transcriptome sequencing enables an in-depth analysis of how SVs disrupt the genome and sheds new light on the complex mechanisms involved in cancer genome evolution.
Keywords: Breast Neoplasms; Female; Gene Amplification; Gene Rearrangement; Genome, Human; Genomic Structural Variation; High-Throughput Nucleotide Sequencing; Humans; MCF-7 Cells; Oncogenes; Receptor, ErbB-2; Repetitive Sequences, Nucleic Acid; Transcriptome

Comprehensive Characterization of Cancer Driver Genes and Mutations. - Bailey, Matthew H; Tokheim, Collin; Porta-Pardo, Eduard; Sengupta, Sohini; Bertrand, Denis; Weerasinghe, Amila; Colaprico, Antonio; Wendl, Michael C; Kim, Jaegil; Reardon, Brendan; Ng, Patrick Kwok-Shing; Jeong, Kang Jin; et al. (Cell, 2018)
Identifying molecular cancer drivers is critical for precision oncology. Multiple advanced algorithms to identify drivers now exist, but systematic attempts to combine and optimize them on large datasets are few. We report a PanCancer and PanSoftware analysis spanning 9,423 tumor exomes (comprising all 33 of The Cancer Genome Atlas projects) and using 26 computational tools to catalog driver genes and mutations. We identify 299 driver genes with implications regarding their anatomical sites and cancer/cell types. Sequence- and structure-based analyses identified >3,400 putative missense driver mutations supported by multiple lines of evidence. Experimental validation confirmed 60%-85% of predicted mutations as likely drivers. We found that >300 MSI tumors are associated with high PD-1/PD-L1, and 57% of tumors analyzed harbor putative clinically actionable events. Our study represents the most comprehensive discovery of cancer genes and mutations to date and will serve as a blueprint for future biological and clinical endeavors.
Keywords: Algorithms; B7-H1 Antigen; Computational Biology; Databases, Genetic; Entropy; Humans; Microsatellite Instability; Mutation; Neoplasms; Principal Component Analysis; Programmed Cell Death 1 Receptor

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

Contributions of rare coding variants in hypotension syndrome genes to population blood pressure variation. - Nandakumar, Priyanka; Morrison, Alanna C; Grove, Megan L; Eric Boerwinkle; Chakravarti, Aravinda (Medicine (Baltimore), 2018)
Rare variants, in particular renal salt handling genes, contribute to monogenic forms of hypertension and hypotension syndromes with electrolyte abnormalities. A study by Ji et al (2008) demonstrated this effect for rare loss-of-function coding variants in SLC12A3 (NCCT), SLC12A1 (NKCC2), and KCNJ1 (ROMK) that led to reduction of ∼6 mm Hg for SBP and ∼3 mm Hg for DBP among carriers in 2492 European ancestry Framingham Heart Study (FHS) subjects. These findings support a potentially large role for these variants in interindividual variation in systolic and diastolic blood pressure (SBP, DBP) in the population. The present study focuses on replicating the analyses completed by Ji et al to identify effects of rare variants in the population-based Atherosclerosis Risk in Communities (ARIC) study.We attempted to replicate the findings by Ji et al by applying their criteria to identify putative loss-of-function variants with allele frequency <0.001 and complete conservation across a set of orthologs, to exome sequencing data from 7444 European ancestry participants of the ARIC study.Although we failed to replicate the previous findings when applying their methods to the ARIC study data, we observed a similar effect when we restricted analyses to the subset of variants they observed.These results simultaneously support the utility of exome sequencing data for studying extremely rare coding variants in hypertension and underscore the need for improved filtering methods for identifying functional variants in human sequences.
Keywords: Black People; Blood Pressure; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Hypertension; Hypotension; Male; Middle Aged; Phenotype; Potassium Channels, Inwardly Rectifying; Prospective Studies; Reproducibility of Results; Risk Factors; Solute Carrier Family 12, Member 1; Solute Carrier Family 12, Member 3; White People

An Epigenome-Wide Association Study of Obesity-Related Traits. - Dhana, Klodian; Braun, Kim V E; Nano, Jana; Voortman, Trudy; Demerath, Ellen W; Guan, Weihua; Fornage, Myriam; van Meurs, Joyce B J; Uitterlinden, André G; Hofman, Albert; Franco, Oscar H; Dehghan, Abbas (Am J Epidemiol, 2018)
We conducted an epigenome-wide association study on obesity-related traits. We used data from 2 prospective, population-based cohort studies: the Rotterdam Study (RS) (2006-2013) and the Atherosclerosis Risk in Communities (ARIC) Study (1990-1992). We used the RS (n = 1,450) as the discovery panel and the ARIC Study (n = 2,097) as the replication panel. Linear mixed-effect models were used to assess the cross-sectional associations between genome-wide DNA methylation in leukocytes and body mass index (BMI) and waist circumference (WC), adjusting for sex, age, smoking, leukocyte proportions, array number, and position on array. The latter 2 variables were modeled as random effects. Fourteen 5'-C-phosphate-G-3' (CpG) sites were associated with BMI and 26 CpG sites with WC in the RS after Bonferroni correction (P < 1.07 × 10-7), of which 12 and 13 CpGs were replicated in the ARIC Study, respectively. The most significant novel CpGs were located on the Musashi RNA binding protein 2 gene (MSI2; cg21139312) and the leucyl-tRNA synthetase 2, mitochondrial gene (LARS2; cg18030453) and were associated with both BMI and WC. CpGs at BRDT, PSMD1, IFI44L, MAP1A, and MAP3K5 were associated with BMI. CpGs at LGALS3BP, MAP2K3, DHCR24, CPSF4L, and TMEM49 were associated with WC. We report novel associations between methylation at MSI2 and LARS2 and obesity-related traits. These results provide further insight into mechanisms underlying obesity-related traits, which can enable identification of new biomarkers in obesity-related chronic diseases.
Keywords: Amino Acyl-tRNA Synthetases; Biomarkers; CpG Islands; DNA Methylation; Epigenomics; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Netherlands; Obesity; Phenotype; Prospective Studies; RNA-Binding Proteins; United States

Functional equivalence of genome sequencing analysis pipelines enables harmonized variant calling across human genetics projects. - Regier, Allison A; Farjoun, Yossi; Larson, David E; Krasheninina, Olga; Kang, Hyun Min; Howrigan, Daniel P; Chen, Bo-Juen; Kher, Manisha; Banks, Eric; Ames, Darren C; English, Adam C; Li, Heng; et al. (Nat Commun, 2018)
Hundreds of thousands of human whole genome sequencing (WGS) datasets will be generated over the next few years. These data are more valuable in aggregate: joint analysis of genomes from many sources increases sample size and statistical power. A central challenge for joint analysis is that different WGS data processing pipelines cause substantial differences in variant calling in combined datasets, necessitating computationally expensive reprocessing. This approach is no longer tenable given the scale of current studies and data volumes. Here, we define WGS data processing standards that allow different groups to produce functionally equivalent (FE) results, yet still innovate on data processing pipelines. We present initial FE pipelines developed at five genome centers and show that they yield similar variant calling results and produce significantly less variability than sequencing replicates. This work alleviates a key technical bottleneck for genome aggregation and helps lay the foundation for community-wide human genetics studies.
Keywords: Genome, Human; Human Genetics; Humans; Whole Genome Sequencing

Gene expression profiling and immune cell-type deconvolution highlight robust disease progression and survival markers in multiple cohorts of CTCL patients. - Lefrançois, Philippe; Xie, Pingxing; Wang, Linghua; Tetzlaff, Michael T; Moreau, Linda; Watters, Andrew K; Netchiporouk, Elena; Provost, Nathalie; Gilbert, Martin; Ni, Xiao; Sasseville, Denis; David A Wheeler; et al. (Oncoimmunology, 2018)
CTCL follows different courses depending on the clinical stage at the time of diagnosis. Patients with early stage Mycosis Fungoides (MF) variant of CTCL may experience an indolent course over decades, whereas patients with advanced MF and Sézary Syndrome (SS) disease at diagnosis, often succumb within 5 years. Even within early stage CTCL/MF, a minority of patients will progress to more advanced stages. We recently generated RNA sequencing data on 284 CTCL-relevant genes for 157 patients and identified differentially expressed genes across stages I-IV. In this study, we aim to validate robust molecular markers linked to disease progression and survival. We performed multiple hypothesis testing-corrected analysis of variance (ANOVA) on the expression of individual genes across all CTCL samples and early stage (≤IIA) CTCL/MF patients. We used immune cell-type deconvolution from gene expression data to estimate immune cell populations. Based on the analysis of all CTCL samples, we identified , and as predictors of disease progression and poor survival. Among early stage (≤IIA) CTCL/MF patients, these 3 genes, along with , were valuable to predict disease progression. We validated these 4 genes in 3 independent, external Sézary Syndrome patient cohorts with RNA-Sequencing data. immune cell-type deconvolution revealed that neutrophil infiltration in early stage MF conveyed a higher risk for disease progression. Also, NK cell infiltration in late stage MF/SS correlated with improved survival. and are robust disease progression and decreased survival biomarkers in CTCL.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.
Keywords: Adult; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cells, Cultured; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genetics, Population; Genome-Wide Association Study; Human Umbilical Vein Endothelial Cells; Humans; Hypertension; Life Style; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Genetic and mechanistic diversity in pediatric hemophagocytic lymphohistiocytosis. - Chinn, Ivan K; Eckstein, Olive S; Peckham-Gregory, Erin C; Goldberg, Baruch R; Forbes, Lisa R; Nicholas, Sarah K; Mace, Emily M; Vogel, Tiphanie P; Abhyankar, Harshal A; Diaz, Maria I; Heslop, Helen E; Krance, Robert A; et al. (Blood, 2018)
The HLH-2004 criteria are used to diagnose hemophagocytic lymphohistiocytosis (HLH), yet concern exists for their misapplication, resulting in suboptimal treatment of some patients. We sought to define the genomic spectrum and associated outcomes of a diverse cohort of children who met the HLH-2004 criteria. Genetic testing was performed clinically or through research-based whole-exome sequencing. Clinical metrics were analyzed with respect to genomic results. Of 122 subjects enrolled over the course of 17 years, 101 subjects received genetic testing. Biallelic familial HLH (fHLH) gene defects were identified in only 19 (19%) and correlated with presentation at younger than 1 year of age ( < .0001). Digenic fHLH variants were observed but lacked statistical support for disease association. In 28 (58%) of 48 subjects, research whole-exome sequencing analyses successfully identified likely molecular explanations, including underlying primary immunodeficiency diseases, dysregulated immune activation and proliferation disorders, and potentially novel genetic conditions. Two-thirds of patients identified by the HLH-2004 criteria had underlying etiologies for HLH, including genetic defects, autoimmunity, and malignancy. Overall survival was 45%, and increased mortality correlated with HLH triggered by infection or malignancy ( < .05). Differences in survival did not correlate with genetic profile or extent of therapy. HLH should be conceptualized as a phenotype of critical illness characterized by toxic activation of immune cells from different underlying mechanisms. In most patients with HLH, targeted sequencing of fHLH genes remains insufficient for identifying pathogenic mechanisms. Whole-exome sequencing, however, may identify specific therapeutic opportunities and affect hematopoietic stem cell transplantation options for these patients.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Genetic Testing; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Lymphohistiocytosis, Hemophagocytic; Male; Multifactorial Inheritance

Genetic Mechanisms of Immune Evasion in Colorectal Cancer. - Grasso, Catherine S; Giannakis, Marios; Wells, Daniel K; Hamada, Tsuyoshi; Mu, Xinmeng Jasmine; Quist, Michael; Nowak, Jonathan A; Nishihara, Reiko; Qian, Zhi Rong; Inamura, Kentaro; Morikawa, Teppei; Nosho, Katsuhiko; et al. (Cancer Discov, 2018)
To understand the genetic drivers of immune recognition and evasion in colorectal cancer, we analyzed 1,211 colorectal cancer primary tumor samples, including 179 classified as microsatellite instability-high (MSI-high). This set includes The Cancer Genome Atlas colorectal cancer cohort of 592 samples, completed and analyzed here. MSI-high, a hypermutated, immunogenic subtype of colorectal cancer, had a high rate of significantly mutated genes in important immune-modulating pathways and in the antigen presentation machinery, including biallelic losses of and genes due to copy-number alterations and copy-neutral loss of heterozygosity. WNT/β-catenin signaling genes were significantly mutated in all colorectal cancer subtypes, and activated WNT/β-catenin signaling was correlated with the absence of T-cell infiltration. This large-scale genomic analysis of colorectal cancer demonstrates that MSI-high cases frequently undergo an immunoediting process that provides them with genetic events allowing immune escape despite high mutational load and frequent lymphocytic infiltration and, furthermore, that colorectal cancer tumors have genetic and methylation events associated with activated WNT signaling and T-cell exclusion. This multi-omic analysis of 1,211 colorectal cancer primary tumors reveals that it should be possible to better monitor resistance in the 15% of cases that respond to immune blockade therapy and also to use WNT signaling inhibitors to reverse immune exclusion in the 85% of cases that currently do not. .
Keywords: beta 2-Microglobulin; Colorectal Neoplasms; DNA Copy Number Variations; DNA Methylation; Germ-Line Mutation; HLA Antigens; Humans; Loss of Heterozygosity; Microsatellite Instability; Tumor Escape; Wnt Signaling Pathway

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Biomarkers; Bipolar Disorder; Body Mass Index; C-Reactive Protein; Child; Female; Genetic Loci; Genome-Wide Association Study; Humans; Inflammation; Liver; Male; Mendelian Randomization Analysis; Metabolic Networks and Pathways; Middle Aged; Schizophrenia; Young Adult

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Protein-Lysine 6-Oxidase; Quantitative Trait Loci; Risk Factors

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Gibbs, Richard A; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

Integrated Molecular Characterization of Testicular Germ Cell Tumors. - Shen, Hui; Shih, Juliann; Hollern, Daniel P; Wang, Linghua; Bowlby, Reanne; Tickoo, Satish K; Thorsson, Vesteinn; Mungall, Andrew J; Newton, Yulia; Hegde, Apurva M; Armenia, Joshua; Sánchez-Vega, Francisco; et al. (Cell Rep, 2018)
We studied 137 primary testicular germ cell tumors (TGCTs) using high-dimensional assays of genomic, epigenomic, transcriptomic, and proteomic features. These tumors exhibited high aneuploidy and a paucity of somatic mutations. Somatic mutation of only three genes achieved significance-KIT, KRAS, and NRAS-exclusively in samples with seminoma components. Integrated analyses identified distinct molecular patterns that characterized the major recognized histologic subtypes of TGCT: seminoma, embryonal carcinoma, yolk sac tumor, and teratoma. Striking differences in global DNA methylation and microRNA expression between histology subtypes highlight a likely role of epigenomic processes in determining histologic fates in TGCTs. We also identified a subset of pure seminomas defined by KIT mutations, increased immune infiltration, globally demethylated DNA, and decreased KRAS copy number. We report potential biomarkers for risk stratification, such as miRNA specifically expressed in teratoma, and others with molecular diagnostic potential, such as CpH (CpA/CpC/CpT) methylation identifying embryonal carcinomas.
Keywords: DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Humans; Male; MicroRNAs; Neoplasms, Germ Cell and Embryonal; Proto-Oncogene Proteins c-kit; ras Proteins; Seminoma; Testicular Neoplasms

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.
Keywords: Atrial Fibrillation; Case-Control Studies; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Quantitative Trait Loci; Transcriptome

Mutation in the intracellular chloride channel CLCC1 associated with autosomal recessive retinitis pigmentosa. - Li, Lin; Jiao, Xiaodong; D'Atri, Ilaria; Ono, Fumihito; Nelson, Ralph; Chan, Chi-Chao; Nakaya, Naoki; Ma, Zhiwei; Ma, Yan; Cai, Xiaoying; Zhang, Longhua; Lin, Siying; et al. (PLoS Genet, 2018)
We identified a homozygous missense alteration (c.75C>A, p.D25E) in CLCC1, encoding a presumptive intracellular chloride channel highly expressed in the retina, associated with autosomal recessive retinitis pigmentosa (arRP) in eight consanguineous families of Pakistani descent. The p.D25E alteration decreased CLCC1 channel function accompanied by accumulation of mutant protein in granules within the ER lumen, while siRNA knockdown of CLCC1 mRNA induced apoptosis in cultured ARPE-19 cells. TALEN KO in zebrafish was lethal 11 days post fertilization. The depressed electroretinogram (ERG) cone response and cone spectral sensitivity of 5 dpf KO zebrafish and reduced eye size, retinal thickness, and expression of rod and cone opsins could be rescued by injection of wild type CLCC1 mRNA. Clcc1+/- KO mice showed decreased ERGs and photoreceptor number. Together these results strongly suggest that intracellular chloride transport by CLCC1 is a critical process in maintaining retinal integrity, and CLCC1 is crucial for survival and function of retinal cells.
Keywords: Animals; Asian People; Cell Line; Chloride Channels; Cytoplasm; Eye Proteins; HEK293 Cells; Homozygote; Humans; Mice; Mice, Knockout; Mutation, Missense; Pakistan; Retina; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa; Zebrafish

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Racial Groups; Young Adult

Perspective on Oncogenic Processes at the End of the Beginning of Cancer Genomics. - Ding, Li; Bailey, Matthew H; Porta-Pardo, Eduard; Thorsson, Vesteinn; Colaprico, Antonio; Bertrand, Denis; Gibbs, David L; Weerasinghe, Amila; Huang, Kuan-Lin; Tokheim, Collin; Cortés-Ciriano, Isidro; Jayasinghe, Reyka; et al. (Cell, 2018)
The Cancer Genome Atlas (TCGA) has catalyzed systematic characterization of diverse genomic alterations underlying human cancers. At this historic junction marking the completion of genomic characterization of over 11,000 tumors from 33 cancer types, we present our current understanding of the molecular processes governing oncogenesis. We illustrate our insights into cancer through synthesis of the findings of the TCGA PanCancer Atlas project on three facets of oncogenesis: (1) somatic driver mutations, germline pathogenic variants, and their interactions in the tumor; (2) the influence of the tumor genome and epigenome on transcriptome and proteome; and (3) the relationship between tumor and the microenvironment, including implications for drugs targeting driver events and immunotherapies. These results will anchor future characterization of rare and common tumor types, primary and relapsed tumors, and cancers across ancestry groups and will guide the deployment of clinical genomic sequencing.
Keywords: Carcinogenesis; Databases, Genetic; DNA Repair; Genes, Neoplasm; Genomics; Humans; Metabolic Networks and Pathways; Microsatellite Instability; Mutation; Neoplasms; Transcriptome; Tumor Microenvironment

Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
Genome-wide association studies (GWAS) have identified >250 loci for body mass index (BMI), implicating pathways related to neuronal biology. Most GWAS loci represent clusters of common, noncoding variants from which pinpointing causal genes remains challenging. Here we combined data from 718,734 individuals to discover rare and low-frequency (minor allele frequency (MAF) < 5%) coding variants associated with BMI. We identified 14 coding variants in 13 genes, of which 8 variants were in genes (ZBTB7B, ACHE, RAPGEF3, RAB21, ZFHX3, ENTPD6, ZFR2 and ZNF169) newly implicated in human obesity, 2 variants were in genes (MC4R and KSR2) previously observed to be mutated in extreme obesity and 2 variants were in GIPR. The effect sizes of rare variants are ~10 times larger than those of common variants, with the largest effect observed in carriers of an MC4R mutation introducing a stop codon (p.Tyr35Ter, MAF = 0.01%), who weighed ~7 kg more than non-carriers. Pathway analyses based on the variants associated with BMI confirm enrichment of neuronal genes and provide new evidence for adipocyte and energy expenditure biology, widening the potential of genetically supported therapeutic targets in obesity.
Keywords: Adult; Animals; Body Mass Index; Drosophila; Energy Intake; Energy Metabolism; Female; Gene Frequency; Genetic Variation; Humans; Male; Obesity; Proteins; Syndrome

Publisher Correction: Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
In the version of this article originally published, the name of author Martin H. de Borst was coded incorrectly in the XML. The error has now been corrected in the HTML version of the paper.

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
In the version of this article originally published, one of the two authors with the name Wei Zhao was omitted from the author list and the affiliations for both authors were assigned to the single Wei Zhao in the author list. In addition, the ORCID for Wei Zhao (Department of Biostatistics and Epidemiology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA) was incorrectly assigned to author Wei Zhou. The errors have been corrected in the HTML and PDF versions of the article.

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
In the published version of this paper, the name of author Emanuele Di Angelantonio was misspelled. This error has now been corrected in the HTML and PDF versions of the article.

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.
Keywords: Alleles; Chromosome Mapping; Diabetes Mellitus, Type 2; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; White People

Sheep genome functional annotation reveals proximal regulatory elements contributed to the evolution of modern breeds. - Naval-Sanchez, Marina; Nguyen, Quan; McWilliam, Sean; Porto-Neto, Laercio R; Tellam, Ross; Vuocolo, Tony; Reverter, Antonio; Perez-Enciso, Miguel; Brauning, Rudiger; Clarke, Shannon; McCulloch, Alan; Zamani, Wahid; et al. (Nat Commun, 2018)
Domestication fundamentally reshaped animal morphology, physiology and behaviour, offering the opportunity to investigate the molecular processes driving evolutionary change. Here we assess sheep domestication and artificial selection by comparing genome sequence from 43 modern breeds (Ovis aries) and their Asian mouflon ancestor (O. orientalis) to identify selection sweeps. Next, we provide a comparative functional annotation of the sheep genome, validated using experimental ChIP-Seq of sheep tissue. Using these annotations, we evaluate the impact of selection and domestication on regulatory sequences and find that sweeps are significantly enriched for protein coding genes, proximal regulatory elements of genes and genome features associated with active transcription. Finally, we find individual sites displaying strong allele frequency divergence are enriched for the same regulatory features. Our data demonstrate that remodelling of gene expression is likely to have been one of the evolutionary forces that drove phenotypic diversification of this common livestock species.
Keywords: Animals; Breeding; Evolution, Molecular; Female; Gene Frequency; Genome; Male; Molecular Sequence Annotation; Phylogeny; Regulatory Elements, Transcriptional; Sheep

Sooty mangabey genome sequence provides insight into AIDS resistance in a natural SIV host. - Palesch, David; Bosinger, Steven E; Tharp, Gregory K; Vanderford, Thomas H; Paiardini, Mirko; Chahroudi, Ann; Johnson, Zachary P; Kirchhoff, Frank; Hahn, Beatrice H; Norgren, Robert B; Patel, Nirav B; Sodora, Donald L; et al. (Nature, 2018)
In contrast to infections with human immunodeficiency virus (HIV) in humans and simian immunodeficiency virus (SIV) in macaques, SIV infection of a natural host, sooty mangabeys (Cercocebus atys), is non-pathogenic despite high viraemia. Here we sequenced and assembled the genome of a captive sooty mangabey. We conducted genome-wide comparative analyses of transcript assemblies from C. atys and AIDS-susceptible species, such as humans and macaques, to identify candidates for host genetic factors that influence susceptibility. We identified several immune-related genes in the genome of C. atys that show substantial sequence divergence from macaques or humans. One of these sequence divergences, a C-terminal frameshift in the toll-like receptor-4 (TLR4) gene of C. atys, is associated with a blunted in vitro response to TLR-4 ligands. In addition, we found a major structural change in exons 3-4 of the immune-regulatory protein intercellular adhesion molecule 2 (ICAM-2); expression of this variant leads to reduced cell surface expression of ICAM-2. These data provide a resource for comparative genomic studies of HIV and/or SIV pathogenesis and may help to elucidate the mechanisms by which SIV-infected sooty mangabeys avoid AIDS.
Keywords: Acquired Immunodeficiency Syndrome; Amino Acid Sequence; Animals; Cell Adhesion Molecules; Cercocebus atys; Exons; Female; Frameshift Mutation; Genetic Predisposition to Disease; Genetic Variation; Genome; Genomics; HIV; Host Specificity; Humans; Macaca; Sequence Deletion; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Species Specificity; Toll-Like Receptor 4; Transcriptome; Whole Genome Sequencing

SPATA7 maintains a novel photoreceptor-specific zone in the distal connecting cilium. - Dharmat, Rachayata; Eblimit, Aiden; Robichaux, Michael A; Zhang, Zhixian; Nguyen, Thanh-Minh T; Jung, Sung Yun; He, Feng; Jain, Antrix; Li, Yumei; Qin, Jun; Overbeek, Paul; Roepman, Ronald; et al. (J Cell Biol, 2018)
Photoreceptor-specific ciliopathies often affect a structure that is considered functionally homologous to the ciliary transition zone (TZ) called the connecting cilium (CC). However, it is unclear how mutations in certain ciliary genes disrupt the photoreceptor CC without impacting the primary cilia systemically. By applying stochastic optical reconstruction microscopy technology in different genetic models, we show that the CC can be partitioned into two regions: the proximal CC (PCC), which is homologous to the TZ of primary cilia, and the distal CC (DCC), a photoreceptor-specific extension of the ciliary TZ. This specialized distal zone of the CC in photoreceptors is maintained by SPATA7, which interacts with other photoreceptor-specific ciliary proteins such as RPGR and RPGRIP1. The absence of results in the mislocalization of DCC proteins without affecting the PCC protein complexes. This collapse results in destabilization of the axonemal microtubules, which consequently results in photoreceptor degeneration. These data provide a novel mechanism to explain how genetic disruption of ubiquitously present ciliary proteins exerts tissue-specific ciliopathy phenotypes.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Antigens, Neoplasm; Carrier Proteins; Cell Cycle Proteins; Cytoskeletal Proteins; DNA-Binding Proteins; Eye Proteins; Mice; Mice, Inbred C57BL; Nuclear Proteins; Photoreceptor Connecting Cilium; Protein Transport

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Genetic Loci; Genetic Predisposition to Disease; Humans; Mental Disorders; Middle Aged; Multifactorial Inheritance; Neurodegenerative Diseases; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Reaction Time; Young Adult

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

Whole-exome sequencing reveals known and novel variants in a cohort of intracranial vertebral-basilar artery dissection (IVAD). - Wang, Kun; Zhao, Sen; Zhang, Qianqian; Yuan, Jian; Liu, Jiaqi; Ding, Xinghuan; Song, Xiaofei; Lin, Jiachen; Du, Renqian; Zhou, Yangzhong; Sugimoto, Michihiko; Chen, Weisheng; et al. (J Hum Genet, 2018)
Intracranial vertebral-basilar artery dissection (IVAD) is an arterial disorder leading to life-threatening consequences. Genetic factors are known to be causative to certain syndromic forms of IVAD. However, systematic study of the molecular basis of sporadic and isolated IVAD is lacking. To identify genetic variants contributing to the etiology of IVAD, we enrolled a cohort of 44 unrelated cases with a clinical diagnosis of isolated IVAD and performed whole-exome sequencing (WES) for all the participants; a trio exome sequencing approach was used when samples from both parents were available. Four previously reported disease-causing heterozygous variants (three in COL3A1 and one in FBN1) and seven novel heterozygous variants in IVAD-related genes were identified. In addition, six variants in novel IVAD genes including two de novo heterozygous nonsynonymous variants (each in VPS52 and CDK18), two stop-gain variants (each in MYH9 and LYL1), and two heterozygous biallelic variants in TNXB were considered to be possibly contributing to the phenotype, with unknown significance according to the existing knowledge. A significantly higher mutational rate of IVAD candidate genes was observed in patients versus our in-house controls (P = 0.002) (DISCO study, http://www.discostudy.org/ , n = 2248). Our study provided a mutational landscape for patients with isolated IVAD.
Keywords: Adult; Aneurysm, Dissecting; Basic Helix-Loop-Helix Transcription Factors; Cohort Studies; Collagen Type III; Exome; Female; Fibrillin-1; High-Throughput Nucleotide Sequencing; Humans; Intracranial Aneurysm; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Neoplasm Proteins

Whole-Exome Sequencing Reveals Uncaptured Variation and Distinct Ancestry in the Southern African Population of Botswana. - Retshabile, Gaone; Mlotshwa, Busisiwe C; Williams, Lesedi; Mwesigwa, Savannah; Mboowa, Gerald; Huang, Zhuoyi; Rustagi, Navin; Swaminathan, Shanker; Katagirya, Eric; Kyobe, Samuel; Wayengera, Misaki; Kisitu, Grace P; et al. (Am J Hum Genet, 2018)
Large-scale, population-based genomic studies have provided a context for modern medical genetics. Among such studies, however, African populations have remained relatively underrepresented. The breadth of genetic diversity across the African continent argues for an exploration of local genomic context to facilitate burgeoning disease mapping studies in Africa. We sought to characterize genetic variation and to assess population substructure within a cohort of HIV-positive children from Botswana-a Southern African country that is regionally underrepresented in genomic databases. Using whole-exome sequencing data from 164 Batswana and comparisons with 150 similarly sequenced HIV-positive Ugandan children, we found that 13%-25% of variation observed among Batswana was not captured by public databases. Uncaptured variants were significantly enriched (p = 2.2 × 10) for coding variants with minor allele frequencies between 1% and 5% and included predicted-damaging non-synonymous variants. Among variants found in public databases, corresponding allele frequencies varied widely, with Botswana having significantly higher allele frequencies among rare (<1%) pathogenic and damaging variants. Batswana clustered with other Southern African populations, but distinctly from 1000 Genomes African populations, and had limited evidence for admixture with extra-continental ancestries. We also observed a surprising lack of genetic substructure in Botswana, despite multiple tribal ethnicities and language groups, alongside a higher degree of relatedness than purported founder populations from the 1000 Genomes project. Our observations reveal a complex, but distinct, ancestral history and genomic architecture among Batswana and suggest that disease mapping within similar Southern African populations will require a deeper repository of genetic variation and allelic dependencies than presently exists.
Keywords: Black People; Botswana; Cohort Studies; Exome Sequencing; Gene Pool; Genetic Variation; Genetics, Population; Genome, Human; Geography; Humans; Phylogeny; Principal Component Analysis

The Alzheimer's Disease Sequencing Project: Study design and sample selection. - Beecham, Gary W; Bis, J C; Martin, E R; Choi, S-H; DeStefano, A L; van Duijn, C M; Fornage, M; Gabriel, S B; Koboldt, D C; Larson, D E; Naj, A C; Psaty, B M; et al. (Neurol Genet, 2017)

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Gibbs, Richard A; Gogarten, Stephanie M; et al. (Nat Genet, 2017)
The exploding volume of whole-genome sequence (WGS) and multi-omics data requires new approaches for analysis. As one solution, we have created a cloud-based Analysis Commons, which brings together genotype and phenotype data from multiple studies in a setting that is accessible by multiple investigators. This framework addresses many of the challenges of multi-center WGS analyses, including data sharing mechanisms, phenotype harmonization, integrated multi-omics analyses, annotation, and computational flexibility. In this setting, the computational pipeline facilitates a sequence-to-discovery analysis workflow illustrated here by an analysis of plasma fibrinogen levels in 3996 individuals from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) WGS program. The Analysis Commons represents a novel model for transforming WGS resources from a massive quantity of phenotypic and genomic data into knowledge of the determinants of health and disease risk in diverse human populations.
Keywords: big data; Fibrinogen; Genetics, Population; Genome; Humans; Information Dissemination; Mobile Applications; Molecular Epidemiology; Regression Analysis; Software; Workflow

ANGPTL3 Deficiency and Protection Against Coronary Artery Disease. - Stitziel, Nathan O; Khera, Amit V; Wang, Xiao; Bierhals, Andrew J; Vourakis, A Christina; Sperry, Alexandra E; Natarajan, Pradeep; Klarin, Derek; Emdin, Connor A; Zekavat, Seyedeh M; Nomura, Akihiro; Erdmann, Jeanette; et al. (J Am Coll Cardiol, 2017)
BACKGROUND: Familial combined hypolipidemia, a Mendelian condition characterized by substantial reductions in all 3 major lipid fractions, is caused by mutations that inactivate the gene angiopoietin-like 3 (ANGPTL3). Whether ANGPTL3 deficiency reduces risk of coronary artery disease (CAD) is unknown. OBJECTIVES: The study goal was to leverage 3 distinct lines of evidence-a family that included individuals with complete (compound heterozygote) ANGPTL3 deficiency, a population based-study of humans with partial (heterozygote) ANGPTL3 deficiency, and biomarker levels in patients with myocardial infarction (MI)-to test whether ANGPTL3 deficiency is associated with lower risk for CAD. METHODS: We assessed coronary atherosclerotic burden in 3 individuals with complete ANGPTL3 deficiency and 3 wild-type first-degree relatives using computed tomography angiography. In the population, ANGPTL3 loss-of-function (LOF) mutations were ascertained in up to 21,980 people with CAD and 158,200 control subjects. LOF mutations were defined as nonsense, frameshift, and splice-site variants, along with missense variants resulting in <25% of wild-type ANGPTL3 activity in a mouse model. In a biomarker study, circulating ANGPTL3 concentration was measured in 1,493 people who presented with MI and 3,232 control subjects. RESULTS: The 3 individuals with complete ANGPTL3 deficiency showed no evidence of coronary atherosclerotic plaque. ANGPTL3 gene sequencing demonstrated that approximately 1 in 309 people was a heterozygous carrier for an LOF mutation. Compared with those without mutation, heterozygous carriers of ANGPTL3 LOF mutations demonstrated a 17% reduction in circulating triglycerides and a 12% reduction in low-density lipoprotein cholesterol. Carrier status was associated with a 34% reduction in odds of CAD (odds ratio: 0.66; 95% confidence interval: 0.44 to 0.98; p = 0.04). Individuals in the lowest tertile of circulating ANGPTL3 concentrations, compared with the highest, had reduced odds of MI (adjusted odds ratio: 0.65; 95% confidence interval: 0.55 to 0.77; p < 0.001). CONCLUSIONS: ANGPTL3 deficiency is associated with protection from CAD.
Keywords: Adult; Angiopoietin-Like Protein 3; Angiopoietin-like Proteins; Angiopoietins; Animals; Atherosclerosis; Case-Control Studies; Coronary Artery Disease; Female; Humans; Lipids; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Mutation, Missense; Myocardial Infarction; Risk Factors

Association of Body Mass Index with DNA Methylation and Gene Expression in Blood Cells and Relations to Cardiometabolic Disease: A Mendelian Randomization Approach. - Mendelson, Michael M; Marioni, Riccardo E; Joehanes, Roby; Liu, Chunyu; Hedman, Åsa K; Aslibekyan, Stella; Demerath, Ellen W; Guan, Weihua; Zhi, Degui; Yao, Chen; Huan, Tianxiao; Willinger, Christine; et al. (PLoS Med, 2017)
BACKGROUND: The link between DNA methylation, obesity, and adiposity-related diseases in the general population remains uncertain. METHODS AND FINDINGS: We conducted an association study of body mass index (BMI) and differential methylation for over 400,000 CpGs assayed by microarray in whole-blood-derived DNA from 3,743 participants in the Framingham Heart Study and the Lothian Birth Cohorts, with independent replication in three external cohorts of 4,055 participants. We examined variations in whole blood gene expression and conducted Mendelian randomization analyses to investigate the functional and clinical relevance of the findings. We identified novel and previously reported BMI-related differential methylation at 83 CpGs that replicated across cohorts; BMI-related differential methylation was associated with concurrent changes in the expression of genes in lipid metabolism pathways. Genetic instrumental variable analysis of alterations in methylation at one of the 83 replicated CpGs, cg11024682 (intronic to sterol regulatory element binding transcription factor 1 [SREBF1]), demonstrated links to BMI, adiposity-related traits, and coronary artery disease. Independent genetic instruments for expression of SREBF1 supported the findings linking methylation to adiposity and cardiometabolic disease. Methylation at a substantial proportion (16 of 83) of the identified loci was found to be secondary to differences in BMI. However, the cross-sectional nature of the data limits definitive causal determination. CONCLUSIONS: We present robust associations of BMI with differential DNA methylation at numerous loci in blood cells. BMI-related DNA methylation and gene expression provide mechanistic insights into the relationship between DNA methylation, obesity, and adiposity-related diseases.
Keywords: Aged; Body Mass Index; Coronary Artery Disease; DNA Methylation; Epigenesis, Genetic; Female; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Lipid Metabolism; Male; Mendelian Randomization Analysis; Obesity; Oligonucleotide Array Sequence Analysis

The association of lipoprotein(a) with incident heart failure hospitalization: Atherosclerosis Risk in Communities study. - Agarwala, Anandita; Pokharel, Yashashwi; Saeed, Anum; Sun, Wensheng; Virani, Salim S; Nambi, Vijay; Ndumele, Chiadi; Shahar, Eyal; Heiss, Gerardo; Boerwinkle, Eric; Konety, Suma; Hoogeveen, Ron C; et al. (Atherosclerosis, 2017)
BACKGROUND AND AIMS: Lipoprotein(a) [Lp(a)] is a proatherogenic lipoprotein associated with coronary heart disease, ischemic stroke, and more recently aortic stenosis and heart failure (HF). We examined the association of Lp(a) levels with incident HF hospitalization in the Atherosclerosis Risk in Communities (ARIC) study. We also assessed the relationship between Lp(a) levels and arterial stiffness as a potential mechanism for development of HF. METHODS: Lp(a) was measured in 14,154 ARIC participants without prevalent HF at ARIC visit 1 (1987-1989). The association of Lp(a) quintiles with incident HF hospitalization was assessed using Cox proportional-hazards models. Arterial stiffness parameters were stratified based on Lp(a) quintiles, and p-trend was calculated across ordered groups. RESULTS: At a median follow-up of 23.4 years, there were 2605 incident HF hospitalizations. Lp(a) levels were directly associated with incident HF hospitalization in models adjusted for age, race, gender, systolic blood pressure, history of hypertension, diabetes, smoking status, body mass index, heart rate, and high-density lipoprotein cholesterol (quintile 5 vs. quintile 1: hazard ratio [HR] 1.24, 95% confidence interval [CI] 1.09-1.41; p-trend across increasing quintiles <0.01), but not after excluding prevalent and incident myocardial infarction cases (HR 1.07, 95% CI 0.91-1.27; p-trend = 0.70). When adjusted for age, gender, and race, Lp(a) quintiles were not significantly associated with arterial stiffness parameters. CONCLUSIONS: Increased Lp(a) levels were associated with increased risk of incident HF hospitalization. After excluding prevalent and incident myocardial infarction, the association was no longer significant. Lp(a) levels were not associated with arterial stiffness parameters.
Keywords: Biomarkers; Chi-Square Distribution; Comorbidity; Female; Heart Failure; Hospitalization; Humans; Incidence; Linear Models; Lipoprotein(a); Male; Middle Aged; Multivariate Analysis; Myocardial Infarction; Prevalence; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors; United States; Up-Regulation; Vascular Stiffness

Copy number increases of transposable elements and protein-coding genes in an invasive fish of hybrid origin. - Dennenmoser, Stefan; Sedlazeck, Fritz J; Iwaszkiewicz, Elzbieta; Li, Xiang-Yi; Altmüller, Janine; Nolte, Arne W (Mol Ecol, 2017)
Evolutionary dynamics of structural genetic variation in lineages of hybrid origin is not well explored, although structural mutations may increase in controlled hybrid crosses. We therefore tested whether structural variants accumulate in a fish of recent hybrid origin, invasive Cottus, relative to both parental species Cottus rhenanus and Cottus perifretum. Copy-number variation in exons of 10,979 genes was assessed using comparative genome hybridization arrays. Twelve genes showed significantly higher copy numbers in invasive Cottus compared to both parents. This coincided with increased expression for three genes related to vision, detoxification and muscle development, suggesting possible gene dosage effects. Copy number increases of putative transposons were assessed by comparative mapping of genomic DNA reads against a de novo assembly of 1,005 repetitive elements. In contrast to exons, copy number increases of repetitive elements were common (20.7%) in invasive Cottus, whereas decrease was very rare (0.01%). Among the increased repetitive elements, 53.8% occurred at higher numbers in C. perifretum compared to C. rhenanus, while only 1.4% were more abundant in C. rhenanus. This implies a biased mutational process that amplifies genetic material from one ancestor. To assess the frequency of de novo mutations through hybridization, we screened 64 laboratory-bred F offspring between the parental species for copy-number changes at five candidate loci. We found no evidence for new structural variants, indicating that they are too rare to be detected given our sampling scheme. Instead, they must have accumulated over more generations than we observed in a controlled cross.
Keywords: Animals; Biological Evolution; DNA Copy Number Variations; DNA Transposable Elements; Hybridization, Genetic; Introduced Species; Perciformes

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish

De Novo Missense Mutations in DHX30 Impair Global Translation and Cause a Neurodevelopmental Disorder. - Lessel, Davor; Schob, Claudia; Küry, Sébastien; Reijnders, Margot R F; Harel, Tamar; Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Denecke, Jonas; Edvardson, Shimon; Colin, Estelle; Stegmann, Alexander P A; Gerkes, Erica H; et al. (Am J Hum Genet, 2017)
DHX30 is a member of the family of DExH-box helicases, which use ATP hydrolysis to unwind RNA secondary structures. Here we identified six different de novo missense mutations in DHX30 in twelve unrelated individuals affected by global developmental delay (GDD), intellectual disability (ID), severe speech impairment and gait abnormalities. While four mutations are recurrent, two are unique with one affecting the codon of one recurrent mutation. All amino acid changes are located within highly conserved helicase motifs and were found to either impair ATPase activity or RNA recognition in different in vitro assays. Moreover, protein variants exhibit an increased propensity to trigger stress granule (SG) formation resulting in global translation inhibition. Thus, our findings highlight the prominent role of translation control in development and function of the central nervous system and also provide molecular insight into how DHX30 dysfunction might cause a neurodevelopmental disorder.
Keywords: Adenosine Triphosphatases; Adolescent; Amino Acids; Cell Line; Cell Line, Tumor; Central Nervous System; Child; Child, Preschool; Developmental Disabilities; Female; HEK293 Cells; Humans; Intellectual Disability; Male; Mutation, Missense; RNA; RNA Helicases

Dominant Transmission Observed in Adolescents and Families With Orthostatic Intolerance. - Posey, Jennifer E; Martinez, Rebecca; Lankford, Jeremy E; Lupski, James R; Numan, Mohammed T; Butler, Ian J (Pediatr Neurol, 2017)
BACKGROUND: Orthostatic intolerance is typically thought to be sporadic and attributed to cerebral autonomic dysfunction. We sought to identify families with inherited autonomic dysfunction manifest as symptomatic orthostatic intolerance to characterize mode of inheritance and clinical features. METHODS: Sixteen families with two or more first- or second-degree relatives with autonomic dysfunction and orthostatic intolerance were enrolled. A clinical diagnosis of autonomic dysfunction defined by symptomatic orthostatic intolerance diagnosed by head-up tilt table testing was confirmed for each proband. Clinical features and evaluation were obtained from each proband using a standardized intake questionnaire, and family history information was obtained from probands and available relatives. RESULTS: Comprehensive pedigree analysis of 16 families (39 individuals with orthostatic intolerance and 40 individuals suspected of having orthostatic intolerance) demonstrated dominant transmission of autonomic dysfunction with incomplete penetrance. Affected individuals were predominantly female (71.8%, 28/39; F:M, 2.5:1). Male-to-male transmission, although less common, was observed and demonstrated to transmit through unaffected males with an affected parent. Similar to sporadic orthostatic intolerance, probands report a range of symptoms across multiple organ systems, with headaches and neuromuscular features being most common. CONCLUSIONS: Familial occurrence and vertical transmission of autonomic dysfunction in 16 families suggest a novel genetic syndrome with dominant transmission, incomplete penetrance, and skewing of the sex ratio. Elucidation of potential genetic contributions to orthostatic intolerance may inform therapeutic management and identification of individuals at risk. Adolescent evaluation should include identification and treatment of potential at-risk relatives.
Keywords: Adolescent; Cohort Studies; Family; Female; Genetic Testing; Humans; Male; Orthostatic Intolerance; Pedigree; Posture; Surveys and Questionnaires; Tilt-Table Test

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Rett Syndrome

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

An Expanded Genome-Wide Association Study of Type 2 Diabetes in Europeans. - Scott, Robert A; Scott, Laura J; Mägi, Reedik; Marullo, Letizia; Gaulton, Kyle J; Kaakinen, Marika; Pervjakova, Natalia; Pers, Tune H; Johnson, Andrew D; Eicher, John D; Jackson, Anne U; Ferreira, Teresa; et al. (Diabetes, 2017)
To characterize type 2 diabetes (T2D)-associated variation across the allele frequency spectrum, we conducted a meta-analysis of genome-wide association data from 26,676 T2D case and 132,532 control subjects of European ancestry after imputation using the 1000 Genomes multiethnic reference panel. Promising association signals were followed up in additional data sets (of 14,545 or 7,397 T2D case and 38,994 or 71,604 control subjects). We identified 13 novel T2D-associated loci ( < 5 × 10), including variants near the , , and genes. Our analysis brought the total number of independent T2D associations to 128 distinct signals at 113 loci. Despite substantially increased sample size and more complete coverage of low-frequency variation, all novel associations were driven by common single nucleotide variants. Credible sets of potentially causal variants were generally larger than those based on imputation with earlier reference panels, consistent with resolution of causal signals to common risk haplotypes. Stratification of T2D-associated loci based on T2D-related quantitative trait associations revealed tissue-specific enrichment of regulatory annotations in pancreatic islet enhancers for loci influencing insulin secretion and in adipocytes, monocytes, and hepatocytes for insulin action-associated loci. These findings highlight the predominant role played by common variants of modest effect and the diversity of biological mechanisms influencing T2D pathophysiology.
Keywords: Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; White People

Fifteen new risk loci for coronary artery disease highlight arterial-wall-specific mechanisms. - Howson, Joanna M M; Zhao, Wei; Barnes, Daniel R; Ho, Weang-Kee; Young, Robin; Paul, Dirk S; Waite, Lindsay L; Freitag, Daniel F; Fauman, Eric B; Salfati, Elias L; Sun, Benjamin B; Eicher, John D; et al. (Nat Genet, 2017)
Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide. Although 58 genomic regions have been associated with CAD thus far, most of the heritability is unexplained, indicating that additional susceptibility loci await identification. An efficient discovery strategy may be larger-scale evaluation of promising associations suggested by genome-wide association studies (GWAS). Hence, we genotyped 56,309 participants using a targeted gene array derived from earlier GWAS results and performed meta-analysis of results with 194,427 participants previously genotyped, totaling 88,192 CAD cases and 162,544 controls. We identified 25 new SNP-CAD associations (P < 5 × 10, in fixed-effects meta-analysis) from 15 genomic regions, including SNPs in or near genes involved in cellular adhesion, leukocyte migration and atherosclerosis (PECAM1, rs1867624), coagulation and inflammation (PROCR, rs867186 (p.Ser219Gly)) and vascular smooth muscle cell differentiation (LMOD1, rs2820315). Correlation of these regions with cell-type-specific gene expression and plasma protein levels sheds light on potential disease mechanisms.
Keywords: Arteries; Atherosclerosis; Cell Adhesion; Chemotaxis, Leukocyte; Coronary Artery Disease; Energy Metabolism; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Histone Code; Humans; Male; Muscle, Smooth, Vascular; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Further delineation of a rare recessive encephalomyopathy linked to mutations in GFER thanks to data sharing of whole exome sequencing data. - Nambot, S; Gavrilov, D; Thevenon, J; Bruel, A L; Bainbridge, M; Rio, M; Goizet, C; Rötig, A; Jaeken, J; Niu, N; Xia, F; Vital, A; et al. (Clin Genet, 2017)
BACKGROUND: Alterations in GFER gene have been associated with progressive mitochondrial myopathy, congenital cataracts, hearing loss, developmental delay, lactic acidosis and respiratory chain deficiency in 3 siblings born to consanguineous Moroccan parents by homozygosity mapping and candidate gene approach (OMIM#613076). Next generation sequencing recently confirmed this association by the finding of compound heterozygous variants in 19-year-old girl with a strikingly similar phenotype, but this ultra-rare entity remains however unknown from most of the scientific community. MATERIALS AND METHODS: Whole exome sequencing was performed as part of a "diagnostic odyssey" for suspected mitochondrial condition in 2 patients, presenting congenital cataracts, progressive encephalomyopathy and hypotrophy and detected unreported compound heterozygous variants in GFER. RESULTS: Thanks to an international data sharing, we found 2 additional patients carrying compound heterozygous variants in GFER. Reverse phenotyping confirmed the phenotypical similarities between the 4 patients. Together with the first literature reports, the review of these 8 cases from 4 unrelated families enables us to better describe this apparently homogeneous disorder, with the clinical and biological stigmata of mitochondrial disease. CONCLUSION: This report highlights the clinical utility of whole exome sequencing and reverse phenotyping for the diagnosis of ultra-rare diseases and underlines the importance of a broad data sharing for accurate clinical delineation of previously unrecognized entities.
Keywords: Adolescent; Adult; Child; Cytochrome Reductases; Exome Sequencing; Female; Genetic Predisposition to Disease; Heterozygote; Humans; Male; Mitochondrial Encephalomyopathies; Mutation; Oxidoreductases Acting on Sulfur Group Donors; Pedigree; Young Adult

The Genetic Causes of Nonsyndromic Congenital Retinal Detachment: A Genetic and Phenotypic Study of Pakistani Families. - Keser, Vafa; Khan, Ayesha; Siddiqui, Sorath; Lopez, Irma; Ren, Huanan; Qamar, Raheel; Nadaf, Javad; Majewski, Jacek; Chen, Rui; Koenekoop, Robert K (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: To evaluate consanguineous pedigrees from Pakistan with a clinical diagnosis of nonsyndromic congenital retinal nonattachment (NCRNA) and identify genes responsible for the disease as currently only one NCRNA gene is known (atonal basic helix-loop-helix transcription factor 7: ATOH7). METHODS: We implemented a three-step genotyping platform: single nucleotide polymorphism genotyping to identify loss of heterozygosity regions in patients, Retinal Information Network panel screening for mutations in currently known retinal genes. Negative patients were then subjected to whole exome sequencing. RESULTS: We evaluated 21 consanguineous NCRNA pedigrees and identified the causal mutations in known retinal genes in 13 out of our 21 families. We found mutations in ATOH7 in three families. Surprisingly, we then found mutations in familial exudative vitreoretinopathy (FEVR) genes; low-density lipoprotein receptor-related protein 5 mutations (six families), tetraspanin 12 mutations (two families), and NDP mutations (two families). Thus, 62% of the patients were successfully genotyped in our study with seven novel and six previously reported mutations in known retinal genes. CONCLUSIONS: Although the clinical diagnosis of all children was NCRNA with severe congenital fibrotic retinal detachments, the molecular diagnosis determined that the disease process was in fact a very severe form of FEVR in 10 families. Because severe congenital retinal detachment has not been previously associated with all the FEVR genes, we have thus expanded the phenotypic spectrum of FEVR, a highly variable retinal detachment phenotype that has clinical overlap with NCRNA. We identified seven novel mutations. We also established for the first time genetic overlap between the Iranian and Pakistani populations. We identified eight NCRNA families that do not harbor mutations in any known retinal genes, suggesting novel causal genes in these families.
Keywords: Basic Helix-Loop-Helix Transcription Factors; Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Helix-Loop-Helix Motifs; Humans; Incidence; Infant; Male; Mutation; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Retina; Retinal Diseases

GenomeScope: fast reference-free genome profiling from short reads. - Vurture, Gregory W; Sedlazeck, Fritz J; Nattestad, Maria; Underwood, Charles J; Fang, Han; Gurtowski, James; Schatz, Michael C (Bioinformatics, 2017)
SUMMARY: GenomeScope is an open-source web tool to rapidly estimate the overall characteristics of a genome, including genome size, heterozygosity rate and repeat content from unprocessed short reads. These features are essential for studying genome evolution, and help to choose parameters for downstream analysis. We demonstrate its accuracy on 324 simulated and 16 real datasets with a wide range in genome sizes, heterozygosity levels and error rates. AVAILABILITY AND IMPLEMENTATION: http://genomescope.org , https://github.com/schatzlab/genomescope.git . CONTACT: mschatz@jhu.edu. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Animals; Computational Biology; Evolution, Molecular; Genome; Genome Size; Heterozygote; Internet; Sequence Analysis, DNA; Software

Genome-wide association study of 1,5-anhydroglucitol identifies novel genetic loci linked to glucose metabolism. - Li, Man; Maruthur, Nisa M; Loomis, Stephanie J; Pietzner, Maik; North, Kari E; Mei, Hao; Morrison, Alanna C; Friedrich, Nele; Pankow, James S; Nauck, Matthias; Boerwinkle, Eric; Teumer, Alexander; et al. (Sci Rep, 2017)
1,5-anhydroglucitol (1,5-AG) is a biomarker of hyperglycemic excursions associated with diabetic complications. Because of its structural similarity to glucose, genetic studies of 1,5-AG can deliver complementary insights into glucose metabolism. We conducted genome-wide association studies of serum 1,5-AG concentrations in 7,550 European ancestry (EA) and 2,030 African American participants (AA) free of diagnosed diabetes from the ARIC Study. Seven loci in/near EFNA1/SLC50A1, MCM6/LCT, SI, MGAM, MGAM2, SLC5A10, and SLC5A1 showed genome-wide significant associations (P < 5 × 10) among EA participants, five of which were novel. Six of the seven loci were successfully replicated in 8,790 independent EA individuals, and MCM6/LCT and SLC5A10 were also associated among AA. Most of 1,5-AG-associated index SNPs were not associated with the clinical glycemic markers fasting glucose or the  HbA1c, and vice versa. Only the index variant in SLC5A1 showed a significant association with fasting glucose in the expected opposing direction. Products of genes in all 1,5-AG-associated loci have known roles in carbohydrate digestion and enteral or renal glucose transport, suggesting that genetic variants associated with 1,5-AG influence its concentration via effects on glucose metabolism and handling.
Keywords: Aged; Black or African American; Deoxyglucose; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose; Glycated Hemoglobin; Humans; Hyperglycemia; Insulin; Male; Middle Aged; Minichromosome Maintenance Complex Component 6; Sodium-Glucose Transporter 1; White People

Genomic landscape and evolution of metastatic chromophobe renal cell carcinoma. - Casuscelli, Jozefina; Weinhold, Nils; Gundem, Gunes; Wang, Lu; Zabor, Emily C; Drill, Esther; Wang, Patricia I; Nanjangud, Gouri J; Redzematovic, Almedina; Nargund, Amrita M; Manley, Brandon J; Arcila, Maria E; et al. (JCI Insight, 2017)
Chromophobe renal cell carcinoma (chRCC) typically shows ~7 chromosome losses (1, 2, 6, 10, 13, 17, and 21) and ~31 exonic somatic mutations, yet carries ~5%-10% metastatic incidence. Since extensive chromosomal losses can generate proteotoxic stress and compromise cellular proliferation, it is intriguing how chRCC, a tumor with extensive chromosome losses and a low number of somatic mutations, can develop lethal metastases. Genomic features distinguishing metastatic from nonmetastatic chRCC are unknown. An integrated approach, including whole-genome sequencing (WGS), targeted ultradeep cancer gene sequencing, and chromosome analyses (FACETS, OncoScan, and FISH), was performed on 79 chRCC patients including 38 metastatic (M-chRCC) cases. We demonstrate that TP53 mutations (58%), PTEN mutations (24%), and imbalanced chromosome duplication (ICD, duplication of ≥ 3 chromosomes) (25%) were enriched in M-chRCC. Reconstruction of the subclonal composition of paired primary-metastatic chRCC tumors supports the role of TP53, PTEN, and ICD in metastatic evolution. Finally, the presence of these 3 genomic features in primary tumors of both The Cancer Genome Atlas kidney chromophobe (KICH) (n = 64) and M-chRCC (n = 35) cohorts was associated with worse survival. In summary, our study provides genomic insights into the metastatic progression of chRCC and identifies TP53 mutations, PTEN mutations, and ICD as high-risk features.

The gut mycobiome of the Human Microbiome Project healthy cohort. - Nash, Andrea K; Auchtung, Thomas A; Wong, Matthew C; Smith, Daniel P; Gesell, Jonathan R; Ross, Matthew C; Stewart, Christopher J; Metcalf, Ginger A; Muzny, Donna M; Gibbs, Richard A; Ajami, Nadim J; Petrosino, Joseph F (Microbiome, 2017)
BACKGROUND: Most studies describing the human gut microbiome in healthy and diseased states have emphasized the bacterial component, but the fungal microbiome (i.e., the mycobiome) is beginning to gain recognition as a fundamental part of our microbiome. To date, human gut mycobiome studies have primarily been disease centric or in small cohorts of healthy individuals. To contribute to existing knowledge of the human mycobiome, we investigated the gut mycobiome of the Human Microbiome Project (HMP) cohort by sequencing the Internal Transcribed Spacer 2 (ITS2) region as well as the 18S rRNA gene. RESULTS: Three hundred seventeen HMP stool samples were analyzed by ITS2 sequencing. Fecal fungal diversity was significantly lower in comparison to bacterial diversity. Yeast dominated the samples, comprising eight of the top 15 most abundant genera. Specifically, fungal communities were characterized by a high prevalence of Saccharomyces, Malassezia, and Candida, with S. cerevisiae, M. restricta, and C. albicans operational taxonomic units (OTUs) present in 96.8, 88.3, and 80.8% of samples, respectively. There was a high degree of inter- and intra-volunteer variability in fungal communities. However, S. cerevisiae, M. restricta, and C. albicans OTUs were found in 92.2, 78.3, and 63.6% of volunteers, respectively, in all samples donated over an approximately 1-year period. Metagenomic and 18S rRNA gene sequencing data agreed with ITS2 results; however, ITS2 sequencing provided greater resolution of the relatively low abundance mycobiome constituents. CONCLUSIONS: Compared to bacterial communities, the human gut mycobiome is low in diversity and dominated by yeast including Saccharomyces, Malassezia, and Candida. Both inter- and intra-volunteer variability in the HMP cohort were high, revealing that unlike bacterial communities, an individual's mycobiome is no more similar to itself over time than to another person's. Nonetheless, several fungal species persisted across a majority of samples, evidence that a core gut mycobiome may exist. ITS2 sequencing data provided greater resolution of the mycobiome membership compared to metagenomic and 18S rRNA gene sequencing data, suggesting that it is a more sensitive method for studying the mycobiome of stool samples.
Keywords: Candida; Cohort Studies; DNA, Ribosomal Spacer; Feces; Fungi; Gastrointestinal Microbiome; Genetic Variation; Healthy Volunteers; High-Throughput Nucleotide Sequencing; Humans; Malassezia; Metagenomics; Microbiota; Mycobiome; RNA, Ribosomal, 18S; Saccharomyces; Sequence Analysis, DNA

Identification of novel candidate disease genes from de novo exonic copy number variants. - Gambin, Tomasz; Bo Yuan; Bi, Weimin; Liu, Pengfei; Rosenfeld, Jill A; Coban-Akdemir, Zeynep; Pursley, Amber N; Nagamani, Sandesh C S; Marom, Ronit; Golla, Sailaja; Dengle, Lauren; Petrie, Heather G; et al. (Genome Med, 2017)
BACKGROUND: Exon-targeted microarrays can detect small (<1000 bp) intragenic copy number variants (CNVs), including those that affect only a single exon. This genome-wide high-sensitivity approach increases the molecular diagnosis for conditions with known disease-associated genes, enables better genotype-phenotype correlations, and facilitates variant allele detection allowing novel disease gene discovery. METHODS: We retrospectively analyzed data from 63,127 patients referred for clinical chromosomal microarray analysis (CMA) at Baylor Genetics laboratories, including 46,755 individuals tested using exon-targeted arrays, from 2007 to 2017. Small CNVs harboring a single gene or two to five non-disease-associated genes were identified; the genes involved were evaluated for a potential disease association. RESULTS: In this clinical population, among rare CNVs involving any single gene reported in 7200 patients (11%), we identified 145 de novo autosomal CNVs (117 losses and 28 intragenic gains), 257 X-linked deletion CNVs in males, and 1049 inherited autosomal CNVs (878 losses and 171 intragenic gains); 111 known disease genes were potentially disrupted by de novo autosomal or X-linked (in males) single-gene CNVs. Ninety-one genes, either recently proposed as candidate disease genes or not yet associated with diseases, were disrupted by 147 single-gene CNVs, including 37 de novo deletions and ten de novo intragenic duplications on autosomes and 100 X-linked CNVs in males. Clinical features in individuals with de novo or X-linked CNVs encompassing at most five genes (224 bp to 1.6 Mb in size) were compared to those in individuals with larger-sized deletions (up to 5 Mb in size) in the internal CMA database or loss-of-function single nucleotide variants (SNVs) detected by clinical or research whole-exome sequencing (WES). This enabled the identification of recently published genes (BPTF, NONO, PSMD12, TANGO2, and TRIP12), novel candidate disease genes (ARGLU1 and STK3), and further confirmation of disease association for two recently proposed disease genes (MEIS2 and PTCHD1). Notably, exon-targeted CMA detected several pathogenic single-exon CNVs missed by clinical WES analyses. CONCLUSIONS: Together, these data document the efficacy of exon-targeted CMA for detection of genic and exonic CNVs, complementing and extending WES in clinical diagnostics, and the potential for discovery of novel disease genes by genome-wide assay.
Keywords: Cohort Studies; DNA Copy Number Variations; Exons; Genetic Diseases, Inborn; Genome, Human; Homeodomain Proteins; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Neurodevelopmental Disorders; Protein Serine-Threonine Kinases; Retrospective Studies; Serine-Threonine Kinase 3; Transcription Factors; Whole Genome Sequencing

Improved annotation of the insect vector of citrus greening disease: biocuration by a diverse genomics community. - Saha, Surya; Hosmani, Prashant S; Villalobos-Ayala, Krystal; Miller, Sherry; Shippy, Teresa; Flores, Mirella; Rosendale, Andrew; Cordola, Chris; Bell, Tracey; Mann, Hannah; DeAvila, Gabe; DeAvila, Daniel; et al. (Database (Oxford), 2017)
https://citrusgreening.org/.
Keywords: Animals; Citrus; Databases, Genetic; Genome, Insect; Hemiptera; Insect Vectors; Pest Control; Plant Diseases; Rhizobiaceae

Integrative Genomic Analysis of Cholangiocarcinoma Identifies Distinct IDH-Mutant Molecular Profiles. - Farshidfar, Farshad; Zheng, Siyuan; Gingras, Marie-Claude; Newton, Yulia; Shih, Juliann; Robertson, A Gordon; Hinoue, Toshinori; Hoadley, Katherine A; Gibb, Ewan A; Roszik, Jason; Covington, Kyle R; Wu, Chia-Chin; et al. (Cell Rep, 2017)
Cholangiocarcinoma (CCA) is an aggressive malignancy of the bile ducts, with poor prognosis and limited treatment options. Here, we describe the integrated analysis of somatic mutations, RNA expression, copy number, and DNA methylation by The Cancer Genome Atlas of a set of predominantly intrahepatic CCA cases and propose a molecular classification scheme. We identified an IDH mutant-enriched subtype with distinct molecular features including low expression of chromatin modifiers, elevated expression of mitochondrial genes, and increased mitochondrial DNA copy number. Leveraging the multi-platform data, we observed that ARID1A exhibited DNA hypermethylation and decreased expression in the IDH mutant subtype. More broadly, we found that IDH mutations are associated with an expanded histological spectrum of liver tumors with molecular features that stratify with CCA. Our studies reveal insights into the molecular pathogenesis and heterogeneity of cholangiocarcinoma and provide classification information of potential therapeutic significance.
Keywords: Adult; Aged; Aged, 80 and over; Bile Duct Neoplasms; Cholangiocarcinoma; Chromatin; DNA Methylation; DNA-Binding Proteins; Female; Gene Expression Regulation, Neoplastic; Genomics; Humans; Isocitrate Dehydrogenase; Liver; Liver Neoplasms; Male; Middle Aged; Mitochondria; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Promoter Regions, Genetic; RNA, Long Noncoding; RNA, Messenger; Transcription Factors

Kaufman oculo-cerebro-facial syndrome in a child with small and absent terminal phalanges and absent nails. - Kariminejad, Ariana; Ajeawung, Norbert Fonya; Bozorgmehr, Bita; Dionne-Laporte, Alexandre; Molidperee, Sirinart; Najafi, Kimia; Gibbs, Richard A; Lee, Brendan H; Hennekam, Raoul C; Campeau, Philippe M (J Hum Genet, 2017)
Kaufman oculo-cerebro-facial syndrome (KOS) is caused by recessive UBE3B mutations and presents with microcephaly, ocular abnormalities, distinctive facial morphology, low cholesterol levels and intellectual disability. We describe a child with microcephaly, brachycephaly, hearing loss, ptosis, blepharophimosis, hypertelorism, cleft palate, multiple renal cysts, absent nails, small or absent terminal phalanges, absent speech and intellectual disability. Syndromes that were initially considered include DOORS syndrome, Coffin-Siris syndrome and Dubowitz syndrome. Clinical investigations coupled with karyotype analysis, array-comparative genomic hybridization, exome and Sanger sequencing were performed to characterize the condition in this child. Sanger sequencing was negative for the DOORS syndrome gene TBC1D24 but exome sequencing identified a homozygous deletion in UBE3B (NM_183415:c.3139_3141del, p.1047_1047del) located within the terminal portion of the HECT domain. This finding coupled with the presence of characteristic features such as brachycephaly, ptosis, blepharophimosis, hypertelorism, short palpebral fissures, cleft palate and developmental delay allowed us to make a diagnosis of KOS. In conclusion, our findings highlight the importance of considering KOS as a differential diagnosis for patients under evaluation for DOORS syndrome and expand the phenotype of KOS to include small or absent terminal phalanges, nails, and the presence of hallux varus and multicystic dysplastic kidneys.
Keywords: Abnormalities, Multiple; Adult; Carrier Proteins; Child; Child, Preschool; Diagnosis, Differential; Eczema; Eye Abnormalities; Face; Facies; Female; Growth Disorders; GTPase-Activating Proteins; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotype; Limb Deformities, Congenital; Male; Membrane Proteins; Microcephaly; Micrognathism; Mutation; Neck; Nerve Tissue Proteins; Pathology, Molecular; Sequence Analysis, DNA; Ubiquitin-Protein Ligases

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.
Keywords: Atrial Fibrillation; Black or African American; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Quantitative Trait Loci; White People

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

MicroRNAs in the miR-17 and miR-15 families are downregulated in chronic kidney disease with hypertension. - Nandakumar, Priyanka; Tin, Adrienne; Grove, Megan L; Ma, Jianzhong; Boerwinkle, Eric; Coresh, Josef; Chakravarti, Aravinda (PLoS One, 2017)
BACKGROUND: In older adults (aged 70-74 years), African-Americans have 4-fold higher risk of developing hypertension-attributed end-stage renal disease (ESRD) than European-Americans. A hypothesized mechanism linking hypertension and progressive chronic kidney disease (CKD) is the innate immune response and inflammation. Persons with CKD are also more susceptible to infection. Gene expression in peripheral blood can provide a view of the innate immune activation profile. We aimed to identify differentially expressed genes, microRNAs, and pathways in peripheral blood between cases with CKD and high blood pressure under hypertension treatment versus controls without CKD and with controlled blood pressure in African Americans. METHODS: Case and control pairs (N = 15x2) were selected from those without diabetes and were matched for age, sex, body mass index, APOL1 risk allele count, and hypertension medication use. High blood pressure under hypertension treatment was defined as hypertension medication use and systolic blood pressure (SBP) ≥ 145 mmHg. CKD was defined as estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2. Cases were selected from those with CKD and high blood pressure under hypertension treatment, and controls were selected from those without CKD (eGFR: 75-120 mL/min/1.73m2 and urine albumin-to-creatinine ratio < 30mg/g) and with blood pressure controlled by hypertension medication use (SBP < 135 mmHg and D(diastolic)BP < 90 mm Hg). We perform RNA sequencing of mRNA and microRNA and conducted differential expression and co-expression network analysis. RESULTS: Of 347 miRNAs included in the analysis, 14 were significantly associated with case status (Benjamini-Hochberg adjusted p-value [BH p] < 0.05). Of these, ten were downregulated in cases: three of each belong to the miR-17 and miR-15 families. In co-expression network analysis of miRNA, one module, which included 13 of the 14 significant miRNAs, had significant association with case status. Of the 14,488 genes and 41,739 transcripts included in the analysis, none had significant association with case status. Gene co-expression network analyses did not yield any significant associations for mRNA. CONCLUSION: We have identified 14 differentially expressed miRNAs in the peripheral blood of CKD cases with high blood pressure under hypertension treatment as compared to appropriate controls. Most of the significant miRNAs were downregulated and have critical roles in immune cell functions. Future studies are needed to replicate our findings and determine whether the downregulation of these miRNAs in immune cells may influence CKD progression or complications.
Keywords: Down-Regulation; Female; Gene Expression Profiling; Gene Ontology; Gene Regulatory Networks; Humans; Hypertension; Male; MicroRNAs; Middle Aged; Renal Insufficiency, Chronic; RNA, Messenger; Sequence Analysis, RNA

Mutations in the Spliceosome Component CWC27 Cause Retinal Degeneration with or without Additional Developmental Anomalies. - Xu, Mingchu; Xie, Yajing Angela; Abouzeid, Hana; Gordon, Christopher T; Fiorentino, Alessia; Sun, Zixi; Lehman, Anna; Osman, Ihab S; Dharmat, Rachayata; Riveiro-Álvarez, Rosa; Bapst-Wicht, Linda; Babino, Darwin; et al. (Am J Hum Genet, 2017)
Pre-mRNA splicing factors play a fundamental role in regulating transcript diversity both temporally and spatially. Genetic defects in several spliceosome components have been linked to a set of non-overlapping spliceosomopathy phenotypes in humans, among which skeletal developmental defects and non-syndromic retinitis pigmentosa (RP) are frequent findings. Here we report that defects in spliceosome-associated protein CWC27 are associated with a spectrum of disease phenotypes ranging from isolated RP to severe syndromic forms. By whole-exome sequencing, recessive protein-truncating mutations in CWC27 were found in seven unrelated families that show a range of clinical phenotypes, including retinal degeneration, brachydactyly, craniofacial abnormalities, short stature, and neurological defects. Remarkably, variable expressivity of the human phenotype can be recapitulated in Cwc27 mutant mouse models, with significant embryonic lethality and severe phenotypes in the complete knockout mice while mice with a partial loss-of-function allele mimic the isolated retinal degeneration phenotype. Our study describes a retinal dystrophy-related phenotype spectrum as well as its genetic etiology and highlights the complexity of the spliceosomal gene network.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Cyclophilins; Female; Humans; Male; Mice; Mutation; Pedigree; Peptidylprolyl Isomerase; Retinal Degeneration; Young Adult

A Pan-Cancer Proteogenomic Atlas of PI3K/AKT/mTOR Pathway Alterations. - Zhang, Yiqun; Kwok-Shing Ng, Patrick; Kucherlapati, Melanie; Chen, Fengju; Liu, Yuexin; Tsang, Yiu Huen; De Velasco, Guillermo; Jeong, Kang Jin; Akbani, Rehan; Hadjipanayis, Angela; Pantazi, Angeliki; Bristow, Christopher A; et al. (Cancer Cell, 2017)
Molecular alterations involving the PI3K/AKT/mTOR pathway (including mutation, copy number, protein, or RNA) were examined across 11,219 human cancers representing 32 major types. Within specific mutated genes, frequency, mutation hotspot residues, in silico predictions, and functional assays were all informative in distinguishing the subset of genetic variants more likely to have functional relevance. Multiple oncogenic pathways including PI3K/AKT/mTOR converged on similar sets of downstream transcriptional targets. In addition to mutation, structural variations and partial copy losses involving PTEN and STK11 showed evidence for having functional relevance. A substantial fraction of cancers showed high mTOR pathway activity without an associated canonical genetic or genomic alteration, including cancers harboring IDH1 or VHL mutations, suggesting multiple mechanisms for pathway activation.
Keywords: Databases, Genetic; Gene Expression Profiling; Humans; Mutation; Neoplasms; Phosphatidylinositol 3-Kinases; Proteogenomics; Proto-Oncogene Proteins c-akt; Signal Transduction; Survival Analysis; TOR Serine-Threonine Kinases

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10, odds ratio (OR) = 0.68, minor allele frequency (MAF) = 0.0059, MAF = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10, OR = 1.43, MAF = 0.011, MAF = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10, OR = 1.67, MAF = 0.0143, MAF = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Recommended Guidelines for Validation, Quality Control, and Reporting of Variants in Clinical Practice. - Leroy, Bernard; Ballinger, Mandy L; Baran-Marszak, Fanny; Bond, Gareth L; Braithwaite, Antony; Concin, Nicole; Donehower, Lawrence A; El-Deiry, Wafik S; Fenaux, Pierre; Gaidano, Gianluca; Langerød, Anita; Hellstrom-Lindberg, Eva; et al. (Cancer Res, 2017)
Accurate assessment of gene status in sporadic tumors and in the germline of individuals at high risk of cancer due to Li-Fraumeni Syndrome (LFS) has important clinical implications for diagnosis, surveillance, and therapy. Genomic data from more than 20,000 cancer genomes provide a wealth of information on cancer gene alterations and have confirmed as the most commonly mutated gene in human cancer. Analysis of a database of 70,000 variants reveals that the two newly discovered exons of the gene, exons 9β and 9γ, generated by alternative splicing, are the targets of inactivating mutation events in breast, liver, and head and neck tumors. Furthermore, germline rearrange-ments in intron 1 of are associated with LFS and are frequently observed in sporadic osteosarcoma. In this context of constantly growing genomic data, we discuss how screening strategies must be improved when assessing status in clinical samples. Finally, we discuss how alterations should be described by using accurate nomenclature to avoid confusion in scientific and clinical reports. .
Keywords: Genetic Variation; Humans; Neoplasms; Practice Guidelines as Topic; Quality Control; Tumor Suppressor Protein p53; Validation Studies as Topic

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

REEP6 deficiency leads to retinal degeneration through disruption of ER homeostasis and protein trafficking. - Agrawal, Smriti A; Burgoyne, Thomas; Eblimit, Aiden; Bellingham, James; Parfitt, David A; Lane, Amelia; Nichols, Ralph; Asomugha, Chinwe; Hayes, Matthew J; Munro, Peter M; Xu, Mingchu; Wang, Keqing; et al. (Hum Mol Genet, 2017)
Retinitis pigmentosa (RP) is the most common form of inherited retinal dystrophy. We recently identified mutations in REEP6, which encodes the receptor expression enhancing protein 6, in several families with autosomal recessive RP. REEP6 is related to the REEP and Yop1p family of ER shaping proteins and potential receptor accessory proteins, but the role of REEP6 in the retina is unknown. Here we characterize the disease mechanisms associated with loss of REEP6 function using a Reep6 knockout mouse generated by CRISPR/Cas9 gene editing. In control mice REEP6 was localized to the inner segment and outer plexiform layer of rod photoreceptors. The Reep6-/- mice exhibited progressive photoreceptor degeneration from P20 onwards. Ultrastructural analyses at P20 by transmission electron microscopy and 3View serial block face scanning EM revealed an expansion of the distal ER in the Reep6-/- rods and an increase in their number of mitochondria. Electroretinograms revealed photoreceptor dysfunction preceded degeneration, suggesting potential defects in phototransduction. There was no effect on the traffic of rhodopsin, Rom1 or peripherin/rds; however, the retinal guanylate cyclases GC1 and GC2 were severely affected in the Reep6 knockout animals, with almost undetectable expression. These changes correlated with an increase in C/EBP homologous protein (CHOP) expression and the activation of caspase 12, suggesting that ER stress contributes to cell death. Collectively, these data suggest that REEP6 plays an essential role in maintaining cGMP homeostasis though facilitating the stability and/or trafficking of guanylate cyclases and maintaining ER and mitochondrial homeostasis.
Keywords: Animals; Base Sequence; Clustered Regularly Interspaced Short Palindromic Repeats; Endoplasmic Reticulum; Eye Proteins; Gene Editing; Guanylate Cyclase; Light Signal Transduction; Membrane Proteins; Membrane Transport Proteins; Mice; Mice, Knockout; Photoreceptor Cells, Vertebrate; Retinal Dystrophies; Retinal Rod Photoreceptor Cells; Rhodopsin

The SWI/SNF Protein PBRM1 Restrains VHL-Loss-Driven Clear Cell Renal Cell Carcinoma. - Nargund, Amrita M; Pham, Can G; Dong, Yiyu; Wang, Patricia I; Osmangeyoglu, Hatice U; Xie, Yuchen; Aras, Omer; Han, Song; Oyama, Toshinao; Takeda, Shugaku; Ray, Chelsea E; Dong, Zhenghong; et al. (Cell Rep, 2017)
PBRM1 is the second most commonly mutated gene after VHL in clear cell renal cell carcinoma (ccRCC). However, the biological consequences of PBRM1 mutations for kidney tumorigenesis are unknown. Here, we find that kidney-specific deletion of Vhl and Pbrm1, but not either gene alone, results in bilateral, multifocal, transplantable clear cell kidney cancers. PBRM1 loss amplified the transcriptional outputs of HIF1 and STAT3 incurred by Vhl deficiency. Analysis of mouse and human ccRCC revealed convergence on mTOR activation, representing the third driver event after genetic inactivation of VHL and PBRM1. Our study reports a physiological preclinical ccRCC mouse model that recapitulates somatic mutations in human ccRCC and provides mechanistic and therapeutic insights into PBRM1 mutated subtypes of human ccRCC.
Keywords: Animals; Carcinoma, Renal Cell; DNA-Binding Proteins; Down-Regulation; Gene Deletion; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; HMGB Proteins; Humans; Hydronephrosis; Hypoxia-Inducible Factor 1, alpha Subunit; Integrases; Kidney; Kidney Neoplasms; Mechanistic Target of Rapamycin Complex 1; Mice; Nuclear Proteins; Oxidative Phosphorylation; Signal Transduction; STAT3 Transcription Factor; Transcription Factors; Transcription, Genetic; Von Hippel-Lindau Tumor Suppressor Protein

Transcriptomic variation of pharmacogenes in multiple human tissues and lymphoblastoid cell lines. - Chhibber, A; French, C E; Yee, S W; Gamazon, E R; Theusch, E; Xiang Qin; Webb, A; Papp, A C; Wang, A; Simmons, C Q; Konkashbaev, A; Chaudhry, A S; et al. (Pharmacogenomics J, 2017)
Variation in the expression level and activity of genes involved in drug disposition and action ('pharmacogenes') can affect drug response and toxicity, especially when in tissues of pharmacological importance. Previous studies have relied primarily on microarrays to understand gene expression differences, or have focused on a single tissue or small number of samples. The goal of this study was to use RNA-sequencing (RNA-seq) to determine the expression levels and alternative splicing of 389 Pharmacogenomics Research Network pharmacogenes across four tissues (liver, kidney, heart and adipose) and lymphoblastoid cell lines, which are used widely in pharmacogenomics studies. Analysis of RNA-seq data from 139 different individuals across the 5 tissues (20-45 individuals per tissue type) revealed substantial variation in both expression levels and splicing across samples and tissue types. Comparison with GTEx data yielded a consistent picture. This in-depth exploration also revealed 183 splicing events in pharmacogenes that were previously not annotated. Overall, this study serves as a rich resource for the research community to inform biomarker and drug discovery and use.
Keywords: Adipose Tissue; Alternative Splicing; Cell Line; Computational Biology; Databases, Genetic; Genotype; High-Throughput Nucleotide Sequencing; Humans; Kidney; Liver; Myocardium; Pharmacogenetics; Pharmacogenomic Variants; Phenotype; Sequence Analysis, RNA; Transcriptome

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
IMPORTANCE: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. OBJECTIVE: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. DESIGN, SETTING, AND PARTICIPANTS: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. MAIN OUTCOMES AND MEASURES: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. RESULTS: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. CONCLUSIONS AND RELEVANCE: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Exome Sequencing; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Muzny, Donna; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Exome Sequencing; Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male

Whole-genome landscape of pancreatic neuroendocrine tumours. - Scarpa, Aldo; Chang, David K; Nones, Katia; Corbo, Vincenzo; Patch, Ann-Marie; Bailey, Peter; Lawlor, Rita T; Johns, Amber L; Miller, David K; Mafficini, Andrea; Rusev, Borislav; Scardoni, Maria; et al. (Nature, 2017)
The diagnosis of pancreatic neuroendocrine tumours (PanNETs) is increasing owing to more sensitive detection methods, and this increase is creating challenges for clinical management. We performed whole-genome sequencing of 102 primary PanNETs and defined the genomic events that characterize their pathogenesis. Here we describe the mutational signatures they harbour, including a deficiency in G:C > T:A base excision repair due to inactivation of MUTYH, which encodes a DNA glycosylase. Clinically sporadic PanNETs contain a larger-than-expected proportion of germline mutations, including previously unreported mutations in the DNA repair genes MUTYH, CHEK2 and BRCA2. Together with mutations in MEN1 and VHL, these mutations occur in 17% of patients. Somatic mutations, including point mutations and gene fusions, were commonly found in genes involved in four main pathways: chromatin remodelling, DNA damage repair, activation of mTOR signalling (including previously undescribed EWSR1 gene fusions), and telomere maintenance. In addition, our gene expression analyses identified a subgroup of tumours associated with hypoxia and HIF signalling.
Keywords: Base Sequence; Calmodulin-Binding Proteins; Carcinoma, Neuroendocrine; Chromatin Assembly and Disassembly; Chromosome Aberrations; DNA Copy Number Variations; DNA Glycosylases; DNA Mutational Analysis; DNA Repair; Female; Genome, Human; Genomics; Germ-Line Mutation; Humans; Male; Pancreatic Neoplasms; RNA-Binding Protein EWS; RNA-Binding Proteins; Telomere; TOR Serine-Threonine Kinases

Aggressive tumor growth and clinical evolution in a patient with X-linked acro-gigantism syndrome. - Naves, Luciana A; Daly, Adrian F; Dias, Luiz Augusto; Yuan, Bo; Zakir, Juliano Coelho Oliveira; Barra, Gustavo Barcellos; Palmeira, Leonor; Villa, Chiara; Trivellin, Giampaolo; Júnior, Armindo Jreige; Neto, Florêncio Figueiredo Cavalcante; Liu, Pengfei; et al. (Endocrine, 2016)
X-linked acro-gigantism (X-LAG) syndrome is a newly described disease caused by microduplications on chromosome Xq26.3 leading to copy number gain of GPR101. We describe the clinical progress of a sporadic male X-LAG syndrome patient with an Xq26.3 microduplication, highlighting the aggressive natural history of pituitary tumor growth in the absence of treatment. The patient first presented elsewhere aged 5 years 8 months with a history of excessive growth for >2 years. His height was 163 cm, his weight was 36 kg, and he had markedly elevated GH and IGF-1. MRI showed a non-invasive sellar mass measuring 32.5 × 23.9 × 29.1 mm. Treatment was declined and the family was lost to follow-up. At the age of 10 years and 7 months, he presented again with headaches, seizures, and visual disturbance. His height had increased to 197 cm. MRI showed an invasive mass measuring 56.2 × 58.1 × 45.0 mm, with compression of optic chiasma, bilateral cavernous sinus invasion, and hydrocephalus. His thyrotrope, corticotrope, and gonadotrope axes were deficient. Surgery, somatostatin analogs, and cabergoline did not control vertical growth and pegvisomant was added, although vertical growth continues (currently 207 cm at 11 years 7 months of age). X-LAG syndrome is a new genomic disorder in which early-onset pituitary tumorigenesis can lead to marked overgrowth and gigantism. This case illustrates the aggressive nature of tumor evolution and the challenging clinical management in X-LAG syndrome.
Keywords: Adenoma; Child; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Pituitary Neoplasms; Treatment Outcome

Altered neuronal network and rescue in a human MECP2 duplication model. - Nageshappa, S; Carromeu, C; Trujillo, C A; Mesci, P; Espuny-Camacho, I; Pasciuto, E; Vanderhaeghen, P; Verfaillie, C M; Raitano, S; Kumar, A; Carvalho, C M B; Bagni, C; et al. (Mol Psychiatry, 2016)
Increased dosage of methyl-CpG-binding protein-2 (MeCP2) results in a dramatic neurodevelopmental phenotype with onset at birth. We generated induced pluripotent stem cells (iPSCs) from patients with the MECP2 duplication syndrome (MECP2dup), carrying different duplication sizes, to study the impact of increased MeCP2 dosage in human neurons. We show that cortical neurons derived from these different MECP2dup iPSC lines have increased synaptogenesis and dendritic complexity. In addition, using multi-electrodes arrays, we show that neuronal network synchronization was altered in MECP2dup-derived neurons. Given MeCP2 functions at the epigenetic level, we tested whether these alterations were reversible using a library of compounds with defined activity on epigenetic pathways. One histone deacetylase inhibitor, NCH-51, was validated as a potential clinical candidate. Interestingly, this compound has never been considered before as a therapeutic alternative for neurological disorders. Our model recapitulates early stages of the human MECP2 duplication syndrome and represents a promising cellular tool to facilitate therapeutic drug screening for severe neurodevelopmental disorders.
Keywords: Cell Differentiation; Dendrites; Gene Dosage; Gene Duplication; Genetic Association Studies; Humans; Induced Pluripotent Stem Cells; Male; Methyl-CpG-Binding Protein 2; Nerve Net; Neurogenesis; Neurons

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Avirulence gene mapping in the Hessian fly (Mayetiola destructor) reveals a protein phosphatase 2C effector gene family. - Zhao, Chaoyang; Shukle, Richard; Navarro-Escalante, Lucio; Chen, Mingshun; Richards, Stephen; Stuart, Jeffrey J (J Insect Physiol, 2016)
The genetic tractability of the Hessian fly (HF, Mayetiola destructor) provides an opportunity to investigate the mechanisms insects use to induce plant gall formation. Here we demonstrate that capacity using the newly sequenced HF genome by identifying the gene (vH24) that elicits effector-triggered immunity in wheat (Triticum spp.) seedlings carrying HF resistance gene H24. vH24 was mapped within a 230-kb genomic fragment near the telomere of HF chromosome X1. That fragment contains only 21 putative genes. The best candidate vH24 gene in this region encodes a protein containing a secretion signal and a type-2 serine/threonine protein phosphatase (PP2C) domain. This gene has an H24-virulence associated insertion in its promoter that appears to silence transcription of the gene in H24-virulent larvae. Candidate vH24 is a member of a small family of genes that encode secretion signals and PP2C domains. It belongs to the fraction of genes in the HF genome previously predicted to encode effector proteins. Because PP2C proteins are not normally secreted, our results suggest that these are PP2C effectors that HF larvae inject into wheat cells to redirect, or interfere, with wheat signal transduction pathways.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; Diptera; Female; Genes, Insect; Genes, Plant; Genes, Recessive; Genes, X-Linked; Host-Parasite Interactions; Male; Phosphoprotein Phosphatases; Plant Immunity; Plant Proteins; Plant Tumors; Protein Phosphatase 2C; Telomere; Triticum; Virulence

Causal Role of Alcohol Consumption in an Improved Lipid Profile: The Atherosclerosis Risk in Communities (ARIC) Study. - Vu, Khanh N; Ballantyne, Christie M; Hoogeveen, Ron C; Nambi, Vijay; Volcik, Kelly A; Boerwinkle, Eric; Morrison, Alanna C (PLoS One, 2016)
INTRODUCTION: Health benefits of low-to-moderate alcohol consumption may operate through an improved lipid profile. A Mendelian randomization (MR) approach was used to examine whether alcohol consumption causally affects lipid levels. METHODS: This analysis involved 10,893 European Americans (EA) from the Atherosclerosis Risk in Communities (ARIC) study. Common and rare variants in alcohol dehydrogenase and acetaldehyde dehydrogenase genes were evaluated for MR assumptions. Five variants, residing in the ADH1B, ADH1C, and ADH4 genes, were selected as genetic instruments and were combined into an unweighted genetic score. Triglycerides (TG), total cholesterol, high-density lipoprotein cholesterol (HDL-c) and its subfractions (HDL2-c and HDL3-c), low-density lipoprotein cholesterol (LDL-c), small dense LDL-c (sdLDL-c), apolipoprotein B (apoB), and lipoprotein (a) (Lp(a)) levels were analyzed. RESULTS: Alcohol consumption significantly increased HDL2-c and reduced TG, total cholesterol, LDL-c, sdLDL-c, and apoB levels. For each of these lipids a non-linear trend was observed. Compared to the first quartile of alcohol consumption, the third quartile had a 12.3% lower level of TG (p < 0.001), a 7.71 mg/dL lower level of total cholesterol (p = 0.007), a 10.3% higher level of HDL2-c (p = 0.007), a 6.87 mg/dL lower level of LDL-c (p = 0.012), a 7.4% lower level of sdLDL-c (p = 0.037), and a 3.5% lower level of apoB (p = 0.058, poverall = 0.022). CONCLUSIONS: This study supports the causal role of regular low-to-moderate alcohol consumption in increasing HDL2-c, reducing TG, total cholesterol, and LDL-c, and provides evidence for the novel finding that low-to-moderate consumption of alcohol reduces apoB and sdLDL-c levels among EA. However, given the nonlinearity of the effect of alcohol consumption, even within the range of low-to-moderate drinking, increased consumption does not always result in a larger benefit.
Keywords: Alcohol Dehydrogenase; Alcohol Drinking; Atherosclerosis; Female; Humans; Lipids; Male; Middle Aged

Chromosomal-Level Assembly of the Asian Seabass Genome Using Long Sequence Reads and Multi-layered Scaffolding. - Vij, Shubha; Kuhl, Heiner; Kuznetsova, Inna S; Komissarov, Aleksey; Yurchenko, Andrey A; Van Heusden, Peter; Singh, Siddharth; Thevasagayam, Natascha M; Prakki, Sai Rama Sridatta; Purushothaman, Kathiresan; Saju, Jolly M; Jiang, Junhui; et al. (PLoS Genet, 2016)
We report here the ~670 Mb genome assembly of the Asian seabass (Lates calcarifer), a tropical marine teleost. We used long-read sequencing augmented by transcriptomics, optical and genetic mapping along with shared synteny from closely related fish species to derive a chromosome-level assembly with a contig N50 size over 1 Mb and scaffold N50 size over 25 Mb that span ~90% of the genome. The population structure of L. calcarifer species complex was analyzed by re-sequencing 61 individuals representing various regions across the species' native range. SNP analyses identified high levels of genetic diversity and confirmed earlier indications of a population stratification comprising three clades with signs of admixture apparent in the South-East Asian population. The quality of the Asian seabass genome assembly far exceeds that of any other fish species, and will serve as a new standard for fish genomics.
Keywords: Animals; Bass; Chromosome Mapping; Genome; In Situ Hybridization, Fluorescence; Phylogeny

Clinical Sequencing Exploratory Research Consortium: Accelerating Evidence-Based Practice of Genomic Medicine. - Green, Robert C; Goddard, Katrina A B; Jarvik, Gail P; Amendola, Laura M; Appelbaum, Paul S; Berg, Jonathan S; Bernhardt, Barbara A; Biesecker, Leslie G; Biswas, Sawona; Blout, Carrie L; Bowling, Kevin M; Brothers, Kyle B; et al. (Am J Hum Genet, 2016)
Despite rapid technical progress and demonstrable effectiveness for some types of diagnosis and therapy, much remains to be learned about clinical genome and exome sequencing (CGES) and its role within the practice of medicine. The Clinical Sequencing Exploratory Research (CSER) consortium includes 18 extramural research projects, one National Human Genome Research Institute (NHGRI) intramural project, and a coordinating center funded by the NHGRI and National Cancer Institute. The consortium is exploring analytic and clinical validity and utility, as well as the ethical, legal, and social implications of sequencing via multidisciplinary approaches; it has thus far recruited 5,577 participants across a spectrum of symptomatic and healthy children and adults by utilizing both germline and cancer sequencing. The CSER consortium is analyzing data and creating publically available procedures and tools related to participant preferences and consent, variant classification, disclosure and management of primary and secondary findings, health outcomes, and integration with electronic health records. Future research directions will refine measures of clinical utility of CGES in both germline and somatic testing, evaluate the use of CGES for screening in healthy individuals, explore the penetrance of pathogenic variants through extensive phenotyping, reduce discordances in public databases of genes and variants, examine social and ethnic disparities in the provision of genomics services, explore regulatory issues, and estimate the value and downstream costs of sequencing. The CSER consortium has established a shared community of research sites by using diverse approaches to pursue the evidence-based development of best practices in genomic medicine.
Keywords: Adult; Biomedical Research; Cardiovascular Diseases; Child; Clinical Trials as Topic; Evidence-Based Practice; Exome; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; National Human Genome Research Institute (U.S.); Polymorphism, Single Nucleotide; Population Groups; Software; United States

Comparative Genomics of Two Closely Related Wolbachia with Different Reproductive Effects on Hosts. - Newton, Irene L G; Clark, Michael E; Kent, Bethany N; Bordenstein, Seth R; Qu, Jiaxin; Richards, Stephen; Kelkar, Yogeshwar D; Werren, John H (Genome Biol Evol, 2016)
Wolbachia pipientis are obligate intracellular bacteria commonly found in many arthropods. They can induce various reproductive alterations in hosts, including cytoplasmic incompatibility, male-killing, feminization, and parthenogenetic development, and can provide host protection against some viruses and other pathogens. Wolbachia differ from many other primary endosymbionts in arthropods because they undergo frequent horizontal transmission between hosts and are well known for an abundance of mobile elements and relatively high recombination rates. Here, we compare the genomes of two closely related Wolbachia (with 0.57% genome-wide synonymous divergence) that differ in their reproductive effects on hosts. wVitA induces a sperm-egg incompatibility (also known as cytoplasmic incompatibility) in the parasitoid insect Nasonia vitripennis, whereas wUni causes parthenogenetic development in a different parasitoid, Muscidifurax uniraptor Although these bacteria are closely related, the genomic comparison reveals rampant rearrangements, protein truncations (particularly in proteins predicted to be secreted), and elevated substitution rates. These changes occur predominantly in the wUni lineage, and may be due in part to adaptations by wUni to a new host environment, or its phenotypic shift to parthenogenesis induction. However, we conclude that the approximately 8-fold elevated synonymous substitution rate in wUni is due to a either an elevated mutation rate or a greater number of generations per year in wUni, which occurs in semitropical host species. We identify a set of genes whose loss or pseudogenization in the wUni lineage implicates them in the phenotypic shift from cytoplasmic incompatibility to parthenogenesis induction. Finally, comparison of these closely related strains allows us to determine the fine-scale mutation patterns in Wolbachia Although Wolbachia are AT rich, mutation probabilities estimated from 4-fold degenerate sites are not AT biased, and predict an equilibrium AT content much less biased than observed (57-50% AT predicted vs. 76% current content at degenerate sites genome wide). The contrast suggests selection for increased AT content within Wolbachia genomes.
Keywords: Animals; Arthropods; Cytoplasm; Drosophila; Genome, Bacterial; Genomics; Host Specificity; Male; Mutation; Phylogeny; Reproduction; Selection, Genetic; Wolbachia

A comprehensive transcriptional map of primate brain development. - Bakken, Trygve E; Miller, Jeremy A; Ding, Song-Lin; Sunkin, Susan M; Smith, Kimberly A; Ng, Lydia; Szafer, Aaron; Dalley, Rachel A; Royall, Joshua J; Lemon, Tracy; Shapouri, Sheila; Aiona, Kaylynn; et al. (Nature, 2016)
The transcriptional underpinnings of brain development remain poorly understood, particularly in humans and closely related non-human primates. We describe a high-resolution transcriptional atlas of rhesus monkey (Macaca mulatta) brain development that combines dense temporal sampling of prenatal and postnatal periods with fine anatomical division of cortical and subcortical regions associated with human neuropsychiatric disease. Gene expression changes more rapidly before birth, both in progenitor cells and maturing neurons. Cortical layers and areas acquire adult-like molecular profiles surprisingly late in postnatal development. Disparate cell populations exhibit distinct developmental timing of gene expression, but also unexpected synchrony of processes underlying neural circuit construction including cell projection and adhesion. Candidate risk genes for neurodevelopmental disorders including primary microcephaly, autism spectrum disorder, intellectual disability, and schizophrenia show disease-specific spatiotemporal enrichment within developing neocortex. Human developmental expression trajectories are more similar to monkey than rodent, although approximately 9% of genes show human-specific regulation with evidence for prolonged maturation or neoteny compared to monkey.
Keywords: Aging; Animals; Autism Spectrum Disorder; Brain; Cell Adhesion; Conserved Sequence; Female; Humans; Intellectual Disability; Macaca mulatta; Male; Microcephaly; Neocortex; Neurodevelopmental Disorders; Neurogenesis; Risk Factors; Schizophrenia; Spatio-Temporal Analysis; Species Specificity; Transcription, Genetic; Transcriptome

Correction: Chromosomal-Level Assembly of the Asian Seabass Genome Using Long Sequence Reads and Multi-layered Scaffolding. - Vij, Shubha; Kuhl, Heiner; Kuznetsova, Inna S; Komissarov, Aleksey; Yurchenko, Andrey A; Van Heusden, Peter; Singh, Siddharth; Thevasagayam, Natascha M; Prakki, Sai Rama Sridatta; Purushothaman, Kathiresan; Saju, Jolly M; Jiang, Junhui; et al. (PLoS Genet, 2016)
[This corrects the article DOI: 10.1371/journal.pgen.1005954.].

CRIPT exonic deletion and a novel missense mutation in a female with short stature, dysmorphic features, microcephaly, and pigmentary abnormalities. - Leduc, Magalie S; Niu, Zhiyv; Bi, Weimin; Zhu, Wenmiao; Miloslavskaya, Irene; Chiang, Theodore; Streff, Haley; Seavitt, John R; Murray, Stephen A; Eng, Christine; Chan, Audrey; Yang, Yaping; et al. (Am J Med Genet A, 2016)
Mutations in CRIPT encoding cysteine-rich PDZ domain-binding protein are rare, and to date have been reported in only two patients with autosomal recessive primordial dwarfism and distinctive facies. Here, we describe a female with biallelic mutations in CRIPT presenting with postnatal growth retardation, global developmental delay, and dysmorphic features including frontal bossing, high forehead, and sparse hair and eyebrows. Additional clinical features included high myopia, admixed hyper- and hypopigmented macules primarily on the face, arms, and legs, and syndactyly of 4-5 toes bilaterally. Using whole exome sequencing (WES) and chromosomal microarray analysis (CMA), we detected a c.8G>A (p.C3Y) missense variant in exon 1 of the CRIPT gene inherited from the mother and a 1,331 bp deletion encompassing exon 1, inherited from the father. The c.8G>A (p.C3Y) missense variant in CRIPT was apparently homozygous in the proband due to the exon 1 deletion. Our findings illustrate the clinical utility of combining WES with copy number variant (CNV) analysis to provide a molecular diagnosis to patients with rare Mendelian disorders. Our findings also illustrate the clinical spectrum of CRIPT related mutations. © 2016 Wiley Periodicals, Inc.
Keywords: Abnormalities, Multiple; Adaptor Proteins, Signal Transducing; Alleles; Amino Acid Substitution; Child, Preschool; DNA Mutational Analysis; Dwarfism; Exons; Facies; Female; Genetic Association Studies; Humans; Microcephaly; Mutation, Missense; Pedigree; Phenotype; Sequence Deletion

Cross-species identification of genomic drivers of squamous cell carcinoma development across preneoplastic intermediates. - Chitsazzadeh, Vida; Coarfa, Cristian; Drummond, Jennifer A; Nguyen, Tri; Joseph, Aaron; Chilukuri, Suneel; Charpiot, Elizabeth; Adelmann, Charles H; Ching, Grace; Nguyen, Tran N; Nicholas, Courtney; Thomas, Valencia D; et al. (Nat Commun, 2016)
Cutaneous squamous cell carcinoma (cuSCC) comprises 15-20% of all skin cancers, accounting for over 700,000 cases in USA annually. Most cuSCC arise in association with a distinct precancerous lesion, the actinic keratosis (AK). To identify potential targets for molecularly targeted chemoprevention, here we perform integrated cross-species genomic analysis of cuSCC development through the preneoplastic AK stage using matched human samples and a solar ultraviolet radiation-driven Hairless mouse model. We identify the major transcriptional drivers of this progression sequence, showing that the key genomic changes in cuSCC development occur in the normal skin to AK transition. Our data validate the use of this ultraviolet radiation-driven mouse cuSCC model for cross-species analysis and demonstrate that cuSCC bears deep molecular similarities to multiple carcinogen-driven SCCs from diverse sites, suggesting that cuSCC may serve as an effective, accessible model for multiple SCC types and that common treatment and prevention strategies may be feasible.
Keywords: Animals; Antineoplastic Agents; Carcinogenesis; Carcinoma, Squamous Cell; Disease Progression; DNA Mutational Analysis; Exome Sequencing; Female; Gene Expression Profiling; Genomics; High-Throughput Nucleotide Sequencing; Humans; Keratosis, Actinic; Mice; Mice, Hairless; Molecular Targeted Therapy; Precancerous Conditions; Sequence Analysis, RNA; Skin; Skin Neoplasms; Ultraviolet Rays

Destabilized SMC5/6 complex leads to chromosome breakage syndrome with severe lung disease. - van der Crabben, Saskia N; Hennus, Marije P; McGregor, Grant A; Ritter, Deborah I; Nagamani, Sandesh C S; Wells, Owen S; Harakalova, Magdalena; Chinn, Ivan K; Alt, Aaron; Vondrova, Lucie; Hochstenbach, Ron; van Montfrans, Joris M; et al. (J Clin Invest, 2016)
The structural maintenance of chromosomes (SMC) family of proteins supports mitotic proliferation, meiosis, and DNA repair to control genomic stability. Impairments in chromosome maintenance are linked to rare chromosome breakage disorders. Here, we have identified a chromosome breakage syndrome associated with severe lung disease in early childhood. Four children from two unrelated kindreds died of severe pulmonary disease during infancy following viral pneumonia with evidence of combined T and B cell immunodeficiency. Whole exome sequencing revealed biallelic missense mutations in the NSMCE3 (also known as NDNL2) gene, which encodes a subunit of the SMC5/6 complex that is essential for DNA damage response and chromosome segregation. The NSMCE3 mutations disrupted interactions within the SMC5/6 complex, leading to destabilization of the complex. Patient cells showed chromosome rearrangements, micronuclei, sensitivity to replication stress and DNA damage, and defective homologous recombination. This work associates missense mutations in NSMCE3 with an autosomal recessive chromosome breakage syndrome that leads to defective T and B cell function and acute respiratory distress syndrome in early childhood.
Keywords: Abnormalities, Multiple; Alleles; B-Lymphocytes; Cell Cycle Proteins; Cell Proliferation; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Chromosome Breakage; Chromosome Segregation; Chromosomes; DNA Damage; DNA Repair; DNA Replication; Family Health; Female; Fibroblasts; Homozygote; Humans; Infant; Intracellular Signaling Peptides and Proteins; Lung Diseases; Male; Meiosis; Mitosis; Mutation, Missense; Pedigree; Recombination, Genetic; Syndrome; T-Lymphocytes

Diagnostic Yield of Clinical Tumor and Germline Whole-Exome Sequencing for Children With Solid Tumors. - Parsons, D Williams; Roy, Angshumoy; Yang, Yaping; Wang, Tao; Scollon, Sarah; Bergstrom, Katie; Kerstein, Robin A; Gutierrez, Stephanie; Petersen, Andrea K; Bavle, Abhishek; Lin, Frank Y; López-Terrada, Dolores H; et al. (JAMA Oncol, 2016)
IMPORTANCE: Whole-exome sequencing (WES) has the potential to reveal tumor and germline mutations of clinical relevance, but the diagnostic yield for pediatric patients with solid tumors is unknown. OBJECTIVE: To characterize the diagnostic yield of combined tumor and germline WES for children with solid tumors. DESIGN: Unselected children with newly diagnosed and previously untreated central nervous system (CNS) and non-CNS solid tumors were prospectively enrolled in the BASIC3 study at a large academic children's hospital during a 23-month period from August 2012 through June 2014. Blood and tumor samples underwent WES in a certified clinical laboratory with genetic results categorized on the basis of perceived clinical relevance and entered in the electronic health record. MAIN OUTCOMES AND MEASURES: Clinical categorization of somatic mutations; frequencies of deleterious germline mutations related to patient phenotype and incidental medically-actionable mutations. RESULTS: Of the first 150 participants (80 boys and 70 girls, mean age, 7.4 years), tumor samples adequate for WES were available from 121 patients (81%). Somatic mutations of established clinical utility (category I) were reported in 4 (3%) of 121 patients, with mutations of potential utility (category II) detected in an additional 29 (24%) of 121 patients. CTNNB1 was the gene most frequently mutated, with recurrent mutations in KIT, TSC2, and MAPK pathway genes (BRAF, KRAS, and NRAS) also identified. Mutations in consensus cancer genes (category III) were found in an additional 24 (20%) of 121 tumors. Fewer than half of somatic mutations identified were in genes known to be recurrently mutated in the tumor type tested. Diagnostic germline findings related to patient phenotype were discovered in 15 (10%) of 150 cases: 13 pathogenic or likely pathogenic dominant mutations in adult and pediatric cancer susceptibility genes (including 2 each in TP53, VHL, and BRCA1), 1 recessive liver disorder with hepatocellular carcinoma (TJP2), and 1 renal diagnosis (CLCN5). Incidental findings were reported in 8 (5%) of 150 patients. Most patients harbored germline uncertain variants in cancer genes (98%), pharmacogenetic variants (89%), and recessive carrier mutations (85%). CONCLUSIONS AND RELEVANCE: Tumor and germline WES revealed mutations in a broad spectrum of genes previously implicated in both adult and pediatric cancers. Combined reporting of tumor and germline WES identified diagnostic and/or potentially actionable findings in nearly 40% of newly diagnosed pediatric patients with solid tumors.

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.
Keywords: Alleles; Basic Helix-Loop-Helix Transcription Factors; Black or African American; Chromosomes, Human, Pair 5; DNA Methylation; Female; Gene Expression Regulation; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Failure; HEK293 Cells; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Cytokine

DNA methylation-based measures of biological age: meta-analysis predicting time to death. - Chen, Brian H; Marioni, Riccardo E; Colicino, Elena; Peters, Marjolein J; Ward-Caviness, Cavin K; Tsai, Pei-Chien; Roetker, Nicholas S; Just, Allan C; Demerath, Ellen W; Guan, Weihua; Bressler, Jan; Fornage, Myriam; et al. (Aging (Albany NY), 2016)
Estimates of biological age based on DNA methylation patterns, often referred to as "epigenetic age", "DNAm age", have been shown to be robust biomarkers of age in humans. We previously demonstrated that independent of chronological age, epigenetic age assessed in blood predicted all-cause mortality in four human cohorts. Here, we expanded our original observation to 13 different cohorts for a total sample size of 13,089 individuals, including three racial/ethnic groups. In addition, we examined whether incorporating information on blood cell composition into the epigenetic age metrics improves their predictive power for mortality. All considered measures of epigenetic age acceleration were predictive of mortality (p≤8.2x10, independent of chronological age, even after adjusting for additional risk factors (p<5.4x10, and within the racial/ethnic groups that we examined (non-Hispanic whites, Hispanics, African Americans). Epigenetic age estimates that incorporated information on blood cell composition led to the smallest p-values for time to death (p=7.5x10). Overall, this study a) strengthens the evidence that epigenetic age predicts all-cause mortality above and beyond chronological age and traditional risk factors, and b) demonstrates that epigenetic age estimates that incorporate information on blood cell counts lead to highly significant associations with all-cause mortality.
Keywords: Aging; DNA Methylation; Epigenesis, Genetic; Female; Humans; Logistic Models; Male; Mortality; Racial Groups; Risk Factors; Survival Analysis; T-Lymphocyte Subsets

The Ensembl gene annotation system. - Aken, Bronwen L; Ayling, Sarah; Barrell, Daniel; Clarke, Laura; Curwen, Valery; Fairley, Susan; Fernandez Banet, Julio; Billis, Konstantinos; García Girón, Carlos; Hourlier, Thibaut; Howe, Kevin; Kähäri, Andreas; et al. (Database (Oxford), 2016)
The Ensembl gene annotation system has been used to annotate over 70 different vertebrate species across a wide range of genome projects. Furthermore, it generates the automatic alignment-based annotation for the human and mouse GENCODE gene sets. The system is based on the alignment of biological sequences, including cDNAs, proteins and RNA-seq reads, to the target genome in order to construct candidate transcript models. Careful assessment and filtering of these candidate transcripts ultimately leads to the final gene set, which is made available on the Ensembl website. Here, we describe the annotation process in detail.Database URL: http://www.ensembl.org/index.html.
Keywords: Animals; Databases, Nucleic Acid; Databases, Protein; Humans; Internet; Mice; Molecular Sequence Annotation

The ethics of conducting molecular autopsies in cases of sudden death in the young. - McGuire, Amy L; Moore, Quianta; Majumder, Mary; Walkiewicz, Magdalena; Eng, Christine M; Belmont, John W; Nassef, Salma; Darilek, Sandra; Rutherford, Katie; Pereira, Stacey; Steven E Scherer; Sutton, V Reid; et al. (Genome Res, 2016)
Keywords: Autopsy; Child; Child, Preschool; Confidentiality; Consent Forms; Coroners and Medical Examiners; Disclosure; Ethics, Medical; Genetic Testing; Humans; Infant; Infant, Newborn

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.
Keywords: Allelic Imbalance; Black or African American; Erythrocyte Indices; Erythrocytes; Erythropoiesis; Exome; Gene Frequency; Genetic Pleiotropy; Genetic Variation; Genotype; Hematocrit; Hemoglobins; Humans; Quantitative Trait Loci

Functional annotation of rare gene aberration drivers of pancreatic cancer. - Tsang, Yiu Huen; Dogruluk, Turgut; Tedeschi, Philip M; Wardwell-Ozgo, Joanna; Lu, Hengyu; Espitia, Maribel; Nair, Nikitha; Minelli, Rosalba; Chong, Zechen; Chen, Fengju; Chang, Qing Edward; Dennison, Jennifer B; et al. (Nat Commun, 2016)
As we enter the era of precision medicine, characterization of cancer genomes will directly influence therapeutic decisions in the clinic. Here we describe a platform enabling functionalization of rare gene mutations through their high-throughput construction, molecular barcoding and delivery to cancer models for in vivo tumour driver screens. We apply these technologies to identify oncogenic drivers of pancreatic ductal adenocarcinoma (PDAC). This approach reveals oncogenic activity for rare gene aberrations in genes including NAD Kinase (NADK), which regulates NADP(H) homeostasis and cellular redox state. We further validate mutant NADK, whose expression provides gain-of-function enzymatic activity leading to a reduction in cellular reactive oxygen species and tumorigenesis, and show that depletion of wild-type NADK in PDAC cell lines attenuates cancer cell growth in vitro and in vivo. These data indicate that annotating rare aberrations can reveal important cancer signalling pathways representing additional therapeutic targets.
Keywords: Animals; Carcinogenesis; Cell Line, Tumor; Female; Humans; Mice; Mice, Nude; Mutation; Pancreatic Neoplasms; Phosphotransferases (Alcohol Group Acceptor); Reactive Oxygen Species

Genome of the Asian longhorned beetle (Anoplophora glabripennis), a globally significant invasive species, reveals key functional and evolutionary innovations at the beetle-plant interface. - McKenna, Duane D; Scully, Erin D; Pauchet, Yannick; Hoover, Kelli; Kirsch, Roy; Geib, Scott M; Mitchell, Robert F; Waterhouse, Robert M; Ahn, Seung-Joon; Arsala, Deanna; Benoit, Joshua B; Blackmon, Heath; et al. (Genome Biol, 2016)
BACKGROUND: Relatively little is known about the genomic basis and evolution of wood-feeding in beetles. We undertook genome sequencing and annotation, gene expression assays, studies of plant cell wall degrading enzymes, and other functional and comparative studies of the Asian longhorned beetle, Anoplophora glabripennis, a globally significant invasive species capable of inflicting severe feeding damage on many important tree species. Complementary studies of genes encoding enzymes involved in digestion of woody plant tissues or detoxification of plant allelochemicals were undertaken with the genomes of 14 additional insects, including the newly sequenced emerald ash borer and bull-headed dung beetle. RESULTS: The Asian longhorned beetle genome encodes a uniquely diverse arsenal of enzymes that can degrade the main polysaccharide networks in plant cell walls, detoxify plant allelochemicals, and otherwise facilitate feeding on woody plants. It has the metabolic plasticity needed to feed on diverse plant species, contributing to its highly invasive nature. Large expansions of chemosensory genes involved in the reception of pheromones and plant kairomones are consistent with the complexity of chemical cues it uses to find host plants and mates. CONCLUSIONS: Amplification and functional divergence of genes associated with specialized feeding on plants, including genes originally obtained via horizontal gene transfer from fungi and bacteria, contributed to the addition, expansion, and enhancement of the metabolic repertoire of the Asian longhorned beetle, certain other phytophagous beetles, and to a lesser degree, other phytophagous insects. Our results thus begin to establish a genomic basis for the evolutionary success of beetles on plants.
Keywords: Animals; Coleoptera; Evolution, Molecular; Gene Transfer, Horizontal; Genome, Insect; Host-Parasite Interactions; Introduced Species; Larva; Sequence Analysis, DNA; Trees

Genomic analyses identify molecular subtypes of pancreatic cancer. - Bailey, Peter; Chang, David K; Nones, Katia; Johns, Amber L; Patch, Ann-Marie; Marie-Claude Gingras; Miller, David K; Christ, Angelika N; Bruxner, Tim J C; Quinn, Michael C; Nourse, Craig; Murtaugh, L Charles; et al. (Nature, 2016)
Integrated genomic analysis of 456 pancreatic ductal adenocarcinomas identified 32 recurrently mutated genes that aggregate into 10 pathways: KRAS, TGF-β, WNT, NOTCH, ROBO/SLIT signalling, G1/S transition, SWI-SNF, chromatin modification, DNA repair and RNA processing. Expression analysis defined 4 subtypes: (1) squamous; (2) pancreatic progenitor; (3) immunogenic; and (4) aberrantly differentiated endocrine exocrine (ADEX) that correlate with histopathological characteristics. Squamous tumours are enriched for TP53 and KDM6A mutations, upregulation of the TP63∆N transcriptional network, hypermethylation of pancreatic endodermal cell-fate determining genes and have a poor prognosis. Pancreatic progenitor tumours preferentially express genes involved in early pancreatic development (FOXA2/3, PDX1 and MNX1). ADEX tumours displayed upregulation of genes that regulate networks involved in KRAS activation, exocrine (NR5A2 and RBPJL), and endocrine differentiation (NEUROD1 and NKX2-2). Immunogenic tumours contained upregulated immune networks including pathways involved in acquired immune suppression. These data infer differences in the molecular evolution of pancreatic cancer subtypes and identify opportunities for therapeutic development.
Keywords: Animals; Basic Helix-Loop-Helix Transcription Factors; Carcinoma, Pancreatic Ductal; Cell Line, Tumor; DNA Methylation; DNA-Binding Proteins; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genes, Neoplasm; Genome, Human; Genomics; Hepatocyte Nuclear Factor 3-beta; Hepatocyte Nuclear Factor 3-gamma; Histone Demethylases; Homeobox Protein Nkx-2.2; Homeodomain Proteins; Humans; Mice; Mutation; Nuclear Proteins; Pancreatic Neoplasms; Prognosis; Receptors, Cytoplasmic and Nuclear; Survival Analysis; Trans-Activators; Transcription Factors; Transcription, Genetic; Transcriptome; Tumor Suppressor Protein p53; Tumor Suppressor Proteins; Zebrafish Proteins

A genomic approach to therapeutic target validation identifies a glucose-lowering GLP1R variant protective for coronary heart disease. - Scott, Robert A; Freitag, Daniel F; Li, Li; Chu, Audrey Y; Surendran, Praveen; Young, Robin; Grarup, Niels; Stančáková, Alena; Chen, Yuning; Varga, Tibor V; Yaghootkar, Hanieh; Luan, Jian'an; et al. (Sci Transl Med, 2016)
Regulatory authorities have indicated that new drugs to treat type 2 diabetes (T2D) should not be associated with an unacceptable increase in cardiovascular risk. Human genetics may be able to guide development of antidiabetic therapies by predicting cardiovascular and other health endpoints. We therefore investigated the association of variants in six genes that encode drug targets for obesity or T2D with a range of metabolic traits in up to 11,806 individuals by targeted exome sequencing and follow-up in 39,979 individuals by targeted genotyping, with additional in silico follow-up in consortia. We used these data to first compare associations of variants in genes encoding drug targets with the effects of pharmacological manipulation of those targets in clinical trials. We then tested the association of those variants with disease outcomes, including coronary heart disease, to predict cardiovascular safety of these agents. A low-frequency missense variant (Ala316Thr; rs10305492) in the gene encoding glucagon-like peptide-1 receptor (GLP1R), the target of GLP1R agonists, was associated with lower fasting glucose and T2D risk, consistent with GLP1R agonist therapies. The minor allele was also associated with protection against heart disease, thus providing evidence that GLP1R agonists are not likely to be associated with an unacceptable increase in cardiovascular risk. Our results provide an encouraging signal that these agents may be associated with benefit, a question currently being addressed in randomized controlled trials. Genetic variants associated with metabolic traits and multiple disease outcomes can be used to validate therapeutic targets at an early stage in the drug development process.
Keywords: Alleles; Coronary Disease; Diabetes Mellitus, Type 2; Dipeptidyl Peptidase 4; Genotype; Glucagon-Like Peptide-1 Receptor; Humans; Obesity; Receptor, Cannabinoid, CB2; Receptor, Serotonin, 5-HT2C; Receptors, Somatostatin; Sodium-Glucose Transporter 1

The genomic basis of circadian and circalunar timing adaptations in a midge. - Kaiser, Tobias S; Poehn, Birgit; Szkiba, David; Preussner, Marco; Sedlazeck, Fritz J; Zrim, Alexander; Neumann, Tobias; Nguyen, Lam-Tung; Betancourt, Andrea J; Hummel, Thomas; Vogel, Heiko; Dorner, Silke; et al. (Nature, 2016)
Organisms use endogenous clocks to anticipate regular environmental cycles, such as days and tides. Natural variants resulting in differently timed behaviour or physiology, known as chronotypes in humans, have not been well characterized at the molecular level. We sequenced the genome of Clunio marinus, a marine midge whose reproduction is timed by circadian and circalunar clocks. Midges from different locations show strain-specific genetic timing adaptations. We examined genetic variation in five C. marinus strains from different locations and mapped quantitative trait loci for circalunar and circadian chronotypes. The region most strongly associated with circadian chronotypes generates strain-specific differences in the abundance of calcium/calmodulin-dependent kinase II.1 (CaMKII.1) splice variants. As equivalent variants were shown to alter CaMKII activity in Drosophila melanogaster, and C. marinus (Cma)-CaMKII.1 increases the transcriptional activity of the dimer of the circadian proteins Cma-CLOCK and Cma-CYCLE, we suggest that modulation of alternative splicing is a mechanism for natural adaptation in circadian timing.
Keywords: Acclimatization; Alternative Splicing; Animals; Calcium-Calmodulin-Dependent Protein Kinase Type 2; Chironomidae; Circadian Clocks; Circadian Rhythm; CLOCK Proteins; Drosophila melanogaster; Genetic Association Studies; Genetic Variation; Genome, Insect; Genomics; Male; Moon; Phenotype; Quantitative Trait Loci; Reproduction; Species Specificity; Tidal Waves; Time Factors; Transcription, Genetic

Hypomorphic mutations identified in the candidate Leber congenital amaurosis gene CLUAP1. - Soens, Zachry T; Li, Yuanyuan; Zhao, Li; Eblimit, Aiden; Dharmat, Rachayata; Li, Yumei; Chen, Yiyun; Naqeeb, Mohammed; Fajardo, Norma; Lopez, Irma; Sun, Zhaoxia; Koenekoop, Robert K; et al. (Genet Med, 2016)
PURPOSE: Leber congenital amaurosis (LCA) is an early-onset form of retinal degeneration. Six of the 22 known LCA genes encode photoreceptor ciliary proteins. Despite the identification of 22 LCA genes, the genetic basis of ~30% of LCA patients remains unknown. We sought to investigate the cause of disease in the remaining 30% by examining cilia-associated genes. METHODS: Whole-exome sequencing was performed on an LCA cohort of 212 unsolved probands previously screened for mutations in known retinal-disease genes. Immunohistochemistry using mouse retinas was used to confirm protein localization and zebrafish were used to perform rescue experiments. RESULTS: A homozygous nonsynonymous mutation was found in a single proband in CLUAP1, a gene required for ciliogenesis and cilia maintenance. Cluap1 knockout zebrafish exhibit photoreceptor cell death as early as 5 days after fertilization, and rescue experiments revealed that our proband's mutation is significantly hypomorphic. CONCLUSION: Consistent with the knowledge that CLUAP1 plays an important role in cilia function and that cilia are critical to photoreceptor function, our results indicate that hypomorphic mutations in CLUAP1 can result in dysfunctional photoreceptors without systemic abnormalities. This is the first report linking mutations in CLUAP1 to human disease and establishes CLUAP1 as a candidate LCA gene.Genet Med 18 10, 1044-1051.
Keywords: Animals; Antigens, Neoplasm; Child, Preschool; Cilia; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Leber Congenital Amaurosis; Male; Mutation; Photoreceptor Cells; Retinal Degeneration; Zebrafish

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

The impact of multiple single day blood pressure readings on cardiovascular risk estimation: The Atherosclerosis Risk in Communities study. - Ogunwale, Abayomi N; Morrison, Alanna C; Sun, Wensheng; Dodge, Rhiannon C; Virani, Salim S; Taylor, Addison; Gottesman, Rebecca F; Yang, Eric; Wei, Peng; McEvoy, John W; Heiss, Gerardo; Boerwinkle, Eric; et al. (Eur J Prev Cardiol, 2016)
AIMS: The aim of this study was to determine the magnitude of change in estimated cardiovascular disease risk when multiple same day blood pressure measurements are used in estimating coronary heart disease, heart failure and stroke risks. METHODS AND RESULTS: Black and White participants, N = 11,129, enrolled in the Atherosclerosis Risk in Communities study (mean age 53.9 ± 5.7 (SD) years) were included. Each participant had three sitting, five supine, and six standing blood pressure measures during one day. Main outcome measures were changes in estimated coronary heart disease, heart failure and stroke risk when using the different blood pressure measures. Mean sitting, standing and supine systolic blood pressure values of the study population were 120.8 ± 18.6, 124.9 ± 20 and 124.7 ± 19.6 mmHg, respectively. The substitution of the second sitting systolic blood pressure with the third sitting systolic blood pressure (taken ∼5 min later) in two separate coronary heart disease risk models reclassified 3.3% to 5.1% of study participants. Similar substitutions for heart failure and stroke risk prediction models led to reclassification of 1.9% and 2.7% of participants respectively. When mean sitting systolic blood pressure was replaced with mean standing systolic blood pressure 5.4% to 11.6% of the participants were reclassified. Maximum upward and downward change in an individual's estimated risk was 31% and 26% respectively. CONCLUSIONS: Estimated risks of coronary heart disease, heart failure, and stroke for an individual can change significantly within a day due to changes in systolic blood pressure. Given recommendations to use estimated risk for therapeutic decisions, our study has implications for the use of a single systolic blood pressure in cardiovascular risk estimation.
Keywords: Atherosclerosis; Blood Pressure; Blood Pressure Determination; Cardiovascular Diseases; Female; Humans; Incidence; Male; Middle Aged; Risk Assessment; Risk Factors; United States

Isolated and Syndromic Retinal Dystrophy Caused by Biallelic Mutations in RCBTB1, a Gene Implicated in Ubiquitination. - Coppieters, Frauke; Ascari, Giulia; Dannhausen, Katharina; Nikopoulos, Konstantinos; Peelman, Frank; Karlstetter, Marcus; Xu, Mingchu; Brachet, Cécile; Meunier, Isabelle; Tsilimbaris, Miltiadis K; Tsika, Chrysanthi; Blazaki, Styliani V; et al. (Am J Hum Genet, 2016)
Inherited retinal dystrophies (iRDs) are a group of genetically and clinically heterogeneous conditions resulting from mutations in over 250 genes. Here, homozygosity mapping and whole-exome sequencing (WES) in a consanguineous family revealed a homozygous missense mutation, c.973C>T (p.His325Tyr), in RCBTB1. In affected individuals, it was found to segregate with retinitis pigmentosa (RP), goiter, primary ovarian insufficiency, and mild intellectual disability. Subsequent analysis of WES data in different cohorts uncovered four additional homozygous missense mutations in five unrelated families in whom iRD segregates with or without syndromic features. Ocular phenotypes ranged from typical RP starting in the second decade to chorioretinal dystrophy with a later age of onset. The five missense mutations affect highly conserved residues either in the sixth repeat of the RCC1 domain or in the BTB1 domain. A founder haplotype was identified for mutation c.919G>A (p.Val307Met), occurring in two families of Mediterranean origin. We showed ubiquitous mRNA expression of RCBTB1 and demonstrated predominant RCBTB1 localization in human inner retina. RCBTB1 was very recently shown to be involved in ubiquitination, more specifically as a CUL3 substrate adaptor. Therefore, the effect on different components of the CUL3 and NFE2L2 (NRF2) pathway was assessed in affected individuals' lymphocytes, revealing decreased mRNA expression of NFE2L2 and several NFE2L2 target genes. In conclusion, our study puts forward mutations in RCBTB1 as a cause of autosomal-recessive non-syndromic and syndromic iRD. Finally, our data support a role for impaired ubiquitination in the pathogenetic mechanism of RCBTB1 mutations.
Keywords: Adolescent; Adult; Age of Onset; Alleles; Child; Consanguinity; Cullin Proteins; Exome; Female; Founder Effect; Genes, Recessive; Guanine Nucleotide Exchange Factors; Haplotypes; Homozygote; Humans; Lymphocytes; Male; Mutation, Missense; NF-E2-Related Factor 2; Pedigree; Phenotype; Retina; Retinal Dystrophies; RNA, Messenger; Syndrome; Turkey; Ubiquitination

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.
Keywords: Blood Cell Count; Exome; Genetic Loci; Genetic Pleiotropy; Genome-Wide Association Study; Humans; Immune System Diseases; Leukocytes; Quality Control

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Sabo, Aniko; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.
Keywords: Angiopoietin-Like Protein 4; Angiopoietins; Exons; Fasting; Female; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

The mitogenome of the bed bug (Hemiptera: Cimicidae). - Kolokotronis, Sergios-Orestis; Foox, Jonathan; Rosenfeld, Jeffrey A; Brugler, Mercer R; Reeves, Darryl; Benoit, Joshua B; Booth, Warren; Robison, Grant; Steffen, Michael; Sakas, Zoe; Palli, Subba R; Schal, Coby; et al. (Mitochondrial DNA B Resour, 2016)
We report the extraction of a bed bug mitogenome from high-throughput sequencing projects originally focused on the nuclear genome of . The assembled mitogenome has a similar AT nucleotide composition bias found in other insects. Phylogenetic analysis of all protein-coding genes indicates that is clearly a member of a paraphyletic Cimicomorpha clade within the Order Hemiptera.

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Multifaceted biological insights from a draft genome sequence of the tobacco hornworm moth, Manduca sexta. - Kanost, Michael R; Arrese, Estela L; Cao, Xiaolong; Chen, Yun-Ru; Chellapilla, Sanjay; Goldsmith, Marian R; Grosse-Wilde, Ewald; Heckel, David G; Herndon, Nicolae; Jiang, Haobo; Papanicolaou, Alexie; Qu, Jiaxin; et al. (Insect Biochem Mol Biol, 2016)
Manduca sexta, known as the tobacco hornworm or Carolina sphinx moth, is a lepidopteran insect that is used extensively as a model system for research in insect biochemistry, physiology, neurobiology, development, and immunity. One important benefit of this species as an experimental model is its extremely large size, reaching more than 10 g in the larval stage. M. sexta larvae feed on solanaceous plants and thus must tolerate a substantial challenge from plant allelochemicals, including nicotine. We report the sequence and annotation of the M. sexta genome, and a survey of gene expression in various tissues and developmental stages. The Msex_1.0 genome assembly resulted in a total genome size of 419.4 Mbp. Repetitive sequences accounted for 25.8% of the assembled genome. The official gene set is comprised of 15,451 protein-coding genes, of which 2498 were manually curated. Extensive RNA-seq data from many tissues and developmental stages were used to improve gene models and for insights into gene expression patterns. Genome wide synteny analysis indicated a high level of macrosynteny in the Lepidoptera. Annotation and analyses were carried out for gene families involved in a wide spectrum of biological processes, including apoptosis, vacuole sorting, growth and development, structures of exoskeleton, egg shells, and muscle, vision, chemosensation, ion channels, signal transduction, neuropeptide signaling, neurotransmitter synthesis and transport, nicotine tolerance, lipid metabolism, and immunity. This genome sequence, annotation, and analysis provide an important new resource from a well-studied model insect species and will facilitate further biochemical and mechanistic experimental studies of many biological systems in insects.
Keywords: Animals; Gene Expression; Gene Expression Profiling; Genome, Insect; Larva; Manduca; Pupa; Sequence Analysis, DNA; Synteny

Multilevel Genomics-Based Taxonomy of Renal Cell Carcinoma. - Chen, Fengju; Zhang, Yiqun; Şenbabaoğlu, Yasin; Ciriello, Giovanni; Yang, Lixing; Reznik, Ed; Shuch, Brian; Micevic, Goran; De Velasco, Guillermo; Shinbrot, Eve; Noble, Michael S; Lu, Yiling; et al. (Cell Rep, 2016)
On the basis of multidimensional and comprehensive molecular characterization (including DNA methalylation and copy number, RNA, and protein expression), we classified 894 renal cell carcinomas (RCCs) of various histologic types into nine major genomic subtypes. Site of origin within the nephron was one major determinant in the classification, reflecting differences among clear cell, chromophobe, and papillary RCC. Widespread molecular changes associated with TFE3 gene fusion or chromatin modifier genes were present within a specific subtype and spanned multiple subtypes. Differences in patient survival and in alteration of specific pathways (including hypoxia, metabolism, MAP kinase, NRF2-ARE, Hippo, immune checkpoint, and PI3K/AKT/mTOR) could further distinguish the subtypes. Immune checkpoint markers and molecular signatures of T cell infiltrates were both highest in the subtype associated with aggressive clear cell RCC. Differences between the genomic subtypes suggest that therapeutic strategies could be tailored to each RCC disease subset.
Keywords: Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Carcinoma, Renal Cell; Chromatin; Gene Expression Profiling; Genomics; Humans; Kidney Neoplasms; MicroRNAs; Mutation; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; RNA, Messenger; Signal Transduction; Survival Rate; TOR Serine-Threonine Kinases

Mutations in REEP6 Cause Autosomal-Recessive Retinitis Pigmentosa. - Arno, Gavin; Agrawal, Smriti A; Eblimit, Aiden; Bellingham, James; Xu, Mingchu; Wang, Feng; Chakarova, Christina; Parfitt, David A; Lane, Amelia; Burgoyne, Thomas; Hull, Sarah; Carss, Keren J; et al. (Am J Hum Genet, 2016)
Retinitis pigmentosa (RP) is the most frequent form of inherited retinal dystrophy. RP is genetically heterogeneous and the genes identified to date encode proteins involved in a wide range of functional pathways, including photoreceptor development, phototransduction, the retinoid cycle, cilia, and outer segment development. Here we report the identification of biallelic mutations in Receptor Expression Enhancer Protein 6 (REEP6) in seven individuals with autosomal-recessive RP from five unrelated families. REEP6 is a member of the REEP/Yop1 family of proteins that influence the structure of the endoplasmic reticulum but is relatively unstudied. The six variants identified include three frameshift variants, two missense variants, and a genomic rearrangement that disrupts exon 1. Human 3D organoid optic cups were used to investigate REEP6 expression and confirmed the expression of a retina-specific isoform REEP6.1, which is specifically affected by one of the frameshift mutations. Expression of the two missense variants (c.383C>T [p.Pro128Leu] and c.404T>C [p.Leu135Pro]) and the REEP6.1 frameshift mutant in cultured cells suggest that these changes destabilize the protein. Furthermore, CRISPR-Cas9-mediated gene editing was used to produce Reep6 knock-in mice with the p.Leu135Pro RP-associated variant identified in one RP-affected individual. The homozygous knock-in mice mimic the clinical phenotypes of RP, including progressive photoreceptor degeneration and dysfunction of the rod photoreceptors. Therefore, our study implicates REEP6 in retinal homeostasis and highlights a pathway previously uncharacterized in retinal dystrophy.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Eye Proteins; Female; Genes, Recessive; Humans; Induced Pluripotent Stem Cells; Male; Membrane Proteins; Membrane Transport Proteins; Mice; Mutation; Mutation, Missense; Phenotype; Photoreceptor Cells, Vertebrate; Retinitis Pigmentosa; Young Adult

Nonrecurrent PMP22-RAI1 contiguous gene deletions arise from replication-based mechanisms and result in Smith-Magenis syndrome with evident peripheral neuropathy. - Yuan, Bo; Neira, Juanita; Gu, Shen; Harel, Tamar; Liu, Pengfei; Briceño, Ignacio; Elsea, Sarah H; Gómez, Alberto; Potocki, Lorraine; Lupski, James R (Hum Genet, 2016)
Hereditary neuropathy with liability to pressure palsies (HNPP) and Smith-Magenis syndrome (SMS) are genomic disorders associated with deletion copy number variants involving chromosome 17p12 and 17p11.2, respectively. Nonallelic homologous recombination (NAHR)-mediated recurrent deletions are responsible for the majority of HNPP and SMS cases; the rearrangement products encompass the key dosage-sensitive genes PMP22 and RAI1, respectively, and result in haploinsufficiency for these genes. Less frequently, nonrecurrent genomic rearrangements occur at this locus. Contiguous gene duplications encompassing both PMP22 and RAI1, i.e., PMP22-RAI1 duplications, have been investigated, and replication-based mechanisms rather than NAHR have been proposed for these rearrangements. In the current study, we report molecular and clinical characterizations of six subjects with the reciprocal phenomenon of deletions spanning both genes, i.e., PMP22-RAI1 deletions. Molecular studies utilizing high-resolution array comparative genomic hybridization and breakpoint junction sequencing identified mutational signatures that were suggestive of replication-based mechanisms. Systematic clinical studies revealed features consistent with SMS, including features of intellectual disability, speech and gross motor delays, behavioral problems and ocular abnormalities. Five out of six subjects presented clinical signs and/or objective electrophysiologic studies of peripheral neuropathy. Clinical profiling may improve the clinical management of this unique group of subjects, as the peripheral neuropathy can be more severe or of earlier onset as compared to SMS patients having the common recurrent deletion. Moreover, the current study, in combination with the previous report of PMP22-RAI1 duplications, contributes to the understanding of rare complex phenotypes involving multiple dosage-sensitive genes from a genetic mechanistic standpoint.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Replication; Female; Gene Deletion; Haploinsufficiency; Homologous Recombination; Humans; Intellectual Disability; Male; Mutation; Myelin Proteins; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors

Novel genetic causes for cerebral visual impairment. - Bosch, Daniëlle G M; Boonstra, F Nienke; de Leeuw, Nicole; Pfundt, Rolph; Nillesen, Willy M; de Ligt, Joep; Gilissen, Christian; Jhangiani, Shalini; Lupski, James R; Cremers, Frans P M; de Vries, Bert B A (Eur J Hum Genet, 2016)
Cerebral visual impairment (CVI) is a major cause of low vision in children due to impairment in projection and/or interpretation of the visual input in the brain. Although acquired causes for CVI are well known, genetic causes underlying CVI are largely unidentified. DNAs of 25 patients with CVI and intellectual disability, but without acquired (eg, perinatal) damage, were investigated by whole-exome sequencing. The data were analyzed for de novo, autosomal-recessive, and X-linked variants, and subsequently classified into known, candidate, or unlikely to be associated with CVI. This classification was based on the Online Mendelian Inheritance in Man database, literature reports, variant characteristics, and functional relevance of the gene. After classification, variants in four genes known to be associated with CVI (AHDC1, NGLY1, NR2F1, PGAP1) in 5 patients (20%) were identified, establishing a conclusive genetic diagnosis for CVI. In addition, in 11 patients (44%) with CVI, variants in one or more candidate genes were identified (ACP6, AMOT, ARHGEF10L, ATP6V1A, DCAF6, DLG4, GABRB2, GRIN1, GRIN2B, KCNQ3, KCTD19, RERE, SLC1A1, SLC25A16, SLC35A2, SOX5, UFSP2, UHMK1, ZFP30). Our findings show that diverse genetic causes underlie CVI, some of which will provide insight into the biology underlying this disease process.
Keywords: Adolescent; Blindness, Cortical; Child; Child, Preschool; Female; Genetic Loci; Humans; Male; Polymorphism, Single Nucleotide; Young Adult

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Muzny, Donna M; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Boerwinkle, Eric; Gibbs, Richard A; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

PGRNseq: a targeted capture sequencing panel for pharmacogenetic research and implementation. - Gordon, Adam S; Fulton, Robert S; Qin, Xiang; Mardis, Elaine R; Nickerson, Deborah A; Scherer, Steve (Pharmacogenet Genomics, 2016)
OBJECTIVES: Although the costs associated with whole-genome and whole-exome next-generation sequencing continue to decline, they remain prohibitively expensive for large-scale studies of genetic variation. As an alternative, custom-target sequencing has become a common methodology on the basis of its favorable balance between cost, throughput, and deep coverage. METHODS: We have developed PGRNseq, a custom-capture panel of 84 genes with associations to pharmacogenetic phenotypes, as a tool to explore the relationship between drug response and genetic variation, both common and rare. We utilized a set of 32 diverse HapMap trios and two clinical cohorts to assess platform performance, accuracy, and ability to discover novel variation. RESULTS: We found that PGRNseq generates ultra-deep coverage data (mean=496x) that are over 99.8% concordant with orthogonal datasets. In addition, in our testing sets, PGRNseq identified many novel, rare variants of interest, underscoring its value in both research and clinical settings. CONCLUSION: PGRNseq is an ideal platform for carrying out sequencing-based analyses of pharmacogenetic variation in large cohorts. In addition, the high accuracy associated with genotypes from PGRNseq highlight its utility as a clinical test.

Phased diploid genome assembly with single-molecule real-time sequencing. - Chin, Chen-Shan; Peluso, Paul; Sedlazeck, Fritz J; Nattestad, Maria; Concepcion, Gregory T; Clum, Alicia; Dunn, Christopher; O'Malley, Ronan; Figueroa-Balderas, Rosa; Morales-Cruz, Abraham; Cramer, Grant R; Delledonne, Massimo; et al. (Nat Methods, 2016)
While genome assembly projects have been successful in many haploid and inbred species, the assembly of noninbred or rearranged heterozygous genomes remains a major challenge. To address this challenge, we introduce the open-source FALCON and FALCON-Unzip algorithms (https://github.com/PacificBiosciences/FALCON/) to assemble long-read sequencing data into highly accurate, contiguous, and correctly phased diploid genomes. We generate new reference sequences for heterozygous samples including an F1 hybrid of Arabidopsis thaliana, the widely cultivated Vitis vinifera cv. Cabernet Sauvignon, and the coral fungus Clavicorona pyxidata, samples that have challenged short-read assembly approaches. The FALCON-based assemblies are substantially more contiguous and complete than alternate short- or long-read approaches. The phased diploid assembly enabled the study of haplotype structure and heterozygosities between homologous chromosomes, including the identification of widespread heterozygous structural variation within coding sequences.
Keywords: Algorithms; Arabidopsis; Basidiomycota; Diploidy; DNA, Fungal; DNA, Plant; Genome, Fungal; Genome, Plant; Genomics; Haplotypes; Heterozygote; Humans; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Vitis

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.
Keywords: Blood Platelets; Exome; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Mean Platelet Volume; Platelet Count

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Boerwinkle, Eric; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.
Keywords: Alleles; Black People; Blood Pressure; Chloride Channels; Exome; Female; Gene Frequency; Humans; Hypertension; Male; Risk Factors; White People

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apolipoproteins E; Drosophila melanogaster; Drosophila Proteins; Exome; Female; Genome-Wide Association Study; Genomics; Humans; Iceland; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Mutation; Phenotype; Receptors, Notch; Tropomyosin; White People

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic or Latino; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis; White People

Reorganization and expansion of the nidoviral family Arteriviridae. - Kuhn, Jens H; Lauck, Michael; Bailey, Adam L; Shchetinin, Alexey M; Vishnevskaya, Tatyana V; Bào, Yīmíng; Ng, Terry Fei Fan; LeBreton, Matthew; Schneider, Bradley S; Gillis, Amethyst; Tamoufe, Ubald; Diffo, Joseph Le Doux; et al. (Arch Virol, 2016)
The family Arteriviridae presently includes a single genus Arterivirus. This genus includes four species as the taxonomic homes for equine arteritis virus (EAV), lactate dehydrogenase-elevating virus (LDV), porcine respiratory and reproductive syndrome virus (PRRSV), and simian hemorrhagic fever virus (SHFV), respectively. A revision of this classification is urgently needed to accommodate the recent description of eleven highly divergent simian arteriviruses in diverse African nonhuman primates, one novel arterivirus in an African forest giant pouched rat, and a novel arterivirus in common brushtails in New Zealand. In addition, the current arterivirus nomenclature is not in accordance with the most recent version of the International Code of Virus Classification and Nomenclature. Here we outline an updated, amended, and improved arterivirus taxonomy based on current data. Taxon-specific sequence cut-offs are established relying on a newly established open reading frame 1b phylogeny and pairwise sequence comparison (PASC) of coding-complete arterivirus genomes. As a result, the current genus Arterivirus is replaced by five genera: Equartevirus (for EAV), Rodartevirus (LDV + PRRSV), Simartevirus (SHFV + simian arteriviruses), Nesartevirus (for the arterivirus from forest giant pouched rats), and Dipartevirus (common brushtail arterivirus). The current species Porcine reproductive and respiratory syndrome virus is divided into two species to accommodate the clear divergence of the European and American "types" of PRRSV, both of which now receive virus status. The current species Simian hemorrhagic fever virus is divided into nine species to accommodate the twelve known simian arteriviruses. Non-Latinized binomial species names are introduced to replace all current species names to clearly differentiate them from virus names, which remain largely unchanged.
Keywords: Arteriviridae; Cluster Analysis; Genome, Viral; Open Reading Frames; Phylogeny; RNA Virus Infections; RNA, Viral; Sequence Homology; Terminology as Topic

Somatic mosaicism underlies X-linked acrogigantism syndrome in sporadic male subjects. - Daly, Adrian F; Bo Yuan; Fina, Frederic; Caberg, Jean-Hubert; Trivellin, Giampaolo; Rostomyan, Liliya; de Herder, Wouter W; Naves, Luciana A; Metzger, Daniel; Cuny, Thomas; Rabl, Wolfgang; Shah, Nalini; et al. (Endocr Relat Cancer, 2016)
Somatic mosaicism has been implicated as a causative mechanism in a number of genetic and genomic disorders. X-linked acrogigantism (XLAG) syndrome is a recently characterized genomic form of pediatric gigantism due to aggressive pituitary tumors that is caused by submicroscopic chromosome Xq26.3 duplications that include GPR101 We studied XLAG syndrome patients (n= 18) to determine if somatic mosaicism contributed to the genomic pathophysiology. Eighteen subjects with XLAG syndrome caused by Xq26.3 duplications were identified using high-definition array comparative genomic hybridization (HD-aCGH). We noted that males with XLAG had a decreased log2ratio (LR) compared with expected values, suggesting potential mosaicism, whereas females showed no such decrease. Compared with familial male XLAG cases, sporadic males had more marked evidence for mosaicism, with levels of Xq26.3 duplication between 16.1 and 53.8%. These characteristics were replicated using a novel, personalized breakpoint junction-specific quantification droplet digital polymerase chain reaction (ddPCR) technique. Using a separate ddPCR technique, we studied the feasibility of identifying XLAG syndrome cases in a distinct patient population of 64 unrelated subjects with acromegaly/gigantism, and identified one female gigantism patient who had had increased copy number variation (CNV) threshold for GPR101 that was subsequently diagnosed as having XLAG syndrome on HD-aCGH. Employing a combination of HD-aCGH and novel ddPCR approaches, we have demonstrated, for the first time, that XLAG syndrome can be caused by variable degrees of somatic mosaicism for duplications at chromosome Xq26.3. Somatic mosaicism was shown to occur in sporadic males but not in females with XLAG syndrome, although the clinical characteristics of the disease were similarly severe in both sexes.
Keywords: Adult; Female; Genetic Diseases, X-Linked; Gigantism; Humans; Male; Middle Aged; Mosaicism; Polymerase Chain Reaction; Syndrome; Young Adult

Targeted sequencing of genome wide significant loci associated with bone mineral density (BMD) reveals significant novel and rare variants: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Hsu, Yi-Hsiang; Li, Guo; Liu, Ching-Ti; Brody, Jennifer A; Karasik, David; Chou, Wen-Chi; Demissie, Serkalem; Nandakumar, Kannabiran; Zhou, Yanhua; Cheng, Chia-Ho; Gill, Richard; Gibbs, Richard A; et al. (Hum Mol Genet, 2016)
Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study ( n =  925) and Cardiovascular Health Study ( n =  366), including 206 women and men with extreme low femoral neck (FN) BMD. A total of 4,964 sequence variants (SNVs) were observed and 80% were rare with MAF <1%. The associations between previously identified SNPs in these loci and BMD, while nominally significant in sequenced participants, were no longer significant after multiple testing corrections. Conditional analyses did not find protein-coding variants that may be responsible for GWAS signals. On the other hand, in the sequenced subjects, we identified novel associations in WLS , ARHGAP1 , and 5' of MEF2C ( P- values < 8x10  -   5 ; false discovery rate (FDR) q-values < 0.01) that were much more strongly associated with BMD compared to the GWAS SNPs. These associated SNVs are less-common; independent from previous GWAS signals in the same loci; and located in gene regulatory elements. Our findings suggest that protein-coding variants in selected GWAS loci did not contribute to GWAS signals. By performing targeted sequencing in GWAS loci, we identified less-common and rare non-coding SNVs associated with BMD independently from GWAS common SNPs, suggesting both common and less-common variants may associate with disease risks and phenotypes in the same loci.
Keywords: Aging; Bone Density; Cardiovascular Diseases; Cohort Studies; Epidemiologic Studies; Female; Femur Neck; Genetic Predisposition to Disease; Genome-Wide Association Study; GTPase-Activating Proteins; Humans; Male; MEF2 Transcription Factors; Middle Aged; Polymorphism, Single Nucleotide

Tumour-suppressor microRNAs regulate ovarian cancer cell physical properties and invasive behaviour. - Chan, Clara K; Pan, Yinghong; Nyberg, Kendra; Marra, Marco A; Lim, Emilia L; Jones, Steven J M; Maar, Dianna; Gibb, Ewan A; Gunaratne, Preethi H; Robertson, A Gordon; Rowat, Amy C (Open Biol, 2016)
The activities of pathways that regulate malignant transformation can be influenced by microRNAs (miRs). Recently, we showed that increased expression of five tumour-suppressor miRs, miR-508-3p, miR-508-5p, miR-509-3p, miR-509-5p and miR-130b-3p, correlate with improved clinical outcomes in human ovarian cancer patients, and that miR-509-3p attenuates invasion of ovarian cancer cell lines. Here, we investigate the mechanism underlying this reduced invasive potential by assessing the impact of these five miRs on the physical properties of cells. Human ovarian cancer cells (HEYA8, OVCAR8) that are transfected with miR mimics representing these five miRs exhibit decreased invasion through collagen matrices, increased cell size and reduced deformability as measured by microfiltration and microfluidic assays. To understand the molecular basis of altered invasion and deformability induced by these miRs, we use predicted and validated mRNA targets that encode structural and signalling proteins that regulate cell mechanical properties. Combined with analysis of gene transcripts by real-time PCR and image analysis of F-actin in single cells, our results suggest that these tumour-suppressor miRs may alter cell physical properties by regulating the actin cytoskeleton. Our findings provide biophysical insights into how tumour-suppressor miRs can regulate the invasive behaviour of ovarian cancer cells, and identify potential therapeutic targets that may be implicated in ovarian cancer progression.
Keywords: Actin Cytoskeleton; Cell Line, Tumor; Cell Movement; Female; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Humans; MicroRNAs; Neoplasm Invasiveness; Ovarian Neoplasms; Signal Transduction; Up-Regulation

Unique features of a global human ectoparasite identified through sequencing of the bed bug genome. - Benoit, Joshua B; Adelman, Zach N; Reinhardt, Klaus; Dolan, Amanda; Poelchau, Monica; Jennings, Emily C; Szuter, Elise M; Hagan, Richard W; Gujar, Hemant; Shukla, Jayendra Nath; Zhu, Fang; Mohan, M; et al. (Nat Commun, 2016)
The bed bug, Cimex lectularius, has re-established itself as a ubiquitous human ectoparasite throughout much of the world during the past two decades. This global resurgence is likely linked to increased international travel and commerce in addition to widespread insecticide resistance. Analyses of the C. lectularius sequenced genome (650 Mb) and 14,220 predicted protein-coding genes provide a comprehensive representation of genes that are linked to traumatic insemination, a reduced chemosensory repertoire of genes related to obligate hematophagy, host-symbiont interactions, and several mechanisms of insecticide resistance. In addition, we document the presence of multiple putative lateral gene transfer events. Genome sequencing and annotation establish a solid foundation for future research on mechanisms of insecticide resistance, human-bed bug and symbiont-bed bug associations, and unique features of bed bug biology that contribute to the unprecedented success of C. lectularius as a human ectoparasite.
Keywords: Animals; Bedbugs; Ectoparasitic Infestations; Feeding Behavior; Gene Transfer, Horizontal; Genome; Host-Parasite Interactions; Humans; Insecticide Resistance; Insecticides; Sequence Analysis, DNA

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Boerwinkle, Eric; Gibbs, Richard A; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.
Keywords: Aged; Atrial Fibrillation; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Microfilament Proteins; Middle Aged; Polymorphism, Single Nucleotide

AAV8(Y733F)-mediated gene therapy in a Spata7 knockout mouse model of Leber congenital amaurosis and retinitis pigmentosa. - Zhong, H; Eblimit, A; Moayedi, Y; Boye, S L; Chiodo, V A; Chen, Y; Li, Y; Nichols, R M; Hauswirth, W W; Chen, R; Mardon, G (Gene Ther, 2015)
Loss of SPATA7 function causes the pathogenesis of Leber congenital amaurosis and retinitis pigmentosa. Spata7 knockout mice mimic human SPATA7-related retinal disease with apparent photoreceptor degeneration observed as early as postnatal day 15 (P15). To test the efficacy of adeno-associated virus (AAV)-mediated gene therapy for rescue of photoreceptor survival and function in Spata7 mutant mice, we employed the AAV8(Y733F) vector carrying hGRK1-driven full-length FLAG-tagged Spata7 cDNA to target both rod and cone photoreceptors. Following subretinal injection of this vector, FLAG-tagged SPATA7 was found to colocalize with endogenous SPATA7 in wild-type mice. In Spata7 mutant mice initially treated at P15, we observed improvement of photoresponse, photoreceptor ultrastructure and significant alleviation of photoreceptor degeneration. Furthermore, we performed treatments at P28 and P56 and found that all treatments (P15-P56) can ameliorate rod and cone loss in the long term (1 year); however, none efficiently protect photoreceptors from degeneration by 86 weeks of age as only a small amount of treated photoreceptors can survive to this time. This study demonstrates long-term improvement of photoreceptor function by AAV8(Y733F)-introduced Spata7 expression in a mouse model as potential treatment of the human disease, but also suggests that treated mutant photoreceptors still undergo progressive degeneration.
Keywords: Animals; Dependovirus; Disease Models, Animal; DNA-Binding Proteins; Genetic Therapy; Genetic Vectors; Leber Congenital Amaurosis; Mice, Inbred C57BL; Mice, Knockout; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Retinitis Pigmentosa

Adult presentation of X-linked Conradi-Hünermann-Happle syndrome. - Posey, Jennifer E; Burrage, Lindsay C; Campeau, Philippe M; Lu, James T; Eble, Tanya N; Kratz, Lisa; Schlesinger, Alan E; Gibbs, Richard A; Lee, Brendan H; Nagamani, Sandesh C S (Am J Med Genet A, 2015)
Conradi-Hünermann-Happle syndrome, or X-linked dominant chondrodysplasia punctata type 2 (CDPX2), is a genodermatosis caused by mutations in EBP. While typically lethal in males, females with CDPX2 generally manifest by infancy or childhood with variable features including congenital ichthyosiform erythroderma, chondrodysplasia punctata, asymmetric shortening of the long bones, and cataracts. We present a 36-year-old female with short stature, rhizomelic and asymmetric limb shortening, severe scoliosis, a sectorial cataract, and no family history of CDPX2. Whole exome sequencing (WES) revealed a p.Arg63del mutation in EBP, and biochemical studies confirmed a diagnosis of CDPX2. Short stature in combination with ichthyosis or alopecia, cataracts, and limb shortening in an adult should prompt consideration of a diagnosis of CDPX2. As in many genetic syndromes, the hallmark features of CDPX2 in pediatric patients are not readily identifiable in adults. This demonstrates the utility of WES as a diagnostic tool in the evaluation of adults with genetic disorders.
Keywords: Adult; Alopecia; Base Sequence; Black or African American; Cataract; Chondrodysplasia Punctata; Dwarfism; Exome; Female; Genes, X-Linked; Humans; Molecular Sequence Data; Sequence Deletion; Steroid Isomerases

Alu-mediated diverse and complex pathogenic copy-number variants within human chromosome 17 at p13.3. - Gu, Shen; Yuan, Bo; Campbell, Ian M; Beck, Christine R; Carvalho, Claudia M B; Nagamani, Sandesh C S; Erez, Ayelet; Patel, Ankita; Bacino, Carlos A; Shaw, Chad A; Stankiewicz, Paweł; Cheung, Sau Wai; et al. (Hum Mol Genet, 2015)
Alu repetitive elements are known to be major contributors to genome instability by generating Alu-mediated copy-number variants (CNVs). Most of the reported Alu-mediated CNVs are simple deletions and duplications, and the mechanism underlying Alu-Alu-mediated rearrangement has been attributed to non-allelic homologous recombination (NAHR). Chromosome 17 at the p13.3 genomic region lacks extensive low-copy repeat architecture; however, it is highly enriched for Alu repetitive elements, with a fraction of 30% of total sequence annotated in the human reference genome, compared with the 10% genome-wide and 18% on chromosome 17. We conducted mechanistic studies of the 17p13.3 CNVs by performing high-density oligonucleotide array comparative genomic hybridization, specifically interrogating the 17p13.3 region with ∼150 bp per probe density; CNV breakpoint junctions were mapped to nucleotide resolution by polymerase chain reaction and Sanger sequencing. Studied rearrangements include 5 interstitial deletions, 14 tandem duplications, 7 terminal deletions and 13 complex genomic rearrangements (CGRs). Within the 17p13.3 region, Alu-Alu-mediated rearrangements were identified in 80% of the interstitial deletions, 46% of the tandem duplications and 50% of the CGRs, indicating that this mechanism was a major contributor for formation of breakpoint junctions. Our studies suggest that Alu repetitive elements facilitate formation of non-recurrent CNVs, CGRs and other structural aberrations of chromosome 17 at p13.3. The common observation of Alu-mediated rearrangement in CGRs and breakpoint junction sequences analysis further demonstrates that this type of mechanism is unlikely attributed to NAHR, but rather may be due to a recombination-coupled DNA replicative repair process.
Keywords: Alleles; Alu Elements; Base Sequence; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Genome, Human; Genomic Instability; Genomics; Homologous Recombination; Humans; Male; Molecular Sequence Data; Segmental Duplications, Genomic; Sequence Deletion

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; Black or African American; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; White People

Autosomal-Dominant Multiple Pterygium Syndrome Is Caused by Mutations in MYH3. - Chong, Jessica X; Burrage, Lindsay C; Beck, Anita E; Marvin, Colby T; McMillin, Margaret J; Shively, Kathryn M; Harrell, Tanya M; Buckingham, Kati J; Bacino, Carlos A; Jain, Mahim; Alanay, Yasemin; Berry, Susan A; et al. (Am J Hum Genet, 2015)
Multiple pterygium syndrome (MPS) is a phenotypically and genetically heterogeneous group of rare Mendelian conditions characterized by multiple pterygia, scoliosis, and congenital contractures of the limbs. MPS typically segregates as an autosomal-recessive disorder, but rare instances of autosomal-dominant transmission have been reported. Whereas several mutations causing recessive MPS have been identified, the genetic basis of dominant MPS remains unknown. We identified four families affected by dominantly transmitted MPS characterized by pterygia, camptodactyly of the hands, vertebral fusions, and scoliosis. Exome sequencing identified predicted protein-altering mutations in embryonic myosin heavy chain (MYH3) in three families. MYH3 mutations underlie distal arthrogryposis types 1, 2A, and 2B, but all mutations reported to date occur in the head and neck domains. In contrast, two of the mutations found to cause MPS in this study occurred in the tail domain. The phenotypic overlap among persons with MPS, coupled with physical findings distinct from other conditions caused by mutations in MYH3, suggests that the developmental mechanism underlying MPS differs from that of other conditions and/or that certain functions of embryonic myosin might be perturbed by disruption of specific residues and/or domains. Moreover, the vertebral fusions in persons with MPS, coupled with evidence of MYH3 expression in bone, suggest that embryonic myosin plays a role in skeletal development.
Keywords: Arthrogryposis; Cytoskeletal Proteins; Exome; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Mutation; Myosins; Osteogenesis

Brain Tumor Epidemiology - A Hub within Multidisciplinary Neuro-oncology. Report on the 15th Brain Tumor Epidemiology Consortium (BTEC) Annual Meeting, Vienna, 2014. - Woehrer, Adelheid; Lau, Ching C; Prayer, Daniela; Bauchet, Luc; Rosenfeld, Myrna; Capper, David; Fisher, Paul G; Kool, Marcel; Müller, Martin; Kros, Johan M; Kruchko, Carol; Wiemels, Joseph; et al. (Clin Neuropathol, 2015)
The Brain Tumor Epidemiology Consortium (BTEC) is an open scientific forum, which fosters the development of multi-center, international and inter-disciplinary collaborations. BTEC aims to develop a better understanding of the etiology, outcomes, and prevention of brain tumors (http://epi.grants.cancer.gov/btec/). The 15th annual Brain Tumor Epidemiology Consortium Meeting, hosted by the Austrian Societies of Neuropathology and Neuro-oncology, was held on September 9 - 11, 2014 in Vienna, Austria. The meeting focused on the central role of brain tumor epidemiology within multidisciplinary neuro-oncology. Knowledge of disease incidence, outcomes, as well as risk factors is fundamental to all fields involved in research and treatment of patients with brain tumors; thus, epidemiology constitutes an important link between disciplines, indeed the very hub. This was reflected by the scientific program, which included various sessions linking brain tumor epidemiology with clinical neuro-oncology, tissue-based research, and cancer registration. Renowned experts from Europe and the United States contributed their personal perspectives stimulating further group discussions. Several concrete action plans evolved for the group to move forward until next year's meeting, which will be held at the Mayo Clinic at Rochester, MN, USA.
Keywords: Austria; Brain Neoplasms; Humans

A comprehensive 1,000 Genomes-based genome-wide association meta-analysis of coronary artery disease. - Nikpay, Majid; Goel, Anuj; Won, Hong-Hee; Hall, Leanne M; Willenborg, Christina; Kanoni, Stavroula; Saleheen, Danish; Kyriakou, Theodosios; Nelson, Christopher P; Hopewell, Jemma C; Webb, Thomas R; Zeng, Lingyao; et al. (Nat Genet, 2015)
Existing knowledge of genetic variants affecting risk of coronary artery disease (CAD) is largely based on genome-wide association study (GWAS) analysis of common SNPs. Leveraging phased haplotypes from the 1000 Genomes Project, we report a GWAS meta-analysis of ∼185,000 CAD cases and controls, interrogating 6.7 million common (minor allele frequency (MAF) > 0.05) and 2.7 million low-frequency (0.005 < MAF < 0.05) variants. In addition to confirming most known CAD-associated loci, we identified ten new loci (eight additive and two recessive) that contain candidate causal genes newly implicating biological processes in vessel walls. We observed intralocus allelic heterogeneity but little evidence of low-frequency variants with larger effects and no evidence of synthetic association. Our analysis provides a comprehensive survey of the fine genetic architecture of CAD, showing that genetic susceptibility to this common disease is largely determined by common SNPs of small effect size.
Keywords: Coronary Artery Disease; Genome, Human; Genome-Wide Association Study; Humans; Phenotype

A comprehensive assessment of somatic mutation detection in cancer using whole-genome sequencing. - Alioto, Tyler S; Buchhalter, Ivo; Derdak, Sophia; Hutter, Barbara; Eldridge, Matthew D; Hovig, Eivind; Heisler, Lawrence E; Beck, Timothy A; Simpson, Jared T; Tonon, Laurie; Sertier, Anne-Sophie; Patch, Ann-Marie; et al. (Nat Commun, 2015)
As whole-genome sequencing for cancer genome analysis becomes a clinical tool, a full understanding of the variables affecting sequencing analysis output is required. Here using tumour-normal sample pairs from two different types of cancer, chronic lymphocytic leukaemia and medulloblastoma, we conduct a benchmarking exercise within the context of the International Cancer Genome Consortium. We compare sequencing methods, analysis pipelines and validation methods. We show that using PCR-free methods and increasing sequencing depth to ∼ 100 × shows benefits, as long as the tumour:control coverage ratio remains balanced. We observe widely varying mutation call rates and low concordance among analysis pipelines, reflecting the artefact-prone nature of the raw data and lack of standards for dealing with the artefacts. However, we show that, using the benchmark mutation set we have created, many issues are in fact easy to remedy and have an immediate positive impact on mutation detection accuracy.
Keywords: Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Leukemia, Lymphoid; Medulloblastoma; Mutation

Convergent evolution of the genomes of marine mammals. - Foote, Andrew D; Liu, Yue; Thomas, Gregg W C; Vinar, Tomas; Alföldi, Jessica; Deng, Jixin; Dugan, Shannon; van Elk, Cornelis E; Hunter, Margaret E; Joshi, Vandita; Khan, Ziad; Kovar, Christie; et al. (Nat Genet, 2015)
Marine mammals from different mammalian orders share several phenotypic traits adapted to the aquatic environment and therefore represent a classic example of convergent evolution. To investigate convergent evolution at the genomic level, we sequenced and performed de novo assembly of the genomes of three species of marine mammals (the killer whale, walrus and manatee) from three mammalian orders that share independently evolved phenotypic adaptations to a marine existence. Our comparative genomic analyses found that convergent amino acid substitutions were widespread throughout the genome and that a subset of these substitutions were in genes evolving under positive selection and putatively associated with a marine phenotype. However, we found higher levels of convergent amino acid substitutions in a control set of terrestrial sister taxa to the marine mammals. Our results suggest that, whereas convergent molecular evolution is relatively common, adaptive molecular convergence linked to phenotypic convergence is comparatively rare.
Keywords: Adaptation, Physiological; Amino Acid Substitution; Animals; Evolution, Molecular; Genome; Humans; Mammals; Phenotype; Phylogeny; Selection, Genetic

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

Ectodysplasin signalling genes and phenotypic evolution in sculpins (Cottus). - Cheng, Jie; Fritz J Sedlazeck; Altmüller, Janine; Nolte, Arne W (Proc Biol Sci, 2015)
Despite their deeply conserved function among vertebrates, ectodysplasin (Eda) signalling genes are involved in microevolutionary change in humans and sticklebacks. If such a dual role is common, Eda signalling genes constitute hotspots for morphological evolution. Variation in sculpin (Cottus) skin prickling and body shape resembles patterns caused by variation in Eda signalling in sticklebacks. We mapped Eda signalling genes and performed quantitative trait locus mapping in crosses between Cottus rhenanus and Cottus perifretum. A genomic region containing the Eda receptor (Edar) was strongly associated with prickling and contributed to shape. The expression of Edar in developing prickles and skeletal elements in Cottus was confirmed by in situ hybridization. Coding sequence changes between Edar alleles in C. rhenanus and C. perifretum exceeded sequence differentiation in other vertebrates. However, it is likely that additional genetic elements besides coding changes affect the phenotypic variation. Although the phenotype in a natural hybrid lineage between C. rhenanus and C. perifretum resembles C. perifretum, the respective coding Edar alleles are not fully fixed (88.6%). Hence, our results support an involvement of Eda signalling in microevolutionary changes, but imply that the Edar gene is affected by multiple evolutionary processes that vary among freshwater sculpins.
Keywords: Animals; Biological Evolution; Body Patterning; Ectodysplasins; Epidermis; Genetics, Population; Hybridization, Genetic; Perciformes; Phenotype; Receptors, Ectodysplasin; Signal Transduction

Epigenome-wide association study (EWAS) of BMI, BMI change and waist circumference in African American adults identifies multiple replicated loci. - Demerath, Ellen W; Guan, Weihua; Grove, Megan L; Aslibekyan, Stella; Mendelson, Michael; Zhou, Yi-Hui; Hedman, Åsa K; Sandling, Johanna K; Li, Li-An; Irvin, Marguerite R; Zhi, Degui; Deloukas, Panos; et al. (Hum Mol Genet, 2015)
Obesity is an important component of the pathophysiology of chronic diseases. Identifying epigenetic modifications associated with elevated adiposity, including DNA methylation variation, may point to genomic pathways that are dysregulated in numerous conditions. The Illumina 450K Bead Chip array was used to assay DNA methylation in leukocyte DNA obtained from 2097 African American adults in the Atherosclerosis Risk in Communities (ARIC) study. Mixed-effects regression models were used to test the association of methylation beta value with concurrent body mass index (BMI) and waist circumference (WC), and BMI change, adjusting for batch effects and potential confounders. Replication using whole-blood DNA from 2377 White adults in the Framingham Heart Study and CD4+ T cell DNA from 991 Whites in the Genetics of Lipid Lowering Drugs and Diet Network Study was followed by testing using adipose tissue DNA from 648 women in the Multiple Tissue Human Expression Resource cohort. Seventy-six BMI-related probes, 164 WC-related probes and 8 BMI change-related probes passed the threshold for significance in ARIC (P < 1 × 10(-7); Bonferroni), including probes in the recently reported HIF3A, CPT1A and ABCG1 regions. Replication using blood DNA was achieved for 37 BMI probes and 1 additional WC probe. Sixteen of these also replicated in adipose tissue, including 15 novel methylation findings near genes involved in lipid metabolism, immune response/cytokine signaling and other diverse pathways, including LGALS3BP, KDM2B, PBX1 and BBS2, among others. Adiposity traits are associated with DNA methylation at numerous CpG sites that replicate across studies despite variation in tissue type, ethnicity and analytic approaches.
Keywords: Aged; Atherosclerosis; Black or African American; Body Mass Index; DNA Methylation; Epigenesis, Genetic; Female; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Metabolic Networks and Pathways; Middle Aged; Obesity; Waist Circumference; White People

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoprotein A-V; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Fine mapping the region reveals a common intronic insertion associated to HDL-C. - van Leeuwen, Elisabeth M; Huffman, Jennifer E; Bis, Joshua C; Isaacs, Aaron; Mulder, Monique; Aniko Sabo; Smith, Albert V; Demissie, Serkalem; Manichaikul, Ani; Brody, Jennifer A; Feitosa, Mary F; Duan, Qing; et al. (NPJ Aging Mech Dis, 2015)
BACKGROUND: Individuals with exceptional longevity and their offspring have significantly larger high-density lipoprotein concentrations (HDL-C) particle sizes due to the increased homozygosity for the I405V variant in the cholesteryl ester transfer protein ( gene. In this study, we investigate the association of and HDL-C further to identify novel, independent variants associated with HDL-C in humans. METHODS: We performed a meta-analysis of HDL-C within the region using 59,432 individuals imputed with 1000 Genomes data. We performed replication in an independent sample of 47,866 individuals and validation was done by Sanger sequencing. RESULTS: The meta-analysis of HDL-C within the region identified five independent variants, including an exonic variant and a common intronic insertion. We replicated these 5 variants significantly in an independent sample of 47,866 individuals. Sanger sequencing of the insertion within a single family confirmed segregation of this variant. The strongest reported association between HDL-C and variants, was rs3764261; however, after conditioning on the five novel variants we identified the support for rs3764261 was highly reduced (=3.179 mg/dl ( value=5.25×10), =0.859 mg/dl ( value=9.51×10)), and this finding suggests that these five novel variants may partly explain the association of with HDL-C. Indeed, three of the five novel variants (rs34065661, rs5817082, rs7499892) are independent of rs3764261. CONCLUSIONS: The causal variants in that account for the association with HDL-C remain unknown. We used studies imputed to the 1000 Genomes reference panel for fine mapping of the region. We identified and validated five variants within this region that may partly account for the association of the known variant (rs3764261), as well as other sources of genetic contribution to HDL-C.

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic fine mapping and genomic annotation defines causal mechanisms at type 2 diabetes susceptibility loci. - Gaulton, Kyle J; Ferreira, Teresa; Lee, Yeji; Raimondo, Anne; Mägi, Reedik; Reschen, Michael E; Mahajan, Anubha; Locke, Adam; Rayner, N William; Robertson, Neil; Scott, Robert A; Prokopenko, Inga; et al. (Nat Genet, 2015)
We performed fine mapping of 39 established type 2 diabetes (T2D) loci in 27,206 cases and 57,574 controls of European ancestry. We identified 49 distinct association signals at these loci, including five mapping in or near KCNQ1. 'Credible sets' of the variants most likely to drive each distinct signal mapped predominantly to noncoding sequence, implying that association with T2D is mediated through gene regulation. Credible set variants were enriched for overlap with FOXA2 chromatin immunoprecipitation binding sites in human islet and liver cells, including at MTNR1B, where fine mapping implicated rs10830963 as driving T2D association. We confirmed that the T2D risk allele for this SNP increases FOXA2-bound enhancer activity in islet- and liver-derived cells. We observed allele-specific differences in NEUROD1 binding in islet-derived cells, consistent with evidence that the T2D risk allele increases islet MTNR1B expression. Our study demonstrates how integration of genetic and genomic information can define molecular mechanisms through which variants underlying association signals exert their effects on disease.
Keywords: Binding Sites; Case-Control Studies; Chromatin Immunoprecipitation; Chromosome Mapping; Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Hepatocyte Nuclear Factor 3-beta; Humans; Islets of Langerhans; Liver; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Receptor, Melatonin, MT2

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

The genomes of two key bumblebee species with primitive eusocial organization. - Sadd, Ben M; Barribeau, Seth M; Bloch, Guy; de Graaf, Dirk C; Dearden, Peter; Elsik, Christine G; Gadau, Jürgen; Grimmelikhuijzen, Cornelis J P; Hasselmann, Martin; Lozier, Jeffrey D; Robertson, Hugh M; Smagghe, Guy; et al. (Genome Biol, 2015)
BACKGROUND: The shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats. RESULTS: We report the high quality draft genome sequences of Bombus terrestris and Bombus impatiens, two ecologically dominant bumblebees and widely utilized study species. Comparing these new genomes to those of the highly eusocial honeybee Apis mellifera and other Hymenoptera, we identify deeply conserved similarities, as well as novelties key to the biology of these organisms. Some honeybee genome features thought to underpin advanced eusociality are also present in bumblebees, indicating an earlier evolution in the bee lineage. Xenobiotic detoxification and immune genes are similarly depauperate in bumblebees and honeybees, and multiple categories of genes linked to social organization, including development and behavior, show high conservation. Key differences identified include a bias in bumblebee chemoreception towards gustation from olfaction, and striking differences in microRNAs, potentially responsible for gene regulation underlying social and other traits. CONCLUSIONS: These two bumblebee genomes provide a foundation for post-genomic research on these key pollinators and insect societies. Overall, gene repertoires suggest that the route to advanced eusociality in bees was mediated by many small changes in many genes and processes, and not by notable expansion or depauperation.
Keywords: Animals; Bee Venoms; Bees; Behavior, Animal; Chemoreceptor Cells; Chromosome Mapping; Databases, Genetic; Evolution, Molecular; Female; Gene Expression Regulation; Gene Rearrangement; Genes, Insect; Genomics; Interspersed Repetitive Sequences; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Selenoproteins; Sequence Analysis, DNA; Social Behavior; Species Specificity; Synteny

Genomic profiling of Sézary syndrome identifies alterations of key T cell signaling and differentiation genes. - Wang, Linghua; Ni, Xiao; Covington, Kyle R; Yang, Betty Y; Shiu, Jessica; Zhang, Xiang; Xi, Liu; Meng, Qingchang; Langridge, Timothy; Drummond, Jennifer; Donehower, Lawrence A; Doddapaneni, Harshavardhan; et al. (Nat Genet, 2015)
Sézary syndrome is a rare leukemic form of cutaneous T cell lymphoma characterized by generalized redness, scaling, itching and increased numbers of circulating atypical T lymphocytes. It is rarely curable, with poor prognosis. Here we present a multiplatform genomic analysis of 37 patients with Sézary syndrome that implicates dysregulation of cell cycle checkpoint and T cell signaling. Frequent somatic alterations were identified in TP53, CARD11, CCR4, PLCG1, CDKN2A, ARID1A, RPS6KA1 and ZEB1. Activating CCR4 and CARD11 mutations were detected in nearly one-third of patients. ZEB1, encoding a transcription repressor essential for T cell differentiation, was deleted in over one-half of patients. IL32 and IL2RG were overexpressed in nearly all cases. Our results demonstrate profound disruption of key signaling pathways in Sézary syndrome and suggest potential targets for new therapies.
Keywords: Case-Control Studies; Cell Differentiation; Exome; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genetic Drift; Genomics; High-Throughput Nucleotide Sequencing; Humans; Lymphocyte Activation; Mutation; Prognosis; Sezary Syndrome; Signal Transduction; Skin Neoplasms; Survival Rate; T-Lymphocytes

Hemichordate genomes and deuterostome origins. - Simakov, Oleg; Kawashima, Takeshi; Marlétaz, Ferdinand; Jenkins, Jerry; Koyanagi, Ryo; Mitros, Therese; Hisata, Kanako; Bredeson, Jessen; Shoguchi, Eiichi; Gyoja, Fuki; Yue, Jia-Xing; Chen, Yi-Chih; et al. (Nature, 2015)
Acorn worms, also known as enteropneust (literally, 'gut-breathing') hemichordates, are marine invertebrates that share features with echinoderms and chordates. Together, these three phyla comprise the deuterostomes. Here we report the draft genome sequences of two acorn worms, Saccoglossus kowalevskii and Ptychodera flava. By comparing them with diverse bilaterian genomes, we identify shared traits that were probably inherited from the last common deuterostome ancestor, and then explore evolutionary trajectories leading from this ancestor to hemichordates, echinoderms and chordates. The hemichordate genomes exhibit extensive conserved synteny with amphioxus and other bilaterians, and deeply conserved non-coding sequences that are candidates for conserved gene-regulatory elements. Notably, hemichordates possess a deuterostome-specific genomic cluster of four ordered transcription factor genes, the expression of which is associated with the development of pharyngeal 'gill' slits, the foremost morphological innovation of early deuterostomes, and is probably central to their filter-feeding lifestyle. Comparative analysis reveals numerous deuterostome-specific gene novelties, including genes found in deuterostomes and marine microbes, but not other animals. The putative functions of these genes can be linked to physiological, metabolic and developmental specializations of the filter-feeding ancestor.
Keywords: Animals; Chordata, Nonvertebrate; Conserved Sequence; Echinodermata; Evolution, Molecular; Genome; Multigene Family; Phylogeny; Signal Transduction; Synteny; Transforming Growth Factor beta

Human adipose tissue as a reservoir for memory CD4+ T cells and HIV. - Couturier, Jacob; Suliburk, James W; Brown, Jeremy M; Luke, David J; Agarwal, Neeti; Yu, Xiaoying; Nguyen, Chi; Iyer, Dinakar; Kozinetz, Claudia A; Overbeek, Paul A; Metzker, Michael L; Balasubramanyam, Ashok; et al. (AIDS, 2015)
OBJECTIVE: The objective of this study is to determine whether adipose tissue functions as a reservoir for HIV-1. DESIGN: We examined memory CD4(+) T cells and HIV DNA in adipose tissue-stromal vascular fraction (AT-SVF) of five patients [four antiretroviral therapy (ART)-treated and one untreated]. To determine whether adipocytes stimulate CD4(+) T cells and regulate HIV production, primary human adipose cells were cocultured with HIV-infected CD4(+) T cells. METHODS: AT-SVF T cells were studied by flow cytometry, and AT-SVF HIV DNA (Gag and Env) was examined by nested PCR and sequence analyses. CD4(+) T-cell activation and HIV production were measured by flow cytometry and ELISA. RESULTS: AT-SVF CD3(+) T cells were activated (>60% CD69(+)) memory CD4(+) and CD8(+) T cells in uninfected and HIV-infected persons, but the AT-SVF CD4(+)/CD8(+) ratio was lower in HIV patients. HIV DNA (Gag and Env) was detected in AT-SVF of all five patients examined by nested PCR, comparably to other tissues [peripheral blood mononuclear cell (PBMC), lymph node or thymus]. In coculture experiments, adipocytes increased CD4(+) T-cell activation and HIV production approximately two to three-fold in synergy with gamma-chain cytokines interleukin (IL)-2, IL7 or IL15. These effects were mitigated by neutralizing antibodies against IL6 and integrin-α1β1. Adipocytes also enhanced T-cell viability. CONCLUSION: Adipose tissues of ART-treated patients harbour activated memory CD4(+) T cells and HIV DNA. Adipocytes promote CD4(+) T-cell activation and HIV production in concert with intrinsic adipose factors. Adipose tissue may be an important reservoir for HIV.
Keywords: Adipocytes; Adipose Tissue; CD4-Positive T-Lymphocytes; Cells, Cultured; Coculture Techniques; DNA, Viral; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; HIV; Humans; Lymphocyte Activation; T-Lymphocyte Subsets

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.
Keywords: Adult; Age Factors; Aging; BRCA1 Protein; Breast Neoplasms; DNA Repair; Female; Gene Regulatory Networks; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genomics; Genotype; Humans; Hypothalamus; Menopause; Middle Aged; Models, Genetic; Phenotype; Reproduction; Signal Transduction

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: Black People; Blood Glucose; Diabetes Mellitus, Type 2; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; White People

A massive expansion of effector genes underlies gall-formation in the wheat pest Mayetiola destructor. - Zhao, Chaoyang; Escalante, Lucio Navarro; Chen, Hang; Benatti, Thiago R; Qu, Jiaxin; Chellapilla, Sanjay; Waterhouse, Robert M; Wheeler, David; Andersson, Martin N; Bao, Riyue; Batterton, Matthew; Behura, Susanta K; et al. (Curr Biol, 2015)
Gall-forming arthropods are highly specialized herbivores that, in combination with their hosts, produce extended phenotypes with unique morphologies [1]. Many are economically important, and others have improved our understanding of ecology and adaptive radiation [2]. However, the mechanisms that these arthropods use to induce plant galls are poorly understood. We sequenced the genome of the Hessian fly (Mayetiola destructor; Diptera: Cecidomyiidae), a plant parasitic gall midge and a pest of wheat (Triticum spp.), with the aim of identifying genic modifications that contribute to its plant-parasitic lifestyle. Among several adaptive modifications, we discovered an expansive reservoir of potential effector proteins. Nearly 5% of the 20,163 predicted gene models matched putative effector gene transcripts present in the M. destructor larval salivary gland. Another 466 putative effectors were discovered among the genes that have no sequence similarities in other organisms. The largest known arthropod gene family (family SSGP-71) was also discovered within the effector reservoir. SSGP-71 proteins lack sequence homologies to other proteins, but their structures resemble both ubiquitin E3 ligases in plants and E3-ligase-mimicking effectors in plant pathogenic bacteria. SSGP-71 proteins and wheat Skp proteins interact in vivo. Mutations in different SSGP-71 genes avoid the effector-triggered immunity that is directed by the wheat resistance genes H6 and H9. Results point to effectors as the agents responsible for arthropod-induced plant gall formation.
Keywords: Adaptation, Biological; Amino Acid Sequence; Animals; Base Sequence; Chromosomes; Diptera; Larva; Models, Genetic; Molecular Sequence Data; Multigene Family; Phylogeny; Plant Tumors; Sequence Analysis, DNA; Sequence Homology; Sexual Behavior, Animal; Triticum; Two-Hybrid System Techniques; Ubiquitin-Protein Ligases

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Racial Groups; Stroke; White Matter

Next-generation sequencing and novel variant determination in a cohort of 92 familial exudative vitreoretinopathy patients. - Salvo, Jason; Lyubasyuk, Vera; Xu, Mingchu; Wang, Hui; Wang, Feng; Nguyen, Duy; Wang, Keqing; Luo, Hongrong; Wen, Cindy; Shi, Catherine; Lin, Danni; Zhang, Kang; et al. (Invest Ophthalmol Vis Sci, 2015)
PURPOSE: Familial exudative vitreoretinopathy (FEVR) is a developmental disease that can cause visual impairment and retinal detachment at a young age. Four genes involved in the Wnt signaling pathway were previously linked to this disease: NDP, FDZ4, LRP5, and TSPAN12. Identification of novel disease-causing alleles allows for a deeper understanding of the disease, better molecular diagnosis, and improved treatment. METHODS: Sequencing libraries from 92 FEVR patients were generated using a custom capture panel to enrich for 163 known retinal disease-causing genes in humans. Samples were processed using next generation sequencing (NGS) techniques followed by data analysis to identify and classify single nucleotide variants and small insertions and deletions. Sanger validation and segregation testing were used to verify suspected variants. RESULTS: Of the cohort of 92, 45 patients were potentially solved (48.9%). Solved cases resulted from the determination of 49 unique mutations, 41 of which are novel. Of the novel variants discovered, 13 were highly likely to cause FEVR due to the nature of these variants (frameshifting indels, splicing mutations, and nonsense variants types). To our knowledge, this is the largest study of a FEVR cohort using NGS. CONCLUSIONS: We were able to determine probable disease-causing variants in a large number of FEVR patients, the majority of which were novel. Knowledge of these variants will help to further characterize and diagnose FEVR.
Keywords: Cohort Studies; DNA Mutational Analysis; DNA-Binding Proteins; Eye Diseases, Hereditary; Eye Proteins; Familial Exudative Vitreoretinopathies; Female; Frizzled Receptors; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Low Density Lipoprotein Receptor-Related Protein-5; Male; Mutation; Nerve Tissue Proteins; Retinal Diseases; Sequence Analysis, DNA; Tetraspanins; Transcription Factors

Recurrent DGCR8, DROSHA, and SIX homeodomain mutations in favorable histology Wilms tumors. - Walz, Amy L; Ooms, Ariadne; Gadd, Samantha; Gerhard, Daniela S; Smith, Malcolm A; Guidry Auvil, Jaime M; Meerzaman, Daoud; Chen, Qing-Rong; Hsu, Chih Hao; Yan, Chunhua; Nguyen, Cu; Hu, Ying; et al. (Cancer Cell, 2015)
We report the most common single-nucleotide substitution/deletion mutations in favorable histology Wilms tumors (FHWTs) to occur within SIX1/2 (7% of 534 tumors) and microRNA processing genes (miRNAPGs) DGCR8 and DROSHA (15% of 534 tumors). Comprehensive analysis of 77 FHWTs indicates that tumors with SIX1/2 and/or miRNAPG mutations show a pre-induction metanephric mesenchyme gene expression pattern and are significantly associated with both perilobar nephrogenic rests and 11p15 imprinting aberrations. Significantly decreased expression of mature Let-7a and the miR-200 family (responsible for mesenchymal-to-epithelial transition) in miRNAPG mutant tumors is associated with an undifferentiated blastemal histology. The combination of SIX and miRNAPG mutations in the same tumor is associated with evidence of RAS activation and a higher rate of relapse and death.
Keywords: Gene Expression Regulation, Neoplastic; Homeodomain Proteins; Humans; Loss of Heterozygosity; MicroRNAs; Mutation; Neoplasm Recurrence, Local; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Ribonuclease III; RNA-Binding Proteins; Wilms Tumor

Recurrent internal tandem duplications of BCOR in clear cell sarcoma of the kidney. - Roy, Angshumoy; Kumar, Vijetha; Zorman, Barry; Fang, Erica; Haines, Katherine M; Doddapaneni, Harshavardhan; Hampton, Oliver A; White, Simon; Bavle, Abhishek A; Patel, Nimesh R; Eldin, Karen W; John Hicks, M; et al. (Nat Commun, 2015)
The X-linked BCL-6 co-repressor (BCOR) gene encodes a key constituent of a variant polycomb repressive complex (PRC) that is mutated or translocated in human cancers. Here we report on the identification of somatic internal tandem duplications (ITDs) clustering in the C terminus of BCOR in 23 of 27 (85%) pediatric clear cell sarcomas of the kidney (CCSK) from two independent cohorts. We profile CCSK tumours using a combination of whole-exome, transcriptome and targeted sequencing. Identical ITD mutations are found in primary and relapsed tumour pairs but not in adjacent normal kidney or blood. Mutant BCOR transcripts and proteins are markedly upregulated in ITD-positive tumours. Transcriptome analysis of ITD-positive CCSKs reveals enrichment for PRC2-regulated genes and similarity to undifferentiated sarcomas harbouring BCOR-CCNB3 fusions. The discovery of recurrent BCOR ITDs defines a major oncogenic event in this childhood sarcoma with significant implications for diagnostic and therapeutic approaches to this tumour.
Keywords: Case-Control Studies; Child, Preschool; Female; Gene Duplication; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Humans; Immunoblotting; Immunohistochemistry; Infant; Kidney Neoplasms; Male; Mutation; Neoplasm Recurrence, Local; Proto-Oncogene Proteins; Repressor Proteins; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Sarcoma, Clear Cell; Sequence Analysis, DNA; Sequence Analysis, RNA; Tandem Repeat Sequences

Rise and fall of subclones from diagnosis to relapse in pediatric B-acute lymphoblastic leukaemia. - Ma, Xiaotu; Edmonson, Michael; Yergeau, Donald; Muzny, Donna M; Hampton, Oliver A; Rusch, Michael; Song, Guangchun; Easton, John; Harvey, Richard C; Wheeler, David A; Ma, Jing; Doddapaneni, Harshavardhan; et al. (Nat Commun, 2015)
There is incomplete understanding of genetic heterogeneity and clonal evolution during cancer progression. Here we use deep whole-exome sequencing to describe the clonal architecture and evolution of 20 pediatric B-acute lymphoblastic leukaemias from diagnosis to relapse. We show that clonal diversity is comparable at diagnosis and relapse and clonal survival from diagnosis to relapse is not associated with mutation burden. Six pathways were frequently mutated, with NT5C2, CREBBP, WHSC1, TP53, USH2A, NRAS and IKZF1 mutations enriched at relapse. Half of the leukaemias had multiple subclonal mutations in a pathway or gene at diagnosis, but mostly with only one, usually minor clone, surviving therapy to acquire additional mutations and become the relapse founder clone. Relapse-specific mutations in NT5C2 were found in nine cases, with mutations in four cases being in descendants of the relapse founder clone. These results provide important insights into the genetic basis of treatment failure in ALL and have implications for the early detection of mutations driving relapse.
Keywords: 5'-Nucleotidase; Child; Clonal Evolution; Clone Cells; CREB-Binding Protein; Disease Progression; DNA Copy Number Variations; Exome; Extracellular Matrix Proteins; Female; GTP Phosphohydrolases; Histone-Lysine N-Methyltransferase; Humans; Ikaros Transcription Factor; Male; Membrane Proteins; Mutation; Neoplasm Recurrence, Local; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Repressor Proteins; Tumor Suppressor Protein p53

Spata7 is a retinal ciliopathy gene critical for correct RPGRIP1 localization and protein trafficking in the retina. - Eblimit, Aiden; Nguyen, Thanh-Minh T; Chen, Yiyun; Esteve-Rudd, Julian; Zhong, Hua; Letteboer, Stef; van Reeuwijk, Jeroen; Simons, David L; Ding, Qian; Wu, Ka Man; Li, Yumei; Van Beersum, Sylvia; et al. (Hum Mol Genet, 2015)
Leber congenital amaurosis (LCA) and juvenile retinitis pigmentosa (RP) are severe hereditary diseases that causes visual impairment in infants and children. SPATA7 has recently been identified as the LCA3 and juvenile RP gene in humans, whose function in the retina remains elusive. Here, we show that SPATA7 localizes at the primary cilium of cells and at the connecting cilium (CC) of photoreceptor cells, indicating that SPATA7 is a ciliary protein. In addition, SPATA7 directly interacts with the retinitis pigmentosa GTPase regulator interacting protein 1 (RPGRIP1), a key connecting cilium protein that has also been linked to LCA. In the retina of Spata7 null mutant mice, a substantial reduction of RPGRIP1 levels at the CC of photoreceptor cells is observed, suggesting that SPATA7 is required for the stable assembly and localization of the ciliary RPGRIP1 protein complex. Furthermore, our results pinpoint a role of this complex in protein trafficking across the CC to the outer segments, as we identified that rhodopsin accumulates in the inner segments and around the nucleus of photoreceptors. This accumulation then likely triggers the apoptosis of rod photoreceptors that was observed. Loss of Spata7 function in mice indeed results in a juvenile RP-like phenotype, characterized by progressive degeneration of photoreceptor cells and a strongly decreased light response. Together, these results indicate that SPATA7 functions as a key member of a retinal ciliopathy-associated protein complex, and that apoptosis of rod photoreceptor cells triggered by protein mislocalization is likely the mechanism of disease progression in LCA3/ juvenile RP patients.
Keywords: Animals; Apoptosis; Cattle; Cytoskeletal Proteins; DNA-Binding Proteins; Gene Deletion; Humans; Mice; Mice, Mutant Strains; Photoreceptor Connecting Cilium; Protein Transport; Proteins; Retinal Cone Photoreceptor Cells; Retinal Rod Photoreceptor Cells; Rhodopsin

Tissue-specific transcriptome sequencing analysis expands the non-human primate reference transcriptome resource (NHPRTR). - Peng, Xinxia; Thierry-Mieg, Jean; Thierry-Mieg, Danielle; Nishida, Andrew; Pipes, Lenore; Bozinoski, Marjan; Thomas, Matthew J; Kelly, Sara; Weiss, Jeffrey M; Raveendran, Muthuswamy; Muzny, Donna; Gibbs, Richard A; et al. (Nucleic Acids Res, 2015)
The non-human primate reference transcriptome resource (NHPRTR, available online at http://nhprtr.org/) aims to generate comprehensive RNA-seq data from a wide variety of non-human primates (NHPs), from lemurs to hominids. In the 2012 Phase I of the NHPRTR project, 19 billion fragments or 3.8 terabases of transcriptome sequences were collected from pools of ∼ 20 tissues in 15 species and subspecies. Here we describe a major expansion of NHPRTR by adding 10.1 billion fragments of tissue-specific RNA-seq data. For this effort, we selected 11 of the original 15 NHP species and subspecies and constructed total RNA libraries for the same ∼ 15 tissues in each. The sequence quality is such that 88% of the reads align to human reference sequences, allowing us to compute the full list of expression abundance across all tissues for each species, using the reads mapped to human genes. This update also includes improved transcript annotations derived from RNA-seq data for rhesus and cynomolgus macaques, two of the most commonly used NHP models and additional RNA-seq data compiled from related projects. Together, these comprehensive reference transcriptomes from multiple primates serve as a valuable community resource for genome annotation, gene dynamics and comparative functional analysis.
Keywords: Animals; Databases, Genetic; Gene Expression Profiling; Internet; Macaca; Molecular Sequence Annotation; Organ Specificity; Primates; Reference Standards; Sequence Alignment; Sequence Analysis, RNA

Whole-exome sequencing points to considerable genetic heterogeneity of cerebral palsy. - McMichael, G; Bainbridge, M N; Haan, E; Corbett, M; Gardner, A; Thompson, S; van Bon, B W M; van Eyk, C L; Broadbent, J; Reynolds, C; O'Callaghan, M E; Nguyen, L S; et al. (Mol Psychiatry, 2015)
Cerebral palsy (CP) is a common, clinically heterogeneous group of disorders affecting movement and posture. Its prevalence has changed little in 50 years and the causes remain largely unknown. The genetic contribution to CP causation has been predicted to be ~2%. We performed whole-exome sequencing of 183 cases with CP including both parents (98 cases) or one parent (67 cases) and 18 singleton cases (no parental DNA). We identified and validated 61 de novo protein-altering variants in 43 out of 98 (44%) case-parent trios. Initial prioritization of variants for causality was by mutation type, whether they were known or predicted to be deleterious and whether they occurred in known disease genes whose clinical spectrum overlaps CP. Further, prioritization used two multidimensional frameworks-the Residual Variation Intolerance Score and the Combined Annotation-dependent Depletion score. Ten de novo mutations in three previously identified disease genes (TUBA1A (n=2), SCN8A (n=1) and KDM5C (n=1)) and in six novel candidate CP genes (AGAP1, JHDM1D, MAST1, NAA35, RFX2 and WIPI2) were predicted to be potentially pathogenic for CP. In addition, we identified four predicted pathogenic, hemizygous variants on chromosome X in two known disease genes, L1CAM and PAK3, and in two novel candidate CP genes, CD99L2 and TENM1. In total, 14% of CP cases, by strict criteria, had a potentially disease-causing gene variant. Half were in novel genes. The genetic heterogeneity highlights the complexity of the genetic contribution to CP. Function and pathway studies are required to establish the causative role of these putative pathogenic CP genes.
Keywords: Adult; Animals; Cerebral Palsy; Cohort Studies; Exome; Female; Gene Library; Genetic Heterogeneity; Genetic Predisposition to Disease; Gestational Age; Humans; Male; Mutation; Parents; Sequence Analysis, DNA

X-linked acrogigantism syndrome: clinical profile and therapeutic responses. - Beckers, Albert; Lodish, Maya Beth; Trivellin, Giampaolo; Rostomyan, Liliya; Lee, Misu; Faucz, Fabio R; Bo Yuan; Choong, Catherine S; Caberg, Jean-Hubert; Verrua, Elisa; Naves, Luciana Ansaneli; Cheetham, Tim D; et al. (Endocr Relat Cancer, 2015)
X-linked acrogigantism (X-LAG) is a new syndrome of pituitary gigantism, caused by microduplications on chromosome Xq26.3, encompassing the gene GPR101, which is highly upregulated in pituitary tumors. We conducted this study to explore the clinical, radiological, and hormonal phenotype and responses to therapy in patients with X-LAG syndrome. The study included 18 patients (13 sporadic) with X-LAG and microduplication of chromosome Xq26.3. All sporadic cases had unique duplications and the inheritance pattern in two families was dominant, with all Xq26.3 duplication carriers being affected. Patients began to grow rapidly as early as 2-3 months of age (median 12 months). At diagnosis (median delay 27 months), patients had a median height and weight standard deviation scores (SDS) of >+3.9 SDS. Apart from the increased overall body size, the children had acromegalic symptoms including acral enlargement and facial coarsening. More than a third of cases had increased appetite. Patients had marked hypersecretion of GH/IGF1 and usually prolactin, due to a pituitary macroadenoma or hyperplasia. Primary neurosurgical control was achieved with extensive anterior pituitary resection, but postoperative hypopituitarism was frequent. Control with somatostatin analogs was not readily achieved despite moderate to high levels of expression of somatostatin receptor subtype-2 in tumor tissue. Postoperative use of adjuvant pegvisomant resulted in control of IGF1 in all five cases where it was employed. X-LAG is a new infant-onset gigantism syndrome that has a severe clinical phenotype leading to challenging disease management.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Chromosomes, Human, X; Female; Gigantism; Humans; Infant; Male; Pituitary Neoplasms; Young Adult

Advances in translational bioinformatics facilitate revealing the landscape of complex disease mechanisms. - Yang, Jack Y; Dunker, A; Liu, Jun S; Qin, Xiang; Arabnia, Hamid R; Yang, William; Niemierko, Andrzej; Chen, Zhongxue; Luo, Zuojie; Wang, Liangjiang; Liu, Yunlong; Xu, Dong; et al. (BMC Bioinformatics, 2014)
Advances of high-throughput technologies have rapidly produced more and more data from DNAs and RNAs to proteins, especially large volumes of genome-scale data. However, connection of the genomic information to cellular functions and biological behaviours relies on the development of effective approaches at higher systems level. In particular, advances in RNA-Seq technology has helped the studies of transcriptome, RNA expressed from the genome, while systems biology on the other hand provides more comprehensive pictures, from which genes and proteins actively interact to lead to cellular behaviours and physiological phenotypes. As biological interactions mediate many biological processes that are essential for cellular function or disease development, it is important to systematically identify genomic information including genetic mutations from GWAS (genome-wide association study), differentially expressed genes, bidirectional promoters, intrinsic disordered proteins (IDP) and protein interactions to gain deep insights into the underlying mechanisms of gene regulations and networks. Furthermore, bidirectional promoters can co-regulate many biological pathways, where the roles of bidirectional promoters can be studied systematically for identifying co-regulating genes at interactive network level. Combining information from different but related studies can ultimately help revealing the landscape of molecular mechanisms underlying complex diseases such as cancer.
Keywords: Computational Biology; Genome, Human; Genomics; Humans; Neoplasms; Phenotype; Transcriptome; Translational Research, Biomedical

Analysis of prostate-specific antigen transcripts in chimpanzees, cynomolgus monkeys, baboons, and African green monkeys. - Mubiru, James N; Yang, Alice S; Olsen, Christian; Nayak, Sudhir; Livi, Carolina B; Dick, Edward J; Owston, Michael; Garcia-Forey, Magdalena; Shade, Robert E; Rogers, Jeffrey (PLoS One, 2014)
The function of prostate-specific antigen (PSA) is to liquefy the semen coagulum so that the released sperm can fuse with the ovum. Fifteen spliced variants of the PSA gene have been reported in humans, but little is known about alternative splicing in nonhuman primates. Positive selection has been reported in sex- and reproductive-related genes from sea urchins to Drosophila to humans; however, there are few studies of adaptive evolution of the PSA gene. Here, using polymerase chain reaction (PCR) product cloning and sequencing, we study PSA transcript variant heterogeneity in the prostates of chimpanzees (Pan troglodytes), cynomolgus monkeys (Macaca fascicularis), baboons (Papio hamadryas anubis), and African green monkeys (Chlorocebus aethiops). Six PSA variants were identified in the chimpanzee prostate, but only two variants were found in cynomolgus monkeys, baboons, and African green monkeys. In the chimpanzee the full-length transcript is expressed at the same magnitude as the transcripts that retain intron 3. We have found previously unidentified splice variants of the PSA gene, some of which might be linked to disease conditions. Selection on the PSA gene was studied in 11 primate species by computational methods using the sequences reported here for African green monkey, cynomolgus monkey, baboon, and chimpanzee and other sequences available in public databases. A codon-based analysis (dN/dS) of the PSA gene identified potential adaptive evolution at five residue sites (Arg45, Lys70, Gln144, Pro189, and Thr203).
Keywords: Alternative Splicing; Amino Acid Sequence; Animals; Base Sequence; Bayes Theorem; Chlorocebus aethiops; Cloning, Molecular; Codon; Introns; Likelihood Functions; Macaca fascicularis; Male; Molecular Sequence Data; Pan troglodytes; Papio; Phylogeny; Prostate-Specific Antigen; Real-Time Polymerase Chain Reaction; RNA, Messenger

Analysis of the ABCA4 genomic locus in Stargardt disease. - Zernant, Jana; Xie, Yajing Angela; Ayuso, Carmen; Riveiro-Álvarez, Rosa; López-Martínez, Miguel-Ángel; Simonelli, Francesca; Testa, Francesco; Gorin, Michael B; Strom, Samuel P; Bertelsen, Mette; Rosenberg, Thomas; Boone, Philip M; et al. (Hum Mol Genet, 2014)
Autosomal recessive Stargardt disease (STGD1, MIM 248200) is caused by mutations in the ABCA4 gene. Complete sequencing of ABCA4 in STGD patients identifies compound heterozygous or homozygous disease-associated alleles in 65-70% of patients and only one mutation in 15-20% of patients. This study was designed to find the missing disease-causing ABCA4 variation by a combination of next-generation sequencing (NGS), array-Comparative Genome Hybridization (aCGH) screening, familial segregation and in silico analyses. The entire 140 kb ABCA4 genomic locus was sequenced in 114 STGD patients with one known ABCA4 exonic mutation revealing, on average, 200 intronic variants per sample. Filtering of these data resulted in 141 candidates for new mutations. Two variants were detected in four samples, two in three samples, and 20 variants in two samples, the remaining 117 new variants were detected only once. Multimodal analysis suggested 12 new likely pathogenic intronic ABCA4 variants, some of which were specific to (isolated) ethnic groups. No copy number variation (large deletions and insertions) was detected in any patient suggesting that it is a very rare event in the ABCA4 locus. Many variants were excluded since they were not conserved in non-human primates, were frequent in African populations and, therefore, represented ancestral, and not disease-associated, variants. The sequence variability in the ABCA4 locus is extensive and the non-coding sequences do not harbor frequent mutations in STGD patients of European-American descent. Defining disease-associated alleles in the ABCA4 locus requires exceptionally well characterized large cohorts and extensive analyses by a combination of various approaches.
Keywords: Alleles; ATP-Binding Cassette Transporters; Blacks; Case-Control Studies; Comparative Genomic Hybridization; Exons; Female; Gene Expression; Genes, Recessive; Genetic Loci; Genetic Variation; Heterozygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Introns; Macular Degeneration; Male; Mutation; Pedigree; Stargardt Disease; Whites

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; Aged; Alleles; Animals; Black People; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides; White People

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Design and anticipated outcomes of the eMERGE-PGx project: a multicenter pilot for preemptive pharmacogenomics in electronic health record systems. - Rasmussen-Torvik, L J; Stallings, S C; Gordon, A S; Almoguera, B; Basford, M A; Bielinski, S J; Brautbar, A; Brilliant, M H; Carrell, D S; Connolly, J J; Crosslin, D R; Doheny, K F; et al. (Clin Pharmacol Ther, 2014)
We describe here the design and initial implementation of the eMERGE-PGx project. eMERGE-PGx, a partnership of the Electronic Medical Records and Genomics Network and the Pharmacogenomics Research Network, has three objectives: (i) to deploy PGRNseq, a next-generation sequencing platform assessing sequence variation in 84 proposed pharmacogenes, in nearly 9,000 patients likely to be prescribed drugs of interest in a 1- to 3-year time frame across several clinical sites; (ii) to integrate well-established clinically validated pharmacogenetic genotypes into the electronic health record with associated clinical decision support and to assess process and clinical outcomes of implementation; and (iii) to develop a repository of pharmacogenetic variants of unknown significance linked to a repository of electronic health record-based clinical phenotype data for ongoing pharmacogenomics discovery. We describe site-specific project implementation and anticipated products, including genetic variant and phenotype data repositories, novel variant association studies, clinical decision support modules, clinical and process outcomes, approaches to managing incidental findings, and patient and clinician education methods.
Keywords: Adolescent; Aged; Child; Databases, Genetic; Drug Therapy; Electronic Health Records; Female; Genetic Association Studies; Genetic Variation; Genotype; Humans; Knowledge Bases; Male; Middle Aged; Pharmacogenetics; Phenotype; Pilot Projects; Sequence Analysis, DNA; Young Adult

Dynamic analyses of alternative polyadenylation from RNA-seq reveal a 3'-UTR landscape across seven tumour types. - Xia, Zheng; Donehower, Lawrence A; Cooper, Thomas A; Neilson, Joel R; Wheeler, David A; Wagner, Eric J; Li, Wei (Nat Commun, 2014)
Alternative polyadenylation (APA) is a pervasive mechanism in the regulation of most human genes, and its implication in diseases including cancer is only beginning to be appreciated. Since conventional APA profiling has not been widely adopted, global cancer APA studies are very limited. Here we develop a novel bioinformatics algorithm (DaPars) for the de novo identification of dynamic APAs from standard RNA-seq. When applied to 358 TCGA Pan-Cancer tumour/normal pairs across seven tumour types, DaPars reveals 1,346 genes with recurrent and tumour-specific APAs. Most APA genes (91%) have shorter 3'-untranslated regions (3' UTRs) in tumours that can avoid microRNA-mediated repression, including glutaminase (GLS), a key metabolic enzyme for tumour proliferation. Interestingly, selected APA events add strong prognostic power beyond common clinical and molecular variables, suggesting their potential as novel prognostic biomarkers. Finally, our results implicate CstF64, an essential polyadenylation factor, as a master regulator of 3'-UTR shortening across multiple tumour types.
Keywords: 3' Untranslated Regions; Cleavage Stimulation Factor; Gene Expression Regulation, Neoplastic; Humans; Neoplasms; Polyadenylation; RNA, Messenger; RNA-Binding Proteins; Sequence Analysis, RNA

The emerging genomics and systems biology research lead to systems genomics studies. - Yang, Mary Qu; Yoshigoe, Kenji; Yang, William; Tong, Weida; Qin, Xiang; Dunker, A; Chen, Zhongxue; Arbania, Hamid R; Liu, Jun S; Niemierko, Andrzej; Yang, Jack Y (BMC Genomics, 2014)
Synergistically integrating multi-layer genomic data at systems level not only can lead to deeper insights into the molecular mechanisms related to disease initiation and progression, but also can guide pathway-based biomarker and drug target identification. With the advent of high-throughput next-generation sequencing technologies, sequencing both DNA and RNA has generated multi-layer genomic data that can provide DNA polymorphism, non-coding RNA, messenger RNA, gene expression, isoform and alternative splicing information. Systems biology on the other hand studies complex biological systems, particularly systematic study of complex molecular interactions within specific cells or organisms. Genomics and molecular systems biology can be merged into the study of genomic profiles and implicated biological functions at cellular or organism level. The prospectively emerging field can be referred to as systems genomics or genomic systems biology. The Mid-South Bioinformatics Centre (MBC) and Joint Bioinformatics Ph.D. Program of University of Arkansas at Little Rock and University of Arkansas for Medical Sciences are particularly interested in promoting education and research advancement in this prospectively emerging field. Based on past investigations and research outcomes, MBC is further utilizing differential gene and isoform/exon expression from RNA-seq and co-regulation from the ChiP-seq specific for different phenotypes in combination with protein-protein interactions, and protein-DNA interactions to construct high-level gene networks for an integrative genome-phoneme investigation at systems biology level.
Keywords: Genetic Research; Genomics; Systems Biology

The first myriapod genome sequence reveals conservative arthropod gene content and genome organisation in the centipede Strigamia maritima. - Chipman, Ariel D; Ferrier, David E K; Brena, Carlo; Qu, Jiaxin; Hughes, Daniel S T; Schröder, Reinhard; Torres-Oliva, Montserrat; Znassi, Nadia; Jiang, Huaiyang; Almeida, Francisca C; Alonso, Claudio R; Apostolou, Zivkos; et al. (PLoS Biol, 2014)
Myriapods (e.g., centipedes and millipedes) display a simple homonomous body plan relative to other arthropods. All members of the class are terrestrial, but they attained terrestriality independently of insects. Myriapoda is the only arthropod class not represented by a sequenced genome. We present an analysis of the genome of the centipede Strigamia maritima. It retains a compact genome that has undergone less gene loss and shuffling than previously sequenced arthropods, and many orthologues of genes conserved from the bilaterian ancestor that have been lost in insects. Our analysis locates many genes in conserved macro-synteny contexts, and many small-scale examples of gene clustering. We describe several examples where S. maritima shows different solutions from insects to similar problems. The insect olfactory receptor gene family is absent from S. maritima, and olfaction in air is likely effected by expansion of other receptor gene families. For some genes S. maritima has evolved paralogues to generate coding sequence diversity, where insects use alternate splicing. This is most striking for the Dscam gene, which in Drosophila generates more than 100,000 alternate splice forms, but in S. maritima is encoded by over 100 paralogues. We see an intriguing linkage between the absence of any known photosensory proteins in a blind organism and the additional absence of canonical circadian clock genes. The phylogenetic position of myriapods allows us to identify where in arthropod phylogeny several particular molecular mechanisms and traits emerged. For example, we conclude that juvenile hormone signalling evolved with the emergence of the exoskeleton in the arthropods and that RR-1 containing cuticle proteins evolved in the lineage leading to Mandibulata. We also identify when various gene expansions and losses occurred. The genome of S. maritima offers us a unique glimpse into the ancestral arthropod genome, while also displaying many adaptations to its specific life history.
Keywords: Animals; Arthropods; Circadian Rhythm Signaling Peptides and Proteins; DNA Methylation; Evolution, Molecular; Female; Genome; Genome, Mitochondrial; Hormones; Male; Multigene Family; Phylogeny; Polymorphism, Genetic; Protein Kinases; Receptors, Odorant; RNA, Untranslated; Selenoproteins; Sex Chromosomes; Synteny; Transcription Factors

A framework for the interpretation of de novo mutation in human disease. - Samocha, Kaitlin E; Robinson, Elise B; Sanders, Stephan J; Stevens, Christine; Sabo, Aniko; McGrath, Lauren M; Kosmicki, Jack A; Rehnström, Karola; Mallick, Swapan; Kirby, Andrew; Wall, Dennis P; MacArthur, Daniel G; et al. (Nat Genet, 2014)
Spontaneously arising (de novo) mutations have an important role in medical genetics. For diseases with extensive locus heterogeneity, such as autism spectrum disorders (ASDs), the signal from de novo mutations is distributed across many genes, making it difficult to distinguish disease-relevant mutations from background variation. Here we provide a statistical framework for the analysis of excesses in de novo mutation per gene and gene set by calibrating a model of de novo mutation. We applied this framework to de novo mutations collected from 1,078 ASD family trios, and, whereas we affirmed a significant role for loss-of-function mutations, we found no excess of de novo loss-of-function mutations in cases with IQ above 100, suggesting that the role of de novo mutations in ASDs might reside in fundamental neurodevelopmental processes. We also used our model to identify ∼1,000 genes that are significantly lacking in functional coding variation in non-ASD samples and are enriched for de novo loss-of-function mutations identified in ASD cases.
Keywords: Child Development Disorders, Pervasive; Exome; Female; Genetic Code; Genetic Predisposition to Disease; Genetics, Medical; Humans; Male; Mutation

Genetic and clinical analysis of ABCA4-associated disease in African American patients. - Zernant, Jana; Collison, Frederick T; Lee, Winston; Fishman, Gerald A; Nõupuu, Kalev; Bo Yuan; Cai, Carolyn; James R Lupski; Yannuzzi, Lawrence A; Tsang, Stephen H; Allikmets, Rando (Hum Mutat, 2014)
Autosomal recessive Stargardt disease (STGD1) is caused by hundreds of mutations in the ABCA4 gene, which are often specific to racial and ethnic groups. Here, we investigated the ABCA4 variation and their phenotypic expression in a cohort of 44 patients of African American descent, a previously under-characterized racial group. Patients were screened for mutations in ABCA4 by next-generation sequencing and array-comparative genomic hybridization (aCGH), followed by analyses for pathogenicity by in silico programs. Thorough ophthalmic examination was performed on all patients. At least two (expected) disease-causing alleles in the ABCA4 gene were identified in 27 (61.4%) patients, one allele in 11 (25%) patients, and no ABCA4 mutations were found in six (13.6%) patients. Altogether, 39 different disease-causing ABCA4 variants, including seven new, were identified on 65 (74%) chromosomes, most of which were unique for this racial group. The most frequent ABCA4 mutation in this cohort was c.6320G>A (p.(R2107H)), representing 19.3% of all disease-associated alleles. No large copy number variants were identified in any patient. Most patients reported later onset of symptoms. In summary, the ABCA4 mutation spectrum in patients of West African descent differs significantly from that in patients of European descent, resulting in a later onset and "milder" disease.
Keywords: Adult; African Americans; ATP-Binding Cassette Transporters; Comparative Genomic Hybridization; DNA Mutational Analysis; Electroretinography; Female; Genetic Predisposition to Disease; Humans; Macular Degeneration; Male; Middle Aged; Mutation; Stargardt Disease; United States; Whites

The genetic basis of DOORS syndrome: an exome-sequencing study. - Campeau, Philippe M; Kasperaviciute, Dalia; Lu, James T; Burrage, Lindsay C; Kim, Choel; Hori, Mutsuki; Powell, Berkley R; Stewart, Fiona; Félix, Têmis Maria; van den Ende, Jenneke; Wisniewska, Marzena; Kayserili, Hulya; et al. (Lancet Neurol, 2014)
BACKGROUND: Deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures (DOORS) syndrome is a rare autosomal recessive disorder of unknown cause. We aimed to identify the genetic basis of this syndrome by sequencing most coding exons in affected individuals. METHODS: Through a search of available case studies and communication with collaborators, we identified families that included at least one individual with at least three of the five main features of the DOORS syndrome: deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures. Participants were recruited from 26 centres in 17 countries. Families described in this study were enrolled between Dec 1, 2010, and March 1, 2013. Collaborating physicians enrolling participants obtained clinical information and DNA samples from the affected child and both parents if possible. We did whole-exome sequencing in affected individuals as they were enrolled, until we identified a candidate gene, and Sanger sequencing to confirm mutations. We did expression studies in human fibroblasts from one individual by real-time PCR and western blot analysis, and in mouse tissues by immunohistochemistry and real-time PCR. FINDINGS: 26 families were included in the study. We did exome sequencing in the first 17 enrolled families; we screened for TBC1D24 by Sanger sequencing in subsequent families. We identified TBC1D24 mutations in 11 individuals from nine families (by exome sequencing in seven families, and Sanger sequencing in two families). 18 families had individuals with all five main features of DOORS syndrome, and TBC1D24 mutations were identified in half of these families. The seizure types in individuals with TBC1D24 mutations included generalised tonic-clonic, complex partial, focal clonic, and infantile spasms. Of the 18 individuals with DOORS syndrome from 17 families without TBC1D24 mutations, eight did not have seizures and three did not have deafness. In expression studies, some mutations abrogated TBC1D24 mRNA stability. We also detected Tbc1d24 expression in mouse phalangeal chondrocytes and calvaria, which suggests a role of TBC1D24 in skeletogenesis. INTERPRETATION: Our findings suggest that mutations in TBC1D24 seem to be an important cause of DOORS syndrome and can cause diverse phenotypes. Thus, individuals with DOORS syndrome without deafness and seizures but with the other features should still be screened for TBC1D24 mutations. More information is needed to understand the cellular roles of TBC1D24 and identify the genes responsible for DOORS phenotypes in individuals who do not have a mutation in TBC1D24. FUNDING: US National Institutes of Health, the CIHR (Canada), the NIHR (UK), the Wellcome Trust, the Henry Smith Charity, and Action Medical Research.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Craniofacial Abnormalities; Exome; Female; GTPase-Activating Proteins; Hand Deformities, Congenital; Hearing Loss, Sensorineural; Humans; Infant; Intellectual Disability; Internationality; Male; Membrane Proteins; Nails, Malformed; Nerve Tissue Proteins; Phenotype; Sequence Analysis, DNA; Young Adult

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genomic encyclopedia of bacteria and archaea: sequencing a myriad of type strains. - Kyrpides, Nikos C; Hugenholtz, Philip; Eisen, Jonathan A; Woyke, Tanja; Göker, Markus; Parker, Charles T; Amann, Rudolf; Beck, Brian J; Chain, Patrick S G; Chun, Jongsik; Colwell, Rita R; Danchin, Antoine; et al. (PLoS Biol, 2014)
Microbes hold the key to life. They hold the secrets to our past (as the descendants of the earliest forms of life) and the prospects for our future (as we mine their genes for solutions to some of the planet's most pressing problems, from global warming to antibiotic resistance). However, the piecemeal approach that has defined efforts to study microbial genetic diversity for over 20 years and in over 30,000 genome projects risks squandering that promise. These efforts have covered less than 20% of the diversity of the cultured archaeal and bacterial species, which represent just 15% of the overall known prokaryotic diversity. Here we call for the funding of a systematic effort to produce a comprehensive genomic catalog of all cultured Bacteria and Archaea by sequencing, where available, the type strain of each species with a validly published name (currently∼11,000). This effort will provide an unprecedented level of coverage of our planet's genetic diversity, allow for the large-scale discovery of novel genes and functions, and lead to an improved understanding of microbial evolution and function in the environment.
Keywords: Archaea; Bacteria; Databases, Genetic; Genome, Archaeal; Genome, Bacterial; Genomics; Phylogeny; Sequence Analysis, DNA

Gibbon genome and the fast karyotype evolution of small apes. - Carbone, Lucia; Harris, R Alan; Gnerre, Sante; Veeramah, Krishna R; Lorente-Galdos, Belen; Huddleston, John; Meyer, Thomas J; Herrero, Javier; Roos, Christian; Aken, Bronwen; Anaclerio, Fabio; Archidiacono, Nicoletta; et al. (Nature, 2014)
Gibbons are small arboreal apes that display an accelerated rate of evolutionary chromosomal rearrangement and occupy a key node in the primate phylogeny between Old World monkeys and great apes. Here we present the assembly and analysis of a northern white-cheeked gibbon (Nomascus leucogenys) genome. We describe the propensity for a gibbon-specific retrotransposon (LAVA) to insert into chromosome segregation genes and alter transcription by providing a premature termination site, suggesting a possible molecular mechanism for the genome plasticity of the gibbon lineage. We further show that the gibbon genera (Nomascus, Hylobates, Hoolock and Symphalangus) experienced a near-instantaneous radiation ∼5 million years ago, coincident with major geographical changes in southeast Asia that caused cycles of habitat compression and expansion. Finally, we identify signatures of positive selection in genes important for forelimb development (TBX5) and connective tissues (COL1A1) that may have been involved in the adaptation of gibbons to their arboreal habitat.
Keywords: Animals; Evolution, Molecular; Genome; Hominidae; Humans; Hylobates; Karyotype; Molecular Sequence Data; Phylogeny; Retroelements; Selection, Genetic; Transcription Termination, Genetic

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Bo Yuan; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Identification of genes and pathways involved in kidney renal clear cell carcinoma. - Yang, William; Yoshigoe, Kenji; Qin, Xiang; Liu, Jun S; Yang, Jack Y; Niemierko, Andrzej; Deng, Youping; Liu, Yunlong; Dunker, A; Chen, Zhongxue; Wang, Liangjiang; Xu, Dong; et al. (BMC Bioinformatics, 2014)
BACKGROUND: Kidney Renal Clear Cell Carcinoma (KIRC) is one of fatal genitourinary diseases and accounts for most malignant kidney tumours. KIRC has been shown resistance to radiotherapy and chemotherapy. Like many types of cancers, there is no curative treatment for metastatic KIRC. Using advanced sequencing technologies, The Cancer Genome Atlas (TCGA) project of NIH/NCI-NHGRI has produced large-scale sequencing data, which provide unprecedented opportunities to reveal new molecular mechanisms of cancer. We combined differentially expressed genes, pathways and network analyses to gain new insights into the underlying molecular mechanisms of the disease development. RESULTS: Followed by the experimental design for obtaining significant genes and pathways, comprehensive analysis of 537 KIRC patients' sequencing data provided by TCGA was performed. Differentially expressed genes were obtained from the RNA-Seq data. Pathway and network analyses were performed. We identified 186 differentially expressed genes with significant p-value and large fold changes (P < 0.01, |log(FC)| > 5). The study not only confirmed a number of identified differentially expressed genes in literature reports, but also provided new findings. We performed hierarchical clustering analysis utilizing the whole genome-wide gene expressions and differentially expressed genes that were identified in this study. We revealed distinct groups of differentially expressed genes that can aid to the identification of subtypes of the cancer. The hierarchical clustering analysis based on gene expression profile and differentially expressed genes suggested four subtypes of the cancer. We found enriched distinct Gene Ontology (GO) terms associated with these groups of genes. Based on these findings, we built a support vector machine based supervised-learning classifier to predict unknown samples, and the classifier achieved high accuracy and robust classification results. In addition, we identified a number of pathways (P < 0.04) that were significantly influenced by the disease. We found that some of the identified pathways have been implicated in cancers from literatures, while others have not been reported in the cancer before. The network analysis leads to the identification of significantly disrupted pathways and associated genes involved in the disease development. Furthermore, this study can provide a viable alternative in identifying effective drug targets. CONCLUSIONS: Our study identified a set of differentially expressed genes and pathways in kidney renal clear cell carcinoma, and represents a comprehensive computational approach to analysis large-scale next-generation sequencing data. The pathway and network analyses suggested that information from distinctly expressed genes can be utilized in the identification of aberrant upstream regulators. Identification of distinctly expressed genes and altered pathways are important in effective biomarker identification for early cancer diagnosis and treatment planning. Combining differentially expressed genes with pathway and network analyses using intelligent computational approaches provide an unprecedented opportunity to identify upstream disease causal genes and effective drug targets.
Keywords: Biomarkers, Tumor; Carcinoma, Renal Cell; Case-Control Studies; Cluster Analysis; Gene Expression Profiling; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Humans; Kidney; Kidney Neoplasms; Signal Transduction; Support Vector Machine

Mammalian Y chromosomes retain widely expressed dosage-sensitive regulators. - Bellott, Daniel W; Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Cho, Ting-Jan; Koutseva, Natalia; Zaghlul, Sara; Graves, Tina; Rock, Susie; Kremitzki, Colin; Fulton, Robert S; et al. (Nature, 2014)
The human X and Y chromosomes evolved from an ordinary pair of autosomes, but millions of years ago genetic decay ravaged the Y chromosome, and only three per cent of its ancestral genes survived. We reconstructed the evolution of the Y chromosome across eight mammals to identify biases in gene content and the selective pressures that preserved the surviving ancestral genes. Our findings indicate that survival was nonrandom, and in two cases, convergent across placental and marsupial mammals. We conclude that the gene content of the Y chromosome became specialized through selection to maintain the ancestral dosage of homologous X-Y gene pairs that function as broadly expressed regulators of transcription, translation and protein stability. We propose that beyond its roles in testis determination and spermatogenesis, the Y chromosome is essential for male viability, and has unappreciated roles in Turner's syndrome and in phenotypic differences between the sexes in health and disease.
Keywords: Animals; Chromosomes, Human, X; Chromosomes, Human, Y; Disease; Evolution, Molecular; Female; Gene Dosage; Gene Expression Regulation; Health; Humans; Male; Mammals; Marsupialia; Molecular Sequence Annotation; Molecular Sequence Data; Protein Biosynthesis; Protein Stability; Selection, Genetic; Sequence Homology; Sex Characteristics; Spermatogenesis; Testis; Transcription, Genetic; Turner Syndrome; X Chromosome; Y Chromosome

Metabolomic patterns and alcohol consumption in African Americans in the Atherosclerosis Risk in Communities Study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Steffen, Lyn M; Nettleton, Jennifer A; Boerwinkle, Eric (Am J Clin Nutr, 2014)
BACKGROUND: Effects of alcohol consumption on health and disease are complex and involve a number of cellular and metabolic processes. OBJECTIVE: We examined the association between alcohol consumption habits and metabolomic profiles. DESIGN: We conducted a cross-sectional study to explore the association of alcohol consumption habits measured by using a questionnaire with serum metabolites measured by using untargeted mass spectrometry in 1977 African Americans from the Jackson field center in the Atherosclerosis Risk in Communities Study. The whole sample was split into a discovery set (n = 1500) and a replication set (n = 477). Alcohol consumption habits were treated as an ordinal variable, with nondrinkers as the reference group and quartiles of current drinkers as ordinal groups with higher values. For each metabolite, a linear regression was conducted to estimate its relation with alcohol consumption habits separately in both sets. A modified Bonferroni procedure was used in the discovery set to adjust the significance threshold (P < 1.9 × 10⁻⁴). RESULTS: In 356 named metabolites, 39 metabolites were significantly associated with alcohol consumption habits in both discovery and replication sets. In general, alcohol consumption was associated with higher levels of most metabolites such as those in amino acid and lipid pathways and with lower levels of γ-glutamyl dipeptides. Three pathways, 2-hydroxybutyrate-related metabolites, γ-glutamyl dipeptides, and lysophosphatidylcholines, which are considered to be involved in inflammation and oxidation, were associated with incident cardiovascular diseases. CONCLUSIONS: To our knowledge, this is the largest metabolomic study thus far conducted in nonwhites. Metabolomic biomarkers of alcohol consumption were identified and replicated. The results lend new insight into potential mediating effects between alcohol consumption and future health and disease.
Keywords: Alcohol Drinking; Atherosclerosis; Biomarkers; Black or African American; Cohort Studies; Cross-Sectional Studies; Female; Humans; Incidence; Linear Models; Longitudinal Studies; Male; Metabolome; Middle Aged; Prevalence; Prospective Studies; Reproducibility of Results; Risk Factors; United States; Up-Regulation

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Muzny, Donna M; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Multilayer-omics analysis of renal cell carcinoma, including the whole exome, methylome and transcriptome. - Arai, Eri; Sakamoto, Hiromi; Ichikawa, Hitoshi; Totsuka, Hirohiko; Chiku, Suenori; Gotoh, Masahiro; Mori, Taisuke; Nakatani, Tamao; Ohnami, Sumiko; Nakagawa, Tohru; Fujimoto, Hiroyuki; Wang, Linghua; et al. (Int J Cancer, 2014)
The aim of this study was to identify pathways that have a significant impact during renal carcinogenesis. Sixty-seven paired samples of both noncancerous renal cortex tissue and cancerous tissue from patients with clear cell renal cell carcinomas (RCCs) were subjected to whole-exome, methylome and transcriptome analyses using Agilent SureSelect All Exon capture followed by sequencing on an Illumina HiSeq 2000 platform, Illumina Infinium HumanMethylation27 BeadArray and Agilent SurePrint Human Gene Expression microarray, respectively. Sanger sequencing and quantitative reverse transcription-PCR were performed for technical verification. MetaCore software was used for pathway analysis. Somatic nonsynonymous single-nucleotide mutations, insertions/deletions and intragenic breaks of 2,153, 359 and 8 genes were detected, respectively. Mutations of GCN1L1, MED12 and CCNC, which are members of CDK8 mediator complex directly regulating β-catenin-driven transcription, were identified in 16% of the RCCs. Mutations of MACF1, which functions in the Wnt/β-catenin signaling pathway, were identified in 4% of the RCCs. A combination of methylome and transcriptome analyses further highlighted the significant role of the Wnt/β-catenin signaling pathway in renal carcinogenesis. Genetic aberrations and reduced expression of ERC2 and ABCA13 were frequent in RCCs, and MTOR mutations were identified as one of the major disrupters of cell signaling during renal carcinogenesis. Our results confirm that multilayer-omics analysis can be a powerful tool for revealing pathways that play a significant role in carcinogenesis.
Keywords: Carcinoma, Renal Cell; DNA Methylation; Exome; Gene Expression Regulation, Neoplastic; Humans; Kidney Neoplasms; Polymorphism, Single Nucleotide; RNA, Messenger; Transcriptome

Mutations in NGLY1 cause an inherited disorder of the endoplasmic reticulum-associated degradation pathway. - Enns, Gregory M; Shashi, Vandana; Bainbridge, Matthew; Gambello, Michael J; Zahir, Farah R; Bast, Thomas; Crimian, Rebecca; Schoch, Kelly; Platt, Julia; Cox, Rachel; Bernstein, Jonathan A; Scavina, Mena; et al. (Genet Med, 2014)
PURPOSE: The endoplasmic reticulum-associated degradation pathway is responsible for the translocation of misfolded proteins across the endoplasmic reticulum membrane into the cytosol for subsequent degradation by the proteasome. To define the phenotype associated with a novel inherited disorder of cytosolic endoplasmic reticulum-associated degradation pathway dysfunction, we studied a series of eight patients with deficiency of N-glycanase 1. METHODS: Whole-genome, whole-exome, or standard Sanger sequencing techniques were employed. Retrospective chart reviews were performed in order to obtain clinical data. RESULTS: All patients had global developmental delay, a movement disorder, and hypotonia. Other common findings included hypolacrima or alacrima (7/8), elevated liver transaminases (6/7), microcephaly (6/8), diminished reflexes (6/8), hepatocyte cytoplasmic storage material or vacuolization (5/6), and seizures (4/8). The nonsense mutation c.1201A>T (p.R401X) was the most common deleterious allele. CONCLUSION: NGLY1 deficiency is a novel autosomal recessive disorder of the endoplasmic reticulum-associated degradation pathway associated with neurological dysfunction, abnormal tear production, and liver disease. The majority of patients detected to date carry a specific nonsense mutation that appears to be associated with severe disease. The phenotypic spectrum is likely to enlarge as cases with a broader range of mutations are detected.
Keywords: Abnormalities, Multiple; Adolescent; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Exome; Family Health; Fatal Outcome; Female; Genome-Wide Association Study; Humans; Infant; Male; Microcephaly; Movement Disorders; Muscle Hypotonia; Mutation; Pedigree; Peptide-N4-(N-acetyl-beta-glucosaminyl) Asparagine Amidase; Retrospective Studies; Seizures; Sequence Analysis, DNA; Signal Transduction; Young Adult

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Muzny, Donna; Boerwinkle, Eric; Gibbs, Richard; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements. - Wang, Feng; Wang, Hui; Tuan, Han-Fang; Nguyen, Duy H; Sun, Vincent; Keser, Vafa; Bowne, Sara J; Sullivan, Lori S; Luo, Hongrong; Zhao, Ling; Wang, Xia; Zaneveld, Jacques E; et al. (Hum Genet, 2014)
Retinitis pigmentosa (RP) is a devastating form of retinal degeneration, with significant social and professional consequences. Molecular genetic information is invaluable for an accurate clinical diagnosis of RP due to its high genetic and clinical heterogeneity. Using a gene capture panel that covers 163 of the currently known retinal disease genes, including 48 RP genes, we performed a comprehensive molecular screening in a collection of 123 RP unsettled probands from a wide variety of ethnic backgrounds, including 113 unrelated simplex and 10 autosomal recessive RP (arRP) cases. As a result, 61 mutations were identified in 45 probands, including 38 novel pathogenic alleles. Interestingly, we observed that phenotype and genotype were not in full agreement in 21 probands. Among them, eight probands were clinically reassessed, resulting in refinement of clinical diagnoses for six of these patients. Finally, recessive mutations in CLN3 were identified in five retinal degeneration patients, including four RP probands and one cone-rod dystrophy patient, suggesting that CLN3 is a novel non-syndromic retinal disease gene. Collectively, our results underscore that, due to the high molecular and clinical heterogeneity of RP, comprehensive screening of all retinal disease genes is effective in identifying novel pathogenic mutations and provides an opportunity to discover new genotype-phenotype correlations. Information gained from this genetic screening will directly aid in patient diagnosis, prognosis, and treatment, as well as allowing appropriate family planning and counseling.
Keywords: Alleles; Computational Biology; Exons; Genes, Recessive; Genetic Association Studies; Genetic Testing; Genotype; High-Throughput Nucleotide Sequencing; Humans; Membrane Glycoproteins; Molecular Chaperones; Mutation; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Retinitis Pigmentosa; Sequence Analysis, DNA

Next-generation sequencing identifies rare variants associated with Noonan syndrome. - Chen, Peng-Chieh; Yin, Jiani; Yu, Hui-Wen; Yuan, Tao; Fernandez, Minerva; Yung, Christina K; Trinh, Quang M; Peltekova, Vanya D; Reid, Jeffrey G; Tworog-Dube, Erica; Morgan, Margaret B; Muzny, Donna M; et al. (Proc Natl Acad Sci U S A, 2014)
Noonan syndrome (NS) is a relatively common genetic disorder, characterized by typical facies, short stature, developmental delay, and cardiac abnormalities. Known causative genes account for 70-80% of clinically diagnosed NS patients, but the genetic basis for the remaining 20-30% of cases is unknown. We performed next-generation sequencing on germ-line DNA from 27 NS patients lacking a mutation in the known NS genes. We identified gain-of-function alleles in Ras-like without CAAX 1 (RIT1) and mitogen-activated protein kinase kinase 1 (MAP2K1) and previously unseen loss-of-function variants in RAS p21 protein activator 2 (RASA2) that are likely to cause NS in these patients. Expression of the mutant RASA2, MAP2K1, or RIT1 alleles in heterologous cells increased RAS-ERK pathway activation, supporting a causative role in NS pathogenesis. Two patients had more than one disease-associated variant. Moreover, the diagnosis of an individual initially thought to have NS was revised to neurofibromatosis type 1 based on an NF1 nonsense mutation detected in this patient. Another patient harbored a missense mutation in NF1 that resulted in decreased protein stability and impaired ability to suppress RAS-ERK activation; however, this patient continues to exhibit a NS-like phenotype. In addition, a nonsense mutation in RPS6KA3 was found in one patient initially diagnosed with NS whose diagnosis was later revised to Coffin-Lowry syndrome. Finally, we identified other potential candidates for new NS genes, as well as potential carrier alleles for unrelated syndromes. Taken together, our data suggest that next-generation sequencing can provide a useful adjunct to RASopathy diagnosis and emphasize that the standard clinical categories for RASopathies might not be adequate to describe all patients.
Keywords: Alleles; Genetic Association Studies; High-Throughput Nucleotide Sequencing; Humans; MAP Kinase Kinase 1; MAP Kinase Signaling System; Mutation; Neurofibromin 1; Noonan Syndrome; ras Proteins

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

Novel somatic and germline mutations in intracranial germ cell tumours. - Wang, Linghua; Yamaguchi, Shigeru; Burstein, Matthew D; Terashima, Keita; Chang, Kyle; Ng, Ho-Keung; Nakamura, Hideo; He, Zongxiao; Doddapaneni, Harshavardhan; Lewis, Lora; Wang, Mark; Suzuki, Tomonari; et al. (Nature, 2014)
Intracranial germ cell tumours (IGCTs) are a group of rare heterogeneous brain tumours that are clinically and histologically similar to the more common gonadal GCTs. IGCTs show great variation in their geographical and gender distribution, histological composition and treatment outcomes. The incidence of IGCTs is historically five- to eightfold greater in Japan and other East Asian countries than in Western countries, with peak incidence near the time of puberty. About half of the tumours are located in the pineal region. The male-to-female incidence ratio is approximately 3-4:1 overall, but is even higher for tumours located in the pineal region. Owing to the scarcity of tumour specimens available for research, little is currently known about this rare disease. Here we report the analysis of 62 cases by next-generation sequencing, single nucleotide polymorphism array and expression array. We find the KIT/RAS signalling pathway frequently mutated in more than 50% of IGCTs, including novel recurrent somatic mutations in KIT, its downstream mediators KRAS and NRAS, and its negative regulator CBL. Novel somatic alterations in the AKT/mTOR pathway included copy number gains of the AKT1 locus at 14q32.33 in 19% of patients, with corresponding upregulation of AKT1 expression. We identified loss-of-function mutations in BCORL1, a transcriptional co-repressor and tumour suppressor. We report significant enrichment of novel and rare germline variants in JMJD1C, which codes for a histone demethylase and is a coactivator of the androgen receptor, among Japanese IGCT patients. This study establishes a molecular foundation for understanding the biology of IGCTs and suggests potentially promising therapeutic strategies focusing on the inhibition of KIT/RAS activation and the AKT1/mTOR pathway.
Keywords: Adult; Brain Neoplasms; Child; Female; Germ-Line Mutation; Humans; Japan; Male; Mutation; Neoplasms, Germ Cell and Embryonal; Oncogene Protein v-akt; Proto-Oncogene Proteins c-kit; ras Proteins; Reproducibility of Results; Signal Transduction; TOR Serine-Threonine Kinases; Young Adult

Parental somatic mosaicism is underrecognized and influences recurrence risk of genomic disorders. - Campbell, Ian M; Yuan, Bo; Robberecht, Caroline; Pfundt, Rolph; Szafranski, Przemyslaw; McEntagart, Meriel E; Nagamani, Sandesh C S; Erez, Ayelet; Bartnik, Magdalena; Wiśniowiecka-Kowalnik, Barbara; Plunkett, Katie S; Pursley, Amber N; et al. (Am J Hum Genet, 2014)
New human mutations are thought to originate in germ cells, thus making a recurrence of the same mutation in a sibling exceedingly rare. However, increasing sensitivity of genomic technologies has anecdotally revealed mosaicism for mutations in somatic tissues of apparently healthy parents. Such somatically mosaic parents might also have germline mosaicism that can potentially cause unexpected intergenerational recurrences. Here, we show that somatic mosaicism for transmitted mutations among parents of children with simplex genetic disease is more common than currently appreciated. Using the sensitivity of individual-specific breakpoint PCR, we prospectively screened 100 families with children affected by genomic disorders due to rare deletion copy-number variants (CNVs) determined to be de novo by clinical analysis of parental DNA. Surprisingly, we identified four cases of low-level somatic mosaicism for the transmitted CNV in DNA isolated from parental blood. Integrated probabilistic modeling of gametogenesis developed in response to our observations predicts that mutations in parental blood increase recurrence risk substantially more than parental mutations confined to the germline. Moreover, despite the fact that maternally transmitted mutations are the minority of alleles, our model suggests that sexual dimorphisms in gametogenesis result in a greater proportion of somatically mosaic transmitting mothers who are thus at increased risk of recurrence. Therefore, somatic mosaicism together with sexual differences in gametogenesis might explain a considerable fraction of unexpected recurrences of X-linked recessive disease. Overall, our results underscore an important role for somatic mosaicism and mitotic replicative mutational mechanisms in transmission genetics.
Keywords: Cell Division; DNA Copy Number Variations; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Male; Models, Genetic; Mosaicism; Mutation; Pedigree; Prospective Studies; Recurrence; Risk; Sex Characteristics; Smith-Magenis Syndrome

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Prospective associations of coronary heart disease loci in African Americans using the MetaboChip: the PAGE study. - Franceschini, Nora; Hu, Yijuan; Reiner, Alex P; Buyske, Steven; Nalls, Mike; Yanek, Lisa R; Li, Yun; Hindorff, Lucia A; Cole, Shelley A; Howard, Barbara V; Stafford, Jeanette M; Carty, Cara L; et al. (PLoS One, 2014)
BACKGROUND: Coronary heart disease (CHD) is a leading cause of morbidity and mortality in African Americans. However, there is a paucity of studies assessing genetic determinants of CHD in African Americans. We examined the association of published variants in CHD loci with incident CHD, attempted to fine map these loci, and characterize novel variants influencing CHD risk in African Americans. METHODS AND RESULTS: Up to 8,201 African Americans (including 546 first CHD events) were genotyped using the MetaboChip array in the Atherosclerosis Risk in Communities (ARIC) study and Women's Health Initiative (WHI). We tested associations using Cox proportional hazard models in sex- and study-stratified analyses and combined results using meta-analysis. Among 44 validated CHD loci available in the array, we replicated and fine-mapped the SORT1 locus, and showed same direction of effects as reported in studies of individuals of European ancestry for SNPs in 22 additional published loci. We also identified a SNP achieving array wide significance (MYC: rs2070583, allele frequency 0.02, P = 8.1 × 10(-8)), but the association did not replicate in an additional 8,059 African Americans (577 events) from the WHI, HealthABC and GeneSTAR studies, and in a meta-analysis of 5 cohort studies of European ancestry (24,024 individuals including 1,570 cases of MI and 2,406 cases of CHD) from the CHARGE Consortium. CONCLUSIONS: Our findings suggest that some CHD loci previously identified in individuals of European ancestry may be relevant to incident CHD in African Americans.
Keywords: Adaptor Proteins, Vesicular Transport; Black or African American; Coronary Disease; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Proto-Oncogene Proteins c-myc

Serum metabolomic profiling and incident CKD among African Americans. - Yu, Bing; Zheng, Yan; Nettleton, Jennifer A; Alexander, Danny; Coresh, Josef; Boerwinkle, Eric (Clin J Am Soc Nephrol, 2014)
BACKGROUND AND OBJECTIVES: Novel biomarkers that more accurately reflect kidney function and predict future CKD are needed. The human metabolome is the product of multiple physiologic or pathophysiologic processes and may provide novel insight into disease etiology and progression. This study investigated whether estimated kidney function would be associated with multiple metabolites and whether selected metabolomic factors would be independent risk factors for incident CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In total, 1921 African Americans free of CKD with a median of 19.6 years follow-up among the Atherosclerosis Risk in Communities Study were included. A total of 204 serum metabolites quantified by untargeted gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry was analyzed by both linear regression for the cross-sectional associations with eGFR (specified by the Chronic Kidney Disease Epidemiology Collaboration equation) and Cox proportional hazards model for the longitudinal associations with incident CKD. RESULTS: Forty named and 34 unnamed metabolites were found to be associated with eGFR specified by the Chronic Kidney Disease Epidemiology Collaboration equation with creatine and 3-indoxyl sulfate showing the strongest positive (2.8 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, 2.1 to 3.5) and negative association (-14.2 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, -17.0 to -11.3), respectively. Two hundred four incident CKD events with a median follow-up time of 19.6 years were included in the survival analyses. Higher levels of 5-oxoproline (hazard ratio, 0.70; 95% confidence interval, 0.60 to 0.82) and 1,5-anhydroglucitol (hazard ratio, 0.68; 95% confidence interval, 0.58 to 0.80) were significantly related to lower risk of incident CKD, and the associations did not appreciably change when mutually adjusted. CONCLUSIONS: These data identify a large number of metabolites associated with kidney function as well as two metabolites that are candidate risk factors for CKD and may provide new insights into CKD biomarker identification.
Keywords: Biomarkers; Black or African American; Chromatography, Liquid; Creatine; Cross-Sectional Studies; Deoxyglucose; Female; Gas Chromatography-Mass Spectrometry; Humans; Incidence; Indican; Kidney; Linear Models; Longitudinal Studies; Male; Metabolomics; Middle Aged; Proportional Hazards Models; Pyrrolidonecarboxylic Acid; Renal Insufficiency, Chronic; Risk Factors; Time Factors; United States

The sheep genome illuminates biology of the rumen and lipid metabolism. - Jiang, Yu; Xie, Min; Chen, Wenbin; Talbot, Richard; Maddox, Jillian F; Faraut, Thomas; Wu, Chunhua; Muzny, Donna M; Li, Yuxiang; Zhang, Wenguang; Stanton, Jo-Ann; Brauning, Rudiger; et al. (Science, 2014)
Sheep (Ovis aries) are a major source of meat, milk, and fiber in the form of wool and represent a distinct class of animals that have a specialized digestive organ, the rumen, that carries out the initial digestion of plant material. We have developed and analyzed a high-quality reference sheep genome and transcriptomes from 40 different tissues. We identified highly expressed genes encoding keratin cross-linking proteins associated with rumen evolution. We also identified genes involved in lipid metabolism that had been amplified and/or had altered tissue expression patterns. This may be in response to changes in the barrier lipids of the skin, an interaction between lipid metabolism and wool synthesis, and an increased role of volatile fatty acids in ruminants compared with nonruminant animals.
Keywords: Amino Acid Sequence; Animals; Fatty Acids, Volatile; Gene Expression Regulation; Genome; Keratins, Hair-Specific; Lipid Metabolism; Molecular Sequence Data; Phylogeny; Rumen; Sheep, Domestic; Transcriptome; Wool

Squamous cell carcinoma of the oral tongue in young non-smokers is genomically similar to tumors in older smokers. - Pickering, Curtis R; Zhang, Jiexin; Neskey, David M; Zhao, Mei; Jasser, Samar A; Wang, Jiping; Ward, Alexandra; Tsai, C Jillian; Ortega Alves, Marcus V; Zhou, Jane H; Drummond, Jennifer; El-Naggar, Adel K; et al. (Clin Cancer Res, 2014)
PURPOSE: Epidemiologic studies have identified an increasing incidence of squamous cell carcinoma of the oral tongue (SCCOT) in younger patients. EXPERIMENTAL DESIGN: DNA isolated from tongue tumors of young (<45 years, non-smokers) and old (>45 years) patients at was subjected to whole-exome sequencing and copy-number analysis. These data were compared with data from similar patients in the TCGA (The Cancer Genome Atlas) project. RESULTS: In this study, we found that gene-specific mutation and copy-number alteration frequencies were similar between young and old patients with SCCOT in two independent cohorts. Likewise, the types of base changes observed in the young cohort were similar to those in the old cohort even though they differed in smoking history. TCGA data also demonstrate that the genomic effects of smoking are tumor site-specific, and we find that smoking has only a minor impact on the types of mutations observed in SCCOT. CONCLUSIONS: Overall, tumors from young patients with SCCOT appear genomically similar to those of older patients with SCCOT, and the cause for the increasing incidence of young SCCOT remains unknown. These data indicate that the functional impact of smoking on carcinogenesis in SCCOT is still poorly understood.
Keywords: Adult; Age Factors; Carcinoma, Squamous Cell; DNA Copy Number Variations; DNA Mutational Analysis; Female; Humans; Male; Middle Aged; Mutation; Prognosis; Smoking; Tongue Neoplasms

Trans-ancestry mutational landscape of hepatocellular carcinoma genomes. - Totoki, Yasushi; Tatsuno, Kenji; Covington, Kyle R; Ueda, Hiroki; Creighton, Chad J; Kato, Mamoru; Tsuji, Shingo; Donehower, Lawrence A; Slagle, Betty L; Nakamura, Hiromi; Yamamoto, Shogo; Shinbrot, Eve; et al. (Nat Genet, 2014)
Diverse epidemiological factors are associated with hepatocellular carcinoma (HCC) prevalence in different populations. However, the global landscape of the genetic changes in HCC genomes underpinning different epidemiological and ancestral backgrounds still remains uncharted. Here a collection of data from 503 liver cancer genomes from different populations uncovered 30 candidate driver genes and 11 core pathway modules. Furthermore, a collaboration of two large-scale cancer genome projects comparatively analyzed the trans-ancestry substitution signatures in 608 liver cancer cases and identified unique mutational signatures that predominantly contribute to Asian cases. This work elucidates previously unexplored ancestry-associated mutational processes in HCC development. A combination of hotspot TERT promoter mutation, TERT focal amplification and viral genome integration occurs in more than 68% of cases, implicating TERT as a central and ancestry-independent node of hepatocarcinogenesis. Newly identified alterations in genes encoding metabolic enzymes, chromatin remodelers and a high proportion of mTOR pathway activations offer potential therapeutic and diagnostic opportunities.
Keywords: Algorithms; Asian People; Carcinoma, Hepatocellular; CpG Islands; DNA Mutational Analysis; Exome; Gene Expression Regulation, Neoplastic; Genome, Human; Genome, Viral; Hepacivirus; Hepatitis B virus; Humans; Japan; Liver Neoplasms; Models, Statistical; Mutation; Principal Component Analysis; Telomerase; TOR Serine-Threonine Kinases; United States; White People

Untangling the influences of unmodeled evolutionary processes on phylogenetic signal in a forensically important HIV-1 transmission cluster. - Doyle, Vinson P; Andersen, John J; Nelson, Bradley J; Metzker, Michael L; Brown, Jeremy M (Mol Phylogenet Evol, 2014)
Stochastic models of sequence evolution have been developed to reflect many biologically important processes, allowing for accurate phylogenetic reconstruction when an appropriate model is selected. However, commonly used models do not incorporate several potentially important biological processes. Spurious phylogenetic inference may result if these processes play an important role in the evolution of a dataset yet are not incorporated into assumed models. Few studies have attempted to assess the relative importance of multiple processes in producing spurious inferences. The application of phylogenetic methods to infer the source of HIV-1 transmission clusters depends upon accurate phylogenetic results, yet there are several relevant unmodeled biological processes (e.g., recombination and convergence) that may cause complications. Here, through analyses of HIV-1 env sequences from a small, forensically important transmission cluster, we tease apart the impact of these processes and present evidence suggesting that convergent evolution and high rates of insertions and deletions (causing alignment uncertainty) led to spurious phylogenetic signal with forensic relevance. Previous analyses show paraphyly of HIV-1 lineages sampled from an individual who, based on non-phylogenetic evidence, had never acted as a source of infection for others in this transmission cluster. If true, this pattern calls into question assumptions underlying phylogenetic approaches to source and recipient identification. By systematically assessing the contribution of different unmodeled processes, we demonstrate that removal of sites likely influenced by strong positive selection both reduces the alignment-wide signal supporting paraphyly of viruses sampled from this individual and eliminates support for the effects of recombination. Additionally, the removal of ambiguously aligned sites alters strongly supported relationships among viruses sampled from different individuals. These observations highlight the need to jointly consider multiple unmodeled evolutionary processes and motivate a phylogenomic perspective when inferring viral transmission histories.
Keywords: Bayes Theorem; env Gene Products, Human Immunodeficiency Virus; Evolution, Molecular; HIV Infections; HIV-1; Humans; Likelihood Functions; Markov Chains; Models, Genetic; Phylogeny; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

Whole exome sequencing identifies novel genes for fetal hemoglobin response to hydroxyurea in children with sickle cell anemia. - Sheehan, Vivien A; Crosby, Jacy R; Sabo, Aniko; Mortier, Nicole A; Howard, Thad A; Muzny, Donna M; Dugan-Perez, Shannon; Aygun, Banu; Nottage, Kerri A; Boerwinkle, Eric; Gibbs, Richard A; Ware, Russell E; et al. (PLoS One, 2014)
Hydroxyurea has proven efficacy in children and adults with sickle cell anemia (SCA), but with considerable inter-individual variability in the amount of fetal hemoglobin (HbF) produced. Sibling and twin studies indicate that some of that drug response variation is heritable. To test the hypothesis that genetic modifiers influence pharmacological induction of HbF, we investigated phenotype-genotype associations using whole exome sequencing of children with SCA treated prospectively with hydroxyurea to maximum tolerated dose (MTD). We analyzed 171 unrelated patients enrolled in two prospective clinical trials, all treated with dose escalation to MTD. We examined two MTD drug response phenotypes: HbF (final %HbF minus baseline %HbF), and final %HbF. Analyzing individual genetic variants, we identified multiple low frequency and common variants associated with HbF induction by hydroxyurea. A validation cohort of 130 pediatric sickle cell patients treated to MTD with hydroxyurea was genotyped for 13 non-synonymous variants with the strongest association with HbF response to hydroxyurea in the discovery cohort. A coding variant in Spalt-like transcription factor, or SALL2, was associated with higher final HbF in this second independent replication sample and SALL2 represents an outstanding novel candidate gene for further investigation. These findings may help focus future functional studies and provide new insights into the pharmacological HbF upregulation by hydroxyurea in patients with SCA.
Keywords: Anemia, Sickle Cell; Child; Cohort Studies; DNA-Binding Proteins; Dose-Response Relationship, Drug; Exome; Fetal Hemoglobin; Genomics; Humans; Hydroxyurea; Maximum Tolerated Dose; Open Reading Frames; Phenotype; Prospective Studies; Sequence Analysis, DNA; Transcription Factors; Treatment Outcome

Why primate models matter. - Phillips, Kimberley A; Bales, Karen L; Capitanio, John P; Conley, Alan; Czoty, Paul W; 't Hart, Bert A; Hopkins, William D; Hu, Shiu-Lok; Miller, Lisa A; Nader, Michael A; Nathanielsz, Peter W; Rogers, Jeffrey; et al. (Am J Primatol, 2014)
Research involving nonhuman primates (NHPs) has played a vital role in many of the medical and scientific advances of the past century. NHPs are used because of their similarity to humans in physiology, neuroanatomy, reproduction, development, cognition, and social complexity-yet it is these very similarities that make the use of NHPs in biomedical research a considered decision. As primate researchers, we feel an obligation and responsibility to present the facts concerning why primates are used in various areas of biomedical research. Recent decisions in the United States, including the phasing out of chimpanzees in research by the National Institutes of Health and the pending closure of the New England Primate Research Center, illustrate to us the critical importance of conveying why continued research with primates is needed. Here, we review key areas in biomedicine where primate models have been, and continue to be, essential for advancing fundamental knowledge in biomedical and biological research.
Keywords: Animal Experimentation; Animals; Disease Models, Animal; Humans; Primates; United States

Analysis of rare, exonic variation amongst subjects with autism spectrum disorders and population controls. - Liu, Li; Sabo, Aniko; Neale, Benjamin M; Nagaswamy, Uma; Stevens, Christine; Lim, Elaine; Bodea, Corneliu A; Muzny, Donna; Reid, Jeffrey G; Banks, Eric; Coon, Hillary; DePristo, Mark; et al. (PLoS Genet, 2013)
We report on results from whole-exome sequencing (WES) of 1,039 subjects diagnosed with autism spectrum disorders (ASD) and 870 controls selected from the NIMH repository to be of similar ancestry to cases. The WES data came from two centers using different methods to produce sequence and to call variants from it. Therefore, an initial goal was to ensure the distribution of rare variation was similar for data from different centers. This proved straightforward by filtering called variants by fraction of missing data, read depth, and balance of alternative to reference reads. Results were evaluated using seven samples sequenced at both centers and by results from the association study. Next we addressed how the data and/or results from the centers should be combined. Gene-based analyses of association was an obvious choice, but should statistics for association be combined across centers (meta-analysis) or should data be combined and then analyzed (mega-analysis)? Because of the nature of many gene-based tests, we showed by theory and simulations that mega-analysis has better power than meta-analysis. Finally, before analyzing the data for association, we explored the impact of population structure on rare variant analysis in these data. Like other recent studies, we found evidence that population structure can confound case-control studies by the clustering of rare variants in ancestry space; yet, unlike some recent studies, for these data we found that principal component-based analyses were sufficient to control for ancestry and produce test statistics with appropriate distributions. After using a variety of gene-based tests and both meta- and mega-analysis, we found no new risk genes for ASD in this sample. Our results suggest that standard gene-based tests will require much larger samples of cases and controls before being effective for gene discovery, even for a disorder like ASD.
Keywords: Case-Control Studies; Child; Child Development Disorders, Pervasive; Exome; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Population Control; Sequence Analysis, DNA; Software

APOE modulates the correlation between triglycerides, cholesterol, and CHD through pleiotropy, and gene-by-gene interactions. - Maxwell, Taylor J; Ballantyne, Christie M; Cheverud, James M; Guild, Cameron S; Ndumele, Chiadi E; Boerwinkle, Eric (Genetics, 2013)
Relationship loci (rQTL) exist when the correlation between multiple traits varies by genotype. rQTL often occur due to gene-by-gene (G × G) or gene-by-environmental interactions, making them a powerful tool for detecting G × G. Here we present an empirical analysis of apolipoprotein E (APOE) with respect to lipid traits and incident CHD leading to the discovery of loci that interact with APOE to affect these traits. We found that the relationship between total cholesterol (TC) and triglycerides (ln TG) varies by APOE isoform genotype in African-American (AA) and European-American (EA) populations. The e2 allele is associated with strong correlation between ln TG and TC while the e4 allele leads to little or no correlation. This led to a priori hypotheses that APOE genotypes affect the relationship of TC and/or ln TG with incident CHD. We found that APOE*TC was significant (P = 0.016) for AA but not EA while APOE*ln TG was significant for EA (P = 0.027) but not AA. In both cases, e2e2 and e2e3 had strong relationships between TC and ln TG with CHD while e2e4 and e4e4 results in little or no relationship between TC and ln TG with CHD. Using ARIC GWAS data, scans for loci that significantly interact with APOE produced four loci for African Americans (one CHD, one TC, and two HDL). These interactions contribute to the rQTL pattern. rQTL are a powerful tool to identify loci that modify the relationship between risk factors and disease and substantially increase statistical power for detecting G × G.
Keywords: Alleles; Apolipoproteins E; Black or African American; Cholesterol; Coronary Disease; Epistasis, Genetic; Female; Genetic Pleiotropy; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Triglycerides; White People

Assemblathon 2: evaluating de novo methods of genome assembly in three vertebrate species. - Bradnam, Keith R; Fass, Joseph N; Alexandrov, Anton; Baranay, Paul; Bechner, Michael; Birol, Inanç; Boisvert, Sébastien; Chapman, Jarrod A; Chapuis, Guillaume; Chikhi, Rayan; Chitsaz, Hamidreza; Chou, Wen-Chi; et al. (Gigascience, 2013)
BACKGROUND: The process of generating raw genome sequence data continues to become cheaper, faster, and more accurate. However, assembly of such data into high-quality, finished genome sequences remains challenging. Many genome assembly tools are available, but they differ greatly in terms of their performance (speed, scalability, hardware requirements, acceptance of newer read technologies) and in their final output (composition of assembled sequence). More importantly, it remains largely unclear how to best assess the quality of assembled genome sequences. The Assemblathon competitions are intended to assess current state-of-the-art methods in genome assembly. RESULTS: In Assemblathon 2, we provided a variety of sequence data to be assembled for three vertebrate species (a bird, a fish, and snake). This resulted in a total of 43 submitted assemblies from 21 participating teams. We evaluated these assemblies using a combination of optical map data, Fosmid sequences, and several statistical methods. From over 100 different metrics, we chose ten key measures by which to assess the overall quality of the assemblies. CONCLUSIONS: Many current genome assemblers produced useful assemblies, containing a significant representation of their genes and overall genome structure. However, the high degree of variability between the entries suggests that there is still much room for improvement in the field of genome assembly and that approaches which work well in assembling the genome of one species may not necessarily work well for another.

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: Atherosclerosis; Black People; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T; White People

Associations between metabolomic compounds and incident heart failure among African Americans: the ARIC Study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Manolio, Teri A; Aguilar, David; Coresh, Josef; Heiss, Gerardo; Boerwinkle, Eric; Nettleton, Jennifer A (Am J Epidemiol, 2013)
Heart failure is more prevalent among African Americans than in the general population. Metabolomic studies among African Americans may efficiently identify novel biomarkers of heart failure. We used untargeted methods to measure 204 stable serum metabolites and evaluated their associations with incident heart failure hospitalization (n = 276) after a median follow-up of 20 years (1987-2008) by using Cox regression in data from 1,744 African Americans aged 45-64 years without heart failure at baseline from the Jackson, Mississippi, field center of the Atherosclerosis Risk in Communities (ARIC) Study. After adjustment for established risk factors, we found that 16 metabolites (6 named with known structural identities and 10 unnamed with unknown structural identities, the latter denoted by using the format X-12345) were associated with incident heart failure (P < 0.0004 based on a modified Bonferroni procedure). Of the 6 named metabolites, 4 are involved in amino acid metabolism, 1 (prolylhydroxyproline) is a dipeptide, and 1 (erythritol) is a sugar alcohol. After additional adjustment for kidney function, 2 metabolites remained associated with incident heart failure (for metabolite X-11308, hazard ratio = 0.75, 95% confidence interval: 0.65, 0.86; for metabolite X-11787, hazard ratio = 1.23, 95% confidence interval: 1.10, 1.37). Further structural analysis revealed X-11308 to be a dihydroxy docosatrienoic acid and X-11787 to be an isoform of either hydroxyleucine or hydroxyisoleucine. Our metabolomic analysis revealed novel biomarkers associated with incident heart failure independent of traditional risk factors.
Keywords: Age Distribution; Atherosclerosis; Biomarkers; Black or African American; Comorbidity; Diabetes Mellitus; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Kidney Diseases; Male; Metabolomics; Middle Aged; Mississippi; Obesity; Proportional Hazards Models; Sedentary Behavior

Bacterial discrimination by dictyostelid amoebae reveals the complexity of ancient interspecies interactions. - Nasser, Waleed; Santhanam, Balaji; Miranda, Edward Roshan; Parikh, Anup; Juneja, Kavina; Rot, Gregor; Dinh, Chris; Chen, Rui; Zupan, Blaz; Shaulsky, Gad; Kuspa, Adam (Curr Biol, 2013)
BACKGROUND: Amoebae and bacteria interact within predator-prey and host-pathogen relationships, but the general response of amoeba to bacteria is not well understood. The amoeba Dictyostelium discoideum feeds on, and is colonized by, diverse bacterial species, including Gram-positive [Gram(+)] and Gram-negative [Gram(-)] bacteria, two major groups of bacteria that differ in structure and macromolecular composition. RESULTS: Transcriptional profiling of D. discoideum revealed sets of genes whose expression is enriched in amoebae interacting with different species of bacteria, including sets that appear specific to amoebae interacting with Gram(+) or with Gram(-) bacteria. In a genetic screen utilizing the growth of mutant amoebae on a variety of bacteria as a phenotypic readout, we identified amoebal genes that are only required for growth on Gram(+) bacteria, including one that encodes the cell-surface protein gp130, as well as several genes that are only required for growth on Gram(-) bacteria, including one that encodes a putative lysozyme, AlyL. These genes are required for parts of the transcriptional response of wild-type amoebae, and this allowed their classification into potential response pathways. CONCLUSIONS: We have defined genes that are critical for amoebal survival during feeding on Gram(+), or Gram(-), bacteria that we propose form part of a regulatory network that allows D. discoideum to elicit specific cellular responses to different species of bacteria in order to optimize survival.
Keywords: Dictyostelium; Gene Expression Profiling; Genes, Bacterial; Genes, Protozoan; Gram-Negative Bacteria; Gram-Positive Bacteria; Host-Pathogen Interactions; Mutation; Transcription, Genetic

Bioactivity and bioavailability of ginsenosides are dependent on the glycosidase activities of the A/J mouse intestinal microbiome defined by pyrosequencing. - Niu, Tao; Smith, Diane L; Yang, Zhen; Gao, Song; Yin, Taijun; Jiang, Zhi-Hong; You, Ming; Gibbs, Richard A; Petrosino, Joseph F; Hu, Ming (Pharm Res, 2013)
PURPOSE: To investigate the ability of bacteria in the intestinal microbiome to convert naturally occurring primary ginsenosides in red ginseng extract to active secondary ginsenosides. METHODS: Anti-proliferative ginsenoside activity was tested using mouse lung cancer LM1 cells. Permeabilities were evaluated in Caco-2 cell monolayers. Systemic exposure of secondary ginsenosides was determined in A/J mice. 16S rRNA gene pyrosequencing was used to determine membership and abundance of bacteria in intestinal microbiome. RESULTS: Secondary ginsenoside C-K exhibited higher anti-proliferative activity and permeability than primary ginsenosides. Significant amounts of secondary ginsenosides (F2 and C-K) were found in blood of A/J mice following oral administration of primary ginsenoside Rb1. Because mammalian cells did not hydrolyze ginsenoside, we determined the ability of bacteria to hydrolyze ginsenosides and found that Rb1 underwent stepwise hydrolysis to Rd, F2, and then C-K. Formation of F2 from Rd was the rate-limiting step in the biotransformation of Rb1 to C-K. CONCLUSION: Conversion to F2 is the rate-limiting step in bioactivation of primary ginsenosides by A/J mouse intestinal microbiome, whose characterization reveals the presence of certain bacterial families capable of enabling the formation of F2 and C-K in vivo.
Keywords: Animals; Antineoplastic Agents, Phytogenic; Bacteria; Biological Availability; Biotransformation; Caco-2 Cells; Cell Line, Tumor; Cell Proliferation; Drugs, Chinese Herbal; Ginsenosides; Glycoside Hydrolases; Humans; Hydrolysis; Intestinal Mucosa; Intestines; Male; Metagenome; Mice; Neoplasms; Panax; RNA, Bacterial

Characterization of transcriptomes from sexual and asexual lineages of a New Zealand snail (Potamopyrgus antipodarum). - Wilton, Peter R; Sloan, Daniel B; Logsdon, John M; Harshavardhan Doddapaneni; Neiman, Maurine (Mol Ecol Resour, 2013)
Understanding the evolution and maintenance of sexual reproduction is one of the central challenges of evolutionary biology, yet we know very little about how sex influences molecular evolution. The New Zealand freshwater snail Potamopyrgus antipodarum is ideally suited to address this knowledge gap because obligately sexual individuals often coexist with multiple independently derived obligately asexual lineages. This unusual situation allows direct comparisons both between sexual and asexual P. antipodarum and across populations that differ in the relative frequency of sexual individuals. As such, P. antipodarum has received a great deal of attention as a model system for the maintenance of sex in nature and is also used as a model for environmental toxicology and biological invasions. Molecular genetic resources for P. antipodarum will thus be useful to investigators in a variety of biological fields. We used 454 sequencing of cDNA libraries to generate transcriptomes from two sexual and two asexual P. antipodarum lineages. A de novo assembly of 116.7 Mb of sequence reads produced 41 396 contigs, and sequence similarity-based Gene Ontology annotations were obtained for 3740 contigs. We detected 408 315 SNP loci and 7315 microsatellite loci, which together represent the first genome-scale resource available for P. antipodarum. Raw 454 read sequences, contig sequences, annotation data and polymorphism data are publicly available in a searchable online database and for download at http://www.biology.uiowa.edu/neiman/transcriptome.php.
Keywords: Animals; Expressed Sequence Tags; Microsatellite Repeats; Phylogeny; Reproduction; Reproduction, Asexual; Sequence Analysis, DNA; Snails; Transcriptome

Combined sequence-based and genetic mapping analysis of complex traits in outbred rats. - Baud, Amelie; Hermsen, Roel; Guryev, Victor; Stridh, Pernilla; Graham, Delyth; McBride, Martin W; Foroud, Tatiana; Calderari, Sophie; Diez, Margarita; Ockinger, Johan; Beyeen, Amennai D; Gillett, Alan; et al. (Nat Genet, 2013)
Genetic mapping on fully sequenced individuals is transforming understanding of the relationship between molecular variation and variation in complex traits. Here we report a combined sequence and genetic mapping analysis in outbred rats that maps 355 quantitative trait loci for 122 phenotypes. We identify 35 causal genes involved in 31 phenotypes, implicating new genes in models of anxiety, heart disease and multiple sclerosis. The relationship between sequence and genetic variation is unexpectedly complex: at approximately 40% of quantitative trait loci, a single sequence variant cannot account for the phenotypic effect. Using comparable sequence and mapping data from mice, we show that the extent and spatial pattern of variation in inbred rats differ substantially from those of inbred mice and that the genetic variants in orthologous genes rarely contribute to the same phenotype in both species.
Keywords: Animals; Animals, Outbred Strains; Anxiety; Chromosome Mapping; Genetic Variation; Genotype; Heart Diseases; Humans; Mice; Mice, Inbred C57BL; Models, Molecular; Multiple Sclerosis; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Sequence Analysis, DNA

Evidence for replicative mechanism in a CHD7 rearrangement in a patient with CHARGE syndrome. - Vatta, Matteo; Niu, Zhiyv; Lupski, James R; Putnam, Philip; Spoonamore, Katherine G; Fang, Ping; Eng, Christine M; Willis, Alecia S (Am J Med Genet A, 2013)
Haploinsufficiency of CHD7 (OMIM# 608892) is known to cause CHARGE syndrome (OMIM# 214800). Molecular testing supports a definitive diagnosis in approximately 65-70% of cases. Most CHD7 mutations arise de novo, and no mutations affecting exon-7 have been reported to date. We report on an 8-year-old girl diagnosed with CHARGE syndrome that was referred to our laboratory for comprehensive CHD7 gene screening. Genomic DNA from the subject with a suspected diagnosis of CHARGE was isolated from peripheral blood lymphocytes and comprehensive Sanger sequencing, along with deletion/duplication analysis of the CHD7 gene using multiplex ligation-dependent probe amplification (MLPA), was performed. MLPA analysis identified a reduced single probe signal for exon-7 of the CHD7 gene consistent with potential heterozygous deletion. Long-range PCR breakpoint analysis identified a complex genomic rearrangement (CGR) leading to the deletion of exon-7 and breakpoints consistent with a replicative mechanism such as fork stalling and template switching (FoSTeS) or microhomology-mediated break-induced replication (MMBIR). Taken together this represents the first evidence for a CHD7 intragenic CGR in a patient with CHARGE syndrome leading to what appears to be also the first report of a mutation specifically disrupting exon-7. Although likely rare, CGR may represent an overlooked mechanism in subjects with CHARGE syndrome that can be missed by current sequencing and dosage assays.
Keywords: Abnormalities, Multiple; CHARGE Syndrome; Child; DNA Helicases; DNA Replication; DNA-Binding Proteins; Exons; Female; Gene Deletion; Haploinsufficiency; Humans; Mutation

Fat mass and obesity gene and cognitive decline: the Atherosclerosis Risk in Communities Study. - Bressler, Jan; Fornage, Myriam; Demerath, Ellen W; Knopman, David S; Monda, Keri L; North, Kari E; Penman, Alan; Mosley, Thomas H; Boerwinkle, Eric (Neurology, 2013)
OBJECTIVE: To determine whether 4 genetic variants in the fat mass and obesity associated gene (FTO) identified in genome-wide association studies of diabetes and obesity are associated with cognitive change in midlife in the Atherosclerosis Risk in Communities (ARIC) Study. METHODS: ARIC is a prospective cohort study of the development of atherosclerosis in 15,792 individuals aged 45 to 64 years at baseline from 1986 to 1989. FTO is highly expressed in human fetal and adult brain, and a single nucleotide polymorphism in FTO has previously been associated with reduced brain volume in cognitively normal subjects. Since a relationship between brain atrophy and diminished cognitive function has been demonstrated in ARIC participants, general linear models were used to evaluate the association between 6-year change in scores on 3 neuropsychological tests and FTO genotype. RESULTS: In a sample of 8,364 white and 2,083 African American men and women with no clinical history of stroke, significantly greater mean change in performance on the Delayed Word Recall Test was associated with 2 of 4 FTO single nucleotide polymorphisms examined (rs9939609, rs805136, rs17817449, and rs1421085) in whites but not in African Americans (p ≤ 0.002). The association of the FTO polymorphisms with cognitive change was independent of potential confounding clinical and demographic variables including age, gender, education, diabetes, hypertension, and body mass index. CONCLUSIONS: Further studies will be needed to clarify the biological mechanisms and genetic pathways through which variants in FTO can increase susceptibility to decline in verbal memory detectable in middle-aged, community-dwelling adults.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Black or African American; Body Mass Index; Cognition Disorders; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Prospective Studies; Proteins; White People

Genome-wide analysis of stepwise hepatocarcinogenesis using next generation sequencer. - Midorikawa, Yutaka; Takayama, Tadatoshi; Yamamoto, Shogo; Ueda, Hiroo; Sonoda, Kohtaro; Takane, Kiyoko; Tsuji, Shingo; Nagae, Genta; Tatsuno, Kenji; Morgan, Margaret; David A Wheeler; Aburatani, Hiroyuki (AACR 104th Annual Meeting 2013, 2013)
Early hepatocellular carcinoma (HCC) originates from the hepatocytes of chronic liver disease and develops into classical HCC. To identify sequential genomic changes in multistep hepatocarcinogenesis, we analyzed fusion genes and mutations using next generation sequencer about 40 early and 80 advanced HCCs. First, exome sequence showed that base sequence aberrations were more frequent in advanced HCC than early HCC, and mutations including TP53 (24%), CTNNB1 (24%), and ARID1A (16%) were recurrently observed in both early and advanced HCCs. Consistent with our previous report homozygous deletions near CSMD1 and CDKN2A were also found in 8 and 5 cases, respectively, only in advanced HCC. Next, we detected 4 types of fusion gene, including interchromosomal (translocation), intrachromosomal (deletion), intrachromosomal (translocation), and inversion by RNA sequencing. We also found that every HCC harbored 2 to 5 fusion genes, which were more frequent in advanced than early HCC, although there were no recurrent rearrangements in neither advanced nor early HCCs. Especially chromathripsis, in which 10 to 100 rearrangements were localized in the specific genomic regions and genomic features imply chromosome breaks occur in one-off crisis, was the event observed only in advanced HCC. Taken together, genomic changes were more frequent in advanced HCC, suggesting early HCC originates in the chronic liver disease and progresses into advanced HCC with genomic aberrations.

Genome-wide association study of a heart failure related metabolomic profile among African Americans in the Atherosclerosis Risk in Communities (ARIC) study. - Yu, Bing; Zheng, Yan; Alexander, Danny; Manolio, Teri A; Alonso, Alvaro; Nettleton, Jennifer A; Boerwinkle, Eric (Genet Epidemiol, 2013)
Both the prevalence and incidence of heart failure (HF) are increasing, especially among African Americans, but no large-scale, genome-wide association study (GWAS) of HF-related metabolites has been reported. We sought to identify novel genetic variants that are associated with metabolites previously reported to relate to HF incidence. GWASs of three metabolites identified previously as risk factors for incident HF (pyroglutamine, dihydroxy docosatrienoic acid, and X-11787, being either hydroxy-leucine or hydroxy-isoleucine) were performed in 1,260 African Americans free of HF at the baseline examination of the Atherosclerosis Risk in Communities (ARIC) study. A significant association on chromosome 5q33 (rs10463316, MAF = 0.358, P-value = 1.92 × 10(-10) ) was identified for pyroglutamine. One region on chromosome 2p13 contained a nonsynonymous substitution in N-acetyltransferase 8 (NAT8) was associated with X-11787 (rs13538, MAF = 0.481, P-value = 1.71 × 10(-23) ). The smallest P-value for dihydroxy docosatrienoic acid was rs4006531 on chromosome 8q24 (MAF = 0.400, P-value = 6.98 × 10(-7) ). None of the above SNPs were individually associated with incident HF, but a genetic risk score (GRS) created by summing the most significant risk alleles from each metabolite detected 11% greater risk of HF per allele. In summary, we identified three loci associated with previously reported HF-related metabolites. Further use of metabolomics technology will facilitate replication of these findings in independent samples.
Keywords: Acetyltransferases; Alleles; Atherosclerosis; Black or African American; Chromosomes, Human, Pair 2; Chromosomes, Human, Pair 5; Cohort Studies; Fatty Acids, Unsaturated; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Isoleucine; Leucine; Male; Metabolome; Metabolomics; Middle Aged; Polymorphism, Single Nucleotide; Pyrrolidonecarboxylic Acid; Risk Factors

Integrative genomic characterization of oral squamous cell carcinoma identifies frequent somatic drivers. - Pickering, Curtis R; Zhang, Jiexin; Yoo, Suk Young; Bengtsson, Linnea; Moorthy, Shhyam; Neskey, David M; Zhao, Mei; Ortega Alves, Marcus V; Chang, Kyle; Drummond, Jennifer; Cortez, Elsa; Xie, Tong-Xin; et al. (Cancer Discov, 2013)
The survival of patients with oral squamous cell carcinoma (OSCC) has not changed significantly in several decades, leading clinicians and investigators to search for promising molecular targets. To this end, we conducted comprehensive genomic analysis of gene expression, copy number, methylation, and point mutations in OSCC. Integrated analysis revealed more somatic events than previously reported, identifying four major driver pathways (mitogenic signaling, Notch, cell cycle, and TP53) and two additional key genes (FAT1, CASP8). The Notch pathway was defective in 66% of patients, and in follow-up studies of mechanism, functional NOTCH1 signaling inhibited proliferation of OSCC cell lines. Frequent mutation of caspase-8 (CASP8) defines a new molecular subtype of OSCC with few copy number changes. Although genomic alterations are dominated by loss of tumor suppressor genes, 80% of patients harbored at least one genomic alteration in a targetable gene, suggesting that novel approaches to treatment may be possible for this debilitating subset of head and neck cancers.
Keywords: Carcinoma, Squamous Cell; Caspase 8; Cell Line, Tumor; DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Genomics; Humans; Mouth Neoplasms; Point Mutation; Receptors, Notch

Metabolomics and incident hypertension among blacks: the atherosclerosis risk in communities study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Mosley, Thomas H; Heiss, Gerardo; Nettleton, Jennifer A; Boerwinkle, Eric (Hypertension, 2013)
Development of hypertension is influenced by genes, environmental effects, and their interactions, and the human metabolome is a measurable manifestation of gene-environment interaction. We explored the metabolomic antecedents of developing incident hypertension in a sample of blacks, a population with a high prevalence of hypertension and its comorbidities. We examined 896 black normotensives (565 women; aged, 45-64 years) from the Atherosclerosis Risk in Communities study, whose metabolome was measured in serum collected at the baseline examination and analyzed by high-throughput methods. The analyses presented here focus on 204 stably measured metabolites during a period of 4 to 6 weeks. Weibull parametric models considering interval censored data were used to assess the hazard ratio for incident hypertension. We used a modified Bonferroni correction accounting for the correlations among metabolites to define a threshold for statistical significance (P<3.9 × 10(-4)). During 10 years of follow-up, 38% of baseline normotensives developed hypertension (n=344). With adjustment for traditional risk factors and estimated glomerular filtration rate, each +1SD difference in baseline 4-hydroxyhippurate, a product of gut microbial fermentation, was associated with 17% higher risk of hypertension (P=2.5 × 10(-4)), which remained significant after adjusting for both baseline systolic and diastolic blood pressure (P=3.8 × 10(-4)). After principal component analyses, a sex steroids pattern was significantly associated with risk of incident hypertension (highest versus lowest quintile hazard ratio, 1.72; 95% confidence interval, 1.05-2.82; P for trend, 0.03), and stratified analyses suggested that this association was consistent in both sexes. Metabolomic analyses identify novel pathways in the pathogenesis of hypertension.
Keywords: Atherosclerosis; Black People; Female; High-Throughput Screening Assays; Humans; Hypertension; Male; Metabolomics; Middle Aged; Principal Component Analysis; Risk Factors

Mutations in KCTD1 cause scalp-ear-nipple syndrome. - Marneros, Alexander G; Beck, Anita E; Turner, Emily H; McMillin, Margaret J; Edwards, Matthew J; Field, Michael; de Macena Sobreira, Nara Lygia; Perez, Ana Beatriz A; Fortes, Jose A R; Lampe, Anne K; Giovannucci Uzielli, Maria Luisa; Gordon, Christopher T; et al. (Am J Hum Genet, 2013)
Scalp-ear-nipple (SEN) syndrome is a rare, autosomal-dominant disorder characterized by cutis aplasia of the scalp; minor anomalies of the external ears, digits, and nails; and malformations of the breast. We used linkage analysis and exome sequencing of a multiplex family affected by SEN syndrome to identify potassium-channel tetramerization-domain-containing 1 (KCTD1) mutations that cause SEN syndrome. Evaluation of a total of ten families affected by SEN syndrome revealed KCTD1 missense mutations in each family tested. All of the mutations occurred in a KCTD1 region encoding a highly conserved bric-a-brac, tram track, and broad complex (BTB) domain that is required for transcriptional repressor activity. KCTD1 inhibits the transactivation of the transcription factor AP-2α (TFAP2A) via its BTB domain, and mutations in TFAP2A cause cutis aplasia in individuals with branchiooculofacial syndrome (BOFS), suggesting a potential overlap in the pathogenesis of SEN syndrome and BOFS. The identification of KCTD1 mutations in SEN syndrome reveals a role for this BTB-domain-containing transcriptional repressor during ectodermal development.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Branchio-Oto-Renal Syndrome; Co-Repressor Proteins; Ear, External; Ectodermal Dysplasia; Exome; Female; Humans; Hypospadias; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation, Missense; Nipples; Pedigree; Phenotype; Protein Structure, Tertiary; Repressor Proteins; Scalp; Sequence Homology, Amino Acid

Rare complete knockouts in humans: population distribution and significant role in autism spectrum disorders. - Lim, Elaine T; Raychaudhuri, Soumya; Sanders, Stephan J; Stevens, Christine; Sabo, Aniko; MacArthur, Daniel G; Neale, Benjamin M; Kirby, Andrew; Ruderfer, Douglas M; Fromer, Menachem; Lek, Monkol; Liu, Li; et al. (Neuron, 2013)
To characterize the role of rare complete human knockouts in autism spectrum disorders (ASDs), we identify genes with homozygous or compound heterozygous loss-of-function (LoF) variants (defined as nonsense and essential splice sites) from exome sequencing of 933 cases and 869 controls. We identify a 2-fold increase in complete knockouts of autosomal genes with low rates of LoF variation (≤ 5% frequency) in cases and estimate a 3% contribution to ASD risk by these events, confirming this observation in an independent set of 563 probands and 4,605 controls. Outside the pseudoautosomal regions on the X chromosome, we similarly observe a significant 1.5-fold increase in rare hemizygous knockouts in males, contributing to another 2% of ASDs in males. Taken together, these results provide compelling evidence that rare autosomal and X chromosome complete gene knockouts are important inherited risk factors for ASD.
Keywords: Case-Control Studies; Child Development Disorders, Pervasive; Child, Preschool; Chromosomes, Human, X; Demography; Female; Gene Deletion; Genetic Variation; Homozygote; Humans; Linkage Disequilibrium; Loss of Heterozygosity; Male; Risk Factors

A recurrent germline PAX5 mutation confers susceptibility to pre-B cell acute lymphoblastic leukemia. - Shah, Sohela; Schrader, Kasmintan A; Waanders, Esmé; Timms, Andrew E; Vijai, Joseph; Miething, Cornelius; Wechsler, Jeremy; Yang, Jun; Hayes, James; Klein, Robert J; Zhang, Jinghui; Wei, Lei; et al. (Nat Genet, 2013)
Somatic alterations of the lymphoid transcription factor gene PAX5 (also known as BSAP) are a hallmark of B cell precursor acute lymphoblastic leukemia (B-ALL), but inherited mutations of PAX5 have not previously been described. Here we report a new heterozygous germline variant, c.547G>A (p.Gly183Ser), affecting the octapeptide domain of PAX5 that was found to segregate with disease in two unrelated kindreds with autosomal dominant B-ALL. Leukemic cells from all affected individuals in both families exhibited 9p deletion, with loss of heterozygosity and retention of the mutant PAX5 allele at 9p13. Two additional sporadic ALL cases with 9p loss harbored somatic PAX5 substitutions affecting Gly183. Functional and gene expression analysis of the PAX5 mutation demonstrated that it had significantly reduced transcriptional activity. These data extend the role of PAX5 alterations in the pathogenesis of pre-B cell ALL and implicate PAX5 in a new syndrome of susceptibility to pre-B cell neoplasia.
Keywords: Genetic Predisposition to Disease; Germ-Line Mutation; Humans; PAX5 Transcription Factor; Polymorphism, Single Nucleotide; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma

RNA interference knockdown of DNA methyl-transferase 3 affects gene alternative splicing in the honey bee. - Li-Byarlay, Hongmei; Li, Yang; Stroud, Hume; Feng, Suhua; Newman, Thomas C; Kaneda, Megan; Hou, Kirk K; Worley, Kim C; Elsik, Christine G; Wickline, Samuel A; Jacobsen, Steven E; Ma, Jian; et al. (Proc Natl Acad Sci U S A, 2013)
Studies of DNA methylation from fungi, plants, and animals indicate that gene body methylation is ancient and highly conserved in eukaryotic genomes, but its role has not been clearly defined. It has been postulated that regulation of alternative splicing of transcripts was an original function of DNA methylation, but a direct experimental test of the effect of methylation on alternative slicing at the whole genome level has never been performed. To do this, we developed a unique method to administer RNA interference (RNAi) in a high-throughput and noninvasive manner and then used it to knock down the expression of DNA methyl-transferase 3 (dnmt3), which is required for de novo DNA methylation. We chose the honey bee (Apis mellifera) for this test because it has recently emerged as an important model organism for studying the effects of DNA methylation on development and social behavior, and DNA methylation in honey bees is predominantly on gene bodies. Here we show that dnmt3 RNAi decreased global genomic methylation level as expected and in addition caused widespread and diverse changes in alternative splicing in fat tissue. Four different types of splicing events were affected by dnmt3 gene knockdown, and change in two types, exon skipping and intron retention, was directly related to decreased methylation. These results demonstrate that one function of gene body DNA methylation is to regulate alternative splicing.
Keywords: Alternative Splicing; Animals; Bees; Behavior, Animal; DNA (Cytosine-5-)-Methyltransferases; DNA Methylation; Gene Knockdown Techniques; Insect Proteins; RNA Interference; Social Behavior

The Centers for Mendelian Genomics: a new large-scale initiative to identify the genes underlying rare Mendelian conditions. - Bamshad, Michael J; Shendure, Jay A; Valle, David; Hamosh, Ada; Lupski, James R; Gibbs, Richard A; Boerwinkle, Eric; Lifton, Richard P; Gerstein, Mark; Gunel, Murat; Mane, Shrikant; Nickerson, Deborah A (Am J Med Genet A, 2012)
Next generation exome sequencing (ES) and whole genome sequencing (WGS) are new powerful tools for discovering the gene(s) that underlie Mendelian disorders. To accelerate these discoveries, the National Institutes of Health has established three Centers for Mendelian Genomics (CMGs): the Center for Mendelian Genomics at the University of Washington; the Center for Mendelian Genomics at Yale University; and the Baylor-Johns Hopkins Center for Mendelian Genomics at Baylor College of Medicine and Johns Hopkins University. The CMGs will provide ES/WGS and extensive analysis expertise at no cost to collaborating investigators where the causal gene(s) for a Mendelian phenotype has yet to be uncovered. Over the next few years and in collaboration with the global human genetics community, the CMGs hope to facilitate the identification of the genes underlying a very large fraction of all Mendelian disorders; see http://mendelian.org.
Keywords: Academies and Institutes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Humans

Complete genome sequence of Enterococcus faecium strain TX16 and comparative genomic analysis of Enterococcus faecium genomes. - Qin, Xiang; Galloway-Peña, Jessica R; Sillanpaa, Jouko; Roh, Jung Hyeob; Nallapareddy, Sreedhar R; Chowdhury, Shahreen; Bourgogne, Agathe; Choudhury, Tina; Muzny, Donna M; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon; et al. (BMC Microbiol, 2012)
BACKGROUND: Enterococci are among the leading causes of hospital-acquired infections in the United States and Europe, with Enterococcus faecalis and Enterococcus faecium being the two most common species isolated from enterococcal infections. In the last decade, the proportion of enterococcal infections caused by E. faecium has steadily increased compared to other Enterococcus species. Although the underlying mechanism for the gradual replacement of E. faecalis by E. faecium in the hospital environment is not yet understood, many studies using genotyping and phylogenetic analysis have shown the emergence of a globally dispersed polyclonal subcluster of E. faecium strains in clinical environments. Systematic study of the molecular epidemiology and pathogenesis of E. faecium has been hindered by the lack of closed, complete E. faecium genomes that can be used as references. RESULTS: In this study, we report the complete genome sequence of the E. faecium strain TX16, also known as DO, which belongs to multilocus sequence type (ST) 18, and was the first E. faecium strain ever sequenced. Whole genome comparison of the TX16 genome with 21 E. faecium draft genomes confirmed that most clinical, outbreak, and hospital-associated (HA) strains (including STs 16, 17, 18, and 78), in addition to strains of non-hospital origin, group in the same clade (referred to as the HA clade) and are evolutionally considerably more closely related to each other by phylogenetic and gene content similarity analyses than to isolates in the community-associated (CA) clade with approximately a 3-4% average nucleotide sequence difference between the two clades at the core genome level. Our study also revealed that many genomic loci in the TX16 genome are unique to the HA clade. 380 ORFs in TX16 are HA-clade specific and antibiotic resistance genes are enriched in HA-clade strains. Mobile elements such as IS16 and transposons were also found almost exclusively in HA strains, as previously reported. CONCLUSIONS: Our findings along with other studies show that HA clonal lineages harbor specific genetic elements as well as sequence differences in the core genome which may confer selection advantages over the more heterogeneous CA E. faecium isolates. Which of these differences are important for the success of specific E. faecium lineages in the hospital environment remain(s) to be determined.
Keywords: DNA, Bacterial; Enterococcus faecium; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA

Cyanophora paradoxa genome elucidates origin of photosynthesis in algae and plants. - Price, Dana C; Chan, Cheong Xin; Yoon, Hwan Su; Yang, Eun Chan; Qiu, Huan; Weber, Andreas P M; Schwacke, Rainer; Gross, Jeferson; Blouin, Nicolas A; Lane, Chris; Reyes-Prieto, Adrián; Durnford, Dion G; et al. (Science, 2012)
The primary endosymbiotic origin of the plastid in eukaryotes more than 1 billion years ago led to the evolution of algae and plants. We analyzed draft genome and transcriptome data from the basally diverging alga Cyanophora paradoxa and provide evidence for a single origin of the primary plastid in the eukaryote supergroup Plantae. C. paradoxa retains ancestral features of starch biosynthesis, fermentation, and plastid protein translocation common to plants and algae but lacks typical eukaryotic light-harvesting complex proteins. Traces of an ancient link to parasites such as Chlamydiae were found in the genomes of C. paradoxa and other Plantae. Apparently, Chlamydia-like bacteria donated genes that allow export of photosynthate from the plastid and its polymerization into storage polysaccharide in the cytosol.
Keywords: Biological Evolution; Cyanobacteria; Cyanophora; Evolution, Molecular; Gene Transfer, Horizontal; Genes, Bacterial; Genome, Plant; Molecular Sequence Data; Photosynthesis; Phylogeny; Symbiosis

The Drosophila melanogaster Genetic Reference Panel. - Mackay, Trudy F C; Richards, Stephen; Stone, Eric A; Barbadilla, Antonio; Ayroles, Julien F; Zhu, Dianhui; Casillas, Sònia; Han, Yi; Magwire, Michael M; Cridland, Julie M; Richardson, Mark F; Anholt, Robert R H; et al. (Nature, 2012)
A major challenge of biology is understanding the relationship between molecular genetic variation and variation in quantitative traits, including fitness. This relationship determines our ability to predict phenotypes from genotypes and to understand how evolutionary forces shape variation within and between species. Previous efforts to dissect the genotype-phenotype map were based on incomplete genotypic information. Here, we describe the Drosophila melanogaster Genetic Reference Panel (DGRP), a community resource for analysis of population genomics and quantitative traits. The DGRP consists of fully sequenced inbred lines derived from a natural population. Population genomic analyses reveal reduced polymorphism in centromeric autosomal regions and the X chromosome, evidence for positive and negative selection, and rapid evolution of the X chromosome. Many variants in novel genes, most at low frequency, are associated with quantitative traits and explain a large fraction of the phenotypic variance. The DGRP facilitates genotype-phenotype mapping using the power of Drosophila genetics.
Keywords: Alleles; Animals; Centromere; Chromosomes, Insect; Drosophila melanogaster; Genome-Wide Association Study; Genomics; Genotype; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Starvation; Telomere; X Chromosome

Exome capture reveals ZNF423 and CEP164 mutations, linking renal ciliopathies to DNA damage response signaling. - Chaki, Moumita; Airik, Rannar; Ghosh, Amiya K; Giles, Rachel H; Chen, Rui; Slaats, Gisela G; Wang, Hui; Hurd, Toby W; Zhou, Weibin; Cluckey, Andrew; Gee, Heon Yung; Ramaswami, Gokul; et al. (Cell, 2012)
Nephronophthisis-related ciliopathies (NPHP-RC) are degenerative recessive diseases that affect kidney, retina, and brain. Genetic defects in NPHP gene products that localize to cilia and centrosomes defined them as "ciliopathies." However, disease mechanisms remain poorly understood. Here, we identify by whole-exome resequencing, mutations of MRE11, ZNF423, and CEP164 as causing NPHP-RC. All three genes function within the DNA damage response (DDR) pathway. We demonstrate that, upon induced DNA damage, the NPHP-RC proteins ZNF423, CEP164, and NPHP10 colocalize to nuclear foci positive for TIP60, known to activate ATM at sites of DNA damage. We show that knockdown of CEP164 or ZNF423 causes sensitivity to DNA damaging agents and that cep164 knockdown in zebrafish results in dysregulated DDR and an NPHP-RC phenotype. Our findings link degenerative diseases of the kidney and retina, disorders of increasing prevalence, to mechanisms of DDR.
Keywords: Animals; Cilia; DNA Damage; DNA-Binding Proteins; Exome; Gene Knockdown Techniques; Genes, Recessive; Humans; Kidney Diseases, Cystic; Mice; Microtubule Proteins; MRE11 Homologue Protein; Proteins; Signal Transduction; Zebrafish

Gene therapy rescues cilia defects and restores olfactory function in a mammalian ciliopathy model. - McIntyre, Jeremy C; Davis, Erica E; Joiner, Ariell; Williams, Corey L; Tsai, I-Chun; Jenkins, Paul M; McEwen, Dyke P; Zhang, Lian; Escobado, John; Thomas, Sophie; Szymanska, Katarzyna; Johnson, Colin A; et al. (Nat Med, 2012)
Cilia are evolutionarily conserved microtubule-based organelles that are crucial for diverse biological functions, including motility, cell signaling and sensory perception. In humans, alterations in the formation and function of cilia manifest clinically as ciliopathies, a growing class of pleiotropic genetic disorders. Despite the substantial progress that has been made in identifying genes that cause ciliopathies, therapies for these disorders are not yet available to patients. Although mice with a hypomorphic mutation in the intraflagellar transport protein IFT88 (Ift88Tg737Rpw mice, also known as ORPK mice)5 have been well studied, the relevance of IFT88 mutations to human pathology is unknown. We show that a mutation in IFT88 causes a hitherto unknown human ciliopathy. In vivo complementation assays in zebrafish and mIMCD3 cells show the pathogenicity of this newly discovered allele. We further show that ORPK mice are functionally anosmic as a result of the loss of cilia on their olfactory sensory neurons (OSNs). Notably, adenoviral-mediated expression of IFT88 in mature, fully differentiated OSNs of ORPK mice is sufficient to restore ciliary structures and rescue olfactory function. These studies are the first to use in vivo therapeutic treatment to reestablish cilia in a mammalian ciliopathy. More broadly, our studies indicate that gene therapy is a viable option for cellular and functional rescue of the complex ciliary organelle in established differentiated cells.
Keywords: Adenoviridae; Animals; Cilia; Genetic Complementation Test; Genetic Diseases, Inborn; Genetic Therapy; Genetic Vectors; Humans; Mice; Microscopy, Fluorescence; Mutation; Olfactory Receptor Neurons; Smell; Tubulin; Tumor Suppressor Proteins; Zebrafish

Genome sequence of the button mushroom Agaricus bisporus reveals mechanisms governing adaptation to a humic-rich ecological niche. - Morin, Emmanuelle; Kohler, Annegret; Baker, Adam R; Foulongne-Oriol, Marie; Lombard, Vincent; Nagy, Laszlo G; Ohm, Robin A; Patyshakuliyeva, Aleksandrina; Brun, Annick; Aerts, Andrea L; Bailey, Andrew M; Billette, Christophe; et al. (Proc Natl Acad Sci U S A, 2012)
Agaricus bisporus is the model fungus for the adaptation, persistence, and growth in the humic-rich leaf-litter environment. Aside from its ecological role, A. bisporus has been an important component of the human diet for over 200 y and worldwide cultivation of the "button mushroom" forms a multibillion dollar industry. We present two A. bisporus genomes, their gene repertoires and transcript profiles on compost and during mushroom formation. The genomes encode a full repertoire of polysaccharide-degrading enzymes similar to that of wood-decayers. Comparative transcriptomics of mycelium grown on defined medium, casing-soil, and compost revealed genes encoding enzymes involved in xylan, cellulose, pectin, and protein degradation are more highly expressed in compost. The striking expansion of heme-thiolate peroxidases and β-etherases is distinctive from Agaricomycotina wood-decayers and suggests a broad attack on decaying lignin and related metabolites found in humic acid-rich environment. Similarly, up-regulation of these genes together with a lignolytic manganese peroxidase, multiple copper radical oxidases, and cytochrome P450s is consistent with challenges posed by complex humic-rich substrates. The gene repertoire and expression of hydrolytic enzymes in A. bisporus is substantially different from the taxonomically related ectomycorrhizal symbiont Laccaria bicolor. A common promoter motif was also identified in genes very highly expressed in humic-rich substrates. These observations reveal genetic and enzymatic mechanisms governing adaptation to the humic-rich ecological niche formed during plant degradation, further defining the critical role such fungi contribute to soil structure and carbon sequestration in terrestrial ecosystems. Genome sequence will expedite mushroom breeding for improved agronomic characteristics.
Keywords: Adaptation, Physiological; Agaricus; Ecology; Evolution, Molecular; Genome, Fungal; Lignin

Genome-wide single nucleotide polymorphism arrays as a diagnostic tool in patients with synchronous endometrial and ovarian cancer. - Ikeda, Yuji; Oda, Katsutoshi; Nakagawa, Shunsuke; Murayama-Hosokawa, Satsuki; Yamamoto, Shogo; Ishikawa, Shumpei; Wang, Linghua; Takazawa, Yutaka; Maeda, Daichi; Wada-Hiraike, Osamu; Kawana, Kei; Fukayama, Masashi; et al. (Int J Gynecol Cancer, 2012)
OBJECTIVE: Synchronous carcinomas in the endometrium and ovaries can be a single primary tumor with metastasis (SPM) or dual primary tumors (DP). Although the prognosis of DP without any metastases is significantly better than that of SPM, pathological diagnosis is difficult in tumors with similar histological features. MATERIALS AND METHODS: In 10 tumors from 5 patients with synchronous endometrial and ovarian carcinomas, 250K single nucleotide polymorphism arrays were performed. The patients were genetically diagnosed according to the pattern of copy number alterations (CNAs), in addition to microsatellite status and mutational analysis of PIK3CA, PTEN, K-Ras, and CTNNB1. RESULTS: Of the 5 patients, 3 exhibited identical CNA patterns, including type, loci, and degree of each alteration in the endometrial and ovarian carcinomas. The other 2 exhibited CNAs only in either endometrial or ovarian carcinoma. All 5 tumors had 1 or more genetic mutations in the genes examined. One patient exhibited mutations both in PIK3CA and PTEN at discordant sites between endometrial and ovarian carcinomas, whereas the other 4 exhibited concordant mutations. Overall, 4 of the 5 patients were genetically diagnosed with SPM, and the remaining 1 with DP. The pathological diagnosis was not in agreement with the genetic diagnosis in 4 of the 5 patients. CONCLUSIONS: Genome-wide genotyping diagnosis may represent a useful approach for distinguishing between SPM and DP in synchronous endometrial and ovarian carcinomas.
Keywords: Adult; beta Catenin; Biomarkers, Tumor; Class I Phosphatidylinositol 3-Kinases; DNA Copy Number Variations; Endometrial Neoplasms; Female; Genome, Human; Genotype; Humans; Immunoenzyme Techniques; Microsatellite Repeats; Middle Aged; Mutation; Neoplasm Grading; Neoplasm Staging; Neoplasms, Multiple Primary; Oligonucleotide Array Sequence Analysis; Ovarian Neoplasms; Phosphatidylinositol 3-Kinases; Polymorphism, Single Nucleotide; Prognosis; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); PTEN Phosphohydrolase; ras Proteins

Genomic sequencing of key genes in mouse pancreatic cancer cells. - Wang, Y; Zhang, Y; Yang, J; Ni, X; Liu, S; Li, Z; Hodges, S E; Fisher, W E; Brunicardi, F C; Gibbs, R A; Gingras, M-C; Li, M (Curr Mol Med, 2012)
Pancreatic cancer is a multiple genetic disorder with many mutations identified during the progression. Two mouse pancreatic cancer cell lines were established which showed different phenotype in vivo: a non-metastatic cell line, Panc02, and a highly metastatic cell line, Panc02-H7, a derivative of Panc02. In order to investigate whether the genetic mutations of key genes in pancreatic cancer such as KRAS, TP53 (p53), CDKN2A (p16), SMAD4, ZIP4, and PDX-1 contribute to the phenotypic difference of these two mouse pancreatic cancer cells, we sequenced the exonic regions of these key genes in both cell lines and in the normal syngeneic mouse pancreas and compared them with the reference mouse genome sequence. The exons of KRAS, SMAD4, CDKN2A (p16), TP53 (p53), ZIP4, and PDX-1 genes were amplified and the genotype of these genes was determined by Sanger sequencing. The sequences were analyzed with Sequencher software. A mutation in SMAD4 was identified in both cell lines. This homozygote G to T mutation in the first position of codon 174 (GAA) generated a stop codon resulting in the translation of a truncated protein. Further functional analysis indicates that different TGF-β/SMAD signaling pathways were involved in those two mouse cell lines, which may explain the phonotypic difference between the two cells. A single nucleotide polymorphism (SNP) in KRAS gene (TAT to TAC at codon 32) was also identified in the normal pancreas DNA of the syngenic mouse and in both derived tumoral Panc02 and Panc02-H7 cells. No mutation or SNP was found in CDKN2A (p16), TP53 (p53), ZIP4, and PDX-1 genes in these two cell lines. The absence of mutations in genes such as KRAS, TP53, and CDKN2A, which are considered as key genes in the development of human pancreatic cancer suggests that SMAD4 might play a central and decisive role in mouse pancreatic cancer. These results also suggest that other mechanisms are involved in the substantial phenotypic difference between these two mouse pancreatic cancer cell lines. Further studies are warranted to elucidate the molecular pathways that lead to the aggressive metastatic potential of Panc02-H7.
Keywords: Animals; Cell Line, Tumor; Cyclin-Dependent Kinase Inhibitor p16; Homeodomain Proteins; Mice; Pancreatic Neoplasms; Polymerase Chain Reaction; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Smad4 Protein; Trans-Activators; Tumor Suppressor Protein p53

Identity and function of a large gene network underlying mutagenic repair of DNA breaks. - Al Mamun, Abu Amar M; Lombardo, Mary-Jane; Shee, Chandan; Lisewski, Andreas M; Gonzalez, Caleb; Lin, Dongxu; Nehring, Ralf B; Saint-Ruf, Claude; Gibson, Janet L; Frisch, Ryan L; Lichtarge, Olivier; Hastings, P J; et al. (Science, 2012)
Mechanisms of DNA repair and mutagenesis are defined on the basis of relatively few proteins acting on DNA, yet the identities and functions of all proteins required are unknown. Here, we identify the network that underlies mutagenic repair of DNA breaks in stressed Escherichia coli and define functions for much of it. Using a comprehensive screen, we identified a network of ≥93 genes that function in mutation. Most operate upstream of activation of three required stress responses (RpoS, RpoE, and SOS, key network hubs), apparently sensing stress. The results reveal how a network integrates mutagenic repair into the biology of the cell, show specific pathways of environmental sensing, demonstrate the centrality of stress responses, and imply that these responses are attractive as potential drug targets for blocking the evolution of pathogens.
Keywords: Bacterial Proteins; DNA Breaks, Double-Stranded; DNA Repair; Escherichia coli; Gene Expression Regulation, Bacterial; Gene Regulatory Networks; Mutagenesis; Sigma Factor; SOS Response, Genetics; Stress, Physiological

Microarray-based capture of novel expressed cell type-specific transfrags (CoNECT) to annotate tissue-specific transcription in Drosophila melanogaster. - Hong, X; Doddapaneni, H; Comeron, J M; Rodesch, M J; Halvensleben, H A; Nien, C Y; Bolei, F; Metpally, R; Richmond, T A; Albert, T J; Manak, J R (G3 (Bethesda), 2012)
Faithful annotation of tissue-specific transcript isoforms is important not only to understand how genes are organized and regulated but also to identify potential novel, unannotated exons of genes, which may be additional targets of mutation in disease states or while performing mutagenic screens. We have developed a microarray enrichment methodology followed by long-read, next-generation sequencing for identification of unannotated transcript isoforms expressed in two Drosophila tissues, the ovary and the testis. Even with limited sequencing, these studies have identified a large number of novel transcription units, including 5' exons and extensions, 3' exons and extensions, internal exons and exon extensions, gene fusions, and both germline-specific splicing events and promoters. Additionally, comparing our capture dataset with tiling array and traditional RNA-seq analysis, we demonstrate that our enrichment strategy is able to capture low-abundance transcripts that cannot readily be identified by the other strategies. Finally, we show that our methodology can help identify transcriptional signatures of minority cell types within the ovary that would otherwise be difficult to reveal without the CoNECT enrichment strategy. These studies introduce an efficient methodology for cataloging tissue-specific transcriptomes in which specific classes of genes or transcripts can be targeted for capture and sequence, thus reducing the significant sequencing depth normally required for accurate annotation. Ovary and testis isotigs over 200 bp have been deposited with the GenBank Transcriptome Shotgun Assembly Sequence Database as bioproject no.PRJNA89451 (accession nos. JV208106–JV230865).
Keywords: Animals; Databases, Genetic; Drosophila melanogaster; Drosophila Proteins; Exons; Female; Male; Oligonucleotide Array Sequence Analysis; Ovary; Promoter Regions, Genetic; Protein Isoforms; RNA Splicing; Testis; Transcriptome

Mutations in the TGF-β repressor SKI cause Shprintzen-Goldberg syndrome with aortic aneurysm. - Doyle, Alexander J; Doyle, Jefferson J; Bessling, Seneca L; Maragh, Samantha; Lindsay, Mark E; Schepers, Dorien; Gillis, Elisabeth; Mortier, Geert; Homfray, Tessa; Sauls, Kimberly; Norris, Russell A; Huso, Nicholas D; et al. (Nat Genet, 2012)
Elevated transforming growth factor (TGF)-β signaling has been implicated in the pathogenesis of syndromic presentations of aortic aneurysm, including Marfan syndrome (MFS) and Loeys-Dietz syndrome (LDS). However, the location and character of many of the causal mutations in LDS intuitively imply diminished TGF-β signaling. Taken together, these data have engendered controversy regarding the specific role of TGF-β in disease pathogenesis. Shprintzen-Goldberg syndrome (SGS) has considerable phenotypic overlap with MFS and LDS, including aortic aneurysm. We identified causative variation in ten individuals with SGS in the proto-oncogene SKI, a known repressor of TGF-β activity. Cultured dermal fibroblasts from affected individuals showed enhanced activation of TGF-β signaling cascades and higher expression of TGF-β-responsive genes relative to control cells. Morpholino-induced silencing of SKI paralogs in zebrafish recapitulated abnormalities seen in humans with SGS. These data support the conclusions that increased TGF-β signaling is the mechanism underlying SGS and that high signaling contributes to multiple syndromic presentations of aortic aneurysm.
Keywords: Animals; Aortic Aneurysm; Arachnodactyly; Cells, Cultured; Craniosynostoses; DNA-Binding Proteins; Fibroblasts; Humans; Loeys-Dietz Syndrome; Marfan Syndrome; Mice; Mutation; Phenotype; Phosphorylation; Proto-Oncogene Mas; Proto-Oncogene Proteins; Signal Transduction; Transforming Growth Factor beta; Zebrafish

Pancreatic cancer genomes reveal aberrations in axon guidance pathway genes. - Biankin, Andrew V; Waddell, Nicola; Kassahn, Karin S; Gingras, Marie-Claude; Muthuswamy, Lakshmi B; Johns, Amber L; Miller, David K; Wilson, Peter J; Patch, Ann-Marie; Wu, Jianmin; Chang, David K; Cowley, Mark J; et al. (Nature, 2012)
Pancreatic cancer is a highly lethal malignancy with few effective therapies. We performed exome sequencing and copy number analysis to define genomic aberrations in a prospectively accrued clinical cohort (n = 142) of early (stage I and II) sporadic pancreatic ductal adenocarcinoma. Detailed analysis of 99 informative tumours identified substantial heterogeneity with 2,016 non-silent mutations and 1,628 copy-number variations. We define 16 significantly mutated genes, reaffirming known mutations (KRAS, TP53, CDKN2A, SMAD4, MLL3, TGFBR2, ARID1A and SF3B1), and uncover novel mutated genes including additional genes involved in chromatin modification (EPC1 and ARID2), DNA damage repair (ATM) and other mechanisms (ZIM2, MAP2K4, NALCN, SLC16A4 and MAGEA6). Integrative analysis with in vitro functional data and animal models provided supportive evidence for potential roles for these genetic aberrations in carcinogenesis. Pathway-based analysis of recurrently mutated genes recapitulated clustering in core signalling pathways in pancreatic ductal adenocarcinoma, and identified new mutated genes in each pathway. We also identified frequent and diverse somatic aberrations in genes described traditionally as embryonic regulators of axon guidance, particularly SLIT/ROBO signalling, which was also evident in murine Sleeping Beauty transposon-mediated somatic mutagenesis models of pancreatic cancer, providing further supportive evidence for the potential involvement of axon guidance genes in pancreatic carcinogenesis.
Keywords: Animals; Axons; Carcinoma, Pancreatic Ductal; Gene Dosage; Gene Expression Regulation, Neoplastic; Genome; Humans; Kaplan-Meier Estimate; Mice; Mutation; Pancreatic Neoplasms; Proteins; Signal Transduction

Patterns and rates of exonic de novo mutations in autism spectrum disorders. - Neale, Benjamin M; Kou, Yan; Liu, Li; Ma'ayan, Avi; Samocha, Kaitlin E; Sabo, Aniko; Lin, Chiao-Feng; Stevens, Christine; Wang, Li-San; Makarov, Vladimir; Polak, Paz; Yoon, Seungtai; et al. (Nature, 2012)
Autism spectrum disorders (ASD) are believed to have genetic and environmental origins, yet in only a modest fraction of individuals can specific causes be identified. To identify further genetic risk factors, here we assess the role of de novo mutations in ASD by sequencing the exomes of ASD cases and their parents (n = 175 trios). Fewer than half of the cases (46.3%) carry a missense or nonsense de novo variant, and the overall rate of mutation is only modestly higher than the expected rate. In contrast, the proteins encoded by genes that harboured de novo missense or nonsense mutations showed a higher degree of connectivity among themselves and to previous ASD genes as indexed by protein-protein interaction screens. The small increase in the rate of de novo events, when taken together with the protein interaction results, are consistent with an important but limited role for de novo point mutations in ASD, similar to that documented for de novo copy number variants. Genetic models incorporating these data indicate that most of the observed de novo events are unconnected to ASD; those that do confer risk are distributed across many genes and are incompletely penetrant (that is, not necessarily sufficient for disease). Our results support polygenic models in which spontaneous coding mutations in any of a large number of genes increases risk by 5- to 20-fold. Despite the challenge posed by such models, results from de novo events and a large parallel case-control study provide strong evidence in favour of CHD8 and KATNAL2 as genuine autism risk factors.
Keywords: Autistic Disorder; Case-Control Studies; DNA-Binding Proteins; Exome; Exons; Family Health; Genetic Predisposition to Disease; Humans; Models, Genetic; Multifactorial Inheritance; Mutation; Phenotype; Poisson Distribution; Protein Interaction Maps; Transcription Factors

PDX-1 is a therapeutic target for pancreatic cancer, insulinoma and islet neoplasia using a novel RNA interference platform. - Liu, Shi-He; Rao, Donald D; Nemunaitis, John; Senzer, Neil; Zhou, Guisheng; Dawson, David; Gingras, Marie-Claude; Wang, Zhaohui; Gibbs, Richard; Norman, Michael; Templeton, Nancy S; DeMayo, Francesco J; et al. (PLoS One, 2012)
Pancreatic and duodenal homeobox-1 (PDX-1) is a transcription factor that regulates insulin expression and islet maintenance in the adult pancreas. Our recent studies demonstrate that PDX-1 is an oncogene for pancreatic cancer and is overexpressed in pancreatic cancer. The purpose of this study was to demonstrate that PDX-1 is a therapeutic target for both hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Immunohistochemistry of human pancreatic and islet neoplasia specimens revealed marked PDX-1 overexpression, suggesting PDX-1 as a "drugable" target within these diseases. To do so, a novel RNA interference effector platform, bifunctional shRNA(PDX-1), was developed and studied in mouse and human cell lines as well as in mouse models of pancreatic cancer, insulinoma and islet neoplasia. Systemic delivery of bi-shRNA(humanPDX-1) lipoplexes resulted in marked reduction of tumor volume and improved survival in a human pancreatic cancer xenograft mouse model. bi-shRNA(mousePDX-1) lipoplexes prevented death from hyperinsulinemia and hypoglycemia in an insulinoma mouse model. shRNA(mousePDX-1) lipoplexes reversed hyperinsulinemia and hypoglycemia in an immune-competent mouse model of islet neoplasia. PDX-1 was overexpressed in pancreatic neuroendocrine tumors and nesidioblastosis. These data demonstrate that PDX-1 RNAi therapy controls hormonal symptoms and tumor volume in mouse models of pancreatic cancer, insulinoma and islet neoplasia, therefore, PDX-1 is a potential therapeutic target for these pancreatic diseases.
Keywords: Animals; Cell Line, Tumor; Cell Proliferation; Disease Models, Animal; Glucose Tolerance Test; Homeodomain Proteins; Humans; Immunohistochemistry; In Situ Nick-End Labeling; Insulin; Insulinoma; Islets of Langerhans; Male; Mice; Mice, SCID; Neoplasm Transplantation; Pancreas; Pancreatic Neoplasms; RNA Interference; Trans-Activators

Residual plasmatic activity of ADAMTS13 is correlated with phenotype severity in congenital thrombotic thrombocytopenic purpura. - Lotta, Luca A; Wu, Haifeng M; Mackie, Ian J; Noris, Marina; Veyradier, Agnes; Scully, Marie A; Remuzzi, Giuseppe; Coppo, Paul; Liesner, Ri; Donadelli, Roberta; Loirat, Chantal; Gibbs, Richard A; et al. (Blood, 2012)
The quantification of residual plasmatic ADAMTS13 activity in congenital thrombotic thrombocytopenic purpura (TTP) patients is constrained by limitations in sensitivity and reproducibility of commonly used assays at low levels of ADAMTS13 activity, blunting efforts to establish genotype-phenotype correlations. In the present study, the residual plasmatic activity of ADAMTS13 was measured centrally by surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (limit of detection = 0.5%) in 29 congenital TTP patients. The results were used to study correlations among ADAMTS13 genotype, residual plasmatic activity, and clinical phenotype severity. An ADAMTS13 activity above 0.5% was measured in 26 (90%) patients and lower levels of activity were associated with earlier age at first TTP episode requiring plasma infusion, more frequent recurrences, and prescription of fresh-frozen plasma prophylaxis. Receiver operating characteristic curve analysis showed that activity levels of less than 2.74% and 1.61% were discriminative of age at first TTP episode requiring plasma infusion < 18 years, annual rate of TTP episodes > 1, and use of prophylaxis. Mutations affecting the highly conserved N-terminal domains of the protein were associated with lower residual ADAMTS13 activity and a more severe phenotype in an allelic-dose dependent manner. The results of the present study show that residual ADAMTS13 activity is associated with the severity of clinical phenotype in congenital TTP and provide insights into genotype-phenotype correlations.
Keywords: ADAM Proteins; ADAMTS13 Protein; Adolescent; Adult; Age Factors; Aged; Blood Chemical Analysis; Blood Transfusion; Child; Child, Preschool; DNA Mutational Analysis; Female; Genetic Association Studies; Humans; Male; Middle Aged; Mutation; Plasma; Purpura, Thrombotic Thrombocytopenic; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Young Adult

Strict evolutionary conservation followed rapid gene loss on human and rhesus Y chromosomes. - Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Graves, Tina; Fulton, Robert S; Dugan, Shannon; Ding, Yan; Buhay, Christian J; Kremitzki, Colin; Wang, Qiaoyan; Shen, Hua; et al. (Nature, 2012)
The human X and Y chromosomes evolved from an ordinary pair of autosomes during the past 200-300 million years. The human MSY (male-specific region of Y chromosome) retains only three percent of the ancestral autosomes' genes owing to genetic decay. This evolutionary decay was driven by a series of five 'stratification' events. Each event suppressed X-Y crossing over within a chromosome segment or 'stratum', incorporated that segment into the MSY and subjected its genes to the erosive forces that attend the absence of crossing over. The last of these events occurred 30 million years ago, 5 million years before the human and Old World monkey lineages diverged. Although speculation abounds regarding ongoing decay and looming extinction of the human Y chromosome, remarkably little is known about how many MSY genes were lost in the human lineage in the 25 million years that have followed its separation from the Old World monkey lineage. To investigate this question, we sequenced the MSY of the rhesus macaque, an Old World monkey, and compared it to the human MSY. We discovered that during the last 25 million years MSY gene loss in the human lineage was limited to the youngest stratum (stratum 5), which comprises three percent of the human MSY. In the older strata, which collectively comprise the bulk of the human MSY, gene loss evidently ceased more than 25 million years ago. Likewise, the rhesus MSY has not lost any older genes (from strata 1-4) during the past 25 million years, despite its major structural differences to the human MSY. The rhesus MSY is simpler, with few amplified gene families or palindromes that might enable intrachromosomal recombination and repair. We present an empirical reconstruction of human MSY evolution in which each stratum transitioned from rapid, exponential loss of ancestral genes to strict conservation through purifying selection.
Keywords: Animals; Chromosomes, Human, Y; Conserved Sequence; Crossing Over, Genetic; Evolution, Molecular; Gene Amplification; Gene Deletion; Humans; In Situ Hybridization, Fluorescence; Macaca mulatta; Male; Models, Genetic; Molecular Sequence Data; Pan troglodytes; Radiation Hybrid Mapping; Selection, Genetic; Time Factors; Y Chromosome

Whole genome sequences of three Treponema pallidum ssp. pertenue strains: yaws and syphilis treponemes differ in less than 0.2% of the genome sequence. - Čejková, Darina; Zobaníková, Marie; Chen, Lei; Pospíšilová, Petra; Strouhal, Michal; Qin, Xiang; Mikalová, Lenka; Norris, Steven J; Muzny, Donna M; Gibbs, Richard A; Fulton, Lucinda L; Sodergren, Erica; et al. (PLoS Negl Trop Dis, 2012)
BACKGROUND: The yaws treponemes, Treponema pallidum ssp. pertenue (TPE) strains, are closely related to syphilis causing strains of Treponema pallidum ssp. pallidum (TPA). Both yaws and syphilis are distinguished on the basis of epidemiological characteristics, clinical symptoms, and several genetic signatures of the corresponding causative agents. METHODOLOGY/PRINCIPAL FINDINGS: To precisely define genetic differences between TPA and TPE, high-quality whole genome sequences of three TPE strains (Samoa D, CDC-2, Gauthier) were determined using next-generation sequencing techniques. TPE genome sequences were compared to four genomes of TPA strains (Nichols, DAL-1, SS14, Chicago). The genome structure was identical in all three TPE strains with similar length ranging between 1,139,330 bp and 1,139,744 bp. No major genome rearrangements were found when compared to the four TPA genomes. The whole genome nucleotide divergence (d(A)) between TPA and TPE subspecies was 4.7 and 4.8 times higher than the observed nucleotide diversity (π) among TPA and TPE strains, respectively, corresponding to 99.8% identity between TPA and TPE genomes. A set of 97 (9.9%) TPE genes encoded proteins containing two or more amino acid replacements or other major sequence changes. The TPE divergent genes were mostly from the group encoding potential virulence factors and genes encoding proteins with unknown function. CONCLUSIONS/SIGNIFICANCE: Hypothetical genes, with genetic differences, consistently found between TPE and TPA strains are candidates for syphilitic treponemes virulence factors. Seventeen TPE genes were predicted under positive selection, and eleven of them coded either for predicted exported proteins or membrane proteins suggesting their possible association with the cell surface. Sequence changes between TPE and TPA strains and changes specific to individual strains represent suitable targets for subspecies- and strain-specific molecular diagnostics.
Keywords: DNA, Bacterial; Gene Order; Genetic Variation; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Synteny; Syphilis; Treponema pallidum; Yaws

Whole-exome sequencing of human pancreatic cancers and characterization of genomic instability caused by MLH1 haploinsufficiency and complete deficiency. - Wang, Linghua; Tsutsumi, Shuichi; Kawaguchi, Tokuichi; Nagasaki, Koichi; Tatsuno, Kenji; Yamamoto, Shogo; Sang, Fei; Sonoda, Kohtaro; Sugawara, Minoru; Saiura, Akio; Hirono, Seiko; Yamaue, Hiroki; et al. (Genome Res, 2012)
Whole-exome sequencing (Exome-seq) has been successfully applied in several recent studies. We here sequenced the exomes of 15 pancreatic tumor cell lines and their matched normal samples. We captured 162,073 exons of 16,954 genes and sequenced the targeted regions to a mean coverage of 56-fold. This study identified a total of 1517 somatic mutations and validated 934 mutations by transcriptome sequencing. We detected recurrent mutations in 56 genes. Among them, 41 have not been described. The mutation rates varied widely among cell lines. The diversity of the mutation rates was significantly correlated with the distinct MLH1 copy-number status. Exome-seq revealed intensive genomic instability in a cell line with MLH1 homozygous deletion, indicated by a dramatically elevated rate of somatic substitutions, small insertions/deletions (indels), as well as indels in microsatellites. Notably, we found that MLH1 expression was decreased by nearly half in cell lines with an allelic loss of MLH1. While these cell lines were negative in conventional microsatellite instability assay, they showed a 10.5-fold increase in the rate of somatic indels, e.g., truncating indels in TP53 and TGFBR2, indicating MLH1 haploinsufficiency in the correction of DNA indel errors. We further analyzed the exomes of 15 renal cell carcinomas and confirmed MLH1 haploinsufficiency. We observed a much higher rate of indel mutations in the affected cases and identified recurrent truncating indels in several cancer genes such as VHL, PBRM1, and JARID1C. Together, our data suggest that MLH1 hemizygous deletion, through increasing the rate of indel mutations, could drive the development and progression of sporadic cancers.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Cell Line, Tumor; Exome; Genomic Instability; Haploinsufficiency; High-Throughput Nucleotide Sequencing; Humans; Loss of Heterozygosity; Mutation; Mutation Rate; MutL Protein Homolog 1; Nuclear Proteins; Pancreatic Neoplasms; Reproducibility of Results

Activation of multiple proto-oncogenic tyrosine kinases in breast cancer via loss of the PTPN12 phosphatase. - Sun, Tingting; Aceto, Nicola; Meerbrey, Kristen L; Kessler, Jessica D; Zhou, Chunshui; Migliaccio, Ilenia; Nguyen, Don X; Pavlova, Natalya N; Botero, Maria; Huang, Jian; Bernardi, Ronald J; Schmitt, Earlene; et al. (Cell, 2011)
Among breast cancers, triple-negative breast cancer (TNBC) is the most poorly understood and is refractory to current targeted therapies. Using a genetic screen, we identify the PTPN12 tyrosine phosphatase as a tumor suppressor in TNBC. PTPN12 potently suppresses mammary epithelial cell proliferation and transformation. PTPN12 is frequently compromised in human TNBCs, and we identify an upstream tumor-suppressor network that posttranscriptionally controls PTPN12. PTPN12 suppresses transformation by interacting with and inhibiting multiple oncogenic tyrosine kinases, including HER2 and EGFR. The tumorigenic and metastatic potential of PTPN12-deficient TNBC cells is severely impaired upon restoration of PTPN12 function or combined inhibition of PTPN12-regulated tyrosine kinases, suggesting that TNBCs are dependent on the proto-oncogenic tyrosine kinases constrained by PTPN12. Collectively, these data identify PTPN12 as a commonly inactivated tumor suppressor and provide a rationale for combinatorially targeting proto-oncogenic tyrosine kinases in TNBC and other cancers based on their profile of tyrosine-phosphatase activity.
Keywords: Breast Neoplasms; Cell Line, Tumor; Cell Transformation, Neoplastic; ErbB Receptors; Female; Gene Expression Regulation, Neoplastic; Humans; MAP Kinase Signaling System; MicroRNAs; Mutation; Neoplasm Metastasis; Protein Processing, Post-Translational; Protein Tyrosine Phosphatase, Non-Receptor Type 12; Tumor Suppressor Proteins

Building a comprehensive genomic program for hepatocellular carcinoma. - Harring, Theresa R; Guiteau, Jacfranz J; Nguyen, N Thao T; Cotton, Ron T; Gingras, Marie-Claude; Wheeler, David A; O'Mahony, Christine A; Gibbs, Richard A; Brunicardi, F Charles; Goss, John A (World J Surg, 2011)
BACKGROUND: Hepatocellular carcinoma (HCC) is the most common primary liver cancer, causing approximately 660,000 deaths worldwide annually. The preferred treatment of HCC is surgical resection or orthotopic liver transplantation (OLT) for patients meeting specific criteria. For patients outside these criteria, options are limited and include medical therapy, radiofrequency ablation, chemoembolization, or palliative measures, and these result in poor outcomes. Various centers at Baylor are elucidating the genomics of HCC to improve treatment options, with a focus on three etiologies: hepatitis C virus, hepatitis B virus, and non-viral. METHODS: Through collaborative efforts, we have established an effective specimen biobanking protocol, and we are using several techniques to analyze HCC, including whole genome sequencing, whole exome sequencing, gene-specific analysis, gene expression, and epigenetic analysis. RESULTS: We have completed whole genome sequencing on two patient samples, whole exome sequencing on 47 patient samples, gene-specific analysis on 94 patient samples, gene expression on 4 patient samples, and epigenetic analysis on 1 patient sample. CONCLUSIONS: We hope to use these results to define novel genetic therapeutic strategies that may work in conjunction with surgical approaches to improve long-term patient and graft survival rates in patients with HCC. We also aim to provide a functional framework of a comprehensive program for genomic analysis that may be imitated by other institutions and for other tumors in the global quest toward personalized genomic medicine.
Keywords: Carcinoma, Hepatocellular; Cell Transformation, Neoplastic; Databases, Nucleic Acid; Disease Progression; Epigenomics; Exome; Forecasting; Gene Expression Regulation, Neoplastic; Genome, Human; Genome-Wide Association Study; Humans; Liver Neoplasms; Precision Medicine; Tissue Banks

Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Worley, Kim C; Nazareth, Lynne V; Muzny, Donna M; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2011)
'Orang-utan' is derived from a Malay term meaning 'man of the forest' and aptly describes the southeast Asian great apes native to Sumatra and Borneo. The orang-utan species, Pongo abelii (Sumatran) and Pongo pygmaeus (Bornean), are the most phylogenetically distant great apes from humans, thereby providing an informative perspective on hominid evolution. Here we present a Sumatran orang-utan draft genome assembly and short read sequence data from five Sumatran and five Bornean orang-utan genomes. Our analyses reveal that, compared to other primates, the orang-utan genome has many unique features. Structural evolution of the orang-utan genome has proceeded much more slowly than other great apes, evidenced by fewer rearrangements, less segmental duplication, a lower rate of gene family turnover and surprisingly quiescent Alu repeats, which have played a major role in restructuring other primate genomes. We also describe a primate polymorphic neocentromere, found in both Pongo species, emphasizing the gradual evolution of orang-utan genome structure. Orang-utans have extremely low energy usage for a eutherian mammal, far lower than their hominid relatives. Adding their genome to the repertoire of sequenced primates illuminates new signals of positive selection in several pathways including glycolipid metabolism. From the population perspective, both Pongo species are deeply diverse; however, Sumatran individuals possess greater diversity than their Bornean counterparts, and more species-specific variation. Our estimate of Bornean/Sumatran speciation time, 400,000 years ago, is more recent than most previous studies and underscores the complexity of the orang-utan speciation process. Despite a smaller modern census population size, the Sumatran effective population size (N(e)) expanded exponentially relative to the ancestral N(e) after the split, while Bornean N(e) declined over the same period. Overall, the resources and analyses presented here offer new opportunities in evolutionary genomics, insights into hominid biology, and an extensive database of variation for conservation efforts.
Keywords: Animals; Centromere; Cerebrosides; Chromosomes; Evolution, Molecular; Female; Gene Rearrangement; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Humans; Male; Phylogeny; Pongo abelii; Pongo pygmaeus; Population Density; Population Dynamics; Species Specificity

Complete genome sequence of Treponema paraluiscuniculi, strain Cuniculi A: the loss of infectivity to humans is associated with genome decay. - Smajs, David; Zobaníková, Marie; Strouhal, Michal; Čejková, Darina; Dugan-Rocha, Shannon; Pospíšilová, Petra; Norris, Steven J; Albert, Tom; Qin, Xiang; Hallsworth-Pepin, Kym; Buhay, Christian; Muzny, Donna M; et al. (PLoS One, 2011)
Treponema paraluiscuniculi is the causative agent of rabbit venereal spirochetosis. It is not infectious to humans, although its genome structure is very closely related to other pathogenic Treponema species including Treponema pallidum subspecies pallidum, the etiological agent of syphilis. In this study, the genome sequence of Treponema paraluiscuniculi, strain Cuniculi A, was determined by a combination of several high-throughput sequencing strategies. Whereas the overall size (1,133,390 bp), arrangement, and gene content of the Cuniculi A genome closely resembled those of the T. pallidum genome, the T. paraluiscuniculi genome contained a markedly higher number of pseudogenes and gene fragments (51). In addition to pseudogenes, 33 divergent genes were also found in the T. paraluiscuniculi genome. A set of 32 (out of 84) affected genes encoded proteins of known or predicted function in the Nichols genome. These proteins included virulence factors, gene regulators and components of DNA repair and recombination. The majority (52 or 61.9%) of the Cuniculi A pseudogenes and divergent genes were of unknown function. Our results indicate that T. paraluiscuniculi has evolved from a T. pallidum-like ancestor and adapted to a specialized host-associated niche (rabbits) during loss of infectivity to humans. The genes that are inactivated or altered in T. paraluiscuniculi are candidates for virulence factors important in the infectivity and pathogenesis of T. pallidum subspecies.
Keywords: Genome; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Treponema

Evolution of pleiotropy: epistatic interaction pattern supports a mechanistic model underlying variation in genotype-phenotype map. - Pavlicev, Mihaela; Norgard, Elizabeth A; Fawcett, Gloria L; Cheverud, James M (J Exp Zool B Mol Dev Evol, 2011)
The genotype-phenotype (GP) map consists of developmental and physiological mechanisms mapping genetic onto phenotypic variation. It determines the distribution of heritable phenotypic variance on which selection can act. Comparative studies of morphology as well as of gene regulatory networks show that the GP map itself evolves, yet little is known about the actual evolutionary mechanisms involved. The study of such mechanisms requires exploring the variation in GP maps at the population level, which presently is easier to quantify by statistical genetic methods rather than by regulatory network structures. We focus on the evolution of pleiotropy, a major structural aspect of the GP map. Pleiotropic genes affect multiple traits and underlie genetic covariance between traits, often causing evolutionary constraints. Previous quantitative genetic studies have demonstrated population-level variation in pleiotropy in the form of loci, at which genotypes differ in the genetic covariation between traits. This variation can potentially fuel evolution of the GP map under selection and/or drift. Here, we propose a developmental mechanism underlying population genetic variation in covariance and test its predictions. Specifically, the mechanism predicts that the loci identified as responsible for genetic variation in pleiotropy are involved in trait-specific epistatic interactions. We test this prediction for loci affecting allometric relationships between traits in an advanced intercross between inbred mouse strains. The results consistently support the prediction. We further find a high degree of sign epistasis in these interactions, which we interpret as an indication of adaptive gene complexes within the diverged parental lines.
Keywords: Animals; Biological Evolution; Crosses, Genetic; Epistasis, Genetic; Evolution, Molecular; Gene Regulatory Networks; Genetic Pleiotropy; Genetic Variation; Genotype; Mice; Mice, Inbred Strains; Models, Genetic; Phenotype; Quantitative Trait Loci

Exome sequencing of ion channel genes reveals complex profiles confounding personal risk assessment in epilepsy. - Klassen, Tara; Davis, Caleb; Goldman, Alica; Burgess, Dan; Chen, Tim; Wheeler, David; McPherson, John; Bourquin, Traci; Lewis, Lora; Villasana, Donna; Morgan, Margaret; Muzny, Donna; et al. (Cell, 2011)
Ion channel mutations are an important cause of rare Mendelian disorders affecting brain, heart, and other tissues. We performed parallel exome sequencing of 237 channel genes in a well-characterized human sample, comparing variant profiles of unaffected individuals to those with the most common neuronal excitability disorder, sporadic idiopathic epilepsy. Rare missense variation in known Mendelian disease genes is prevalent in both groups at similar complexity, revealing that even deleterious ion channel mutations confer uncertain risk to an individual depending on the other variants with which they are combined. Our findings indicate that variant discovery via large scale sequencing efforts is only a first step in illuminating the complex allelic architecture underlying personal disease risk. We propose that in silico modeling of channel variation in realistic cell and network models will be crucial to future strategies assessing mutation profile pathogenicity and drug response in individuals with a broad spectrum of excitability disorders.
Keywords: Computer Simulation; Epilepsy; Epistasis, Genetic; Gene Expression Profiling; Hippocampus; Humans; Ion Channels; Mutation, Missense; Neurons; Polymorphism, Single Nucleotide; Risk Assessment

Genome sequence of an Australian kangaroo, Macropus eugenii, provides insight into the evolution of mammalian reproduction and development. - Renfree, Marilyn B; Papenfuss, Anthony T; Deakin, Janine E; Lindsay, James; Heider, Thomas; Belov, Katherine; Rens, Willem; Waters, Paul D; Pharo, Elizabeth A; Shaw, Geoff; Wong, Emily S W; Lefèvre, Christophe M; et al. (Genome Biol, 2011)
BACKGROUND: We present the genome sequence of the tammar wallaby, Macropus eugenii, which is a member of the kangaroo family and the first representative of the iconic hopping mammals that symbolize Australia to be sequenced. The tammar has many unusual biological characteristics, including the longest period of embryonic diapause of any mammal, extremely synchronized seasonal breeding and prolonged and sophisticated lactation within a well-defined pouch. Like other marsupials, it gives birth to highly altricial young, and has a small number of very large chromosomes, making it a valuable model for genomics, reproduction and development. RESULTS: The genome has been sequenced to 2 × coverage using Sanger sequencing, enhanced with additional next generation sequencing and the integration of extensive physical and linkage maps to build the genome assembly. We also sequenced the tammar transcriptome across many tissues and developmental time points. Our analyses of these data shed light on mammalian reproduction, development and genome evolution: there is innovation in reproductive and lactational genes, rapid evolution of germ cell genes, and incomplete, locus-specific X inactivation. We also observe novel retrotransposons and a highly rearranged major histocompatibility complex, with many class I genes located outside the complex. Novel microRNAs in the tammar HOX clusters uncover new potential mammalian HOX regulatory elements. CONCLUSIONS: Analyses of these resources enhance our understanding of marsupial gene evolution, identify marsupial-specific conserved non-coding elements and critical genes across a range of biological systems, including reproduction, development and immunity, and provide new insight into marsupial and mammalian biology and genome evolution.
Keywords: Animals; Australia; Biological Evolution; Chromosome Mapping; Chromosomes, Mammalian; Female; Gene Expression Regulation; Genome; Genomic Imprinting; In Situ Hybridization, Fluorescence; Macropodidae; MicroRNAs; Molecular Sequence Data; Reproduction; Sequence Alignment; Sequence Analysis, DNA; Transcriptome

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger; White People

A high-resolution map of human evolutionary constraint using 29 mammals. - Lindblad-Toh, Kerstin; Garber, Manuel; Zuk, Or; Lin, Michael F; Parker, Brian J; Washietl, Stefan; Kheradpour, Pouya; Ernst, Jason; Jordan, Gregory; Mauceli, Evan; Ward, Lucas D; Lowe, Craig B; et al. (Nature, 2011)
The comparison of related genomes has emerged as a powerful lens for genome interpretation. Here we report the sequencing and comparative analysis of 29 eutherian genomes. We confirm that at least 5.5% of the human genome has undergone purifying selection, and locate constrained elements covering ∼4.2% of the genome. We use evolutionary signatures and comparisons with experimental data sets to suggest candidate functions for ∼60% of constrained bases. These elements reveal a small number of new coding exons, candidate stop codon readthrough events and over 10,000 regions of overlapping synonymous constraint within protein-coding exons. We find 220 candidate RNA structural families, and nearly a million elements overlapping potential promoter, enhancer and insulator regions. We report specific amino acid residues that have undergone positive selection, 280,000 non-coding elements exapted from mobile elements and more than 1,000 primate- and human-accelerated elements. Overlap with disease-associated variants indicates that our findings will be relevant for studies of human biology, health and disease.
Keywords: Animals; Disease; Evolution, Molecular; Exons; Genome; Genome, Human; Genomics; Health; Humans; Mammals; Molecular Sequence Annotation; Phylogeny; RNA; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

Interaction of folate intake and the paraoxonase Q192R polymorphism with risk of incident coronary heart disease and ischemic stroke: the atherosclerosis risk in communities study. - Luu, Hung N; Kingah, Pascal L; North, Kari; Boerwinkle, Eric; Volcik, Kelly A (Ann Epidemiol, 2011)
PURPOSE: To investigate the potential interaction between folate intake and the paraoxonase 1 (PON1) Q192R polymorphism with the risk of incident coronary heart disease (CHD) and ischemic stroke in the Atherosclerosis Risk in Communities study, a population-based prospective cohort of cardiovascular disease in 15,792 white and African-American subject. METHODS: Race-stratified Cox proportional hazards models were performed to examine the interaction between folate intake and the PON1 Q192R polymorphism. RESULTS: A significant inverse association between folate intake and risk of incident CHD among white subjects was found (hazard rate ratio, 1.30; 95% confidence interval, 1.09-1.56; P = .004; folate intake ≤155 μg vs ≥279 μg, reference group). An interaction effect was observed between the dominant genetic model and folate intake with regards to incident ischemic stroke in white subjects (hazard rate ratio, 0.68; 95% confidence interval, 0.91-0.99; and 1.24 from 1st-4th quartile, respectively; P-trend = .05). CONCLUSIONS: There was an interaction between folate intake and PON1 Q192 polymorphism with regard to the risk of ischemic stroke in white subjects. Future studies should investigate the interaction between additional polymorphisms within the PON1 gene and genetic variants in other folate metabolizing genes with folate intake on the risk of incident CHD and stroke.
Keywords: Adult; Aryldialkylphosphatase; Atherosclerosis; Black or African American; Cohort Studies; Coronary Disease; Female; Folic Acid; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Stroke; United States; White People

Long-range massively parallel mate pair sequencing detects distinct mutations and similar patterns of structural mutability in two breast cancer cell lines. - Hampton, Oliver A; Koriabine, Maxim; Miller, Christopher A; Coarfa, Cristian; Li, Jian; Den Hollander, Petra; Schoenherr, Caroline; Carbone, Lucia; Nefedov, Mikhail; Ten Hallers, Boudewijn F H; Lee, Adrian V; De Jong, Pieter J; et al. (Cancer Genet, 2011)
Cancer genomes frequently undergo genomic instability resulting in accumulation of chromosomal rearrangement. To date, one of the main challenges has been to confidently and accurately identify these rearrangements by using short-read massively parallel sequencing. We were able to improve cancer rearrangement detection by combining two distinct massively parallel sequencing strategies: fosmid-sized (36 kb on average) and standard 5 kb mate pair libraries. We applied this combined strategy to map rearrangements in two breast cancer cell lines, MCF7 and HCC1954. We detected and validated a total of 91 somatic rearrangements in MCF7 and 25 in HCC1954, including genomic alterations corresponding to previously reported transcript aberrations in these two cell lines. Each of the genomes contains two types of breakpoints: clustered and dispersed. In both cell lines, the dispersed breakpoints show enrichment for low copy repeats, while the clustered breakpoints associate with high copy number amplifications. Comparing the two genomes, we observed highly similar structural mutational spectra affecting different sets of genes, pointing to similar histories of genomic instability against the background of very different gene network perturbations.
Keywords: Breast Neoplasms; Cell Line, Tumor; Chromosome Aberrations; Chromosome Mapping; DNA, Neoplasm; Female; Genome, Human; Genomic Instability; High-Throughput Nucleotide Sequencing; Humans; Mutation; Polymerase Chain Reaction; Sequence Analysis, DNA

Minimum information about a marker gene sequence (MIMARKS) and minimum information about any (x) sequence (MIxS) specifications. - Yilmaz, Pelin; Kottmann, Renzo; Field, Dawn; Knight, Rob; Cole, James R; Amaral-Zettler, Linda; Gilbert, Jack A; Karsch-Mizrachi, Ilene; Johnston, Anjanette; Cochrane, Guy; Vaughan, Robert; Hunter, Christopher; et al. (Nat Biotechnol, 2011)
Here we present a standard developed by the Genomic Standards Consortium (GSC) for reporting marker gene sequences--the minimum information about a marker gene sequence (MIMARKS). We also introduce a system for describing the environment from which a biological sample originates. The 'environmental packages' apply to any genome sequence of known origin and can be used in combination with MIMARKS and other GSC checklists. Finally, to establish a unified standard for describing sequence data and to provide a single point of entry for the scientific community to access and learn about GSC checklists, we present the minimum information about any (x) sequence (MIxS). Adoption of MIxS will enhance our ability to analyze natural genetic diversity documented by massive DNA sequencing efforts from myriad ecosystems in our ever-changing biosphere.
Keywords: Biomarkers; Checklist; Databases, Genetic; Environment; Genes, rRNA; Genetic Variation; Humans; Information Storage and Retrieval; Internet; Metagenomics; Programming Languages; Sequence Analysis, DNA; Software

PDX-1: demonstration of oncogenic properties in pancreatic cancer. - Liu, Shi-He; Patel, Sanjeet; Gingras, Marie-Claude; Nemunaitis, John; Zhou, Guisheng; Chen, Changyi; Li, Min; Fisher, William; Gibbs, Richard; Brunicardi, F Charles (Cancer, 2011)
BACKGROUND: Pancreatic-duodenal homeobox 1 (PDX-1) is a transcription factor that regulates embryologic pancreas development and insulin expression in the adult islet; however, it is overexpressed in many types of cancer, including pancreatic cancer. The purpose of this study was to investigate the role of PDX-1 in tumorigenesis in human cells. METHODS: In vitro cell proliferation, invasion, and transformation were performed in human embryonic kidney cell line (HEK 293), pancreatic cancer cell line MIA PaCa2, and human pancreatic ductal epithelial (HPDE) cells transiently or stably expressing PDX-1 or green fluorescent protein (GFP) PDX-1, with or without cotransfection of PDX-1 short hairpin RNA (shRNA). In vivo tumor formation was carried out in severe combined immunodeficiency (SCID) mice with subcutaneous injection of HEK 293 and MIA PaCa2 stably transfected cells. Cell cycle was analyzed by Western blot or immunostaining. Microarray of RNA from pancreatic adenocarcinoma cells with and without PDX-1 shRNA was performed and analyzed. RESULTS: Transient and stable expressing PDX-1 significantly increased cell proliferation and invasion in HEK 293, human pancreatic ductal epithelial (HPDE), and MIA PaCa2 cells versus controls (P < .05), human PDX-1 shRNA reversed these effects. Expression of PDX-1 significantly increased colony formation in HEK 293, HPDE, and MIA PaCa2 cells versus controls in vitro (P < .05). PDX-1 promoted HEK 293 and MIA PaCa2 tumor formation in SCID mice as compared with that of control (P < .05). PDX-1 overexpression disrupted cell cycles proteins. PDX-1 expression was confirmed by Western blot and tracked by viewing of GFP-PDX-1 expression. Microarray data support an oncogenic role of PDX-1 in pancreas cancer cells. CONCLUSIONS: PDX-1 induced increased cell proliferation, invasion, and colony formation in vitro, and resulted in markedly increased HEK 293 and MIA PaCa2 tumor formation in SCID mice. These data suggest that PDX-1 is a potential oncogene that regulates tumorigenesis.
Keywords: Animals; Cell Cycle; Cell Line, Tumor; Cell Proliferation; HEK293 Cells; Homeodomain Proteins; Humans; Mice; Mice, SCID; Neoplasm Transplantation; Oncogenes; Pancreatic Neoplasms; RNA, Small Interfering; Trans-Activators; Transfection; Up-Regulation

A primer on a hepatocellular carcinoma bioresource bank using the cancer genome atlas guidelines: practical issues and pitfalls. - Nguyen, N Thao T; Cotton, Ron T; Harring, Theresa R; Guiteau, Jacfranz J; Gingras, Marie-Claude; Wheeler, David A; O'Mahony, Christine A; Gibbs, Richard A; Brunicardi, F Charles; Goss, John A (World J Surg, 2011)
BACKGROUND: Since the advent of the human genome, the era of personalized genomic medicine is indisputably in progress. METHODS: In an effort to contribute to the evolving knowledge of genomic medicine, we have aimed directly at building a bioresource bank for hepatocellular carcinoma. This tumor bank is based on the rigorous guidelines set forth by the National Cancer Institute, and it offers analytes to help elucidate the mechanisms of progression from cirrhosis to malignancy, risk factors for recurrence, and applicability of current treatment options to a diverse group of people. CONCLUSIONS: Surgeons have a privileged position between patients (and their cancer) and the benches of basic science. Thus, we offer a primer based on our own experiences, from which surgeons may take elements to build their own bioresource bank for use in collaboration with others. We highlight some practicalities and pitfalls that could be overlooked, as well as a discussion of possible solutions.
Keywords: Carcinoma, Hepatocellular; Cell Transformation, Neoplastic; Cooperative Behavior; Databases, Genetic; Databases, Nucleic Acid; Disease Progression; Forecasting; Genetic Predisposition to Disease; Genome, Human; Guidelines as Topic; Humans; Interdisciplinary Communication; Liver; Liver Cirrhosis; Liver Neoplasms; National Cancer Institute (U.S.); Neoplasm Invasiveness; Neoplasm Recurrence, Local; Precision Medicine; Tissue Banks; United States

Targeted enrichment beyond the consensus coding DNA sequence exome reveals exons with higher variant densities. - Bainbridge, Matthew N; Wang, Min; Wu, Yuanqing; Newsham, Irene; Muzny, Donna M; Jefferies, John L; Albert, Thomas J; Burgess, Daniel L; Gibbs, Richard A (Genome Biol, 2011)
BACKGROUND: Enrichment of loci by DNA hybridization-capture, followed by high-throughput sequencing, is an important tool in modern genetics. Currently, the most common targets for enrichment are the protein coding exons represented by the consensus coding DNA sequence (CCDS). The CCDS, however, excludes many actual or computationally predicted coding exons present in other databases, such as RefSeq and Vega, and non-coding functional elements such as untranslated and regulatory regions. The number of variants per base pair (variant density) and our ability to interrogate regions outside of the CCDS regions is consequently less well understood. RESULTS: We examine capture sequence data from outside of the CCDS regions and find that extremes of GC content that are present in different subregions of the genome can reduce the local capture sequence coverage to less than 50% relative to the CCDS. This effect is due to biases inherent in both the Illumina and SOLiD sequencing platforms that are exacerbated by the capture process. Interestingly, for two subregion types, microRNA and predicted exons, the capture process yields higher than expected coverage when compared to whole genome sequencing. Lastly, we examine the variation present in non-CCDS regions and find that predicted exons, as well as exonic regions specific to RefSeq and Vega, show much higher variant densities than the CCDS. CONCLUSIONS: We show that regions outside of the CCDS perform less efficiently in capture sequence experiments. Further, we show that the variant density in computationally predicted exons is more than 2.5-times higher than that observed in the CCDS.
Keywords: Alleles; Computational Biology; Consensus Sequence; Exome; Exons; Gene Frequency; Genome, Human; Humans; Introns; Mutation Rate; Open Reading Frames; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

TTC21B contributes both causal and modifying alleles across the ciliopathy spectrum. - Davis, Erica E; Zhang, Qi; Liu, Qin; Diplas, Bill H; Davey, Lisa M; Hartley, Jane; Stoetzel, Corinne; Szymanska, Katarzyna; Ramaswami, Gokul; Logan, Clare V; Muzny, Donna M; Young, Alice C; et al. (Nat Genet, 2011)
Ciliary dysfunction leads to a broad range of overlapping phenotypes, collectively termed ciliopathies. This grouping is underscored by genetic overlap, where causal genes can also contribute modifier alleles to clinically distinct disorders. Here we show that mutations in TTC21B, which encodes the retrograde intraflagellar transport protein IFT139, cause both isolated nephronophthisis and syndromic Jeune asphyxiating thoracic dystrophy. Moreover, although resequencing of TTC21B in a large, clinically diverse ciliopathy cohort and matched controls showed a similar frequency of rare changes, in vivo and in vitro evaluations showed a significant enrichment of pathogenic alleles in cases (P < 0.003), suggesting that TTC21B contributes pathogenic alleles to ∼5% of ciliopathy cases. Our data illustrate how genetic lesions can be both causally associated with diverse ciliopathies and interact in trans with other disease-causing genes and highlight how saturated resequencing followed by functional analysis of all variants informs the genetic architecture of inherited disorders.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Ciliary Motility Disorders; Genetic Variation; Humans; Mice; Mutation; Pedigree; Photoreceptor Cells; Zebrafish

Whole-exome sequencing identifies compound heterozygous mutations in WDR62 in siblings with recurrent polymicrogyria. - Murdock, David R; Clark, Gary D; Bainbridge, Matthew N; Newsham, Irene; Wu, Yuan-Qing; Muzny, Donna M; Cheung, Sau Wai; Gibbs, Richard A; Ramocki, Melissa B (Am J Med Genet A, 2011)
Polymicrogyria is a disorder of neuronal development resulting in structurally abnormal cerebral hemispheres characterized by over-folding and abnormal lamination of the cerebral cortex. Polymicrogyria is frequently associated with severe neurologic deficits including intellectual disability, motor problems, and epilepsy. There are acquired and genetic causes of polymicrogyria, but most patients with a presumed genetic etiology lack a specific diagnosis. Here we report using whole-exome sequencing to identify compound heterozygous mutations in the WD repeat domain 62 (WDR62) gene as the cause of recurrent polymicrogyria in a sibling pair. Sanger sequencing confirmed that the siblings both inherited 1-bp (maternal allele) and 2-bp (paternal allele) frameshift deletions, which predict premature truncation of WDR62, a protein that has a role in early cortical development. The probands are from a non-consanguineous family of Northern European descent, suggesting that autosomal recessive PMG due to compound heterozygous mutation of WDR62 might be a relatively common cause of PMG in the population. Further studies to identify mutation frequency in the population are needed.
Keywords: Abnormalities, Multiple; Adult; Base Sequence; Cell Cycle Proteins; Child; Craniofacial Abnormalities; Exome; Female; Frameshift Mutation; Genetic Testing; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Malformations of Cortical Development; Mutation; Nerve Tissue Proteins; Sequence Analysis, DNA; Sequence Deletion; Siblings

Whole-genome sequencing for optimized patient management. - Bainbridge, Matthew N; Wiszniewski, Wojciech; Murdock, David R; Friedman, Jennifer; Gonzaga-Jauregui, Claudia; Newsham, Irene; Reid, Jeffrey G; Fink, John K; Morgan, Margaret B; Gingras, Marie-Claude; Muzny, Donna M; Hoang, Linh D; et al. (Sci Transl Med, 2011)
Whole-genome sequencing of patient DNA can facilitate diagnosis of a disease, but its potential for guiding treatment has been under-realized. We interrogated the complete genome sequences of a 14-year-old fraternal twin pair diagnosed with dopa (3,4-dihydroxyphenylalanine)-responsive dystonia (DRD; Mendelian Inheritance in Man #128230). DRD is a genetically heterogeneous and clinically complex movement disorder that is usually treated with l-dopa, a precursor of the neurotransmitter dopamine. Whole-genome sequencing identified compound heterozygous mutations in the SPR gene encoding sepiapterin reductase. Disruption of SPR causes a decrease in tetrahydrobiopterin, a cofactor required for the hydroxylase enzymes that synthesize the neurotransmitters dopamine and serotonin. Supplementation of l-dopa therapy with 5-hydroxytryptophan, a serotonin precursor, resulted in clinical improvements in both twins.
Keywords: Adolescent; Decision Making; Dystonic Disorders; Female; Genome, Human; Humans; Levodopa; Male; Patient Care; Pedigree; Sequence Analysis, DNA; Treatment Outcome; Twins, Dizygotic

Associations between dietary patterns and flow cytometry-measured biomarkers of inflammation and cellular activation in the Atherosclerosis Risk in Communities (ARIC) Carotid Artery MRI Study. - Nettleton, Jennifer A; Matijevic, Nena; Follis, Jack L; Folsom, Aaron R; Boerwinkle, Eric (Atherosclerosis, 2010)
BACKGROUND: Specific foods and overall dietary patterns are associated with soluble biomarkers of systemic inflammation and endothelial activation. However, no large epidemiological studies have evaluated relationships between such dietary factors and cell-specific markers of activation and inflammation as measured by flow cytometry. METHODS: Cell aggregates and multiple platelet and leukocyte markers were quantified by flow cytometry in fresh whole blood from 1101 white adults participating in the Carotid Artery MRI Study, a subset of the larger Atherosclerosis Risk in Communities (ARIC) Study. Two dietary patterns ("Healthy" and "Western") were empirically derived via principal components analysis using data collected by food frequency questionnaire. Cross-sectional associations between dietary patterns and flow cytometry-measured biomarkers were evaluated, adjusting for demographics and lifestyle factors, including medications use. RESULTS: After multivariable adjustment, monocyte lipopolysaccharide receptor (CD14), monocyte toll-like receptor-2, and platelet glycoprotein IIb (CD41) showed inverse associations with the Healthy dietary pattern (p=0.01, 0.04, and 0.01, respectively). In contrast, the Western dietary pattern was positively associated with CD41 and platelet-granulocyte aggregates (p=0.01 and 0.04, respectively). Independent of other dietary factors, alcohol consumption was inversely associated with levels of pan-leukocyte marker (CD45), P-selectin (CD62P) on PLA1 and on PLA2 platelets, and platelet-monocyte, platelet-granulocyte, and platelet-lymphocyte aggregates. CONCLUSION: Dietary patterns and alcohol intake were each cross-sectionally associated with select markers of cellular activation and inflammation measured by flow cytometry. These data are consistent with the hypothesis that holistic measures of dietary intake are associated with inflammation.
Keywords: Aged; Alcohol Drinking; Biomarkers; Carotid Arteries; Carotid Artery Diseases; Cross-Sectional Studies; Diet Records; Feeding Behavior; Female; Flow Cytometry; Humans; Inflammation; Inflammation Mediators; Leukocyte Common Antigens; Life Style; Linear Models; Lipopolysaccharide Receptors; Magnetic Resonance Angiography; Male; P-Selectin; Platelet Membrane Glycoprotein IIb; Principal Component Analysis; Risk Assessment; Risk Factors; Surveys and Questionnaires; Toll-Like Receptor 2; United States

Calpain-10 is a component of the obesity-related quantitative trait locus Adip1. - Cheverud, James M; Fawcett, Gloria L; Jarvis, Joseph P; Norgard, Elizabeth A; Pavlicev, Mihaela; Pletscher, L Susan; Polonsky, Kenneth S; Ye, Honggang; Bell, Graeme I; Semenkovich, Clay F (J Lipid Res, 2010)
We previously mapped Adip1, an obesity quantitative trait locus (QTL), to the central portion of murine chromosome 1 containing the calpain-10 (Capn10) gene. Human studies have associated calpain-10 (CAPN10) variants with type 2 diabetes and various metabolic traits. We performed a quantitative hybrid complementation test (QHCT) to determine whether differences attributed to Adip1 are the result of variant Capn10 alleles in LG/J and SM/J mice. We crossed LG/J and SM/J to wild-type (C57BL/6J) and Capn10 knockout (Capn10(-/-)) mice to form four F(1) hybrid groups: LG/J by wild-type, LG/J by Capn10(-/-), SM/J by wild-type, and SM/J by Capn10(-/-). We performed a two-way ANOVA with the experimental strain, tester strain, and their interaction as the factors. Significant interaction indicates a quantitative failure to complement. We found failure to complement for fat, organ, and body weights, and leptin, female free fatty acid, and triglyceride levels. Capn10(-/-) resulted in heavier weights and higher serum levels in LG/J crosses but not in SM/J crosses. For glucose tolerance and insulin response tests, the Capn10(-/-) allele resulted in lower glucose levels in crosses with SM/J but had no effect in the LG/J crosses. Differences between the LG/J and SM/J Capn10 alleles are the likely source of some of the QTL effects mapped to Adip1 in the LG/J-by-SM/J cross. Capn10 plays an important role in regulating obesity and diabetes in mice.
Keywords: Alleles; Animals; Calpain; Female; Gene Knockout Techniques; Genetic Complementation Test; Genetic Variation; Hybridization, Genetic; Male; Mice; Obesity; Quantitative Trait Loci

A catalog of reference genomes from the human microbiome. - Nelson, Karen E; Weinstock, George M; Highlander, Sarah K; Worley, Kim C; Creasy, Heather Huot; Wortman, Jennifer Russo; Rusch, Douglas B; Mitreva, Makedonka; Sodergren, Erica; Chinwalla, Asif T; Feldgarden, Michael; Gevers, Dirk; et al. (Science, 2010)
The human microbiome refers to the community of microorganisms, including prokaryotes, viruses, and microbial eukaryotes, that populate the human body. The National Institutes of Health launched an initiative that focuses on describing the diversity of microbial species that are associated with health and disease. The first phase of this initiative includes the sequencing of hundreds of microbial reference genomes, coupled to metagenomic sequencing from multiple body sites. Here we present results from an initial reference genome sequencing of 178 microbial genomes. From 547,968 predicted polypeptides that correspond to the gene complement of these strains, previously unidentified ("novel") polypeptides that had both unmasked sequence length greater than 100 amino acids and no BLASTP match to any nonreference entry in the nonredundant subset were defined. This analysis resulted in a set of 30,867 polypeptides, of which 29,987 (approximately 97%) were unique. In addition, this set of microbial genomes allows for approximately 40% of random sequences from the microbiome of the gastrointestinal tract to be associated with organisms based on the match criteria used. Insights into pan-genome analysis suggest that we are still far from saturating microbial species genetic data sets. In addition, the associated metrics and standards used by our group for quality assurance are presented.
Keywords: Bacteria; Bacterial Proteins; Biodiversity; Computational Biology; Databases, Genetic; Gastrointestinal Tract; Genes, Bacterial; Genetic Variation; Genome, Archaeal; Genome, Bacterial; Humans; Metagenome; Metagenomics; Mouth; Peptides; Phylogeny; Respiratory System; Sequence Analysis, DNA; Skin; Urogenital System

Comparative genomics of Gardnerella vaginalis strains reveals substantial differences in metabolic and virulence potential. - Yeoman, Carl J; Yildirim, Suleyman; Thomas, Susan M; Durkin, A Scott; Torralba, Manolito; Sutton, Granger; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon P; Muzny, Donna M; Qin, Xiang; Gibbs, Richard A; et al. (PLoS One, 2010)
BACKGROUND: Gardnerella vaginalis is described as a common vaginal bacterial species whose presence correlates strongly with bacterial vaginosis (BV). Here we report the genome sequencing and comparative analyses of three strains of G. vaginalis. Strains 317 (ATCC 14019) and 594 (ATCC 14018) were isolated from the vaginal tracts of women with symptomatic BV, while Strain 409-05 was isolated from a healthy, asymptomatic individual with a Nugent score of 9. PRINCIPAL FINDINGS: Substantial genomic rearrangement and heterogeneity were observed that appeared to have resulted from both mobile elements and substantial lateral gene transfer. These genomic differences translated to differences in metabolic potential. All strains are equipped with significant virulence potential, including genes encoding the previously described vaginolysin, pili for cytoadhesion, EPS biosynthetic genes for biofilm formation, and antimicrobial resistance systems, We also observed systems promoting multi-drug and lantibiotic extrusion. All G. vaginalis strains possess a large number of genes that may enhance their ability to compete with and exclude other vaginal colonists. These include up to six toxin-antitoxin systems and up to nine additional antitoxins lacking cognate toxins, several of which are clustered within each genome. All strains encode bacteriocidal toxins, including two lysozyme-like toxins produced uniquely by strain 409-05. Interestingly, the BV isolates encode numerous proteins not found in strain 409-05 that likely increase their pathogenic potential. These include enzymes enabling mucin degradation, a trait previously described to strongly correlate with BV, although commonly attributed to non-G. vaginalis species. CONCLUSIONS: Collectively, our results indicate that all three strains are able to thrive in vaginal environments, and therein the BV isolates are capable of occupying a niche that is unique from 409-05. Each strain has significant virulence potential, although genomic and metabolic differences, such as the ability to degrade mucin, indicate that the detection of G. vaginalis in the vaginal tract provides only partial information on the physiological potential of the organism.
Keywords: Bacterial Proteins; Female; Gardnerella vaginalis; Genomics; Humans; Male; Molecular Sequence Data; Phylogeny; Vagina; Vaginosis, Bacterial; Virulence

Complete Khoisan and Bantu genomes from southern Africa. - Schuster, Stephan C; Miller, Webb; Ratan, Aakrosh; Tomsho, Lynn P; Giardine, Belinda; Kasson, Lindsay R; Harris, Robert S; Petersen, Desiree C; Zhao, Fangqing; Qi, Ji; Alkan, Can; Kidd, Jeffrey M; et al. (Nature, 2010)
The genetic structure of the indigenous hunter-gatherer peoples of southern Africa, the oldest known lineage of modern human, is important for understanding human diversity. Studies based on mitochondrial and small sets of nuclear markers have shown that these hunter-gatherers, known as Khoisan, San, or Bushmen, are genetically divergent from other humans. However, until now, fully sequenced human genomes have been limited to recently diverged populations. Here we present the complete genome sequences of an indigenous hunter-gatherer from the Kalahari Desert and a Bantu from southern Africa, as well as protein-coding regions from an additional three hunter-gatherers from disparate regions of the Kalahari. We characterize the extent of whole-genome and exome diversity among the five men, reporting 1.3 million novel DNA differences genome-wide, including 13,146 novel amino acid variants. In terms of nucleotide substitutions, the Bushmen seem to be, on average, more different from each other than, for example, a European and an Asian. Observed genomic differences between the hunter-gatherers and others may help to pinpoint genetic adaptations to an agricultural lifestyle. Adding the described variants to current databases will facilitate inclusion of southern Africans in medical research efforts, particularly when family and medical histories can be correlated with genome-wide data.
Keywords: Asian People; Black People; Ethnicity; Exons; Genetics, Medical; Genome, Human; Humans; Phylogeny; Polymorphism, Single Nucleotide; South Africa; White People

Deep resequencing reveals excess rare recent variants consistent with explosive population growth. - Coventry, Alex; Bull-Otterson, Lara M; Liu, Xiaoming; Clark, Andrew G; Maxwell, Taylor J; Crosby, Jacy; Hixson, James E; Rea, Thomas J; Donna M Muzny; Lewis, Lora R; David A Wheeler; Aniko Sabo; et al. (Nat Commun, 2010)
Accurately determining the distribution of rare variants is an important goal of human genetics, but resequencing of a sample large enough for this purpose has been unfeasible until now. Here, we applied Sanger sequencing of genomic PCR amplicons to resequence the diabetes-associated genes KCNJ11 and HHEX in 13,715 people (10,422 European Americans and 3,293 African Americans) and validated amplicons potentially harbouring rare variants using 454 pyrosequencing. We observed far more variation (expected variant-site count ∼578) than would have been predicted on the basis of earlier surveys, which could only capture the distribution of common variants. By comparison with earlier estimates based on common variants, our model shows a clear genetic signal of accelerating population growth, suggesting that humanity harbours a myriad of rare, deleterious variants, and that disease risk and the burden of disease in contemporary populations may be heavily influenced by the distribution of rare variants.

Discovery of novel microRNAs in female reproductive tract using next generation sequencing. - Creighton, Chad J; Benham, Ashley L; Zhu, Huifeng; Khan, Mahjabeen F; Reid, Jeffrey G; Nagaraja, Ankur K; Fountain, Michael D; Dziadek, Olivia; Han, Derek; Ma, Lang; Kim, Jong; Hawkins, Shannon M; et al. (PLoS One, 2010)
MicroRNAs (miRNAs) are small non-coding RNAs that mediate post-transcriptional gene silencing. Over 700 human miRNAs have currently been identified, many of which are mutated or de-regulated in diseases. Here we report the identification of novel miRNAs through deep sequencing the small RNAome (<30 nt) of over 100 tissues or cell lines derived from human female reproductive organs in both normal and disease states. These specimens include ovarian epithelium and ovarian cancer, endometrium and endometriomas, and uterine myometrium and uterine smooth muscle tumors. Sequence reads not aligning with known miRNAs were each mapped to the genome to extract flanking sequences. These extended sequence regions were folded in silico to identify RNA hairpins. Sequences demonstrating the ability to form a stem loop structure with low minimum free energy (<-25 kcal) and predicted Drosha and Dicer cut sites yielding a mature miRNA sequence matching the actual sequence were considered putative novel miRNAs. Additional confidence was achieved when putative novel hairpins assembled a collection of sequences highly similar to the putative mature miRNA but with heterogeneous 3'-ends. A confirmed novel miRNA fulfilled these criteria and had its "star" sequence in our collection. We found 7 distinct confirmed novel miRNAs, and 51 additional novel miRNAs that represented highly confident predictions but without detectable star sequences. Our novel miRNAs were detectable in multiple samples, but expressed at low levels and not specific to any one tissue or cell type. To date, this study represents the largest set of samples analyzed together to identify novel miRNAs.
Keywords: Cell Line; DNA, Complementary; Female; Genetic Techniques; Genitalia, Female; Humans; MicroRNAs; Nucleic Acid Conformation; Ovarian Neoplasms; Ovary; Polymerase Chain Reaction; Ribonuclease III; Sequence Analysis, DNA; Tissue Distribution

The fms21 (pilA)-fms20 locus encoding one of four distinct pili of Enterococcus faecium is harboured on a large transferable plasmid associated with gut colonization and virulence. - Kim, David S; Singh, Kavindra V; Nallapareddy, Sreedhar R; Qin, Xiang; Panesso, Diana; Arias, Cesar A; Murray, Barbara E (J Med Microbiol, 2010)
Keywords: Chromosome Mapping; Electrophoresis, Gel, Pulsed-Field; Enterococcus faecium; Fimbriae, Bacterial; Humans; Intestines; Plasmids; Virulence

A full-length cDNA resource for the pea aphid, Acyrthosiphon pisum. - Shigenobu, S; Richards, S; Cree, A G; Morioka, M; Fukatsu, T; Kudo, T; Miyagishima, S; Gibbs, R A; Stern, D L; Nakabachi, A (Insect Mol Biol, 2010)
Large collections of full-length cDNAs are important resources for genome annotation and functional genomics. We report the creation of a collection of 50 599 full-length cDNA clones from the pea aphid, Acyrthosiphon pisum. Sequencing from 5' and 3' ends of the clones generated 97 828 high-quality expressed sequence tags, representing approximately 9000 genes. These sequences were imported to AphidBase and are shown to play crucial roles in both automatic gene prediction and manual annotation. Our detailed analyses demonstrated that the full-length cDNAs can further improve gene models and can even identify novel genes that are not included in the current version of the official gene set. This full-length cDNA collection can be utilized for a wide variety of functional studies, serving as a community resource for the study of the functional genomics of the pea aphid.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Animals; Aphids; Base Sequence; DNA Primers; DNA, Complementary; Expressed Sequence Tags; Gene Library; Genome, Insect; Host-Pathogen Interactions; Models, Genetic; Pisum sativum

Functional and evolutionary insights from the genomes of three parasitoid Nasonia species. - Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; et al. (Science, 2010)
We report here genome sequences and comparative analyses of three closely related parasitoid wasps: Nasonia vitripennis, N. giraulti, and N. longicornis. Parasitoids are important regulators of arthropod populations, including major agricultural pests and disease vectors, and Nasonia is an emerging genetic model, particularly for evolutionary and developmental genetics. Key findings include the identification of a functional DNA methylation tool kit; hymenopteran-specific genes including diverse venoms; lateral gene transfers among Pox viruses, Wolbachia, and Nasonia; and the rapid evolution of genes involved in nuclear-mitochondrial interactions that are implicated in speciation. Newly developed genome resources advance Nasonia for genetic research, accelerate mapping and cloning of quantitative trait loci, and will ultimately provide tools and knowledge for further increasing the utility of parasitoids as pest insect-control agents.
Keywords: Animals; Arthropods; Biological Evolution; DNA Methylation; DNA Transposable Elements; Female; Gene Transfer, Horizontal; Genes, Insect; Genetic Speciation; Genetic Variation; Genome, Insect; Host-Parasite Interactions; Insect Proteins; Insect Viruses; Insecta; Male; Molecular Sequence Data; Quantitative Trait Loci; Recombination, Genetic; Sequence Analysis, DNA; Wasp Venoms; Wasps; Wolbachia

Integrating common and rare genetic variation in diverse human populations. - Altshuler, David M; Gibbs, Richard A; Peltonen, Leena; Altshuler, David M; Gibbs, Richard A; Peltonen, Leena; Dermitzakis, Emmanouil; Schaffner, Stephen F; Yu, Fuli; Peltonen, Leena; Dermitzakis, Emmanouil; Bonnen, Penelope E; et al. (Nature, 2010)
Despite great progress in identifying genetic variants that influence human disease, most inherited risk remains unexplained. A more complete understanding requires genome-wide studies that fully examine less common alleles in populations with a wide range of ancestry. To inform the design and interpretation of such studies, we genotyped 1.6 million common single nucleotide polymorphisms (SNPs) in 1,184 reference individuals from 11 global populations, and sequenced ten 100-kilobase regions in 692 of these individuals. This integrated data set of common and rare alleles, called 'HapMap 3', includes both SNPs and copy number polymorphisms (CNPs). We characterized population-specific differences among low-frequency variants, measured the improvement in imputation accuracy afforded by the larger reference panel, especially in imputing SNPs with a minor allele frequency of <or=5%, and demonstrated the feasibility of imputing newly discovered CNPs and SNPs. This expanded public resource of genome variants in global populations supports deeper interrogation of genomic variation and its role in human disease, and serves as a step towards a high-resolution map of the landscape of human genetic variation.
Keywords: DNA Copy Number Variations; Genome, Human; Human Genome Project; Humans; Polymorphism, Single Nucleotide; Population Groups

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; White People

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin; White People

MMP2 genetic variation is associated with measures of fibrous cap thickness: The Atherosclerosis Risk in Communities Carotid MRI Study. - Volcik, Kelly A; Campbell, Stephen; Chambless, Lloyd E; Coresh, Josef; Folsom, Aaron R; Mosley, Thomas H; Ni, Hanyu; Wagenknecht, Lynne E; Wasserman, Bruce A; Boerwinkle, Eric (Atherosclerosis, 2010)
OBJECTIVE: Genetic variation in matrix metalloproteinase (MMP) promoter regions alter the transcriptional activity of MMPs and has been consistently associated with CHD, presumably through plaque degradation and remodeling. We examined the association of MMP promoter variation with multiple plaque characteristics measured by gadolinium-enhanced MRI among 1700 participants in the Atherosclerosis Risk in Communities (ARIC) Carotid MRI Study. METHODS: For the analyses presented here, 1700 participants of the biracial ARIC Carotid MRI Study ( approximately 1000 participants with thick carotid artery walls and approximately 700 randomly sampled participants) were evaluated for associations of MMP genetic variation with multiple plaque characteristics, including carotid artery wall thickness, lipid core and fibrous cap measures. MRI studies were performed on a 1.5T scanner equipped with a bilateral 4-element phased array carotid coil. RESULTS: Fifty-one percent of the participants were female, 77% white, 23% African American, and the mean age was 70 years. MMP2 C-1306T variant genotypes (CT+TT) were significantly associated with higher cap thickness measures, but not with wall thickness or lipid core measures. Individuals with the CC genotype had approximately 0.1mm thinner cap thickness compared to those carrying a T allele (P=0.02). CONCLUSION: Genetic variation within the MMP2 promoter region was associated with cap thickness and therefore may influence the role of MMP2 in plaque vulnerability.
Keywords: Aged; Atherosclerosis; Carotid Arteries; Female; Genetic Variation; Genotype; Humans; Magnetic Resonance Imaging; Male; Matrix Metalloproteinase 2; Middle Aged; Promoter Regions, Genetic; Prospective Studies; Transcription, Genetic

Pretranscriptional regulation of Tgf-beta1 by PI polyamide prevents scarring and accelerates wound healing of the cornea after exposure to alkali. - Chen, Min; Matsuda, Hiroyuki; Wang, Linghua; Watanabe, Takayoshi; Kimura, Makoto T; Igarashi, Jun; Wang, Xiaofei; Sakimoto, Tohru; Fukuda, Noboru; Sawa, Mitsuru; Nagase, Hiroki (Mol Ther, 2010)
Corneal alkali burns are a serious clinical problem that often leads to permanent visual impairment. In this process, transforming growth factor (Tgf)-beta1 is upregulated and involved in the response to corneal injury and the process of corneal stromal scarring. To develop an efficient compound to inhibit Tgf-beta1 in the cornea, we designed GB1201, a pyrrole-imidazole (PI) polyamide targeting rat Tgf-beta1 gene promoter to the activator protein-1 (AP-1) binding site. GB1201 showed a high binding affinity to the target DNA sequence in the gel mobility shift and Biacore assays. GB1201 significantly inhibited the rat Tgf-beta1 gene promoter activity in HEK (human embryonic kidney) 293 cells in a concentration-dependent manner. Topically administrated GB1201 was distributed immediately to the nuclei of all cell layers of the cornea and remained for 24 hours. A corneal alkali burn model in rats was used to evaluate the therapeutic efficacy of GB1201. GB1201 suppressed the upregulation of Tgf-beta1 in the burned cornea, both in the mRNA and protein levels. Moreover, daily treatment with GB1201 for a week significantly improved the corneal tissue wound healing, reduced corneal stromal scarring, and prevented corneal haze formation. Our data suggest that PI polyamide may open new opportunities for therapeutic intervention in the treatment of chemically burned corneas.
Keywords: Animals; Binding Sites; Cicatrix; Cornea; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Imidazoles; Nylons; Promoter Regions, Genetic; Pyrroles; Rats; RNA, Messenger; Transforming Growth Factor beta1; Wound Healing

Whole exome capture in solution with 3 Gbp of data. - Bainbridge, Matthew N; Wang, Min; Burgess, Daniel L; Kovar, Christie; Rodesch, Matthew J; D'Ascenzo, Mark; Kitzman, Jacob; Wu, Yuan-Qing; Newsham, Irene; Richmond, Todd A; Jeddeloh, Jeffrey A; Muzny, Donna; et al. (Genome Biol, 2010)
We have developed a solution-based method for targeted DNA capture-sequencing that is directed to the complete human exome. Using this approach allows the discovery of greater than 95% of all expected heterozygous singe base variants, requires as little as 3 Gbp of raw sequence data and constitutes an effective tool for identifying rare coding alleles in large scale genomic studies.
Keywords: Base Pairing; Databases, Nucleic Acid; Exons; Gene Library; Haplotypes; Humans; Polymorphism, Single Nucleotide; Reproducibility of Results; Sequence Alignment; Sequence Analysis, DNA; Solutions

Whole-genome sequencing in a patient with Charcot-Marie-Tooth neuropathy. - Lupski, James R; Reid, Jeffrey G; Gonzaga-Jauregui, Claudia; Rio Deiros, David; Chen, David C Y; Nazareth, Lynne; Bainbridge, Matthew; Dinh, Huyen; Jing, Chyn; Wheeler, David A; McGuire, Amy L; Zhang, Feng; et al. (N Engl J Med, 2010)
BACKGROUND: Whole-genome sequencing may revolutionize medical diagnostics through rapid identification of alleles that cause disease. However, even in cases with simple patterns of inheritance and unambiguous diagnoses, the relationship between disease phenotypes and their corresponding genetic changes can be complicated. Comprehensive diagnostic assays must therefore identify all possible DNA changes in each haplotype and determine which are responsible for the underlying disorder. The high number of rare, heterogeneous mutations present in all humans and the paucity of known functional variants in more than 90% of annotated genes make this challenge particularly difficult. Thus, the identification of the molecular basis of a genetic disease by means of whole-genome sequencing has remained elusive. We therefore aimed to assess the usefulness of human whole-genome sequencing for genetic diagnosis in a patient with Charcot-Marie-Tooth disease. METHODS: We identified a family with a recessive form of Charcot-Marie-Tooth disease for which the genetic basis had not been identified. We sequenced the whole genome of the proband, identified all potential functional variants in genes likely to be related to the disease, and genotyped these variants in the affected family members. RESULTS: We identified and validated compound, heterozygous, causative alleles in SH3TC2 (the SH3 domain and tetratricopeptide repeats 2 gene), involving two mutations, in the proband and in family members affected by Charcot-Marie-Tooth disease. Separate subclinical phenotypes segregated independently with each of the two mutations; heterozygous mutations confer susceptibility to neuropathy, including the carpal tunnel syndrome. CONCLUSIONS: As shown in this study of a family with Charcot-Marie-Tooth disease, whole-genome sequencing can identify clinically relevant variants and provide diagnostic information to inform the care of patients.
Keywords: Adult; Aged; Aged, 80 and over; Charcot-Marie-Tooth Disease; Codon, Nonsense; Female; Genes, Recessive; Genetic Association Studies; Genome, Human; Genotype; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

A-beta-subtype of ketosis-prone diabetes is not predominantly a monogenic diabetic syndrome. - Haaland, Wade C; Scaduto, Diane I; Maldonado, Mario R; Mansouri, Dena L; Nalini, Ramaswami; Iyer, Dinakar; Patel, Sanjeet; Guthikonda, Anu; Hampe, Christiane S; Balasubramanyam, Ashok; Metzker, Michael L (Diabetes Care, 2009)
OBJECTIVE: Ketosis-prone diabetes (KPD) is an emerging syndrome that encompasses several distinct phenotypic subgroups that share a predisposition to diabetic ketoacidosis. We investigated whether the A-beta- subgroup of KPD, characterized by complete insulin dependence, absent beta-cell functional reserve, lack of islet cell autoantibodies, and strong family history of type 2 diabetes, represents a monogenic form of diabetes. RESEARCH DESIGN AND METHODS: Over 8 years, 37 patients with an A-beta- phenotype were identified in our longitudinally followed cohort of KPD patients. Seven genes, including hepatocyte nuclear factor 4A (HNF4A), glucokinase (GCK), HNF1A, pancreas duodenal homeobox 1 (PDX1), HNF1B, neurogenic differentiation 1 (NEUROD1), and PAX4, were directly sequenced in all patients. Selected gene regions were also sequenced in healthy, unrelated ethnically matched control subjects, consisting of 84 African American, 96 Caucasian, and 95 Hispanic subjects. RESULTS: The majority (70%) of the A-beta- KPD patients had no significant causal polymorphisms in either the proximal promoter or coding regions of the seven genes. The combination of six potentially significant low-frequency, heterozygous sequence variants in HNF-1 alpha (A174V or G574S), PDX1 (putative 5'-untranslated region CCAAT box, P33T, or P239Q), or PAX4 (R133W) were found in 27% (10/37) of patients, with one additional patient revealing two variants, PDX1 P33T and PAX4 R133W. The A174V variant has not been previously reported. CONCLUSIONS: Despite its well-circumscribed, robust, and distinctive phenotype of severe, nonautoimmune-mediated beta-cell dysfunction, A-beta- KPD is most likely not a predominantly monogenic diabetic syndrome. Several A-beta- KPD patients have low-frequency variants in HNF1A, PDX1, or PAX4 genes, which may be of functional significance in their pathophysiology.
Keywords: Adult; Autoantibodies; Basic Helix-Loop-Helix Transcription Factors; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Female; Genetic Variation; Glucokinase; Glycated Hemoglobin; Hepatocyte Nuclear Factor 1-beta; Hepatocyte Nuclear Factor 4; Homeodomain Proteins; Humans; Insulin; Insulin-Secreting Cells; Islets of Langerhans; Male; Middle Aged; Paired Box Transcription Factors; Trans-Activators

Apoptosis, autophagy, accelerated senescence and reactive oxygen in the response of human breast tumor cells to adriamycin. - Di, Xu; Shiu, Robert P; Newsham, Irene F; Gewirtz, David A (Biochem Pharmacol, 2009)
Although the primary response to Adriamycin (doxorubicin) in p53 mutant MDA-MB231 and p53 null MCF-7/E6 breast tumor cells is apoptotic cell death, the residual surviving population appears to be in a state of senescence, based on cell morphology, beta galactosidase staining, induction of p21(waf1/cip1) and down regulation of cdc2/cdk1. Suppression of apoptosis in MDA-MB231 and MCF-7/E6 cells treated with Adriamycin using the broad spectrum caspase inhibitor, zvad-Fmk, results in substantial induction of autophagy. Overall sensitivity to Adriamycin, measured by clonogenic survival, is not altered in the cells undergoing autophagy, consistent with autophagy contributing to cell death in response to Adriamycin. The free radical scavengers, glutathione and N-acetyl cysteine attenuate the accelerated senescence response to Adriamycin in MCF-7 cells as well as in MDA-MB231 and MCF-7/E6 cells, but protect primarily the MCF-7 cells, indicating that reactive oxygen is unlikely to be directly responsible for Adriamycin toxicity in breast tumor cells. Expression of caspase 3 or induced expression of c-myc in MCF-7 cells fails to abrogate accelerated senescence induced by Adriamycin. Taken together, these studies suggest that accelerated senescence induced by Adriamycin is similar in cells with wild type p53 and in cells lacking functional p53 with regard to the upregulation of p21(waf1/cip1), down regulation of cdc2 and the involvement of reactive oxygen species. Furthermore, accelerated senescence, autophagy and apoptosis all appear to be effective in suppressing self-renewal capacity in breast tumor cells exposed to Adriamycin.
Keywords: Apoptosis; Autophagy; Breast Neoplasms; Cell Line, Tumor; Cellular Senescence; Doxorubicin; Humans; Reactive Oxygen Species

Carbohydrate intake modifies associations between ANGPTL4[E40K] genotype and HDL-cholesterol concentrations in White men from the Atherosclerosis Risk in Communities (ARIC) study. - Nettleton, Jennifer A; Volcik, Kelly A; Hoogeveen, Ron C; Boerwinkle, Eric (Atherosclerosis, 2009)
BACKGROUND: Common allelic variation in the angiopoietin-like 4 gene (ANGPTL4[E40K]) has been associated with low triglyceride (TG) and high HDL-C. OBJECTIVE: We examined whether dietary macronutrient intake modified associations between ANGPTL4[E40K] variation and TG and HDL-C in White men and women from the Atherosclerosis Risk in Communities study. DESIGN: Diet was assessed by food frequency questionnaire. Intake of fat (total fat [TF], saturated fat [SF], monounsaturated fat [MUFA], polyunsaturated fat [PUFA], and n-3 PUFA) and carbohydrate were expressed as percentage of total energy intake. ANGPTL4 A allele carriers (n=148 in men, 200 in women) were compared to non-carriers (n=3667 in men, 4496 in women). Interactions were tested separately in men and women, adjusting for study center, age, smoking, physical activity, BMI, and alcohol intake. RESULTS: ANGPTL4 A allele carriers had significantly greater HDL-C and lower TG than non-carriers (p<or=0.001). In all participants, carbohydrate intake was inversely associated with HDL-C and positively associated with TG, whereas TF, SF, and MUFA showed opposite associations with TG and HDL-C (p<0.001). These relations were uniform between sex-specific genotype groups, with one exception. In men, but not women, the inverse association between carbohydrate and HDL-C was stronger in A allele carriers (beta+/-S.E. -1.80+/-0.54) than non-carriers (beta+/-S.E. -0.54+/-0.11, p(interaction)=0.04 in men and 0.69 in women; p 3-way interaction=0.14). CONCLUSIONS: These data suggest that ANGPTL4 variation and relative contributions of dietary fat and carbohydrate influence TG and HDL-C concentrations. In men, ANGPTL4 variation and dietary carbohydrate may interactively influence HDL-C.
Keywords: Alleles; Angiopoietin-Like Protein 4; Angiopoietins; Atherosclerosis; Cholesterol; Cholesterol, HDL; Community Health Services; Diet; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Nutritional Sciences; Risk; Sex Factors; Triglycerides; White People

A collagen-binding adhesin, Acb, and ten other putative MSCRAMM and pilus family proteins of Streptococcus gallolyticus subsp. gallolyticus (Streptococcus bovis Group, biotype I). - Sillanpaa, Jouko; Nallapareddy, Sreedhar R; Qin, Xiang; Singh, Kavindra V; Muzny, Donna M; Kovar, Christie L; Nazareth, Lynne V; Gibbs, Richard A; Ferraro, Mary J; Steckelberg, James M; Weinstock, George M; Murray, Barbara E (J Bacteriol, 2009)
Members of the Streptococcus bovis group are important causes of endocarditis. However, factors associated with their pathogenicity, such as adhesins, remain uncharacterized. We recently demonstrated that endocarditis-derived Streptococcus gallolyticus subsp. gallolyticus isolates frequently adhere to extracellular matrix (ECM) proteins. Here, we generated a draft genome sequence of an ECM protein-adherent S. gallolyticus subsp. gallolyticus strain and found, by genome-wide analyses, 11 predicted LPXTG-type cell wall-anchored proteins with characteristics of MSCRAMMs, including a modular architecture of domains predicted to adopt immunoglobulin (Ig)-like folding. A recombinant segment of one of these, Acb, showed high-affinity binding to immobilized collagen, and cell surface expression of Acb correlated with the presence of acb and collagen adherence of isolates. Three of the 11 proteins have similarities to major pilus subunits and are organized in separate clusters, each including a second Ig-fold-containing MSCRAMM and a class C sortase, suggesting that the sequenced strain encodes three distinct types of pili. Reverse transcription-PCR demonstrated that all three genes of one cluster, acb-sbs7-srtC1, are cotranscribed, consistent with pilus operons of other gram-positive bacteria. Further analysis detected expression of all 11 genes in cells grown to mid to late exponential growth phases. Wide distribution of 9 of the 11 genes was observed among S. gallolyticus subsp. gallolyticus isolates with fewer genes present in other S. bovis group species/subspecies. The high prevalence of genes encoding putative MSCRAMMs and pili, including a collagen-binding MSCRAMM, among S. gallolyticus subsp. gallolyticus isolates may play an important role in the predominance of this subspecies in S. bovis endocarditis.
Keywords: Adhesins, Bacterial; Fimbriae, Bacterial; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genome, Bacterial; Multigene Family; Streptococcus

The genome sequence of taurine cattle: a window to ruminant biology and evolution. - Elsik, Christine G; Tellam, Ross L; Worley, Kim C; Gibbs, Richard A; Muzny, Donna M; Weinstock, George M; Adelson, David L; Eichler, Evan E; Elnitski, Laura; Guigó, Roderic; Hamernik, Debora L; Kappes, Steve M; et al. (Science, 2009)
To understand the biology and evolution of ruminants, the cattle genome was sequenced to about sevenfold coverage. The cattle genome contains a minimum of 22,000 genes, with a core set of 14,345 orthologs shared among seven mammalian species of which 1217 are absent or undetected in noneutherian (marsupial or monotreme) genomes. Cattle-specific evolutionary breakpoint regions in chromosomes have a higher density of segmental duplications, enrichment of repetitive elements, and species-specific variations in genes associated with lactation and immune responsiveness. Genes involved in metabolism are generally highly conserved, although five metabolic genes are deleted or extensively diverged from their human orthologs. The cattle genome sequence thus provides a resource for understanding mammalian evolution and accelerating livestock genetic improvement for milk and meat production.
Keywords: Alternative Splicing; Animals; Animals, Domestic; Biological Evolution; Cattle; Evolution, Molecular; Female; Genetic Variation; Genome; Humans; Male; MicroRNAs; Molecular Sequence Data; Proteins; Sequence Analysis, DNA; Species Specificity; Synteny

Genome-wide survey of SNP variation uncovers the genetic structure of cattle breeds. - Gibbs, Richard A; Taylor, Jeremy F; Van Tassell, Curtis P; Barendse, William; Eversole, Kellye A; Gill, Clare A; Green, Ronnie D; Hamernik, Debora L; Kappes, Steven M; Lien, Sigbjørn; Matukumalli, Lakshmi K; McEwan, John C; et al. (Science, 2009)
The imprints of domestication and breed development on the genomes of livestock likely differ from those of companion animals. A deep draft sequence assembly of shotgun reads from a single Hereford female and comparative sequences sampled from six additional breeds were used to develop probes to interrogate 37,470 single-nucleotide polymorphisms (SNPs) in 497 cattle from 19 geographically and biologically diverse breeds. These data show that cattle have undergone a rapid recent decrease in effective population size from a very large ancestral population, possibly due to bottlenecks associated with domestication, selection, and breed formation. Domestication and artificial selection appear to have left detectable signatures of selection within the cattle genome, yet the current levels of diversity within breeds are at least as great as exists within humans.
Keywords: Animals; Breeding; Cattle; Female; Gene Frequency; Genetic Variation; Genome; Male; Molecular Sequence Data; Mutation; Polymorphism, Single Nucleotide; Population Density

Genomics. Genome project standards in a new era of sequencing. - Chain, P S G; Grafham, D V; Fulton, R S; Fitzgerald, M G; Hostetler, J; Muzny, D; Ali, J; Birren, B; Bruce, D C; Buhay, C; Cole, J R; Ding, Y; et al. (Science, 2009)
More detailed sequence standards that keep up with revolutionary sequencing technologies will aid the research community in evaluating data.
Keywords: Computational Biology; Databases, Nucleic Acid; Genome; Genomics; Sequence Analysis, DNA

Glucocorticoid receptor gene variant in the 3' untranslated region is associated with multiple measures of blood pressure. - Chung, Charles C; Shimmin, Lawrence; Natarajan, Sivamani; Hanis, Craig L; Boerwinkle, Eric; Hixson, James E (J Clin Endocrinol Metab, 2009)
CONTEXT: The glucocorticoid receptor (GR) is a key hormone in the hypothalamus-pituitary-adrenal axis that regulates many pathways including blood pressure homeostasis. Thus, GR gene variation may influence interindividual differences in blood pressure in human populations. OBJECTIVE: We resequenced individual GR alleles for comprehensive discovery of GR variants and their chromosomal phase in three major American ethnic groups. We examined the influence of GR variants on blood pressure in large numbers of families using family-based association methods. DESIGN AND PARTICIPANTS: For association studies, we genotyped GR variants in family members from the Genetic Epidemiology Network of Arteriopathy (GENOA) study that were measured for multiple blood pressure traits. The GENOA families consisted of African-Americans, Mexican-Americans, and European-Americans. MAIN MEASUREMENTS: The blood pressure measurements for association studies included systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure. RESULTS: Single-nucleotide polymorphisms (SNPs) identified by resequencing were tested for associations with blood pressure measures in GENOA families. Analysis of individual SNPs identified significant associations of rs6198 A/G in exon 9beta with multiple blood pressure measures in European-Americans. Analysis of GR haplotypes found significant associations of a haplotype that is distinguished by rs6198 A/G. CONCLUSIONS: Significant associations of blood pressure with rs6198 A/G likely reflect allelic effects on GR signaling. This SNP disrupts a 3' untranslated region sequence element in exon 9beta that destabilizes mRNA, resulting in increased production of the inactive GRbeta isoform. Excess heterodimerization with the active GRalpha isoform may reduce GR signaling with subsequent physiological effects on blood pressure regulation.
Keywords: 3' Untranslated Regions; Blood Pressure; Cell Line; Haplotypes; Humans; Polymorphism, Single Nucleotide; Protein Isoforms; Receptors, Glucocorticoid

The prolonged effect of repeated maternal glucocorticoid exposure on the maternal and fetal leptin/insulin-like growth factor axis in Papio species. - Schlabritz-Loutsevitch, Natalia E; Lopez-Alvarenga, Juan C; Comuzzie, Anthony G; Miller, Myrna M; Ford, Stephen P; Li, Cun; Hubbard, Gene B; Ferry, Robert J; Nathanielsz, Peter W (Reprod Sci, 2009)
BACKGROUND: Maternal obesity represents a risk factor for pregnancy-related complications. Glucocorticoids are known to promote obesity in adults. METHODS: We evaluated maternal and fetal metabolic changes during and after 3 weekly courses of betamethasone administered to pregnant baboons (Papio subspecies) at doses equivalent to those given to pregnant women. RESULTS: Betamethasone administration during the second half of pregnancy increased maternal weight but neither maternal food intake nor fetal weight, as assessed at the end of gestation. Betamethasone increased maternal serum glucose concentration, the ratio of insulin-like growth factor-I and insulin-like growth factor binding protein-3, and serum leptin during treatment (normalized by 17, 35, and 45 days posttreatment, respectively, for each parameter). Maternal and fetal serum leptin concentrations did not differ between groups at the end of gestation. CONCLUSION: Prolonged maternal hyperleptinemia caused by betamethasone administration in the second half of gestation did not change fetal metabolic parameters measured and placental leptin distribution at the end of gestation.
Keywords: Animals; Betamethasone; Blood Glucose; Body Weight; Cesarean Section; Cholesterol; Drug Administration Schedule; Eating; Female; Fetal Blood; Fetal Weight; Fetus; Gestational Age; Glucocorticoids; Hydrocortisone; Injections, Intramuscular; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Insulin-Like Growth Factor II; Leptin; Maternal-Fetal Exchange; Papio cynocephalus; Placenta; Pregnancy

Replication of long-bone length QTL in the F9-F10 LG,SM advanced intercross. - Norgard, Elizabeth A; Jarvis, Joseph P; Roseman, Charles C; Maxwell, Taylor J; Kenney-Hunt, Jane P; Samocha, Kaitlin E; Pletscher, L Susan; Wang, Bing; Fawcett, Gloria L; Leatherwood, Christopher J; Wolf, Jason B; Cheverud, James M (Mamm Genome, 2009)
Quantitative trait locus (QTL) mapping techniques are frequently used to identify genomic regions associated with variation in phenotypes of interest. However, the F(2) intercross and congenic strain populations usually employed have limited genetic resolution resulting in relatively large confidence intervals that greatly inhibit functional confirmation of statistical results. Here we use the increased resolution of the combined F(9) and F(10) generations (n = 1455) of the LG,SM advanced intercross to fine-map previously identified QTL associated with the lengths of the humerus, ulna, femur, and tibia. We detected 81 QTL affecting long-bone lengths. Of these, 49 were previously identified in the combined F(2)-F(3) population of this intercross, while 32 represent novel contributors to trait variance. Pleiotropy analysis suggests that most QTL affect three to four long bones or serially homologous limb segments. We also identified 72 epistatic interactions involving 38 QTL and 88 novel regions. This analysis shows that using later generations of an advanced intercross greatly facilitates fine-mapping of confidence intervals, resolving three F(2)-F(3) QTL into multiple linked loci and narrowing confidence intervals of other loci, as well as allowing identification of additional QTL. Further characterization of the biological bases of these QTL will help provide a better understanding of the genetics of small variations in long-bone length.
Keywords: Animals; Bone and Bones; Crosses, Genetic; DNA Replication; Female; Hybridization, Genetic; Male; Mice; Organ Size; Quantitative Trait Loci

Resources for genetic management and genomics research on non-human primates at the National Primate Research Centers (NPRCs). - Kanthaswamy, S; Capitanio, J P; Dubay, C J; Ferguson, B; Folks, T; Ha, J C; Hotchkiss, C E; Johnson, Z P; Katze, M G; Kean, L S; Kubisch, H Michael; Lank, S; et al. (J Med Primatol, 2009)
The National Primate Research Centers (NPRCs) established Working Groups (WGs) for developing resources and mechanisms to facilitate collaborations among non-human primate (NHP) researchers. Here we report the progress of the Genome Banking and the Genetics and Genomics WGs in developing resources to advance the exchange, analysis and comparison of NHP genetic and genomic data across the NPRCs. The Genome Banking WG has established a National NHP DNA bank comprising 1250 DNA samples from unrelated animals and family trios from the 10 NHP species housed within the NPRC system. The Genetics and Genomics WG is developing SNP arrays that will provide a uniform, highly informative, efficient and low-cost method for rhesus and long-tailed macaque genotyping across the eight NPRCs. This WG is also establishing a Biomedical Informatics Research Network-based portal for shared bioinformatics resources including vital statistics, genotype and population data and information on the National NHP DNA bank.
Keywords: Animals; Genomics; National Institutes of Health (U.S.); Primates; United States

Sequencing the full-length of the phosphatase and tensin homolog (PTEN) gene in hepatocellular carcinoma (HCC) using the 454 GS20 and Illumina GA DNA sequencing platforms. - Rodriguez, Joel A; Guiteau, Jacfranz J; Nazareth, Lynne; Reid, Jeff G; Goss, John A; Richard A Gibbs; Marie-Claude Gingras (World J Surg, 2009)
BACKGROUND: Phosphatase and tensin homolog (PTEN) is a tumor-suppressor gene that is mutated in cancer of the liver, pancreas, endometrium, and prostate. PTEN-dependent pathways are involved in mediating cell growth and invasion. To sequence the whole gene (including introns and exons), we have taken advantage of new technologies that allow for rapid, inexpensive sequencing to great depth. METHODS: DNA from 15 HCC specimens were pooled, and long-range PCR was performed by using the GeneAmp XL PCR kit. Primer parameters included: length of 20-30 base pairs (bp), melting temperature of -68 degrees C, and G/C content of 50-60%. PCR products were then column-purified and pooled, and DNA libraries were prepared for "shotgun sequencing" on both the 454 GS and Illumina GA sequencing platforms. RESULTS: We successfully amplified approximately 98.9% of the PTEN gene by using one long-range PCR protocol applied to 24 primer sets, resulting in 20 amplicons approximately 6.5 kilobases (kb) in length, 2 amplicons approximately 10 kb in length, and 2 amplicons approximately 2.5 kb in length. Sequencing of fragmented PCR products on both sequencing platforms identified six high-frequency SNPs that were catalogued in dbSNP as known variants. CONCLUSIONS: Shotgun sequencing based on a single long-range PCR protocol in pooled samples is an efficient and relatively inexpensive way to sequence an entire gene.
Keywords: Carcinoma, Hepatocellular; Exons; Gene Library; Genes, Tumor Suppressor; Humans; Inteins; Liver Neoplasms; Polymerase Chain Reaction; PTEN Phosphohydrolase; Sequence Analysis, DNA; Sequence Analysis, Protein

The complete genome of an individual by massively parallel DNA sequencing. - Wheeler, David A; Srinivasan, Maithreyan; Egholm, Michael; Shen, Yufeng; Chen, Lei; McGuire, Amy; He, Wen; Chen, Yi-Ju; Makhijani, Vinod; Roth, G Thomas; Gomes, Xavier; Tartaro, Karrie; et al. (Nature, 2008)
The association of genetic variation with disease and drug response, and improvements in nucleic acid technologies, have given great optimism for the impact of 'genomic medicine'. However, the formidable size of the diploid human genome, approximately 6 gigabases, has prevented the routine application of sequencing methods to deciphering complete individual human genomes. To realize the full potential of genomics for human health, this limitation must be overcome. Here we report the DNA sequence of a diploid genome of a single individual, James D. Watson, sequenced to 7.4-fold redundancy in two months using massively parallel sequencing in picolitre-size reaction vessels. This sequence was completed in two months at approximately one-hundredth of the cost of traditional capillary electrophoresis methods. Comparison of the sequence to the reference genome led to the identification of 3.3 million single nucleotide polymorphisms, of which 10,654 cause amino-acid substitution within the coding sequence. In addition, we accurately identified small-scale (2-40,000 base pair (bp)) insertion and deletion polymorphism as well as copy number variation resulting in the large-scale gain and loss of chromosomal segments ranging from 26,000 to 1.5 million base pairs. Overall, these results agree well with recent results of sequencing of a single individual by traditional methods. However, in addition to being faster and significantly less expensive, this sequencing technology avoids the arbitrary loss of genomic sequences inherent in random shotgun sequencing by bacterial cloning because it amplifies DNA in a cell-free system. As a result, we further demonstrate the acquisition of novel human sequence, including novel genes not previously identified by traditional genomic sequencing. This is the first genome sequenced by next-generation technologies. Therefore it is a pilot for the future challenges of 'personalized genome sequencing'.
Keywords: Alleles; Computational Biology; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genomics; Genotype; Humans; Individuality; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Sequence Alignment; Sequence Analysis, DNA; Software

The complete genome sequence of Escherichia coli DH10B: insights into the biology of a laboratory workhorse. - Durfee, Tim; Nelson, Richard; Baldwin, Schuyler; Plunkett, Guy; Burland, Valerie; Mau, Bob; Petrosino, Joseph F; Qin, Xiang; Muzny, Donna M; Ayele, Mulu; Gibbs, Richard A; Csörgo, Bálint; et al. (J Bacteriol, 2008)
Escherichia coli DH10B was designed for the propagation of large insert DNA library clones. It is used extensively, taking advantage of properties such as high DNA transformation efficiency and maintenance of large plasmids. The strain was constructed by serial genetic recombination steps, but the underlying sequence changes remained unverified. We report the complete genomic sequence of DH10B by using reads accumulated from the bovine sequencing project at Baylor College of Medicine and assembled with DNAStar's SeqMan genome assembler. The DH10B genome is largely colinear with that of the wild-type K-12 strain MG1655, although it is substantially more complex than previously appreciated, allowing DH10B biology to be further explored. The 226 mutated genes in DH10B relative to MG1655 are mostly attributable to the extensive genetic manipulations the strain has undergone. However, we demonstrate that DH10B has a 13.5-fold higher mutation rate than MG1655, resulting from a dramatic increase in insertion sequence (IS) transposition, especially IS150. IS elements appear to have remodeled genome architecture, providing homologous recombination sites for a 113,260-bp tandem duplication and an inversion. DH10B requires leucine for growth on minimal medium due to the deletion of leuLABCD and harbors both the relA1 and spoT1 alleles causing both sensitivity to nutritional downshifts and slightly lower growth rates relative to the wild type. Finally, while the sequence confirms most of the reported alleles, the sequence of deoR is wild type, necessitating reexamination of the assumed basis for the high transformability of DH10B.
Keywords: Escherichia coli; Genes, Bacterial; Genome, Bacterial; Models, Genetic; Mutation; Sequence Analysis, DNA

Complete genome sequence of Treponema pallidum ssp. pallidum strain SS14 determined with oligonucleotide arrays. - Matejková, Petra; Strouhal, Michal; Smajs, David; Norris, Steven J; Palzkill, Timothy; Petrosino, Joseph F; Sodergren, Erica; Norton, Jason E; Singh, Jaz; Richmond, Todd A; Molla, Michael N; Albert, Thomas J; et al. (BMC Microbiol, 2008)
BACKGROUND: Syphilis spirochete Treponema pallidum ssp. pallidum remains the enigmatic pathogen, since no virulence factors have been identified and the pathogenesis of the disease is poorly understood. Increasing rates of new syphilis cases per year have been observed recently. RESULTS: The genome of the SS14 strain was sequenced to high accuracy by an oligonucleotide array strategy requiring hybridization to only three arrays (Comparative Genome Sequencing, CGS). Gaps in the resulting sequence were filled with targeted dideoxy-terminators (DDT) sequencing and the sequence was confirmed by whole genome fingerprinting (WGF). When compared to the Nichols strain, 327 single nucleotide substitutions (224 transitions, 103 transversions), 14 deletions, and 18 insertions were found. On the proteome level, the highest frequency of amino acid-altering substitution polymorphisms was in novel genes, while the lowest was in housekeeping genes, as expected by their evolutionary conservation. Evidence was also found for hypervariable regions and multiple regions showing intrastrain heterogeneity in the T. pallidum chromosome. CONCLUSION: The observed genetic changes do not have influence on the ability of Treponema pallidum to cause syphilitic infection, since both SS14 and Nichols are virulent in rabbit. However, this is the first assessment of the degree of variation between the two syphilis pathogens and paves the way for phylogenetic studies of this fascinating organism.
Keywords: Animals; Chromosome Mapping; DNA Fingerprinting; Genome, Bacterial; Humans; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Open Reading Frames; Polymorphism, Single Nucleotide; Rabbits; Reproducibility of Results; Sequence Analysis, DNA; Syphilis; Treponema pallidum

The genome of the model beetle and pest Tribolium castaneum. - Stephen Richards; Richard A Gibbs; Weinstock, George M; Brown, Susan J; Denell, Robin; Beeman, Richard W; Richard A Gibbs; Beeman, Richard W; Brown, Susan J; Bucher, Gregor; Friedrich, Markus; Grimmelikhuijzen, Cornelis J P; et al. (Nature, 2008)
Tribolium castaneum is a member of the most species-rich eukaryotic order, a powerful model organism for the study of generalized insect development, and an important pest of stored agricultural products. We describe its genome sequence here. This omnivorous beetle has evolved the ability to interact with a diverse chemical environment, as shown by large expansions in odorant and gustatory receptors, as well as P450 and other detoxification enzymes. Development in Tribolium is more representative of other insects than is Drosophila, a fact reflected in gene content and function. For example, Tribolium has retained more ancestral genes involved in cell-cell communication than Drosophila, some being expressed in the growth zone crucial for axial elongation in short-germ development. Systemic RNA interference in T. castaneum functions differently from that in Caenorhabditis elegans, but nevertheless offers similar power for the elucidation of gene function and identification of targets for selective insect control.
Keywords: Animals; Base Composition; Body Patterning; Cytochrome P-450 Enzyme System; DNA Transposable Elements; Genes, Insect; Genome, Insect; Growth and Development; Humans; Insecticides; Neurotransmitter Agents; Oogenesis; Phylogeny; Proteome; Receptors, G-Protein-Coupled; Receptors, Odorant; Repetitive Sequences, Nucleic Acid; RNA Interference; Taste; Telomere; Tribolium; Vision, Ocular

Identification and phenotypic characterization of a second collagen adhesin, Scm, and genome-based identification and analysis of 13 other predicted MSCRAMMs, including four distinct pilus loci, in Enterococcus faecium. - Sillanpaa, Jouko; Nallapareddy, Sreedhar R; Prakash, Vittal P; Qin, Xiang; Höök, Magnus; Weinstock, George M; Murray, Barbara E (Microbiology (Reading), 2008)
Attention has recently been drawn to Enterococcus faecium because of an increasing number of nosocomial infections caused by this species and its resistance to multiple antibacterial agents. However, relatively little is known about the pathogenic determinants of this organism. We have previously identified a cell-wall-anchored collagen adhesin, Acm, produced by some isolates of E. faecium, and a secreted antigen, SagA, exhibiting broad-spectrum binding to extracellular matrix proteins. Here, we analysed the draft genome of strain TX0016 for potential microbial surface components recognizing adhesive matrix molecules (MSCRAMMs). Genome-based bioinformatics identified 22 predicted cell-wall-anchored E. faecium surface proteins (Fms), of which 15 (including Acm) had characteristics typical of MSCRAMMs, including predicted folding into a modular architecture with multiple immunoglobulin-like domains. Functional characterization of one [Fms10; redesignated second collagen adhesin of E. faecium (Scm)] revealed that recombinant Scm(65) (A- and B-domains) and Scm(36) (A-domain) bound to collagen type V efficiently in a concentration-dependent manner, bound considerably less to collagen type I and fibrinogen, and differed from Acm in their binding specificities to collagen types IV and V. Results from far-UV circular dichroism measurements of recombinant Scm(36) and of Acm(37) indicated that these proteins were rich in beta-sheets, supporting our folding predictions. Whole-cell ELISA and FACS analyses unambiguously demonstrated surface expression of Scm in most E. faecium isolates. Strikingly, 11 of the 15 predicted MSCRAMMs clustered in four loci, each with a class C sortase gene; nine of these showed similarity to Enterococcus faecalis Ebp pilus subunits and also contained motifs essential for pilus assembly. Antibodies against one of the predicted major pilus proteins, Fms9 (redesignated EbpC(fm)), detected a 'ladder' pattern of high-molecular-mass protein bands in a Western blot analysis of cell surface extracts from E. faecium, suggesting that EbpC(fm) is polymerized into a pilus structure. Further analysis of the transcripts of the corresponding gene cluster indicated that fms1 (ebpA(fm)), fms5 (ebpB(fm)) and ebpC(fm) are co-transcribed, a result consistent with those for pilus-encoding gene clusters of other Gram-positive bacteria. All 15 genes occurred frequently in 30 clinically derived diverse E. faecium isolates tested. The common occurrence of MSCRAMM- and pilus-encoding genes and the presence of a second collagen-binding protein may have important implications for our understanding of this emerging pathogen.
Keywords: Adhesins, Bacterial; Bacterial Adhesion; Circular Dichroism; Collagen; DNA, Bacterial; Enterococcus faecium; Enzyme-Linked Immunosorbent Assay; Fimbriae, Bacterial; Flow Cytometry; Genes, Bacterial; Genome, Bacterial; Multigene Family; Phenotype; Protein Binding; Protein Conformation; Recombinant Proteins; Reverse Transcriptase Polymerase Chain Reaction; RNA, Bacterial; Substrate Specificity

Identification of quantitative trait loci affecting murine long bone length in a two-generation intercross of LG/J and SM/J Mice. - Norgard, Elizabeth A; Roseman, Charles C; Fawcett, Gloria L; Pavlicev, Mihaela; Morgan, Clinton D; Pletscher, L Susan; Wang, Bing; Cheverud, James M (J Bone Miner Res, 2008)
INTRODUCTION: Study of mutations with large phenotypic effects has allowed the identification of key players in skeletal development. However, the molecular nature of variation in large, phenotypically normal populations tends to be characterized by smaller phenotypic effects that remain undefined. MATERIALS AND METHODS: We use interval mapping and quantitative trait locus (QTL) mapping techniques in the combined F2-F3 populations (n = 2111) of an LG/J x SM/J mouse intercross to detect QTLs associated with the lengths of the humerus, ulna, femur, and tibia. RESULTS: Seventy individual trait QTLs affecting long bone lengths were detected, with several chromosomes harboring multiple QTLs. The genetic architecture suggests mainly small, additive effects on long bone length, with roughly one third of the QTLs displaying dominance. Sex interactions were common, and four sex-specific QTLs were observed. Pleiotropy could not be rejected for most of the QTLs identified. Thirty-one epistatic interactions were detected, almost all affecting regions including or immediately adjacent to QTLs. CONCLUSIONS: A complex regulatory network with many gene interactions modulates bone growth, possibly with integrated skeletal modules that allow fine-tuning of developmental processes present. Candidate genes in the QTL CIs include many genes known to affect endochondral bone growth and genes that have not yet been associated with bone growth or body size but have a strong potential to influence these traits.
Keywords: Animals; Bone and Bones; Chromosomes; Epistasis, Genetic; Female; Male; Mice; Quantitative Trait Loci

Large scale variation in Enterococcus faecalis illustrated by the genome analysis of strain OG1RF. - Bourgogne, Agathe; Garsin, Danielle A; Qin, Xiang; Singh, Kavindra V; Sillanpaa, Jouko; Yerrapragada, Shailaja; Ding, Yan; Dugan-Rocha, Shannon; Buhay, Christian; Shen, Hua; Chen, Guan; Williams, Gabrielle; et al. (Genome Biol, 2008)
BACKGROUND: Enterococcus faecalis has emerged as a major hospital pathogen. To explore its diversity, we sequenced E. faecalis strain OG1RF, which is commonly used for molecular manipulation and virulence studies. RESULTS: The 2,739,625 base pair chromosome of OG1RF was found to contain approximately 232 kilobases unique to this strain compared to V583, the only publicly available sequenced strain. Almost no mobile genetic elements were found in OG1RF. The 64 areas of divergence were classified into three categories. First, OG1RF carries 39 unique regions, including 2 CRISPR loci and a new WxL locus. Second, we found nine replacements where a sequence specific to V583 was substituted by a sequence specific to OG1RF. For example, the iol operon of OG1RF replaces a possible prophage and the vanB transposon in V583. Finally, we found 16 regions that were present in V583 but missing from OG1RF, including the proposed pathogenicity island, several probable prophages, and the cpsCDEFGHIJK capsular polysaccharide operon. OG1RF was more rapidly but less frequently lethal than V583 in the mouse peritonitis model and considerably outcompeted V583 in a murine model of urinary tract infections. CONCLUSION: E. faecalis OG1RF carries a number of unique loci compared to V583, but the almost complete lack of mobile genetic elements demonstrates that this is not a defining feature of the species. Additionally, OG1RF's effects in experimental models suggest that mediators of virulence may be diverse between different E. faecalis strains and that virulence is not dependent on the presence of mobile genetic elements.
Keywords: Animals; Anti-Bacterial Agents; Bacterial Proteins; Biofilms; DNA, Bacterial; Drug Resistance, Bacterial; Enterococcus faecalis; Fusidic Acid; Genetic Variation; Genome, Bacterial; Genomics; Interspersed Repetitive Sequences; Membrane Proteins; Mice; Operon; Repetitive Sequences, Nucleic Acid; Rifampin; Sequence Homology, Nucleic Acid

Longitudinal changes in triglycerides according to ANGPTL4[E40K] genotype and longitudinal body weight change in the atherosclerosis risk in communities study. - Nettleton, Jennifer A; Volcik, Kelly A; Demerath, Ellen W; Boerwinkle, Eric; Folsom, Aaron R (Ann Epidemiol, 2008)
PURPOSE: Allelic variation in the adipokine angiopoietin-like 4 gene (ANGPTL4[E40K]) has been cross-sectionally associated with triglycerides, but the effects of genotype, or the interaction between genotype and body weight, on longitudinal triglyceride change have not been studied. METHODS: Body weight, triglycerides, and ANGPTL4[E40K] genotype were determined at baseline (1987-1989) and at 3 follow-up exams (1990-1992, 1993-1995, 1996-1998) in 7,939 white ANGPTL4[E40K] G allele homozygotes and 344 A allele carriers. Changes in body weight and triglycerides were characterized as the difference between exam 4 and baseline measurements. RESULTS: ANGPTL4[E40K] A allele carriers had triglyceride concentrations that were 15 to 18 mg/dL lower than G allele homozygotes at all exams (P<0.0001). Triglycerides increased in both genotype groups over the 9-year period (+19.1+/-0.9 and +16.2+/-4.1 mg/dL in GG and GA/AA, respectively; P difference, 0.48). Weight gain was associated with increased triglycerides to a comparable degree in both genotype groups (+5.5+/-0.3 and +4.3+/-0.9 mg/dL per 2-kg increase in body weight in GG and GA/AA, respectively, p interaction=0.30). CONCLUSIONS: Differences in triglyceride concentrations between ANGPTL4[E40K] A allele carriers and G allele homozygotes are maintained over time, but the degree of increase in triglycerides was similar between groups and was not modified by body weight changes.
Keywords: Aged; Angiopoietin-Like Protein 4; Angiopoietins; Atherosclerosis; Body Mass Index; Female; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Triglycerides; United States; Weight Gain

Mouse let-7 miRNA populations exhibit RNA editing that is constrained in the 5'-seed/ cleavage/anchor regions and stabilize predicted mmu-let-7a:mRNA duplexes. - Reid, Jeffrey G; Nagaraja, Ankur K; Lynn, Francis C; Drabek, Rafal B; Muzny, Donna M; Shaw, Chad A; Weiss, Michelle K; Naghavi, Arash O; Khan, Mahjabeen; Zhu, Huifeng; Tennakoon, Jayantha; Gunaratne, Gemunu H; et al. (Genome Res, 2008)
Massively parallel sequencing of millions of < 30-nt RNAs expressed in mouse ovary, embryonic pancreas (E14.5), and insulin-secreting beta-cells (betaTC-3) reveals that approximately 50% of the mature miRNAs representing mostly the mmu-let-7 family display internal insertion/deletions and substitutions when compared to precursor miRNA and the mouse genome reference sequences. Approximately, 12%-20% of species associated with mmu-let-7 populations exhibit sequence discrepancies that are dramatically reduced in nucleotides 3-7 (5'-seed) and 10-15 (cleavage and anchor sites). This observation is inconsistent with sequencing error and leads us to propose that the changes arise predominantly from post-transcriptional RNA-editing activity operating on miRNA:target mRNA complexes. Internal nucleotide modifications are most enriched at the ninth nucleotide position. A common ninth base edit of U-to-G results in a significant increase in stability of down-regulated let-7a targets in inhibin-deficient mice (Inha-/-). An excess of U-insertions (14.8%) over U-deletions (1.5%) and the presence of cleaved intermediates suggest that a mammalian TUTase (terminal uridylyl transferase) mediated dUTP-dependent U-insertion/U-deletion cycle may be a possible mechanism. We speculate that mRNA target site-directed editing of mmu-let-7a duplex-bulges stabilizes "loose" miRNA:mRNA target associations and functions to expand the target repertoire and/or enhance mRNA decay over translational repression. Our results also demonstrate that the systematic study of sequence variation within specific RNA classes in a given cell type from millions of sequences generated by next-generation sequencing (NGS) technologies ("intranomics") can be used broadly to infer functional constraints on specific parts of completely uncharacterized RNAs.
Keywords: Animals; Base Sequence; Cells, Cultured; Deoxyuracil Nucleotides; Embryo, Mammalian; Female; Mice; MicroRNAs; Molecular Sequence Data; Nucleic Acid Conformation; RNA Editing; RNA Nucleotidyltransferases; RNA Stability; RNA, Messenger; RNA, Small Untranslated

Novel microRNA candidates and miRNA-mRNA pairs in embryonic stem (ES) cells. - Gu, Peili; Reid, Jeffrey G; Gao, Xiaolian; Shaw, Chad A; Creighton, Chad; Tran, Peter L; Zhou, Xiaochuan; Drabek, Rafal B; Steffen, David L; Hoang, David M; Weiss, Michelle K; Naghavi, Arash O; et al. (PLoS One, 2008)
BACKGROUND: MicroRNAS (miRNAS: a class of short non-coding RNAs) are emerging as important agents of post transcriptional gene regulation and integral components of gene networks. MiRNAs have been strongly linked to stem cells, which have a remarkable dual role in development. They can either continuously replenish themselves (self-renewal), or differentiate into cells that execute a limited number of specific actions (pluripotence). METHODOLOGY/PRINCIPAL FINDINGS: In order to identify novel miRNAs from narrow windows of development we carried out an in silico search for micro-conserved elements (MCE) in adult tissue progenitor transcript sequences. A plethora of previously unknown miRNA candidates were revealed including 545 small RNAs that are enriched in embryonic stem (ES) cells over adult cells. Approximately 20% of these novel candidates are down-regulated in ES (Dicer(-/-)) ES cells that are impaired in miRNA maturation. The ES-enriched miRNA candidates exhibit distinct and opposite expression trends from mmu-mirs (an abundant class in adult tissues) during retinoic acid (RA)-induced ES cell differentiation. Significant perturbation of trends is found in both miRNAs and novel candidates in ES (GCNF(-/-)) cells, which display loss of repression of pluripotence genes upon differentiation. CONCLUSION/SIGNIFICANCE: Combining expression profile information with miRNA target prediction, we identified miRNA-mRNA pairs that correlate with ES cell pluripotence and differentiation. Perturbation of these pairs in the ES (GCNF(-/-)) mutant suggests a role for miRNAs in the core regulatory networks underlying ES cell self-renewal, pluripotence and differentiation.
Keywords: Algorithms; Animals; Blotting, Northern; Cell Differentiation; Computational Biology; Conserved Sequence; Embryonic Stem Cells; False Positive Reactions; Humans; MicroRNAs; Models, Biological; Models, Genetic; RNA, Messenger; Time Factors; Tretinoin

Peroxisome proliferator-activated receptor [alpha] genetic variation interacts with n-6 and long-chain n-3 fatty acid intake to affect total cholesterol and LDL-cholesterol concentrations in the Atherosclerosis Risk in Communities Study. - Volcik, Kelly A; Nettleton, Jennifer A; Ballantyne, Christie M; Boerwinkle, Eric (Am J Clin Nutr, 2008)
BACKGROUND: Peroxisome proliferator-activated receptor-alpha (PPARA) regulates the expression of genes involved in lipid metabolism. The binding of polyunsaturated fatty acids (PUFAs) to PPARA results in rapid changes in the expression of genes involved in lipid oxidation, with long-chain n-3 fatty acids being potent activators of PPARA. OBJECTIVE: We evaluated the potential effect modification of PPARA genetic variation on the association between PUFA intake, specifically n-6 and long-chain n-3 fatty acid intakes, and multiple lipid measures in the large biethnic Atherosclerosis Risk in Communities (ARIC) Study. DESIGN: Study participants (10 134 whites and 3480 African Americans) were selected from the ARIC Study--a prospective investigation of atherosclerosis and its clinical sequelae. Multiple linear regression models were used to assess the relation between PPARA genotypes, as well as dietary fatty acid intake, and baseline lipid measures. PPARA-specific effects of variation were assessed by including genotype-by-fatty acid interaction terms in each statistical model. RESULTS: PPARA genotype frequencies were significantly different between whites and African Americans. No significant associations between lipid measures and PPARA genotype were observed in either whites or African Americans. Significant genotype-by-n-6 fatty acid intake interactions were observed only in whites for the 3'untranslated region (UTR) G-->A single nucleotide polymorphism (SNP) and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.03). Significant genotype-by-long-chain n-3 fatty acid intake interactions were observed only in African Americans for the 3'UTR C-->T SNP and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.02). CONCLUSIONS: Findings from the current study suggest that PPARA 3'UTR SNPs modulate the association between lipid concentrations and dietary n-6 fatty acid intake (in whites) and long-chain n-3 fatty acid intake (in African Americans) such that persons with homozygous variant genotypes have significantly lower total cholesterol and LDL-cholesterol measures when consuming higher quantities of n-6 or long-chain n-3 fatty acids.
Keywords: 3' Untranslated Regions; Atherosclerosis; Black People; Cholesterol; Cholesterol, LDL; Dietary Fats; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Female; Gene Frequency; Genetic Variation; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; PPAR alpha; Risk Factors; United States; White People

Pleiotropic patterns of quantitative trait loci for 70 murine skeletal traits. - Kenney-Hunt, Jane P; Wang, Bing; Norgard, Elizabeth A; Fawcett, Gloria; Falk, Doug; Pletscher, L Susan; Jarvis, Joseph P; Roseman, Charles; Wolf, Jason; Cheverud, James M (Genetics, 2008)
Quantitative trait locus (QTL) studies of a skeletal trait or a few related skeletal components are becoming commonplace, but as yet there has been no investigation of pleiotropic patterns throughout the skeleton. We present a comprehensive survey of pleiotropic patterns affecting mouse skeletal morphology in an intercross of LG/J and SM/J inbred strains (N = 1040), using QTL analysis on 70 skeletal traits. We identify 798 single-trait QTL, coalescing to 105 loci that affect on average 7-8 traits each. The number of traits affected per locus ranges from only 1 trait to 30 traits. Individual traits average 11 QTL each, ranging from 4 to 20. Skeletal traits are affected by many, small-effect loci. Significant additive genotypic values average 0.23 standard deviation (SD) units. Fifty percent of loci show codominance with heterozygotes having intermediate phenotypic values. When dominance does occur, the LG/J allele tends to be dominant to the SM/J allele (30% vs. 8%). Over- and underdominance are relatively rare (12%). Approximately one-fifth of QTL are sex specific, including many for pelvic traits. Evaluating the pleiotropic relationships of skeletal traits is important in understanding the role of genetic variation in the growth and development of the skeleton.
Keywords: Animals; Bone and Bones; Chromosomes, Mammalian; Mice; Quantitative Trait Loci; Quantitative Trait, Heritable

Somatic mutations affect key pathways in lung adenocarcinoma. - Ding, Li; Getz, Gad; Wheeler, David A; Mardis, Elaine R; McLellan, Michael D; Cibulskis, Kristian; Sougnez, Carrie; Greulich, Heidi; Muzny, Donna M; Morgan, Margaret B; Fulton, Lucinda; Fulton, Robert S; et al. (Nature, 2008)
Determining the genetic basis of cancer requires comprehensive analyses of large collections of histopathologically well-classified primary tumours. Here we report the results of a collaborative study to discover somatic mutations in 188 human lung adenocarcinomas. DNA sequencing of 623 genes with known or potential relationships to cancer revealed more than 1,000 somatic mutations across the samples. Our analysis identified 26 genes that are mutated at significantly high frequencies and thus are probably involved in carcinogenesis. The frequently mutated genes include tyrosine kinases, among them the EGFR homologue ERBB4; multiple ephrin receptor genes, notably EPHA3; vascular endothelial growth factor receptor KDR; and NTRK genes. These data provide evidence of somatic mutations in primary lung adenocarcinoma for several tumour suppressor genes involved in other cancers--including NF1, APC, RB1 and ATM--and for sequence changes in PTPRD as well as the frequently deleted gene LRP1B. The observed mutational profiles correlate with clinical features, smoking status and DNA repair defects. These results are reinforced by data integration including single nucleotide polymorphism array and gene expression array. Our findings shed further light on several important signalling pathways involved in lung adenocarcinoma, and suggest new molecular targets for treatment.
Keywords: Adenocarcinoma, Bronchiolo-Alveolar; Female; Gene Dosage; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Lung Neoplasms; Male; Mutation; Proto-Oncogenes

Understanding the development of human bladder cancer by using a whole-organ genomic mapping strategy. - Majewski, Tadeusz; Lee, Sangkyou; Jeong, Joon; Yoon, Dong-Sup; Kram, Andrzej; Kim, Mi-Sook; Tuziak, Tomasz; Bondaruk, Jolanta; Lee, Sooyong; Park, Weon-Seo; Tang, Kuang S; Chung, Woonbok; et al. (Lab Invest, 2008)
The search for the genomic sequences involved in human cancers can be greatly facilitated by maps of genomic imbalances identifying the involved chromosomal regions, particularly those that participate in the development of occult preneoplastic conditions that progress to clinically aggressive invasive cancer. The integration of such regions with human genome sequence variation may provide valuable clues about their overall structure and gene content. By extension, such knowledge may help us understand the underlying genetic components involved in the initiation and progression of these cancers. We describe the development of a genome-wide map of human bladder cancer that tracks its progression from in situ precursor conditions to invasive disease. Testing for allelic losses using a genome-wide panel of 787 microsatellite markers was performed on multiple DNA samples, extracted from the entire mucosal surface of the bladder and corresponding to normal urothelium, in situ preneoplastic lesions, and invasive carcinoma. Using this approach, we matched the clonal allelic losses in distinct chromosomal regions to specific phases of bladder neoplasia and produced a detailed genetic map of bladder cancer development. These analyses revealed three major waves of genetic changes associated with growth advantages of successive clones and reflecting a stepwise conversion of normal urothelial cells into cancer cells. The genetic changes map to six regions at 3q22-q24, 5q22-q31, 9q21-q22, 10q26, 13q14, and 17p13, which may represent critical hits driving the development of bladder cancer. Finally, we performed high-resolution mapping using single nucleotide polymorphism markers within one region on chromosome 13q14, containing the model tumor suppressor gene RB1, and defined a minimal deleted region associated with clonal expansion of in situ neoplasia. These analyses provided new insights on the involvement of several non-coding sequences mapping to the region and identified novel target genes, termed forerunner (FR) genes, involved in early phases of cancer development.
Keywords: Aged; Carcinoma, Transitional Cell; Chromosome Mapping; Chromosomes, Human, Pair 13; Humans; Male; Microsatellite Repeats; Middle Aged; Polymorphism, Single Nucleotide; Retinoblastoma Protein; Urinary Bladder; Urinary Bladder Neoplasms; Urothelium

28-way vertebrate alignment and conservation track in the UCSC Genome Browser. - Miller, Webb; Rosenbloom, Kate; Hardison, Ross C; Hou, Minmei; Taylor, James; Raney, Brian; Burhans, Richard; King, David C; Baertsch, Robert; Blankenberg, Daniel; Kosakovsky Pond, Sergei L; Nekrutenko, Anton; et al. (Genome Res, 2007)
This article describes a set of alignments of 28 vertebrate genome sequences that is provided by the UCSC Genome Browser. The alignments can be viewed on the Human Genome Browser (March 2006 assembly) at http://genome.ucsc.edu, downloaded in bulk by anonymous FTP from http://hgdownload.cse.ucsc.edu/goldenPath/hg18/multiz28way, or analyzed with the Galaxy server at http://g2.bx.psu.edu. This article illustrates the power of this resource for exploring vertebrate and mammalian evolution, using three examples. First, we present several vignettes involving insertions and deletions within protein-coding regions, including a look at some human-specific indels. Then we study the extent to which start codons and stop codons in the human sequence are conserved in other species, showing that start codons are in general more poorly conserved than stop codons. Finally, an investigation of the phylogenetic depth of conservation for several classes of functional elements in the human genome reveals striking differences in the rates and modes of decay in alignability. Each functional class has a distinctive period of stringent constraint, followed by decays that allow (for the case of regulatory regions) or reject (for coding regions and ultraconserved elements) insertions and deletions.
Keywords: Animals; Base Sequence; Cats; Cattle; Codon, Initiator; Codon, Terminator; Conserved Sequence; Databases, Genetic; Dogs; Genome, Human; Guinea Pigs; Humans; Mice; Molecular Sequence Data; Mutagenesis, Insertional; Rabbits; Rats; Sequence Alignment; Sequence Deletion

Analyses of deep mammalian sequence alignments and constraint predictions for 1% of the human genome. - Margulies, Elliott H; Cooper, Gregory M; Asimenos, George; Thomas, Daryl J; Dewey, Colin N; Siepel, Adam; Birney, Ewan; Keefe, Damian; Schwartz, Ariel S; Hou, Minmei; Taylor, James; Nikolaev, Sergey; et al. (Genome Res, 2007)
A key component of the ongoing ENCODE project involves rigorous comparative sequence analyses for the initially targeted 1% of the human genome. Here, we present orthologous sequence generation, alignment, and evolutionary constraint analyses of 23 mammalian species for all ENCODE targets. Alignments were generated using four different methods; comparisons of these methods reveal large-scale consistency but substantial differences in terms of small genomic rearrangements, sensitivity (sequence coverage), and specificity (alignment accuracy). We describe the quantitative and qualitative trade-offs concomitant with alignment method choice and the levels of technical error that need to be accounted for in applications that require multisequence alignments. Using the generated alignments, we identified constrained regions using three different methods. While the different constraint-detecting methods are in general agreement, there are important discrepancies relating to both the underlying alignments and the specific algorithms. However, by integrating the results across the alignments and constraint-detecting methods, we produced constraint annotations that were found to be robust based on multiple independent measures. Analyses of these annotations illustrate that most classes of experimentally annotated functional elements are enriched for constrained sequences; however, large portions of each class (with the exception of protein-coding sequences) do not overlap constrained regions. The latter elements might not be under primary sequence constraint, might not be constrained across all mammals, or might have expendable molecular functions. Conversely, 40% of the constrained sequences do not overlap any of the functional elements that have been experimentally identified. Together, these findings demonstrate and quantify how many genomic functional elements await basic molecular characterization.
Keywords: Animals; Evolution, Molecular; Genome, Human; Human Genome Project; Humans; Mammals; Open Reading Frames; Phylogeny; Sequence Alignment

Characterizing the cancer genome in lung adenocarcinoma. - Weir, Barbara A; Woo, Michele S; Getz, Gad; Perner, Sven; Ding, Li; Beroukhim, Rameen; Lin, William M; Province, Michael A; Kraja, Aldi; Johnson, Laura A; Shah, Kinjal; Sato, Mitsuo; et al. (Nature, 2007)
Somatic alterations in cellular DNA underlie almost all human cancers. The prospect of targeted therapies and the development of high-resolution, genome-wide approaches are now spurring systematic efforts to characterize cancer genomes. Here we report a large-scale project to characterize copy-number alterations in primary lung adenocarcinomas. By analysis of a large collection of tumours (n = 371) using dense single nucleotide polymorphism arrays, we identify a total of 57 significantly recurrent events. We find that 26 of 39 autosomal chromosome arms show consistent large-scale copy-number gain or loss, of which only a handful have been linked to a specific gene. We also identify 31 recurrent focal events, including 24 amplifications and 7 homozygous deletions. Only six of these focal events are currently associated with known mutations in lung carcinomas. The most common event, amplification of chromosome 14q13.3, is found in approximately 12% of samples. On the basis of genomic and functional analyses, we identify NKX2-1 (NK2 homeobox 1, also called TITF1), which lies in the minimal 14q13.3 amplification interval and encodes a lineage-specific transcription factor, as a novel candidate proto-oncogene involved in a significant fraction of lung adenocarcinomas. More generally, our results indicate that many of the genes that are involved in lung adenocarcinoma remain to be discovered.
Keywords: Adenocarcinoma; Cell Line, Tumor; Chromosome Deletion; Chromosomes, Human, Pair 14; Gene Amplification; Genome, Human; Genomics; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Loss of Heterozygosity; Lung Neoplasms; Neoplasms; Nuclear Proteins; Polymorphism, Single Nucleotide; Proto-Oncogene Mas; RNA Interference; Thyroid Nuclear Factor 1; Transcription Factors

Corticotropin releasing hormone (CRH) gene variation: comprehensive resequencing for variant and molecular haplotype discovery in monosomic hybrid cell lines. - Shimmin, Lawrence C; Natarajan, Sivamani; Ibarguen, Heladio; Montasser, May; Kim, Do-Kyun; Hanis, Craig L; Eric Boerwinkle; Wadhwa, Pathik D; Hixson, James E (DNA Seq, 2007)
Candidate gene association studies have met with mixed success due to many reasons including incomplete surveys of genetic variation and differences in patterns of genetic variation among study populations. We present the results of comprehensive variant discovery for the corticotropin releasing hormone gene (CRH on chromosome 8) encoding a neuropeptide that is central to many physiologic pathways. Mouse-human hybrid cell lines were constructed that are monosomic for human chromosome 8 for resequencing of separated CRH alleles to identify variants and directly determine their chromosomal phase for three major ethnic groups including African Americans (AA), Mexican Americans (MA) and European Americans (EA). We also resequenced diploid individuals to evaluate single nucleotide polymorphism (SNP) discovery in the limited numbers of monosomic hybrid cell lines. Our results show that CRH variation is very different in AA, yielding larger numbers of variants and haplotypes compared to MA and EA. Analysis of LD structure found three haplotype blocks in AA and two blocks in EA. Comparisons between AA and EA groups yielded extremely high measures of genetic differentiation (Wright's F(ST)>0.6), likely reflecting disruptive selection in CRH evolution. Network analysis showed that AA have retained an ancestral CRH haplotype, while the most common EA haplotype is derived from a single recombination event.
Keywords: Animals; Base Sequence; Cell Line; Corticotropin-Releasing Hormone; Ethnicity; Female; Haplotypes; Humans; Hybrid Cells; Linkage Disequilibrium; Male; Mice; Molecular Sequence Data; Monosomy; Phylogeny; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Demographic histories and patterns of linkage disequilibrium in Chinese and Indian rhesus macaques. - Hernandez, Ryan D; Hubisz, Melissa J; David A Wheeler; Smith, David G; Ferguson, Betsy; Jeffrey Rogers; Nazareth, Lynne; Indap, Amit; Bourquin, Traci; McPherson, John; Donna M Muzny; Richard A Gibbs; et al. (Science, 2007)
To understand the demographic history of rhesus macaques (Macaca mulatta) and document the extent of linkage disequilibrium (LD) in the genome, we partially resequenced five Encyclopedia of DNA Elements regions in 9 Chinese and 38 captive-born Indian rhesus macaques. Population genetic analyses of the 1467 single-nucleotide polymorphisms discovered suggest that the two populations separated about 162,000 years ago, with the Chinese population tripling in size since then and the Indian population eventually shrinking by a factor of four. Using coalescent simulations, we confirmed that these inferred demographic events explain a much faster decay of LD in Chinese (r(2) approximately 0.15 at 10 kilobases) versus Indian (r(2) approximately 0.52 at 10 kilobases) macaque populations.
Keywords: Animals; China; Demography; DNA, Mitochondrial; Genetics, Medical; Humans; India; Linkage Disequilibrium; Macaca mulatta; Polymorphism, Single Nucleotide

Direct selection of human genomic loci by microarray hybridization. - Albert, Thomas J; Molla, Michael N; Donna M Muzny; Nazareth, Lynne; Wheeler, David; Song, Xingzhi; Richmond, Todd A; Middle, Chris M; Rodesch, Matthew J; Packard, Charles J; Weinstock, George M; Richard A Gibbs (Nat Methods, 2007)
We applied high-density microarrays to the enrichment of specific sequences from the human genome for high-throughput sequencing. After capture of 6,726 approximately 500-base 'exon' segments, and of 'locus-specific' regions ranging in size from 200 kb to 5 Mb, followed by sequencing on a 454 Life Sciences FLX sequencer, most sequence reads represented selection targets. These direct selection methods supersede multiplex PCR for the large-scale analysis of genomic regions.
Keywords: BRCA1 Protein; Cell Line, Tumor; Gene Library; Genome, Human; Humans; Nucleic Acid Hybridization; Oligodeoxyribonucleotides; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Evolutionary and biomedical insights from the rhesus macaque genome. - Richard A Gibbs; Jeffrey Rogers; Katze, Michael G; Bumgarner, Roger; Weinstock, George M; Mardis, Elaine R; Remington, Karin A; Strausberg, Robert L; Venter, J Craig; Wilson, Richard K; Batzer, Mark A; Bustamante, Carlos D; et al. (Science, 2007)
The rhesus macaque (Macaca mulatta) is an abundant primate species that diverged from the ancestors of Homo sapiens about 25 million years ago. Because they are genetically and physiologically similar to humans, rhesus monkeys are the most widely used nonhuman primate in basic and applied biomedical research. We determined the genome sequence of an Indian-origin Macaca mulatta female and compared the data with chimpanzees and humans to reveal the structure of ancestral primate genomes and to identify evidence for positive selection and lineage-specific expansions and contractions of gene families. A comparison of sequences from individual animals was used to investigate their underlying genetic diversity. The complete description of the macaque genome blueprint enhances the utility of this animal model for biomedical research and improves our understanding of the basic biology of the species.
Keywords: Animals; Biomedical Research; Evolution, Molecular; Female; Gene Duplication; Gene Rearrangement; Genetic Diseases, Inborn; Genetic Variation; Genome; Humans; Macaca mulatta; Male; Multigene Family; Mutation; Pan troglodytes; Sequence Analysis, DNA; Species Specificity

A genomewide admixture map for Latino populations. - Price, Alkes L; Patterson, Nick; Yu, Fuli; Cox, David R; Waliszewska, Alicja; McDonald, Gavin J; Tandon, Arti; Schirmer, Christine; Neubauer, Julie; Bedoya, Gabriel; Duque, Constanza; Villegas, Alberto; et al. (Am J Hum Genet, 2007)
Admixture mapping is an economical and powerful approach for localizing disease genes in populations of recently mixed ancestry and has proven successful in African Americans. The method holds equal promise for Latinos, who typically inherit a mix of European, Native American, and African ancestry. However, admixture mapping in Latinos has not been practical because of the lack of a map of ancestry-informative markers validated in Native American and other populations. To address this, we screened multiple databases, containing millions of markers, to identify 4,186 markers that were putatively informative for determining the ancestry of chromosomal segments in Latino populations. We experimentally validated each of these markers in at least 232 new Latino, European, Native American, and African samples, and we selected a subset of 1,649 markers to form an admixture map. An advantage of our strategy is that we focused our map on markers distinguishing Native American from other ancestries and restricted it to markers with very similar frequencies in Europeans and Africans, which decreased the number of markers needed and minimized the possibility of false disease associations. We evaluated the effectiveness of our map for localizing disease genes in four Latino populations from both North and South America.
Keywords: Alleles; Black People; Case-Control Studies; Chromosome Mapping; Chromosomes, Human; Computer Simulation; Databases, Genetic; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetics, Population; Genome, Human; Hispanic or Latino; Humans; Indians, North American; Reproducibility of Results; White People

Genome-wide detection and characterization of positive selection in human populations. - Sabeti, Pardis C; Varilly, Patrick; Fry, Ben; Lohmueller, Jason; Hostetter, Elizabeth; Cotsapas, Chris; Xie, Xiaohui; Byrne, Elizabeth H; McCarroll, Steven A; Gaudet, Rachelle; Schaffner, Stephen F; Lander, Eric S; et al. (Nature, 2007)
With the advent of dense maps of human genetic variation, it is now possible to detect positive natural selection across the human genome. Here we report an analysis of over 3 million polymorphisms from the International HapMap Project Phase 2 (HapMap2). We used 'long-range haplotype' methods, which were developed to identify alleles segregating in a population that have undergone recent selection, and we also developed new methods that are based on cross-population comparisons to discover alleles that have swept to near-fixation within a population. The analysis reveals more than 300 strong candidate regions. Focusing on the strongest 22 regions, we develop a heuristic for scrutinizing these regions to identify candidate targets of selection. In a complementary analysis, we identify 26 non-synonymous, coding, single nucleotide polymorphisms showing regional evidence of positive selection. Examination of these candidates highlights three cases in which two genes in a common biological process have apparently undergone positive selection in the same population:LARGE and DMD, both related to infection by the Lassa virus, in West Africa;SLC24A5 and SLC45A2, both involved in skin pigmentation, in Europe; and EDAR and EDA2R, both involved in development of hair follicles, in Asia.
Keywords: Antiporters; Edar Receptor; Gene Frequency; Genetics, Population; Genome, Human; Geography; Haplotypes; Humans; Models, Molecular; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Selection, Genetic

Identification and analysis of functional elements in 1% of the human genome by the ENCODE pilot project. - Birney, Ewan; Stamatoyannopoulos, John A; Dutta, Anindya; Guigó, Roderic; Gingeras, Thomas R; Margulies, Elliott H; Weng, Zhiping; Snyder, Michael; Dermitzakis, Emmanouil T; Thurman, Robert E; Kuehn, Michael S; Taylor, Christopher M; et al. (Nature, 2007)
We report the generation and analysis of functional data from multiple, diverse experiments performed on a targeted 1% of the human genome as part of the pilot phase of the ENCODE Project. These data have been further integrated and augmented by a number of evolutionary and computational analyses. Together, our results advance the collective knowledge about human genome function in several major areas. First, our studies provide convincing evidence that the genome is pervasively transcribed, such that the majority of its bases can be found in primary transcripts, including non-protein-coding transcripts, and those that extensively overlap one another. Second, systematic examination of transcriptional regulation has yielded new understanding about transcription start sites, including their relationship to specific regulatory sequences and features of chromatin accessibility and histone modification. Third, a more sophisticated view of chromatin structure has emerged, including its inter-relationship with DNA replication and transcriptional regulation. Finally, integration of these new sources of information, in particular with respect to mammalian evolution based on inter- and intra-species sequence comparisons, has yielded new mechanistic and evolutionary insights concerning the functional landscape of the human genome. Together, these studies are defining a path for pursuit of a more comprehensive characterization of human genome function.
Keywords: Chromatin; Chromatin Immunoprecipitation; Conserved Sequence; DNA Replication; Evolution, Molecular; Exons; Genetic Variation; Genome, Human; Genomics; Heterozygote; Histones; Humans; Pilot Projects; Protein Binding; Regulatory Sequences, Nucleic Acid; RNA, Messenger; RNA, Untranslated; Transcription Factors; Transcription Initiation Site; Transcription, Genetic

Paradoxical DNA repair and peroxide resistance gene conservation in Bacillus pumilus SAFR-032. - Gioia, Jason; Yerrapragada, Shailaja; Qin, Xiang; Jiang, Huaiyang; Igboeli, Okezie C; Muzny, Donna; Dugan-Rocha, Shannon; Ding, Yan; Hawes, Alicia; Liu, Wen; Perez, Lesette; Kovar, Christie; et al. (PLoS One, 2007)
BACKGROUND: Bacillus spores are notoriously resistant to unfavorable conditions such as UV radiation, gamma-radiation, H2O2, desiccation, chemical disinfection, or starvation. Bacillus pumilus SAFR-032 survives standard decontamination procedures of the Jet Propulsion Lab spacecraft assembly facility, and both spores and vegetative cells of this strain exhibit elevated resistance to UV radiation and H2O2 compared to other Bacillus species. PRINCIPAL FINDINGS: The genome of B. pumilus SAFR-032 was sequenced and annotated. Lists of genes relevant to DNA repair and the oxidative stress response were generated and compared to B. subtilis and B. licheniformis. Differences in conservation of genes, gene order, and protein sequences are highlighted because they potentially explain the extreme resistance phenotype of B. pumilus. The B. pumilus genome includes genes not found in B. subtilis or B. licheniformis and conserved genes with sequence divergence, but paradoxically lacks several genes that function in UV or H2O2 resistance in other Bacillus species. SIGNIFICANCE: This study identifies several candidate genes for further research into UV and H2O2 resistance. These findings will help explain the resistance of B. pumilus and are applicable to understanding sterilization survival strategies of microbes.
Keywords: Bacillus; DNA Repair; Drug Resistance, Bacterial; Gamma Rays; Genes, Bacterial; Genome, Bacterial; Hydrogen Peroxide; Oxidative Stress; Sequence Analysis, DNA; Spores, Bacterial; Ultraviolet Rays

A second generation human haplotype map of over 3.1 million SNPs. - Frazer, Kelly A; Ballinger, Dennis G; Cox, David R; Hinds, David A; Stuve, Laura L; Gibbs, Richard A; Belmont, John W; Boudreau, Andrew; Hardenbol, Paul; Leal, Suzanne M; Pasternak, Shiran; Wheeler, David A; et al. (Nature, 2007)
We describe the Phase II HapMap, which characterizes over 3.1 million human single nucleotide polymorphisms (SNPs) genotyped in 270 individuals from four geographically diverse populations and includes 25-35% of common SNP variation in the populations surveyed. The map is estimated to capture untyped common variation with an average maximum r2 of between 0.9 and 0.96 depending on population. We demonstrate that the current generation of commercial genome-wide genotyping products captures common Phase II SNPs with an average maximum r2 of up to 0.8 in African and up to 0.95 in non-African populations, and that potential gains in power in association studies can be obtained through imputation. These data also reveal novel aspects of the structure of linkage disequilibrium. We show that 10-30% of pairs of individuals within a population share at least one region of extended genetic identity arising from recent ancestry and that up to 1% of all common variants are untaggable, primarily because they lie within recombination hotspots. We show that recombination rates vary systematically around genes and between genes of different function. Finally, we demonstrate increased differentiation at non-synonymous, compared to synonymous, SNPs, resulting from systematic differences in the strength or efficacy of natural selection between populations.
Keywords: Female; Haplotypes; Homozygote; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Racial Groups; Recombination, Genetic; Selection, Genetic

Sequence variation in DOCK9 and heterogeneity in bipolar disorder. - Detera-Wadleigh, Sevilla D; Liu, Chun-yu; Maheshwari, Manjula; Cardona, Imer; Corona, Winston; Akula, Nirmala; Steele, C J M; Badner, Judith A; Kundu, Mukta; Kassem, Layla; Potash, James B; Richard A Gibbs; et al. (Psychiatr Genet, 2007)
BACKGROUND: Linkage of bipolar disorder to a broad region on chromosome 13q has been supported in several studies including a meta-analysis on genome scans. Subsequent reports have shown that variations in the DAOA (G72) locus on 13q33 display association with bipolar disorder but these may not account for all of the linkage evidence in the region. OBJECTIVE: To identify additional susceptibility loci on 13q32-q33 by linkage disequilibrium mapping and explore the impact of phenotypic heterogeneity on association. METHODS: In the initial phase, 98 single nucleotide polymorphism (SNPs) located on 13q32-q33 were genotyped on 285 probands with bipolar disorder and their parents were drawn from families in the NIMH Genetics Initiative consortium for bipolar disorder (NIMH1-4) and two other series. Fine scale mapping using one family series (NIMH1-2) as the test sample was targeted on a gene that displayed the highest evidence of association. A secondary analysis of familial component phenotypes of bipolar disorder was conducted. RESULTS: Three of seven SNPs in DOCK9, a gene that encodes an activator of the Rho-GTPase Cdc42, showed significant excess allelic transmission (P=0.0477-0.00067). Fine scale mapping on DOCK9 yielded evidence of association at nine SNPs in the gene (P=0.02-0.006). Follow-up tests detected excess transmission of the same allele of rs1340 in two out of three other sets of families. The association signals were largely attributable to maternally transmitted alleles (rs1927568: P=0.000083; odds ratio=3.778). A secondary analysis of familial component phenotypes of bipolar disorder detected significant association across multiple DOCK9 markers for racing thoughts, psychosis, delusion during mania and course of illness indicators. CONCLUSION: These results suggest that DOCK9 contributes to both risk and increased illness severity in bipolar disorder. We found evidence for the effect of phenotypic heterogeneity on association. To our knowledge this is the first report to implicate DOCK9 or the Rho-GTPase pathway in the etiology of bipolar disorder.
Keywords: Bipolar Disorder; Family; Female; Genetic Predisposition to Disease; Genetic Variation; Guanine Nucleotide Exchange Factors; Humans; Linkage Disequilibrium; Male; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index

Subtle genetic changes enhance virulence of methicillin resistant and sensitive Staphylococcus aureus. - Highlander, Sarah K; Hultén, Kristina G; Qin, Xiang; Jiang, Huaiyang; Yerrapragada, Shailaja; Mason, Edward O; Shang, Yue; Williams, Tiffany M; Fortunov, Régine M; Liu, Yamei; Igboeli, Okezie; Petrosino, Joseph; et al. (BMC Microbiol, 2007)
BACKGROUND: Community acquired (CA) methicillin-resistant Staphylococcus aureus (MRSA) increasingly causes disease worldwide. USA300 has emerged as the predominant clone causing superficial and invasive infections in children and adults in the USA. Epidemiological studies suggest that USA300 is more virulent than other CA-MRSA. The genetic determinants that render virulence and dominance to USA300 remain unclear. RESULTS: We sequenced the genomes of two pediatric USA300 isolates: one CA-MRSA and one CA-methicillin susceptible (MSSA), isolated at Texas Children's Hospital in Houston. DNA sequencing was performed by Sanger dideoxy whole genome shotgun (WGS) and 454 Life Sciences pyrosequencing strategies. The sequence of the USA300 MRSA strain was rigorously annotated. In USA300-MRSA 2658 chromosomal open reading frames were predicted and 3.1 and 27 kilobase (kb) plasmids were identified. USA300-MSSA contained a 20 kb plasmid with some homology to the 27 kb plasmid found in USA300-MRSA. Two regions found in US300-MRSA were absent in USA300-MSSA. One of these carried the arginine deiminase operon that appears to have been acquired from S. epidermidis. The USA300 sequence was aligned with other sequenced S. aureus genomes and regions unique to USA300 MRSA were identified. CONCLUSION: USA300-MRSA is highly similar to other MRSA strains based on whole genome alignments and gene content, indicating that the differences in pathogenesis are due to subtle changes rather than to large-scale acquisition of virulence factor genes. The USA300 Houston isolate differs from another sequenced USA300 strain isolate, derived from a patient in San Francisco, in plasmid content and a number of sequence polymorphisms. Such differences will provide new insights into the evolution of pathogens.
Keywords: Adolescent; Anti-Bacterial Agents; Base Sequence; Genomic Islands; Humans; Hydrolases; Methicillin Resistance; Molecular Epidemiology; Molecular Sequence Data; Open Reading Frames; Plasmids; Polymorphism, Genetic; Staphylococcal Infections; Staphylococcus aureus; United States

Widespread lateral gene transfer from intracellular bacteria to multicellular eukaryotes. - Dunning Hotopp, Julie C; Clark, Michael E; Oliveira, Deodoro C S G; Foster, Jeremy M; Fischer, Peter; Muñoz Torres, Mónica C; Giebel, Jonathan D; Kumar, Nikhil; Ishmael, Nadeeza; Wang, Shiliang; Ingram, Jessica; Nene, Rahul V; et al. (Science, 2007)
Although common among bacteria, lateral gene transfer-the movement of genes between distantly related organisms-is thought to occur only rarely between bacteria and multicellular eukaryotes. However, the presence of endosymbionts, such as Wolbachia pipientis, within some eukaryotic germlines may facilitate bacterial gene transfers to eukaryotic host genomes. We therefore examined host genomes for evidence of gene transfer events from Wolbachia bacteria to their hosts. We found and confirmed transfers into the genomes of four insect and four nematode species that range from nearly the entire Wolbachia genome (>1 megabase) to short (<500 base pairs) insertions. Potential Wolbachia-to-host transfers were also detected computationally in three additional sequenced insect genomes. We also show that some of these inserted Wolbachia genes are transcribed within eukaryotic cells lacking endosymbionts. Therefore, heritable lateral gene transfer occurs into eukaryotic hosts from their prokaryote symbionts, potentially providing a mechanism for acquisition of new genes and functions.
Keywords: Animals; Chromosome Mapping; Crosses, Genetic; DNA, Bacterial; Drosophila; Female; Gene Transfer, Horizontal; Genes, Bacterial; In Situ Hybridization, Fluorescence; Insecta; Male; Molecular Sequence Data; Nematoda; Retroelements; Reverse Transcriptase Polymerase Chain Reaction; Sequence Analysis, DNA; Symbiosis; Wolbachia

Comparative analysis of the bovine MHC class IIb sequence identifies inversion breakpoints and three unexpected genes. - Childers, C P; Newkirk, H L; Honeycutt, D A; Ramlachan, N; Donna M Muzny; Sodergren, E; Richard A Gibbs; Weinstock, G M; Womack, J E; Skow, L C (Anim Genet, 2006)
The bovine major histocompatibility complex (MHC) or BoLA is organized differently from typical mammalian MHCs in that a large portion of the class II region, called class IIb, has been transposed to a position near the centromere on bovine chromosome 23. Gene mapping indicated that the rearrangement resulted from a single inversion, but the boundaries and gene content of the inverted segment have not been fully determined. Here, we report the genomic sequence of BoLA IIb. Comparative sequence analysis with the human MHC revealed that the proximal inversion breakpoint occurred approximately 2.5 kb from the 3' end of the glutamate-cysteine ligase, catalytic subunit (GCLC) locus and that the distal breakpoint occurred about 2 kb from the 5' end from a divergent class IIDRbeta-like sequence designated DSB. Gene content, order and orientation of BoLA IIb are consistent with the single inversion hypothesis when compared with the corresponding region of the human class II MHC (HLA class II). Differences with HLA include the presence of a single histone H2B gene located between the proteasome subunit, beta type, 9 (PSMB9) and DMB loci and a duplicated TAP2 with a variant splice site. BoLA IIb spans approximately 450 kb DNA, with 20 apparently intact genes and no obvious pseudogenes. The region contains 227 simple sequence repeats (SSRs) and approximately 167 kb of retroviral-related repetitive DNA. Nineteen of the 20 genes identified in silico are supported by bovine EST data indicating that the functional gene content of BoLA IIb has not been diminished because it has been transposed from the remainder of BoLA genes.
Keywords: Animals; Cattle; Chromosome Inversion; Chromosomes, Mammalian; Contig Mapping; Evolution, Molecular; Genes, MHC Class II; Histones; Humans; Molecular Sequence Data; Sequence Analysis, DNA

Desmosomal dysfunction due to mutations in desmoplakin causes arrhythmogenic right ventricular dysplasia/cardiomyopathy. - Yang, Zhao; Bowles, Neil E; Steven E Scherer; Taylor, Michael D; Kearney, Debra L; Ge, Shuping; Nadvoretskiy, Vyacheslav V; DeFreitas, Gilberto; Carabello, Blasé; Brandon, Lois I; Godsel, Lisa M; Green, Kathleen J; et al. (Circ Res, 2006)
Arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is characterized by progressive degeneration of the right ventricular myocardium, ventricular arrhythmias, fibrous-fatty replacement, and increased risk of sudden death. Mutations in 6 genes, including 4 encoding desmosomal proteins (Junctional plakoglobin (JUP), Desmoplakin (DSP), Plakophilin 2, and Desmoglein 2), have been identified in patients with ARVD/C. Mutation analysis of 66 probands identified 4 variants in DSP; V30M, Q90R, W233X, and R2834H. To establish a cause and effect relationship between those DSP missense mutations and ARVD/C, we performed in vitro and in vivo analyses of the mutated proteins. Unlike wild-type (WT) DSP, the N-terminal mutants (V30M and Q90R) failed to localize to the cell membrane in desomosome-forming cell line and failed to bind to and coimmunoprecipitate JUP. Multiple attempts to generate N-terminal DSP (V30M and Q90R) cardiac-specific transgenes have failed: analysis of embryos revealed evidence of profound ventricular dilation, which likely resulted in embryonic lethality. We were able to develop transgenic (Tg) mice with cardiac-restricted overexpression of the C-terminal mutant (R2834H) or WT DSP. Whereas mice overexpressing WT DSP had no detectable histologic, morphological, or functional cardiac changes, the R2834H-Tg mice had increased cardiomyocyte apoptosis, cardiac fibrosis, and lipid accumulation, along with ventricular enlargement and cardiac dysfunction in both ventricles. These mice also displayed interruption of DSP-desmin interaction at intercalated discs (IDs) and marked ultra-structural changes of IDs. These data suggest DSP expression in cardiomyocytes is crucial for maintaining cardiac tissue integrity, and DSP abnormalities result in ARVD/C by cardiomyocyte death, changes in lipid metabolism, and defects in cardiac development.
Keywords: Animals; Apoptosis; Arrhythmogenic Right Ventricular Dysplasia; Cardiomyopathies; Cell Communication; Cell Line, Tumor; Desmoplakins; Desmosomes; DNA Mutational Analysis; Embryo, Mammalian; Heart; Humans; Intercellular Junctions; Lipid Metabolism; Mice; Mice, Transgenic; Mutation, Missense; Myocytes, Cardiac

The DNA sequence, annotation and analysis of human chromosome 3. - Donna M Muzny; Steven E Scherer; Kaul, Rajinder; Wang, Jing; Yu, Jun; Sudbrak, Ralf; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; et al. (Nature, 2006)
After the completion of a draft human genome sequence, the International Human Genome Sequencing Consortium has proceeded to finish and annotate each of the 24 chromosomes comprising the human genome. Here we describe the sequencing and analysis of human chromosome 3, one of the largest human chromosomes. Chromosome 3 comprises just four contigs, one of which currently represents the longest unbroken stretch of finished DNA sequence known so far. The chromosome is remarkable in having the lowest rate of segmental duplication in the genome. It also includes a chemokine receptor gene cluster as well as numerous loci involved in multiple human cancers such as the gene encoding FHIT, which contains the most common constitutive fragile site in the genome, FRA3B. Using genomic sequence from chimpanzee and rhesus macaque, we were able to characterize the breakpoints defining a large pericentric inversion that occurred some time after the split of Homininae from Ponginae, and propose an evolutionary history of the inversion.
Keywords: Animals; Base Sequence; Chromosome Breakage; Chromosome Inversion; Chromosomes, Human, Pair 3; Contig Mapping; CpG Islands; DNA, Complementary; Evolution, Molecular; Expressed Sequence Tags; Human Genome Project; Humans; Macaca mulatta; Molecular Sequence Data; Pan troglodytes; Sequence Analysis, DNA; Synteny

The finished DNA sequence of human chromosome 12. - Scherer, Steven E; Donna M Muzny; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; Gunaratne, Preethi; R. Alan Harris; Hawes, Alicia C; Hernandez, Judith; et al. (Nature, 2006)
Human chromosome 12 contains more than 1,400 coding genes and 487 loci that have been directly implicated in human disease. The q arm of chromosome 12 contains one of the largest blocks of linkage disequilibrium found in the human genome. Here we present the finished sequence of human chromosome 12, which has been finished to high quality and spans approximately 132 megabases, representing approximately 4.5% of the human genome. Alignment of the human chromosome 12 sequence across vertebrates reveals the origin of individual segments in chicken, and a unique history of rearrangement through rodent and primate lineages. The rate of base substitutions in recent evolutionary history shows an overall slowing in hominids compared with primates and rodents.
Keywords: Animals; Base Composition; Chromosomes, Human, Pair 12; CpG Islands; Evolution, Molecular; Expressed Sequence Tags; Genes; Humans; Linkage Disequilibrium; Microsatellite Repeats; Molecular Sequence Data; Mutagenesis, Insertional; Pan troglodytes; Sequence Analysis, DNA; Sequence Deletion; Short Interspersed Nucleotide Elements; Synteny

The generation of a conditional Fmr1 knock out mouse model to study Fmrp function in vivo. - Mientjes, E J; Nieuwenhuizen, I; Kirkpatrick, L; Zu, T; Hoogeveen-Westerveld, M; Severijnen, L; Rifé, M; Willemsen, R; Nelson, D L; Oostra, B A (Neurobiol Dis, 2006)
The FMR1 gene, mutated in Fragile X syndrome patients, has been modeled in mice with a neomycin cassette inserted in exon 5 of the mouse Fmr1 gene creating an Fmr1 knockout (Fmr1 KO) allele. This results in animals lacking Fmr1 protein (Fmrp) expression in all tissues. We have created a new, more versatile Fmr1 in vivo KO model (Fmr1 KO2) and generated conditional Fmr1 KO (CKO) mice by flanking the promoter and first exon of Fmr1 with lox P sites. This enables us to create a null allele in specific cell types and at specific time points by crossing Fmr1 CKO mice with tissue specific or inducible cre-recombinase expressing mice. The new Fmr1 KO2 line does not express any Fmrp and also lacks detectable Fmr1 transcripts. Crossing the Fmr1 CKO line with a Purkinje cell-specific cre-recombinase expresser produces mice that are null for Fmr1 in Purkinje neurons but wild type in all other cell types.
Keywords: Animals; Blotting, Western; Disease Models, Animal; Fragile X Mental Retardation Protein; Fragile X Syndrome; Immunohistochemistry; Mice; Mice, Knockout; Purkinje Cells; Reverse Transcriptase Polymerase Chain Reaction

The genome of the sea urchin Strongylocentrotus purpuratus. - Sodergren, Erica; Weinstock, George M; Davidson, Eric H; Cameron, R Andrew; Gibbs, Richard A; Angerer, Robert C; Angerer, Lynne M; Arnone, Maria Ina; Burgess, David R; Burke, Robert D; Coffman, James A; Dean, Michael; et al. (Science, 2006)
We report the sequence and analysis of the 814-megabase genome of the sea urchin Strongylocentrotus purpuratus, a model for developmental and systems biology. The sequencing strategy combined whole-genome shotgun and bacterial artificial chromosome (BAC) sequences. This use of BAC clones, aided by a pooling strategy, overcame difficulties associated with high heterozygosity of the genome. The genome encodes about 23,300 genes, including many previously thought to be vertebrate innovations or known only outside the deuterostomes. This echinoderm genome provides an evolutionary outgroup for the chordates and yields insights into the evolution of deuterostomes.
Keywords: Animals; Calcification, Physiologic; Cell Adhesion Molecules; Complement Activation; Computational Biology; Embryonic Development; Evolution, Molecular; Gene Expression Regulation, Developmental; Genes; Genome; Immunity, Innate; Immunologic Factors; Male; Nervous System Physiological Phenomena; Proteins; Sequence Analysis, DNA; Signal Transduction; Strongylocentrotus purpuratus; Transcription Factors

Reactivity of antibodies from syphilis patients to a protein array representing the Treponema pallidum proteome. - Brinkman, Mary Beth; McKevitt, Matthew; McLoughlin, Melanie; Perez, Carla; Howell, Jerrilyn; Weinstock, George M; Norris, Steven J; Palzkill, Timothy (J Clin Microbiol, 2006)
To identify antigens important in the human immune response to syphilis, the serum antibody reactivity of syphilitic patients was examined with 908 of the 1,039 proteins in the proteome of Treponema pallidum subsp. pallidum using a protein array enzyme-linked immunosorbent assay. Thirty-four proteins exhibited significant reactivity when assayed with human sera from patients in the early latent stage of syphilis. A subset of antigens identified were further scrutinized for antibody reactivity at primary, secondary, and latent disease stages, and the results demonstrate that the humoral immune response to individual T. pallidum proteins develops at different rates during the time course of infection.
Keywords: Antibodies, Bacterial; Antigens, Bacterial; Bacterial Proteins; Enzyme-Linked Immunosorbent Assay; Humans; In Vitro Techniques; Protein Array Analysis; Proteome; Syphilis; Treponema pallidum

Recurrent duplication-driven transposition of DNA during hominoid evolution. - Johnson, Matthew E; Cheng, Ze; Morrison, V Anne; Scherer, Steven; Ventura, Mario; Gibbs, Richard A; Green, Eric D; Eichler, Evan E (Proc Natl Acad Sci U S A, 2006)
The underlying mechanism by which the interspersed pattern of human segmental duplications has evolved is unknown. Based on a comparative analysis of primate genomes, we show that a particular segmental duplication (LCR16a) has been the source locus for the formation of the majority of intrachromosomal duplications blocks on human chromosome 16. We provide evidence that this particular segment has been active independently in each great ape and human lineage at different points during evolution. Euchromatic sequence that flanks sites of LCR16a integration are frequently lineage-specific duplications. This process has mobilized duplication blocks (15-200 kb in size) to new genomic locations in each species. Breakpoint analysis of lineage-specific insertions suggests coordinated deletion of repeat-rich DNA at the target site, in some cases deleting genes in that species. Our data support a model of duplication where the probability that a segment of DNA becomes duplicated is determined by its proximity to core duplicons, such as LCR16a.
Keywords: Animals; Base Sequence; Biological Evolution; Chromosomes, Human, Pair 16; DNA; DNA Transposable Elements; Evolution, Molecular; Gene Duplication; Hominidae; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

Spectrum of CHD7 mutations in 110 individuals with CHARGE syndrome and genotype-phenotype correlation. - Lalani, Seema R; Safiullah, Arsalan M; Fernbach, Susan D; Harutyunyan, Karine G; Thaller, Christina; Peterson, Leif E; McPherson, John D; Gibbs, Richard A; White, Lisa D; Hefner, Margaret; Davenport, Sandra L H; Graham, John M; et al. (Am J Hum Genet, 2006)
CHARGE syndrome is a well-established multiple-malformation syndrome with distinctive consensus diagnostic criteria. Characteristic associated anomalies include ocular coloboma, choanal atresia, cranial nerve defects, distinctive external and inner ear abnormalities, hearing loss, cardiovascular malformations, urogenital anomalies, and growth retardation. Recently, mutations of the chromodomain helicase DNA-binding protein gene CHD7 were reported to be a major cause of CHARGE syndrome. We sequenced the CHD7 gene in 110 individuals who had received the clinical diagnosis of CHARGE syndrome, and we detected mutations in 64 (58%). Mutations were distributed throughout the coding exons and conserved splice sites of CHD7. Of the 64 mutations, 47 (73%) predicted premature truncation of the protein. These included nonsense and frameshift mutations, which most likely lead to haploinsufficiency. Phenotypically, the mutation-positive group was more likely to exhibit cardiovascular malformations (54 of 59 in the mutation-positive group vs. 30 of 42 in the mutation-negative group; P=.014), coloboma of the eye (55 of 62 in the mutation-positive group vs. 30 of 43 in the mutation-negative group; P=.022), and facial asymmetry, often caused by seventh cranial nerve abnormalities (36 of 56 in the mutation-positive group vs. 13 of 39 in the mutation-negative group; P=.004). Mouse embryo whole-mount and section in situ hybridization showed the expression of Chd7 in the outflow tract of the heart, optic vesicle, facio-acoustic preganglion complex, brain, olfactory pit, and mandibular component of the first branchial arch. Microarray gene-expression analysis showed a signature pattern of gene-expression differences that distinguished the individuals with CHARGE syndrome with CHD7 mutation from the controls. We conclude that cardiovascular malformations, coloboma, and facial asymmetry are common findings in CHARGE syndrome caused by CHD7 mutation.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Child; Child, Preschool; Coloboma; DNA Helicases; DNA Mutational Analysis; DNA-Binding Proteins; Embryo, Mammalian; Facial Asymmetry; Female; Genotype; Heart Defects, Congenital; Humans; In Situ Hybridization, Fluorescence; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Phenotype; RNA Splice Sites; RNA, Messenger; Syndrome

Targeting iCre expression to murine progesterone receptor cell-lineages using bacterial artificial chromosome transgenesis. - Mukherjee, Atish; Soyal, Selma M; David A Wheeler; Fernández-Valdivia, Rodrigo; Nguyen, Jonathan; DeMayo, Francesco J; Lydon, John P (Genesis, 2006)
Gene-targeting in embryonic stem cells has been the dominant genetic approach when engineering mouse models to query the physiologic importance of the progesterone receptor (PR). Although these models have been instrumental in disclosing the in vivo significance of the progesterone signaling pathway, generation of such mice exacts considerable expenditure of time, effort, and expense. Considering the growing list of new PR mouse models that are urgently required to address the next questions in progestin biology, bacterial artificial chromosome (BAC) recombineering in conjunction with transgenesis was evaluated as an alternative method to accelerate the creation of these models in the future. Using this approach, we describe the generation of three PR-BAC(iCre) transgenic lines in which improved Cre recombinase (iCre) was targeted in-frame, downstream, and under the control of the PR promoter contained within a BAC transgene. Crossing with the ROSA26R revealed that the PR-BAC(iCre) transgenic expresses active iCre only in cell-lineages that express the PR. The specificity of the PR-BAC(iCre) transgene not only underscores the importance of BAC-mediated transgenesis as a quick, easy, and affordable method by which to engineer the next generation of PR mouse models, but also provides a unique opportunity to investigate transcriptional control of PR expression as well as PR structure-function relationships in vivo.
Keywords: Animals; Cell Lineage; Chromosomes, Artificial, Bacterial; Computational Biology; DNA Primers; Gene Components; Gene Transfer Techniques; Integrases; Mice; Mice, Transgenic; Models, Animal; Promoter Regions, Genetic; Receptors, Progesterone

Color-blind fluorescence detection for four-color DNA sequencing. - Lewis, Ernest K; Haaland, Wade C; Nguyen, Freddy; Heller, Daniel A; Allen, Matthew J; MacGregor, Robert R; Berger, C Scott; Willingham, Britain; Burns, Lori A; Scott, Graham B I; Kittrell, Carter; Johnson, Bruce R; et al. (Proc Natl Acad Sci U S A, 2005)
We present an approach called pulsed multiline excitation (PME) for measurements of multicomponent, fluorescence species and demonstrate its application in capillary electrophoresis for DNA sequencing. To fully demonstrate the advantages of PME, a fluorescent dye set has been developed whose absorption maxima span virtually the entire visible spectrum. Unlike emission wavelength-dependent approaches for identifying fluorescent species, the removal of the spectral component in PME confers a number of advantages including higher and normalized signals from all dyes present in the assay, the elimination of spectral cross-talk between dyes, and higher signal collection efficiency. Base-calling is unambiguously determined once dye mobility corrections are made. These advantages translate into significantly enhanced signal quality as illustrated in the primary DNA sequencing data and provide a means for achieving accurate base-calling at lower reagent concentrations.
Keywords: Base Sequence; Color; Fluorescence; Fluorescent Dyes; Reproducibility of Results; Sensitivity and Specificity; Sequence Analysis, DNA

Comparative genome sequencing of Drosophila pseudoobscura: chromosomal, gene, and cis-element evolution. - Richards, Stephen; Liu, Yue; Bettencourt, Brian R; Hradecky, Pavel; Letovsky, Stan; Nielsen, Rasmus; Thornton, Kevin; Hubisz, Melissa J; Chen, Rui; Meisel, Richard P; Couronne, Olivier; Hua, Sujun; et al. (Genome Res, 2005)
We have sequenced the genome of a second Drosophila species, Drosophila pseudoobscura, and compared this to the genome sequence of Drosophila melanogaster, a primary model organism. Throughout evolution the vast majority of Drosophila genes have remained on the same chromosome arm, but within each arm gene order has been extensively reshuffled, leading to a minimum of 921 syntenic blocks shared between the species. A repetitive sequence is found in the D. pseudoobscura genome at many junctions between adjacent syntenic blocks. Analysis of this novel repetitive element family suggests that recombination between offset elements may have given rise to many paracentric inversions, thereby contributing to the shuffling of gene order in the D. pseudoobscura lineage. Based on sequence similarity and synteny, 10,516 putative orthologs have been identified as a core gene set conserved over 25-55 million years (Myr) since the pseudoobscura/melanogaster divergence. Genes expressed in the testes had higher amino acid sequence divergence than the genome-wide average, consistent with the rapid evolution of sex-specific proteins. Cis-regulatory sequences are more conserved than random and nearby sequences between the species--but the difference is slight, suggesting that the evolution of cis-regulatory elements is flexible. Overall, a pattern of repeat-mediated chromosomal rearrangement, and high coadaptation of both male genes and cis-regulatory sequences emerges as important themes of genome divergence between these species of Drosophila.
Keywords: Animals; Chromosome Breakage; Chromosome Inversion; Chromosome Mapping; Chromosomes; Conserved Sequence; Drosophila; Drosophila melanogaster; Enhancer Elements, Genetic; Evolution, Molecular; Gene Rearrangement; Genes, Insect; Genetic Variation; Genome; Molecular Sequence Data; Predictive Value of Tests; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA

Deletion of FMR1 in Purkinje cells enhances parallel fiber LTD, enlarges spines, and attenuates cerebellar eyelid conditioning in Fragile X syndrome. - Koekkoek, S K E; Yamaguchi, K; Milojkovic, B A; Dortland, B R; Ruigrok, T J H; Maex, R; De Graaf, W; Smit, A E; VanderWerf, F; Bakker, C E; Willemsen, R; Ikeda, T; et al. (Neuron, 2005)
Absence of functional FMRP causes Fragile X syndrome. Abnormalities in synaptic processes in the cerebral cortex and hippocampus contribute to cognitive deficits in Fragile X patients. So far, the potential roles of cerebellar deficits have not been investigated. Here, we demonstrate that both global and Purkinje cell-specific knockouts of Fmr1 show deficits in classical delay eye-blink conditioning in that the percentage of conditioned responses as well as their peak amplitude and peak velocity are reduced. Purkinje cells of these mice show elongated spines and enhanced LTD induction at the parallel fiber synapses that innervate these spines. Moreover, Fragile X patients display the same cerebellar deficits in eye-blink conditioning as the mutant mice. These data indicate that a lack of FMRP leads to cerebellar deficits at both the cellular and behavioral levels and raise the possibility that cerebellar dysfunctions can contribute to motor learning deficits in Fragile X patients.
Keywords: Animals; Cerebellum; Conditioning, Eyelid; Dendrites; Fragile X Mental Retardation Protein; Fragile X Syndrome; Gene Deletion; Humans; Long-Term Synaptic Depression; Male; Mice; Mice, Knockout; Mice, Mutant Strains; Models, Neurological; Nerve Fibers; Nerve Tissue Proteins; Purkinje Cells; Reflex, Startle; RNA-Binding Proteins

The DNA sequence of the human X chromosome. - Ross, Mark T; Grafham, Darren V; Coffey, Alison J; Scherer, Steven; McLay, Kirsten; Muzny, Donna; Platzer, Matthias; Howell, Gareth R; Burrows, Christine; Bird, Christine P; Frankish, Adam; Lovell, Frances L; et al. (Nature, 2005)
The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that is consistent with their proposed role as way stations in the process of X-chromosome inactivation. We found 1,098 genes in the sequence, of which 99 encode proteins expressed in testis and in various tumour types. A disproportionately high number of mendelian diseases are documented for the X chromosome. Of this number, 168 have been explained by mutations in 113 X-linked genes, which in many cases were characterized with the aid of the DNA sequence.
Keywords: Animals; Antigens, Neoplasm; Centromere; Chromosomes, Human, X; Chromosomes, Human, Y; Contig Mapping; Crossing Over, Genetic; Dosage Compensation, Genetic; Evolution, Molecular; Female; Genetic Linkage; Genetics, Medical; Genomics; Humans; Male; Polymorphism, Single Nucleotide; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Testis

Generation and annotation of the DNA sequences of human chromosomes 2 and 4. - Hillier, LaDeana W; Graves, Tina A; Fulton, Robert S; Fulton, Lucinda A; Pepin, Kymberlie H; Minx, Patrick; Wagner-McPherson, Caryn; Layman, Dan; Wylie, Kristine; Sekhon, Mandeep; Becker, Michael C; Fewell, Ginger A; et al. (Nature, 2005)
Human chromosome 2 is unique to the human lineage in being the product of a head-to-head fusion of two intermediate-sized ancestral chromosomes. Chromosome 4 has received attention primarily related to the search for the Huntington's disease gene, but also for genes associated with Wolf-Hirschhorn syndrome, polycystic kidney disease and a form of muscular dystrophy. Here we present approximately 237 million base pairs of sequence for chromosome 2, and 186 million base pairs for chromosome 4, representing more than 99.6% of their euchromatic sequences. Our initial analyses have identified 1,346 protein-coding genes and 1,239 pseudogenes on chromosome 2, and 796 protein-coding genes and 778 pseudogenes on chromosome 4. Extensive analyses confirm the underlying construction of the sequence, and expand our understanding of the structure and evolution of mammalian chromosomes, including gene deserts, segmental duplications and highly variant regions.
Keywords: Animals; Base Composition; Base Sequence; Centromere; Chromosomes, Human, Pair 2; Chromosomes, Human, Pair 4; Conserved Sequence; CpG Islands; Euchromatin; Expressed Sequence Tags; Gene Duplication; Genetic Variation; Genomics; Humans; Molecular Sequence Data; Physical Chromosome Mapping; Polymorphism, Genetic; Primates; Proteins; Pseudogenes; Recombination, Genetic; RNA, Messenger; RNA, Untranslated; Sequence Analysis, DNA

The genome of the social amoeba Dictyostelium discoideum. - Eichinger, L; Pachebat, J A; Glöckner, G; Rajandream, M-A; Sucgang, R; Berriman, M; Song, J; Olsen, R; Szafranski, K; Xu, Q; Tunggal, B; Kummerfeld, S; et al. (Nature, 2005)
The social amoebae are exceptional in their ability to alternate between unicellular and multicellular forms. Here we describe the genome of the best-studied member of this group, Dictyostelium discoideum. The gene-dense chromosomes of this organism encode approximately 12,500 predicted proteins, a high proportion of which have long, repetitive amino acid tracts. There are many genes for polyketide synthases and ABC transporters, suggesting an extensive secondary metabolism for producing and exporting small molecules. The genome is rich in complex repeats, one class of which is clustered and may serve as centromeres. Partial copies of the extrachromosomal ribosomal DNA (rDNA) element are found at the ends of each chromosome, suggesting a novel telomere structure and the use of a common mechanism to maintain both the rDNA and chromosomal termini. A proteome-based phylogeny shows that the amoebozoa diverged from the animal-fungal lineage after the plant-animal split, but Dictyostelium seems to have retained more of the diversity of the ancestral genome than have plants, animals or fungi.
Keywords: Animals; ATP-Binding Cassette Transporters; Base Composition; Cell Adhesion; Cell Movement; Centromere; Conserved Sequence; Dictyostelium; DNA Transposable Elements; DNA, Ribosomal; Eukaryotic Cells; Gene Duplication; Gene Transfer, Horizontal; Genome; Genomics; Humans; Molecular Sequence Data; Phylogeny; Proteome; Protozoan Proteins; Repetitive Sequences, Nucleic Acid; RNA, Transfer; Sequence Analysis, DNA; Signal Transduction; Social Behavior; Telomere

Genome scale identification of Treponema pallidum antigens. - McKevitt, Matthew; Brinkman, Mary Beth; McLoughlin, Melanie; Perez, Carla; Howell, Jerrilyn K; Weinstock, George M; Norris, Steven J; Palzkill, Timothy (Infect Immun, 2005)
Antibody responses for 882 of the 1,039 proteins in the proteome of Treponema pallidum were examined. Sera collected from infected rabbits were used to systematically identify 106 antigenic proteins, including 22 previously identified antigens and 84 novel antigens. Additionally, sera collected from rabbits throughout the course of infection demonstrated a progression in the breadth and intensity of humoral immunoreactivity against a representative panel of T. pallidum antigens.
Keywords: Animals; Antibodies, Bacterial; Antigens, Bacterial; Genome, Bacterial; Proteome; Rabbits; Treponema pallidum

Highly multiplexed molecular inversion probe genotyping: over 10,000 targeted SNPs genotyped in a single tube assay. - Hardenbol, Paul; Yu, Fuli; Belmont, John; Mackenzie, Jennifer; Bruckner, Carsten; Brundage, Tiffany; Boudreau, Andrew; Chow, Steve; Eberle, Jim; Erbilgin, Ayca; Falkowski, Mat; Fitzgerald, Ron; et al. (Genome Res, 2005)
Large-scale genetic studies are highly dependent on efficient and scalable multiplex SNP assays. In this study, we report the development of Molecular Inversion Probe technology with four-color, single array detection, applied to large-scale genotyping of up to 12,000 SNPs per reaction. While generating 38,429 SNP assays using this technology in a population of 30 trios from the Centre d'Etude Polymorphisme Humain family panel as part of the International HapMap project, we established SNP conversion rates of approximately 90% with concordance rates >99.6% and completeness levels >98% for assays multiplexed up to 12,000plex levels. Furthermore, these individual metrics can be "traded off" and, by sacrificing a small fraction of the conversion rate, the accuracy can be increased to very high levels. No loss of performance is seen when scaling from 6,000plex to 12,000plex assays, strongly validating the ability of the technology to suppress cross-reactivity at high multiplex levels. The results of this study demonstrate the suitability of this technology for comprehensive association studies that use targeted SNPs in indirect linkage disequilibrium studies or that directly screen for causative mutations.
Keywords: Chromosome Inversion; Cluster Analysis; DNA Probes; Gene Expression Profiling; Genome, Human; Genotype; Humans; Molecular Probe Techniques; Molecular Probes; Polymorphism, Single Nucleotide; Research Design

Molecular characterization of a widespread, pathogenic, and antibiotic resistance-receptive Enterococcus faecalis lineage and dissemination of its putative pathogenicity island. - Nallapareddy, Sreedhar R; Wenxiang, Huang; Weinstock, George M; Murray, Barbara E (J Bacteriol, 2005)
Enterococcus faecalis, a common cause of endocarditis and known for its capacity to transfer antibiotic resistance to other pathogens, has recently emerged as an important, multidrug-resistant nosocomial pathogen. However, knowledge of its lineages and the potential of particular clones of this species to disseminate and cause disease is limited. Using a nine-gene multilocus sequence typing (MLST) scheme, we identified an evolving and widespread clonal complex of E. faecalis that has caused outbreaks and life-threatening infections. Moreover, this unusual clonal complex was found to contain isolates of unexpected relatedness, including the first known U.S. vancomycin-resistant enterococcus (E. faecalis strain V583), the first known penicillinase-producing (Bla(+)) E. faecalis isolate, and the previously described widespread clone of penicillinase producers, a trait found in <0.1% of E. faecalis isolates. All members of this clonal cluster (designated as BVE for Bla(+) Van(r) endocarditis) were found to contain a previously described putative pathogenicity island (PAI). Further analysis of this PAI demonstrated its dissemination worldwide, albeit with considerable variability, confirmed its association with clinical isolates, and found a common insertion site in different clonal lineages. PAI deletions, MLST, and the uncommon resistances were used to predict the evolution of the BVE clonal cluster. The finding of a virulent and highly successful clonal complex of E. faecalis with different members resistant to the primary therapies of choice, ampicillin and vancomycin, has important implications for the evolution of virulence and successful lineages and for public health monitoring and control.
Keywords: Bacterial Proteins; Chromosomes, Bacterial; Drug Resistance, Bacterial; Endocarditis; Enterococcus faecalis; Genomic Islands; Gram-Positive Bacterial Infections; Humans; Virulence; Virulence Factors

Positive selection of a pre-expansion CAG repeat of the human SCA2 gene. - Yu, Fuli; Sabeti, Pardis C; Hardenbol, Paul; Fu, Qing; Fry, Ben; Lu, Xiuhua; Ghose, Sy; Vega, Richard; Perez, Ag; Pasternak, Shiran; Leal, Suzanne M; Willis, Thomas D; et al. (PLoS Genet, 2005)
A region of approximately one megabase of human Chromosome 12 shows extensive linkage disequilibrium in Utah residents with ancestry from northern and western Europe. This strikingly large linkage disequilibrium block was analyzed with statistical and experimental methods to determine whether natural selection could be implicated in shaping the current genome structure. Extended Haplotype Homozygosity and Relative Extended Haplotype Homozygosity analyses on this region mapped a core region of the strongest conserved haplotype to the exon 1 of the Spinocerebellar ataxia type 2 gene (SCA2). Direct DNA sequencing of this region of the SCA2 gene revealed a significant association between a pre-expanded allele [(CAG)8CAA(CAG)4CAA(CAG)8] of CAG repeats within exon 1 and the selected haplotype of the SCA2 gene. A significantly negative Tajima's D value (-2.20, p < 0.01) on this site consistently suggested selection on the CAG repeat. This region was also investigated in the three other populations, none of which showed signs of selection. These results suggest that a recent positive selection of the pre-expansion SCA2 CAG repeat has occurred in Utah residents with European ancestry.
Keywords: Ataxins; Base Sequence; Chromosome Mapping; Chromosomes, Human, Pair 12; Europe; Exons; Gene Frequency; Humans; Molecular Sequence Data; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Selection, Genetic; Spinocerebellar Degenerations; Trinucleotide Repeats; Utah; White People

Transcriptome of Treponema pallidum: gene expression profile during experimental rabbit infection. - Smajs, David; McKevitt, Matthew; Howell, Jerrilyn K; Norris, Steven J; Cai, Wei-Wen; Palzkill, Timothy; Weinstock, George M (J Bacteriol, 2005)
RNA transcript levels in the syphilis spirochete Treponema pallidum subsp. pallidum (Nichols) isolated from experimentally infected rabbits were determined by the use of DNA microarray technology. This characterization of the T. pallidum transcriptome during experimental infection provides further insight into the importance of gene expression levels for the survival and pathogenesis of this bacterium.
Keywords: Animals; Gene Expression; Gene Expression Profiling; Oligonucleotide Array Sequence Analysis; Open Reading Frames; Rabbits; RNA, Bacterial; RNA, Messenger; Syphilis; Treponema pallidum

Biochemical and genetic interaction between the fragile X mental retardation protein and the microRNA pathway. - Jin, Peng; Zarnescu, Daniela C; Ceman, Stephanie; Nakamoto, Mika; Mowrey, Julie; Jongens, Thomas A; Nelson, David L; Moses, Kevin; Warren, Stephen T (Nat Neurosci, 2004)
Fragile X syndrome is caused by a loss of expression of the fragile X mental retardation protein (FMRP). FMRP is a selective RNA-binding protein which forms a messenger ribonucleoprotein (mRNP) complex that associates with polyribosomes. Recently, mRNA ligands associated with FMRP have been identified. However, the mechanism by which FMRP regulates the translation of its mRNA ligands remains unclear. MicroRNAs are small noncoding RNAs involved in translational control. Here we show that in vivo mammalian FMRP interacts with microRNAs and the components of the microRNA pathways including Dicer and the mammalian ortholog of Argonaute 1 (AGO1). Using two different Drosophila melanogaster models, we show that AGO1 is critical for FMRP function in neural development and synaptogenesis. Our results suggest that FMRP may regulate neuronal translation via microRNAs and links microRNAs with human disease.
Keywords: Animals; Argonaute Proteins; Blotting, Western; Disease Models, Animal; Drosophila melanogaster; Drosophila Proteins; Eye; Fragile X Syndrome; HeLa Cells; Humans; Immunohistochemistry; Male; MicroRNAs; Microscopy, Electron, Scanning; Nerve Tissue Proteins; Neuromuscular Junction; Neuronal Plasticity; Precipitin Tests; Ribonuclease III; RNA-Induced Silencing Complex

Comparison of genome degradation in Paratyphi A and Typhi, human-restricted serovars of Salmonella enterica that cause typhoid. - McClelland, Michael; Sanderson, Kenneth E; Clifton, Sandra W; Latreille, Phil; Porwollik, Steffen; Aniko Sabo; Meyer, Rekha; Bieri, Tamberlyn; Ozersky, Phil; McLellan, Michael; Harkins, C Richard; Wang, Chunyan; et al. (Nat Genet, 2004)
Salmonella enterica serovars often have a broad host range, and some cause both gastrointestinal and systemic disease. But the serovars Paratyphi A and Typhi are restricted to humans and cause only systemic disease. It has been estimated that Typhi arose in the last few thousand years. The sequence and microarray analysis of the Paratyphi A genome indicates that it is similar to the Typhi genome but suggests that it has a more recent evolutionary origin. Both genomes have independently accumulated many pseudogenes among their approximately 4,400 protein coding sequences: 173 in Paratyphi A and approximately 210 in Typhi. The recent convergence of these two similar genomes on a similar phenotype is subtly reflected in their genotypes: only 30 genes are degraded in both serovars. Nevertheless, these 30 genes include three known to be important in gastroenteritis, which does not occur in these serovars, and four for Salmonella-translocated effectors, which are normally secreted into host cells to subvert host functions. Loss of function also occurs by mutation in different genes in the same pathway (e.g., in chemotaxis and in the production of fimbriae).
Keywords: Base Sequence; Evolution, Molecular; Gene Library; Genetic Variation; Genome Components; Genome, Bacterial; Humans; Microarray Analysis; Molecular Sequence Data; Mutation; Pseudogenes; Salmonella paratyphi A; Salmonella typhi; Sequence Analysis, DNA; Species Specificity

Comparison of the genome of the oral pathogen Treponema denticola with other spirochete genomes. - Seshadri, Rekha; Myers, Garry S A; Tettelin, Hervé; Eisen, Jonathan A; Heidelberg, John F; Dodson, Robert J; Davidsen, Tanja M; DeBoy, Robert T; Fouts, Derrick E; Haft, Dan H; Selengut, Jeremy; Ren, Qinghu; et al. (Proc Natl Acad Sci U S A, 2004)
We present the complete 2,843,201-bp genome sequence of Treponema denticola (ATCC 35405) an oral spirochete associated with periodontal disease. Analysis of the T. denticola genome reveals factors mediating coaggregation, cell signaling, stress protection, and other competitive and cooperative measures, consistent with its pathogenic nature and lifestyle within the mixed-species environment of subgingival dental plaque. Comparisons with previously sequenced spirochete genomes revealed specific factors contributing to differences and similarities in spirochete physiology as well as pathogenic potential. The T. denticola genome is considerably larger in size than the genome of the related syphilis-causing spirochete Treponema pallidum. The differences in gene content appear to be attributable to a combination of three phenomena: genome reduction, lineage-specific expansions, and horizontal gene transfer. Genes lost due to reductive evolution appear to be largely involved in metabolism and transport, whereas some of the genes that have arisen due to lineage-specific expansions are implicated in various pathogenic interactions, and genes acquired via horizontal gene transfer are largely phage-related or of unknown function.
Keywords: ATP-Binding Cassette Transporters; Bacterial Proteins; Base Sequence; Borrelia burgdorferi; Genes, Bacterial; Genome, Bacterial; Leptospira interrogans; Models, Genetic; Molecular Sequence Data; Mouth; Sequence Homology, Amino Acid; Treponema; Treponema pallidum

Construction of small genome BAC library for functional and genomic applications. - Smajs, David; Norris, Steven J; Weinstock, George M (Methods Mol Biol, 2004)
Keywords: Base Sequence; Chromosomes, Artificial, Bacterial; DNA Primers; DNA, Bacterial; Electrophoresis, Gel, Pulsed-Field; Escherichia coli; Genetic Vectors; Genome, Bacterial; Genomic Library; Genomics; Restriction Mapping; Treponema pallidum

Fxr1 knockout mice show a striated muscle phenotype: implications for Fxr1p function in vivo. - Mientjes, Edwin J; Willemsen, Rob; Kirkpatrick, Laura L; Nieuwenhuizen, Ingeborg M; Hoogeveen-Westerveld, Marianne; Verweij, Marcel; Reis, Surya; Bardoni, Barbara; Hoogeveen, Andre T; Oostra, Ben A; Nelson, David L (Hum Mol Genet, 2004)
FXR1 is one of the two known homologues of FMR1. FXR1 shares a high degree of sequence homology with FMR1 and also encodes two KH domains and an RGG domain, conferring RNA-binding capabilities. In comparison with FMRP, very little is known about the function of FXR1P in vivo. Mouse knockout (KO) models exist for both Fmr1 and Fxr2. To study the function of Fxr1 in vivo, we generated an Fxr1 KO mouse model. Homozygous Fxr1 KO neonates die shortly after birth most likely due to cardiac or respiratory failure. Histochemical analyses carried out on both skeletal and cardiac muscles show a disruption of cellular architecture and structure in E19 Fxr1 neonates compared with wild-type (WT) littermates. In WT E19 skeletal and cardiac muscles, Fxr1p is localized to the costameric regions within the muscles. In E19 Fxr1 KO littermates, in addition to the absence of Fxr1p, costameric proteins vinculin, dystrophin and alpha-actinin were found to be delocalized. A second mouse model (Fxr1 + neo), which expresses strongly reduced levels of Fxr1p relative to WT littermates, does not display the neonatal lethal phenotype seen in the Fxr1 KOs but does display a strongly reduced limb musculature and has a reduced life span of approximately 18 weeks. The results presented here point towards a role for Fxr1p in muscle mRNA transport/translation control similar to that seen for Fmrp in neuronal cells.
Keywords: Animals; Cytoskeletal Proteins; Fragile X Mental Retardation Protein; Hindlimb; Longevity; Mice; Mice, Knockout; Muscle, Skeletal; Myocardium; Nerve Tissue Proteins; Protein Structure, Tertiary; RNA, Messenger; RNA-Binding Proteins; Sequence Homology

Genetics. The critical region in trisomy 21. - Nelson, David L; Richard A Gibbs (Science, 2004)
Keywords: Animals; Chromosome Deletion; Chromosomes, Human, Pair 21; Chromosomes, Mammalian; Craniofacial Abnormalities; Crosses, Genetic; Disease Models, Animal; Down Syndrome; Female; Gene Duplication; Humans; Male; Mice; Recombination, Genetic; Skull; Trisomy

Genome sequence of the Brown Norway rat yields insights into mammalian evolution. - Gibbs, Richard A; Weinstock, George M; Metzker, Michael L; Muzny, Donna M; Sodergren, Erica J; Scherer, Steven; Scott, Graham; Steffen, David; Worley, Kim C; Burch, Paula E; Okwuonu, Geoffrey; Hines, Sandra; et al. (Nature, 2004)
The laboratory rat (Rattus norvegicus) is an indispensable tool in experimental medicine and drug development, having made inestimable contributions to human health. We report here the genome sequence of the Brown Norway (BN) rat strain. The sequence represents a high-quality 'draft' covering over 90% of the genome. The BN rat sequence is the third complete mammalian genome to be deciphered, and three-way comparisons with the human and mouse genomes resolve details of mammalian evolution. This first comprehensive analysis includes genes and proteins and their relation to human disease, repeated sequences, comparative genome-wide studies of mammalian orthologous chromosomal regions and rearrangement breakpoints, reconstruction of ancestral karyotypes and the events leading to existing species, rates of variation, and lineage-specific and lineage-independent evolutionary events such as expansion of gene families, orthology relations and protein evolution.
Keywords: Animals; Base Composition; Centromere; Chromosomes, Mammalian; CpG Islands; DNA Transposable Elements; DNA, Mitochondrial; Evolution, Molecular; Gene Duplication; Genome; Genomics; Humans; Introns; Male; Mice; Models, Molecular; Mutagenesis; Polymorphism, Single Nucleotide; Rats; Rats, Inbred BN; Regulatory Sequences, Nucleic Acid; Retroelements; RNA Splice Sites; RNA, Untranslated; Sequence Analysis, DNA; Telomere

In silico genetics: identification of a functional element regulating H2-Ealpha gene expression. - Liao, Guochun; Wang, Jianmei; Guo, Jingshu; Allard, John; Cheng, Janet; Ng, Anh; Shafer, Steve; Puech, Anne; McPherson, John D; Foernzler, Dorothee; Peltz, Gary; Usuka, Jonathan (Science, 2004)
Computational tools can markedly accelerate the rate at which murine genetic models can be analyzed. We developed a computational method for mapping phenotypic traits that vary among inbred strains onto haplotypic blocks. This method correctly predicted the genetic basis for strain-specific differences in several biologically important traits. It was also used to identify an allele-specific functional genomic element regulating H2-Ealpha gene expression. This functional element, which contained the binding sites for YY1 and a second transcription factor that is probably serum response factor, is located within the first intron of the H2-Ealpha gene. This computational method will greatly improve our ability to identify the genetic basis for a variety of phenotypic traits, ranging from qualitative trait information to quantitative gene expression data, which vary among inbred mouse strains.
Keywords: Alleles; Animals; Binding Sites; Computational Biology; Electrophoretic Mobility Shift Assay; Gene Expression Profiling; Gene Expression Regulation; Genes, MHC Class II; Genetic Variation; H-2 Antigens; Haplotypes; Hydrocarbons, Aromatic; Introns; Liver; Lung; Major Histocompatibility Complex; Mice; Mice, Inbred Strains; Oligodeoxyribonucleotides; Oligonucleotide Array Sequence Analysis; Phenotype; Polymorphism, Single Nucleotide; Receptors, Aryl Hydrocarbon; Regulatory Sequences, Nucleic Acid; Serum Response Factor; Transcription Factors

A physical map of the chicken genome. - Wallis, John W; Aerts, Jan; Groenen, Martien A M; Crooijmans, Richard P M A; Layman, Dan; Graves, Tina A; Scheer, Debra E; Kremitzki, Colin; Fedele, Mary J; Mudd, Nancy K; Cardenas, Marco; Higginbotham, Jamey; et al. (Nature, 2004)
Strategies for assembling large, complex genomes have evolved to include a combination of whole-genome shotgun sequencing and hierarchal map-assisted sequencing. Whole-genome maps of all types can aid genome assemblies, generally starting with low-resolution cytogenetic maps and ending with the highest resolution of sequence. Fingerprint clone maps are based upon complete restriction enzyme digests of clones representative of the target genome, and ultimately comprise a near-contiguous path of clones across the genome. Such clone-based maps are used to validate sequence assembly order, supply long-range linking information for assembled sequences, anchor sequences to the genetic map and provide templates for closing gaps. Fingerprint maps are also a critical resource for subsequent functional genomic studies, because they provide a redundant and ordered sampling of the genome with clones. In an accompanying paper we describe the draft genome sequence of the chicken, Gallus gallus, the first species sequenced that is both a model organism and a global food source. Here we present a clone-based physical map of the chicken genome at 20-fold coverage, containing 260 contigs of overlapping clones. This map represents approximately 91% of the chicken genome and enables identification of chicken clones aligned to positions in other sequenced genomes.
Keywords: Animals; Chickens; Chromosomes, Artificial, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Genetic Linkage; Genome; Genomics; Physical Chromosome Mapping; Sequence Tagged Sites

Somatic and germline instability of the ATTCT repeat in spinocerebellar ataxia type 10. - Matsuura, Tohru; Fang, Ping; Lin, Xi; Khajavi, Mehrdad; Tsuji, Kuniko; Rasmussen, Astrid; Grewal, Raji P; Achari, Madhureeta; Alonso, Maria E; Pulst, Stefan M; Zoghbi, Huda Y; Nelson, David L; et al. (Am J Hum Genet, 2004)
Spinocerebellar ataxia type 10 (SCA10) is an autosomal dominant disorder characterized by ataxia, seizures, and anticipation. It is caused by an expanded ATTCT pentanucleotide repeat in intron 9 of a novel gene, designated "SCA10." The ATTCT expansion in SCA10 represents a novel class of microsatellite repeat and is one of the largest found to cause human diseases. The expanded ATTCT repeat is unstably transmitted from generation to generation, and an inverse correlation has been observed between size of repeat and age at onset. In this multifamily study, we investigated the intergenerational instability, somatic and germline mosaicism, and age-dependent repeat-size changes of the expanded ATTCT repeat. Our results showed that (1) the expanded ATTCT repeats are highly unstable when paternally transmitted, whereas maternal transmission resulted in significantly smaller changes in repeat size; (2) blood leukocytes, lymphoblastoid cells, buccal cells, and sperm have a variable degree of mosaicism in ATTCT expansion; (3) the length of the expanded repeat was not observed to change in individuals over a 5-year period; and (4) clinically determined anticipation is sometimes associated with intergenerational contraction rather than expansion of the ATTCT repeat.
Keywords: Age Distribution; Cell Line; Disease Transmission, Infectious; DNA; Female; Genes, Dominant; Germ Cells; Humans; Leukocytes; Male; Microsatellite Repeats; Mouth Mucosa; Pedigree; Repetitive Sequences, Nucleic Acid; Spermatozoa; Spinocerebellar Ataxias

WormBase: a multi-species resource for nematode biology and genomics. - Harris, Todd W; Chen, Nansheng; Cunningham, Fiona; Tello-Ruiz, Marcela; Antoshechkin, Igor; Bastiani, Carol; Bieri, Tamberlyn; Blasiar, Darin; Bradnam, Keith; Chan, Juancarlos; Chen, Chao-Kung; Chen, Wen J; et al. (Nucleic Acids Res, 2004)
WormBase (http://www.wormbase.org/) is the central data repository for information about Caenorhabditis elegans and related nematodes. As a model organism database, WormBase extends beyond the genomic sequence, integrating experimental results with extensively annotated views of the genome. The WormBase Consortium continues to expand the biological scope and utility of WormBase with the inclusion of large-scale genomic analyses, through active data and literature curation, through new analysis and visualization tools, and through refinement of the user interface. Over the past year, the nearly complete genomic sequence and comparative analyses of the closely related species Caenorhabditis briggsae have been integrated into WormBase, including gene predictions, ortholog assignments and a new synteny viewer to display the relationships between the two species. Extensive site-wide refinement of the user interface now provides quick access to the most frequently accessed resources and a consistent browsing experience across the site. Unified single-page views now provide complete summaries of commonly accessed entries like genes. These advances continue to increase the utility of WormBase for C.elegans researchers, as well as for those researchers exploring problems in functional and comparative genomics in the context of a powerful genetic system.
Keywords: Animals; Caenorhabditis; Caenorhabditis elegans; Computational Biology; Databases, Genetic; Genomics; Information Storage and Retrieval; Internet; User-Computer Interface

Association of the T-cell regulatory gene CTLA4 with susceptibility to autoimmune disease. - Ueda, Hironori; Howson, Joanna M M; Esposito, Laura; Heward, Joanne; Snook, Hywel; Chamberlain, Giselle; Rainbow, Daniel B; Hunter, Kara M D; Smith, Annabel N; Di Genova, Gianfranco; Herr, Mathias H; Dahlman, Ingrid; et al. (Nature, 2003)
Genes and mechanisms involved in common complex diseases, such as the autoimmune disorders that affect approximately 5% of the population, remain obscure. Here we identify polymorphisms of the cytotoxic T lymphocyte antigen 4 gene (CTLA4)--which encodes a vital negative regulatory molecule of the immune system--as candidates for primary determinants of risk of the common autoimmune disorders Graves' disease, autoimmune hypothyroidism and type 1 diabetes. In humans, disease susceptibility was mapped to a non-coding 6.1 kb 3' region of CTLA4, the common allelic variation of which was correlated with lower messenger RNA levels of the soluble alternative splice form of CTLA4. In the mouse model of type 1 diabetes, susceptibility was also associated with variation in CTLA-4 gene splicing with reduced production of a splice form encoding a molecule lacking the CD80/CD86 ligand-binding domain. Genetic mapping of variants conferring a small disease risk can identify pathways in complex disorders, as exemplified by our discovery of inherited, quantitative alterations of CTLA4 contributing to autoimmune tissue destruction.
Keywords: Abatacept; Alternative Splicing; Animals; Antigens, CD; Antigens, Differentiation; Autoimmune Diseases; Base Sequence; CTLA-4 Antigen; Diabetes Mellitus, Type 1; Disease Models, Animal; Genetic Predisposition to Disease; Genotype; Graves Disease; Humans; Hypothyroidism; Immunoconjugates; Mice; Polymorphism, Single Nucleotide; Protein Isoforms; T-Lymphocytes

Clinical isolates of Enterococcus faecium exhibit strain-specific collagen binding mediated by Acm, a new member of the MSCRAMM family. - Nallapareddy, Sreedhar R; Weinstock, George M; Murray, Barbara E (Mol Microbiol, 2003)
A collagen-binding adhesin of Enterococcus faecium, Acm, was identified. Acm shows 62% similarity to the Staphylococcus aureus collagen adhesin Cna over the entire protein and is more similar to Cna (60% and 75% similarity with Cna A and B domains respectively) than to the Enterococcus faecalis collagen-binding adhesin, Ace, which shares homology with Acm only in the A domain. Despite the detection of acm in 32 out of 32 E. faecium isolates, only 11 of these (all clinical isolates, including four vancomycin-resistant endocarditis isolates and seven other isolates) exhibited binding to collagen type I (CI). Although acm from three CI-binding vancomycin-resistant E. faecium clinical isolates showed 100% identity, analysis of acm genes and their promoter regions from six non-CI-binding strains identified deletions or mutations that introduced stop codons and/or IS elements within the gene or the promoter region in five out of six strains, suggesting that the presence of an intact functional acm gene is necessary for binding of E. faecium strains to CI. Recombinant Acm A domain showed specific and concentration-dependent binding to collagen, and this protein competed with E. faecium binding to immobilized CI. Consistent with the adherence phenotype and sequence data, probing with Acm-specific IgGs purified from anti-recombinant Acm A polyclonal rabbit serum confirmed the surface expression of Acm in three out of three collagen-binding clinical isolates of E. faecium tested, but in none of the strains with a non-functional pseudo acm gene. Introduction of a functional acm gene into two non-CI-binding natural acm mutant strains conferred a CI-binding phenotype, further confirming that native Acm is sufficient for the binding of E. faecium to CI. These results demonstrate that acm, which encodes a potential virulence factor, is functional only in certain infection-derived clinical isolates of E. faecium, and suggest that Acm is the primary adhesin responsible for the ability of E. faecium to bind collagen.
Keywords: Adhesins, Bacterial; Amino Acid Sequence; Animals; Bacterial Adhesion; Cell Membrane; Collagen; Collagen Type I; Enterococcus faecium; Genetic Complementation Test; Gram-Positive Bacteria; Humans; Molecular Sequence Data; Mutation; Protein Structure, Tertiary; Pseudogenes; Rabbits; Recombinant Proteins; Sequence Homology, Amino Acid; Species Specificity

Dissection of K+ currents in Caenorhabditis elegans muscle cells by genetics and RNA interference. - Santi, C M; Yuan, A; Fawcett, G; Wang, Z-W; Butler, A; Nonet, M L; Wei, A; Rojas, P; Salkoff, L (Proc Natl Acad Sci U S A, 2003)
GFP-promoter experiments have previously shown that at least nine genes encoding potassium channel subunits are expressed in Caenorhabditis elegans muscle. By using genetic, RNA interference, and physiological techniques we revealed the molecular identity of the major components of the outward K+ currents in body wall muscle cells in culture. We found that under physiological conditions, outward current is dominated by the products of only two genes, Shaker (Kv1) and Shal (Kv4), both expressing voltage-dependent potassium channels. Other channels may be held in reserve to respond to particular circumstances. Because GFP-promoter experiments indicated that slo-2 expression is prominent, we created a deletion mutant to identify the SLO-2 current in vivo. In both whole-cell and single-channel modes, in vivo SLO-2 channels were active only when intracellular Ca2+ and Cl- were raised above normal physiological conditions, as occurs during hypoxia. Under such conditions, SLO-2 is the largest outward current, contributing up to 87% of the total current. Other channels are present in muscle, but our results suggest that they are unlikely to contribute a large outward component under physiological conditions. However, they, too, may contribute currents conditional on other factors. Hence, the picture that emerges is of a complex membrane with a small number of household conductances functioning under normal circumstances, but with additional conductances that are activated during unusual circumstances.
Keywords: Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Genes, Helminth; Membrane Transport Proteins; Muscles; Mutation; Potassium Channels; Potassium Channels, Voltage-Gated; RNA Interference; Shaker Superfamily of Potassium Channels; Shal Potassium Channels

The DNA sequence of human chromosome 7. - Hillier, LaDeana W; Fulton, Robert S; Fulton, Lucinda A; Graves, Tina A; Pepin, Kymberlie H; Wagner-McPherson, Caryn; Layman, Dan; Maas, Jason; Jaeger, Sara; Walker, Rebecca; Wylie, Kristine; Sekhon, Mandeep; et al. (Nature, 2003)
Human chromosome 7 has historically received prominent attention in the human genetics community, primarily related to the search for the cystic fibrosis gene and the frequent cytogenetic changes associated with various forms of cancer. Here we present more than 153 million base pairs representing 99.4% of the euchromatic sequence of chromosome 7, the first metacentric chromosome completed so far. The sequence has excellent concordance with previously established physical and genetic maps, and it exhibits an unusual amount of segmentally duplicated sequence (8.2%), with marked differences between the two arms. Our initial analyses have identified 1,150 protein-coding genes, 605 of which have been confirmed by complementary DNA sequences, and an additional 941 pseudogenes. Of genes confirmed by transcript sequences, some are polymorphic for mutations that disrupt the reading frame.
Keywords: Animals; Base Sequence; Chromosomes, Human, Pair 7; Gene Duplication; Humans; Mice; Molecular Sequence Data; Physical Chromosome Mapping; Proteins; Pseudogenes; RNA, Untranslated; Sequence Analysis, DNA; Species Specificity; Williams Syndrome

FMR2 function: insight from a mouse knockout model. - Gu, Y; Nelson, D L (Cytogenet Genome Res, 2003)
The FMR2 gene is dysregulated by the fragile X E triplet repeat expansion in patients with FRAXE mental retardation syndrome. A CCG triplet, located in the 5' untranslated region of the FRAXE gene undergoes expansion and methylation in these patients, eliminating detectable gene transcription. FRAXE syndrome is distinct from fragile X syndrome, a more common genetic form of mental retardation caused by expansion and methylation of a similar repeat in the FMR1 gene located 600 kb proximal to FRAXE. FRAXE syndrome is rare, and patients' phenotypes are highly variable, leading to difficulties with predicting specific FMR2 functions based on the human disease. Recently, Lilliputian(Lilli), a Drosophila FMR2 orthologue, was identified; this gene has been linked with several signal transduction pathways, including the transforming growth factor-beta (TGF-beta) pathway, the Raf/MEK/MAP kinase (MAPK) pathway, and the P13K/PKB pathway. Mutation of Lilli shows defects in germinal band extension, cytoskeletal structure, cell growth, and organ development. The Lilli gene suggests possible functions for FMR2 (and related genes) in humans and mice, but cannot predict specific functions. Modeling FMR2 mutation in the mouse will be useful to understand specific functions of this gene in vertebrates. This review presents what has been learned thus far from the FMR2 knockout mouse model and suggests future studies on this model in order to compare it with the human FRAXE mental retardation disorder, Lilli mutants in Drosophila and other mouse models of genes in this family.
Keywords: Amino Acid Sequence; Animals; Disease Models, Animal; Fragile X Syndrome; Gene Expression Regulation, Developmental; Genes; Humans; Mental Retardation, X-Linked; Mice; Mice, Knockout; Molecular Sequence Data; Nuclear Proteins; Sequence Homology, Amino Acid; Trans-Activators; Trinucleotide Repeat Expansion

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part I. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document focuses on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Acute Disease; Arteriosclerosis; Consensus; Coronary Disease; Death, Sudden, Cardiac; Disease Progression; Humans; Models, Cardiovascular; Risk Assessment; Syndrome; Terminology as Topic

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part II. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document will focus on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Animals; Biomarkers; Coronary Artery Disease; Death, Sudden, Cardiac; Disease Susceptibility; Female; Humans; Male; Mass Screening; Myocardial Infarction; Myocardium; Risk Assessment; Severity of Illness Index; Swine; Thrombophilia

Genetic disruption of cortical interneuron development causes region- and GABA cell type-specific deficits, epilepsy, and behavioral dysfunction. - Powell, Elizabeth M; Campbell, Daniel B; Stanwood, Gregg D; Davis, Caleb; Noebels, Jeffrey L; Levitt, Pat (J Neurosci, 2003)
The generation of properly functioning circuits during brain development requires precise timing of cell migration and differentiation. Disruptions in the developmental plan may lead to neurological and psychiatric disorders. Neocortical circuits rely on inhibitory GABAergic interneurons, the majority of which migrate from subcortical sources. We have shown that the pleiotropic molecule hepatocyte growth factor/scatter factor (HGF/SF) mediates interneuron migration. Mice with a targeted mutation of the gene encoding urokinase plasminogen activator receptor (uPAR), a key component in HGF/SF activation and function, have decreased levels of HGF/SF and a 50% reduction in neocortical GABAergic interneurons at embryonic and perinatal ages. Disruption of interneuron development leads to early lethality in most models. Thus, the long-term consequences of such perturbations are unknown. Mice of the uPAR-/- strain survive until adulthood, and behavior testing demonstrates that they have an increased anxiety state. The uPAR-/- strain also exhibits spontaneous seizure activity and higher susceptibility to pharmacologically induced convulsions. The neocortex of the adult uPAR-/- mouse exhibits a dramatic region- and subtype-specific decrease in GABA-immunoreactive interneurons. Anterior cingulate and parietal cortical areas contain 50% fewer GABAergic interneurons compared with wild-type littermates. However, interneuron numbers in piriform and visual cortical areas do not differ from those of normal mice. Characterization of interneuron subpopulations reveals a near complete loss of the parvalbumin subtype, with other subclasses remaining intact. These data demonstrate that a single gene mutation can selectively alter the development of cortical interneurons in a region- and cell subtype-specific manner, with deficits leading to long-lasting changes in circuit organization and behavior.
Keywords: Animals; Anxiety; Behavior, Animal; Calcium-Binding Proteins; Cell Count; Darkness; Electroencephalography; Epilepsy; Exploratory Behavior; GABA Antagonists; gamma-Aminobutyric Acid; Genetic Predisposition to Disease; Interneurons; Light; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Neocortex; Receptors, Cell Surface; Receptors, Urokinase Plasminogen Activator; Spatial Behavior

Haplotype structure, LD blocks, and uneven recombination within the LRP5 gene. - Twells, Rebecca C J; Mein, Charles A; Phillips, Michael S; Hess, J Fred; Veijola, Riitta; Gilbey, Matthew; Bright, Matthew; Metzker, Michael; Lie, Benedicte A; Kingsnorth, Amanda; Gregory, Edward; Nakagawa, Yusuke; et al. (Genome Res, 2003)
Patterns of linkage disequilibrium (LD) in the human genome are beginning to be characterized, with a paucity of haplotype diversity in "LD blocks," interspersed by apparent "hot spots" of recombination. Previously, we cloned and physically characterized the low-density lipoprotein-receptor-related protein 5 (LRP5) gene. Here, we have extensively analysed both LRP5 and its flanking three genes, spanning 269 kb, for single nucleotide polymorphisms (SNPs), and we present a comprehensive SNP map comprising 95 polymorphisms. Analysis revealed high levels of recombination across LRP5, including a hot-spot region from intron 1 to intron 7 of LRP5, where there are 109 recombinants/Mb (4882 meioses), in contrast to flanking regions of 14.6 recombinants/Mb. This region of high recombination could be delineated into three to four hot spots, one within a 601-bp interval. For LRP5, three haplotype blocks were identified, flanked by the hot spots. Each LD block comprised over 80% common haplotypes, concurring with a previous study of 14 genes that showed that common haplotypes account for at least 80% of all haplotypes. The identification of hot spots in between these LD blocks provides additional evidence that LD blocks are separated by areas of higher recombination.
Keywords: 3' Flanking Region; 5' Flanking Region; Alleles; Chromosome Mapping; Chromosomes, Human, Pair 11; Diabetes Mellitus, Type 1; Gene Frequency; Genetic Markers; Genetics, Population; Genotype; Haplotypes; Humans; Introns; LDL-Receptor Related Proteins; Linkage Disequilibrium; Low Density Lipoprotein Receptor-Related Protein-5; Microsatellite Repeats; Nuclear Family; Polymorphism, Single Nucleotide; Receptors, LDL; Recombination, Genetic

Human genetics. Primate shadow play. - Richard A Gibbs; Nelson, David L (Science, 2003)
Keywords: Animals; Biological Evolution; Cebidae; Cercopithecidae; Computational Biology; Conserved Sequence; Exons; Genome; Genome, Human; Hominidae; Humans; Models, Statistical; Phylogeny; Primates; Regulatory Sequences, Nucleic Acid; Sequence Analysis, DNA; Species Specificity

The male-specific region of the human Y chromosome is a mosaic of discrete sequence classes. - Skaletsky, Helen; Kuroda-Kawaguchi, Tomoko; Minx, Patrick J; Cordum, Holland S; Hillier, LaDeana; Brown, Laura G; Repping, Sjoerd; Pyntikova, Tatyana; Ali, Johar; Bieri, Tamberlyn; Chinwalla, Asif; Delehaunty, Andrew; et al. (Nature, 2003)
The male-specific region of the Y chromosome, the MSY, differentiates the sexes and comprises 95% of the chromosome's length. Here, we report that the MSY is a mosaic of heterochromatic sequences and three classes of euchromatic sequences: X-transposed, X-degenerate and ampliconic. These classes contain all 156 known transcription units, which include 78 protein-coding genes that collectively encode 27 distinct proteins. The X-transposed sequences exhibit 99% identity to the X chromosome. The X-degenerate sequences are remnants of ancient autosomes from which the modern X and Y chromosomes evolved. The ampliconic class includes large regions (about 30% of the MSY euchromatin) where sequence pairs show greater than 99.9% identity, which is maintained by frequent gene conversion (non-reciprocal transfer). The most prominent features here are eight massive palindromes, at least six of which contain testis genes.
Keywords: Chromosomes, Human, X; Chromosomes, Human, Y; Crossing Over, Genetic; DNA Transposable Elements; Euchromatin; Evolution, Molecular; Female; Gene Amplification; Gene Conversion; Genes; Heterochromatin; Humans; In Situ Hybridization, Fluorescence; Male; Models, Genetic; Multigene Family; Organ Specificity; Pseudogenes; Sequence Homology, Nucleic Acid; Sex Characteristics; Sex Determination Processes; Species Specificity; Testis; Transcription, Genetic; Transducin

Systematic cloning of Treponema pallidum open reading frames for protein expression and antigen discovery. - McKevitt, Matthew; Patel, Krupa; Smajs, David; Marsh, Michael; McLoughlin, Melanie; Norris, Steven J; Weinstock, George M; Palzkill, Timothy (Genome Res, 2003)
A topoisomerase-based method was used to clone PCR products encoding 991 of the 1041 open reading frames identified in the genome sequence of the bacterium that causes syphilis, Treponema pallidum subsp. pallidum. Cloning the open reading frames into the univector plasmid system permitted the rapid conversion of the original clone set to other functional vectors containing a variety of promoters or tag sequences. A computational prediction of signal sequences identified 248 T. pallidum proteins that are potentially secreted from the cell. These clones were systematically converted into vectors designed to express the encoded proteins as glutathione-S-transferase fusion proteins. To test the potential of the clone set for novel antigen discovery, 85 of these fusion proteins were expressed from Escherichia coli, partially purified, and tested for antigenicity by using sera from rabbits infected with T. pallidum. Twelve of the 85 proteins bound significant levels of antibody. Of these 12 proteins, seven had previously been identified as T. pallidum antigens, and the remaining five represent novel antigens. These results demonstrate the potential of the T. pallidum clone set for antigen discovery and, more generally, for advancing the biology of this enigmatic spirochete.
Keywords: Antigens, Bacterial; Bacterial Proteins; Cloning, Molecular; Genetic Vectors; Glutathione Transferase; Open Reading Frames; Recombinant Proteins; Treponema pallidum

Finishing a whole-genome shotgun: release 3 of the Drosophila melanogaster euchromatic genome sequence. - Celniker, Susan E; Wheeler, David A; Kronmiller, Brent; Carlson, Joseph W; Halpern, Aaron; Patel, Sandeep; Adams, Mark; Champe, Mark; Dugan, Shannon P; Frise, Erwin; Hodgson, Ann; George, Reed A; et al. (Genome Biol, 2002)
BACKGROUND: The Drosophila melanogaster genome was the first metazoan genome to have been sequenced by the whole-genome shotgun (WGS) method. Two issues relating to this achievement were widely debated in the genomics community: how correct is the sequence with respect to base-pair (bp) accuracy and frequency of assembly errors? And, how difficult is it to bring a WGS sequence to the accepted standard for finished sequence? We are now in a position to answer these questions. RESULTS: Our finishing process was designed to close gaps, improve sequence quality and validate the assembly. Sequence traces derived from the WGS and draft sequencing of individual bacterial artificial chromosomes (BACs) were assembled into BAC-sized segments. These segments were brought to high quality, and then joined to constitute the sequence of each chromosome arm. Overall assembly was verified by comparison to a physical map of fingerprinted BAC clones. In the current version of the 116.9 Mb euchromatic genome, called Release 3, the six euchromatic chromosome arms are represented by 13 scaffolds with a total of 37 sequence gaps. We compared Release 3 to Release 2; in autosomal regions of unique sequence, the error rate of Release 2 was one in 20,000 bp. CONCLUSIONS: The WGS strategy can efficiently produce a high-quality sequence of a metazoan genome while generating the reagents required for sequence finishing. However, the initial method of repeat assembly was flawed. The sequence we report here, Release 3, is a reliable resource for molecular genetic experimentation and computational analysis.
Keywords: Animals; Drosophila melanogaster; Euchromatin; Genome; Physical Chromosome Mapping; Research Design; Sequence Analysis, DNA; X Chromosome

Haplotype and linkage disequilibrium architecture for human cancer-associated genes. - Bonnen, Penelope E; Wang, Peggy J; Kimmel, Marek; Chakraborty, Ranajit; Nelson, David L (Genome Res, 2002)
To facilitate association-based linkage studies we have studied the linkage disequilibrium (LD) and haplotype architecture around five genes of interest for cancer risk: ATM, BRCA1, BRCA2, RAD51, and TP53. Single nucleotide polymorphisms (SNPs) were identified and used to construct haplotypes that span 93-200 kb per locus with an average SNP density of 12 kb. These markers were genotyped in four ethnically defined populations that contained 48 each of African Americans, Asian Americans, Hispanic Americans, and European Americans. Haplotypes were inferred using an expectation maximization (EM) algorithm, and the data were analyzed using D', R(2), Fisher's exact P-values, and the four-gamete test for recombination. LD levels varied widely between loci from continuously high LD across 200 kb to a virtual absence of LD across a similar length of genome. LD structure also varied at each gene and between populations studied. This variation indicates that the success of linkage-based studies will require a precise description of LD at each locus and in each population to be studied. One striking consistency between genes was that at each locus a modest number of haplotypes present in each population accounted for a high fraction of the total number of chromosomes. We conclude that each locus has its own genomic profile with regard to LD, and despite this there is the widespread trend of relatively low haplotype diversity. As a result, a low marker density should be adequate to identify haplotypes that represent the common variation at a locus, thereby decreasing costs and increasing efficacy of association studies.
Keywords: Alleles; Cell Line, Transformed; Chromosome Mapping; Gene Frequency; Genes, Neoplasm; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Haplotypes; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Recombination, Genetic

Initial sequencing and comparative analysis of the mouse genome. - Waterston, Robert H; Lindblad-Toh, Kerstin; Birney, Ewan; Rogers, Jane; Abril, Josep F; Agarwal, Pankaj; Agarwala, Richa; Ainscough, Rachel; Alexandersson, Marina; An, Peter; Antonarakis, Stylianos E; Attwood, John; et al. (Nature, 2002)
The sequence of the mouse genome is a key informational tool for understanding the contents of the human genome and a key experimental tool for biomedical research. Here, we report the results of an international collaboration to produce a high-quality draft sequence of the mouse genome. We also present an initial comparative analysis of the mouse and human genomes, describing some of the insights that can be gleaned from the two sequences. We discuss topics including the analysis of the evolutionary forces shaping the size, structure and sequence of the genomes; the conservation of large-scale synteny across most of the genomes; the much lower extent of sequence orthology covering less than half of the genomes; the proportions of the genomes under selection; the number of protein-coding genes; the expansion of gene families related to reproduction and immunity; the evolution of proteins; and the identification of intraspecies polymorphism.
Keywords: Animals; Base Composition; Chromosomes, Mammalian; Conserved Sequence; CpG Islands; Evolution, Molecular; Gene Expression Regulation; Genes; Genetic Variation; Genome; Genome, Human; Genomics; Humans; Mice; Mice, Knockout; Mice, Transgenic; Models, Animal; Multigene Family; Mutagenesis; Neoplasms; Physical Chromosome Mapping; Proteome; Pseudogenes; Quantitative Trait Loci; Repetitive Sequences, Nucleic Acid; RNA, Untranslated; Selection, Genetic; Sequence Analysis, DNA; Sex Chromosomes; Species Specificity; Synteny

Polymorphism in soluble epoxide hydrolase and blood pressure in spontaneously hypertensive rats. - Fornage, Myriam; Hinojos, Cruz A; Nurowska, Barbara W; Eric Boerwinkle; Hammock, Bruce D; Morisseau, Christophe H P; Doris, Peter A (Hypertension, 2002)
We measured soluble epoxide hydrolase (sEH) renal gene expression in prehypertensive (4 to 5 weeks old) spontaneously hypertensive rats of the Heidelberg SP substrain (SHR [Heid]) and when blood pressure levels entered the hypertensive plateau (17 to 18 weeks old) and compared expression with matched Wistar-Kyoto (WKY [Heid]) rats. Less expression of the gene encoding sEH (EPHX2) was observed in SHR (Heid) than in WKY (Heid). Analysis of sEH protein abundance showed a similar difference. However, no correlation between sEH abundance and blood pressure was observed in the F(2) progeny of a parental strain cross. Measurement of protein abundance in SHR and WKY obtained from Charles River confirmed a recent report that abundance of sEH was greater in SHR (CRiv) than WKY (CRiv) strains. Polymorphisms were detected in EPHX2. Resequencing revealed that 2 alleles of EPHX2 exist in these 4 rat strains, differing by 4 single nucleotide polymorphisms, of which 3 produce nonsynonymous amino acid substitutions. The ancestral allele was shared by SHR (Heid) and WKY (CRiv), and the variant allele was shared by WKY (Heid) and SHR (CRiv). Activity of sEH was greater in animals carrying the variant allele. However, inheritance of this allele was not correlated with blood pressure in the F(2) progeny of a cross between SHR (Heid) and WKY (Heid). These data indicate that sequence variation determining functional alterations in EPHX2 is not likely to contribute to blood pressure levels in SHR.
Keywords: Animals; Blood Pressure; Epoxide Hydrolases; Hypertension; Kidney; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY; RNA, Messenger

Evolution tunes the excitability of individual neurons. - Salkoff, L; Butler, A; Fawcett, G; Kunkel, M; McArdle, C; Paz-y-Mino, G; Nonet, M; Walton, N; Wang, Z W; Yuan, A; Wei, A (Neuroscience, 2001)
The relationship between the genome and the evolution of the nervous system may differ between an animal like C. elegans with 302 neurons, and mammals with tens of billions of neurons. Here we report that a class of nonconserved potassium channels highly expanded in C. elegans may play a special role in the evolution of its nervous system. The C. elegans genome contains an extended gene family of potassium channels whose members fall into two evolutionary divergent classes. One class constitutes an ancient conserved "set" of K+ channels with orthologues in both humans and Drosophila and a second larger class made up of rapidly evolving genes unique to C. elegans. Chief among this second class are novel potassium channels having four transmembrane domains per subunit that function as regulated leak conductances to modulate cell electrical excitability. This inventory of novel potassium channels is far larger in C. elegans than in humans or Drosophila. We found that, unlike conserved channel genes, the majority of these genes are expressed in very few cells. We also identified DNA enhancer elements associated with these genes that direct gene expression to individual neurons. We conclude that C. elegans may maintain an exceptionally large inventory of these channels (as well as ligand-gated channels) as an adaptive mechanism to "fine tune" individual neurons, making the most of its limited circuitry.
Keywords: Adaptation, Physiological; Animals; Base Sequence; Biological Evolution; Caenorhabditis; Caenorhabditis elegans; DNA; Enhancer Elements, Genetic; Gene Expression; Molecular Sequence Data; Multigene Family; Neurons; Potassium Channels; Protein Isoforms

Initial sequencing and analysis of the human genome. - Lander, E S; Linton, L M; Birren, B; Nusbaum, C; Zody, M C; Baldwin, J; Devon, K; Dewar, K; Doyle, M; FitzHugh, W; Funke, R; Gage, D; et al. (Nature, 2001)
The human genome holds an extraordinary trove of information about human development, physiology, medicine and evolution. Here we report the results of an international collaboration to produce and make freely available a draft sequence of the human genome. We also present an initial analysis of the data, describing some of the insights that can be gleaned from the sequence.
Keywords: Animals; Chromosome Mapping; Conserved Sequence; CpG Islands; Databases, Factual; DNA Transposable Elements; Drug Industry; Evolution, Molecular; Forecasting; GC Rich Sequence; Gene Duplication; Genes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Human Genome Project; Humans; Mutation; Private Sector; Proteins; Proteome; Public Sector; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Species Specificity

A physical map of the human genome. - McPherson, J D; Marra, M; Hillier, L; Waterston, R H; Chinwalla, A; Wallis, J; Sekhon, M; Wylie, K; Mardis, E R; Wilson, R K; Fulton, R; Kucaba, T A; et al. (Nature, 2001)
The human genome is by far the largest genome to be sequenced, and its size and complexity present many challenges for sequence assembly. The International Human Genome Sequencing Consortium constructed a map of the whole genome to enable the selection of clones for sequencing and for the accurate assembly of the genome sequence. Here we report the construction of the whole-genome bacterial artificial chromosome (BAC) map and its integration with previous landmark maps and information from mapping efforts focused on specific chromosomal regions. We also describe the integration of sequence data with the map.
Keywords: Chromosomes, Artificial, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Gene Duplication; Genome, Human; Humans; In Situ Hybridization, Fluorescence; Repetitive Sequences, Nucleic Acid

A BAC-based physical map of the major autosomes of Drosophila melanogaster. - Hoskins, R A; Nelson, C R; Berman, B P; Laverty, T R; George, R A; Ciesiolka, L; Naeemuddin, M; Arenson, A D; Durbin, J; David, R G; Tabor, P E; Bailey, M R; et al. (Science, 2000)
We constructed a bacterial artificial chromosome (BAC)-based physical map of chromosomes 2 and 3 of Drosophila melanogaster, which constitute 81% of the genome. Sequence tagged site (STS) content, restriction fingerprinting, and polytene chromosome in situ hybridization approaches were integrated to produce a map spanning the euchromatin. Three of five remaining gaps are in repeat-rich regions near the centromeres. A tiling path of clones spanning this map and STS maps of chromosomes X and 4 was sequenced to low coverage; the maps and tiling path sequence were used to support and verify the whole-genome sequence assembly, and tiling path BACs were used as templates in sequence finishing.
Keywords: Animals; Centromere; Chromatin; Chromosomes, Bacterial; Cloning, Molecular; Contig Mapping; DNA Fingerprinting; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genetic Markers; Genetic Vectors; Genome; In Situ Hybridization; Repetitive Sequences, Nucleic Acid; Restriction Mapping; Sequence Analysis, DNA; Sequence Tagged Sites; Telomere

The genome sequence of Drosophila melanogaster. - Adams, M D; Celniker, S E; Holt, R A; Evans, C A; Gocayne, J D; Amanatides, P G; Steven E Scherer; Li, P W; Hoskins, R A; Galle, R F; George, R A; Lewis, S E; et al. (Science, 2000)
The fly Drosophila melanogaster is one of the most intensively studied organisms in biology and serves as a model system for the investigation of many developmental and cellular processes common to higher eukaryotes, including humans. We have determined the nucleotide sequence of nearly all of the approximately 120-megabase euchromatic portion of the Drosophila genome using a whole-genome shotgun sequencing strategy supported by extensive clone-based sequence and a high-quality bacterial artificial chromosome physical map. Efforts are under way to close the remaining gaps; however, the sequence is of sufficient accuracy and contiguity to be declared substantially complete and to support an initial analysis of genome structure and preliminary gene annotation and interpretation. The genome encodes approximately 13,600 genes, somewhat fewer than the smaller Caenorhabditis elegans genome, but with comparable functional diversity.
Keywords: Animals; Biological Transport; Chromatin; Cloning, Molecular; Computational Biology; Contig Mapping; Cytochrome P-450 Enzyme System; DNA Repair; DNA Replication; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genome; Heterochromatin; Insect Proteins; Nuclear Proteins; Protein Biosynthesis; Sequence Analysis, DNA; Transcription, Genetic

Haplotypes at ATM identify coding-sequence variation and indicate a region of extensive linkage disequilibrium. - Bonnen, P E; Story, M D; Ashorn, C L; Buchholz, T A; Weil, M M; Nelson, D L (Am J Hum Genet, 2000)
Genetic variation in the human population may lead to functional variants of genes that contribute to risk for common chronic diseases such as cancer. In an effort to detect such possible predisposing variants, we constructed haplotypes for a candidate gene and tested their efficacy in association studies. We developed haplotypes consisting of 14 biallelic neutral-sequence variants that span 142 kb of the ATM locus. ATM is the gene responsible for the autosomal recessive disease ataxia-telangiectasia (AT). These ATM noncoding single-nucleotide polymorphisms (SNPs) were genotyped in nine CEPH families (89 individuals) and in 260 DNA samples from four different ethnic origins. Analysis of these data with an expectation-maximization algorithm revealed 22 haplotypes at this locus, with three major haplotypes having frequencies > or = .10. Tests for recombination and linkage disequilibrium (LD) show reduced recombination and extensive LD at the ATM locus, in all four ethnic groups studied. The most striking example was found in the study population of European ancestry, in which no evidence for recombination could be discerned. The potential of ATM haplotypes for detection of genetic variants through association studies was tested by analysis of 84 individuals carrying one of three ATM coding SNPs. Each coding SNP was detected by association with an ATM haplotype. We demonstrate that association studies with haplotypes for candidate genes have significant potential for the detection of genetic backgrounds that contribute to disease.
Keywords: Algorithms; Alleles; Animals; Ataxia Telangiectasia; Ataxia Telangiectasia Mutated Proteins; Case-Control Studies; Cell Cycle Proteins; Codon; DNA-Binding Proteins; Ethnicity; Europe; Gene Frequency; Genetic Variation; Haplotypes; Hominidae; Humans; Linkage Disequilibrium; Molecular Sequence Data; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Racial Groups; Recombination, Genetic; Tumor Suppressor Proteins

Large expansion of the ATTCT pentanucleotide repeat in spinocerebellar ataxia type 10. - Matsuura, T; Yamagata, T; Burgess, D L; Rasmussen, A; Grewal, R P; Watase, K; Khajavi, M; McCall, A E; Davis, C F; Zu, L; Achari, M; Pulst, S M; et al. (Nat Genet, 2000)
Spinocerebellar ataxia type 10 (SCA10; MIM 603516; refs 1,2) is an autosomal dominant disorder characterized by cerebellar ataxia and seizures. The gene SCA10 maps to a 3.8-cM interval on human chromosome 22q13-qter (refs 1,2). Because several other SCA subtypes show trinucleotide repeat expansions, we examined microsatellites in this region. We found an expansion of a pentanucleotide (ATTCT) repeat in intron 9 of SCA10 in all patients in five Mexican SCA10 families. There was an inverse correlation between the expansion size, up to 22.5 kb larger than the normal allele, and the age of onset (r2=0.34, P=0.018). Analysis of 562 chromosomes from unaffected individuals of various ethnic origins (including 242 chromosomes from Mexican persons) showed a range of 10 to 22 ATTCT repeats with no evidence of expansions. Our data indicate that the new SCA10 intronic ATTCT pentanucleotide repeat in SCA10 patients is unstable and represents the largest microsatellite expansion found so far in the human genome.
Keywords: Animals; Asian People; Brain; Chromosome Mapping; Chromosomes, Human, Pair 22; DNA; Epilepsy; Female; Humans; Male; Mexican Americans; Mice; Mice, Inbred C57BL; Molecular Sequence Data; Pedigree; Polymorphism, Genetic; Repetitive Sequences, Nucleic Acid; Spinocerebellar Ataxias; United States; White People

Identification of three novel Ca(2+) channel gamma subunit genes reveals molecular diversification by tandem and chromosome duplication. - Burgess, D L; Davis, C F; Gefrides, L A; Noebels, J L (Genome Res, 1999)
Gene duplication is believed to be an important evolutionary mechanism for generating functional diversity within genomes. The accumulated products of ancient duplication events can be readily observed among the genes encoding voltage-dependent Ca(2+) ion channels. Ten paralogous genes have been identified that encode isoforms of the alpha(1) subunit, four that encode beta subunits, and three that encode alpha(2)delta subunits. Until recently, only a single gene encoding a muscle-specific isoform of the Ca(2+) channel gamma subunit (CACNG1) was known. Expression of a distantly related gene in the brain was subsequently demonstrated upon isolation of the Cacng2 gene, which is mutated in the mouse neurological mutant stargazer (stg). In this study, we sought to identify additional genes that encoded gamma subunits. Because gene duplication often generates paralogs that remain in close syntenic proximity (tandem duplication) or are copied onto related daughter chromosomes (chromosome or whole-genome duplication), we hypothesized that the known positions of CACNG1 and CACNG2 could be used to predict the likely locations of additional gamma subunit genes. Low-stringency genomic sequence analysis of targeted regions led to the identification of three novel Ca(2+) channel gamma subunit genes, CACNG3, CACNG4, and CACNG5, on chromosomes 16 and 17. These results demonstrate the value of genome evolution models for the identification of distantly related members of gene families.
Keywords: Amino Acid Sequence; Calcium Channels; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 17; Evolution, Molecular; Expressed Sequence Tags; Gene Duplication; Genetic Variation; Humans; Molecular Sequence Data; Multigene Family; Peptides; Phylogeny; Physical Chromosome Mapping; Sequence Alignment

Molecular and phenotypic variation in patients with severe Hunter syndrome. - Timms, K M; Bondeson, M L; Ansari-Lari, M A; Lagerstedt, K; Donna M Muzny; Dugan-Rocha, S P; Nelson, D L; Pettersson, U; Richard A Gibbs (Hum Mol Genet, 1997)
Severe Hunter syndrome is a fatal X-linked lysosomal storage disorder caused by iduronate-2-sulphatase (IDS) deficiency. Patients with complete deletion of the IDS locus often have atypical phenotypes including ptosis, obstructive sleep apnoea, and the occurrence of seizures. We have used genomic DNA sequencing to identify several new genes in the IDS region. DNA deletion patients with atypical symptoms have been analysed to determine whether these atypical symptoms could be due to involvement of these other loci. The occurrence of seizures in two individuals correlated with a deletion extending proximal of IDS, up to and including part of the FMR2 locus. Other (non-seizure) symptoms were associated with distal deletions. In addition, a group of patients with no variant symptoms, and a characteristic rearrangement involving a recombination between the IDS gene and an adjacent IDS pseudogene (IDS psi), showed normal expression of loci distal to IDS. Together, these results identify FMR2 as a candidate gene for seizures, when mutated along with IDS.
Keywords: Chromosome Mapping; Cloning, Molecular; Electrophoresis, Agar Gel; Gene Deletion; Gene Expression; Gene Rearrangement; Humans; Iduronate Sulfatase; Male; Molecular Sequence Data; Mucopolysaccharidosis II; Nuclear Proteins; Phenotype; Polymerase Chain Reaction; Proteins; Pseudogenes; Recombination, Genetic; Seizures; Trans-Activators; X Chromosome

Sequencing and functional analysis of the SNRPN promoter: in vitro methylation abolishes promoter activity. - Huq, A H; Sutcliffe, J S; Nakao, M; Shen, Y; Gibbs, R A; Beaudet, A L (Genome Res, 1997)
The gene encoding the small nuclear ribonucleoprotein-associated polypeptide N (SNRPN) maps to the Prader-Willi syndrome critical region on chromosome 15 and is expressed preferentially from the paternal allele. A CpG island encompassing the first exon of SNRPN is methylated on the inactive maternal allele. DNA sequence was determined for a cosmid containing the first three exons of SNRPN and extending 20 kb upstream and 15 kb downstream from the CpG island. This region is extremely rich in Alu elements and other repetitive sequences and contains a single CpG island, which includes numerous short direct repeat sequences. Functional analysis of the first exon revealed strong promoter activity for a 260-bp fragment extending 207 bp upstream from the exon. In vitro methylation of this 260-bp fragment abolished promoter activity completely, suggesting that the silencing of the maternal SNRPN allele may be a direct consequence of methylation of the promoter region.
Keywords: Alleles; Autoantigens; Cells, Cultured; Chromosomes, Human, Pair 15; Cloning, Molecular; CpG Islands; DNA Methylation; DNA-Cytosine Methylases; Exons; Gene Expression; HeLa Cells; Humans; Methylation; Molecular Sequence Data; Polymerase Chain Reaction; Prader-Willi Syndrome; Promoter Regions, Genetic; Repetitive Sequences, Nucleic Acid; Ribonucleoproteins, Small Nuclear; Sequence Analysis, DNA; snRNP Core Proteins; Transfection

Duplication of a gene-rich cluster between 16p11.1 and Xq28: a novel pericentromeric-directed mechanism for paralogous genome evolution. - Eichler, E E; Lu, F; Shen, Y; Antonacci, R; Jurecic, V; Doggett, N A; Moyzis, R K; Baldini, A; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1996)
We have identified a 26.5 kb gene-rich duplication shared by human Xq28 and 16p11.1. Complete comparative sequence analysis of cosmids from both loci has revealed identical Xq28 and 16p11.1 genomic structures for both the human creatine transporter gene (SLC6A8) and five exons of the CDM gene (DXS1357E). Overall nucleotide similarity within the duplication was found to be 94.6%, suggesting that this interchromosomal duplication occurred within recent evolutionary time (7-10 mya). Based on comparisons between genomic and cDNA sequence, both the Xq28 creatine transporter and DXS1357E genes are transcriptionally active. Predicted translation of exons and RT-PCR analysis reveal that chromosome 16 paralogs likely represent pseudogenes. Comparative fluorescent in situ hybridization (FISH) analyses of chromosomes from various primates indicate that this gene-rich segment has undergone several duplications. In gorilla and chimpanzee, multiple pericentromeric localizations on a variety of chromosomes were found using probes from the duplicated region. In other species, such as the orangutan and gibbon, FISH signals were only identified at the distal end of the X chromosome, suggesting that the Xq28 locus represents the ancestral copy. Sequencing of the 16p 11.1/Xq28 duplication breakpoints has revealed the presence of repetitive immunoglobulin-like CAGGG pentamer sequences at or near the paralogy boundaries. The mobilization and dispersal of this gene-rich 27 kb element to the pericentromeric regions of primate chromosomes defines an unprecedented form of recent genome evolution and a novel mechanism for the generation of genetic diversity among closely related species.
Keywords: Animals; Base Sequence; Carrier Proteins; Centromere; Chromosome Mapping; Chromosomes, Human, Pair 16; Cosmids; Creatine; Evolution, Molecular; Exons; Hominidae; Humans; Hylobates; Membrane Proteins; Membrane Transport Proteins; Models, Genetic; Molecular Sequence Data; Multigene Family; Proteins; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; X Chromosome

Identification of FMR2, a novel gene associated with the FRAXE CCG repeat and CpG island. - Gu, Y; Shen, Y; Richard A Gibbs; Nelson, D L (Nat Genet, 1996)
Five folate-sensitive fragile sites have been identified at the molecular level to date. Each is characterized by an expanded and methylated trinucleotide repeat CGG (CCG). Of the three X chromosome sites, FRAXA, FRAXE and FRAXF, the former two are associated with mental retardation in their expanded forms. FRAXA expansion results in fragile X syndrome due to down regulation of expression of the FMR1 gene, which carries the hypermutable CGG repeat in the 5' untranslated portion of its first exon. Mild mental retardation without consistent physical findings has been found associated with expanded CCG repeats at FRAXE. We have identified a large gene (FMR2) transcribed distally from the CpG island at FRAXE, and down-regulated by repeat expansion and methylation. The gene is novel, expressed in adult brain and placenta, and shows similarity with another human protein, MLLT2, expressed from a gene at chromosome 4q21 involved in translocations found in acute lymphoblastic leukaemia (ALL) cells. Identification of this gene will facilitate further studies to determine the role of its product in FRAXE associated mental deficiency.
Keywords: Adult; Amino Acid Sequence; Base Sequence; Brain; Chromosomes, Human, Pair 4; Cloning, Molecular; Dinucleoside Phosphates; DNA Primers; Female; Fragile X Syndrome; Gene Expression; Humans; Intellectual Disability; Molecular Sequence Data; Nuclear Proteins; Organ Specificity; Placenta; Polymerase Chain Reaction; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pregnancy; Protein Biosynthesis; Proteins; Repetitive Sequences, Nucleic Acid; RNA, Messenger; Sequence Homology, Amino Acid; Trans-Activators; Transcription, Genetic; X Chromosome

130 kb of DNA sequence reveals two new genes and a regional duplication distal to the human iduronate-2-sulfate sulfatase locus. - Timms, K M; Lu, F; Shen, Y; Pierson, C A; Donna M Muzny; Gu, Y; Nelson, D L; Richard A Gibbs (Genome Res, 1995)
Deficiency of IDs activity results in Hunter Syndrome (mucopolysaccharidosis type II), a fatal X-linked recessive disorder. We report characterization of 28 cosmids around the IDS locus in Xq28. Four overlapping cosmids have been sequenced in their entirety generating a 130-kb contig. These studies show the fine structure of the IDS gene and identify an IDS pseudogene-like structure located 20 kb distal to the active gene. Two novel genes have also been identified in this sequence, and one of these genes is also locally duplicated. Both homologs are expressed, and a number of alternative transcript products have been characterized. The presence of a highly conserved pseudogene-like structure within a larger duplicated region close to the IDS gene has significant implications for the study of mutations at this locus.
Keywords: Base Sequence; Chromosome Walking; Chromosomes, Artificial, Yeast; Cosmids; Gene Expression; Genes; Genetic Markers; Humans; Iduronate Sulfatase; Male; Mucopolysaccharidosis II; Multigene Family; Polymerase Chain Reaction; Pseudogenes; Repetitive Sequences, Nucleic Acid; RNA, Messenger; Sequence Alignment; Transcription, Genetic; X Chromosome

Fine structure of the human FMR1 gene. - Eichler, E E; Stephen Richards; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1994)
Keywords: Base Sequence; Exons; Fragile X Mental Retardation Protein; Fragile X Syndrome; Genes; Humans; Molecular Sequence Data; Nerve Tissue Proteins; RNA-Binding Proteins

Molecular cloning of the wild-type and mutant thyA gene from Shigella flexneri Y. - Nur-E-Kamal, M S; al Mamun, A A; Ahmed, Z U (Microbiol Immunol, 1994)
The thyA gene which codes for thymidylate synthase has been cloned and sequenced from the wild-type Shigella flexneri Y strain SH4 and a thyA mutant TSF21 after amplifying the gene by polymerase chain reaction (PCR). The nucleotide sequence revealed 98% homology to the E. coli K-12 thyA gene. The sequence of the wild-type thyA gene of Shigella flexneri Y was identical with that of the thyA mutant except that the residue T at position 345 was replaced by residue A in the thyA mutant. This change would cause a predicted amino acid substitution of leucine at position 44 in the polypeptide product of the wild type by glutamine in the mutant. Thus, Leu44 may be critical in enzymatic activity of the thyA gene product thymidylate synthase.
Keywords: Base Sequence; Cloning, Molecular; Escherichia coli; Genes, Bacterial; Molecular Sequence Data; Mutation; Phenotype; Polymerase Chain Reaction; Sequence Homology, Nucleic Acid; Shigella flexneri; Thymidylate Synthase

Fine structure of the human FMR1 gene. - Eichler, E E; Stephen Richards; Richard A Gibbs; Nelson, D L (Hum Mol Genet, 1993)
The fragile X syndrome is due to a CGG triplet expansion in the first exon of FMR1, resulting in hypermethylation and extinction of gene expression. To further our understanding of the gene's involvement in the syndrome, we report the physical structure of this locus. A high resolution restriction map of the FRAX(A) locus has been prepared encompassing approximately 50 kb. Using exon-exon PCR and restriction analysis, the FMR1 gene has been determined to consist of 17 exons spanning 38 kb of Xq27.3. Each intron-exon boundary has been sequenced. In general, the splice donors and acceptors located in the 5' portion of the gene demonstrate greater adherence to consensus than those in the 3' end, providing a possible explanation for the finding of alternative splicing in FMR1. The elucidation of the exon composition of the FMR1 gene and its flanking region will enhance detection of coding sequence mutations possible in fragile X phenocopy individuals.
Keywords: Alternative Splicing; Base Sequence; Cloning, Molecular; Cosmids; Exons; Fragile X Mental Retardation Protein; Fragile X Syndrome; Humans; Introns; Molecular Sequence Data; Nerve Tissue Proteins; Oligodeoxyribonucleotides; Polymerase Chain Reaction; Repetitive Sequences, Nucleic Acid; Restriction Mapping; RNA, Messenger; RNA-Binding Proteins; X Chromosome

Alu-primed polymerase chain reaction for regional assignment of 110 yeast artificial chromosome clones from the human X chromosome: identification of clones associated with a disease locus. - Nelson, D L; Ballabio, A; Victoria, M F; Pieretti, M; Bies, R D; Gibbs, R A; Maley, J A; Chinault, A C; Webster, T D; Caskey, C T (Proc Natl Acad Sci U S A, 1991)
Over 400 yeast artificial chromosome (YAC) clones were isolated from the human X chromosome, and 110 of these were assigned to regions defined by chromosome translocation and deletion breakpoints. Polymerase chain reaction using Alu primers was applied to YAC clones in order to generate probes, to identify overlapping clones, and to derive "fingerprints" and sequence data directly from total yeast DNA. Several clones were identified in regions of medical interest. One set of three overlapping clones was found to cross a chromosomal translocation implicated in Lowe syndrome. The regional assignment of groups of YAC clones provides initiation points for further attempts to develop large cloned contiguous sequences, as well as material for investigation of regions involved in genetic diseases.
Keywords: Base Sequence; Blotting, Southern; Chromosome Mapping; Chromosomes, Fungal; Cloning, Molecular; Deoxyribonucleases, Type II Site-Specific; Gene Library; Genetic Diseases, Inborn; Humans; Molecular Sequence Data; Nucleotide Mapping; Oligonucleotide Probes; Polymerase Chain Reaction; Restriction Mapping; Saccharomyces cerevisiae; X Chromosome

Evolution of human immunodeficiency virus type 1 nucleotide sequence diversity among close contacts. - Burger, H; Weiser, B; Flaherty, K; Gulla, J; Nguyen, P N; Gibbs, R A (Proc Natl Acad Sci U S A, 1991)
The degree of change in the nucleotide sequence of human immunodeficiency virus type 1 (HIV-1) that occurs when it is transmitted sexually from one individual to another or vertically from mother to child is unknown. Previous studies have shown that most cultured HIV-1 isolates from the same individuals differed in the entire envelope gene nucleotide sequence by up to 2%, although most isolates from unrelated individuals differed by 6-22%. To examine diversity among HIV-1 isolates from close contacts, we determined the nucleotide sequences of viruses from a family with a known epidemiologic profile, in which a woman transmitted HIV-1 heterosexually to her partner and vertically to her daughter. Direct DNA sequence analysis of primary HIV-1 isolates amplified by PCR was used to distinguish the major and minor viral sequences, termed quasispecies, to rapidly determine the predominant sequences and their phylogenetic relationships. The nucleotide sequence diversity of a major portion of the HIV-1 envelope gene was 3.7% between isolates from the woman and her heterosexual partner and 8.5% between isolates from this woman and her daughter, who had been infected for a longer period than the partner. The configuration of the phylogenetic tree demonstrated that the daughter's predominant isolate evolved from a progenitor of her mother's current strain. This study provides evidence of a continuous spectrum of sequence diversity between any two isolates ranging from those derived from the same person to those from close contacts and, ultimately, those from unrelated individuals. These data and methods can be applied to epidemiologic investigations of possible HIV-1 transmission between health care workers and their patients.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; Amino Acid Sequence; Base Sequence; Biological Evolution; DNA, Viral; Female; Genes, env; Genetic Variation; HIV-1; Humans; Male; Molecular Sequence Data; Oligodeoxyribonucleotides; Phylogeny; Polymerase Chain Reaction; Sequence Homology, Nucleic Acid

Long HIV-1 incubation periods and dynamics of transmission within a family. - Burger, H; Belman, A L; Grimson, R; Kaell, A; Flaherty, K; Gulla, J; Richard A Gibbs; Nguyun, P N; Weiser, B (Lancet, 1990)
The incubation period of human immunodeficiency virus type 1 (HIV-1) infection was studied in a family of five in which vertical and heterosexual transmission occurred from one index case. This investigation documented incubation periods of longer than 12 years in a mother and her daughter; although neither has symptoms, both are definitely infected and have very low CD4(+)-lymphocyte counts. The study confirmed the predictions of incubation periods longer than 10 years in a small proportion of infected individuals. It provides evidence that vertically HIV-1-infected teenagers can be expected to appear in the population.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Adult; CD4-Positive T-Lymphocytes; Child; DNA, Viral; Family; Family Health; Female; HIV Antibodies; HIV Seropositivity; HIV-1; Humans; Leukocyte Count; Male; Sexual Behavior; Substance Abuse, Intravenous; Time Factors

Multiplex DNA deletion detection and exon sequencing of the hypoxanthine phosphoribosyltransferase gene in Lesch-Nyhan families. - Richard A Gibbs; Nguyen, P N; Edwards, A; Civitello, A B; Caskey, C T (Genomics, 1990)
The Lesch-Nyhan (LN) syndrome is a genetically lethal human neurological disease that results from mutations that inactivate the hypoxanthine phosphoribosyltransferase (HPRT) gene. The elucidation of the complete DNA sequence of the human HPRT gene locus has enabled the construction of multiple oligonucleotide primer sets for the simultaneous in vitro amplification of all nine HPRT exons. The multiplex polymerase chain reaction provides a facile assay for the detection of HPRT exon deletions and the reaction products can be analyzed by direct automated fluorescent DNA sequencing to identify subtle alterations in the gene. Alterations have been identified in the HPRT genes from 15 independent LN cases, and 10 LN family studies were performed. The sequencing method uses solid supports and is sufficiently simple and sensitive to be a favored approach for LN diagnosis. LN heterozygotes can be diagnosed without reference to the affected male. In addition, these procedures will be useful for somatic mutagenesis studies.
Keywords: Base Sequence; Chromosome Deletion; DNA; Exons; Female; Genes; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Molecular Sequence Data; Pedigree; Polymerase Chain Reaction

Automated DNA sequencing methods for detection and analysis of mutations: applications to the Lesch-Nyhan syndrome. - Edwards, A; Richard A Gibbs; Nguyen, P N; Ansorge, W; Caskey, C T (Trans Assoc Am Physicians, 1989)
Keywords: Base Sequence; Chromosome Deletion; DNA; Female; Genetic Carrier Screening; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Male; Mutation; Pedigree; Polymerase Chain Reaction; Polymorphism, Genetic; Pregnancy; Prenatal Diagnosis; Repetitive Sequences, Nucleic Acid; Restriction Mapping

Detection of single DNA base differences by competitive oligonucleotide priming. - Richard A Gibbs; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1989)
Synthetic DNA oligonucleotides can serve as efficient primers for DNA synthesis even when there is a single base mismatch between the primers and the corresponding DNA template. However, when the primer-template annealing is carried out with a mixture of primers and at low stringency the binding of a perfectly matched primer is strongly favored relative to a primer differing by a single base. This primer competition is observed over a range of oligonucleotide sizes from twelve to sixteen bases and with a variety of base mismatches. When coupled with the polymerase chain reaction, for the amplification of specific DNA sequences, competitive oligonucleotide priming provides a simple general strategy for the detection of single DNA base differences.
Keywords: Animals; Base Sequence; Binding, Competitive; DNA; DNA, Single-Stranded; DNA-Directed DNA Polymerase; Gene Amplification; Mice; Mice, Mutant Strains; Molecular Sequence Data; Mutation; Oligonucleotides; Taq Polymerase; Templates, Genetic

Identification of mutations leading to the Lesch-Nyhan syndrome by automated direct DNA sequencing of in vitro amplified cDNA. - Gibbs, R A; Nguyen, P N; McBride, L J; Koepf, S M; Caskey, C T (Proc Natl Acad Sci U S A, 1989)
The Lesch-Nyhan (LN) syndrome is a severe X chromosome-linked disease that results from a deficiency of the purine salvage enzyme hypoxanthine phosphoribosyltransferase (HPRT). The mutations leading to the disease are heterogeneous and frequently arise as de novo events. We have identified nucleotide alterations in 15 independently arising HPRT-deficiency cases by direct DNA sequencing of in vitro amplified HPRT cDNA. We also demonstrate that the direct DNA sequence analysis can be automated, further simplifying the detection of new mutations at this locus. The mutations include DNA base substitutions, small DNA deletions, a single DNA base insertion, and errors in RNA splicing. The application of these procedures allows DNA diagnosis and carrier identification by the direct detection of the mutant alleles within individual families affected by LN.
Keywords: Alleles; Autoanalysis; Base Sequence; DNA; DNA-Directed DNA Polymerase; Gene Amplification; Humans; Hypoxanthine Phosphoribosyltransferase; Lesch-Nyhan Syndrome; Mutation; Nucleic Acid Hybridization; Oligonucleotide Probes; Pedigree; RNA Splicing; Software

Deletion screening of the Duchenne muscular dystrophy locus via multiplex DNA amplification. - Chamberlain, J S; Richard A Gibbs; Ranier, J E; Nguyen, P N; Caskey, C T (Nucleic Acids Res, 1988)
The application of recombinant DNA technology to prenatal diagnosis of many recessively inherited X-linked diseases is complicated by a high frequency of heterogeneous, new mutations (1). Partial gene deletions account for more than 50% of Duchenne muscular dystrophy (DMD) lesions, and approximately one-third of all cases result from a new mutation (2-5). We report the isolation and DNA sequence of several deletion prone exons from the human DMD gene. We also describe a rapid method capable of detecting the majority of deletions in the DMD gene. This procedure utilizes simultaneous genomic DNA amplification of multiple widely separated sequences and should permit deletion scanning at any hemizygous locus. We demonstrate the application of this multiplex reaction for prenatal and postnatal diagnosis of DMD.
Keywords: Base Sequence; Chromosome Deletion; Cloning, Molecular; DNA; Female; Gene Amplification; Humans; Male; Molecular Sequence Data; Muscular Dystrophies; Prenatal Diagnosis